2019 ESC guidelines for the diagnosis and management of chronic coronary syndromes - Knuuti, Juhani; Wijns, William; Achenbach, Stephan; Agewall, Stefan; Barbato, Emanuele; Bax, Jeroen J.; Capodanno, Davide; Cuisset, Thomas; Deaton, Christi; Dickstein, Kenneth; Edvardsen, Thor; Escaned, Javier; et al. (European Heart Journal, 2020)
Coronary artery disease (CAD) is a pathological process characterized by atherosclerotic plaque accumulation in the epicardial arteries, whether obstructive or non-obstructive. This process can be modified by lifestyle adjustments, pharmacological therapies, and invasive interventions designed to achieve disease stabilization or regression. The disease can have long, stable periods but can also become unstable at any time, typically due to an acute atherothrombotic event caused by plaque rupture or erosion. However, the disease is chronic, most often progressive, and hence serious, even in clinically apparently silent periods. The dynamic nature of the CAD process results in various clinical presentations, which can be conveniently categorized as either acute coronary syndromes (ACS) or chronic coronary syndromes (CCS). The Guidelines presented here refer to the management of patients with CCS. The natural history of CCS is illustrated in Figure 1.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Angina pectoris; Anti-ischaemic drugs; Antithrombotic therapy; Chronic coronary syndromes; Coronary artery disease; Diagnostic testing; Guidelines; Imaging; Lifestyle modifications; Lipid-lowering drugs; Microvascular angina; Myocardial ischaemia; Myocardial revascularization; Risk assessment; Screening; Vasospastic angina

2019 ESC Guide on the Diagnosis and Treatment of Chronic Coronary Syndromes - Knuuti, Juhani; Wijns, William; Saraste, Antti; Capodanno, Davide; Barbato, Emanuele; Funck-Brentano, Christian; Prescott, Eva; Storey, Robert F.; Deaton, Christi; Cuisset, Thomas; Agewall, Stefan; Dickstein, Kenneth; et al. (Revista Espanola De Cardiologia, 2020)
CRIS-Team WoS Importer:2020-12-18

2-Year Clinical Outcomes of an Abluminal Groove–Filled Biodegradable-Polymer Sirolimus-Eluting Stent Compared With a Durable-Polymer Everolimus-Eluting Stent - Xu, Bo; Saito, Yuichi; Baumbach, Andreas; Kelbæk, Henning; van Royen, Niels; Zheng, Ming; Morel, Marie Angèle; Knaapen, Paul; Slagboom, Ton; Johnson, Thomas W.; Vlachojannis, Georgios; Arkenbout, Karin E.; et al. (Jacc-Cardiovascular Interventions, 2019)
Objectives: The aim of this study was to assess the 2-year clinical outcomes of the Firehawk stent (Shanghai MicroPort Medical Group, Shanghai, China), a novel abluminal groove–filled biodegradable-polymer sirolimus-eluting coronary stent, compared with XIENCE (Abbott Vascular, Santa Clara, California), a durable-polymer everolimus-eluting coronary stent. Background: The long-term outcomes of the Firehawk stent have not been evaluated beyond 1 year in a randomized all-comers clinical trial. Methods: The TARGET All Comers study is a prospective, multicenter, all-comers, randomized, noninferiority trial conducted in Europe. A total of 1,653 patients were randomly assigned to undergo implantation of either the Firehawk or the XIENCE stent. The primary endpoint was target lesion failure, a composite of cardiac death, target vessel myocardial infarction, or ischemia-driven target lesion revascularization. Results: At 2-year follow-up, the incidence of target lesion failure was 8.7% in the Firehawk group versus 8.6% in the XIENCE group (p = 0.92). The event rates of individual components of the primary endpoint were comparable for the 2 groups. Landmark analyses between 1- and 2-year follow-up revealed no statistically significant difference of TLF for the Firehawk versus the XIENCE stent. Beyond 1 year, very late definite or probable stent thrombosis occurred in 3 patients (0.4%) in the Firehawk group and in 7 patients (0.9%) in the XIENCE group (p = 0.34). Conclusions: The 2-year follow-up of the TARGET All Comers study confirms comparable safety and efficacy profiles of the Firehawk and XIENCE stents.
CRIS-Team Scopus Importer:2019-09-03
Keywords: clinical outcome; drug-eluting stent; everolimus-eluting stent; Firehawk

3D imaging of myocardial perfusion and coronary tree morphology from a single rotational angiogram - Lauritsch, Günter; Rohkohl, Christopher; Hornegger, Joachim; Sinha, Anil-Martin; Rittger, Harald; Brachmann, Johannes; Rieber, Johannes; Rittger, Harald (Medical Imaging 2011: Visualization, Image-Guided Procedures, and Modeling, 2011)
Diagnosis and treatment of coronary heart disease are performed in the catheter laboratory using an angiographic X-ray C-arm system. The morphology of the coronary tree and potentially ischemic lesions are determined in 2D projection views. The hemodynamic impact of the lesion would be valuable information for treatment decision. Using other modalities for functional imaging is disrupting the clinical workflow since the patient has to be transferred from the catheter laboratory to another scanner, and back to the catheter laboratory for performing the treatment. In this work a novel technology is used for simultaneous 3D imaging of first pass perfusion and the morphology of the coronary tree from a single rotational angiogram. A selective, single shot of contrast agent of less than 20ml directly into the coronaries is sufficient for a proper contrast resolution. Due to the long acquisition time cardiac motion has to be considered. A novel reconstruction technique for estimation and compensation of cardiac motion from the acquired projection data is used. The overlay of the 3D structure of the coronary tree and the perfusion image shows the correlation of myocardial areas and the associated coronary sections supporting that region. In a case example scar lesions caused by a former myocardial infarct are investigated. A first pass perfusion defect is found which is validated by a late enhancement magnetic resonance image. No ischemic defects are found. The non vital regions are still supported by the coronary vasculature. © 2011 SPIE.

3D printing for sizing left atrial appendage closure device: head-to-head comparison with computed tomography and transoesophageal echocardiography. - Hell, Michaela M.; Yoo, In Seong; Achenbach, Stephan; Franke, Jörg; Blachutzik, Florian; Röther, Jens; Graf, Verena; Raaz-Schrauder, Dorette; Marwan, Mohamed; Schlundt, Christian (EuroIntervention, 2017)
AIMS Device sizing for LAA closure using transoesophageal echocardiography (TEE) can be challenging due to complex LAA anatomy. We investigated whether the use of 3D-printed left atrial appendage (LAA) models based on preprocedural computed tomography (CT) permits accurate device sizing. METHODS AND RESULTS Twenty-two (22) patients (73±8 years, 55% male) with atrial fibrillation requiring anticoagulation at high bleeding risk underwent LAA closure (WATCHMAN device). Preprocedurally, LAA was sized by TEE and third-generation dual-source CT. Based on CT, 3D printing models of LAA anatomy were created for simulation of device implantation. Device compression was assessed in a CT scan of the 3D model with the implanted device. Implantation was successful in all patients. Mean LAA ostium diameter based on TEE was 22±4 mm and based on CT 25±3 mm (p=0.014). Predicted device size based on simulated implantation in the 3D model was equal to the device finally implanted in 21/22 patients (95%). TEE would have undersized the device in 10/22 patients (45%). Device compression determined in the 3D-CT model corresponded closely with compression upon implantation (16±3% vs. 18±5%, r=0.622, p=0.003). CONCLUSIONS Patient-specific CT-based 3D printing models may assist device selection and prediction of device compression in the context of interventional LAA closur

67-year-old woman with exercise-induced angina pectoris - Mitschke, M.; Gattenloehner, S.; Achenbach, Susanne (Deutsche Medizinische Wochenschrift, 2014)
Was sehen Sie? Abb.1 Invasive Koronarangiografie des linken Koronararteriensystems. Eine 67-jahrige Patientin stellte sich mit belastungsabhangiger Angina pectoris vor. Eine dilatative Kardiomyopathie war bekannt. 5 Jahre zuvor war invasiv eine koronare Herzerkrankung ausgeschlossen worden. Die invasive Koronarangiografie des linken Koronararteriensystems zeigt einen Befund. Welcher ist das? Erlaubt dieser Befund eine Diagnose? Wenn ja, welche? Sind Differenzialdiagnosen moglich? Wenn ja, welche?
EVALuna2:12018

A 3-Hour Diagnostic Algorithm for Non-ST-Elevation Myocardial Infarction Using High-Sensitivity Cardiac Troponin T in Unselected Older Patients Presenting to the Emergency Department - Bahrmann, Philipp; Christ, Michael; Bahrmann, Anke; Rittger, Harald; Heppner, Hans Jürgen; Achenbach, Stephan; Bertsch, Thomas; Sieber, Cornel (Journal of the American Medical Directors Association, 2013)
Objectives: To determine if an algorithm implementing a serial high-sensitive cardiac troponin T (hs-cTnT) measurement at presentation (0h) and at 3 hours after presentation (3h) is helpful for early diagnosis of non-ST-elevation myocardial infarction (NSTEMI) in older patients.Design: Prospective observational cohort study.Setting: An emergency department (ED) of a city hospital covering a population of approximately 1 million in Germany.Participants: A total of 332 consecutive unselected patients were recruited, of whom 25 had one or more of the prespecified exclusion criteria and 1 had a missing hs-cTnT at 3h, resulting in a final population of 306 patients.Measurements: In addition to clinical examination, hs-cTnT was measured at 0h and 3h. The final diagnosis of NSTEMI was adjudicated by two independent consultants and an algorithm for rule-in and rule-out of NSTEMI was developed using classification and regression tree analysis. All patients were followed-up for cardiovascular outcome within 12 months.Results: Among 306 patients (mean age 81 +/- 6 years), 38 (12%) patients had NSTEMI. Accuracy to diagnose NSTEMI was significantly higher for hs-cTnT measurements at 3h versus 0h (area under the receiver operating characteristic curve [AUC] 0.88 vs. 0.82, P = .0038) and for absolute versus relative hs-cTnT delta changes (AUC 0.89 versus 0.69, P < .001). A diagnostic algorithm using hs-cTnT values at presentation and absolute delta changes values ruled-in NSTEMI in 23% and ruled-out NSTEMI in 35% of patients. For patients neither fulfilling the rule-in nor the rule-out criteria, an observational zone was established. Cumulative 1-year survival was 79.4%, 88.5%, and 99.1% in patients classified as rule-in, observational zone, and rule-out, respectively.Conclusion: In older patients, serial hs-cTnT measurements and absolute delta-changes at 3h were valuable for early diagnosis of NSTEMI. An algorithm ruled-in NSTEMI in one quarter of patients with high risk and ruled-out NSTEMI in one-third with low risk. Copyright (c) 2013 - American Medical Directors Association, Inc.
Keywords: Troponin; aged; emergencies; myocardial infarction; decision support techniques

Ability to remotely monitor atrial high-rate episodes using a single-chamber implantable cardioverter-defibrillator with a floating atrial sensing dipole - Hindricks, Gerhard; Theuns, Dominic A.; Bar-Lev, David; Anguera, Ignasi; Ayala Paredes, Félix Alejandro; Arnold, Martin; Geller, J. Christoph; Merkely, Béla; Dyrda, Katia Marjolaine; Perings, Christian; Maglia, Giampiero; Ploux, Sylvain; et al. (Europace, 2023)
AIMS: To allow timely initiation of anticoagulation therapy for the prevention of stroke, the European guidelines on atrial fibrillation (AF) recommend remote monitoring (RM) of device-detected atrial high-rate episodes (AHREs) and progression of arrhythmia duration along pre-specified strata (6 min…<1 h, 1 h…<24 h, ≥ 24 h). We used the MATRIX registry data to assess the capability of a single-lead implantable cardioverter-defibrillator (ICD) with atrial sensing dipole (DX ICD system) to follow this recommendation in patients with standard indication for single-chamber ICD. METHODS AND RESULTS: In 1841 DX ICD patients with daily automatic RM transmissions, electrograms of first device-detected AHREs per patient in each duration stratum were adjudicated, and the corresponding positive predictive values (PPVs) for the detections to be true atrial arrhythmia were calculated. Moreover, the incidence and progression of new-onset AF was assessed in 1451 patients with no AF history. A total of 610 AHREs ≥6 min were adjudicated. The PPV was 95.1% (271 of 285) for episodes 6min…<1 h, 99.6% (253/254) for episodes 1 h…<24 h, 100% (71/71) for episodes ≥24 h, or 97.5% for all episodes (595/610). The incidence of new-onset AF was 8.2% (119/1451), and in 31.1% of them (37/119), new-onset AF progressed to a higher duration stratum. Nearly 80% of new-onset AF patients had high CHA2DS2-VASc stroke risk, and 70% were not on anticoagulation therapy. Age was the only significant predictor of new-onset AF. CONCLUSION: A 99.7% detection accuracy for AHRE ≥1 h in patients with DX ICD systems in combination with daily RM allows a reliable guideline-recommended screening for subclinical AF and monitoring of AF-duration progression.
CRIS-Team Scopus Importer:2023-07-14
Keywords: AHRE; Atrial fibrillation; DX ICD; Remote monitoring; Risk of stroke; Single-lead ICD with atrial sensing

Absorb bioresorbable scaffold versus Xience metallic stent for prevention of restenosis following percutaneous coronary intervention in patients at high risk of restenosis: Rationale and design of the COMPARE ABSORB trial - Chang, Chun Chin; Onuma, Yoshinobu; Achenbach, Stephan; Barbato, Emanuele; Chevalier, Bernard; Cook, Stéphane; Dudek, Dariusz; Escaned, Javier; Gori, Tommaso; Kočka, Viktor; Tarantini, Giuseppe; West, Nick E.J.; et al. (Cardiovascular Revascularization Medicine, 2019)
Background: The advent of bioresorbable vascular scaffolds (BVS)was considered as a potential improvement in percutaneous coronary intervention (PCI)after the groundbreaking development of drug eluting stents (DES). However, the clinical performance, long-term safety and efficacy of BVS in complex coronary lesions remain uncertain. COMPARE ABSORB, a multicenter, single blind, prospective randomized trial, aims to compare the clinical outcomes between the Absorb BVS and Xience everolimus-eluting metallic stent (EES)in patients with coronary artery disease and a high risk of restenosis. Design: COMPARE ABSORB is designed to enroll 2100 patients at up to 45 European sites. Enrolled patients will possess high risk for restenosis due to clinical profile or coronary lesion complexity and will undergo elective or emergent PCI. Once included in the study, patients will receive either Absorb BVS or Xience EES. Specific advice on implantation technique including mandatory pre-dilatation, sizing and post-dilatation (PSP), will be used in the Absorb BVS arm. The primary endpoint is target lesion failure (TLF), a device-oriented composite endpoint (cardiac death, target vessel myocardial infarction and clinically-indicated target lesion revascularization). The trial is powered to assess non-inferiority of Absorb BVS compared with Xience EES with a predetermined non-inferiority margin of 4.5% at 1 year after index procedure. The clinical follow-up will continue for 7 years. Conclusions: The prospective COMPARE ABSORB randomized trial (ClinicalTrials.gov NCT02486068)will help to assess the long-term safety and efficacy of Absorb BVS compared with Xience EES in the treatments of patients with complex coronary artery disease and a high attendant risk of restenosis.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Absorb; Bioresorbable scaffold; Coronary artery disease

ABSORB bioresorbable scaffold versus Xience metallic stent in acute coronary syndromes with treated with percutaneous coronary intervention. A subanalysis of the COMPARE-ABSORB trial - Van Geuns, R. J.; Smits, P. C.; Chang, C. C.; Wlodarczyk, A.; Chevalier, B.; West, N.; Gori, T.; Barbato, E.; Tarantini, G.; Kocka, V.; Achenbach, Stephan; Dudek, D.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

ACCURACY AND SAFETY OF BIS MONITORING USING A NOVEL INTERFACE DEVICE CONNECTING CONVENTIONAL NEEDLE ELECTRODES AND BIS SENSORS FOR FOREHEAD SURGICAL APPROACH - Harada, Hideki; Tauchi, Miyuki (ANESTHESIA AND ANALGESIA, 2019)
CRIS-Team WoS Importer:2021-10-18

Accuracy of automated software-guided detection of significant coronary artery stenosis by CT angiography: Comparison with invasive catheterisation - Anders, Katharina; Achenbach, Stephan; Petit, Isabel; Daniel, Werner; Uder, Michael; Pflederer, Tobias (European Radiology, 2013)
Purpose: True automated detection of coronary artery stenoses might be useful whenever expert evaluation is not available, or as a "second reader" to enhance diagnostic confidence. We evaluated the accuracy of a PC-based stenosis detection tool alone and combined with expert interpretation. Methods: One hundred coronary CT angiography datasets were evaluated with the automated software alone, by manual interpretation (axial images, multiplanar reformations and maximum intensity projections in free double-oblique planes), and by expert interpretation aware of the automated findings. Stenoses ≥ 50 % were noted per-vessel and per-patient, and compared with invasive angiography. Results: Automated post-processing was successful in 90 % of patients (88 % of vessels). When excluding uninterpretable datasets, per-patient sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 89 %, 79 %, 74 % and 92 % (per-vessel: 82 %, 85 %, 48 % and 96 %). All 100 datasets were evaluable by expert interpretation. Per-patient sensitivity, specificity, PPV and NPV were 95 %, 95 %, 93 % and 97 % (per-vessel: 89 %,98 %, 88 % and 98 %). Knowing the results of automated interpretation did not improve the performance of expert readers. Conclusion: Automated off-line post-processing of coronary CT angiography shows adequate sensitivity, but relatively low specificity in coronary stenosis detection. It does not increase accuracy of expert interpretation. Failure of post-processing in 10 % of all patients necessitates additional manual image work-up. Key Points: • Coronary CT angiography is increasingly used for detection of coronary artery stenosis • Computer assisted diagnosis might facilitate and speed up interpretation • Performance in properly segmented cases compared favourably with manual image interpretation • However, automated segmentation failed in about 10 % of cases • Manual reading is still mandatory; computer assisted diagnosis can provide a useful second read © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer assisted diagnosis; Coronary angiography; Coronary artery disease; Coronary stenosis; Multidetector computed tomography

Accuracy of BIS monitoring using a novel interface device connecting conventional needle-electrodes and BIS sensors during frontal neurosurgical procedures - Harada, Hideki; Muta, Seiya; Kakuma, Tatsuyuki; Ukeda, Misa; Ota, So; Hirata, Maiko; Fujioka, Hiroshi; Nakashima, Osamu; Dietel, Barbara; Tauchi, Miyuki (PLoS ONE, 2021)
Background Bispectral index (BIS) monitoring is a widely used non-invasive method to monitor the depth of anesthesia. However, in the event of surgeries requiring a frontal approach, placement of the electrode may be impossible at the designated area to achieve a proper BIS measurement. Methods We developed an investigational interface device to connect needle-electrodes to BIS sensors. The safety and clinical performance were investigated in patients who underwent surgery. Direct BIS values from a disposable BIS electrode and indirect values via the interface device were simultaneously recorded from the same areas of electrode placement in a single patient. The agreement between the direct and indirect BIS values was statistically analyzed. Results The interface device with a silver electrode demonstrated sufficient electric conduction to transmit electroencephalogram signals. The overall BIS curves were similar to those of direct BIS monitoring. Direct and indirect BIS values from 18 patients were statistically analyzed using a linear mixed model and a significant concordance was confirmed (indirect BIS = 7.0405 + 0.8286 ∗ direct BIS, p<0.0001). Most observed data (2582/2787 data points, 92.64%) had BIS unit differences of 10 or less. Conclusions The interface device provides an opportunity for intraoperative BIS monitoring of patients, whose clinical situation does not permit the placement of conventional adhesive sensors at the standard location.
CRIS-Team Scopus Importer:2021-11-05

Accuracy of coronary computed tomography angiography vs intravascular ultrasound for evaluation of vessel area - Kruk, Mariusz; Wardziak, Lukasz; Mintz, Gary S.; Achenbach, Stephan; Pregowski, Jerzy; Ruzyllo, Witold; Dzielinska, Zofia; Demkow, Marcin; Witkowski, Adam; Kepka, Cezary (Journal of Cardiovascular Computed Tomography, 2014)
We evaluated the accuracy of commonly used thresholds for vessel area evaluation on coronary CT angiography (CTA) and assessed ability of CTA to image the adventitial border.We evaluated 137 paired (coronary CTA and intravascular ultrasound [IVUS]) coronary artery cross-sections in 30 patients. CTA analysis included measurements of external vessel border area defined at Hounsfield unit (HU) thresholds of 0 (presumed adventitia), 50, and 70 (presumed external elastic membrane [EEM]). IVUS analysis included measurements of lumen, EEM, and outer border of the highly echogenic area adjacent to EEM (presumed adventitia area).High correlation was found between CTA and IVUS measurements for EEM areas (R(2) = 0.65, P < .001 and R(2) = 0.60, P < .001 for CTA thresholds of 50 and 70 HU, respectively). CTA and IVUS measurements of adventitia areas were significantly correlated (R(2) = 0.74; P < .001), with no significant difference between the 2 methods (20.2 ± 6.4 mm(2) vs 19.8 ± 6.4 mm(2), respectively; P = .278). Cross-sectional coronary lumen radiodensity on CTA images and plaque burden measured on IVUS significantly affected the accuracy of CTA in assessment of the EEM area but not the presumed adventitial area.We have demonstrated that use of a 50-HU threshold for vessel area determination by CTA led to its significant overestimation, whereas 70-HU threshold was close to that of EEM on IVUS. CTA may accurately delineate the coronary adventitial border by using a 0-HU threshold.
EVALuna2:12002

Accuracy of dual-source CT to identify significant coronary artery disease in patients with uncontrolled hypertension presenting with chest pain: Comparison with coronary angiography - Marwan, Mohamed; Pflederer, Tobias; Schepis, Tiziano; Seltmann, Martin; Klinghammer, Lutz; Muschiol, Gerd; Ropers, Dieter; Daniel, Werner; Achenbach, Stephan (International Journal of Cardiovascular Imaging, 2012)
It has been previously reported that the sensitivity and specificity of multislice CT for detecting significant CAD (coronary artery disease) is high. Chest pain is a common presentation in patients with uncontrolled hypertension. We investigated the sensitivity and specificity of Dual-Source CT to detect and rule out significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. 260 consecutive patients presenting with acute chest pain in the context of stage 2 hypertension (systolic pressure ≥160 and/or diastolic pressure ≥100) were enrolled in the study. After admission, control of blood pressure and risk stratification, 82 patients were excluded due to renal insufficiency, prior coronary revascularisation or refused participation in the study. 90 further patients with low pre-test probability of CAD were also excluded. 88 remaining patients were subjected to CT coronary angiography using Dual-Source CT (Definition, Siemens Medical Solutions, Forchheim, Germany) within 24 h before invasive coronary angiography. A contrast-enhanced volume dataset was acquired (120 kV, 400 mAs/rot, collimation 2 × 64 × 0.6 mm, retrospective ECG gating). Data sets were evaluated concerning the presence or absence of significant coronary stenoses and validated against invasive coronary angiography. A significant stenosis was assumed if the diameter reduction was ≥50%. 88 patients (mean age 66 ± 11 years, mean heart rate 61 ± 9 bpm) were evaluated regarding the presence or absence of significant CAD (at least one stenosis ≥50% diameter reduction). Mean systolic blood pressure on presentation was 203 ± 20 mmHg and mean diastolic blood pressure was 103 ± 13 mmHg. On a per patient basis, the sensitivity and specificity for Dual-Source CT to detect significant CAD in vessels > 1.5 mm diameter was 100% (36/36, 95% CI 90-100) and 90% (47/52, 95% CI 79-97), respectively with a negative predictive value (NPV) of 100% (47/47, 95% CI 92-100) and a positive predictive value (PPV) of 88% (36/41, 95% CI 74-96). On a per artery basis, 352 vessels were evaluated (left main, left anterior descending, left circumflex and right coronary artery in 88 patients, 12 vessels could not be assessed due to either motion artefacts or heavy calcification and were considered positive for stenoses) with a sensitivity of 84% (54/64, 95% CI 72-95) and specificity of 94% (272/288, 95% CI 88-100); NPV was 96% (272/282, 95% CI 90-100) and PPV was 77% (54/70, 95% CI 62-91). Our study demonstrates high sensitivity, specificity and negative predictive value of Dual- Source CT to detect significant CAD in patients presenting with uncontrolled hypertension accompanied by chest pain. Dual-Source CT angiography may be useful to safely rule out coronary artery stenoses and avoid invasive angiograms in these patients. © Springer Science+Business Media, B.V. 2011.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CT; Stenosis; Uncontrolled hypertension

Accuracy of Fractional Flow Reserve Derived From Coronary Angiography - Fearon, William F.; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard; Jeremias, Allen; Fournier, Stephane; Kirtane, Ajay J.; Kornowski, Ran; Greenberg, Gabriel; Jubeh, Rami; Kolansky, Daniel M.; et al. (Circulation, 2019)
Background: Measuring fractional flow reserve (FFR) with a pressure wire remains underutilized because of the invasiveness of guide wire placement or the need for a hyperemic stimulus. FFR derived from routine coronary angiography (FFRangio) eliminates both of these requirements and displays FFR values of the entire coronary tree. The FFRangio Accuracy versus Standard FFR (FAST-FFR) study is a prospective, multicenter, international trial with the primary goal of determining the accuracy of FFRangio.
CRIS-Team WoS Importer:2019-03-06

Accuracy of prospectively ECG-triggered very low-dose coronary dual-source CT angiography using iterative reconstruction for the detection of coronary artery stenosis: comparison with invasive catheterization - Layritz, Christian; Schmid, Julia; Achenbach, Stephan; Ulzheimer, Stefan; Wüst, Wolfgang; May, Matthias; Ropers, Dieter; Klinghammer, Lutz; Daniel, Werner; Pflederer, Tobias; Lell, Michael (European Heart Journal - Cardiovascular Imaging, 2014)
To evaluate the image quality and diagnostic accuracy of very low-dose computed tomography (CT) angiography (CTA) for the evaluation of coronary artery stenosis.Iterative reconstruction (IR) has shown to substantially reduce image noise and hence permit the use of very low-dose data acquisition protocols in coronary CTA.Fifty symptomatic patients with an intermediate likelihood for coronary artery disease underwent coronary CTA (heart rate: 59 ± 5 bpm, prospectively ECG-triggered axial acquisition, 100 kV, 160 mAs, 2 × 128 × 0.6 mm collimation, 60 mL contrast, 6 mL/s) prior to invasive coronary angiography. CTA images were reconstructed using both standard filtered back projection (FBP) and a raw data-based IR algorithm [Sinogram Affirmed Iterative Reconstruction (SAFIRE), Siemens Healthcare]. Subjective image quality (four-point Likert scale from 0 = non-diagnostic to 3 = excellent image quality), image noise, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), as well as the presence of coronary stenosis >50% were independently determined by two observers.The mean dose-length product was 46.8 ± 3.5 mGy cm (estimated effective dose 0.66 ± 0.05 mSv). IR led to significantly improved objective image quality compared with FBP (image noise: 41 ± 12 vs. 49 ± 11 HU, P < 0.0001; CNR: 16 ± 8 vs. 12 ± 4, P < 0.0001; SNR: 13 ± 7 vs. 10 ± 3, P < 0.0001). Four coronary segments were not evaluable on FBP data, whereas all segments showed diagnostic image quality with IR. To detect significant coronary stenosis, sensitivity, specificity, positive predictive value, and negative predictive value were 69% (11/16), 97% (175/180), 69% (11/16), and 97% (175/180) per vessel with FBP data sets, respectively. With IR data sets, the corresponding values were 81% (13/16), 97% (178/184), 68% (13/19), and 98% (178/181). These differences were not statistically significant (P = 0.617).Raw data-based IR significantly improves image quality in very low-dose prospectively ECG-triggered coronary dual-source CTA when compared with standard reconstruction using FBP.
EVALuna2:11955

A clinical model to identify patients with high-risk coronary artery disease - Yang, Yelin; Chen, Li; Yam, Yeung; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor Y.; Chinnaiyan, Kavitha; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
This study sought to develop a clinical model that identifies patients with and without high-risk coronary artery disease (CAD).Although current clinical models help to estimate a patient's pre-test probability of obstructive CAD, they do not accurately identify those patients with and without high-risk coronary anatomy.Retrospective analysis of a prospectively collected multinational coronary computed tomographic angiography (CTA) cohort was conducted. High-risk anatomy was defined as left main diameter stenosis >=50%, 3-vessel disease with diameter stenosis >=70%, or 2-vessel disease involving the proximal left anterior descending artery. Using a cohort of 27,125, patients with a history of CAD, cardiac transplantation, and congenital heart disease were excluded. The model was derived from 24,251 consecutive patients in the derivation cohort and an additional 7,333 nonoverlapping patients in the validation cohort.The risk score consisted of 9 variables: age, sex, diabetes, hypertension, current smoking, hyperlipidemia, family history of CAD, history of peripheral vascular disease, and chest pain symptoms. Patients were divided into 3 risk categories: low (<=7 points), intermediate (8 to 17 points) and high (>=18 points). The model was statistically robust with area under the curve of 0.76 (95% confidence interval [CI]: 0.75 to 0.78) in the derivation cohort and 0.71 (95% CI: 0.69 to 0.74) in the validation cohort. Patients who scored <=7 points had a low negative likelihood ratio (<0.1), whereas patients who scored >=18 points had a high specificity of 99.3% and a positive likelihood ratio (8.48). In the validation group, the prevalence of high-risk CAD was 1% in patients with <=7 points and 16.7% in those with >=18 points.We propose a scoring system, based on clinical variables, that can be used to identify patients at high and low pre-test probability of having high-risk CAD. Identification of these populations may detect those who may benefit from a trial of medical therapy and those who may benefit most from an invasive strategy.
EVALuna2:12062

A cross-sectional survey of coronary plaque composition in individuals on non-statin lipid lowering drug therapies and undergoing coronary computed tomography angiography - Al'Aref, Subhi J.; Su, Amanda; Gransar, Heidi; van Rosendael, Alexander R.; Rizvi, Asim; Berman, Daniel S.; Callister, Tracy Q.; DeLago, Augustin; Hadamitzky, Martin; Hausleiter, Joerg; Al-Mallah, Mouaz H.; Budoff, Matthew J.; et al. (Journal of Cardiovascular Computed Tomography, 2019)
Introduction: Non-statin therapy (NST) is used as second-line treatment when statin monotherapy is inadequate or poorly tolerated. Objective: To determine the association of NST with plaque composition, alone or in combination with statins, in patients undergoing coronary computed tomography angiography (coronary CTA). Methods: From the multicenter CONFIRM registry, we analyzed individuals who underwent coronary CTA with known lipid-lowering therapy status and without prior coronary artery disease at baseline. We created a propensity score for being on NST, followed by stepwise multivariate linear regression, adjusting for the propensity score as well as risk factors, to determine the association between NST and the number of coronary artery segments with each plaque type (non-calcified (NCP), partially calcified (PCP) or calcified (CP)) and segment stenosis score (SSS). Results: Of the 27,125 subjects in CONFIRM, 4,945 met the inclusion criteria; 371 (7.5%) took NST. At baseline, patients on NST had more prevalent risk factors and were more likely to be on concomitant cardiac medications. After multivariate and propensity score adjustment, NST was not associated with plaque composition: NCP (0.07 increase, 95% CI: −0.05, 0.20; p = 0.26), PCP (0.10 increase, 95% CI: −0.10, 0.31; p = 0.33), CP (0.18 increase, 95% CI: −0.10, 0.46; p = 0.21) or SSS (0.45 increase, 95% CI: −0.02,0.93; p = 0.06). The absence of an effect of NST on plaque type was not modified by statin use (p for interaction > 0.05 for all). Conclusion: In this cross-sectional study, non-statin therapy was not associated with differences in plaque composition as assessed by coronary CTA.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Coronary computed tomography angiography; Coronary plaque composition; Ezetimibe; Fibrate; Niacin; Non-statin therapy

Acute kidney injury and renal replacement therapy after resuscitated out-of-hospital cardiac arrest: risk factors and impact on prognosis in patients treated with mild therapeutic hypothermia - Bal, Zeynep; Achenbach, Stephan; Unger, C.; Schindler, F.; Schneider, R. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Acute Mechanical Performance of Magmaris vs. DESolve Bioresorbable Scaffolds in a Real-World Scenario - Boeder, Niklas F.; Doerr, Oliver; Koepp, Tim; Blachutzik, Florian; Achenbach, Stephan; Elsaesser, Albrecht; Hamm, Christian W.; Nef, Holger M. (Frontiers in Cardiovascular Medicine, 2021)
Background: After the bioresorbable PLLA-based vascular scaffold (Absorb BVS) was taken from the market due to its high adverse event rates, a magnesium-based scaffold (Magmaris) was introduced.
CRIS-Team WoS Importer:2021-07-09

Acute right insular ischaemic lesions and poststroke left ventricular dysfunction - Winder, Klemens; Villegas Millar, Carolina; Siedler, Gabriela; Knott, Michael; Dörfler, Arnd; Engel, Anna; Achenbach, Stephan; Hilz, Max-Josef; Kallmünzer, Bernd; Schwab, Stefan; Seifert, Frank; Fröhlich, Kilian (Stroke and Vascular Neurology, 2023)
IntroductionMyocardial injury related to acute ischaemic stroke is common even without primary cardiac disease. We intended to determine associations between values of left ventricular ejection fraction (LVEF) and ischaemic stroke lesion sites. MethodsOf a local database, patients with acute first-ever ischaemic stroke confirmed by brain imaging but without pre-existing heart disease were included. The cardiac morphology and LVEF were obtained from transthoracic or transesophageal echocardiography, and impaired LVEF was categorised as mild (35%-50%), moderate (34%-25%) and severe (<25%). Patient age, stroke severity, ischaemic lesion volume, prevalence of troponin I increase (>0.1 ng/mL), atrial fibrillation and cardiac wall motion abnormalities were assessed and compared between patients with and without impaired LVEF after stroke (significance: p<0.05). A multivariate voxelwise lesion analysis correlated LVEF after stroke with sites of ischaemic lesions. ResultsOf 1209 patients who had a stroke, 231 (mean age 66.3 +/- 14.0 years) met the inclusion criteria; 40 patients (17.3%) had an impaired LVEF after stroke. Patients with impaired LVEF had higher infarct volumes (53.8 mL vs 30.0 mL, p=0.042), a higher prevalence of troponin increase (17.5% vs 4.2%, p=0.006), cardiac wall motion abnormalities (42.5% vs 5.2%, p<0.001) and atrial fibrillation (60.0% vs 26.2%, p<0.001) than patients with LVEF of >50%. The multivariate voxelwise lesion analysis yielded associations between decreased LVEF and damaged voxels in the insula, amygdala and operculum of the right hemisphere. ConclusionOur imaging analysis unveils a prominent role of the right hemispheric central autonomic network, especially of the insular cortex, in the brain-heart axis. Our results support preliminary evidence that acute ischaemic stroke in distinct brain regions of the central autonomic network may directly impair cardiac function and thus further supports the concept of a distinct stroke-heart syndrome.
CRIS-Team WoS Importer:2023-02-24

Adding or selecting imaging modalities for incremental diagnosis: A case study of 18FDG PET/CT in prosthetic valve endocarditis - Dilsizian, Vasken; Achenbach, Stephan; Narula, Jagat (Journal of the American College of Cardiology : Cardiovascular imaging, 2013)
CRIS-Team Scopus Importer:2023-03-08

Additional diagnostic and prognostic value of copeptin ultra-sensitive for diagnosis of non-ST-elevation myocardial infarction in older patients presenting to the emergency department - Bahrmann, Philipp; Bahrmann, Anke; Breithardt, Ole-A.; Daniel, Werner; Christ, Michael; Sieber, Cornel; Bertsch, Thomas (Clinical Chemistry and Laboratory Medicine, 2013)
Background: Identifying older patients with non-ST-elevation myocardial infarction (NSTEMI) within the very large proportion with elevated high-sensitive cardiac troponin T (hs-cTnT) is a diagnostic challenge because they often present without clear symptoms or electrocardiographic features of acute coronary syndrome to the emergency department (ED). We prospectively investigated the diagnostic and prognostic performance of copeptin ultra-sensitive (copeptin-us) and hs-cTnT compared to hs-cTnT alone for NSTEMI at prespecified cut-offs in unselected older patients.Methods: We consecutively enrolled 306 non-surgical patients >= 70 years presenting to the ED. In addition to clinical examination, copeptin-us and hs-cTnT were measured at admission. Two cardiologists independently adjudicated the final diagnosis of NSTEMI after reviewing all available data. All patients were followed up for cardiovascular-related death within the following 12 months.Results: NSTEMI was diagnosed in 38 (12%) patients (age 81 +/- 6 years). The combination of copeptin- us >= 14 pmol/L and hs-cTnT >= 0.014 mu g/L compared to hs-cTnT >= 0.014 mu g/L alone had a positive predictive value of 21% vs. 19% to rule in NSTEMI. The combination of copeptinus <14 pmol/L and hs-cTnT <0.014 mu g/L compared to hs-cTnT <0.014 mu g/L alone had a negative predictive value of 100% vs. 99% to rule out NSTEMI. Hs-cTnT >= 0.014 mu g/L alone was significantly associated with outcome. When copeptin- us >= 14 pmol/L was added, the net reclassification improvement for outcome was not significant (p=0.809).Conclusions: In unselected older patients presenting to the ED, the additional use of copeptin- us at predefined cut-offs may help to reliably rule out NSTEMI but may not help to increase predicted risk for outcome compared to hs-cTnT alone.
Keywords: aged; copeptins; emergencies; myocardial infarction; troponin

Admission of patients with STEMI since the outbreak of the COVID-19 pandemic: a survey by the European Society of Cardiology - Pessoa-Amorim, Guilherme; Camm, Christian F.; Gajendragadkar, Parag; De Maria, Giovanni Luigi; Arsac, Celine; Laroche, Cecile; Zamorano, José Luis; Weidinger, Franz; Achenbach, Stephan; Maggioni, Aldo P.; Gale, Chris P.; Poppas, Athena; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2020)
AIMS: The COVID-19 pandemic required a significant redeployment of worldwide healthcare resources. Fear of infection, national lockdowns and altered healthcare priorities have the potential to impact utilisation of healthcare resources for non-communicable diseases. To survey health professionals' views of the impact of the COVID-19 pandemic on the rate and timing of admission of patients with ST-elevation myocardial infarction (STEMI), the European Society of Cardiology (ESC) administered an internet-based questionnaire to cardiologists and cardiovascular nurses across 6 continents. METHODS AND RESULTS: 3101 responses were received from 141 countries across 6 continents. 88.3% responded that their country was in "total lockdown" and 7.1% in partial lockdown. 78.8% responded that the number of patients presenting with STEMI was reduced since the coronavirus outbreak and 65.2% indicated that the reduction in STEMI presentations was >40%. Approximately 60% of all respondents reported that STEMI patients presented later than usual and 58.5% that >40% of STEMI patients admitted to hospital presented beyond the optimal window for primary percutaneous intervention (PCI) or thrombolysis. Independent predictors of the reported higher rate of delayed STEMI presentation were a country in total lockdown, >100 COVID-19 cases admitted locally, and the complete restructuring of the local cardiology service. CONCLUSION: The survey indicates that the impact of COVID-19 on STEMI presentations is likely to be substantial, with both lower presentations and a higher rate of delayed presentations occurring. This has potentially important ramifications for future healthcare and policy planning in the event of further waves of this pandemic.
CRIS-Team Scopus Importer:2020-08-07
Keywords: COVID-19; European Society of Cardiology; ST-elevation myocardial infarction

Advanced computed tomographic anatomical and morphometric plaque analysis for prediction of fractional flow reserve in intermediate coronary lesions - Opolski, Maksymilian P.; Kepka, Cezary; Achenbach, Stephan; Pregowski, Jerzy; Kruk, Mariusz; Staruch, Adam D.; Kadziela, Jacek; Ruzyllo, Witold; Witkowski, Adam (European Journal of Radiology, 2014)
To determine the application of advanced coronary computed tomography angiography (CCTA) plaque analysis for predicting invasive fractional flow reserve (FFR) in intermediate coronary lesions.Sixty-one patients with 71 single intermediate coronary lesions (>= 50-80% stenosis) on CCTA prospectively underwent coronary angiography and FFR. Advanced anatomical and morphometric plaque analysis was performed based on CCTA data set to determine optimal criteria for significant flow impairment. A significant stenosis was defined as FFR <= 0.80.FFR averaged 0.85 ± 0.09, and 19 lesions (27%) were functionally significant. FFR correlated with minimum lumen area (MLA) (r=0.456, p<0.001), minimum lumen diameter (MLD) (r=0.326, p=0.006), reference lumen diameter (RLD) (r=0.245, p=0.039), plaque burden (r=-0.313, p=0.008), lumen area stenosis (r=-0.305, p=0.01), lesion length (r=-0.692, p<0.001), and plaque volume (r=-0.668, p<0.001). There was no relationship between FFR and CCTA morphometric plaque parameters. By multivariate analysis the independent predictors of FFR were lesion length (beta=-0.581, p<0.001), MLA (beta=0.360, p=0.041), and RLD (beta=-0.255, p=0.036). The optimal cutoffs for lesion length, MLA, MLD, RLD, and lumen area stenosis were >18.5mm, <= 3.0mm(2), <= 2.1mm, <= 3.2mm, and >69%, respectively (max. sensitivity: 100% for MLA, max. specificity: 79% for lumen area stenosis).CCTA predictors for FFR support the mathematical relationship between stenosis pressure drop and coronary flow. CCTA could prove to be a useful rule-out test for significant hemodynamic effects of intermediate coronary stenoses.
EVALuna2:11882

After ISCHEMIA: Is coronary CTA the new gatekeeper? - Smolka, Silvia; Desai, Milind Y.; Achenbach, Stephan (Herz, 2020)
The ISCHEMIA trial investigated two major principles in the therapy of coronary artery disease (CAD), i.e., symptom relief and improvement of prognosis. Specifically, it was designed to answer the question of whether, after ruling out left main stenosis, a routine interventional strategy in addition to optimal medical therapy can improve clinical outcome. Overall, this hypothesis could not be confirmed. Nevertheless, the trial yields interesting new aspects in the field of cardiac imaging. As a noninvasive diagnostic approach for individuals with suspected coronary artery disease, two different concepts are available: stress testing for ischemia (single-photon emission computed tomography, positron emission tomography, cardiac magnetic resonance imaging, stress echocardiography) and anatomic visualization of coronary artery stenosis by coronary computed tomography (CT) angiography (coronary CTA). While there was no randomized comparison between these two approaches in ISCHEMIA, the good outcome achieved by using coronary CTA as a “gatekeeper” to randomization supports the potential of coronary CTA as a diagnostic tool—both as first- and as second-line—when CAD is suspected. However, the trial also raises new questions in the field of cardiac imaging that need to be addressed in future studies.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Computed tomography angiography; Coronary artery disease; Diagnostic techniques; cardiovascular; Prognosis; Stress testing

Age-related risk of major adverse cardiac event risk and coronary artery disease extent and severity by coronary CT angiography: results from 15 187 patients from the International Multisite CONFIRM Study - Nakazato, Ryo; Arsanjani, Reza; Achenbach, Stephan; Gransar, Heidi; Cheng, Victor Y.; Dunning, Allison; Lin, Fay Y.; Al-Mallah, Mouaz; Budoff, Matthewj.; Callister, Tracy Q.; Chang, Hyuk-Jae; Cademartiri, Filippo; et al. (European Heart Journal - Cardiovascular Imaging, 2014)
Prior studies evaluating the prognostic utility of cardiac CT angiography (CCTA) have been largely constrained to an all-cause mortality endpoint, with other cardiac endpoints generally not reported. To this end, we sought to determine the relationship of extent and severity of coronary artery disease (CAD) by CCTA to risk of incident major adverse cardiac events (MACEs) (defined as death, myocardial infarction, and late revascularization).We identified subjects without prior known CAD who underwent CCTA and were followed for MACE. CAD by CCTA was defined as none (0% luminal stenosis), mild (1-49% luminal stenosis), moderate (50-69% luminal stenosis), or severe (>=70% luminal stenosis), and >=50% luminal stenosis was considered as obstructive. CAD severity was judged on per-patient, per-vessel, and per-segment basis. Time to MACE was estimated using univariable and multivariable Cox proportional hazards models. Among 15 187 patients (57 ± 12 years, 55% male), 595 MACE events (3.9%) occurred at a 2.4 ± 1.2 year follow-up. In multivariable analyses, an increased risk of MACE was observed for both non-obstructive [hazard ratio (HR) 2.43, P < 0.001] and obstructive CAD (HR: 11.21, P < 0.001) when compared with patients with normal CCTA. Risk-adjusted MACE increased in a dose-response relationship based on the number of vessels with obstructive CAD >=50%, with increasing hazards observed for non-obstructive (HR: 2.54, P < 0.001), obstructive one-vessel (HR: 9.15, P < 0.001), two-vessel (HR: 15.00, P < 0.001), or three-vessel or left main (HR: 24.53, P < 0.001) CAD. Among patients stratified by age <65 vs. >=65 years, older individuals experienced higher risk-adjusted hazards for MACE for non-obstructive, one-, and two-vessel, with similar event rates for three-vessel or left main (P < 0.001 for all) compared with normal individuals age <65. Finally, there was a dose relationship of CAD findings by CCTA and MACE event rates with each advancing decade of life.Among individuals without known CAD, non-obstructive, and obstructive CAD are associated with higher MACE rates, with different risk profiles based on age.
EVALuna2:11997

A global registry of fractional flow reserve (FFR)–guided management during routine care: Study design, baseline characteristics and outcomes of invasive management - Schampaert, Erick; Kumar, Gautam; Achenbach, Stephan; Galli, Stefano; Tanaka, Nobuhiro; Teraphongphom, Tarn; Ginn, Greg; Zhang, Zhen; Somi, Samer; Amoroso, Giovanni; Brueren, Guus; Krasnow, Joshua; et al. (Catheterization and Cardiovascular Interventions, 2020)
Background: The use and clinical outcomes of fractional flow reserve (FFR)–guided revascularization in patients presenting with either stable coronary artery disease (CAD) or an acute coronary syndrome (ACS) in daily clinical practice are uncertain. Objective: To prospectively characterize the frequency of the change in treatment plan when FFR is performed compared to the initial decision based on angiography alone and procedure-related outcomes. Methods: We undertook a prospective, multicenter, multinational, open-label, observational study of coronary physiologic measurements during clinically indicated coronary angiography. The treatment plan, including medical therapy, PCI or CABG, was prospectively recorded before and after performing FFR. Adverse events were pre-defined and prospectively recorded per local investigators (PRESSUREwire; ClinicalTrials.gov identifier: NCT02935088). Results: Two thousand two hundred and seventeen subjects were enrolled in 70 hospitals across 15 countries between October 2016–February 2018. The mean FFR (all measurements) was 0.84. The treatment plan based on angiography-alone changed in 763/2196 subjects (34.7%) and 872/2931 lesions (29.8%) post-FFR. In the per-patient analysis, the initial treatment plan based on angiography versus the final treatment plan post-FFR were medical management 1,350 (61.5%) versus 1,470 (66.9%) (p =.0017); PCI 717 (32.7%) versus 604 (27.5%) (p =.0004); CABG 119 (5.4%) versus 121 (5.5%) (p =.8951). The frequency of intended revascularization changed from 38.1 to 33.0% per patient (p =.0005) and from 35.5 to 29.6% per lesion (p <.0001) following FFR. Conclusions: On an individual patient basis, use of FFR in everyday practice changes the treatment plan compared to angiography in more than one third of all-comers selected for physiology-guided managements. FFR measurement is safe, providing incremental information to guide revascularization decisions.
CRIS-Team Scopus Importer:2020-03-27
Keywords: coronary; imaging; physiology; registries; reporting

ALTERATION OF CONNEXIN EXPRESSION DURING EARLY STAGE OF ATHEROSCLEROSIS - Oshita, Kensuke; Urschel, K.; Botos, B.; Achenbach, Stephan; Dietel, B.; Tauchi-Brück, Miyuki (ATHEROSCLEROSIS, 2021)
CRIS-Team WoS Importer:2021-09-24

Analgosedierung in der Kardiologie - Konsensuspapier der DGK und DGAI 2024 - Tilz, Roland R.; Busch, Sonia; Chun, K. R.J.; Frerker, Christian; Gaede, Luise; Steven, Daniel; Tiefenbacher, Christiane; Eckardt, Lars; Sander, Michael; Zwißler, Bernhard; Wappler, Frank; von Dossow, Vera; et al. (Die Kardiologie, 2024)
Interventions in electrophysiology and interventional cardiology are increasingly common. Many of these interventions are performed under sedation. This is necessary to ensure the patient’s comfort and safety to facilitate transesophageal echocardiography, pain control, or long procedure duration, e.g., with stable mapping conditions. This consensus document by the German Cardiac Society (DGK) together with the German Association of Anesthesia and Intensive Care (DGAI) describes—based on current evidence—the structured pathways for sedation in cardiovascular medicine. The major goal is patient safety for patients undergoing electrophysiology and endovascular cardiovascular procedures. This consensus document is also aligned to the published German S3 guideline for sedation in gastroenterology.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Atrial fibrillation; Catheter ablation; Defibrillators; implantable; Mitraclip; Pacemaker; artificial

Analysis of left ventricular function, left ventricular outflow tract and aortic valve area using computed tomography: Influence of reconstruction parameters on measurement accuracy - Hell, Michaela; Steinmann, Bettine; Scherkamp, Tassilo; Arnold, Martin; Achenbach, Stephan; Marwan, Mohamed (British Journal of Radiology, 2021)
Objectives: Computed tomography (CT) allows reproducible assessment of left ventricular (LV) function, left ventricular outflow tract area (LVOTarea) and aortic valve area (AVA). We evaluated the influence of image reconstruction parameters on these measurements.
CRIS-Team WoS Importer:2021-08-06

Analysis of the Movement of ICD Leads During Cardiac Contraction as Determinant of Intracardiac Impedance - Kirchner, Jens; Fischer, Georg; Arnold, Martin (2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2018)
Intracardiac impedance (ICI) has been proposed as an indicator of cardiac status in heart failure patients. We introduce a biophysical model of the measurement setup and apply it to the movement of ICD leads reconstructed from clinical-routine X-ray recordings in a study population of 12 patients. Tilting of the right ventricular lead is found to be a major determinant of ICI changes during cardiac contraction with a mean contribution of 42+-23%. The relative position between right and left ventricular lead is the second major contributor (40+-22%). However, the contributions of the components of movement strongly differ between the patients. The proposed method provides means for a better interpretation of ICI measurements and for an improvement of its performance for monitoring heart failure statu

Analyzing iron oxide nanoparticles for drug delivery - innovative investigation tools for nanotoxicology - Janko, Christina; Poettler, M.; Friedrich, Ralf P.; Zaloga, Jan; Unterweger, Harald; Dürr, Stephan; Tietze, Rainer; Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph (2016)
EVALuna2:33178

A new novolimus-eluting bioresorbable coronary scaffold: Present status and future clinical perspectives - Nef, Holger M.; Wiebe, Jens; Foin, Nicolas; Blachutzik, Florian; Doerr, Oliver; Toyloy, Sara; Hamm, Christian W. (International Journal of Cardiology, 2017)
The DESolve® scaffold (Elixir Medical Corporation, Sunnyvale, California, USA) is manufactured from a poly-l-lactide based polymer and elutes an anti-proliferative, anti-inflammatory drug, Novolimus from a poly-l-lactide based topcoat mixture. The strut thickness is 150μm and the scaffold has platinum-iridium radiopaque markers at both ends. Radial support is available during the early time period to prevent recoil. The scaffold biodegrades within 1year (>90% reduction in molecular weight) and then completely bioresorbs within 2years. The DESolve® scaffold permits a wide range of expansion with a consequently reduced risk for strut fracture. Lumen and scaffold enlargement is observed within 3-6months in both preclinical and clinical studies potentially allowing for the scaffolded region to respond to vasoactive stimuli. The device has a unique property of self-correction observed in bench top studies, which in clinical practice has the potential to eliminate minor malapposition following deployment.
EVALuna2:33654

A new novolimus-eluting bioresorbable scaffold for large coronary arteries: an OCT study of acute mechanical performance - Boeder, Niklas F.; Koepp, Tim; Dorr, Oliver; Bauer, Timm; Mattesini, Alessio; Elsasser, Albrecht; Mollmann, Helge; Blachutzik, Florian; Achenbach, Stephan; Ghanem, Alexander; Hamm, Christian W.; Nef, Holger M. (International Journal of Cardiology, 2016)
AIMS: To evaluate the acute performance of a novolimus-eluting bioresorbable scaffold (BRS) with a nominal diameter of 4.0mm (DESolve® XL) using optical coherence tomography (OCT) in terms of appropriate scaffold deployment. METHODS AND RESULTS: Ten patients (55.6% male, mean age 60.0 y) undergoing OCT-guided scaffold implantation were enrolled consecutively in this retrospective study. Using data from the final pullback, the following indexes were calculated: mean and minimum area, residual area stenosis, incomplete strut apposition, tissue prolapse, eccentricity and symmetry indexes, strut fracture, and edge dissection. The clinical indication for the procedure was acute coronary syndrome in roughly half (55.5%) of the cases. All three main vessels were affected equally. The maximum post-dilatation balloon inflation pressure was 14.7±4.2atm. OCT analysis showed a lumen area of 11.4±1.9mm(2) and a scaffold area of 11.5±2.1mm(2). Mean residual area stenosis was 28.6%. No strut fractures or edge dissections were apparent. The mean eccentricity index was 0.65±0.16 and the mean symmetry index 0.39±0.25. CONCLUSION: The size of large vessels does not adversely influence acute mechanical performance as assessed by the eccentricity and symmetry indexes. No adverse cardiac event occurred during the hospital stay or the 30-day follow-up. It is feasible to treat large vessels with the DESolve® XL BRS.
EVALuna2:33673

Angiographic Findings and Revascularization Success in Patients With Acute Myocardial Infarction and Previous Coronary Bypass Grafting - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Röther, Jens; Nef, Holger; Hamm, Christian; Schlundt, Christian (American Journal of Cardiology, 2016)
Current guidelines recommend invasive coronary angiography and interventional revascularization in ST-elevation and Non-ST-elevation myocardial infarction (STEMI and NSTEMI). The aim of this study was to analyze culprit lesions and percutaneous coronary intervention (PCI) success in patients with previous coronary artery bypass grafting (CABG). We analyzed the data of 121 consecutive patients in whom coronary angiography was performed in the setting of STEMI or NSTEMI and who had previous CABG. Coronary angiograms were reviewed, and clinical data were evaluated. The culprit vessel was identified by means of electrocardiographic findings, echocardiography, and coronary angiography. A bypass graft was the culprit vessel in 86% of patients with STEMI and 68% of patients with NSTEMI. Venous grafts were culprit vessels significantly more frequently than arterial grafts (81 of 260 venous grafts vs 4 of 65 arterial grafts, p <0.001). Attempted acute PCI was successful in 97% of native arteries (31 of 32 patients) but only in 81% of bypass grafts (68 of 84 patients, p = 0.031). Overall in-hospital mortality was 13% (STEMI: 25%, NSTEMI: 10%, p <0.001) and was significantly higher after failed acute PCI (6 of 11 patients; 55%) compared with successful acute PCI (7 of 110 patients; 6%; p = 0.006). In conclusion, the culprit lesion in patients with previous CABG who present with STEMI or NSTEMI is more often located in bypass grafts than in native arteries. Successful PCI is more likely in native arteries compared with bypass grafts.
EVALuna2:33683

Angiographic patterns of drug-eluting stent restenosis after treatment with drug-coated balloon versus balloon angioplasty: Late lumen loss subgroup analyses of the PEPCAD-DES study - Rittger, Harald; Woehrle, Jochen; Brachmann, Johannes; Hohenforst-Schmidt, Wolfgang; Schlundt, Christian; Lonke, Sandra; Von Cranach, Moritz; Markovic, Sinisa; Achenbach, Stephan; Waliszewski, Matthias (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVES: This report provides the results of additional late lumen loss (LLL) analyses the predefined subgroup of diabetics and post hoc analyses of selected lesion morphologies to further elucidate the efficacy of paclitaxel coated balloon (PCB) angioplasty (clinical trials identifier NCT00998439). BACKGROUND: The PEPCAD-DES trial revealed that in lesion LLL and the target lesion revascularization rate (TLR) were significantly reduced with PCB angioplasty as compared with plain old balloon angioplasty (POBA) in patients with drug-eluting stent restenosis (DES-ISR). METHODS: A total of 110 patients with restenosis of Sirolimus- (SES), Everolimus- (EES), or Paclitaxel-eluting (PES) stents in native coronary arteries were randomized 2:1 to receive treatment with PCB (72 patients) or POBA (38 patients). RESULTS: In the PCB group, LLL did not differ for PES versus non-PES lesions (0.46 ± 0.55 mm vs. 0.41 ± 0.65 mm, P = 0.81). Moreover, there was no difference in LLL when PCB's were used in single and multiple layer DES-ISR (0.35 ± 0.60 mm vs. 0.51 ± 0.63 mm, P = 0.31). In contrast, patients treated with POBA for multilayer DES-ISR were more likely to have significantly higher LLL as compared with single layer DES-ISR (1.29 ± 0.76 mm vs. 0.65 ± 0.60 mm, P = 0.02). There was no LLL difference between diabetics and non-diabetics when treated with PCB angioplasty (0.46 ± 0.76 mm vs. 0.43 ± 0.54 mm, P = 0.83). CONCLUSION: Our hypothesis generating results indicated that there were no differences in terms of LLL when PCB angioplasty was applied in subgroups of single versus multiple layer DES-ISR and PES-ISR versus non-PES ISR. LLL was not higher in diabetic patients as compared with the their non-diabetic counterparts when treated with PCB's. © 2016 Wiley Periodicals, Inc.
EVALuna2:33671

Angiography-Derived Fractional Flow Reserve Versus Invasive Nonhyperemic Pressure Ratios - Johnson, Nils P.; Matsumura, Mitsuaki; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Jeremias, Allen; Fournier, Stephane; De Bruyne, Bernard; Leon, Martin B.; Fearon, William F. (Journal of the American College of Cardiology, 2019)
EVALuna2:213003

Angiotensin pathways under therapy with empagliflozin in patients with chronic heart failure - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Rauh, Manfred; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2023)
Aims: Large outcome studies demonstrated a reduction of heart failure hospitalization or cardiovascular death in patients with chronic heart failure (CHF). The renin–angiotensin system (RAS) is a key player in fluid and sodium regulation. The classic angiotensin-converting enzyme–angiotensin II–angiotensin-1 receptor axis (Ang I–ACE–Ang II receptor axis) is predominantly angiotensin II (Ang-II) induced and promotes vasoconstriction. In contrast, the angiotensin-converting-enzyme-2–angiotensin-(1-7)–Mas axis (Mas-axis) is mediated by the metabolites angiotensin-1-7 (Ang-(1-7)) and angtiotensin-1-5 (Ang-(1-5)) and exerts cardioprotective effects. Methods: We previously investigated the effect of empagliflozin on the systemic haemodynamic in patients with stable CHF (NYHA II–III) in a randomized placebo-controlled clinical trial ‘Analysing the Effect of Empagliflozin on Reduction of Tissue Sodium Content in Patients With Chronic Heart Failure (ELSI)’. In a post hoc analysis, we now analysed whether empagliflozin has an effect on the RAS by measuring detailed RAS profiles (LC-MS/MS-based approach) in 72 patients from ELSI. We compared RAS parameters after 1-month and 3-months treatment with empagliflozin or placebo to baseline. The secondary goal was to analyse whether the effect of empagliflozin on RAS parameters was dependent on angiotensin-receptor-blocking (ARB) or angiotensin-converting-enzyme-inhibitor (ACEI) co-medication. Results: Empagliflozin medication induced a significant rise in Ang-II [68.5 pmol/L (21.3–324.2) vs. 131.5 pmol/L (34.9–564.0), P = 0.001], angiotensin-I (Ang-I) [78.7 pmol/L (21.5–236.6) vs. 125.9 pmol/L (52.6–512.9), P < 0.001], Ang-(1-7) [3.0 pmol/L (3.0–15.0) vs. 10.1 pmol/L (3.0–31.3), P = 0.006], and Ang-(1-5) [5.4 pmol/L (2.0–22.9) vs. 9.9 pmol/L (2.8–36.4), P = 0.004], which was not observed in the placebo group (baseline to 3-months treatment). A significant rise in Ang-II (206.4 pmol/L (64.2–750.6) vs. 568.2 pmol/L (164.7–1616.4), P = 0.001), Ang-(1-7) (3.0 pmol/L (3.0–14.1) vs. 15.0 pmol/L (3.0–31.3), P = 0.017), and Ang-(1-5) [12.2 pmol/L (3.8–46.6) vs. 36.4 pmol/L (11.1–90.7), P = 0.001] under empagliflozin treatment was only seen in the subgroup of patients with ARB co-medication, whereas no change of Ang-II (16.7 pmol/L (2.0–60.8) vs. 26.4 pmol/L (10.7–63.4), P = 0.469), Ang-(1-7) (6.6 pmol/L (3.0–20.7) vs. 10.5 pmol/L (3.0–50.5), P = 0.221), and Ang-(1-5) (2.7 pmol/L (2.0–8.4) vs. 2.8 pmol/L (2.0–6.9), P = 0.851) was observed in patients with empagliflozin that were on ACEI co-medication (baseline to 3-months treatment). Conclusions: Our data indicate that empagliflozin might lead to an activation of both the Ang I–ACE–Ang II receptor axis and the Mas-axis pathway. Activation of the Ang I–ACE–Ang II receptor axis and the protective Mas-axis pathway after initiating treatment with empagliflozin was only seen in patients with ARB co-medication, in contrast to co-medication with ACEI.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Angiotensin profiles; Cardioprotective effects; Chronic heart failure; Empagliflozin; Renin–angiotensin system

An interview with Professor Stephan Achenbach, Chairman ESC Congress Programme Committee 2016-2018 - Achenbach, Stephan (EuroIntervention, 2017)
EVALuna2:33625

ANNOYANCE DUE TO NOISE TRIGGERS VASCULAR CHANGES IN THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, Joanna M.; Striepe, Kristina; Karg, Marina V.; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

A novel human artery model to assess the magnetic accumulation of SPIONs under flow conditions - Janikowska, Agata; Matuszak, Jasmin; Lyer, Stefan; Schreiber, Eveline; Unterweger, Harald; Zaloga, Jan; Groll, Juergen; Alexiou, Christoph; Cicha, Iwona (Scientific Reports, 2017)
Magnetic targeting utilises the properties of superparamagnetic iron oxide nanoparticles (SPIONs) to accumulate particles in specified vasculature regions under an external magnetic field. As the behaviour of circulating particles varies depending on nanoparticle characteristics, magnetic field strength and flow dynamics, we established an improved ex vivo model in order to estimate the magnetic capture of SPIONs in physiological-like settings. We describe here a new, easy to handle ex vivo model of human umbilical artery. Using this model, the magnetic targeting of different types of SPIONs under various external magnetic field gradients and flow conditions was investigated by atomic emission spectroscopy and histology. Among tested particles, SPION-1 with lauric acid shell had the largest capacity to accumulate at the specific artery segment. SPION-2 (lauric acid/albumin-coated) were also successfully targeted, although the observed peak in the iron content under the tip of the magnet was smaller than for SPION-1. In contrast, we did not achieve magnetic accumulation of dextran-coated SPION-3. Taken together, the umbilical artery model constitutes a time- and cost-efficient, 3R-compliant tool to assess magnetic targeting of SPIONs under flow. Our results further imply the possibility of an efficient in vivo targeting of certain types of SPIONs to superficial arteries.
EVALuna2:33177

A novel machine learning-derived radiotranscriptomic signature of perivascular fat improves cardiac risk prediction using coronary CT angiography - Oikonomou, Evangelos K.; Williams, Michelle C.; Kotanidis, Christos P.; Desai, Milind Y.; Antonopoulos, Alexios S.; Thomas, Katharine E.; Thomas, Sheena; Akoumianakis, Ioannis; Fan, Lampson M.; Kesavan, Sujatha; Herdman, Laura; Alashi, Alaa; et al. (European Heart Journal, 2019)
BACKGROUND: Coronary inflammation induces dynamic changes in the balance between water and lipid content in perivascular adipose tissue (PVAT), as captured by perivascular Fat Attenuation Index (FAI) in standard coronary CT angiography (CCTA). However, inflammation is not the only process involved in atherogenesis and we hypothesized that additional radiomic signatures of adverse fibrotic and microvascular PVAT remodelling, may further improve cardiac risk prediction. METHODS AND RESULTS: We present a new artificial intelligence-powered method to predict cardiac risk by analysing the radiomic profile of coronary PVAT, developed and validated in patient cohorts acquired in three different studies. In Study 1, adipose tissue biopsies were obtained from 167 patients undergoing cardiac surgery, and the expression of genes representing inflammation, fibrosis and vascularity was linked with the radiomic features extracted from tissue CT images. Adipose tissue wavelet-transformed mean attenuation (captured by FAI) was the most sensitive radiomic feature in describing tissue inflammation (TNFA expression), while features of radiomic texture were related to adipose tissue fibrosis (COL1A1 expression) and vascularity (CD31 expression). In Study 2, we analysed 1391 coronary PVAT radiomic features in 101 patients who experienced major adverse cardiac events (MACE) within 5 years of having a CCTA and 101 matched controls, training and validating a machine learning (random forest) algorithm (fat radiomic profile, FRP) to discriminate cases from controls (C-statistic 0.77 [95%CI: 0.62-0.93] in the external validation set). The coronary FRP signature was then tested in 1575 consecutive eligible participants in the SCOT-HEART trial, where it significantly improved MACE prediction beyond traditional risk stratification that included risk factors, coronary calcium score, coronary stenosis, and high-risk plaque features on CCTA (Δ[C-statistic] = 0.126, P < 0.001). In Study 3, FRP was significantly higher in 44 patients presenting with acute myocardial infarction compared with 44 matched controls, but unlike FAI, remained unchanged 6 months after the index event, confirming that FRP detects persistent PVAT changes not captured by FAI. CONCLUSION: The CCTA-based radiomic profiling of coronary artery PVAT detects perivascular structural remodelling associated with coronary artery disease, beyond inflammation. A new artificial intelligence (AI)-powered imaging biomarker (FRP) leads to a striking improvement of cardiac risk prediction over and above the current state-of-the-art.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Adipose tissue; Computed tomography; Coronary artery disease; Machine learning; Radiomics; Risk stratification

Answer to the letter of Dr. Bestehorn - Gaede, Luise; Möllmann, Helge (Clinical Research in Cardiology, 2022)
CRIS-Team Scopus Importer:2022-12-02

Anti-HLA alloantibodies of the IgA isotype in re-transplant candidates part II: Correlation with graft survival - Bach, Christian; Heinemann, F. M.; Horn, P. A.; Ziemann, M.; Lachmann, N.; Muehlbacher, A.; Dick, A.; Ender, A.; Thammanichanond, D.; Schaub, S.; Honger, G.; Fischer, G. F.; et al. (International Journal of Immunogenetics, 2018)
We reported previously on the widespread occurrence of anti-HLA alloantibodies of the IgA isotype (anti-HLA IgA) in the sera of solid-organ re-transplantation (re-tx) candidates (Arnold et al., ). Specifically focussing on kidney re-tx patients, we now extended our earlier findings by examining the impact of the presence and donor specificity of anti-HLA IgA on graft survival. We observed frequent concurrence of anti-HLA IgA and anti-HLA IgG in 27% of our multicenter collective of 694 kidney re-tx patients. This subgroup displayed significantly reduced graft survival as evidenced by the median time to first dialysis after transplantation (TTD 77 months) compared to patients carrying either anti-HLA IgG or IgA (TTD 102 and 94 months, respectively). In addition, donor specificity of anti-HLA IgA had a significant negative impact on graft survival (TTD 74 months) in our study. Taken together, our data strongly indicate that presence of anti-HLA IgA, in particular in conjunction with anti-HLA-IgG, in sera of kidney re-tx patients is associated with negative transplantation outcome.
EVALuna2:34168

Anti-inflammatory effects of Danshen on human vascular endothelial cells in culture - Stumpf, Christian; Fan, Quiaoling; Hintermann, Christian; Raaz-Schrauder, Dorette; Kurfuerst, Ingrid; Losert, Sigrid; Pflederer, Wolfgang; Achenbach, Stephan; Daniel, Werner; Garlichs, Christoph (American Journal of Chinese Medicine, 2013)
Inflammation plays a crucial role in the pathophysiology of atherosclerosis. Besides cytokines, chemokines and cell adhesion molecules, CD40 and P-selectin play important roles as key regulators of the inflammatory process in atherosclerosis. Danshen (DS) is commonly used in traditional Chinese medicine for therapy of cardiovascular diseases such as coronary artery disease. The aim of the present study was to evaluate the protective effects of DS with respect to possible anti-inflammatory effects. Human umbilical vein endothelial cells as well as platelets were incubated with an extract of DS or one of its major ingredients salvianolic acid B (Sal B), tanshinone IIA (Tansh) and protocatechuic acid (Protoc) under tumor necrosis factor (TNF)-α or ADP stimulation. Expression of CD40 and cellular adhesion molecules (VCAM-1/ICAM-1) were assessed via flow cytometry. Levels of interleukin (IL)-6, IL-8, monocyte-chemoattractant-protein (MCP)-1 as well as soluble VCAM1 and ICAM-1 in the supernatants were examined via luminex based analysis. Treatment with DS attenuated TNF-α induced expression of CD40. Furthermore, the expression of VCAM-1 and ICAM-1 as well as the release of soluble VCAM-1 and ICAM-1 were downregulated. In the cell supernatants we also observed a significant reduction of IL-6, IL8 and MCP-1. DS and its major ingredients, Sal B and Protoc, significantly inhibited TNF-induced expression and release of adhesion molecules, cytokines and chemokines as well as ADP-induced expression of platelet P-selectin. Because of the key roles of inflammatory mediators in the etiology of atherosclerosis, this work provides useful insight in understanding the pharmacological efficacy of Chinese herbal medicine. © 2013 World Scientific Publishing Company Institute for Advanced Research in Asian Science and Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adhesion Molecules; Cytokines; Danshen; Endothelial Cells

Aortic annulus eccentricity before and after transcatheter aortic valve implantation: Comparison of balloon-expandable and self-expanding prostheses - Schuhbaeck, Annika; Weingartner, Christina; Schmid, Jasmin; Pflederer, Tobias; Rixe, Johannes; Nef, Holger; Schneider, Christian; Lell, Michael; Uder, Michael; Ensminger, Stephan; Feyrer, Richard; Weyand, Michael; et al. (European Journal of Radiology, 2015)
The geometry of the aortic annulus and implanted transcatheter aortic valve prosthesis might influence valve function. We investigated the influence of valve type and aortic valve calcification on post-implant geometry of catheter-based aortic valve prostheses.Eighty consecutive patients with severe aortic valve stenosis (mean age 82 ± 6 years) underwent computed tomography before and after TAVI. Aortic annulus diameters were determined. Influence of prosthesis type and degree of aortic valve calcification on post-implant eccentricity were analysed.Aortic annulus eccentricity was reduced in patients after TAVI (0.21 ± 0.06 vs. 0.08 ± 0.06, p<0.0001). Post-TAVI eccentricity was significantly lower in 65 patients following implantation of a balloon-expandable prosthesis as compared to 15 patients who received a self-expanding prosthesis (0.06 ± 0.05 vs. 0.15 ± 0.07, p<0.0001), even though the extent of aortic valve calcification was not different. After TAVI, patients with a higher calcium amount retained a significantly higher eccentricity compared to patients with lower amounts of calcium.Patients undergoing TAVI with a balloon-expandable prosthesis show a more circular shape of the implanted prosthesis as compared to patients with a self-expanding prosthesis. Eccentricity of the deployed prosthesis is affected by the extent of aortic valve calcification.
EVALuna2:12030

Aortic valve replacement in Germany in 2019 - Gaede, Luise; Blumenstein, Johannes; Husser, Oliver; Liebetrau, Christoph; Doerr, Oliver; Grothusen, Christina; Eckel, Clemens; Al-Terki, Hani; Kim, Won-Keun; Nef, Holger; Tesche, Christian; Hamm, Christian W.; et al. (Clinical Research in Cardiology, 2021)
Aims: Both surgical aortic valve replacement (SAVR) and transcatheter aortic valve implantation (TAVI) are established options to treat aortic valve stenosis. We present the outcome of the complete cohort of all patients undergoing SAVR or TAVI in Germany during the calendar year 2019. Methods and results: Data concerning all isolated aortic valve procedures performed in Germany in 2019 were retrieved from the mandatory nationwide quality control program: 22,973 transvascular (TV)-TAVI procedures, 7905 isolated SAVR (iSAVR), and 1413 transapical (TA)-TAVI. Data was complete in 99.9% (n = 32,156). In-hospital mortality after TV-TAVI (2.3%) was significantly lower when compared with iSAVR (2.8%, p = 0.007) or TA-TAVI (6.3%; p < 0.001). Expected mortality was calculated with a new version of the German Aortic valve score (AKL Score) based on the data of either catheter-based (AKL-CATH) or surgical (AKL-CHIR) aortic valve replacements in Germany in 2018. TV-TAVI and iSAVR both showed lower observed mortality in 2019 than expected based on their respective performance in 2018, yielding an observed/expected (O/E) mortality ratio < 1. This was particularly apparent for patients at low risk. After exclusion of emergency procedures, in-hospital mortality after TV-TAVI (2.1%) and after iSAVR (2.1%) was identical, even though patients undergoing TV-TAVI showed a considerably higher perioperative risk profile. Conclusion: After excluding emergency procedures, in-hospital mortality of TV-TAVI and iSAVR in 2019 in Germany was identical. In 2019, TV-TAVI and iSAVR both show lower matched mortality ratios compared with 2018, which suggests technical improvements of both therapies. Graphical abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-01-15
Keywords: Mortality; Real world; Registry; SAVR; TAVI; TAVR

Aortic valve stenosis: computed tomography prior to transcatheter aortic valve implantation (TAVI). How can the outcome be improved? - Hell, M.; Achenbach, Susanne; Arnold, Martin (Herz, 2015)
Computed tomography (CT) plays an important role in the preinterventional work-up of patients referred for transcatheter aortic valve implantation (TAVI). Contrast-enhanced CT allows a comprehensive examination with evaluation of both the vascular access route as well as aortic valve and aortic root geometry. Analysis of the minimum luminal vessel diameter, tortuosity and vascular calcification are important to determine the ability to perform the procedure via a transfemoral access. The size of the aortic annulus can be accurately measured by CT to aid selection of the appropriate prosthesis and the use of CT for prosthesis sizing has been associated with a decreased incidence of paravalvular leakage as compared to 2-dimensional echocardiography. In addition CT permits accurate assessment of aortic root anatomy, distance between coronary ostia and the annulus plane as well as the dimensions of the ascending aorta. Furthermore, suitable fluoroscopic projections that permit an exact orthogonal visualization of the aortic annulus plane by fluoroscopy during the procedure can be extracted from the CT data set. In summary, CT permits comprehensive imaging in TAVI candidates and optimizes procedural outcome.
EVALuna2:12072

Applicability and procedural success rate of bioresorbable-vascular scaffolds for percutaneous coronary intervention in an all-comer cohort of 383 consecutive patients - Schlundt, Christian; Achenbach, Stephan; Felten, Fabiola; Röther, Jens; Nef, Holger; Ludwig, Josef; Tröbs, Monique; Marwan, Mohamed (Acta Cardiologica, 2017)
Objectives The purpose of this study was to determine applicability and procedural success of bioresorbable vascular scaffolds (BVS) for percutaneous coronary intervention (PCI) in an all-comer cohort. Background BVS use in bifurcations and severely calcified lesions is not recommended, and a relatively large crossing profile may cause limitations. It is has never been studied how widely BVS can be applied in all-comer cohorts. Methods In 383 consecutive patients (acute coronary syndrome: 124, stable coronary disease 259), a BVS (Absorb) was used as first-line device unless any of the following contraindications were present: bifurcation with side branch >2.0 mm, reference diameter <2.5 mm or >4.0 mm, required device length <12 mm, in-stent stenosis, or contraindications to 6 months of DAPT. Patients and lesions were evaluated regarding suitability for BVS treatment, procedural success (successful BVS placement and residual stenosis <30%), and outcome. Results Of 588 lesions, 303 (52%) were unsuitable for BVS placement due to presence of a bifurcation (30% of unsuitable lesions), reference -diameter >4.0 mm (13%) or <2.5 mm (12%), contraindication to 6 months DAPT (13%), in-stent stenosis (14%), and desired device length <12 mm (4%). If BVS use was attempted, procedural success with a scaffold was 95% (271/285). Crossing failure occurred in 14 cases (5%), affected lesions were significantly more calcified. After a mean follow-up period of 259 days, definite/probable scaffold thrombosis occurred in 1.1% of patients. Conclusions Approximately one-half of lesions in an all-comer population can successfully be treated with BVS. Crossing failure is rare.
EVALuna2:33655

APPLICATION OF A CENTRAL ILIAC ARTERIOVENOUS COUPLER DEVICE IN SEVERE TREATMENT-RESISTANT ARTERIAL HYPERTENSION: A FOUR-YEAR FOLLOW-UP - Jung, Susan; Ott, Christian; Karg, M.; Bosch, A.; Schmid, M.; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (2018)
EVALuna2:35985

Application of a central iliac arteriovenous coupler device in severe treatment-resistant hypertension: a 3.5-year follow-up - Jung, Susanne; Ott, Christian; Karg, Marina V.; Bosch, Agnes; Schmid, Michael; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2018)
OBJECTIVE: In patients with resistant hypertension, percutaneous placement of an iliac arteriovenous coupler device leads to a reduction of blood pressure (BP) via decreased total vascular resistance and improved arterial compliance. However, long-term efficacy and safety need to be further explored. We report on the first case of 3.5-year follow-up in a patient who underwent implantation of an iliac arteriovenous coupler device. RESULTS: A patient with resistant hypertension was admitted to hospital. Despite treatment with six anti-hypertensive drugs, his BP was poorly controlled. Previously, he had undergone renal denervation, which did not cause a significant BP decrease. Therefore, an arteriovenous coupler device was implanted, leading to an immediate and significant BP decrease. The patient was discharged with an office BP of 122/71 mmHg. After 3 months, there was a sustained BP decrease (-14/9 mmHg), whereas later, it was fluctuant (office BP: 147-173/85-95 mmHg, ABPM: 153-166/81-94 mmHg) probably due to medication non-adherence confirmed by a urinary toxicological screening test. Follow-up right heart catheterization showed changes in hemodynamic parameters related to volume congestion, which were accompanied by progressive dyspnea and weight gain. This was controlled by an optimized diuretic therapy. Additionally, an invasive closure maneuver was performed, leading to an immediate BP increase after closure and a similar decrease after re-opening of the anastomosis, verifying its proper long-term function. CONCLUSION: The implantation of an iliac arteriovenous coupler device appears to be a promising and effective method to decrease BP and therefore reduce cardiovascular risk in patients with severe, treatment-resistant hypertension.
EVALuna2:34505

Appropriateness criteria for cardiovascular imaging use in clinical practice: a position statement of the ESC/EACVI taskforce - Garbi, Madalina; Habib, Gilbert; Plein, Sven; Neglia, Danilo; Kitsiou, Anastasia; Donal, Erwan; Pinto, Fausto; Bax, Jeroen; Achenbach, Stephan; Popescu, Bogdan A.; Edvardsen, Thor; Badano, Luigi P.; et al. (European Heart Journal - Cardiovascular Imaging, 2014)
There is a growing interest from the scientific community in the appropriate use of cardiovascular imaging techniques for diagnosis and decision making in Europe. To develop appropriateness criteria for cardiovascular imaging use in clinical practice in Europe, a dedicated taskforce has been appointed by the European Society of Cardiology (ESC) and the European Association of Cardiovascular Imaging (EACVI). The present paper describes the appropriateness criteria development process.
EVALuna2:11995

A Print-and-Fuse Strategy for Sacrificial Filaments Enables Biomimetically Structured Perfusable Microvascular Networks with Functional Endothelium Inside 3D Hydrogels - Ryma, Matthias; Genc, Hatice; Nadernezhad, Ali; Paulus, Ilona; Schneidereit, Dominik; Friedrich, Oliver; Andelovic, Kristina; Lyer, Stefan; Alexiou, Christoph; Cicha, Iwona; Groll, Juergen (Advanced Materials, 2022)
A facile and flexible approach for the integration of biomimetically branched microvasculature within bulk hydrogels is presented. For this, sacrificial scaffolds of thermoresponsive poly(2-cyclopropyl-2-oxazoline) (PcycloPrOx) are created using melt electrowriting (MEW) in an optimized and predictable way and subsequently placed into a customized bioreactor system, which is then filled with a hydrogel precursor solution. The aqueous environment above the lower critical solution temperature (LCST) of PcycloPrOx at 25 degrees C swells the polymer without dissolving it, resulting in fusion of filaments that are deposited onto each other (print-and-fuse approach). Accordingly, an adequate printing pathway design results in generating physiological-like branchings and channel volumes that approximate Murray's law in the geometrical ratio between parent and daughter vessels. After gel formation, a temperature decrease below the LCST produces interconnected microchannels with distinct inlet and outlet regions. Initial placement of the sacrificial scaffolds in the bioreactors in a pre-defined manner directly yields perfusable structures via leakage-free fluid connections in a reproducible one-step procedure. Using this approach, rapid formation of a tight and biologically functional endothelial layer, as assessed not only through fluorescent dye diffusion, but also by tumor necrosis factor alpha (TNF-alpha) stimulation, is obtained within three days.
CRIS-Team WoS Importer:2022-06-17

A randomized controlled trial of the effect of spironolactone on left ventricular mass in hemodialysis patients - Hammer, Fabian; Malzahn, Uwe; Donhauser, Julian; Betz, Christoph; Schneider, Markus; Grupp, Clemens; Pollak, Nils; Störk, Stefan; Wanner, Christoph; Krane, Vera; Berweck, Susanne; Biggar, Patrick; et al. (Kidney International, 2019)
Mineralocorticoid receptor antagonists have beneficial effects on left ventricular remodeling, cardiac fibrosis, and arrhythmia in heart failure, but efficacy and safety in dialysis patients is less clear. We evaluated the effect of spironolactone on left ventricular mass (LVM), an independent predictor of all-cause and cardiovascular mortality, in hemodialysis patients. In this placebo-controlled, parallel-group trial, 97 hemodialysis patients (23% female; mean age 60.3 years) were randomized to spironolactone 50 mg once daily (n=50) or placebo (n=47). The primary efficacy endpoint was change in LVM index (LVMi) from baseline to 40 weeks as determined by cardiac magnetic resonance imaging. Safety endpoints were development of hyperkalemia and change in residual renal function. There was no significant change in LVMi in participants randomized to spironolactone compared to placebo (-2.86±11.87 vs. 0.41±10.84 g/m2). There was also no difference in the secondary outcomes of mean 24-hour systolic or diastolic ambulatory blood pressure, left ventricular ejection fraction, 6-minute walk test distance, or New York Heart Association functional class. Moderate hyperkalemia (pre-dialysis potassium levels of 6.0-6.5 mmol/L) was more frequent with spironolactone treatment (155 vs. 80 events), but severe hyperkalemia (≥6.5 mmol/L) was not (14 vs. 24 events). Changes in residual urine volume and measured glomerular filtration rate did not differ between groups. There were no deaths in the spironolactone group and 4 deaths in the placebo group. Thus, treatment with 50 mg spironolactone did not change left ventricular mass index, cardiac function, or blood pressure in hemodialysis patients. Spironolactone increased the frequency of moderate hyperkalemia, but did not increase severe hyperkalemia.
EVALuna2:36276

Arbeitsanweisung in Herzkatheterlabor und Hybridoperationssaal - Schächinger, V.; Nef, H.; Achenbach, Susanne; Butter, C.; Deisenhofer, I.; Eckardt, L.; Eggebrecht, H.; Kuon, E.; Levenson, B.; Linke, A.; Madlener, K.; Mudra, H.; et al. (Der Kardiologe, 2015)
According to the German Radiation Act §18 (2) (Röntgenverordnung) every radiation facility administering radiation to humans has to provide written working instructions for those examinations and treatment procedures which are frequently performed. This is also valid for catheterization laboratories and hybrid operating rooms. It is the duty of the radiation protection officer (Strahlenschutzbeauftragte), a person who has to be appointed by German law (§15 Abs. 2 Nr. 1 Röntgenverordnung) to formulate and implement the working instructions. The current manuscript is a template to create such working instructions, which fulfill the legal requirements.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac catheterization; Hybrid operating room; Radiation act; Radiation protection; Work instruction

Arrhythmia classification using RR intervals: Improvement with sinusoidal regression feature - Leutheuser, Heike; Tobola, Andreas; Anneken, Lars; Gradl, Stefan; Lang, Nadine; Achenbach, Stephan; Eskofier, Björn; Arnold, Martin (12th International Conference on Wearable and Implantable Body Sensor Networks (BSN), 2015)
Far too many people are dying from stroke or other heart related diseases each year. Early detection of abnormal heart rhythm could trigger the timely presentation to the emergency department or outpatient unit. Smartphones are an integral part of everyone;s life and they form the ideal basis for mobile monitoring and real-time analysis of signals related to the human heart. In this work, we investigated the performance of arrhythmia classification systems using only features calculated from the time instances of individual heart beats. We built a sinusoidal model using N (N = 10, 15, 20) consecutive RR intervals to predict the (N+1)th RR interval. The integration of the innovative sinusoidal regression feature, together with the amplitude and phase of the proposed sinusoidal model, led to an increase in the mean class-dependent classification accuracies. Best mean class-dependent classification accuracies of 90% were achieved using a Naïve Bayes classifier. Well-performing realtime analysis arrhythmia classification algorithms using only the time instances of individual heart beats could have a tremendous impact in reducing healthcare costs and reducing the high number of deaths related to cardiovascular diseases.

Artificial Intelligence-based quantification of atherosclerotic plaque and stenosis from coronary computed tomography angiography using a novel method - Lin, Andrew; Manral, Nipun; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Park, Caroline; Doris, Mhairi; Kwan, Alan; et al. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2022)
Background: Coronary computed tomography angiography (CCTA) allows non-invasive assessment of luminal stenosis and coronary atherosclerotic plaque. We aimed to develop and externally validate an artificial intelligence-based deep learning (DL) network for CCTA-based measures of plaque volume and stenosis severity. Methods: This was an international multicenter study of 1,183 patients undergoing CCTA at 11 sites. A novel DL convolutional neural network was trained to segment coronary plaque in 921 patients (5,045 lesions). The DL architecture consisted of a novel hierarchical convolutional long short-term memory (ConvLSTM) Network. The training set was further split temporally into training (80%) and internal validation (20%) datasets. Each coronary lesion was assessed in a 3D slab about the vessel centrelines. Following training and internal validation, the model was applied to an independent test set of 262 patients (1,469 lesions), which included an external validation cohort of 162 patients Results: In the test set, there was excellent agreement between DL and clinician expert reader measurements of total plaque volume (intraclass correlation coefficient [ICC] 0.964) and percent diameter stenosis (ICC 0.879; both p<0.001, see tables and figure). The average per-patient DL plaque analysis time was 5.7 seconds versus 25-30 minutes taken by experts. There was significantly higher overlap measured by the Dice coefficient (DC) for ConvLSTM compared to UNet (DC for vessel 0.94 vs 0.83, p<0.0001; DC for lumen and plaque 0.90 vs 0.83, p<0.0001) or DeepLabv3 (DC for vessel both 0.94; DC for lumen and plaque 0.89 vs 0.84, p<0.0001). Conclusions: A novel externally validated artificial intelligence-based network provides rapid measurements of plaque volume and stenosis severity from CCTA which agree closely with clinician expert readers.
CRIS-Team Scopus Importer:2022-06-10
Keywords: artificial intelligence; atherosclerosis; coronary computed tomography angiography; deep learning

Aspirin and Statin Therapy for Nonobstructive Coronary Artery Disease: Five-yearOutcomes from the CONFIRM Registry - Indraratna, Praveen; Naoum, Christopher; Zekry, Sagit Ben; Gransar, Heidi; Blanke, Philipp; Sellers, Stephanie; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; et al. (Radiology: Cardiothoracic Imaging, 2022)
Purpose: In this cohort study, 5-year data from the Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry (ie, CONFIRM) were examined to identify associations of baseline aspirin and statin use with mortality, major adverse cardiovascular events (MACE), and myocardial infarction (MI) in individuals without substantial (>50%) stenosis. Materials and Methods: In this prospective cohort study, all participants in the registry underwent coronary CT angiography and were classified as having no detectable coronary plaque or having nonobstructive coronary artery disease (CAD) (1%—49% stenosis). Participants with obstructive (>50%) stenosis were excluded from analysis. The study commenced in June 2003 and was completed in March 2016. All unadjusted and risk-adjusted analyses utilized the Cox proportional hazard model with hospital sites modeled using shared frailty. Results: A total of 6386 participants with no detectable plaque or with nonobstructive CAD were included (mean age, 56.0 years 6 13.3 [SD], 52% men). The mean follow-up period was 5.66 years 6 1.10. Nonobstructive CAD (n = 2815, 44% of all participants included in the study) was associated with a greater risk of all-cause mortality (10.6% [298 of 2815] vs 4.8% [170 of 3571], P <.001) compared to those without CAD (n = 3571, 56%). Baseline aspirin and statin use was documented for 1415 and 1429 participants, respectively, with nonobstructive CAD, and for 1560 and 1565 participants without detectable plaque, respectively. In individuals with nonobstructive CAD, baseline aspirin use was not associated with a reduction in MACE (10.9% [102 of 936] vs 14.7% [52 of 355], P =.06), all-cause mortality (9.6% [95 of 991] vs 10.9% [46 of424], P =.468), or MI (4.4% [41 of 936] vs 6.2% [22 of 355], P =.18). On multivariate risk-adjusted analysis, baseline statin use was associated with a lower rate of MACE (hazard ratio, 0.59; 95% CI: 0.40, 0. 87; P =.007). Neither therapy improved clinical outcomes for participants with no detectable plaque. Conclusion: In participants with nonobstructive CAD, baseline use of statins, but not of aspirin, was associated with improved clinical outcomes. Neither therapy was associated with benefit in participants without plaque. Clinical trial registration no. NCT01443637 Supplemental material is available for this article.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Aspirin; Coronary Artery Disease; CT Angiography; Nonob-structive Coronary Artery Disease; Statin

Assessment of cavopulmonary connections by advanced imaging: Value of flat-detector computed tomography - Glöckler, Martin; Koch, Andreas; Halbfass, Julia; Greim, Verena; Rueffer, Andre; Cesnjevar, Robert; Achenbach, Stephan; Dittrich, Sven (Cardiology in the Young, 2013)
Objectives To investigate the impact of flat-detector computed tomography on the clinical assessment of patients with cavopulmonary connections, and to evaluate the obtained diagnostic accuracy and supplementary information, as well as the value of overlaid three-dimensional reconstructions on fluoroscopic images during catheter-based interventions. Methods We analysed 31 consecutive patients retrospectively in whom flat-detector computed tomography was used to visualise the cavopulmonary connection. We investigated patients with cavopulmonary connections either early post-operatively (first group), before converting to a total cavopulmonary connection (second group), and patients with failing total cavopulmonary connection (third group). Flat-detector computed tomography based on a single rotational angiography was used to create a three-dimensional vascular model. The clinical value of flat-detector computed tomography was evaluated using standard categories of diagnostic utility. Used contrast volume and radiation exposure were quantified. Results Within 18 months, flat-detector computed tomography was performed in 31 cases with cavopulmonary connections. The median age was 1.9 years (range 0.3-43 years). In the first group, we found anomalies in 4 out of 8 cases, which led to therapeutic or prophylactic procedures; in the second and third groups, we performed interventions in 14 out of 23 cases. The overall clinical value was always rated superior to conventional biplane angiography. The median dose area product was 91.8 microgray square metres (range 33.0-679.3 microgray square metres). The required contrast medium was 2.08 millilitres per kilogram (range 0.66-4.7 millilitres per kilogram). Conclusion Flat-detector computed tomography improves the diagnostic accuracy in cavopulmonary connections and provides additional diagnostic information, which may lead to therapeutic or prophylactic procedures. Overlaid three-dimensional images on fluoroscopy facilitate and provide security for interventions. © Cambridge University Press 2012.
CRIS-Team Scopus Importer:2023-03-08
Keywords: interventions in congenital heart disease; rotational angiography; Three-dimensional

Assessment of edema using STIR+ via 3D cardiovascular magnetic resonance imaging in patients with suspected myocarditis - Jeserich, Michael; Merkely, Bela; Schlosser, Pascal; Kimmel, Simone; Pavlik, Gabor; Achenbach, Stephan (Magnetic Resonance Materials in Physics Biology and Medicine, 2017)
OBJECTIVE: To evaluate three-dimensional T2-weighted fast spin echo triple inversion recovery sequences (STIR+) for the diagnosis of myocardial edema in patients with suspected early myocarditis after respiratory or gastrointestinal tract viral infection and at follow-up. MATERIALS AND METHODS: We prospectively examined 28 patients with suspected myocarditis and 37 controls matched for gender and age. An ECG-triggered STIR+ was used to cover the entire left ventricle in short-axis images with 10-mm slice thickness and no interslice gap. The global signal intensity ratio (heart muscle in relation to skeletal muscle) was calculated (global STIR+ ratio) to evaluate edema. All patients had repeat examinations at follow-up (mean interval 4.9 months, 1-12 months). RESULTS: The mean global STIR+ ratio was 2.15 ± 0.4 in the initial examination of patients as compared to 1.78 ± 0.3 in controls (p < 0.0001) and 1.89 ± 0.3 in patients at follow-up (p = 0.0001 vs. first visit). Left ventricular ejection fraction did not differ between patients and controls at baseline and at follow-up. CONCLUSION: We could identify a significantly higher global STIR+ ratio in patients with suspected myocarditis compared to controls, and a dynamic change during follow-up. The global STIR+ ratio may, therefore, be useful for the diagnosis of myocarditis and should be further explored.
EVALuna2:33639

Association of a coding polymorphism in Fc gamma receptor 2A and graft survival in re-transplant candidates - Fuernrohr, Barbara G.; Weiss, Katrin M.; Harre, Ulrike; Wiesener, Michael S.; Spriewald, Bernd M.; Arnold, Martin (Human Immunology, 2015)
The family of Fc gamma receptors (Fc?Rs) is involved in mediating immunological effector functions. Fc?Rs are differentially expressed on immune cells and can act either activating or inhibitory, with Fc?R2A belonging to the first group. The polymorphism H131R (rs1801274) in FCGR2A has been associated with acute rejection and can shift the overall balance between activating and inhibitory Fc?Rs. Anti-HLA allo-antibodies in transplant recipients have been identified as risk factor for organ survival after transplantation. In this study we genotyped FCGR2A H131R in 200 patients who had undergone kidney transplantation and experienced loss of graft function. FCGR2A polymorphism was related to graft survival and anti-HLA antibodies. Graft survival was calculated as the time interval between transplantation and return to chronic dialysis after transplantation. The gene frequency of FCGR2A R/R131 was found significantly more often in patients with earlier (?60months) compared to patients with later (>60months) graft failure. Overall patients homozygous for R/R131 had a significantly shorter graft survival, compared to H/H131 or H/R131 which is even more pronounced, when anti-HLA antibodies were present. These data suggest, that FCGR2A polymorphisms constitute a risk factor for graft loss following kidney transplantation and that this effect is related to anti-HLA antibodie
EVALuna2:3812

Association of CRP receptor polymorphisms with culprit lesion morphology in patients with acute myocardial infarction as first manifestation of coronary artery disease - Raaz-Schrauder, Dorette; Klinghammer, Lutz; Lichtenstern, David; Schlundt, Christian; Achenbach, Stephan (2017)
EVALuna2:36024

Association of Hepatic Steatosis With Major Adverse Cardiovascular Events, Independent of Coronary Artery Disease - Meyersohn, Nandini M.; Mayrhofer, Thomas; Corey, Kathleen E.; Bittner, Daniel O.; Staziaki, Pedro V.; Szilveszter, Balint; Hallett, Travis; Lu, Michael T.; Puchner, Stefan B.; Simon, Tracey G.; Foldyna, Borek; Voora, Deepak; et al. (Clinical Gastroenterology and Hepatology, 2021)
Background & Aims: Hepatic steatosis has been associated with increased risk of major adverse cardiovascular events (MACE) but it is not clear whether steatosis is independently associated with risk of MACE. We investigated whether steatosis is associated with risk of MACE independently of the presence and extent of baseline coronary artery disease, assessed by comprehensive contrast-enhanced computed tomography angiography (CTA). Methods: We conducted a nested cohort study of 3756 subjects (mean age, 60.6 years; 48.4% men) who underwent coronary CTA at 193 sites in North America, from July 2010 through September 2013, as part of the PROMISE study, which included noninvasive cardiovascular analyses of symptomatic outpatients without coronary artery disease. Independent core laboratory readers measured hepatic and splenic attenuation, using non-contrast computed tomography images to identify steatosis, and evaluated coronary plaques and stenosis in coronary CTA images. We collected data on participants’ cardiovascular risk factors, presence of metabolic syndrome, and body mass index. The primary endpoint was an adjudicated composite of MACE (death, myocardial infarction, or unstable angina) during a median follow-up time of 25 months. Results: Among the 959 subjects who had steatosis (25.5% of the cohort), 42 had MACE (4.4%), whereas among the 2797 subjects without steatosis, 73 had MACE (2.6%) (hazard ratio [HR] for MACE in subjects with steatosis, 1.69; 95% CI, 1.16–2.48; P = .006 for MACE in subjects with vs without steatosis). This association remained after adjustment for atherosclerotic cardiovascular disease risk scores, significant stenosis, and metabolic syndrome (adjusted HR, 1.72; 95% CI, 1.16–2.54; P = .007) or obesity (adjusted HR, 1.75; 95% CI, 1.19–2.59; P = .005). Steatosis remained independently associated with MACE after adjustment for all CTA measures of plaques and stenosis. Conclusions: Hepatic steatosis is associated with MACE independently of other cardiovascular risk factors or extent of coronary artery disease. Strategies to reduce steatosis might reduce risk of MACE. ClinicalTrials.gov no: NCT01174550
CRIS-Team Scopus Importer:2021-06-25
Keywords: CT; Heart Disease; MAFLD; NAFLD

Association of Metabolic Phenotypes With Coronary Artery Disease and Cardiovascular Events in Patients With Stable Chest Pain - Kammerlander, Andreas A.; Mayrhofer, Thomas; Ferencik, Maros; Pagidipati, Neha J.; Karady, Julia; Ginsburg, Geoffrey S.; Lu, Michael T.; Bittner, Daniel O.; Puchner, Stefan B.; Bihlmeyer, Nathan A.; Meyersohn, Nandini M.; Emami, Hamed; et al. (Diabetes Care, 2021)
OBJECTIVE Obesity and metabolic syndrome are associated with major adverse cardiovascular events (MACE). However, whether distinct metabolic phenotypes differ in risk for coronary artery disease (CAD) and MACE is unknown. We sought to determine the association of distinct metabolic phenotypes with CAD and MACE. RESEARCH DESIGN AND METHODS We included patients from the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) who underwent coronary computed tomography (CT) angiography. Obesity was defined as a BMI >= 30 kg/m(2) and metabolically healthy as less than or equal to one metabolic syndrome component except diabetes, distinguishing four metabolic phenotypes: metabolically healthy/unhealthy and nonobese/obese (MHN, MHO, MUN, and MUO). Differences in severe calcification (coronary artery calcification [CAC] >= 400), severe CAD (>= 70% stenosis), high-risk plaque (HRP), and MACE were assessed using adjusted logistic and Cox regression models. RESULTS Of 4,381 patients (48.4% male, 60.5 +/- 8.1 years of age), 49.4% were metabolically healthy (30.7% MHN and 18.7% MHO) and 50.6% unhealthy (22.3% MUN and 28.4% MUO). MHO had similar coronary CT findings as compared with MHN (severe CAC/CAD and HRP; P > 0.36 for all). Among metabolically unhealthy patients, those with obesity had similar CT findings as compared with nonobese (P > 0.10 for all). However, both MUN and MUO had unfavorable CAD characteristics as compared with MHN (P <= 0.017 for all). A total of 130 events occurred during follow-up (median 26 months). Compared with MHN, MUN (hazard ratio [HR] 1.61 [95% CI 1.02-2.53]) but not MHO (HR 1.06 [0.62-1.82]) or MUO (HR 1.06 [0.66-1.72]) had higher risk for MACE. CONCLUSIONS In patients with stable chest pain, four metabolic phenotypes exhibit distinctly different CAD characteristics and risk for MACE. Individuals who are metabolically unhealthy despite not being obese were at highest risk in our cohort.
CRIS-Team WoS Importer:2021-04-09

Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Kannenkeril, Dennis; Jung, Susanne; Ott, Christian; Striepe, Kristina; Kolwelter, Julie; Schmieder, Roland; Bosch, Agnes (Kidney & Blood Pressure Research, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 +/- 106 vs. 663 +/- 124 mL/min, p = 0.009), lower renal blood flow (1,068 +/- 203 vs. 1,172 +/- 225 mL/min, p = 0.047), higher filtration fraction (22.7 +/- 3.3 vs. 21.3 +/- 3.0, p = 0.012), higher renal vascular resistance (88.9 +/- 25.6 vs. 75.8 +/- 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 +/- 1,253.4 vs. 1,849.9 +/- 1,242.0 dyn s(-1) cm(-5), p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 +/- 11.8 vs. 138 +/- 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 +/- 472.2 vs. 2,245.8 +/- 370.3 dyn s(-1) cm(-5), p = 0.060), and intraglomerular pressure (64.0 +/- 3.1 vs. 64.6 +/- 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.
CRIS-Team WoS Importer:2021-05-14

Association of Plaque Location and Vessel Geometry Determined by Coronary Computed Tomographic Angiography With Future Acute Coronary Syndrome-Causing Culprit Lesions - Han, Donghee; Lin, Andrew; Kuronuma, Keiichiro; Tzolos, Evangelos; Kwan, Alan C.; Klein, Eyal; Andreini, Daniele; Bax, Jeroen J.; Cademartiri, Filippo; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Conte, Edoardo; et al. (JAMA Cardiology, 2022)
IMPORTANCE Distinct plaque locations and vessel geometric features predispose to altered coronary flow hemodynamics. The association between these lesion-level characteristics assessed by coronary computed tomographic angiography (CCTA) and risk of future acute coronary syndrome (ACS) is unknown.
CRIS-Team WoS Importer:2022-02-11

Association of systemic inflammation markers with the presence and extent of coronary artery calcification - Raaz-Schrauder, Dorette; Klinghammer, Lutz; Baum, Christina; Frank, Thomas; Lewczuk, Piotr; Achenbach, Stephan; Cicha, Iwona; Stumpf, Christian; Wiltfang, Jens; Kornhuber, Johannes; Daniel, Werner; Garlichs, Christoph (Cytokine, 2012)
Background: Coronary artery calcification (CAC) is a marker for the presence and extent of coronary atherosclerotic plaques and can be detected non-invasively by multi-detector row CT (MDCT). Well known predictors of CAC are age, gender, and the classical atherogenic risk factors. CAC is associated with atherosclerotic plaque burden, but it is still elusive if atherosclerosis-relevant cytokines and chemokines are also associated with CAC. Methods: We conducted a clinical study among 455 consecutive individuals who underwent coronary calcium assessment performed by MDCT. Before MDCT, blood was drawn and subsequently analyzed for 20 different atherosclerosis-relevant cytokines and chemokines using a Luminex-laser-based fluorescence analysis. Results: Using univariate analyses, CAC patients revealed significantly higher levels of the chemokines IP-10 (P=0.047) and eotaxin (P=0.031) as compared to non-CAC patients. In multivariate analyses using common thresholds for calcium burden, the three cytokines interleukin-6 (P=0.028), interleukin-8 (P=0.009), and interleukin-13 (P=0.024) were associated with high coronary calcium levels after adjustment for classical variables and risk factors. Conclusions: In a large group of individuals with atypical chest pain and a low to intermediate likelihood for coronary artery disease elevated plasma levels of IL-6 and reduced levels of IL-8 and IL-13 were predictive for distinct coronary artery calcification. These findings support a specific role of these cytokines in coronary calcification. © 2011 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Cardiac computed tomography; Coronary calcification; Cytokines; Inflammation

Association of systemic inflammation with epicardial fat and coronary artery calcification - Gauss, Soeren; Klinghammer, Lutz; Steinhoff, Alina; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph D.; Marwan, Mohamed (Inflammation Research, 2015)
Increased epicardial fat volume (EFV) has been shown to be associated with coronary atherosclerosis. While it is postulated to be an independent risk factor, a possible mechanism is local or systemic inflammation. We analyzed the relationship between coronary atherosclerosis, quantified by coronary calcium in CT, epicardial fat volume and systemic inflammation.Using non-enhanced dual-source CT, we quantified epicardial fat volume (EFV) and coronary artery calcium (CAC) in 391 patients who underwent coronary computed tomography for suspected coronary artery disease. In addition to traditional risk factors, serum markers of systemic inflammation were measured (IL-1?, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10,IL-12, IL-13, IL-15, IL-17, IFN-?, TNF-?, hs-CRP, GM-CS, G-CSF, MCP-1, MIP-1, Eotaxin and IP-10). In 94 patients follow-up data were obtained after 1.9 ± 0.5 years.The 391 patients had a mean age of 60 ± 10 years, and 69 % were males. Mean EFV was 116 ± 50 mL. Median CAC was 12 (IQR 0; 152). CAC and EFV showed a significant correlation (? = 0.37; P < 0.001). EFV and CAC were significantly correlated with the traditional risk factors like age, male gender, diabetes, smoking and hypertension. With regard to biomarkers, CAC was significantly associated (negatively) to G-CSF and IL-13. EFV (median binned) was significantly associated (positively) with IP-10 (P = 0.002) and MCP-1 (? = 0.037). In follow-up, EFV showed a mean annualized progression of 6 mL (IQR 3; 9) (P < 0.001); CAC progressed by a mean of six Agatston Units (IQR 0; 30). The progression of CAC was significantly correlated with the extent of EFV (P < 0.001) while there was no significant correlation between progression of EFV or CAC with systemic inflammation markers.Epicardial fat volume and the baseline extent as well as progression of coronary atherosclerosis-measured by the calcium score-are significantly correlated. While both baseline EFV and CAC displayed significant correlations with systemic inflammation markers, biomarkers were not predictive of the progression of CAC or EFV.
EVALuna2:12060

Associations between dyspnoea, coronary atherosclerosis, and cardiovascular outcomes: results from the long-term follow-up CONFIRM registry - van Rosendael, Alexander R.; Bax, A. Maxim; van den Hoogen, Inge J.; Smit, Jeff M.; Al'Aref, Subhi J.; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; et al. (European Heart Journal - Cardiovascular Imaging, 2022)
AIMS : The relationship between dyspnoea, coronary artery disease (CAD), and major cardiovascular events (MACE) is poorly understood. This study evaluated (i) the association of dyspnoea with the severity of anatomical CAD by coronary computed tomography angiography (CCTA) and (ii) to which extent CAD explains MACE in patients with dyspnoea. METHODS AND RESULTS : From the international COronary CT Angiography EvaluatioN for Clinical Outcomes: An InteRnational Multicenter (CONFIRM) registry, 4425 patients (750 with dyspnoea) with suspected but without known CAD were included and prospectively followed for ≥5 years. First, the association of dyspnoea with CAD severity was assessed using logistic regression analysis. Second, the prognostic value of dyspnoea for MACE (myocardial infarction and death), and specifically, the interaction between dyspnoea and CAD severity was investigated using Cox proportional-hazard analysis. Mean patient age was 60.3 ± 11.9 years, 63% of patients were male and 592 MACE events occurred during a median follow-up duration of 5.4 (IQR 5.1-6.0) years. On uni- and multivariable analysis (adjusting for age, sex, body mass index, chest pain typicality, and risk factors), dyspnoea was associated with two- and three-vessel/left main (LM) obstructive CAD. The presence of dyspnoea increased the risk for MACE [hazard ratio (HR) 1.57, 95% confidence interval (CI): 1.29-1.90], which was modified after adjusting for clinical predictors and CAD severity (HR 1.26, 95% CI: 1.02-1.55). Conversely, when stratified by CAD severity, dyspnoea did not provide incremental prognostic value in one-, two-, or three-vessel/LM obstructive CAD, but dyspnoea did provide incremental prognostic value in non-obstructive CAD. CONCLUSION : In patients with suspected CAD, dyspnoea was independently associated with severe obstructive CAD on CCTA. The severity of obstructive CAD explained the elevated MACE rates in patients presenting with dyspnoea, but in patients with non-obstructive CAD, dyspnoea portended additional risk.
CRIS-Team Scopus Importer:2022-02-11
Keywords: coronary artery disease; coronary computed tomography angiography; dyspnoea; prognosis

A systematic report on non-coronary cardiac computed tomography angiographies in 1,097 patients from the German cardiac CT registry - Gitsioudis, Gitsios; Achenbach, Stephan; Schneider, S.; Schmermund, A.; Korosoglou, G.; Hausleiter, J.; Schroeder, S.; Rixe, R.; Leber, A.; Bruder, O.; Senges, J.; Marwan, Mohamed (2017)
EVALuna2:36028

A systematic report on non-coronary cardiac CTA in 1097 patients from the German cardiac CT registry - Gitsioudis, Gitsios; Schneider, Steffen; Schmermund, Axel; Korosoglou, Grigorios; Hausleiter, Jörg; Schroeder, Stephen; Rixe, Johannes; Leber, Alexander; Bruder, Oliver; Katus, Hugo A.; Senges, Jochen; Achenbach, Stephan; et al. (European Journal of Radiology, 2020)
Purpose: To prospectively evaluate contemporary indications, safety and diagnostic impact of cardiac CTA in patients undergoing cardiac CTA examinations for non-coronary clinical indications. Method: We analyzed 1097 consecutive patients from the German Cardiac CT Registry who underwent cardiac CTA between 2009 and 2014 due to clinically indicated non-coronary reasons using 64-slice or newer CT systems in twelve tertiary German heart centers in order to evaluate the impact of clinical indications on procedure-associated parameters. All participating centers electronically submitted patient and examination data including detailed indications, clinical symptoms, procedural parameters, complications and diagnostic results in a predefined template. Results: The most frequent indication for non-coronary cardiac CTA was the evaluation of pulmonary vein anatomy (65.9 %, 723/1097). In the remaining cases, most frequent indications were planning before TAVI (44.5 %, 69/155), evaluation of valvular disease (31.6 %, 49/155), and evaluation of implants (5.8 %, 9/155). Non-coronary cardiac CTA required a median amount of iodinated contrast agent of 100.0 mL (IQR 95.0–110.0 mL). Prospectively ECG-triggered acquisition was the most frequently used protocol (74.0 %), followed by retrospectively ECG-gated acquisition with and without tube current modulation (19.9 % and 6.0 %, respectively), resulting in a mean estimated effective dose of 5.2 mSv (IQR 2.9−9.5 mSv, average conversion factor k = 0.026). Overall, complication rate was very low (1.5 %). Non-coronary cardiac CTA revealed a new clinical diagnostic aspect in 3.2 % of all patients, and a new main clinical diagnosis in 2.2 %. Conclusions: Non-coronary cardiac CTA as a routinely applied diagnostic modality is associated with a very low procedure-related rate of complications and reasonably low radiation exposure using contemporary CT systems.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Non-coronary CTA; Pulmonary veins; TAVI; Valvular disease

A tribute to our reviewers - Crea, Filippo; Achenbach, Stephan (European Heart Journal, 2022)
CRIS-Team Scopus Importer:2023-03-08

Attenuation-based automatic kilovolt (kV)-selection in computedtomography of the chest: Effects on radiation exposure and imagequality - Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Achenbach, Stephan; Uder, Michael; Lell, Michael (European Journal of Radiology, 2013)
Objectives: To evaluate an automated attenuation-based kV-selection in computed tomography of thechest in respect to radiation dose and image quality, compared to a standard 120 kV protocol.Materials and methods: 104 patients were examined using a 128-slice scanner. Fifty examinations (58 ± 15years, study group) were performed using the automated adaption of tube potential (100-140 kV), basedon the attenuation profile of the scout scan, 54 examinations (62 ± 14 years, control group) with fixed120 kV. Estimated CT dose index (CTDI) of the software-proposed setting was compared with a 120 kVprotocol. After the scan CTDI volume (CTDIvol) and dose length product (DLP) were recorded. Imagequality was assessed by region of interest (ROI) measurements, subjective image quality by two observerswith a 4-point scale (3 - excellent, 0 - not diagnostic).Results: The algorithm selected 100 kV in 78% and 120 kV in 22%. Overall CTDIvol reduction was 26.6%(34% in 100 kV) overall DLP reduction was 22.8% (32.1% in 100 kV) (all p < 0.001). Subjective image qualitywas excellent in both groups.Conclusion: The attenuation based kV-selection algorithm enables relevant dose reduction (?27%) inchest-CT while keeping image quality parameters at high levels. © 2013 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chest; Computed tomography; Dose reduction; Tube potentialImage quality

Atypical Fibroxanthoma - Histological Diagnosis, Immunohistochemical Markers and Concepts of Therapy - Koch, Michael; Freundl, Anne J.; Agaimy, Abbas; Kiesewetter, Franklin; Kuenzel, Julian; Cicha, Iwona; Alexiou, Christoph (Anticancer Research, 2015)
Atypical fibroxanthoma (AFX) is an uncommon, rapidly growing cutaneous neoplasm of uncertain histogenesis. Thus far, there are no guidelines for diagnosis and therapy of this tumor.We included 18 patients with 21 AFX, and 2,912 patients with a total of 2,939 AFX cited in the literature between 1962 and 2014.In our cohort, excision with safety margin was performed in 100% of primary tumors. Local recurrences were observed in 25% of primary tumors and parotid metastases in 5%. Ten-year disease-specific survival was 100%. The literature research yielded 280 relevant publications. Over 90% of the reported cases were negative for cytokeratins, S100, desmin and human melanoma black 45 (HMB-45). Recurrent AFX was reported in 7.6% and metastasizing AFX in 2.75% cases. No significant differences in the recurrence and survival rates following wide local excision versus Mohs microsurgery were observed. Twenty-year disease-specific survival rate was 97.8%.A well-selected panel of immunohistochemical markers is necessary to establish AFX diagnosis with sufficient certainty. Adequately treated, AFX has an excellent prognosis, but long-term follow-up is recommended due to the potential for aggressive behavior.
EVALuna2:6738

Autoinflammation leading to autoimmunity in adult-onset Still’s disease: more than simple coincidence? - Valor-Mendez, Larissa; Manger, Bernhard; Cavallaro, Alexander Josef; Achenbach, Stephan; Schett, Georg; Rech, Jürgen (European Journal of Medical Research, 2021)
Background: Adult-onset Still’s disease (AOSD) should be considered in the differential diagnosis of patients with endocarditis, with or without a cardiac decompensation. Case presentation: We report the case of a 68-year-old Caucasian male diagnosed with AOSD after an initial acute manifestation of endocarditis with severe aortic acute manifestation of endocarditis with severe aortic insufficiency. The histological findings revealed Libman–Sacks endocarditis. He was treated with the IL-1 receptor inhibitor anakinra. Two years later the patient developed a symptomatic dilated cardiomyopathy with reduced ejection fraction (23.5%) and functional anti-beta-1-adrenergic receptor antibodies, which was initially treated with plasmapheresis; anakinra was maintained. While his AOSD symptoms responded well, our patient presented with recurrent arthritis in multiple joints, dual-energy CT showed urate deposition compatible with a gouty arthropathy. Over 7 years, he presented with recurrent episodes of arthritis and the adjustment of dosages of colchicine and febuxostat was needed. In 2018, our patient died due to a deterioration of his underlying cardiac disease. Conclusions: Only two cases with initial endocarditis prior to AOSD diagnosis have been published, and we are not aware of any other cases reporting -β1AR-Ab development with DCM and gout in the setting of AOSD treated with anakinra.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Adult-onset Still’s disease; Anakinra; ANTI-beta-1-adrenergic receptor antibodies; Dilated cardiomyopathy; Gout; IL-1 receptor inhibitor; Libman–Sacks endocarditis

Automated attenuation-based selection of tube voltage and tube current for coronary CT angiography: Reduction of radiation exposure versus a BMI-based strategy with an expert investigator - Layritz, Christian; Muschiol, Gerd; Flohr, Thomas; Bietau, Christian; Marwan, Mohamed; Schuhbaeck, Annika; Schmid, Jasmin; Ropers, Dieter; Achenbach, Stephan; Pflederer, Tobias (Journal of Cardiovascular Computed Tomography, 2013)
Background: Recently developed automated algorithms use the topogram and the corresponding attenuation information before coronary CT angiography (CTA) to allow for an individualized anatomic-based selection of tube current (mAs) and voltage (kV). Objectives: The value of these algorithms in reducing the associated radiation exposure was evaluated. Methods: One hundred patients underwent coronary CTA with dual-source CT with prospectively electrocardiogram-triggered axial data acquisition. In all patients, tube parameters (current and voltage) were suggested by both an experienced investigator according to the patient's body mass index (BMI; calculated as weight divided by height squared; kg/m2) and by an automated software according to attenuation values of the initial topogram. The first 50 consecutive patients (group 1) underwent coronary CTA with dual-source CT with tube parameters suggested by the experienced investigator (BMI-based tube parameters), whereas in another 50 consecutive patients (group 2) CT data acquisition was performed with tube settings of the automated software. Subsequently, subjective image quality (4-point rating score from 0= nondiagnostic to 3= excellent image quality), image noise (SD of CT number within the aortic root), as well as signal- and contrast-to-noise ratios and mean effective radiation doses, were compared between both groups. Results: Both groups showed comparable image quality parameters (group 1 vs 2: noise, 28.1± 6.0 HU vs 29.9 ± 5.4 HU, P= .12; signal-to-noise ratio, 16.4 ± 3.9 vs 16.8 ± 4.1, P= .54; contrast-to-noise ratio, 18.6 ± 4.1 vs 19.2 ± 4.3, P= .49; 4-point rating score, 2.8 ± 0.3 vs 2.9± 0.3, P= .81). Tube voltage, current, and mean effective radiation dose for groups 1 and 2 were 111 ± 12 kV and 108 ± 12 kV (P= .18), 361 ± 32 mAs and 320 ± 48 mAs (P < .001), and 2.3 mSv (25th; 75th percentile, 1.5; 2.8 mSv) and 1.4 mSv (25th; 75th percentile, 1.1; 1.9 mSv) (P < .001), respectively. Conclusions: Automated attenuation-based selections of individualized tube parameters are superior to BMI-based selections with expert oversight and show a potential for reduction of radiation exposure in coronary CTA, and image quality is maintained. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Automated software; Coronary CT angiography; Radiation dose; Tube current; Tube voltage

Automated quantification of epicardial adipose tissue from non-contrast CT on multi-center and multi-vendor data using deep learning - Commandeur, F.; Göller, Markus; Razipour, A.; Cadet, S.; Hell, Michaela; Kwiecinski, J.; Chen, X.; Chang, H. J.; Achenbach, Stephan; Berman, D. S.; Slomka, P. J.; Tamarappoo, B. K.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Automated Quantitative Plaque Burden from Coronary CT Angiography Noninvasively Predicts Hemodynamic Significance by using Fractional Flow Reserve in Intermediate Coronary Lesions - Diaz-Zamudio, Mariana; Dey, Damini; Schuhbaeck, Annika; Nakazato, Ryo; Gransar, Heidi; Slomka, Piotr J.; Narula, Jagat; Berman, Daniel S.; Achenbach, Stephan; Min, James K.; Doh, Joon-Hyung; Koo, Bon-Kwon (Radiology, 2015)
To evaluate the utility of multiple automated plaque measurements from coronary computed tomographic (CT) angiography in determining hemodynamic significance by using invasive fractional flow reserve (FFR) in patients with intermediate coronary stenosis.The study was approved by the institutional review board. All patients provided written informed consent. Fifty-six intermediate lesions (with 30%-69% diameter stenosis) in 56 consecutive patients (mean age, 62 years; range, 46-88 years), who subsequently underwent invasive coronary angiography with assessment of FFR (values <=0.80 were considered hemodynamically significant) were analyzed at coronary CT angiography. Coronary CT angiography images were quantitatively analyzed with automated software to obtain the following measurements: volume and burden (plaque volume × 100 per vessel volume) of total, calcified, and noncalcified plaque; low-attenuation (<30 HU) noncalcified plaque; diameter stenosis; remodeling index; contrast attenuation difference (maximum percent difference in attenuation per unit area with respect to the proximal reference cross section); and lesion length. Logistic regression adjusted for potential confounding factors, receiver operating characteristics, and integrated discrimination improvement were used for statistical analysis.FFR was 0.80 or less in 21 (38%) of the 56 lesions. Compared with nonischemic lesions, ischemic lesions had greater diameter stenosis (65% vs 52%, P = .02) and total (49% vs 37%, P = .0003), noncalcified (44% vs 33%, P = .0004), and low-attenuation noncalcified (9% vs 4%, P < .0001) plaque burden. Calcified plaque and remodeling index were not significantly different. In multivariable analysis, only total, noncalcified, and low-attenuation noncalcified plaque burden were significant predictors of ischemia (P < .015). For predicting ischemia, the area under the receiver operating characteristics curve was 0.83 for total plaque burden versus 0.68 for stenosis (P = .04).Compared with stenosis grading, automatic quantification of total, noncalcified, and low-attenuation noncalcified plaque burden substantially improves determination of lesion-specific hemodynamic significance by FFR in patients with intermediate coronary lesions.
EVALuna2:12083

Automatic ECG Arrhythmia Detection in Real-Time on Android-based Mobile Devices - Leutheuser, Heike; Gottschalk, Tristan; Anneken, Lars; Struck, Matthias; Heuberger, Albert; Achenbach, Stephan; Eskofier, Björn; Arnold, Martin (Proceedings of International Conference on Mobile and Information Technologies in Medicine and Health, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.automa_72

Avoiding unnecessary ventricular pacing is associated with reduced incidence of heart failure hospitalizations and persistent atrial fibrillation in pacemaker patients - Arnold, Martin; Richards, Mark; D'Onofrio, Antonio; Faulknier, Brett; Gulizia, Michele; Thakur, Ranjan; Sakata, Yasushi; Lin, Wenjiao; Pollastrelli, Annalisa; Grammatico, Andrea; Auricchio, Angelo; Boriani, Giuseppe; et al. (Europace, 2023)
Aims In bradycardia patients treated with dual-chamber pacing, we aimed to evaluate whether pacing with atrioventricular (AV) delay management [AV hysteresis (AVH)], compared with standard pacing with fixed AV delays, reduces unnecessary ventricular pacing percentage (VPP) and is associated with better clinical outcomes. Main study endpoints were the incidence of heart failure hospitalizations (HFH), persistent atrial fibrillation (AF), and cardiac death. Methods and results Data from two identical prospective observational studies, BRADYCARE I in the USA and BRADYCARE II in Europe, Africa, and Asia, were pooled. Overall, 2592 patients (75 +/- 10 years, 45.1% female, 50% with AVH) had complete clinical and device data at 1-year follow-up and were analysed. Primary pacing indication was sinus node disease (SND) in 1177 (45.4%), AV block (AVB) in 974 (37.6%), and other indications in 441 (17.0%) patients. Pacing with AVH, compared with standard pacing, was associated with a lower 1-year incidence of HFH [1.3% vs. 3.1%, relative risk reduction (RRR) 57.5%, P = 0.002] and of persistent AF (5.3% vs. 7.7%, RRR = 31.1%, P = 0.028). Cardiac mortality was not different between groups (1.0% vs. 1.4%, RRR = 27.8%, P = 0.366). Pacing with AVH, compared with standard pacing, was associated with a lower (P < 0.001) median VPP in all patients (7% vs. 75%), in SND (3% vs. 44%), in AVB (25% vs. 98%), and in patients with other pacing indications (3% vs. 47%). Conclusion Cardiac pacing with AV delay management via AVH is associated with reduced 1-year incidence of HFH and persistent AF, most likely due to a reduction in VPP compared to standard pacing.
CRIS-Team WoS Importer:2023-04-07

Bifurcation lesions: Are new strategies and devices needed? Bifurkationsläsionen: Braucht es neue Strategien und Devices? - Gaede, Luise (Herz, 2022)
Interventional treatment of bifurcation lesions, especially true complex bifurcation lesions, continue to be a challenge for interventional cardiologists. A primary one stent strategy is always preferred for simple bifurcation lesions, whereas studies in recent years have shown that a two stent strategy may be advantageous for true bifurcations, i.e. those involving at least the distal main branch as well as the side branch. This seems to be even more pronounced when the lesion presents as complex, i.e., the side branch shows high-grade stenosis over longer stretches and the complete lesion fulfils certain criteria, e.g., severe calcification and a bifurcation angle < 45° or > 70°. According to the latest randomized trials and meta-analyses, the double kissing (DK) crush and double kissing mini-crush (DKMC) techniques in particular seem to be advantageous for these lesions; however, in recent years the established techniques have been continuously refined and further developed. The DK culotte technique and the nano-crush technique deserve special attention. Both techniques seem to further improve and simplify the existing underlying strategies; however, further studies to prove the superiority of these techniques over the established ones are still pending. Overall, the implementation of the available randomized study results, the further development of the techniques and also of the materials can continuously improve the outcome of the patients after interventional treatment of bifurcation lesions. This is also confirmed by the latest registry data, which for the first time could show equal event rates in patients after treatment of complex lesions compared to simple lesions in the clinical practice.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Coronary vessels; Culotte technique; DK crush technique; Stent strategies; Stent techniques

Bildgebende Diagnostik der kardialen Sarkoidose - Blankstein, Ron; Achenbach, Stephan (Herz, 2023)
Cardiac involvement is clinically apparent in approximately 5% of all patients with systemic sarcoidosis, whereas evidence of cardiac involvement by imaging studies can be found in approximately 20% of cases. Occasionally, isolated cardiac sarcoidosis is encountered and is the only sign of the disease. The most frequent cardiac manifestations of the multifocal granulomatous inflammation include atrioventricular (AV) blocks and other conduction disorders, ventricular arrhythmias, sudden cardiac death and left and right ventricular wall disorders. Accordingly, symptoms that should raise suspicion include palpitations, lightheadedness and syncope. The diagnostic approach to cardiac sarcoidosis is not straightforward. Typical echocardiographic findings include regional thinning and contraction abnormalities particularly in basal, septal and lateral locations. Infrequently, myocardial hypertrophy may be present; however, the sensitivity of echocardiography is low and cardiac sarcoidosis can be present even when an echocardiogram is unrevealing. Cardiac magnetic resonance imaging (MRI) frequently shows late gadolinium enhancement (LGE) in a multifocal pattern often involving the basal septum and lateral walls. The sensitivity and specificity of MRI for detecting cardiac sarcoidosis are high. Fluorodeoxyglucose positron emission tomography (FDG-PET) plays an important role in the diagnostic algorithm due to its ability to visualize focal inflammatory activity both in the myocardium and in extracardiac locations. This may help target the optimal location for biopsy in order to obtain histologic proof of sarcoidosis and can also be used to follow the response to anti-inflammatory treatment. Notably, the sensitivity of endomyocardial biopsy is poor due to the patchy nature of myocardial involvement. In clinical practice, either histologic evidence of noncaseating granulomas from the myocardium or evidence from extracardiac tissue in combination with typical cardiac imaging findings are required to establish the diagnosis.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Atrioventricular block; FDG-PET; Heart failure; Sarcoidosis; Ventricular tachycardia

Biofabrication of vessel grafts based on natural hydrogels - Cicha, Iwona; Detsch, Rainer; Singh, Raminder; Reakasame, Supachai; Alexiou, Christoph; Boccaccini, Aldo R. (Current Opinion in Biomedical Engineering, 2017)

Bioresorbable Scaffold Versus Metallic Drug-Eluting Stent in Patients at High Risk of Restenosis (COMPARE-ABSORB trial): Very Late Device Thrombosis While on Extended DAPT - Van Geuns, Robert-Jan; Chang, Chun-Chin; Chevalier, Bernard; Gori, Tommaso; Barbato, Emanuele; Tarantini, Giuseppe; Achenbach, Stephan; Dudek, Dariusz; Escaned, Javier; Abdel-Wahab, Mohamed; Esposito, Giovanni; Tijssen, Jan; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Bioresorbable vascular scaffold thrombosis in a consecutive cohort of 550 patients - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Klinghammer, Lutz; Schlundt, Christian (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVE: To determine the rate of bioresorbable vascular scaffold (BVS) thrombosis in a large, real-world population. BACKGROUND: There is some concern about device thrombosis after percutaneous coronary intervention (PCI) using BVS. No data have been published for PCI using both BVS and metal stents. METHODS: A cohort of 550 consecutive patients who underwent PCI for stable chest pain or acute coronary syndromes with implantation of at least one BVS (Absorb, Abbott Vascular) was systematically followed up by telephone interview and review of medical charts. Data on device thrombosis were retrospectively analyzed in relationship to clinical and angiographic characteristics. RESULTS: Follow-up was achieved in 533 patients (97%, median follow-up 233 days). A total of 964 BVS were implanted in 645 vessels. In addition, 234 metal stents were implanted in 149 patients, including "hybrid intervention" with the combined use of BVS and stents in the same artery in 122 patients. Documented were 15 definite, 1 probable, and 8 possible cases of device thrombosis (rate of definite/probable device thrombosis: 3.0%). Of these, 6 definite and 6 possible thromboses could be unambiguously attributed to BVS (1.1%), whereas a total of 11 definite, 1 probable, and 8 possible thromboses were potentially attributable to BVS (2.3%). Definite device thrombosis occurred in 7/122 patients with "hybrid intervention" (5.7%). CONCLUSIONS: In a large real-world cohort treated with BVS, the rate of scaffold thrombosis was higher than published for randomized trials. A high rate of thrombosis was observed after combined implantation of BVS and stents within one vessel. © 2016 Wiley Periodicals, Inc.
EVALuna2:33663

Bioresorbable vascular scaffold versus metallic drug-eluting stent in patients at high risk of restenosis: the COMPARE- ABSORB randomised clinical trial - Smits, Pieter C.; Chang, Chun Chin; Chevalier, Bernard; West, Nick E. J.; Gori, Tommaso; Barbato, Emanuele; Tarantini, Giuseppe; Kocka, Viktor; Achenbach, Stephan; Dudek, Dariusz; Escaned, Javier; Wlodarczak, Adrian; et al. (EuroIntervention, 2020)
Aims: The aim of this study was to investigate clinical outcomes of patients at high risk of restenosis after implantation of a bioresorbable vascular scaffold (BVS).
CRIS-Team WoS Importer:2020-11-13

Biosensor-Integrated Drug Delivery Systems as New Materials for Biomedical Applications - Cicha, Iwona; Priefer, Ronny; Severino, Patricia; Souto, Eliana B.; Jain, Sona (Biomolecules, 2022)
Biosensor-integrated drug delivery systems are innovative devices in the health area, enabling continuous monitoring and drug administration. The use of smart polymer, bioMEMS, and electrochemical sensors have been extensively studied for these systems, especially for chronic diseases such as diabetes mellitus, cancer and cardiovascular diseases as well as advances in regenerative medicine. Basically, the technology involves sensors designed for the continuous analysis of biological molecules followed by drug release in response to specific signals. The advantages include high sensitivity and fast drug release. In this work, the main advances of biosensor-integrated drug delivery systems as new biomedical materials to improve the patients’ quality of life with chronic diseases are discussed.
CRIS-Team Scopus Importer:2022-10-07
Keywords: biomedical applications; biosensors; chronic treatments; drug delivery systems; smart polymers

Body mass index and the prevalence, severity, and risk of coronary artery disease: An international multicentre study of 13 874 patients - Labounty, Troy M.; Gomez, Millie J.; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor; Chinnaiyan, Kavitha M.; Chow, Benjamin; et al. (European Heart Journal - Cardiovascular Imaging, 2013)
AimsObesity is associated with the presence of coronary artery disease (CAD) risk factors and cardiovascular events. We examined the relationship between body mass index (BMI) and the presence, extent, severity, and risk of CAD in patients referred for coronary computed tomographic angiography (CCTA).Methods and resultsWe evaluated 13 874 patients from a prospective, international, multicentre registry of individuals without known CAD undergoing CCTA. We compared risk factors, CAD findings, and risk of all-cause mortality and non-fatal myocardial infarction (MI) amongst individuals with underweight (18.5-20.0 kg/m2), normal (20.1-24.9 kg/m2), overweight (25-29.9 kg/m2), and obese (≥30 kg/m2) BMI. The mean follow-up was 2.4 ± 1.2 years with 143 deaths and 193 MIs. Among underweight, normal weight, overweight, and obese individuals, there was increasing prevalence of diabetes (7 vs.10% vs. 12 vs. 19%), hypertension (37 vs. 40% vs. 46 vs. 59%), and hyperlipidaemia (48 vs. 52% vs. 56 vs. 56%; P < 0.001 for trend). After multivariable adjustment, BMI was positively associated with the prevalence of any CAD [odds ratio (OR) 1.25 per +5 kg/m2, 95% confidence interval (CI): 1.20-1.30, P < 0.001] and obstructive (≥50% stenosis) CAD (OR: 1.13 per +5 kg/m2, 95% CI: 1.08-1.19, P < 0.001); a higher BMI was also associated with an increased number of segments with plaque (+0.26 segments per +5 kg/m2, 95% CI: 0.22-0.30, P < 0.001). Larger BMI categories were associated with an increase in all-cause mortality (P = 0.004), but no difference in non-fatal MI. After multivariable adjustment, a higher BMI was independently associated with increased risk of MI (hazards ratio: 1.28 per +5 kg/m2, 95% CI: 1.12-1.45, P < 0.001).ConclusionsAmongst patients with suspected CAD referred for CCTA, individuals with increased BMI have greater prevalence, extent, and severity of CAD that is not fully explained by the presence of traditional risk factors. A higher BMI is independently associated with increased risk of intermediate-term risk of myocardial infarction. © The Author 2012.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Body mass index; Coronary artery disease; Myocardial infarction; Obesity

CAD-RADS™ 2.0 - 2022 Coronary Artery Disease - Reporting and Data System.: An expert consensus document of the Society of Cardiovascular Computed Tomography (SCCT), the American College of Cardiology (ACC), the American College of Radiology (ACR) and the North America Society of Cardiovascular Imaging (NASCI) - Cury, Ricardo C.; Leipsic, Jonathon; Abbara, Suhny; Achenbach, Stephan; Berman, Daniel; Bittencourt, Marcio; Budoff, Matthew; Chinnaiyan, Kavitha; Choi, Andrew D.; Ghoshhajra, Brian; Jacobs, Jill; Koweek, Lynne; et al. (JACR Journal of the American College of Radiology, 2022)
Coronary Artery Disease Reporting and Data System (CAD-RADS) was created to standardize reporting system for patients undergoing coronary CT angiography (CCTA) and to guide possible next steps in patient management. The goal of this updated 2022 CAD-RADS 2.0 is to improve the initial reporting system for CCTA by considering new technical developments in Cardiac CT, including data from recent clinical trials and new clinical guidelines. The updated CAD-RADS classification will follow an established framework of stenosis, plaque burden, and modifiers, which will include assessment of lesion-specific ischemia using CT fractional-flow-reserve (CT-FFR) or myocardial CT perfusion (CTP), when performed. Similar to the method used in the original CAD-RADS version, the determinant for stenosis severity classification will be the most severe coronary artery luminal stenosis on a per-patient basis, ranging from CAD-RADS 0 (zero) for absence of any plaque or stenosis to CAD-RADS 5 indicating the presence of at least one totally occluded coronary artery. Given the increasing data supporting the prognostic relevance of coronary plaque burden, this document will provide various methods to estimate and report total plaque burden. The addition of P1 to P4 descriptors are used to denote increasing categories of plaque burden. The main goal of CAD-RADS, which should always be interpreted together with the impression found in the report, remains to facilitate communication of test results with referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will continue to provide a framework of standardization that may benefit education, research, peer-review, artificial intelligence development, clinical trial design, population health and quality assurance with the ultimate goal of improving patient care.
EVALuna2:545520
Keywords: Coronary artery disease; Coronary CTA; CAD-RADS; Reporting and data system; Stenosis severity; Report standardization terminology; Plaque burden; Ischemia

CAD-RADS™ 2.0 - 2022 Coronary Artery Disease – Reporting and Data System an expert consensus document of the Society of Cardiovascular Computed Tomography (SCCT), the American College of Cardiology (ACC), the American College of Radiology (ACR) and the North America society of cardiovascular imaging (NASCI) - Cury, Ricardo C.; Leipsic, Jonathon; Abbara, Suhny; Achenbach, Stephan; Berman, Daniel; Bittencourt, Marcio; Budoff, Matthew; Chinnaiyan, Kavitha; Choi, Andrew D.; Ghoshhajra, Brian; Jacobs, Jill; Koweek, Lynne; et al. (Journal of Cardiovascular Computed Tomography, 2022)
Coronary Artery Disease Reporting and Data System (CAD-RADS) was created to standardize reporting system for patients undergoing coronary CT angiography (CCTA) and to guide possible next steps in patient management. The goal of this updated 2022 CAD-RADS 2.0 is to improve the initial reporting system for CCTA by considering new technical developments in Cardiac CT, including data from recent clinical trials and new clinical guidelines. The updated CAD-RADS classification will follow an established framework of stenosis, plaque burden, and modifiers, which will include assessment of lesion-specific ischemia using CT fractional-flow-reserve (CT-FFR) or myocardial CT perfusion (CTP), when performed. Similar to the method used in the original CAD-RADS version, the determinant for stenosis severity classification will be the most severe coronary artery luminal stenosis on a per-patient basis, ranging from CAD-RADS 0 (zero) for absence of any plaque or stenosis to CAD-RADS 5 indicating the presence of at least one totally occluded coronary artery. Given the increasing data supporting the prognostic relevance of coronary plaque burden, this document will provide various methods to estimate and report total plaque burden. The addition of P1 to P4 descriptors are used to denote increasing categories of plaque burden. The main goal of CAD-RADS, which should always be interpreted together with the impression found in the report, remains to facilitate communication of test results with referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will continue to provide a framework of standardization that may benefit education, research, peer-review, artificial intelligence development, clinical trial design, population health and quality assurance with the ultimate goal of improving patient care.
CRIS-Team Scopus Importer:2022-09-09
Keywords: CAD-RADS; Coronary artery disease; Coronary CTA; Ischemia; Plaque burden; Report standardization terminology; Reporting and data system; Stenosis severity

CAD-RADS™ 2.0 - 2022 Coronary Artery Disease - Reporting and Data System An Expert Consensus Document of the Society of Cardiovascular Computed Tomography (SCCT), the American College of Cardiology (ACC), the American College of Radiology (ACR) and the North America Society of Cardiovascular Imaging (NASCI). - Cury, Ricardo C.; Leipsic, Jonathon; Abbara, Suhny; Achenbach, Stephan; Berman, Daniel; Bittencourt, Marcio; Budoff, Matthew; Chinnaiyan, Kavitha; Choi, Andrew D.; Ghoshhajra, Brian; Jacobs, Jill; Koweek, Lynne; et al. (Radiology: Cardiothoracic Imaging, 2022)
Coronary Artery Disease Reporting and Data System (CAD-RADS) was created to standardize reporting system for patients undergoing coronary CT angiography (CCTA) and to guide possible next steps in patient management. The goal of this updated 2022 CAD-RADS 2.0 is to improve the initial reporting system for CCTA by considering new technical developments in Cardiac CT, including data from recent clinical trials and new clinical guidelines. The updated CAD-RADS classification will follow an established framework of stenosis, plaque burden, and modifiers, which will include assessment of lesion-specific ischemia using CT fractional-flow-reserve (CT-FFR) or myocardial CT perfusion (CTP), when performed. Similar to the method used in the original CAD-RADS version, the determinant for stenosis severity classification will be the most severe coronary artery luminal stenosis on a per-patient basis, ranging from CAD-RADS 0 (zero) for absence of any plaque or stenosis to CAD-RADS 5 indicating the presence of at least one totally occluded coronary artery. Given the increasing data supporting the prognostic relevance of coronary plaque burden, this document will provide various methods to estimate and report total plaque burden. The addition of P1 to P4 descriptors are used to denote increasing categories of plaque burden. The main goal of CAD-RADS, which should always be interpreted together with the impression found in the report, remains to facilitate communication of test results with referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will continue to provide a framework of standardization that may benefit education, research, peer-review, artificial intelligence development, clinical trial design, population health and quality assurance with the ultimate goal of improving patient care. Keywords: Coronary Artery Disease, Coronary CTA, CAD-RADS, Reporting and Data System, Stenosis Severity, Report Standardization Terminology, Plaque Burden, Ischemia Supplemental material is available for this article. This article is published synchronously in Radiology: Cardiothoracic Imaging, Journal of Cardiovascular Computed Tomography, JACC: Cardiovascular Imaging, Journal of the American College of Radiology, and International Journal for Cardiovascular Imaging. © 2022 Society of Cardiovascular Computed Tomography. Published by RSNA with permission.
EVALuna2:545538
Keywords: Coronary Artery Disease; Coronary CTA; CAD-RADS; Reporting and Data System; Stenosis Severity; Report Standardization Terminology; Plaque Burden; Ischemia

CAD-RADS(TM) 2.0-2022 Coronary Artery Disease-Reporting and Data System - Cury, Ricardo C.; Leipsic, Jonathon; Abbara, Suhny; Achenbach, Stephan; Berman, Daniel; Bittencourt, Marcio; Budoff, Matthew; Chinnaiyan, Kavitha; Choi, Andrew D.; Ghoshhajra, Brian; Jacobs, Jill; Koweek, Lynne; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
Coronary Artery Disease Reporting and Data System (CAD-RADS) was created to standardize reporting system for patients undergoing coronary CT angiography (CCTA) and to guide possible next steps in patient management. The goal of this updated 2022 CAD-RADS 2.0 is to improve the initial reporting system for CCTA by considering new technical developments in cardiac CT, including data from recent clinical trials and new clinical guidelines. The updated CAD-RADS classification will follow an established framework of stenosis, plaque burden, and modifiers, which will include assessment of lesion-specific ischemia using CT fractional-flow-reserve (CT-FFR) or myocardial CT perfusion (CTP), when performed. Similar to the method used in the original CAD-RADS version, the determinant for stenosis severity classification will be the most severe coronary artery luminal stenosis on a per-patient basis, ranging from CAD-RADS 0 (zero) for absence of any plaque or stenosis to CAD-RADS 5 indicating the presence of at least one totally occluded coronary artery. Given the increasing data supporting the prognostic relevance of coronary plaque burden, this document will provide various methods to estimate and report total plaque burden. The addition of P1 to P4 descriptors are used to denote increasing categories of plaque burden. The main goal of CAD-RADS, which should always be interpreted together with the impression found in the report, remains to facilitate communication of test results with referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will continue to provide a framework of standardization that may benefit education, research, peer-review, artificial intelligence development, clinical trial design, population health and quality assurance with the ultimate goal of improving patient care. (J Am Coll Cardiol Img 2022;15:1974-2001) (c) 2022 Society of Cardiovascular Computed Tomography. Published by Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2023-03-10

CAD-RADS™: Coronary Artery Disease - Reporting and Data System: An Expert Consensus Document of the Society of Cardiovascular Computed Tomography (SCCT), the American College of Radiology (ACR) and the North American Society for Cardiovascular Imaging (NASCI). Endorsed by the American College of Cardiology - Cury, Ricardo C.; Abbara, Suhny; Achenbach, Stephan; Agatston, Arthur; Berman, Daniel S.; Budoff, Matthew J.; Dill, Karin E.; Jacobs, Jill E.; Maroules, Christopher D.; Rubin, Geoffrey D.; Rybicki, Frank J.; Schoepf, U. Joseph; et al. (JACR Journal of the American College of Radiology, 2016)
The intent of CAD-RADS - Coronary Artery Disease Reporting and Data System is to create a standardized method to communicate findings of coronary CT angiography (coronary CTA) in order to facilitate decision-making regarding further patient management. The suggested CAD-RADS classification is applied on a per-patient basis and represents the highest-grade coronary artery lesion documented by coronary CTA. It ranges from CAD-RADS 0 (Zero) for the complete absence of stenosis and plaque to CAD-RADS 5 for the presence of at least one totally occluded coronary artery and should always be interpreted in conjunction with the impression found in the report. Specific recommendations are provided for further management of patients with stable or acute chest pain based on the CAD-RADS classification. The main goal of CAD-RADS is to standardize reporting of coronary CTA results and to facilitate communication of test results to referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will provide a framework of standardization that may benefit education, research, peer-review and quality assurance with the potential to ultimately result in improved quality of care.
EVALuna2:33661

Calcium score, coronary artery disease extent and severity, and clinical outcomes among low Framingham risk patients with low vs high lifetime risk: Results from the CONFIRM registry - Hulten, Edward; Villines, Todd C.; Cheezum, Michael K.; Berman, Daniel S.; Dunning, Allison; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor Y.; et al. (Journal of Nuclear Cardiology, 2014)
Short-term risk scores, such as the Framingham risk score (FRS), frequently classify younger patients as low risk despite the presence of uncontrolled cardiovascular risk factors. Among patients with low FRS, estimation of lifetime risk is associated with significant differences in coronary arterial calcium scores (CACS); however, the relationship of lifetime risk to coronary atherosclerosis on coronary CT angiography (CCTA) and prognosis has not been studied.We evaluated asymptomatic 20-60-year-old patients without diabetes or known coronary artery disease (CAD) within an international CT registry who underwent >=64-slice CCTA. Patients with low FRS (<10%) were stratified as low (<39%) or high (>=39%) lifetime CAD risk, and compared for the presence and severity of CAD and prognosis for death, myocardial infarction, and late coronary revascularization (>90 days post CCTA). 1,863 patients of mean age of 47 years were included, with 48% of the low FRS patients at high lifetime risk. Median follow-up was 2.0 years. Comparing low-to-high lifetime risk, respectively, the prevalence of any CAD was 32% vs 41% (P < .001) and >=50% stenosis was 7.4% vs 9.6% (P = .09). For those with CAD, subjects at low vs high lifetime risk had lower CACS (median 12 [IQR 0-94] vs 38 [IQR 0.05-144], P = .02) and less purely calcified plaque, 35% vs 45% (P < .001). Prognosis did not differ due to low number of events.Assessment of lifetime risk among patients at low FRS identified those with the increase in CAD prevalence and severity and a higher proportion of calcified plaque.
EVALuna2:11897

Can coronary computed tomography angiography replace invasive angiography? Yes: it is all about finding the right test for the right person at the right time - Achenbach, Stephan (Circulation, 2015)
EVALuna2:12087

CAN WE IDENTIFY GLOMERULAR HYPERFILTRATION IN PATIENTS WITH TYPE 2 DIABETES BY CLINICAL PARAMETERS? - Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Jung, Susanne; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Cardiac computed tomography core syllabus of the European Association of Cardiovascular Imaging (EACVI) - Nieman, Koen; Achenbach, Stephan; Pugliese, Francesca; Cosyns, Bernard; Lancellotti, Patrizio; Kitsiou, Anastasia (European Heart Journal - Cardiovascular Imaging, 2015)
The European Association of Cardiovascular Imaging (EACVI) Core Syllabus for Cardiac Computed Tomography (CT) is now available online. The syllabus lists key elements of knowledge in Cardiac CT. It represents a framework for the development of training curricula and provides expected knowledge-based learning outcomes to the Cardiac CT trainees.
EVALuna2:12051

Cardiac computed tomography - Current diagnostic role in cardiology - Achenbach, Stephan (Deutsche Medizinische Wochenschrift, 2022)
Computed tomography (CT) imaging of the heart requires specific equipment and protocols in order to synchronize image generation with the electrocardiogram (ECG), usually achieved via ECG-gated reconstruction or ECG-triggered acquisition. The main application of cardiac CT is coronary artery imaging. Contrast-enhanced coronary artery CT allows the identification and rule-out of stenoses and is a diagnostic approach to patients with suspected chronic coronary artery disease or acute chest pain, provided that patient characteristics are associated with a high likelihood of fully diagnostic image quality. In addition, CT has the potential to visualize coronary atherosclerotic plaque, even if non-obstructive, and data suggest that this may be a valuable guide towards more intensive risk modification strategy such as statin therapy. In recent years, the use of CT imaging to guide structural heart interventions has become another important application, and many interventions, such as transcatheter aortic valve implantation, substantially depend on CT imaging to plan the procedure, minimize risks, and optimize outcome.
CRIS-Team WoS Importer:2022-05-13

Cardiac CT for Quantification of Epicardial Fat: Where to Measure and Why? - Marwan, Mohamed; Achenbach, Stephan (Current Cardiovascular Imaging Reports, 2015)
Epicardial adipose tissue has been attracting increasing attention over the last decade with a large body of evidence pointing towards significant associations between the volume of epicardial fat and atherosclerotic and non-atherosclerotic heart diseases. On the other hand, recent data from relatively large studies question the hypothesis of epicardial fat as an independent risk factor for atherosclerosis. This article reviews the available literature concerning imaging and quantification of epicardial adipose tissue and its potential clinical significance.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Epicardial; Intrathoracic; Paracardiac; Pericardial

Cardiac CT: Technological Advances in Hardware, Software, and Machine Learning Applications. - Commandeur, Frederic; Göller, Markus; Dey, Damini (Current Cardiovascular Imaging Reports, 2018)
Purpose of Review: Multidetector row computed tomography (CT) allows noninvasive imaging of the heart and coronary arteries. The purpose of this review is to briefly summarize recent advances in CT hardware and software technology, and machine learning applications for cardiovascular imaging. Recent Findings: In the last decades, there have been significant improvements in CT hardware focusing on faster gantry rotation resulting in improved temporal resolution. Concurrent hardware improvements include improved spatial resolution and higher coverage of the patient, enabling faster acquisition. Advances in cardiac CT software include methods for measurement of noninvasive FFR, coronary plaque characterization, and adipose tissue characteristics around the heart. Machine learning approaches using cardiac CT have been shown to improve both risk of prognosis and lesion-specific ischemia. Summary: Recent advances in CT hardware and software have expanded the clinical utility of CT for cardiovascular imaging. In the next decades, continued advances can be anticipated in these areas, and in machine learning applications in cardiac CT, as they are incorporated into clinical routine for image acquisition, image analysis, and prediction of patient outcomes.
EVALuna2:423072

Cardiac MRI: An Alternative Method to Determine the Left Ventricular Function - Michler, Kerstin; Hessman, Christopher; Prümmer, Marcus; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias (Diagnostics, 2023)
(1) Background: With the conventional contour surface method (KfM) for the evaluation of cardiac function parameters, the papillary muscle is considered to be part of the left ventricular volume. This systematic error can be avoided with a relatively easy-to-implement pixel-based evaluation method (PbM). The objective of this thesis is to compare the KfM and the PbM with regard to their difference due to papillary muscle volume exclusion. (2) Material and Methods: In the retrospective study, 191 cardiac-MR image data sets (126 male, 65 female; median age 51 years; age distribution 20–75 years) were analysed. The left ventricular function parameters: end-systolic volume (ESV), end-diastolic volume (EDV), ejection fraction (EF) and stroke volume (SV) were determined using classical KfW (syngo.via and cvi42 = gold standard) and PbM. Papillary muscle volume was calculated and segmented automatically via cvi42. The time required for evaluation with the PbM was collected. (3) Results: The size of EDV was 177 mL (69–444.5 mL) [average, [minimum–maximum]], ESV was 87 mL (20–361.4 mL), SV was 88 mL and EF was 50% (13–80%) in the pixel-based evaluation. The corresponding values with cvi42 were EDV 193 mL (89–476 mL), ESV 101 mL (34–411 mL), SV 90 mL and EF 45% (12–73%) and syngo.via: EDV 188 mL (74–447 mL), ESV 99 mL (29–358 mL), SV 89 mL (27–176 mL) and EF 47% (13–84%). The comparison between the PbM and KfM showed a negative difference for end-diastolic volume, a negative difference for end-systolic volume and a positive difference for ejection fraction. No difference was seen in stroke volume. The mean papillary muscle volume was calculated to be 14.2 mL. The evaluation with PbM took an average of 2:02 min. (4) Conclusion: PbM is easy and fast to perform for the determination of left ventricular cardiac function. It provides comparable results to the established disc/contour area method in terms of stroke volume and measures “true” left ventricular cardiac function while omitting the papillary muscles. This results in an average 6% higher ejection fraction, which can have a significant influence on therapy decisions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac MRI; cine MRI; ejection fraction; left ventricular function; MRI

Cardiac Resynchronization Therapy in geriatric Patients - Normann, J.; Bahrmann, A.; Bahrmann, P.; Becker, R.; Katus, Hugo; Sieber, Cornel (Internist, 2013)

Cardiovascular computed tomography: highlights of latest research presented at the 2014 Congress of the European Society of Cardiology - Schuhbaeck, Annika; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2014)
EVALuna2:12020

Cardiovascular risk among stable individuals suspected of having coronary artery disease with no modifiable risk factors: Results from an international multicenter study of 5262 patients - Leipsic, Jonathon; Taylor, Carolyn M.; Grunau, Gilat; Heilbron, Brett G.; Mancini, G. B. John; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (Radiology, 2013)
Purpose: To assess the prevalence, extent, severity, and risk of coronary artery disease (CAD) in patients suspected of having CAD but with no medically modifiable risk factors. Materials and Methods: Institutional review board approval or waiver of consent was obtained at each center. This study was HIPAA compliant. From an international multicenter cohort study of 27 125 subjects undergoing coronary computed tomographic (CT) angiography from 12 centers, 5262 patients without known CAD and without modifiable risk factors were identified. CAD severity was defined as none (0%), mild (1%-49%), or obstructive (≥50%) on a per-patient, per-vessel, and per-segment basis. CAD presence, extent, and severity were related to incidence of major adverse cardiovascular event (MACE) by using Cox proportional hazards models. Results: At a mean follow-up of 2.3 years ± 1.2 (standard deviation), MACE occurred in 106 patients. CAD was common for nonobstructive (n = 1452, 27%) and obstructive (n = 629, 12%) CAD. In risk-adjusted analysis, per-patient obstructive CAD (hazard ratio [HR], 6.64; 95% confidence interval [CI]: 3.68, 12.00; P ≤ .001) was related to MACE. MACE was associated with a dose-response relationship to the number of vessels exhibiting obstructive CAD, increasing risk for obstructive one-vessel (HR, 6.11; 95% CI: 3.22, 11.6; P ≤ .001), two-vessel (HR, 5.86; 95% CI: 2.75, 12.5; P ≤ .0001), or three-vessel or left main (HR, 11.69; 95% CI: 5.38, 25.4; P ≤ .001) CAD. The increased hazard for MACE of obstructive disease holds true for symptomatic (HR, 11.9; 95% CI: 4.81, 29.6; P ≤ .001) and asymptomatic (HR, 6.3; 95% CI: 2.4, 16.7; P ≤ .001) patients. No CAD at coronary CT angiography was associated with a low annualized MACE rate: 0.31% versus 2.06% with obstructive disease. Conclusion: Among individuals suspected of having CAD but without modifiable risk factors, CAD is common, with significantly increased hazards for MACE and mortality. © RSNA, 2013.
CRIS-Team Scopus Importer:2023-03-08

CD40/CD154 system and pro-inflammatory cytokines in young healthy male smokers without additional risk factors for atherosclerosis - Garlichs, Christoph; Cicha, Iwona; Raaz-Schrauder, Dorette; Meyer, L.; Stumpf, Christian; Klinghammer, Lutz; Yilmaz, Atilla; Daniel, Werner (Inflammation Research, 2009)
Objective and design:: Atherosclerosis, as an inflammatory disease, is characterized by pathologically altered levels of cytokines. We investigated whether smoking affects the CD40/CD154 system and pro-inflammatory cytokines in young males without other risk factors for atherosclerosis. Subjects:: Young male smokers (n=13) and 14 non-smoking controls were investigated. Methods:: The differences in CD40/CD154 system and serum cytokines between the groups were measured using flow cytometry and ELISA. Results:: In smokers, there was a strong trend (P<0.06) for increased CD40 expression on platelets as compared with non-smokers. However, there were no significant differences in CD40 expression on monocytes or in CD154 expression on platelets and T-cells between smokers and non-smokers. There was a strong trend for increased platelet-monocyte aggregates in smokers (P<0.06). Also, smokers had slightly but not significantly elevated hsCRP and IL-6 levels, and slightly decreased TNF-α and MCP-1. Interestingly, IL-18, a cytokine which has the ability to promote both Th1 and Th2 responses, was significantly decreased in smokers group (P=0.03 vs controls). Conclusions:: In young healthy males, smoking is not associated with dramatic changes in CD40/CD154 system. However, cigarette smoke alters the secreted cytokine profile, leading to significant decrease in systemic IL-18 levels. © 2009 Birkhäuser Verlag, Basel.
CRIS-Team Scopus Importer:2023-07-10
Keywords: CD40/CD154; Cytokines; Interleukin-18; Platelets; Smoking

Cell specificity of magnetic cell seeding approach to hydrogel colonization - Singh, Raminder; Wieser, Anna; Reakasame, Supachai; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona (Journal of Biomedical Materials Research Part A, 2017)
Keywords: alginate-based hydrogels; endothelial cells; fibroblasts; magnetic cell seeding; superparamagnetic iron oxide nanoparticles

Central Core Laboratory versus Site Interpretation of Coronary CT Angiography: Agreement and Association with Cardiovascular Events in the PROMISE Trial - Lu, Michael T.; Meyersohn, Nandini M.; Mayrhofer, Thomas; Bittner, Daniel O.; Emami, Hamed; Puchner, Stefan B.; Foldyna, Borek; Mueller, Martin E.; Hearne, Steven; Yang, Clifford; Achenbach, Stephan; Truong, Quynh A.; et al. (Radiology, 2018)
Purpose To assess concordance and relative prognostic utility between central core laboratory and local site interpretation for significant coronary artery disease (CAD) and cardiovascular events. Materials and Methods In the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial, readers at 193 North American sites interpreted coronary computed tomographic (CT) angiography as part of the clinical evaluation of stable chest pain. Readers at a central core laboratory also interpreted CT angiography blinded to clinical data, site interpretation, and outcomes. Significant CAD was defined as stenosis greater than or equal to 50%; cardiovascular events were defined as a composite of cardiovascular death or myocardial infarction. Results In 4347 patients (51.8% women; mean age ± standard deviation, 60.4 years ± 8.2), core laboratory and site interpretations were discordant in 16% (683 of 4347), most commonly because of a finding of significant CAD by site but not by core laboratory interpretation (80%, 544 of 683). Overall, core laboratory interpretation resulted in 41% fewer patients being reported as having significant CAD (14%, 595 of 4347 vs 23%, 1000 of 4347; P < .001). Over a median follow-up period of 25 months, 1.3% (57 of 4347) sustained myocardial infarction or cardiovascular death. The C statistic for future myocardial infarction or cardiovascular death was 0.61 (95% confidence interval [CI]: 0.54, 0.68) for the core laboratory and 0.63 (95% CI: 0.56, 0.70) for the sites. Conclusion Compared with interpretation by readers at 193 North American sites, standardized core laboratory interpretation classified 41% fewer patients as having significant CAD. © RSNA, 2017 Online supplemental material is available for this article. Clinical trial registration no. NCT01174550.
EVALuna2:36002

Cerebrovascular complications of immunologically mediated heparin-induced thrombocytopenia - Macha, K.; Kloska, Stephan; Dörfler, Arnd; Raaz-Schrauder, D.; Schwab, Sibylle; Köhrmann, Martin; Seifert, Frank (Fortschritte der Neurologie - Psychiatrie, 2014)
Immunologically mediated heparin-induced thrombocytopenia (HIT) is a thrombotic disease caused by antibodies occurring after heparin exposure. Thrombocytopenia occurs within a few days after heparin exposure, about half of HIT-patients develop venous or arterial thrombotic complications. Neurological complications of HIT are mainly ischaemic stroke and sinus vein thrombosis. To ensure the primary clinical diagnosis functional and immunological assays for antibody detection are available. The probability for the occurrence of HIT depends on the nature of heparin employed (LMWH vs. UFH) and individual patient characteristics such as gender and primary disease (medical vs. surgical patients). In the case of suspected HIT heparin administration should be discontinued immediately and replaced by an alternative anticoagulation to prevent the expansion or development of further thrombotic complications. Herein we report a case of a patient suffering from HIT-associated embolic cerebral ischaemic stroke.
EVALuna2:22326

Change of renal function after short-term use of cardioprotective agents in patients with type 2 diabetes is not accurately assessed by the change of estimated glomerular filtration rate: an observational study - Kolwelter, Julie; Striepe, Kristina; Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Schiffer, Mario; Schmieder, Roland (Diabetology & Metabolic Syndrome, 2022)
Background After initiating cardioprotective agents, a fall of estimated glomerular filtration rate (eGFR) has been reported in several studies. Our goal was to evaluate the accuracy of change of Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFR in patients with type 2 diabetes (T2D) after short-term pharmacological intervention with angiotensin-converting enzyme inhibitor, angiotensin-receptor blocker, gliptin or sodium-glucose cotransporter-2 inhibitor. Methods We analyzed 190 patients with T2D in the early stage of the disease, having no overt renal impairment by CKD-EPI equation. In each patient, we measured GFR (mGFR) by applying the constant infusion input clearance technique with sinistrin (Inutest; Fresenius, Linz, Austria) at baseline and after short-term (4-12 weeks) pharmacological intervention with cardioprotective agents (ramipril, telmisartan, linagliptin, metformin, empagliflozin) that potentially lead to an alteration of renal function. Simultaneously, a standardized analysis of serum creatinine was performed and eGFR was estimated by the CKD-EPI equation. Results Average mGFR was 111 +/- 20 ml/min/1.73m(2), whereas eGFR was lower with 93 +/- 13 ml/min/1.73m(2). The ratio eGFR/mGFR in relation to mGFR was almost curvilinear, showing an underestimation of renal function by eGFR in the upper normal range. At baseline only 80 patients (42%) lay within +/- 10% of mGFR and the concordance correlation coefficient (CCC) was extremely low (- 0.07). After short-term pharmacological intervention changes in eGFR and mGFR correlated with each other (r = 0.286, p < 0.001). For example, for a given mGFR of 111 ml/min/1.73m(2), a change of mGFR by +/- 10% corresponded to +/- 11 ml/min/1.73m(2), but the confidence interval of eGFR was 25 ml/min/1.73m(2). The CCC was low (0.22). Conclusion The agreement between eGFR by CKD-EPI and mGFR is modest and the change of renal function after short-term pharmacological intervention is not accurately and precisely reflected by the change of eGFR in patients with T2D in the early stage of their disease.
CRIS-Team WoS Importer:2022-08-05

Changes of tricuspid valve geometry after interventional implantation of an anuloplasty band - Landendinger, M.; Smolka, S.; Haug, J.; Tröbs, Monique; Ammon, Fabian; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Chronic development of ischaemic mitral regurgitation during post-infarction remodelling - Klinghammer, Lutz; et al. (Cardiology, 2007)
Keywords: Left-ventricular remodelling; Myocardial infarction; Mitral regurgitation; Prognosis

Chronic Kidney Disease and Coronary Artery Disease: JACC State-of-the-Art Review - Sarnak, Mark J.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Journal of the American College of Cardiology, 2019)
Chronic kidney disease (CKD) is a major risk factor for coronary artery disease (CAD). As well as their high prevalence of traditional CAD risk factors, such as diabetes and hypertension, persons with CKD are also exposed to other nontraditional, uremia-related cardiovascular disease risk factors, including inflammation, oxidative stress, and abnormal calcium-phosphorus metabolism. CKD and end-stage kidney disease not only increase the risk of CAD, but they also modify its clinical presentation and cardinal symptoms. Management of CAD is complicated in CKD patients, due to their likelihood of comorbid conditions and potential for side effects during interventions. This summary of the Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference on CAD and CKD (including end-stage kidney disease and transplant recipients) seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of CAD in CKD and to identify knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-10-01
Keywords: acute coronary syndromes; calcification; chronic kidney disease; coronary artery disease; revascularization

Chronic kidney disease and valvular heart disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference - Marwick, Thomas H.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Kidney International, 2019)
Chronic kidney disease (CKD) is a major risk factor for valvular heart disease (VHD). Mitral annular and aortic valve calcifications are highly prevalent in CKD patients and commonly lead to valvular stenosis and regurgitation, as well as complications including conduction system abnormalities and endocarditis. VHD, especially mitral regurgitation and aortic stenosis, is associated with significantly reduced survival among CKD patients. Knowledge related to VHD in the general population is not always applicable to CKD patients because the pathophysiology may be different, and CKD patients have a high prevalence of comorbid conditions and elevated risk for periprocedural complications and mortality. This Kidney Disease: Improving Global Outcomes (KDIGO) review of CKD and VHD seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of VHD in CKD by summarizing knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-09-24
Keywords: aortic stenosis; chronic kidney disease; end-stage kidney disease; mitral annular calcification; valvular heart disease

Circadian and circaseptan rhythms in implant-based thoracic impedance - Kirchner, J.; Paule, S.; Beckendorf, C.; Achenbach, Susanne; Arnold, Martin (Physiological Measurement, 2015)
Thoracic impedance (TI) denotes the electrical resistance that is measured between the right ventricular lead and the can of an implantable cardioverter-defibrillator. It is used in medical diagnostics for fluid load monitoring in heart failure patients. We analysed TI for diurnal and weekly components that go along with the recurrent patterns of daily life.TI was measured in 53 patients over 280 d each with a resolution of 1 h. Information about the patients' professional occupation and typical sleeping rhythm was sought. Periodic signal components were identified in the amplitude spectrum, and their main characteristics were derived by cosinor analysis. The typical daily and weekly pattern were reconstructed by Fourier filtering.The Fourier spectrum indicates a strong circadian and a weaker circaseptan component in TI. The latter is significantly elevated in patients who regularly go to work, on error level [Formula: see text]. Cosinor analysis states a significant circadian rhythm in all patients ([Formula: see text]), with MESOR 61.8 [Formula: see text], amplitude 1.9 [Formula: see text], and acrophase 17.5 h. A significant weekly rhythm is found in 25 patients ([Formula: see text]), with amplitude 0.31 [Formula: see text] and acrophase typically on Wednesday. Both rhythms typically obtain their maximum during the 'active' phase of the period in daily life, i.e. in the afternoon and on working days, respectively, while the minimum is reached in the 'recreative' phase.Circadian and circaseptan variation are hence prevalent components of TI, which can induce impedance changes of several Ohms and thus be an error source for daily TI measurements.
EVALuna2:12074

Circadian and circaseptan rhythms in implant-based thoracic impedance - Kirchner, Jens; Paule, Stefan; Beckendorf, Claudia; Achenbach, Stephan; Arnold, Martin (Physiological Measurement, 2015)
Thoracic impedance (TI) denotes the electrical resistance that is measured between the right ventricular lead and the can of an implantable cardioverter-defibrillator. It is used in medical diagnostics for fluid load monitoring in heart failure patients. We analysed TI for diurnal and weekly components that go along with the recurrent patterns of daily life. TI was measured in 53 patients over 280d each with a resolution of 1h. Information about the patients' professional occupation and typical sleeping rhythm was sought. Periodic signal components were identified in the amplitude spectrum, and their main characteristics were derived by cosinor analysis. The typical daily and weekly pattern were reconstructed by Fourier filtering. The Fourier spectrum indicates a strong circadian and a weaker circaseptan component in TI. The latter is significantly elevated in patients who regularly go to work, on error level p < 0.05. Cosinor analysis states a significant circadian rhythm in all patients (p < 0.001), with MESOR 61.8Ohm, amplitude 1.9Ohm, and acrophase 17.5h. A significant weekly rhythm is found in 25 patients (p < 0.05), with amplitude 0.31Ohm and acrophase typically on Wednesday. Both rhythms typically obtain their maximum during the 'active' phase of the period in daily life, i.e. in the afternoon and on working days, respectively, while the minimum is reached in the 'recreative' phase. Circadian and circaseptan variation are hence prevalent components of TI, which can induce impedance changes of several Ohms and thus be an error source for daily TI measurements.

Circadian variation in thoracic impedance - Beckendorf, Claudia; Kirchner, Jens; Paule, Stefan; Achenbach, Stephan; Arnold, Martin (Clinical Research in Cardiology Supplements, 2014)
Introduction: Thoracic impedance (TI) is the electrical resistance measured between the right ventricular shock coil and the can of an implantable cardioverter-defibrillator. As it is known to decrease on lung congestion, it has been proposed as a marker of worsening of cardiac status in heart failure patients. However, the diagnostic value of TI is limited by various confounding factors and the extent of physiologic variability is poorly understood. We therefore analyzed circadian variation of TI. Methods: In 54 patients with an implanted ICD (n = 47) or CRT-D (n = 7) device (85% male, 66 ± 11 years, NYHA class I-IV, EF 31 ± 14 %), TI was measured with an hourly resolution. The resulting 24 TI values per day were transmitted via home monitoring. For each patient, data from an observation interval of 28 days were averaged separately for each time of the day. Intra-day variability was correlated to each individual patient´s daily routine, which was determined by a questionnaire. Results: Daily mean thoracic impedance of all 54 subjects was 61.0 ± 6.2 Ω (range: 43.8-71.8 Ω). Intra-day variation was present in all subjects, ranging from 1.1 to 8.4 Ω and with 3.2 ± 1.7 Ω in average. The typical day-curve (see figure) exhibits a clear minimum in the early morning (average lowest TI: -1.9 ± 1.4 Ω below mean) and a plateau in the afternoon (maximum height: 1.3 ± 1.0 Ω above mean). The phases of the day with large changes in TI - nighttime and morning hours till noon - are strongly correlated with the patients going to bed and getting up from bed, respectively: After both events, TI exhibits a trend in negative respectively positive direction (p < 0.001, Page trend test), which leads to significant changes of TI over at least 6 hours (p < 0.001 for all measurement times, Wilcoxon signed-rank test). Figure: circadian variation of the thoracic impedance of a heart failure patient. Conclusion: Thoracic impedance exhibits a strong circadian variation, which amounts to 7 % of its absolute value and seems to be based on the sleep-wake rhythm. Therefore, daily TI values from a single measurement time per day are prone to errors of the same size, particularly when measured in high-dynamic phases. More appropriate is the use of either the mean or an extremal value of the TI day-curve from several equidistant measurement

Clinical applications of cardiac computed tomography: a consensus paper of the European Association of Cardiovascular Imaging-part I - Pontone, Gianluca; Rossi, Alexia; Guglielmo, Marco; Dweck, Marc R.; Gaemperli, Oliver; Nieman, Koen; Pugliese, Francesca; Maurovich-Horvat, Pal; Gimelli, Alessia; Cosyns, Bernard; Achenbach, Stephan (European Heart Journal - Cardiovascular Imaging, 2022)
Cardiac computed tomography (CT) was introduced in the late 1990's. Since then, an increasing body of evidence on its clinical applications has rapidly emerged. From an initial emphasis on its technical efficiency and diagnostic accuracy, research around cardiac CT has now evolved towards outcomes-based studies that provide information on prognosis, safety, and cost. Thanks to the strong and compelling data generated by large, randomized control trials, the scientific societies have endorsed cardiac CT as pivotal diagnostic test for the management of appropriately selected patients with acute and chronic coronary syndrome. This consensus document endorsed by the European Association of Cardiovascular Imaging is divided into two parts and aims to provide a summary of the current evidence and to give updated indications on the appropriate use of cardiac CT in different clinical scenarios. This first part focuses on the most established applications of cardiac CT from primary prevention in asymptomatic patients, to the evaluation of patients with chronic coronary syndrome, acute chest pain, and previous coronary revascularization.
CRIS-Team Scopus Importer:2022-03-04
Keywords: acute chest pain; chronic coronary syndrome; coronary artery bypass graft; coronary calcium; coronary computed tomography angiography; coronary stent

Clinical benefit of left atrial appendage closure in octogenarians - Mohrez, Yamen; Gloekler, Steffen; Schnupp, Steffen; Allakkis, Wasim; Liu, Xiao-Xia; Fuerholz, Monika; Brachmann, Johannes; Windecker, Stephan; Achenbach, Stephan; Meier, Bernhard; Kleinecke, Caroline (Journal of Geriatric Cardiology, 2021)
OBJECTIVES Whether left atrial appendage closure (LAAC) in octogenarians yield similar net clinical benefit compared to younger patients, was the purpose of the present study.
CRIS-Team WoS Importer:2022-02-25

Clinical Outcome of Fractional Flow Reserve (FFR) and Its Associated Alternate Indices During Practical Routine Clinical Procedures (PRESSUREwire Registry) - Berry, Colin; Achenbach, Stephan; Kumar, Gautam; Schampaert, Erick; Tanaka, Nobuhiro; Teraphongphom, Tarn; Ginn, Gregory; Zhang, Zhen; Somi, Samer; Amoroso, Giovanni; Knaapen, Paul; Krasnow, Joshua; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Clinical Performance of the Consensus Immunoscore in Colon Cancer in the Asian Population from the Multicenter International SITC Study - Mlecnik, Bernhard; Torigoe, Toshihiko; Bindea, Gabriela; Popivanova, Boryana; Xu, Mingli; Fujita, Tomonobu; Hazama, Shoichi; Suzuki, Nobuaki; Nagano, Hiroaki; Okuno, Kiyotaka; Hirohashi, Yoshihiko; Furuhata, Tomohisa; et al. (Cancers, 2022)
BACKGROUND: In this study, we evaluated the prognostic value of Immunoscore in patients with stage I–III colon cancer (CC) in the Asian population. These patients were originally included in an international study led by the Society for Immunotherapy of Cancer (SITC) on 2681 patients with AJCC/UICC-TNM stages I–III CC. METHODS: CD3+ and cytotoxic CD8+ T-lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The association of Immunoscore with prognosis was evaluated for time to recurrence (TTR), disease-free survival (DFS), and overall survival (OS). RESULTS: Immunoscore stratified Asian patients (n = 423) into different risk categories and was not impacted by age. Recurrence-free rates at 3 years were 78.5%, 85.2%, and 98.3% for a Low, Intermediate, and High Immunoscore, respectively (HR[Low-vs-High] = 7.26 (95% CI 1.75−30.19); p = 0.0064). A High Immunoscore showed a significant association with prolonged TTR, OS, and DFS (p < 0.05). In Cox multivariable analysis stratified by center, Immunoscore association with TTR was independent (HR[Low-vs-Int+High] = 2.22 (95% CI 1.10–4.55) p = 0.0269) of the patient’s gender, T-stage, N-stage, sidedness, and MSI status. A significant association of a High Immunoscore with prolonged TTR was also found among MSS (HR[Low-vs-Int+High] = 4.58 (95% CI 2.27−9.23); p ≤ 0.0001), stage II (HR[Low-vs-Int+High] = 2.72 (95% CI 1.35−5.51); p = 0.0052), low-risk stage-II (HR[Low-vs-Int+High] = 2.62 (95% CI 1.21−5.68); p = 0.0146), and high-risk stage II patients (HR[Low-vs-Int+High] = 3.11 (95% CI 1.39−6.91); p = 0.0055). CONCLUSION: A High Immunoscore is significantly associated with the prolonged survival of CC patients within the Asian population.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Asian; classification; colon cancer; immune response; Immunoscore; MSI; prognostic markers; risk stratification; T cell; tumor microenvironment

Clinical Predictors of Obstructive Coronary Artery Disease in Individuals with Suspected Coronary Artery Disease - Al'Aref, Subhi; Van Rosendael, Alexander; Maliakal, Gabriel; Singh, Gurpreet; Ma, Xiaoyue; Pandey, Mohit; Wang, Jing; Do, Virginie; Kim, Timothy Suyong; Gummalla, Manasa; Achenbach, Stephan; Al-Mallah, Mouaz; et al. (2018)
EVALuna2:35966

Clinical presentation does not affect acute mechanical performance of the Novolimus-eluting bioresorbable vascular scaffold as assessed by optical coherence tomography - Boeder, Niklas F.; Doerr, Oliver; Gaderer, Rosalina; Blachutzik, Florian; Achenbach, Stephan; Elsaesser, Albrecht; Hamm, Christian; Nef, Holger M. (Postepy W Kardiologii Interwencyjnej, 2021)
Introduction: Initial trials of bioresorbable vascular scaffolds (BVS) have mostly excluded patients presenting with acute coronary syndrome (ACS). However, these patients might benefit from a BVS platform, in particular as they are often younger and have been less frequently treated than patients with chronic disease. Aim: To compare the acute performance of a Novolimus eluting BVS in ACS and non-ACS patients using optical coherence tomography (OCT) in patients presenting with acute or chronic coronary syndrome. Material and methods: The final OCT pullback of 79 patients (34 with ACS, 45 non-ACS) was analysed at 1-mm intervals. The following indices were calculated: mean and minimal area, residual area stenosis, incomplete strut apposition, tissue prolapse, eccentricity index, symmetry index, strut fracture, and edge dissection. Results: OCT showed a minimum lumen area (non-ACS vs. ACS) of 6.2 +/- 2.1 vs. 5.6 +/- 1.5 mm2 (p = 0.21). Mean residual area stenosis was 14.5% vs. 19.5% (p = 0.39). The mean eccentricity index did not differ significantly (0.78 +/- 0.13 vs. 0.78 +/- 0.06; p = 0.42). There was a non-significant tendency for more fractures in the non-ACS group (22.2% vs. 5.9%; p = 0.07). Prolapse area was comparable (4.4 +/- 7.4 mm2 vs. 5.2 +/- 10.9 mm2; p = 0.62). Conclusions: This is the first study to investigate the acute mechanical performance of a Novolimus-eluting BVS in patients with different clinical presentations using OCT. We found that clinical presentation did not determine acute mechanical performance as assessed by the final OCT pullback. There was evidence of more mechanical complications in terms of fractures and a higher percentage of incomplete strut apposition in the group of patients with chronic coronary syndrome.
CRIS-Team WoS Importer:2021-11-19

Clinical presentation, shock severity and mortality in patients with de novo versus acute-on-chronic heart failure-related cardiogenic shock - Sundermeyer, Jonas; Kellner, Caroline; Beer, Benedikt N.; Besch, Lisa; Dettling, Angela; Bertoldi, Letizia Fausta; Blankenberg, Stefan; Dauw, Jeroen; Dindane, Zouhir; Eckner, Dennis; Eitel, Ingo; Graf, Tobias; et al. (European Journal of Heart Failure, 2023)
Aims: Heart failure-related cardiogenic shock (HF-CS) accounts for a significant proportion of CS cases. Whether patients with de novo HF and those with acute-on-chronic HF in CS differ in clinical characteristics and outcome remains unclear. The aim of this study was to evaluate differences in clinical presentation and mortality between patients with de novo and acute-on-chronic HF-CS. Methods and results: In this international observational study, patients with HF-CS from 16 tertiary care centres in five countries were enrolled between 2010 and 2021. To investigate differences in clinical presentation and 30-day mortality, adjusted logistic/Cox regression models were fitted. Patients (n = 1030) with HF-CS were analysed, of whom 486 (47.2%) presented with de novo HF-CS and 544 (52.8%) with acute-on-chronic HF-CS. Traditional markers of CS severity (e.g. blood pressure, heart rate and lactate) as well as use of treatments were comparable between groups. However, patients with acute-on-chronic HF-CS were more likely to have a higher CS severity and also a higher mortality risk, after adjusting for relevant confounders (de novo HF 45.5%, acute-on-chronic HF 55.9%, adjusted hazard ratio 1.38, 95% confidence interval 1.10–1.72, p = 0.005). Conclusion: In this large HF-CS cohort, acute-on-chronic HF-CS was associated with more severe CS and higher mortality risk compared to de novo HF-CS, although traditional markers of CS severity and use of treatments were comparable. These findings highlight the vast heterogeneity of patients with HF-CS, emphasize that HF chronicity is a relevant disease modifier in CS, and indicate that future clinical trials should account for this.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Acute-on-chronic heart failure; Cardiogenic shock; De novo heart failure; Heart failure

Clinical restenosis and its predictors after implantation of everolimus-eluting bioresorbable vascular scaffolds: results from GABI-R - Mehilli, Julinda; Achenbach, Stephan; Woehrle, Jochen; Baquet, Morritz; Riemer, Thomas; Muenzel, Thomas; Nef, Holger M.; Naber, Christoph; Richardt, Gert; Zahn, Ralf; Gori, Tommaso; Neumann, Till; et al. (EuroIntervention, 2017)
Aims: The aim of this study was to assess clinical restenosis and its predictors after implantation of bioresorbable vascular scaffolds (BVS) in everyday practice in the large-scale German-Austrian ABSORB Registry (GABI-R). Methods and results: Between November 2013 and January 2016, 3,264 patients underwent BVS implantation in the 93 centres of GABI-R (ClinicalTrials.gov NCT02066623). At six-month follow-up, 24 patients experienced clinically indicated target lesion revascularisation (cTLR) unrelated to BVS thrombosis (cumulative incidence 0.76%; angiographically, 58.3% of in-BVS restenosis of focal pattern). Compared to patients without cTLR, patients with cTLR had more lesions per patient (1.83 +/- 1.0 vs. 1.36 +/- 0.7), complex (52.3% vs. 36.2%) and mild-to-moderately calcified lesions (65.9% vs. 60.5%) treated, and more frequently had overlapping BVS (22.2% vs. 10.8%), all p<0.05. Implanted BVS length was 40.0 mm (28.0, 46.9) vs. 23.0 mm (18.0, 30.0), p<0.001, remaining in the multivariable analysis the only independent predictor of cTLR (hazard ratio 1.02, 95% CI: 1.01-1.04, p<0.001). The myocardial infarction rate was also significantly higher among patients with cTLR, 29.2% vs. 1.7%, p<0.0001. Conclusions: cTLR related to BVS restenosis at six months after BVS implantation is a rare event depending on implanted BVS length. Whether cTLR increases the myocardial infarction risk needs to be evaluated at longer-term follow-up and within the setting of adequately powered randomised trials.
EVALuna2:36016

Clinical risk factors and atherosclerotic plaque extent to define risk for major events in patients without obstructive coronary artery disease: the long-term coronary computed tomography angiography CONFIRM registry - van Rosendael, Alexander R.; Bax, A. Maxim; Smit, Jeff M.; van den Hoogen, Inge J.; Ma, Xiaoyue; Al'Aref, Subhi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; et al. (European Heart Journal - Cardiovascular Imaging, 2020)
AIMS: In patients without obstructive coronary artery disease (CAD), we examined the prognostic value of risk factors and atherosclerotic extent. METHODS AND RESULTS: Patients from the long-term CONFIRM registry without prior CAD and without obstructive (≥50%) stenosis were included. Within the groups of normal coronary computed tomography angiography (CCTA) (N = 1849) and non-obstructive CAD (N = 1698), the prognostic value of traditional clinical risk factors and atherosclerotic extent (segment involvement score, SIS) was assessed with Cox models. Major adverse cardiac events (MACE) were defined as all-cause mortality, non-fatal myocardial infarction, or late revascularization. In total, 3547 patients were included (age 57.9 ± 12.1 years, 57.8% male), experiencing 460 MACE during 5.4 years of follow-up. Age, body mass index, hypertension, and diabetes were the clinical variables associated with increased MACE risk, but the magnitude of risk was higher for CCTA defined atherosclerotic extent; adjusted hazard ratio (HR) for SIS >5 was 3.4 (95% confidence interval [CI] 2.3-4.9) while HR for diabetes and hypertension were 1.7 (95% CI 1.3-2.2) and 1.4 (95% CI 1.1-1.7), respectively. Exclusion of revascularization as endpoint did not modify the results. In normal CCTA, presence of ≥1 traditional risk factors did not worsen prognosis (log-rank P = 0.248), while it did in non-obstructive CAD (log-rank P = 0.025). Adjusted for SIS, hypertension and diabetes predicted MACE risk in non-obstructive CAD, while diabetes did not increase risk in absence of CAD (P-interaction = 0.004). CONCLUSION: Among patients without obstructive CAD, the extent of CAD provides more prognostic information for MACE than traditional cardiovascular risk factors. An interaction was observed between risk factors and CAD burden, suggesting synergistic effects of both.
CRIS-Team Scopus Importer:2020-05-15
Keywords: atherosclerosis; coronary computed tomography angiography; imaging; preventive cardiology; risk stratification

Clinician Well-Being: Addressing Global Needs for Improvements in the Health Care Field A Joint Opinion From the American College of Cardiology, American Heart Association, European Society of Cardiology, and the World Heart Federation - Mehta, Laxmi S.; Elkind, Mitchell S.V.; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena (Journal of the American College of Cardiology, 2021)
CRIS-Team Scopus Importer:2021-08-06
Keywords: burnout; practice efficiency; professional fulfillment; resiliency; well-being

Clinician Well-Being-addressing global needs for improvements in the health care field: a joint opinion from the American College of Cardiology, American Heart Association, European Society of Cardiology, World Heart Federation. - Mehta, Laxmi S.; Elkind, Mitchell S.; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena (European Heart Journal, 2021)
EVALuna2:482748

Clinician well-being: Addressing global needs for improvements in the health care field - Mehta, Laxmi S.; Elkind, Mitchell S.V.; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena (Global Heart, 2021)
CRIS-Team Scopus Importer:2021-08-06
Keywords: Burnout; Practice efficiency; Professional fulfillment; Resiliency; Well-being

CODE-EHR best practice framework for the use of structured electronic healthcare records in clinical research. - Kotecha, Dipak; Asselbergs, Folkert W.; Achenbach, Stephan; Anker, Stefan D.; Atar, Dan; Baigent, Colin; Banerjee, Amitava; Beger, Birgit; Brobert, Gunnar; Casadei, Barbara; Ceccarelli, Cinzia; Cowie, Martin R.; et al. (British Medical Journal, 2022)
Big data is central to new developments in global clinical science aiming to improve the lives of patients. Technological advances have led to the routine use of structured electronic healthcare records with the potential to address key gaps in clinical evidence. The covid-19 pandemic has demonstrated the potential of big data and related analytics, but also important pitfalls. Verification, validation, and data privacy, as well as the social mandate to undertake research are key challenges. The European Society of Cardiology and the BigData@Heart consortium have brought together a range of international stakeholders, including patient representatives, clinicians, scientists, regulators, journal editors and industry. We propose the CODE-EHR Minimum Standards Framework as a means to improve the design of studies, enhance transparency and develop a roadmap towards more robust and effective utilisation of healthcare data for research purposes.
EVALuna2:545523

CODE-EHR best practice framework for the use of structured electronic healthcare records in clinical research - Kotecha, Dipak; Asselbergs, Folkert W.; Achenbach, Stephan; Anker, Stefan D.; Atar, Dan; Baigent, Colin; Banerjee, Amitava; Beger, Birgit; Brobert, Gunnar; Casadei, Barbara; Ceccarelli, Cinzia; Cowie, Martin R.; et al. (European Heart Journal, 2022)
Big data is central to new developments in global clinical science aiming to improve the lives of patients. Technological advances have led to the routine use of structured electronic healthcare records with the potential to address key gaps in clinical evidence. The covid-19 pandemic has demonstrated the potential of big data and related analytics, but also important pitfalls. Verification, validation, and data privacy, as well as the social mandate to undertake research are key challenges. The European Society of Cardiology and the BigData@Heart consortium have brought together a range of international stakeholders, including patient representatives, clinicians, scientists, regulators, journal editors and industry. We propose the CODE-EHR Minimum Standards Framework as a means to improve the design of studies, enhance transparency and develop a roadmap towards more robust and effective utilisation of healthcare data for research purposes.
CRIS-Team WoS Importer:2022-09-09

CODE-EHR best-practice framework for the use of structured electronic health-care records in clinical research. - Kotecha, Dipak; Asselbergs, Folkert W.; Achenbach, Stephan; Anker, Stefan D.; Atar, Dan; Baigent, Colin; Banerjee, Amitava; Beger, Birgit; Brobert, Gunnar; Casadei, Barbara; Ceccarelli, Cinzia; Cowie, Martin R.; et al. (The Lancet Digital Health, 2022)
Big data is important to new developments in global clinical science that aim to improve the lives of patients. Technological advances have led to the regular use of structured electronic health-care records with the potential to address key deficits in clinical evidence that could improve patient care. The COVID-19 pandemic has shown this potential in big data and related analytics but has also revealed important limitations. Data verification, data validation, data privacy, and a mandate from the public to conduct research are important challenges to effective use of routine health-care data. The European Society of Cardiology and the BigData@Heart consortium have brought together a range of international stakeholders, including representation from patients, clinicians, scientists, regulators, journal editors, and industry members. In this Review, we propose the CODE-EHR minimum standards framework to be used by researchers and clinicians to improve the design of studies and enhance transparency of study methods. The CODE-EHR framework aims to develop robust and effective utilisation of health-care data for research purposes.
EVALuna2:545525

Combination of computed tomography angiography with coronary artery calcium score for improved diagnosis of coronary artery disease: a collaborative meta-analysis of stable chest pain patients referred for invasive coronary angiography - Mohamed, Mahmoud; Bosserdt, Maria; Wieske, Viktoria; Dubourg, Benjamin; Alkadhi, Hatem; Garcia, Mario J.; Leschka, Sebastian; Zimmermann, Elke; Shabestari, Abbas A.; Nørgaard, Bjarne L.; Meijs, Matthijs F.L.; Øvrehus, Kristian A.; et al. (European Radiology, 2023)
Objectives: Coronary computed tomography angiography (CCTA) has higher diagnostic accuracy than coronary artery calcium (CAC) score for detecting obstructive coronary artery disease (CAD) in patients with stable chest pain, while the added diagnostic value of combining CCTA with CAC is unknown. We investigated whether combining coronary CCTA with CAC score can improve the diagnosis of obstructive CAD compared with CCTA alone. Methods: A total of 2315 patients (858 women, 37%) aged 61.1 ± 10.2 from 29 original studies were included to build two CAD prediction models based on either CCTA alone or CCTA combined with the CAC score. CAD was defined as at least 50% coronary diameter stenosis on invasive coronary angiography. Models were built by using generalized linear mixed-effects models with a random intercept set for the original study. The two CAD prediction models were compared by the likelihood ratio test, while their diagnostic performance was compared using the area under the receiver-operating-characteristic curve (AUC). Net benefit (benefit of true positive versus harm of false positive) was assessed by decision curve analysis. Results: CAD prevalence was 43.5% (1007/2315). Combining CCTA with CAC improved CAD diagnosis compared with CCTA alone (AUC: 87% [95% CI: 86 to 89%] vs. 80% [95% CI: 78 to 82%]; p < 0.001), likelihood ratio test 236.3, df: 1, p < 0.001, showing a higher net benefit across almost all threshold probabilities. Conclusion: Adding the CAC score to CCTA findings in patients with stable chest pain improves the diagnostic performance in detecting CAD and the net benefit compared with CCTA alone. Clinical relevance statement: CAC scoring CT performed before coronary CTA and included in the diagnostic model can improve obstructive CAD diagnosis, especially when CCTA is non-diagnostic. Key Points: • The combination of coronary artery calcium with coronary computed tomography angiography showed significantly higher AUC (87%, 95% confidence interval [CI]: 86 to 89%) for diagnosis of coronary artery disease compared to coronary computed tomography angiography alone (80%, 95% CI: 78 to 82%, p < 0.001). • Diagnostic improvement was mostly seen in patients with non-diagnostic C. • The improvement in diagnostic performance and the net benefit was consistent across age groups, chest pain types, and genders.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Computed tomography angiography; Coronary angiography; Coronary artery disease

Combined therapy of empagliflozin and linagliptin is superior to metformin and insulin glargine in improving blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, D.; Karg, M.; Striepe, Kristina; Bramlage, P.; Ott, Christian; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Commissural misalignment independently predicts leaflet thrombosis after transcatheter aortic valve implantation - Jung, Susanne; Ammon, Fabian; Smolka, Silvia; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Stephan (Clinical Research in Cardiology, 2023)
Aims: Transcatheter aortic valve implantation (TAVI) has become a minimally invasive alternative to surgical aortic valve replacement. Hypo-attenuated leaflet thickening (HALT)—a marker of subclinical leaflet thrombosis commonly detected by cardiac computed tomography (CT) after TAVI—may influence valve durability and function. The purpose of this study was to compare commissural alignment of the native and prosthetic aortic valves in cardiac CT in subjects with and without HALT and thereby identify commissural misalignment as potential predictor for leaflet thrombosis after TAVI. Methods and results: In 170 subjects, 85 with and 85 without HALT in post-TAVI CT, commissural orientation of the prosthesis was determined comparing native and prosthetic aortic valve orientation in cardiac CT by measuring the commissural angle relative to the right coronary ostium in the aortic valve plane. For the prosthetic valve, any deviation ≤ 15° compared to the native valve was classified as “aligned”; 16–30° as “mild”, 31–45° as “moderate” and ≥ 45° as “severe” misalignment. Among subjects with HALT, median angular deviation was higher (36°, IQR 31°) than in the control group (29°, IQR 29°, p = 0.042). “Severe” misalignment was more frequent in subjects who developed HALT (n = 31, 37%) compared to the control group (n = 17, 20%, p = 0.013). In logistic regression analysis, more severe deviation (p = 0.015, OR = 1.02 per 1° deviation) and “severe” misalignment (p = 0.018, OR = 2.2) represented independent predictors for the occurrence of HALT after TAVI. Conclusion: Subclinical leaflet thrombosis after TAVI is associated with commissural misalignment. Potential clinical advantages of obtaining commissural alignment remain to be systematically assessed. Graphical abstract: [Figure not available: see fulltext.] Association of HALT with commissural misalignment after TAVI. HALT hypo-attenuated leaflet thickening, IQR interquartile range, TAVI transfemoral aortic valve replacement
CRIS-Team Scopus Importer:2023-04-21
Keywords: Commissural misalignment; HALT; Leaflet thrombosis; TAVI

Comparative assessment of image quality for coronary CT angiography with iobitridol and two contrast agents with higher iodine concentrations: iopromide and iomeprol. A multicentre randomized double-blind trial - Achenbach, Stephan; Paul, Jean-Francois; Laurent, Francois; Becker, Hans-Christoph; Rengo, Marco; Caudron, Jerome; Leschka, Sebastian; Vignaux, Olivier; Knobloch, Gesine; Benea, Giorgio; Schlosser, Thomas; Andreu, Jordi; et al. (European Radiology, 2017)
OBJECTIVES: To demonstrate non-inferiority of iobitridol 350 for coronary CT angiography (CTA) compared to higher iodine content contrast media regarding rate of patients evaluable for the presence of coronary artery stenoses. METHODS: In this multicentre trial, 452 patients were randomized to receive iobitridol 350, iopromide 370 or iomeprol 400 and underwent coronary CTA using CT systems with 64-detector rows or more. Two core lab readers assessed 18 coronary segments per patient regarding image quality (score 0 = non diagnostic to 4 = excellent quality), vascular attenuation, signal and contrast to noise ratio (SNR, CNR). Patients were considered evaluable if no segment had a score of 0. RESULTS: Per-patient, the rate of fully evaluable CT scans was 92.1, 95.4 and 94.6 % for iobitridol, iopromide and iomeprol, respectively. Non-inferiority of iobitridol over the best comparator was demonstrated with a 95 % CI of the difference of [-8.8 to 2.1], with a pre-specified non-inferiority margin of -10 %. Although average attenuation increased with higher iodine concentrations, average SNR and CNR did not differ between groups. CONCLUSIONS: With current CT technology, iobitridol 350 mg iodine/ml is not inferior to contrast media with higher iodine concentrations in terms of image quality for coronary stenosis assessment. KEY POINTS: • Iodine concentration is an important parameter for image quality in coronary CTA. • Contrast enhancement must be balanced against the amount of iodine injected. • Iobitridol 350 is non-inferior compared to CM with higher iodine concentrations. • Higher attenuation with higher iodine concentrations, but no SNR or CNR differences.
EVALuna2:33652

Comparison between core-lab and site-read assessment of coronary CT angiography for detection of ischemia-causing lesions: a substudy of the NXT trial - Marwan, M.; Gaur, S.; Leipsic, J.; Seneviratne, S.; Ito, H.; Mauri, L.; De Bruyne, B.; Bezerra, H.; Naber, C.; Park, S. J.; Achenbach, Stephan (2016)
EVALuna2:33689

Comparison between treatment of "established" versus complex "off-label" coronary lesions with Absorb bioresorbable scaffold implantation: results from the GABI-R registry - Huseynov, A.; Baumann, S.; Nef, H.; Riemer, T.; Schneider, S.; Pfannebecker, T.; Achenbach, Stephan; Mehilli, J.; Gori, T.; Woehrle, J.; Zahn, R.; Schmermund, A.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Comparison between treatment of “established” versus complex “off-label” coronary lesions with Absorb® bioresorbable scaffold implantation: results from the GABI-R® registry - Huseynov, Aydin; Baumann, Stefan; Nef, Holger; Riemer, Thomas; Schneider, Steffen; Pfannenbecker, Thomas; Achenbach, Stephan; Mehilli, Julinda; Münzel, Thomas; Gori, Tommaso; Wöhrle, Jochen; Zahn, Ralf; et al. (Clinical Research in Cardiology, 2019)
Objectives: The purpose of this study was to compare the clinical outcomes of patients treated with bioresorbable scaffold (BRS) for off-label versus approved indications. Background: The BRS promised some advantages in terms of complete biodegradation within 2–4 years, restored vascular physiology, and absence of potential stent-related long-term complications. However, the implication of BRS for off-label indications and further long-term follow-up of this particular patient group is not well described. Methods: The short- and long-term outcome after implantation of an everolimus-eluting, poly-l-lactic acid-based bioresorbable scaffold system (ABSORB, Abbott Vascular, Santa Clara, CA, USA) was evaluated in the prospective, non-interventional, multicenter real-world German–Austrian ABSORB RegIstRy (GABI-R). Results: A total of 3188 patients were enrolled. Patients were divided into two groups: on-label BRS use (33.0%) and off-label use (66.9%) if at least one off-label use criteria was met. The incidence of scaffold thrombosis in confirmed cases was significantly higher in off-label group (1.3% versus 0.5%, p = 0.04; OR 2.41 (95% CI 1.00–5.82) with also a trend toward higher myocardial infarction rate (2.3% versus 1.4%, p = 0.077; OR 1.70 (95% CI 0.95–3.03) and cardiovascular death (1.2% versus 1.1%, p = 0.76, OR 1.11 (95% CI 0.56–2.21) at 6-month follow-up. Conclusions: In a real-world setting, the majority patients were treated with BRS for off-label indications. The off-label use of BRS compared to confirmed indications appears to be associated with a higher rate of clinical endpoints considering more complex lesions and higher morbidity in this patients’ group. Graphic abstract: Comparison between treatment of “established” versus complex “off-label” coronary lesions with Absorb® bioresorbable scaffold implantation: results from the GABI-R® registry.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-09
Keywords: Bioresorbable scaffold; Coronary artery disease; Off-label use; Real-world population

Comparison in Patients < 75 Years of Age - Versus – Those > 75 Years on One-year-Events With Atrial Fibrillation and Left Atrial Appendage Occluder (From the Prospective Multicenter German LAARGE Registry) - Nasasra, Aref El; Brachmann, Johannes; Lewalter, Thorsten; Akin, Ibrahim; Sievert, Horst; Nienaber, Christoph A.; Weiß, Christian; Pleger, Sven T.; Ince, Hüseyin; Maier, Jens; Achenbach, Stephan; Sigusch, Holger H.; et al. (American Journal of Cardiology, 2020)
Left atrial appendage closure (LAAC) is an alternative to oral anticoagulation therapy in patients with non-valvular atrial fibrillation for the prevention of embolic stroke and systemic embolism. Although elderly patients (>75 years) have both higher ischemic and bleeding risk as compared with younger patients, they benefit from optimal anticoagulation. The subanalysis aimed to assess the indications, the safety, efficacy, and 1-year outcomes of interventional LAAC in elderly patients (≥ 75 years) compared with younger (< 75 years) patients in clinical practice. We analyzed data from the prospective Left-Atrium-Appendage Occluder Registry Germany. A total of 638 patients were included in the registry, 402 (63%) were aged ≥ 75 years. Compared with younger subjects, patients aged ≥75 were more likely to have higher CHA2DS2-VASC and HAS-BLED scores. Procedural success rate was high und similar in both groups (97.6%). Periprocedural adverse events were not statistically significant in groups (11.9% in <75 years vs 12.9% in ≥75 years; p = 0.80). At 1 year follow-up, all-cause mortality was higher in patients aged ≥75 compared withwith younger group (13.0% vs 7.8 %,p = 0.04), mainly due to non-cardiovascular causes (10.6% vs 6.0%). No significant differences in major bleeding, stroke, systemic embolism were observed. In conclusion, LAAC is feasible and safe in patients with AF at high stroke risk and with contraindications for OAC and should be considered as candidates for LAA closure. Elderly patients often present these characteristics and could benefit from this novel therapy.
CRIS-Team Scopus Importer:2020-10-09

Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Comparison of aortic valve annulus diameter determination through 3-dimensional transesophageal echo with cardiac MDCT and assessment of predictors for annulus sizing - Anger, Thomas; Schmid, Michael; Geisler, Tobias; Gawaz, Meinrad P.; Oberhoff, Martin; Hoeher, Martin (Journal of Heart Valve Disease, 2015)
The long-term success of CoreValve stent prosthesis (Medtronic) implantation for severe aortic valve stenosis is limited in determination of correct aortic valve annulus.We retrospectively investigated preinterventional cardiac 256-slice computed tomography (cardiac CT) scans and 3-dimensional transesophageal echocardiography (3D TEE) for assessment of aortic valve annulus to (i) compare both methods as well as (ii) to define predictors for annulus sizing.We investigated 200 consecutive patients with a mean aortic valve annulus (AA) of 24mm and a mean age of 81 years. Primarily we defined mean diameters of AA individually and grouped the different patients according to age, gender, body weight, length, surface area and body mass index. Thereby, we found statistical significant different annulus diameter in age (larger diameter when < 80 years of age), gender (male > femal), and body length (larger diameter when length > 165cm). Secondly, the multivariate analysis demonstrated that the age, the gender and the body length were additionally independent predictors for annulus size.Our data demonstrate the feasibility of cardiac CT and 3D TEE with no difference in the quality of the aortic valve annulus diameter determination. We describe predictors for annulus size in age, gender and body length. Conclusive, we support patient dependent parameters as age, gender and body length as predictors that must go into selection of CoreValve stent prosthesis size individually prior to implantation procedure.
EVALuna2:12054

Comparison of Coronary Atherosclerotic Plaque Burden and Composition as Assessed on Coronary Computed Tomography Angiography in East Asian and European-Origin Caucasians - Ihdayhid, Abdul Rahman; Göller, Markus; Dey, Damini; Nerlekar, Nitesh; Yap, Grace; Thakur, Udit; Adams, Daniel; Cameron, James; Seneviratne, Sujith; Achenbach, Stephan; Ko, Brian (American Journal of Cardiology, 2019)
Recent evidence suggests plaque morphology evaluated on coronary computed tomography angiography has prognostic implications. East Asians have a lower prevalence of myocardial infarction and cardiovascular mortality compared with European-origin Caucasians. We aimed to compare coronary atherosclerotic burden and plaque composition in a matched cohort of Caucasian and East Asians patients with stable chest pain who underwent computed tomography angiography. Two-hundred symptomatic patients (age 58.8 ± 7.9, male 51%) were matched for age, gender, body mass index, and diabetes (100 each ethnic group). A blinded core-laboratory quantified calcified and noncalcified plaque (NCP) volume and burden. Components of NCP were differentiated by plaque hounsfield unit (HU) thresholds which defined high-risk necrotic core (−30 to 30HU), fibrofatty plaque (31 to 130HU); and low-risk fibrous plaque (131 to 350HU). Composition of NCP components was derived as (NCP component volume/total NCP volume) × 100%. Segment Involvement Score, percent diameter and area stenosis were comparable in both groups. Similarly, there was no difference in the volume and burden of total, calcified and NCP. Compared with Caucasians, East Asians demonstrated lower composition of plaque attenuation corresponding to necrotic core (3.5 vs 5.1%; p = 0.004) and fibrofatty plaque (29.6 vs 37.3%; p = 0.005), and higher fibrous plaque (65.7 vs 57.6%; p = 0.004). On multivariable analysis East Asian ethnicity was independently associated with lower composition of high-risk plaque after adjustment for risk factors and scan parameters. These findings were consistent in a propensity-matched sensitivity-analysis. In conclusion, based on this matched cohort, East Asian ethnicity is associated with significantly less composition of high-risk NCP (necrotic core and fibrofatty plaque) and a higher composition of low-risk fibrous plaque compared with Caucasians; which may confer a lower risk of cardiovascular events.
CRIS-Team Scopus Importer:2019-09-03

Comparison of Coronary Intravascular Lithotripsy and Rotational Atherectomy in the Modification of Severely Calcified Stenoses - Blachutzik, Florian; Meier, Sophie; Weissner, Melissa; Schlattner, Sophia; Gori, Tommaso; Ullrich-Daub, Helen; Gaede, Luise; Achenbach, Stephan; Möllmann, Helge; Chitic, Bogdan; Aksoy, Adem; Nickenig, Georg; et al. (American Journal of Cardiology, 2023)
Debulking techniques are often necessary for successful lesion preparation in percutaneous coronary intervention. The aim of this study was to compare plaque modification of severely calcified lesions by coronary intravascular lithotripsy (IVL) with that of rotational atherectomy (RA) using optical coherence tomography (OCT). ROTA.shock was a 1:1 randomized, prospective, double-arm, multicenter noninferiority trial designed to compare final minimal stent area after IVL with RA for lesion preparation in percutaneous coronary interventional treatment of severely calcified lesions. On the basis of OCT acquired before and immediately after IVL or RA in 21 of the 70 patients included, we performed a detailed analysis of the modification of the calcified plaque. After RA and IVL, calcified plaque fractures were present in 14 of the patients (67%), with a significantly greater number of fractures after IVL (3.23 ± 0.49) than after RA (1.67 ± 0.52; p < 0.001). Plaque fractures after IVL were longer than after RA (IVL: 1.67 ± 0.43 mm vs RA: 0.57 ± 0.55 mm; p = 0.01), resulting in a greater total volume of the fractures (IVL: 1.47 ± 0.40 mm3 vs RA: 0.48 ± 0.27 mm3; p = 0.003). Use of RA was associated with a greater acute lumen gain than was use of IVL (RA: 0.46 ± 0.16 mm2 vs IVL: 0.17 ± 0.14 mm2; p = 0.03). In conclusion, we were able to show differences in plaque modification of calcified coronary lesions by OCT: although RA leads to a greater acute lumen gain, IVL induces more and longer fractures of the calcified plaque.
CRIS-Team Scopus Importer:2023-04-07

Comparison of direct oral anticoagulants to vitamin-K antagonists as treatment for leaflet thrombosis after Transcatheter Aortic Valve Implantation (TAVI) - Ferstl, Paul; Marwan, Mohamed; Achenbach, Stephan; Bittner, Daniel (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Comparison of Dual-Source Computed Tomography for the Quantification of the Aortic Valve Area in Patients With Aortic Stenosis Versus Transthoracic Echocardiography and Invasive Hemodynamic Assessment - Ropers, Dieter; Ropers, Ulrike; Marwan, Mohamed; Schepis, Titiano; Pflederer, Tobias; Wechsel, Martin; Klinghammer, Lutz; Flachskampf, Frank A.; Daniel, Werner; Achenbach, Stephan (American Journal of Cardiology, 2009)
We compared the measurements of the aortic valve area (AVA) using dual-source computed tomography (DSCT) in patients with mid to severe aortic stenosis to measurements using transthoracic echocardiography (TTE) and invasive hemodynamic assessment. A total of 50 patients (mean age 73 ± 10 years) with suspected aortic stenosis were included. The computed tomographic data were acquired using DSCT with standardized scan parameters (2 × 64 × 0.6 mm collimation, 330-ms rotation, 120-kV tube voltage, 560 mA/rot tube current). After injection of 35 ml contrast agent (flow rate 5 ml/s), a targeted volume data set, ranging from the top of the leaflets to the infundibulum, was acquired. Ten cross-sectional data sets (slice thickness 1 mm, no overlap, increment 0.6 mm) were reconstructed during systole in 5% increments of the R-R interval. The AVA determined in systole by planimetry was compared to the calculated AVA values using the continuity equation on TTE and the Gorlin formula on catheterization. DSCT allowed the planimetry of the AVA in all patients. The mean AVA using DSCT was 1.16 ± 0.47 cm2 compared to a mean AVA of 1.04 ± 0.45 cm2 using TTE and 1.06 ± 0.45 cm2 using catheterization, with a significant correlation between DSCT/TTE (r = 0.93, p <0.001) and DSCT/cardiac catheterization (r = 0.97, p <0.001). However, DSCT demonstrated a slight, but significant, overestimation of the AVA compared to TTE (+0.12 ± 0.17 cm) and catheterization (+0.10 ± 0.12 cm2). In conclusion, DSCT permits one to assess the AVA with a high-image quality and diagnostic accuracy compared to TTE and invasive determination. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

Comparison of Exo-Seal(®) and Angio-Seal (®) for arterial puncture site closure: A randomized, multicenter, single-blind trial - Ketterle, Johannes; Rittger, Harald; Helmig, Inga; Klinghammer, Lutz; Zimmermann, Stefan; Hohenforst-Schmidt, Wolfgang; Brachmann, Johannes; Nef, Holger; Achenbach, Stephan; Schlundt, Christian (Herz, 2015)
The use of extravascular femoral closure devices in patients undergoing coronary angiography/intervention has not been sufficiently evaluated. We sought to define the impact of an extravascular polyglycolic acid (PGA) plug for the closure of a femoral access site in patients undergoing coronary angiography and/or percutaneous coronary intervention.In this prospective, single-blind, multicenter trial we randomly assigned 319 patients to vessel closure with Angio-Seal(®) or Exo-Seal(®). We hypothesized that the use of an extravascular closure device is not inferior to an anchor/plug-mediated device regarding the occurrence of the composite primary endpoint: hematoma > 5 cm, significant groin bleeding (TIMI major bleed), false aneurysm, and device failure.There was no significant difference in patient baseline characteristics or procedural results. After 24 h the primary endpoint occurred in nine patients (5.6 %) in the Angio-Seal(®) group and in 13 patients (8.2 %) inthe Exo-Seal(®) group (p = 0.38). Hematoma > 5 cm was noted in three patients (1.9 %) receiving Angio-Seal(®) vs. two patients (1.3 %) receiving Exo-Seal(®) (p = 0.99). In one patient (0.6 %) of the Exo-Seal(®) group, TIMI major bleeding occurred, requiring transfusion (p = 0.49). There were four (2.5 %) false aneurysms found in patients treated with Angio-Seal(®) and two (1.3 %) in patients treated with Exo-Seal(®) (p = 0.68). There was a trend for a higher incidence of device failure in the Exo-Seal(®) group (1.2 vs. 5.2 %, p = 0.06). At telephone interview after 30 days, there was no significant difference found regarding the events readmission with surgery of puncture site, infection, bleeding, hematoma, or pain.In the present study, there were no significant differences found regarding the occurrence of hematoma > 5 cm, major bleeding, false aneurysm, and device failure between Angio-Seal(®) and Exo-Seal(®) 24 h after device implantation.
EVALuna2:12086

Comparison of fractional flow reserve and instantaneous wave-free ratio for the hemodynamic assessment of jailed side branches in bifurcation stenting - Altstidl, J. M.; Tröbs, Monique; Achenbach, Stephan; Gaede, L.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Comparison of Fractional Flow Reserve Based on Computational Fluid Dynamics Modeling Using Coronary Angiographic Vessel Morphology Versus Invasively Measured Fractional Flow Reserve - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Redel, Thomas; Scheuering, Michael; Winneberger, David; Klingenbeck, Klaus; Itu, Lucian; Passerini, Tiziano; Kamen, Ali; Sharma, Puneet; Comaniciu, Dorin; et al. (American Journal of Cardiology, 2016)
Invasive fractional flow reserve (FFRinvasive), although gold standard to identify hemodynamically relevant coronary stenoses, is time consuming and potentially associated with complications. We developed and evaluated a new approach to determine lesion-specific FFR on the basis of coronary anatomy as visualized by invasive coronary angiography (FFRangio): 100 coronary lesions (50% to 90% diameter stenosis) in 73 patients (48 men, 25 women; mean age 67 ± 9 years) were studied. On the basis of coronary angiograms acquired at rest from 2 views at angulations at least 30° apart, a PC-based computational fluid dynamics modeling software used personalized boundary conditions determined from 3-dimensional reconstructed angiography, heart rate, and blood pressure to derive FFRangio. The results were compared with FFRinvasive. Interobserver variability was determined in a subset of 25 narrowings. Twenty-nine of 100 coronary lesions were hemodynamically significant (FFRinvasive <=0.80). FFRangio identified these with an accuracy of 90%, sensitivity of 79%, specificity of 94%, positive predictive value of 85%, and negative predictive value of 92%. The area under the receiver operating characteristic curve was 0.93. Correlation between FFRinvasive (mean: 0.84 ± 0.11) and FFRangio (mean: 0.85 ± 0.12) was r = 0.85. Interobserver variability of FFRangio was low, with a correlation of r = 0.88. In conclusion, estimation of coronary FFR with PC-based computational fluid dynamics modeling on the basis of lesion morphology as determined by invasive angiography is possible with high diagnostic accuracy compared to invasive measurements.
EVALuna2:12050

Comparison of intracoronary versus intravenous administration of adenosine for measurement of coronary fractional flow reserve - Schlundt, Christian; Bietau, Christian; Klinghammer, Lutz; Wiedemann, Ricarda; Rittger, Harald; Ludwig, Josef; Achenbach, Stephan (Circulation: Cardiovascular Interventions, 2015)
Measurement of fractional flow reserve (FFR) constitutes the current gold standard to evaluate the hemodynamic significance of coronary stenoses. Limited data validate the intracoronary application of adenosine against standard intravenous infusion. We systematically compared FFR measurements during intracoronary and intravenous application of adenosine about agreement and reproducibility.We included 114 patients with an intermediate degree of stenosis in coronary angiography. Two FFR measurements were performed during intracoronary bolus injection (40 ?g for the right and 80 ?g for the left coronary artery, FFRic), and 2 FFR measurements during continuous intravenous infusion of adenosine (140 ?g/kg per minute, FFRiv). FFR value, the time to reach FFR and patient discomfort (on a subjective scale from 0 for no symptoms to 5 for maximal discomfort) were recorded for each measurement. Mean time to FFR was 100 ± 27 s for continuous intravenous infusion versus 23 ± 14 s for intracoronary bolus administration of adenosine (P < 0.001). Reported discomfort after intracoronary application was significantly lower compared with intravenous adenosine (subjective scale > 0 in 35.1% versus 87.7% of the patients; P < 0.001). Correlation between FFRiv and FFRic was extremely close (r = 0.99; P < 0.001) with no systematic bias in Bland-Altman analysis (bias 0.002 [confidence interval, -0.001 to 0.005]) and low intermethod variability (1.56%). Intramethod variability was not different between intravenous and intracoronary administration (1.47% versus 1.33%; P=0.5).Intracoronary bolus injection of adenosine (40 ?g for the right and 80 ?g for the left coronary artery) yields identical FFR results compared with intravenous infusion (140 ?g/kg per minute), while requiring less time and offering superior patient comfort.
EVALuna2:12052

Comparison of invasively measured FFR with FFR derived from coronary CT angiography for detection of lesion-specific ischemia: Results from a PC-based prototype algorithm - Röther, Jens; Moshage, Maximilian; Dey, Damini; Schwemmer, Chris; Tröbs, Monique; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We evaluated the diagnostic accuracy of a novel prototype for on-site determination of CT-based FFR (cFFR) on a standard personal computer (PC) compared to invasively measured FFR in patients with suspected coronary artery disease. METHODS: A total of 91 vessels in 71 patients (mean age 65 ± 9 years) in whom coronary CT angiography had been performed due to suspicion of coronary artery disease, and who subsequently underwent invasive coronary angiography with FFR measurement were analyzed. For both cFFR and FFR, a threshold of ≤0.80 was used to indicate a hemodynamically relevant stenosis. The mean time needed to calculate cFFR was 12.4 ± 3.4 min. A very close correlation between cFFR and FFR could be shown (r = 0.85; p < 0.0001) with Bland-Altman analysis showing moderate agreement between FFR and cFFR with mild systematic overestimation of FFR values in CT (mean difference 0.0049, 95% limits of agreement ±2SD -0.007 to 0.008). Compared to FFR, the sensitivity of cFFR to detect hemodynamically significant lesions was 91% (19/21, 95% CI: 70%-99%), specificity was 96% (67/70, 95% CI: 88%-99%), positive predictive value 86% (95% CI: 65%-97%) and negative predictive value was 97% (95% CI: 90%-100%) with an accuracy of 93%. CONCLUSION: cFFR obtained using an on-site algorithm implemented on a standard PC shows high diagnostic accuracy to detect lesions causing ischemia as compared to FFR. Importantly, the time needed for analysis is short which may be useful for improving clinical workflow.
EVALuna2:36006

Comparison of oral anticoagulation by vitamin-K antagonists and non-vitamin-K antagonists for treatment of leaflet thickening after transcatheter aortic valve implantation (TAVI) - Ferstl, Paul; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (International Journal of Cardiology, 2023)
Introduction: Hypoattenuated leaflet thickening (HALT), as identified by CT imaging, is not infrequent after transcatheter aortic valve implantation (TAVI). The best choice of oral anticoagulation is unknown. We compared the effectiveness of Direct Oral AntiCoagulants (DOAC) and Vitamin-K Antagonists (VKA) to resolve HALT in patients with serial CT aquisitions. Methods: A total of 46 consecutive TAVI patients in whom anticoagulation had been initiated because of HALT and who underwent follow-up CT were identified. Indication and type of anticoagulation was according to physician discretion. Patients on DOAC were compared to VKA therapy regarding resolution of HALT. Results: Mean age of the 46 patients was 80 ± 6 years (59% men), and the mean duration of anticoagulation was 156 days. Overall, 41 patients (89%) showed resolution of HALT with anticoagulation therapy, whereas HALT persisted in 5 patients (11%). Resolution of HALT was seen in 26 out of 30 (87%) patients receiving VKA and in 15 out of 16 (94%) patients receiving DOAC, respectively. Groups did not differ regarding age, cardiovascular risk factors, TAVI prosthesis type and size or duration of anticoagulation (all p > 0.05). Conclusion: Anticoagulation therapy resolves leaflet thickening after TAVI in most patients. Non-Vitamin-K antagonists seem to be an effective alternative to Vitamin-K antagonists. This finding needs to be confirmed in larger prospective trials.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Anticoagulation; HALT; Leaflet thickening; TAVI

Comparison of quantitative atherosclerotic plaque burden from coronary CT angiography in patients with first acute coronary syndrome and stable coronary artery disease - Dey, Damini; Achenbach, Stephan; Schuhbaeck, Annika; Pflederer, Tobias; Nakazato, Ryo; Slomka, Piotr J.; Berman, Daniel S.; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Coronary CTA allows characterization of non-calcified and calcified plaque and identification of high-risk plaque features.We aimed to quantitatively characterize and compare coronary plaque burden from CTA in patients with a first acute coronary syndrome (ACS) and controls with stable coronary artery disease.We retrospectively analyzed consecutive patients with non-ST-segment elevation myocardial infarction (NSTEMI) or unstable angina with a first ACS, who underwent CTA as part of their initial workup before invasive coronary angiography and age- and gender-matched controls with stable chest pain; controls also underwent CTA with subsequent invasive angiography (total n = 28). Culprit arteries were identified in ACS patients. Coronary arteries were analyzed by automated software to quantify calcified plaque (CP), noncalcified plaque (NCP), and low-density NCP (LD-NCP, attenuation <30 Hounsfield units) volumes, and corresponding burden (plaque volume × 100%/vessel volume), stenosis, remodeling index, contrast density difference (maximum percent difference in attenuation/cross-sectional area from proximal cross-section), and plaque length.ACS patients had fewer lesions (median, 1), with higher total NCP and LD-NCP burdens (NCP: 57.4% vs 41.5%; LD-NCP: 12.5% vs 8%; P <= .04), higher maximal stenoses (85.6% vs 53.0%; P = .003) and contrast density differences (46.1 vs 16.3%; P < .006). Per-patient CP burden was not different between ACS and controls. NCP and LD-NCP plaque burden was higher in culprit vs nonculprit arteries (NCP: 57.8% vs 9.5%; LD-NCP: 8.4% vs 0.6%; P <= .0003); CP was not significantly different. Culprit arteries had increased plaque lengths, remodeling indices, stenoses, and contrast density differences (46.1% vs 10.9%; P <= .001).Noninvasive quantitative coronary artery analysis identified several differences for ACS, both on per-patient and per-vessel basis, including increased NCP, LD-NCP burden, and contrast density difference.
EVALuna2:11863

Comparison of Real-Time Classification Systems for Arrhythmia Detection on Android-based Mobile Devices - Leutheuser, Heike; Gradl, Stefan; Kugler, Patrick; Anneken, Lars; Achenbach, Stephan; Eskofier, Björn; Arnold, Martin (IEEE EMBC 2014, 2014)

Comparison of standard- and high-dose intracoronary adenosine for the measurement of coronary fractional flow reserve (FFR) - Röther, Jens; Achenbach, Stephan; Tröbs, Monique; Blachutzik, Florian; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Clinical Research in Cardiology, 2016)
BACKGROUND: Measurement of fractional flow reserve (FFR) by intravenous infusion or intracoronary injection of adenosine is the reference method to determine the hemodynamic relevance of coronary artery stenoses. The goal of this prospective study was to compare standard (40 µg adenosine for the right and 80 µg for the left coronary artery) to high doses of intracoronary adenosine for FFR measurement. METHODS AND RESULTS: In 130 intermediate coronary artery stenoses, two sequential FFR measurements were performed with standard-dose intracoronary application of adenosine (40 µg for the right and 80 μg for the left coronary artery), followed by one FFR measurement with a bolus of 200 μg for the right and 400 μg for the left coronary artery. There was strong correlation (r = 0.97, p < 0.001) between FFR values determined with standard-dose adenosine (0.86 ± 0.08) versus high-dose adenosine (0.85 ± 0.08). High-dose adenosine did not yield FFR values ≤0.80 or ≤0.75 significantly more frequently than standard-dose adenosine. Patients reported more discomfort after high-dose adenosine application compared to standard-dose adenosine (p < 0.001). CONCLUSIONS: For FFR measurements with intracoronary adenosine injection, results achieved with doses of 40 µg adenosine for the right and 80 µg for the left coronary artery display no clinically relevant difference to doses of 200 and 400 µg, respectively.
EVALuna2:33662

Comparison of Two Contemporary Quantitative Atherosclerotic Plaque Assessment Tools for Coronary Computed Tomography Angiography: Single-Center Analysis and Multi-Center Patient Cohort Validation - Weichsel, Loris; Giesen, Alexander; André, Florian; Renker, Matthias; Baumann, Stefan; Breitbart, Philipp; Beer, Meinrad; Maurovitch-Horvat, Pal; Szilveszter, Bálint; Vattay, Borbála; Buss, Sebastian J.; Marwan, Mohamed; et al. (Diagnostics, 2024)
Background: Coronary computed tomography angiography (CCTA) provides non-invasive quantitative assessments of plaque burden and composition. The quantitative assessment of plaque components requires the use of analysis software that provides reproducible semi-automated plaque detection and analysis. However, commercially available plaque analysis software can vary widely in the degree of automation, resulting in differences in terms of reproducibility and time spent. Aim: To compare the reproducibility and time spent of two CCTA analysis software tools using different algorithms for the quantitative assessment of coronary plaque volumes and composition in two independent patient cohorts. Methods: The study population included 100 patients from two different cohorts: 50 patients from a single-center (Siemens Healthineers, SOMATOM Force (DSCT)) and another 50 patients from a multi-center study (5 different > 64 slice CT scanner types). Quantitative measurements of total calcified and non-calcified plaque volume of the right coronary artery (RCA), left anterior descending (LAD), and left circumflex coronary artery (LCX) were performed on a total of 300 coronaries by two independent readers, using two different CCTA analysis software tools (Tool #1: Siemens Healthineers, syngo.via Frontier CT Coronary Plaque Analysis and Tool #2: Siemens Healthineers, successor CT Coronary Plaque Analysis prototype). In addition, the total time spent for the analysis was recorded with both programs. Results: The patients in cohorts 1 and 2 were 62.8 ± 10.2 and 70.9 ± 11.7 years old, respectively, 10 (20.0%) and 35 (70.0%) were female and 34 (68.0%) and 20 (40.0%), respectively, had hyperlipidemia. In Cohort #1, the inter- and intra-observer variabilities for the assessment of plaque volumes per patient for Tool #1 versus Tool #2 were 22.8%, 22.0%, and 26.0% versus 2.3%, 3.9%, and 2.5% and 19.7%, 21.4%, and 22.1% versus 0.2%, 0.1%, and 0.3%, respectively, for total, noncalcified, and calcified lesions (p < 0.001 for all between Tools #1 and 2 both for inter- and intra-observer). The inter- and intra-observer variabilities using Tool #2 remained low at 2.9%, 2.7%, and 3.0% and 3.8%, 3.7%, and 4.0%, respectively, for total, non-calcified, and calcified lesions in Cohort #2. For each dataset, the median processing time was higher for Tool #1 versus Tool #2 (459.5 s IQR = 348.0–627.0 versus 208.5 s; IQR = 198.0–216.0) (p < 0.001). Conclusion: The plaque analysis Tool #2 (CT-guided PCI) encompassing a higher degree of automated support required less manual editing, was more time-efficient, and showed a higher intra- and inter-observer reproducibility for the quantitative assessment of plaque volumes both in a representative single-center and in a multi-center validation cohort.
CRIS-Team Scopus Importer:2024-02-02
Keywords: calcified; composition; inter- and intra-observer variabilities; non-calcified; plaque quantification; plaque volume; serial studies

Competency-based cardiac imaging for patient-centred care. A statement of the European Society of Cardiology (ESC). With the contribution of the European Association of Cardiovascular Imaging (EACVI), and the support of the Association of Cardiovascular Nursing & Allied Professions (ACNAP), the Association for Acute CardioVascular Care (ACVC), the European Association of Preventive Cardiology (EAPC), the European Association of Percutaneous Cardiovascular Interventions (EAPCI), the European Heart Rhythm Association (EHRA), and the Heart Failure Association (HFA) of the ESC - Westwood, Mark; Almeida, Ana G.; Barbato, Emanuele; Delgado, Victoria; Dellegrottaglie, Santo; Fox, Kevin F.; Gargani, Luna; Huber, Kurt; Maurovich-Horvat, Pál; Merino, Jose L.; Mindham, Richard; Muraru, Denisa; et al. (European Heart Journal - Cardiovascular Imaging, 2023)
Imaging plays an integral role in all aspects of managing heart disease and cardiac imaging is a core competency of cardiologists. The adequate delivery of cardiac imaging services requires expertise in both imaging methodology-with specific adaptations to imaging of the heart-as well as intricate knowledge of heart disease. The European Society of Cardiology (ESC) and the European Association of Cardiovascular Imaging have developed and implemented a successful education and certification programme for all cardiac imaging modalities. This programme equips cardiologists to provide high quality competency-based cardiac imaging services ensuring they are adequately trained and competent in the entire process of cardiac imaging, from the clinical indication via selecting the best imaging test to answer the clinical question, to image acquisition, analysis, interpretation, storage, repository, and results dissemination. This statement emphasizes the need for competency-based cardiac imaging delivery which is key to optimal, effective and efficient, patient care.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Cardiac computed tomography; Cardiovascular magnetic resonance; Competency-based cardiac imaging; Echocardiography; Nuclear cardiology

Complete recovery after out-of-hospital cardiac arrest with prolonged (59 min) mechanical cardiopulmonary resuscitation, mild therapeutic hypothermia and complex percutaneous coronary intervention for ST-elevation myocardial infarction - Zimmermann, Stefan; Rohde, Doris; Ludwig, Josef; Achenbach, Stephan; Marwan, Mohamed (Heart & Lung, 2014)
We report on a 68 years old survivor of an out-of-hospital cardiac arrest with favorable neurological outcome following prolonged cardiopulmonary resuscitation (CPR 59 min) until return of spontaneous circulation (ROSC) due to ST-elevation myocardial infarction (STEMI). The case demonstrates the beneficial effect of an optimal rescue chain including basic life support performed by trained bystanders, short response time of the emergency medical service, uninterrupted CPR during transportation using a mechanical chest compression system (LUCAS®), in combination with optimal intensive care management of cardiogenic shock after ROSC including multivessel emergency percutaneous coronary intervention (PCI) and intravascular therapeutic hypothermia (Coolgard®-System).
EVALuna2:11884

Computational fluid dynamics: can computed tomography imaging compete with cath-lab physiology? - Marwan, Mohamed (Cardiovascular Research, 2019)
CRIS-Team WoS Importer:2019-04-12

Computed Tomography Angiography Reply - Tröbs, Monique (Deutsches Ärzteblatt international, 2019)
CRIS-Team WoS Importer:2019-10-08

Computed tomography–based pericoronary adipose tissue attenuation in patients undergoing TAVR: a novel method for risk assessment - Steyer, Alexandra; Mas-Peiro, Silvia; Leistner, David M.; Puntmann, Valentina O.; Nagel, Eike; Dey, Damini; Göller, Markus; Koch, Vitali; Booz, Christian; Vogl, Thomas J.; Martin, Simon S. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: This study aims to assess the attenuation of pericoronary adipose tissue (PCAT) surrounding the proximal right coronary artery (RCA) in patients with aortic stenosis (AS) and undergoing transcatheter aortic valve replacement (TAVR). RCA PCAT attenuation is a novel computed tomography (CT)–based marker for evaluating coronary inflammation. Coronary artery disease (CAD) in TAVR patients is common and usually evaluated prior to intervention. The most sensible screening method and consequential treatment approach are unclear and remain a matter of ceaseless discussion. Thus, interest remains for safe and low-demand predictive markers to identify patients at risk for adverse outcomes postaortic valve replacement. Methods: This single-center retrospective study included patients receiving a standard planning CT scan prior to TAVR. Conventional CAD diagnostic tools, such as coronary artery calcium score and significant stenosis via invasive coronary angiography and coronary computed tomography angiography, were determined in addition to RCA PCAT attenuation using semiautomated software. These were assessed for their relationship with major adverse cardiovascular events (MACE) during a 24-month follow-up period. Results: From a total of 62 patients (mean age: 82 ± 6.7 years), 15 (24.2%) patients experienced an event within the observation period, 10 of which were attributed to cardiovascular death. The mean RCA PCAT attenuation was higher in patients enduring MACE than that in those without an endpoint (−69.8 ± 7.5 vs. −74.6 ± 6.2, P = 0.02). Using a predefined cutoff of >−70.5 HU, 20 patients (32.3%) with high RCA PCAT attenuation were identified, nine (45%) of which met the endpoint within 2 years after TAVR. In a multivariate Cox regression model including conventional CAD diagnostic tools, RCA PCAT attenuation prevailed as the only marker with significant association with MACE (P = 0.02). After dichotomization of patients into high- and low-RCA PCAT attenuation groups, high attenuation was related to greater risk of MACE (hazard ration: 3.82, P = 0.011). Conclusion: RCA PCAT attenuation appears to have predictive value also in a setting of concomitant AS in patients receiving TAVR. RCA PCAT attenuation was more reliable than conventional CAD diagnostic tools in identifying patients at risk for MACE.
CRIS-Team Scopus Importer:2023-06-16
Keywords: computed tomography angiography; coronary artery disease; major adverse cardiovascular events; pericoronary adipose tissue; risk stratification; transcatheter aortic valve replacements

Computed tomography-derived characterisation of pericoronary,epicardial and paracardial adipose tissue and its association with myocardial ischemia as assessed by computed and invasive fractional flow - Göller, Markus; Duncker, Hendrik; Moshage, Maximilian; Dey, D.; Bittner, Daniel; Ammon, Fabian; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Computed Tomography-derived Characterization of Pericoronary, Epicardial, and Paracardial Adipose Tissue and Its Association with Myocardial Ischemia as Assessed by Computed Fractional Flow Reserve - Duncker, Hendrik; Achenbach, Stephan; Moshage, Maximilian; Dey, Damini; Bittner, Daniel O.; Ammon, Fabian; Marwan, Mohamed; Oeller, Markus (Journal of Thoracic Imaging, 2023)
Background: Increased pericoronary adipose tissue (PCAT) attenuation derived from coronary computed tomography (CT) angiography (CTA) relates to coronary inflammation and cardiac mortality. We aimed to investigate the association between CT-derived characterization of different cardiac fat compartments and myocardial ischemia as assessed by computed fractional flow reserve (FFRCT). Methods: In all, 133 patients (median 64 y, 74% male) with coronary artery disease (CAD) underwent CTA including FFRCT measurement followed by invasive FFR assessment (FFRINVASIVE). CT attenuation and volume of PCAT were quantified around the proximal right coronary artery (RCA), left anterior descending artery (LAD), and left circumflex artery (LCX). Epicardial adipose tissue (EAT) and paracardial adipose tissue (PAT; all intrathoracic adipose tissue outside the pericardium) were quantified in noncontrast cardiac CT datasets. Results: Median FFRCT was 0.86 [0.79, 0.91] and median FFRINVASIVE was 0.87 [0.81, 0.93]. Subjects with the presence of myocardial ischemia (n=26) defined by an FFRCT-threshold of ≤0.75 showed significantly higher RCA PCAT attenuation than individuals without myocardial ischemia (n=107) (-75.1±10.8 vs. -81.1±10.6 HU, P=0.011). In multivariable analysis adjusted for age, body mass index, sex and risk factors, increased RCA PCAT attenuation remained a significant predictor of myocardial ischemia. Between individuals with myocardial ischemia compared with individuals without myocardial ischemia, there was no significant difference in the volume and CT attenuation of EAT and PAT or in the PCAT volume of RCA, LAD, and LCX. Conclusions: Increased RCA PCAT attenuation is associated with the presence of myocardial ischemia as assessed by FFR, while PCAT volume, EAT, and PAT are not.
CRIS-Team Scopus Importer:2023-01-06
Keywords: computed tomography attenuation; coronary computed tomography angiography; epicardial adipose tissue; fractional flow reserve; myocardial ischemia; paracardial adipose tissue; pericoronary adipose tissue

Computed Tomography–Derived Fractional Flow Reserve: An Invitation to Learn More - Achenbach, Stephan (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
CRIS-Team Scopus Importer:2022-02-04
Keywords: computed tomography; coronary artery disease; fractional flow reserve; SPECT

Computed Tomography for Diagnosis and Classification of Bicuspid Aortic Valve Disease in Transcatheter Aortic Valve Replacement - Kim, Won-Keun; Gaede, Luise; Husser, Oliver; Liebetrau, Christoph; Renker, Matthias; Rolf, Andreas; Fischer-Rasokat, Ulrich; Moellmann, Susanne; Blumenstein, Johannes; Guenther, Eva; Van Linden, Arnaud; Arsalan, Mani; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2018)
EVALuna2:35965

Computed tomography imaging in the context of transcatheter aortic valve implantation (TAVI) / transcatheter aortic valve replacement (TAVR): An expert consensus document of the Society of Cardiovascular Computed Tomography. - Blanke, Philipp; Weir-Mccall, Jonathan R.; Achenbach, Stephan; Delgado, Victoria; Hausleiter, Joerg; Jilaihawi, Hasan; Marwan, Mohamed; Norgaard, Bjarne L.; Piazza, Niccolo; Schoenhagen, Paul; Leipsic, Jonathon A. (Journal of Cardiovascular Computed Tomography, 2019)
EVALuna2:213035

Computed Tomography Imaging in the Context of Transcatheter Aortic Valve Implantation (TAVI)/Transcatheter Aortic Valve Replacement (TAVR): An Expert Consensus Document of the Society of Cardiovascular Computed Tomography - Blanke, Philipp; Weir-Mccall, Jonathan R.; Achenbach, Stephan; Delgado, Victoria; Hausleiter, Joerg; Jilaihawi, Hasan; Norgaard, Bjarne L.; Piazza, Niccolo; Schoenhagen, Paul; Leipsic, Jonathon A.; Marwan, Mohamed (Journal of the American College of Cardiology : Cardiovascular imaging, 2019)
EVALuna2:35956

Computed tomography to guide transcatheter aortic valve implantation - Daghem, Marwa; Weidinger, Florian; Achenbach, Stephan (Herz, 2023)
Since its introduction in 2022, transcatheter aortic valve implantation (TAVI) has revolutionized the treatment and prognosis of patients with aortic stenosis. Robust clinical trial data and a wealth of scientific evidence support its efficacy and safety. One of the key factors for success of the TAVI procedure is careful preprocedural planning using imaging. Computed tomography (CT) has developed into the standard imaging method for comprehensive patient assessment in this context. Suitability of the femoral and iliac arteries for transfemoral access, exact measurement of aortic annulus size and geometry as the basis for prosthesis selection, quantification of the spatial relationship of the coronary ostia to the aortic annular plane, and identification of optimal fluoroscopic projection angles for the implantation procedure are among the most important information that can be gained from preprocedural CT. Further research is aimed at improving risk stratification, for example, with respect to annular perforation, periprosthetic aortic regurgitation, and need for postprocedural implantation of a permanent pacemaker.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Bicuspid aortic valve; CT angiography; Imaging; Transcatheter aortic valve implantation; Valve-in-valve

Computer-aided evaluation of low-dose and low-contrast agent third-generation dual-source CT angiography prior to transcatheter aortic valve implantation (TAVI) - Dankerl, Peter; Hammon, Matthias; Seuß, Hannes; Tröbs, Monique; Schuhbaeck, Annika; Hell, Michaela M.; Achenbach, Stephan; Uder, Michael; Marwan, Mohamed; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2016)
To evaluate the performance of computer-aided evaluation software for a comprehensive workup of patients prior to transcatheter aortic valve implantation (TAVI) using low-contrast agent and low radiation dose third-generation dual-source CT angiography.We evaluated 30 consecutive patients scheduled for TAVI. All patients underwent ECG-triggered high-pitch dual-source CT angiography of the aortic root and aorta with a standardized contrast agent volume (30 ml Imeron350, flow rate 4 ml/s) and low-dose (100 kv/350 mAs) protocol. An expert (10 years of experience) manually evaluated aortic root and iliac access dimensions (distance between coronary ostia and aortic annulus, minimal/maximal diameters and area-derived diameter of the aortic annulus) and best CT-predicted fluoroscopic projection angle as the reference standard. Utilizing computer-aided software (syngo.via), the same pre-TAVI workup was performed and compared to the reference standard.Mean CTDI[Formula: see text] was 3.46 mGy and mean DLP 217.6 ± 12.1 mGy cm, corresponding to a mean effective dose of 3.7 ± 0.2 mSv. Computer-aided evaluation was successful in all but one patient. Compared to the reference standard, Bland-Altman analysis indicated very good agreement for the distances between aortic annulus and coronary ostia (RCA: mean difference 0.8 mm; 95 % CI 0.4-1.2 mm; LM: mean difference 0.9 mm; 95 % CI 0.5-1.3 mm); however, we demonstrated a systematic overestimation of annulus- derived diameter using the software (mean difference 44.4 mm[Formula: see text]; 95 % CI 30.4-58.3 mm[Formula: see text]). Based on respective annulus dimensions, the recommended prosthesis size (Edwards SAPIEN 3) matched in 26 out of the 29 patients (90 %). CT-derived fluoroscopic projection angles showed an excellent agreement for both methods. Out of 58 iliac arteries, 15 (25 %) arteries could not be segmented by the software. Preprocessing time of the software was 71 ± 11 s (range 51-96 s), and reading time with the software was 118 ± 31 s (range 68-201 s).In the workup of pre-TAVI CT angiography, computer-aided evaluation of low-contrast, low-dose examinations is feasible with good agreement and quick reading time. However, a systematic overestimation of the aortic annulus area is observed.
EVALuna2:14602

Consistency-based Respiratory Motion Estimation in Rotational Angiography - Unberath, Mathias; Aichert, André; Achenbach, Stephan; Maier, Andreas (Medical Physics, 2017)
Purpose: Rotational coronary angiography enables 3D reconstruction but suffers from intra-scan cardiac and respiratory motion. While gating handles cardiac motion, respiratory motion requires compensation. State-of-the-art algorithms rely on 3D-2D registration that depends on initial reconstructions of sufficient quality. We propose a compensation method that is applied directly in projection domain. It overcomes the need for reconstruction and thus complements the state-of-the-art. Methods: Virtual single-frame background subtraction based on vessel segmentation and spectral deconvolution yields non-truncated images of the contrasted lumen. This allows motion compensation based on data consistency conditions. We compensate craniocaudal shifts by optimizing epipolar consistency to (a) devise an image-based surrogate for cardiac motion and (b) compensate for respiratory motion. We validate our approach in two numerical phantom studies and three clinical cases. Results: Correlation of the image-based surrogate for cardiac motion with the ECG-based ground truth was excellent yielding a Pearson correlation of 0.93 ± 0.04. Considering motion compensation, the target error measure decreased by 98% and 69%, respectively, for the phantom experiments while for the clinical cases the same figure of merit improved by 46 ± 21%. Conclusions: The proposed method is entirely image-based and accurately estimates craniocaudal shifts due to respiration and cardiac contraction. Future work will investigate experimental trajectories and possibilities for simplification of the single-frame subtraction pipeline.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.consis
Keywords: cone-beam CT; inpainting; motion correction; vessel segmentation

Constructing custom-made radiotranscriptomic signatures of vascular inflammation from routine CT angiograms: a prospective outcomes validation study in COVID-19 - Kotanidis, Christos; Xie, Cheng; Alexander, Donna; Rodrigues, Jonathan C.L.; Burnham, Katie; Mentzer, Alexander; O'Connor, Daniel; Knight, Julian; Siddique, Muhammad; Lockstone, Helen; Thomas, Sheena; Kotronias, Rafail; et al. (The Lancet Digital Health, 2022)
Background: Direct evaluation of vascular inflammation in patients with COVID-19 would facilitate more efficient trials of new treatments and identify patients at risk of long-term complications who might respond to treatment. We aimed to develop a novel artificial intelligence (AI)-assisted image analysis platform that quantifies cytokine-driven vascular inflammation from routine CT angiograms, and sought to validate its prognostic value in COVID-19. Methods: For this prospective outcomes validation study, we developed a radiotranscriptomic platform that uses RNA sequencing data from human internal mammary artery biopsies to develop novel radiomic signatures of vascular inflammation from CT angiography images. We then used this platform to train a radiotranscriptomic signature (C19-RS), derived from the perivascular space around the aorta and the internal mammary artery, to best describe cytokine-driven vascular inflammation. The prognostic value of C19-RS was validated externally in 435 patients (331 from study arm 3 and 104 from study arm 4) admitted to hospital with or without COVID-19, undergoing clinically indicated pulmonary CT angiography, in three UK National Health Service (NHS) trusts (Oxford, Leicester, and Bath). We evaluated the diagnostic and prognostic value of C19-RS for death in hospital due to COVID-19, did sensitivity analyses based on dexamethasone treatment, and investigated the correlation of C19-RS with systemic transcriptomic changes. Findings: Patients with COVID-19 had higher C19-RS than those without (adjusted odds ratio [OR] 2·97 [95% CI 1·43–6·27], p=0·0038), and those infected with the B.1.1.7 (alpha) SARS-CoV-2 variant had higher C19-RS values than those infected with the wild-type SARS-CoV-2 variant (adjusted OR 1·89 [95% CI 1·17–3·20] per SD, p=0·012). C19-RS had prognostic value for in-hospital mortality in COVID-19 in two testing cohorts (high [≥6·99] vs low [<6·99] C19-RS; hazard ratio [HR] 3·31 [95% CI 1·49–7·33], p=0·0033; and 2·58 [1·10–6·05], p=0·028), adjusted for clinical factors, biochemical biomarkers of inflammation and myocardial injury, and technical parameters. The adjusted HR for in-hospital mortality was 8·24 (95% CI 2·16–31·36, p=0·0019) in patients who received no dexamethasone treatment, but 2·27 (0·69–7·55, p=0·18) in those who received dexamethasone after the scan, suggesting that vascular inflammation might have been a therapeutic target of dexamethasone in COVID-19. Finally, C19-RS was strongly associated (r=0·61, p=0·00031) with a whole blood transcriptional module representing dysregulation of coagulation and platelet aggregation pathways. Interpretation: Radiotranscriptomic analysis of CT angiography scans introduces a potentially powerful new platform for the development of non-invasive imaging biomarkers. Application of this platform in routine CT pulmonary angiography scans done in patients with COVID-19 produced the radiotranscriptomic signature C19-RS, a marker of cytokine-driven inflammation driving systemic activation of coagulation and responsible for adverse clinical outcomes, which predicts in-hospital mortality and might allow targeted therapy. Funding: Engineering and Physical Sciences Research Council, British Heart Foundation, Oxford BHF Centre of Research Excellence, Innovate UK, NIHR Oxford Biomedical Research Centre, Wellcome Trust, Onassis Foundation.
CRIS-Team Scopus Importer:2023-03-08

Contemporary practice and technical aspects in coronary intervention with bioresorbable scaffolds: a European perspective - Tamburino, Corrado; Latib, Azeem; Van Geuns, Robert-Jan; Sabate, Manel; Mehilli, Julinda; Gori, Tommaso; Achenbach, Stephan; Pan Alvarez, Manuel; Nef, Holger; Lesiak, Maciej; Di Mario, Carlo; Colombo, Antonio; et al. (EuroIntervention, 2015)
Next to patient characteristics, the lack of a standardised approach for bioresorbable vascular scaffold (BVS) implantation is perceived as a potential explanation for the heterogeneous results reported so far. To provide some guidance, we sought to find a consensus on the best practices for BVS implantation and management across a broad array of patient and lesion scenarios.Fourteen European centres with a high volume of BVS procedures combined their efforts in an informal collaboration. To get the most objective snapshot of different practices among the participating centres, a survey with 45 multiple choice questions was prepared and conducted. The results of the survey represented a basis for the technical advice provided in the document, whereas areas of controversy are highlighted.Consensus criteria for patient and lesion selection, BVS implantation and optimisation, use of intravascular imaging guidance, approach to multiple patient and lesion scenarios, and management of complications, were identified.
EVALuna2:12066

Contrast medium application in pediatric high-pitch cardiovascular CT angiography: manual or power injection? - Saake, Marc; Lell, Michael; Rompel, Oliver; Glöckler, Martin; May, Matthias; Eller, Achim; Achenbach, Stephan; Uder, Michael; Wüst, Wolfgang (Journal of Cardiovascular Computed Tomography, 2014)
Dual-source CT offers accurate depiction of cardiac structures in children with congenital heart disease. For cardiac CT, optimal enhancement of the cardiovascular structures is essential. There is considerable controversy about the administration of contrast medium (CM) in infants and small children, with either a power injector or a manual (hand) injection.The aim of this study was to compare image quality with power injection of CM (study group) and manual injection (control group).Thirty-four patients (study group, 6.8 ± 9.6 months and control group, 4.6 ± 8.9 months, nonrandomized) underwent dual-source CT angiography of the chest using a prospective electrocardiography-triggered high-pitch spiral mode (pitch, 3.4; 80 kV). In the study group (17 patients), a power injector was used, and in the control group (17 patients, historical group), manual CM injection had been performed. To assess image quality, both subjective and objective parameters were evaluated independently by 2 experienced radiologists.Subjective overall image quality, signal-to-noise ratio, and contrast-to-noise ratio were significantly higher using power injection compared with manual injection (P < .05). However, depiction of cardiovascular structures did not differ significantly between both groups in all evaluated regions except the superior vena cava and the coronary arteries.In infants and small children with congenital heart disease, both manual and power injector protocols allowed for diagnostic imaging of cardiac and extracardiac structures. However, image quality and vascular attenuation were superior using a power injector.
EVALuna2:11950

Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation - Bittner, Daniel O.; Klinghammer, Lutz; Schuhbaeck, Annika; Hell, Michaela M.; Muschiol, Gerd; Gauss, Soeren; Lell, Michael; Uder, Michael; Hoffmann, Udo; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (European Radiology, 2016)
Chronic renal failure is common in patients referred for transcatheter aortic valve implantation (TAVI). CT angiography is recommended and provides crucial information prior to TAVI. We evaluated the feasibility of a reduced contrast volume protocol for pre-procedural CT imaging.Forty consecutive patients were examined with prospectively ECG-triggered high-pitch spiral acquisition using a novel third-generation dual-source CT system; 38 ml contrast agent was used. Image quality was graded on a visual scale (1-4). Contrast attenuation was measured at the level of the aortic root and at the iliac bifurcation.Mean patient age was 82 ± 6 years (23 males; 58 %). Mean attenuation/average image quality was 285 ± 60 HU/1.5 at the aortic annulus compared to 289 ± 74 HU/1.8 at the iliac bifurcation (p = 0.77/p = 0.29). Mean estimated effective radiation dose was 2.9 ± 0.3 mSv. A repeat acquisition was necessary in one patient due to image quality. Out of the 35 patients who underwent TAVI, 31 (89 %) patients had no or mild aortic regurgitation. Thirty-two (91 %) patients were discharged successfully.Pre-procedural CTA with a total of 38 ml contrast volume is feasible and clinically useful, using third-generation dual-source CT, allowing comprehensive imaging for procedural success.o Reduction of contrast agent volume is crucial in patients with chronic renal failure. o Novel third-generation computed tomography helps to reduce contrast agent volume. o Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. o A low-contrast CT protocol is feasible for pre-procedural TAVI planning.
EVALuna2:14600

Cooling or Warming the Esophagus to Reduce Esophageal Injury During Left Atrial Ablation in the Treatment of Atrial Fibrillation - Zagrodzky, Jason; Gallagher, Mark M.; Leung, Lisa W.M.; Sharkoski, Tiffany; Santangeli, Pasquale; Tschabrunn, Cory; Guerra, Jose M.; Campos, Bieito; MacGregor, John; Hayat, Jamal; Clark, Brad; Mazur, Alex; et al. (Journal of Visualized Experiments, 2020)
Ablation of the left atrium using either radiofrequency (RF) or cryothermal energy is an effective treatment for atrial fibrillation (AF) and is the most frequent type of cardiac ablation procedure performed. Although generally safe, collateral injury to surrounding structures, particularly the esophagus, remains a concern. Cooling or warming the esophagus to counteract the heat from RF ablation, or the cold from cryoablation, is a method that is used to reduce thermal esophageal injury, and there are increasing data to support this approach. This protocol describes the use of a commercially available esophageal temperature management device to cool or warm the esophagus to reduce esophageal injury during left atrial ablation. The temperature management device is powered by standard water-blanket heat exchangers, and is shaped like a standard orogastric tube placed for gastric suctioning and decompression. Water circulates through the device in a closed-loop circuit, transferring heat across the silicone walls of the device, through the esophageal wall. Placement of the device is analogous to the placement of a typical orogastric tube, and temperature is adjusted via the external heat-exchanger console.
CRIS-Team Scopus Importer:2020-04-10

Coronary Angiography With Pressure Wire and Fractional Flow Reserve State of the Art in the Diagnosis of Coronary Stenosis - Gaede, Luise; Moellmann, Helge; Rudolph, Tanja; Rieber, Johannes; Boenner, Florian; Tröbs, Monique (Deutsches Ärzteblatt international, 2019)
Background: Approximately 800 000 coronary angiography procedures are per formed in Germany each year, mainly in order to identify coronary artery stenoses. As a rule, revascularization is indicated only when coronary artery stenoses cause relevant ischemia, but this cannot be determined unequivocally by angiography alone. Pressure wire measurement and the measurement of fractional flow reserve (FFR) enable direct evaluation of the hemodynamic relevance of coronary artery stenoses during diagnostic coronary angiography.
CRIS-Team WoS Importer:2019-05-21

Coronary Artery Disease Burden in Patients with Stable Angina and Symptoms of Heart Failure: A Coronary Computed Tomography Angiography Study from the German Cardiac CT Registry - Gitsioudis, Gitsios; Achenbach, Stephan; Schneider, S.; Schmermund, A.; Korosoglou, G.; Hausleiter, J.; Schroeder, S.; Rixe, J.; Leber, A.; Bruder, O.; Senges, J.; Marwan, Mohamed (2017)
EVALuna2:36029

Coronary Artery Disease - Reporting and Data System (CAD-RADS): An Expert Consensus Document of SCCT, ACR and NASCI: Endorsed by the ACC - Cury, Ricardo C.; Abbara, Suhny; Achenbach, Stephan; Agatston, Arthur; Berman, Daniel S.; Budoff, Matthew J.; Dill, Karin E.; Jacobs, Jill E.; Maroules, Christopher D.; Rubin, Geoffrey D.; Rybicki, Frank J.; Schoepf, U. Joseph; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2016)
The intent of CAD-RADS - Coronary Artery Disease Reporting and Data System is to create a standardized method to communicate findings of coronary CT angiography (coronary CTA) in order to facilitate decision-making regarding further patient management. The suggested CAD-RADS classification is applied on a per-patient basis and represents the highest-grade coronary artery lesion documented by coronary CTA. It ranges from CAD-RADS 0 (Zero) for the complete absence of stenosis and plaque to CAD-RADS 5 for the presence of at least one totally occluded coronary artery and should always be interpreted in conjunction with the impression found in the report. Specific recommendations are provided for further management of patients with stable or acute chest pain based on the CAD-RADS classification. The main goal of CAD-RADS is to standardize reporting of coronary CTA results and to facilitate communication of test results to referring physicians along with suggestions for subsequent patient management. In addition, CAD-RADS will provide a framework of standardization that may benefit education, research, peer-review and quality assurance with the potential to ultimately result in improved quality of care.
EVALuna2:33678

Coronary atherosclerosis scoring with semiquantitative CCTA risk scores for prediction of major adverse cardiac events: Propensity score-based analysis of diabetic and non-diabetic patients - van den Hoogen, Inge J.; van Rosendael, Alexander R.; Lin, Fay Y.; Lu, Yao; Dimitriu-Leen, Aukelien C.; Smit, Jeff M.; Scholte, Arthur J.H.A.; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Budoff, Matthew J.; et al. (Journal of Cardiovascular Computed Tomography, 2019)
Aims: We aimed to compare semiquantitative coronary computed tomography angiography (CCTA) risk scores – which score presence, extent, composition, stenosis and/or location of coronary artery disease (CAD) – and their prognostic value between patients with and without diabetes mellitus (DM). Risk scores derived from general chest-pain populations are often challenging to apply in DM patients, because of numerous confounders. Methods: Out of a combined cohort from the Leiden University Medical Center and the CONFIRM registry with 5-year follow-up data, we performed a secondary analysis in diabetic patients with suspected CAD who were clinically referred for CCTA. A total of 732 DM patients was 1:1 propensity-matched with 732 non-DM patients by age, sex and cardiovascular risk factors. A subset of 7 semiquantitative CCTA risk scores was compared between groups: 1) any stenosis ≥50%, 2) any stenosis ≥70%, 3) stenosis-severity component of the coronary artery disease-reporting and data system (CAD-RADS), 4) segment involvement score (SIS), 5) segment stenosis score (SSS), 6) CT-adapted Leaman score (CT-LeSc), and 7) Leiden CCTA risk score. Cox-regression analysis was performed to assess the association between the scores and the primary endpoint of all-cause death and non-fatal myocardial infarction. Also, area under the receiver-operating characteristics curves were compared to evaluate discriminatory ability. Results: A total of 1,464 DM and non-DM patients (mean age 58 ± 12 years, 40% women) underwent CCTA and 155 (11%) events were documented after median follow-up of 5.1 years. In DM patients, the 7 semiquantitative CCTA risk scores were significantly more prevalent or higher as compared to non-DM patients (p ≤ 0.022). All scores were independently associated with the primary endpoint in both patients with and without DM (p ≤ 0.020), with non-significant interaction between the scores and diabetes (interaction p ≥ 0.109). Discriminatory ability of the Leiden CCTA risk score in DM patients was significantly better than any stenosis ≥50% and ≥70% (p = 0.003 and p = 0.007, respectively), but comparable to the CAD-RADS, SIS, SSS and CT-LeSc that also focus on the extent of CAD (p ≥ 0.265). Conclusion: Coronary atherosclerosis scoring with semiquantitative CCTA risk scores incorporating the total extent of CAD discriminate major adverse cardiac events well, and might be useful for risk stratification of patients with DM beyond the binary evaluation of obstructive stenosis alone.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Atherosclerosis; Computed tomography (CT); Diabetes mellitus; Prognostic application; Risk stratification

Coronary atherosclerotic plaque burden and composition as assessed on CT angiography in East Asian and Caucasian populations - Ihdayhid, A. R.; Göller, Markus; Dey, D.; Adams, D.; Nerlekar, N.; Yap, G.; Thakur, U.; Cameron, J.; Seneviratne, S. K.; Achenbach, Stephan; Ko, B. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Coronary calcium: 'bad news' for men, but even 'worse news' for women? - Achenbach, Stephan (European Heart Journal, 2018)
EVALuna2:35961

Coronary calcium scoring from contrast coronary CT angiography using a semiautomated standardized method - Schuhbaeck, Annika; Otaki, Yuka; Achenbach, Stephan; Schneider, Christian; Slomka, Piotr; Berman, Daniel S.; Dey, Damini (Journal of Cardiovascular Computed Tomography, 2015)
When coronary calcium scoring is performed in patients with suspected coronary artery disease, a separate noncontrast scan is acquired before contrast-enhanced coronary CT angiography (CTA).Our aim was to develop and validate an automated method for calculating the coronary calcium score (CCS) from coronary CTA.We analyzed coronary CTA and noncontrast CT data sets of 84 patients (Agatston score >0). The CCS on noncontrast CT was measured using commercial methods. Coronary calcium volume was measured on coronary CTA using an automated standardized method with scan-specific calcium thresholds. Data sets were split into derivation (n = 40) and validation groups (n = 44). To calculate the CCS on coronary CTA, a conversion factor between calcium scores measured in noncontrast CT and the calcium volume measured on coronary CTA was derived by linear regression.In the validation group, the median calculated CCS derived from CTA was 277 and 244 on noncontrast images (P = .12). This CCS showed an excellent correlation with the CCS from noncontrast images (Pearson, r = 0.95). In the validation group, 39 of 44 patients (88.6%) were classified into the same standard category (1-10, 11-100, 101-400, or >400) with an excellent agreement (weighted ? of 0.87).CCSs can be accurately measured from contrast-enhanced coronary CTA by using an automated, standardized method, obviating the need for a noncontrast scan.
EVALuna2:12081

Coronary Computed Tomographic Angiography Can Predict Chronic Total Occlusion Recanalization Success: Where Do We Go From Here? - Achenbach, Stephan; Tröbs, Monique (Journal of the American College of Cardiology : Cardiovascular imaging, 2018)
EVALuna2:33583

Coronary computed tomographic imaging in women: An expert consensus statement from the Society of Cardiovascular Computed Tomography - Quynh A Truong,; Rinehart, Sarah; Abbara, Suhny; Achenbach, Stephan; Berman, Daniel S.; Bullock-Palmer, Renee; Carrascosa, Patricia; Chinnaiyan, Kavitha M.; Dey, Damini; Ferencik, Maros; Fuechtner, Gudrun; Hecht, Harvey; et al. (Journal of Cardiovascular Computed Tomography, 2018)
This expert consensus statement from the Society of Cardiovascular Computed Tomography (SCCT) provides an evidence synthesis on the use of computed tomography (CT) imaging for diagnosis and risk stratification of coronary artery disease in women. From large patient and population cohorts of asymptomatic women, detection of any coronary artery calcium that identifies females with a 10-year atherosclerotic cardiovascular disease risk of >7.5% may more effectively triage women who may benefit from pharmacologic therapy. In addition to accurate detection of obstructive coronary artery disease (CAD), CT angiography (CTA) identifies nonobstructive atherosclerotic plaque extent and composition which is otherwise not detected by alternative stress testing modalities. Moreover, CTA has superior risk stratification when compared to stress testing in symptomatic women with stable chest pain (or equivalent) symptoms. For the evaluation of symptomatic women both in the emergency department and the outpatient setting, there is abundant evidence from large observational registries and multi-center randomized trials, that CT imaging is an effective procedure. Although radiation doses are far less for CT when compared to nuclear imaging, radiation dose reduction strategies should be applied in all women undergoing CT imaging. Effective and appropriate use of CT imaging can provide the means for improved detection of at-risk women and thereby focus preventive management resulting in long-term risk reduction and improved clinical outcomes.
EVALuna2:35960

Coronary computed tomographic prediction rule for time-efficient guidewire crossing through chronic total occlusion: insights from the CT-RECTOR multicenter registry (Computed Tomography Registry of Chronic Total Occlusion Revascularization) - Opolski, Maksymilian P.; Achenbach, Stephan; Schuhbaeck, Annika; Rolf, Andreas; Moellmann, Helge; Nef, Holger; Rixe, Johannes; Renker, Matthias; Witkowski, Adam; Kepka, Cezary; Walther, Claudia; Schlundt, Christian; et al. (Jacc-Cardiovascular Interventions, 2015)
This study sought to establish a coronary computed tomography angiography prediction rule for grading chronic total occlusion (CTO) difficulty for percutaneous coronary intervention (PCI).The uncertainty of procedural outcome remains the strongest barrier to PCI in CTO.Data from 4 centers involving 240 consecutive CTO lesions with pre-procedural coronary computed tomography angiography were analyzed. Successful guidewire (GW) crossing <=30 min was set as an endpoint to eliminate operator bias. The CT-RECTOR (Computed Tomography Registry of Chronic Total Occlusion Revascularization) score was developed by assigning 1 point for each independent predictor, and then summing all points accrued. Continuous distribution of scores was used to stratify CTO into 4 difficulty groups: easy (score 0); intermediate (score 1); difficult (score 2); and very difficult (score >=3). Discriminatory performance was tested by 10-fold cross-validation and compared with the angiographic J-CTO (Multicenter CTO Registry of Japan) score.Study endpoint was achieved in 55% of cases. Multivariable analysis yielded multiple occlusions, blunt stump, severe calcification, bending, duration of CTO >=12 months, and previously failed PCI as independent predictors for GW crossing. The probability of successful GW crossing <=30 min for each group (from easy to very difficult) was 95%, 88%, 57%, and 22%, respectively. Areas under receiver-operator characteristic curves for the CT-RECTOR and J-CTO scores were 0.83 and 0.71, respectively (p < 0.001). Both the original model fit and 10-fold cross-validation correctly classified 77.3% of lesions.The CT-RECTOR score represents a simple and accurate noninvasive tool for predicting time-efficient GW crossing that may aid in grading CTO difficulty before PCI. (Computed Tomography Angiography Prediction Score for Percutaneous Revascularization for Chronic Total Occlusions [CT-RECTOR]; NCT02022878).
EVALuna2:12088

Coronary computed tomography and cardiac devices: Diagnostic results or nothing but artifacts? Koronare Computertomographie bei Device-Trägern: Sinnvolle Diagnostik oder nur Artefakt? - Smolka, Silvia; Achenbach, Stephan (Herzschrittmachertherapie und Elektrophysiologie, 2022)
Coronary computed tomography (CT) angiography has become a major cornerstone in the diagnostic workup of cardiologic patients, particularly for evaluation of the coronary arteries and preprocedural planning of interventions for structural heart disease. Despite the possible problems that intensive electromagnetic radiation (including X‑rays) might cause when directly impacting on implanted cardiac devices, cardiac CT is a safe diagnostic test and should not be withheld from patients with devices if properly indicated. Sufficient image quality is paramount for the evaluation; hence, special attention should be paid to a low heart rate (< 60 bpm) and sufficient compliance with breathing instructions. Furthermore, pacemaker or implantable cardioverter–defibrillator (ICD) leads may cause metal artifacts, especially around the lead tip. Their dense material causes beam hardening and streak artifacts which may result in reduced image quality and limited diagnostic assessability. The prevalence of such artifacts depends not only on lead material but also on lead positioning relative to the gantry plane. Metal artifacts are more frequent in patients with unipolar leads and shock coils, which can impair the assessment of coronary arteries, mainly of the right coronary artery (RCA). Artifacts caused by left ventricular (LV) leads of cardiac resynchronization therapy (CRT) systems tend to affect assessment of the left circumflex artery (LCX). By using dual energy CT and postprocessing algorithms, the impact of artifacts can be reduced and diagnostic image quality can be achieved in most cases. Unfortunately, the actual occurrence of such artifacts or the degree of impairment of image quality cannot be reliably predicted.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Cardiac diagnostics; Coronary diseases; Imaging quality; Implantable cardioverter–defibrillator; Pacemaker

Coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD): diagnostic impact and clinical consequences in the German Cardiac CT Registry depending on stress test results - Barth, Sebastian; Hausleiter, Joerg; Moshage, Werner; Korosoglou, Grigorios; Leber, Alexander; Schmermund, Axel; Gohlke, Helmut; Bruder, Oliver; Dill, Thorsten; Schroeder, Stephen; Kerber, Sebastian; Hamm, Karsten; et al. (International Journal of Cardiovascular Imaging, 2019)
To evaluate diagnostic impact of clinical use of coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD) and its consequences in daily practice for patient management, depending on stress test results in daily practice. Between 2009 and 2014 of a total population of 1352 patients of the German Cardiac Computed Tomography (CT) Registry who had previously undergone stress tests, CCTA visualizations were carried out on the coronary arteries with suspected stable CAD. Patients were divided into three groups according to stress test results: Group 1 with inconclusive (n = 178, 13.2%), Group 2 with ischemia in stress test (n = 372, 27.5%) and Group 3 without ischemia in stress test (n = 802, 59.3%). The test of preference was the stress electrocardiogram (ECG), which was performed more frequently in patients without ischemia in stress test as compared to those with ischemia (96.3% vs. 93.0%, p = 0.015). The incidence of detected obstructive CAD was lower in patients with suggested ischemia in stress test as compared to patients with inconclusive results (14.1% vs. 21.1%, p = 0.037). There was no difference in the incidence of an obstructive CAD in patients with and without ischemia in stress test (14.1% vs. 15.8%, p = 0.440). CCTA is a reliable, non-invasive option for ruling-out obstructive CAD irrespective of the stress test result.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Coronary computed tomography angiography; Pre-test probability; Stable coronary artery disease; Stress test

Coronary Computed Tomography Angiography-Specific Definitions of High-Risk Plaque Features Improve Detection of Acute Coronary Syndrome - Bittner, Daniel O.; Mayrhofer, Thomas; Puchner, Stefan B.; Lu, Michael T.; Maurovich-Horvat, Pal; Ghemigian, Khristine; Kitslaar, Pieter H.; Broersen, Alexander; Bamberg, Fabian; Truong, Quynh A.; Schlett, Christopher L.; Hoffmann, Udo; et al. (Circulation: Cardiovascular Imaging, 2018)
Background High-risk plaque (HRP) features as detected by coronary computed tomography angiography (CTA) predict acute coronary syndrome (ACS). We sought to determine whether coronary CTA-specific definitions of HRP improve discrimination of patients with ACS as compared with definitions from intravascular ultrasound (IVUS). Methods and Results In patients with suspected ACS, randomized to coronary CTA in the ROMICAT II (Rule Out Myocardial Infarction/Ischemia Using Computer Assisted Tomography II) trial, we retrospectively performed semiautomated quantitative analysis of HRP (including remodeling index, plaque burden as derived by plaque area, low computed tomography attenuation plaque volume) and degree of luminal stenosis and analyzed the performance of traditional IVUS thresholds to detect ACS. Furthermore, we derived CTA-specific thresholds in patients with ACS to detect culprit lesions and applied those to all patients to calculate the discriminatory ability to detect ACS in comparison to IVUS thresholds. Of 472 patients, 255 patients (56±7.8 years; 63% men) had coronary plaque. In 32 patients (6.8%) with ACS, culprit plaques (n=35) differed from nonculprit plaques (n=172) with significantly greater values for all HRP features except minimal luminal area (significantly lower; all P<0.01). IVUS definitions showed good performance while minimal luminal area (odds ratio: 6.82; P=0.014) and plaque burden (odds ratio: 5.71; P=0.008) were independently associated with ACS but not remodeling index (odds ratio: 0.78; P=0.673). Optimized CTA-specific thresholds for plaque burden (area under the curve: 0.832 versus 0.676) and degree of stenosis (area under the curve: 0.826 versus 0.721) showed significantly higher diagnostic performance for ACS as compared with IVUS-based thresholds (all P<0.05) with borderline significance for minimal luminal area (area under the curve: 0.817 versus 0.742; P=0.066). Conclusions CTA-specific definitions of HRP features may improve the discrimination of patients with ACS as compared with IVUS-based definitions. CLINICAL TRIAL REGISTRATION URL: https://www.clinicaltrials.gov . Unique identifier: NCT01084239.
EVALuna2:50445

Coronary CTA and percutaneous coronary intervention - A symbiosis waiting to happen - Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2016)
EVALuna2:33682

Coronary CT angiography-future directions - Achenbach, Stephan (Cardiovascular Diagnosis and Therapy, 2017)
Clinical applications of coronary CT angiography (CTA) will typically be based on the method´s very high sensitivity to identify coronary stenosis if image quality is good and if the pre-test likelihood of the patients is in the lower range. Guidelines of national and international cardiac societies are starting to incorporate coronary CTA into their recommendations for the management of patients with stable and acute chest pain. Initial data show that in the future, the use of coronary CTA may not only be able to replace other forms of diagnostic testing, but, in fact, may improve patient outcome. In this article, a perspective is provided on the future directions of coronary CTA.
EVALuna2:36022

Coronary CT angiography in the elderly - Nijveldt, R.; Pflederer, T.; Achenbach, Susanne (Netherlands Heart Journal, 2014)
People over 75 years of age represent a specific group of patients for which the clinician is often in doubt about what to do, whether additional diagnostic workup is helpful or a primary medical approach would suffice. However, this patient population is less prone to the long-term effects of radiation burden or contrast medium-induced nephropathy, and therefore it may be especially worthwhile to use advanced imaging techniques such as contrast-enhanced CT in these patients. The following cases illustrate two common diagnostic problems, in which coronary CT angiography decided the clinical course.
EVALuna2:12009

Coronary CT Angiography: Moving Up on the Risk Scale - Achenbach, Stephan (Journal of the American College of Cardiology, 2020)
CRIS-Team Scopus Importer:2020-02-04
Keywords: acute coronary syndrome; cardiac CT; diagnostic accuracy; timing

Coronary CT angiography: Native vessels - Achenbach, Stephan (Springer International Publishing, 2016)
Coronary CT Angiography has become increasingly stable and robust and accuracy to identify and rule out high-grade stenosis of the coronary arteries is high. The main clinical application is to rule out significant coronary artery disease in patients with a relatively low pre-test likelihood of disease. For this application, several guidelines in the US and Europe endorse the use of cardiac CT. Other applications of coronary CTA include the support of coronary interventions, especially in the context of chronic total coronary occlusion, the identification of coronary anomalies, and, to some extent, the assessment of non-obstructive coronary atherosclerosis. However, the use of coronary CTA for screening purposes is currently not supported by official recommendations.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Computed tomography; Coronary artery disease; Coronary CT angiography; Coronary CTA; Plaque; Stenosis

Coronary CT Angiography to Guide Treatment Decision Making: Lessons From the SYNTAX II Trial - Norgaard, Bjarne L.; Leipsic, Jonathon; Achenbach, Stephan (Journal of the American College of Cardiology, 2018)
EVALuna2:35982

Coronary dominance and prognosis in patients undergoing coronary computed tomographic angiography: results from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry - Gebhard, Catherine; Fuchs, Tobias A.; Stehli, Julia; Gransar, Heidi; Berman, Daniel S.; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (European Heart Journal - Cardiovascular Imaging, 2015)
Coronary computed tomographic angiography (CCTA) has become an important tool for non-invasive diagnosis of coronary artery disease (CAD). Coronary dominance can be assessed by CCTA; however, the predictive value of coronary dominance is controversially discussed. The aim of this study was to evaluate the prevalence and prognosis of coronary dominance in a large prospective, international multicentre cohort of patients undergoing CCTA.The study population consisted of 6382 patients with or without CAD (47% females, 53% males, mean age 56.9 ± 12.3 years) who underwent CCTA and were followed over a period of 60 months. Right or left coronary dominance was determined. Right dominance was present in 91% (n = 5817) and left in 9% (n = 565) of the study population. At the end of follow-up, outcome in patients with obstructive CAD (>50% luminal stenosis) and right dominance was similar compared with patients with left dominance [hazard ratio (HR) 0.46, 95% CI 0.16-1.32, P = 0.15]. Furthermore, no differences were observed for the type of coronary dominance in patients with non-obstructive CAD (HR 0.95, 95% CI 0.41-2.21, P = 0.8962) or normal coronary arteries (HR 1.04, 95% CI 0.68-1.59, P = 0.9). Subgroup analysis in patients with left main disease revealed an elevated hazard of the combined endpoint for left dominance (HR 6.45, 95% CI 1.66-25.0, P = 0.007), but not for right dominance.In our study population, survival after 5 years of follow-up did not differ significantly between patients with left or right coronary dominance. Thus, assessment of coronary vessel dominance by CCTA may not enhance risk stratification in patients with normal coronary arteries or obstructive CAD, but may add prognostic information for specific subpopulations.
EVALuna2:12057

Coronary intravascular lithotripsy and rotational atherectomy for severely calcified stenosis: Results from the ROTA.shock trial - Blachutzik, F.; Meier, S.; Weissner, M.; Schlattner, S.; Gori, T.; Ullrich, H.; Gaede, Luise; Achenbach, Stephan; Möllmann, H.; Chitic, B.; Aksoy, A.; Nickenig, G.; et al. (Catheterization and Cardiovascular Interventions, 2023)
Background: Severely calcified coronary lesions present a particular challenge for percutaneous coronary intervention. Aims: The aim of this randomized study was to determine whether coronary intravascular lithotripsy (IVL) is non-inferior to rotational atherectomy (RA) regarding minimal stent area (MSA). Methods: The randomized, prospective non-inferiority ROTA.shock trial enrolled 70 patients between July 2019 and November 2021. Patients were randomly (1:1) assigned to undergo either IVL or RA before percutaneous coronary intervention of severely calcified coronary lesions. Optical coherence tomography was performed at the end of the procedure for primary endpoint analysis. Results: The primary endpoint MSA was lower but non-inferior after IVL (mean: 6.10 mm2, 95% confidence interval [95% CI]: 5.32–6.87 mm2) versus RA (6.60 mm2, 95% CI: 5.66–7.54 mm2; difference in MSA: −0.50 mm2, 95% CI: −1.52–0.52 mm2; non-inferiority margin: −1.60 mm2). Stent expansion was similar (RA: 0.83 ± 0.10 vs. IVL: 0.82 ± 0.11; p = 0.79). There were no significant differences regarding contrast media consumption (RA: 183.1 ± 68.8 vs. IVL: 163.3 ± 55.0 mL; p = 0.47), radiation dose (RA: 7269 ± 11288 vs. IVL: 5010 ± 4140 cGy cm2; p = 0.68), and procedure time (RA: 79.5 ± 34.5 vs. IVL: 66.0 ± 19.4 min; p = 0.18). Conclusion: IVL is non-inferior regarding MSA and results in a similar stent expansion in a random comparison with RA. Procedure time, contrast volume, and dose-area product do not differ significantly.
CRIS-Team Scopus Importer:2023-09-15
Keywords: calcified stenosis; drug-eluting stent; optical coherence tomography; rotational atherectomy

Coronary plaque characterization using CT - Saremi, Farhood; Achenbach, Stephan (American Journal of Roentgenology, 2015)
OBJECTIVE. In this article, we review the histopathologic classification of coronary atherosclerotic plaques and describe the possibilities and limitations of CT regarding the evaluation of coronary artery plaques. CONCLUSION. The composition of atherosclerotic plaques in the coronary arteries displays substantial variability and is associated with the likelihood for rupture and downstream ischemic events. Accurate identification and quantification of coronary plaque components on CT is challenging because of the limited temporal, spatial, and contrast resolutions of current scanners. Nonetheless, CT may provide valuable information that has potential for characterization of coronary plaques. For example, the extent of calcification can be determined, lipid-rich lesions can be separated from more fibrous ones, and positive remodeling can be identified.
EVALuna2:12058

Coronary plaque quantification and fractional flow reserve by coronary computed tomography angiography identify ischaemia-causing lesions - Gaur, Sara; Ovrehus, Kristian Altern; Dey, Damini; Leipsic, Jonathon; Botker, Hans Erik; Jensen, Jesper Moller; Narula, Jagat; Ahmadi, Amir; Achenbach, Stephan; Ko, Brian S.; Christiansen, Evald Hoj; Kaltoft, Anne Kjer; et al. (European Heart Journal, 2016)
AIMS: Coronary plaque characteristics are associated with ischaemia. Differences in plaque volumes and composition may explain the discordance between coronary stenosis severity and ischaemia. We evaluated the association between coronary stenosis severity, plaque characteristics, coronary computed tomography angiography (CTA)-derived fractional flow reserve (FFRCT), and lesion-specific ischaemia identified by FFR in a substudy of the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps). METHODS AND RESULTS: Coronary CTA stenosis, plaque volumes, FFRCT, and FFR were assessed in 484 vessels from 254 patients. Stenosis >50% was considered obstructive. Plaque volumes (non-calcified plaque [NCP], low-density NCP [LD-NCP], and calcified plaque [CP]) were quantified using semi-automated software. Optimal thresholds of quantitative plaque variables were defined by area under the receiver-operating characteristics curve (AUC) analysis. Ischaemia was defined by FFR or FFRCT ≤0.80. Plaque volumes were inversely related to FFR irrespective of stenosis severity. Relative risk (95% confidence interval) for prediction of ischaemia for stenosis >50%, NCP ≥185 mm(3), LD-NCP ≥30 mm(3), CP ≥9 mm(3), and FFRCT ≤0.80 were 5.0 (3.0-8.3), 3.7 (2.4-5.6), 4.6 (2.9-7.4), 1.4 (1.0-2.0), and 13.6 (8.4-21.9), respectively. Low-density NCP predicted ischaemia independent of other plaque characteristics. Low-density NCP and FFRCT yielded diagnostic improvement over stenosis assessment with AUCs increasing from 0.71 by stenosis >50% to 0.79 and 0.90 when adding LD-NCP ≥30 mm(3) and LD-NCP ≥30 mm(3) + FFRCT ≤0.80, respectively. CONCLUSION: Stenosis severity, plaque characteristics, and FFRCT predict lesion-specific ischaemia. Plaque assessment and FFRCT provide improved discrimination of ischaemia compared with stenosis assessment alone.
EVALuna2:12095

Coronary plaque volume and composition assessed by computed tomography angiography in patients with late-onset major depression - Devantier, Torben Albert; Norgaard, Bjarne Linde; Ovrehus, Kristian Altem; Poulsen, Mikael Kjaer; Achenbach, Stephan; Dey, Damini; Videbech, Poul; Marwan, Mohamed (Psychosomatics, 2014)
Depression is a stronger predictor for the onset of or death from clinical coronary artery disease than traditional cardiovascular risk factors. The association between depression and coronary artery disease has previously been investigated in non-contrast enhanced computed tomography studies with conflicting results. The aim of this study was to further elucidate the depression-coronary artery disease relation by use of coronary computed tomography angiography.The calcified and noncalcified coronary plaque volumes were determined by semiautomatic volumetric quantification in 28 patients with late-onset major depression and 27 controls. The calcified plaque proportion, i.e., the calcified plaque volume divided by the total plaque volume, was used to assess the plaque composition.There was no statistically significant difference in the total (p = 0.48), calcified (p = 0.15), and noncalcified (p = 0.62) plaque volume between patients and controls, and the total plaque volume did not predict depression, odds ratio = 1.001 [95% confidence interval: 0.999-1.003; p = 0.23]. However, the calcified plaque proportion was twice as high in patients compared with controls (14% vs. 7%, p = 0.044). Correspondingly, having depression was associated with an increased calcified plaque proportion of 11.3 [95% confidence interval: 2.63-20.1; p = 0.012] percentage points after adjustment for demographics and cardiovascular risk factors.The proportion of the total coronary plaque volume that was calcified was significantly higher in patients with late-onset major depression than in controls, indicating a difference in plaque composition.
EVALuna2:11983

Coronary revascularization vs. medical therapy following coronary-computed tomographic angiography in patients with low-, intermediate- and high-risk coronary artery disease: results from the CONFIRM long-term registry - Schulman-Marcus, Joshua; Lin, Fay Y.; Gransar, Heidi; Berman, Daniel; Callister, Tracy; Delago, Augustin; Hadamitzky, Martin; Hausleiter, Joerg; Al-Mallah, Mouaz; Budoff, Matthew; Kaufmann, Philipp; Achenbach, Stephan; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: To identify the effect of early revascularization on 5-year survival in patients with CAD diagnosed by coronary-computed tomographic angiography (CCTA). Methods and results: We examined 5544 stable patients with suspected CAD undergoing CCTA who were followed a median of 5.5 years in a large international registry. Patients were categorized as having low-, intermediate-, or high-risk CAD based on CCTA findings. Two treatment groups were defined: early revascularization within 90 days of CCTA (n = 1171) and medical therapy (n = 4373). To account for the non-randomized referral to revascularization, we developed a propensity score by logistic regression. This score was incorporated into Cox proportional hazard models to calculate the effect of revascularization on all-cause mortality. Death occurred in 363 (6.6%) patients and was more frequent in medical therapy. In multivariable models, when compared with medical therapy, the mortality benefit of revascularization varied significantly over time and by CAD risk (P for interaction 0.04). In high-risk CAD, revascularization was significantly associated with lower mortality at 1 year (hazard ratio [HR] 0.22, 95% confidence interval [CI] 0.11-0.47) and 5 years (HR 0.31, 95% CI 0.18-0.54). For intermediate-risk CAD, revascularization was associated with reduced mortality at 1 year (HR 0.45, 95% CI 0.22-0.93) but not 5 years (HR 0.63, 95% CI 0.33-1.20). For low-risk CAD, there was no survival benefit at either time point. Conclusions: Early revascularization was associated with reduced 1-year mortality in intermediate- and high-risk CAD detected by CCTA, but this association only persisted for 5-year mortality in high-risk CAD.
EVALuna2:33626

Coronary Stent Strut Fractures: Classification, Prevalence and Clinical Associations - Schochlow, Katharina; Weissner, Melissa; Blachutzik, Florian; Boeder, Niklas F.; Tröbs, Monique; Lorenz, Liv; Dijkstra, Jouke; Munzel, Thomas; Achenbach, Stephan; Nef, Holger; Gori, Tommaso (Journal of Clinical Medicine, 2021)
Introduction. The frequency, characteristics and clinical implications of Strut fractures (SFs) remain incompletely understood. Methods and results. A total of 185 (160 patients) newer-generation drug-eluting stents (DES) were imaged. SFs were found in 21 DES (11.4%) and were classified in four patterns: one single stacked strut (41%); two or more stacked struts (23%); deformation without gap (27%); transection (9%). In multivariable analysis, calcific and bifurcation lesions were associated with SF in DES (OR: 3.5 [1.1-11] and 4.0 [2.2-7.2], p < 0.05). Device eccentricity and asymmetry as well as optical coherence tomography (OCT) features of impaired strut healing were also associated with SF. The prevalence of fractures was similar in a set of 289 bioresorbable scaffolds (BRS). In a separate series of 20 device thromboses and 36 device restenoses, the prevalence of SF was higher (61.2% of DES and 66.7% of BRS, p < 0.001 for both), with a higher frequency of complex SF patterns (p < 0.0001). In logistic regression analysis, fractures were a correlate of device complications (p < 0.0001, OR = 24.9 [5.6-111] for DES and OR = 6.0 [1.8-20] for BRS). Discussion. The prevalence of OCT-diagnosed SF was unexpectedly high in the setting of elective controls and it increased by about three-fold in the setting of device failure. Fractures were associated with increased lesion complexity and device asymmetry/eccentricity and were more frequent in the setting of device failure such as restenosis and thrombosis.
CRIS-Team WoS Importer:2021-05-07

C-reactive protein levels predict systolic heart failure and outcome in patients with first ST-elevation myocardial infarction treated with coronary angioplasty - Stumpf, Christian; Sheriff, Ahmed; Zimmermann, Stefan; Schaefauer, Liane; Schlundt, Christian; Raaz, Dorette; Garlichs, Christoph D.; Achenbach, Stephan (Archives of Medical Science, 2017)
INTRODUCTION: There is growing evidence that inflammation plays a pivotal role in the etiology and progression of atherosclerosis. High C-reactive protein (CRP) levels have been associated with high mortality in patients with acute myocardial infarction (AMI). Furthermore, in animal models CRP has been found to significantly increase infarct size. So there is growing evidence that CRP is not only a marker for cardiovascular disease but also might be pathogenic. The aim of our study was to test the hypothesis that peak CRP levels could predict heart failure (HF) in ST-elevation myocardial infarction (STEMI) patients. MATERIAL AND METHODS: Eighty-one consecutive patients with STEMI were prospectively enrolled in the study. C-reactive protein concentrations were measured on admission and after 6, 12, 24, 30, 48, 72 and 96 h. We assessed the association between the elevation of CRP, heart failure and cardiovascular mortality following the first 12 months after STEMI. RESULTS: C-reactive protein levels reached a peak after 48 h. Patients with STEMI and signs of HF showed significantly higher peak CRP levels. We found a positive correlation between maximum CK levels and peak CRP and a negative correlation between left ventricular ejection fraction (EF) and peak CRP. One year total mortality and HF mortality rates were found to be higher in patients with peak CRP > 47.5 mg/l than in those with CRP below that level (p< 0.001). CONCLUSIONS: Peak CRP levels in STEMI patients predict emergence of HF. Peak CRP is also a strong predictor of global and cardiovascular mortality during the following year after STEMI.
EVALuna2:33656

Crystalline sirolimus-coated balloon (cSCB) angioplasty in an all-comers, patient population with stable and unstable coronary artery disease including chronic total occlusions: rationale, methodology and design of the SCORE trial - Otto, Sylvia; Diaz, Victor Alfonso Jimenez; Weilenmann, Daniel; Cuculi, Florim; Nuruddin, Amin Ariff; Leibundgut, Gregor; Alfonso, Fernando; Wan Ahmad, Wan Azman; Pyxaras, Stylianos; Rittger, Harald; Steen, Philip; Gaede, Luise; et al. (Bmc Cardiovascular Disorders, 2023)
BackgroundA decade ago, the iopromide-paclitaxel coated balloon (iPCB) was added to the cardiologist's toolbox to initially treat in-stent restenosis followed by the treatment of de novo coronary lesions. In the meantime, DES technologies have been substantially improved to address in-stent restenosis and thrombosis, and shortened anti-platelet therapy. Recently, sirolimus-coated balloon catheters (SCB) have emerged to provide an alternative drug to combat restenosis.MethodsThe objective of this study is to determine the safety and efficacy of a novel crystalline sirolimus-coated balloon (cSCB) technology in an unselective, international, large-scale patient population. Percutaneous coronary interventions of native stenosis, in-stent stenosis, and chronic total occlusions with the SCB in patients with stable coronary artery disease or acute coronary syndrome were included. The primary outcome variable is the target lesion failure (TLF) rate at 12 months, defined as the composite rate of target vessel myocardial infarction (TV-MI), cardiac death or ischemia-driven target lesion revascularization (TLR). The secondary outcome variables include TLF at 24 months, ischemia driven TLR at 12 and 24 months and all-cause death, cardiac death at 12 and 24 months.DiscussionSince there is a wealth of patient-based all-comers data for iPCB available for this study, a propensity-score matched analysis is planned to compare cSCB and iPCB for the treatment of de novo and different types of ISR. In addition, pre-specified analyses in challenging lesion subsets such as chronic total occlusions will provide evidence whether the two balloon coating technologies differ in their clinical benefit for the patient.
CRIS-Team WoS Importer:2023-04-21

CT analysis of left ventricular function predicts short term survival in patients following transcatheter aortic valve implantation: 1-year outcome data - Ijgua, Mohamed Cherif; Arnold, Martin; Eckstein, Markus; Smolka, S.; Bittner, Daniel O.; Ammon, Fabian; Kondruweit, Markus; Moshage, Maximilian; Achenbach, Susanne; Marwan, Mohamed (European Heart Journal, 2022)
CRIS-Team WoS Importer:2023-03-03

CT and MRI - Achenbach, Stephan; Gitsioudis, Gitsios (Elsevier, 2018)
CRIS-Team Scopus Importer:2023-03-08

CT Angiography for Revascularization of CTO: Crossing the Borders of Diagnosis and Treatment - Opolski, Maksymilian P.; Achenbach, Stephan (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
Coronary computed tomography angiography (CTA) is increasingly used to diagnose and rule out coronary artery disease. Beyond stenosis detection, the ability of CTA to visualize and characterize coronary atherosclerotic plaque, as well as to obtain 3-dimensional coronary vessel trajectories, has generated considerable interest in the context of pre-procedural planning for revascularization of chronic total occlusions (CTOs). Coronary CTA can characterize features that influence the success rate of percutaneous coronary intervention (PCI) for CTOs such as the extent of calcification, vessel tortuosity, stump morphology, presence of multiple occlusions, and lesion length. Single features and combined scoring systems based on CTA may be used to grade the level of difficulty of the CTOs before PCI and have been shown to predict procedural success rates in several trials. In addition, the procedure itself may be facilitated by real-time integration of 3-dimensional CTA data and fluoroscopic images in the catheterization laboratory. Finally, the ability of coronary CTA to assess anatomy, perfusion, and viability in 1 single examination makes it a potential "one stop shop" that predicts not only the likelihood of successful PCI but also the clinical benefit of CTO revascularization. Further research is clearly needed, but many experienced sites have already integrated coronary CTA into the routine planning and guiding of CTO procedures.
EVALuna2:12080

CT Angiography for the Detection of Coronary Artery Stenoses in Patients Referred for Cardiac Valve Surgery: Systematic Review and Meta-Analysis - Opolski, Maksymilian P.; Staruch, Adam D.; Jakubczyk, Michal; Min, James K.; Gransar, Heidi; Staruch, Michal; Witkowski, Adam; Kepka, Cezary; Kim, Won-Keun; Hamm, Christian W.; Moellmann, Helge; Achenbach, Stephan (Journal of the American College of Cardiology : Cardiovascular imaging, 2016)
OBJECTIVES: This study aimed to evaluate the diagnostic accuracy of coronary computed tomography angiography (CTA) for detecting coronary artery stenoses in patients with valvular heart disease undergoing valve surgery. BACKGROUND: Coronary CTA is currently not routinely recommended for detecting coronary artery stenoses before cardiac valve surgery. However, recent improvements in computed tomography technology may enable the identification of the most appropriate candidates for coronary CTA before valve surgery. METHODS: A systematic review was performed of PubMed, EMBASE, and the Cochrane databases for all studies that used ≥16-detector row computed tomography scanning to perform coronary CTA in patients with valvular heart disease scheduled for valve surgery and validated the results against invasive angiography. Summary diagnostic accuracies were calculated by using a bivariate random effects model, and a generalized linear mixed model was applied for heterogeneity analysis. RESULTS: Seventeen studies analyzing 1,107 patients and 12,851 coronary segments were included. Patient-based analysis revealed a pooled sensitivity of 93% (95% confidence interval [CI]: 86 to 97), specificity of 89% (95% CI: 86 to 91), a negative likelihood ratio (LR) of 0.07 (95% CI: 0.04 to 0.16), and a positive LR of 8.44 (95% CI: 6.49 to 10.99) for coronary CTA to identify individuals with stenosis ≥50%. Specificity and positive LR were higher in patients without aortic stenosis (AS) versus those with AS (96% vs. 87% and 21.2 vs. 7.4, respectively), as well as with ≥64 detectors versus <64 detectors (90% vs. 86% and 9.5 vs. 6.9). Heterogeneity analysis revealed a significant impact of AS and the number of detectors on specificity of CTA. CONCLUSIONS: Coronary CTA using currently available technology is a reliable imaging alternative to invasive angiography with excellent sensitivity and negative LR for the detection of significant coronary stenoses in patients undergoing cardiac valve surgery. The specificity of coronary CTA may be decreased against the background of AS (Computed Tomography Angiography for the Detection of Coronary Artery Disease in Patients Referred for Cardiac Valve Surgery: A Meta-Analysis; CRD42015016213).
EVALuna2:33677

CT angiography to evaluate coronary artery disease and revascularization requirement before trans-catheter aortic valve replacement - Rossi, Alexia; De Cecco, Carlo N.; Kennon, Simon R. O.; Zou, Lu; Meinel, Felix G.; Toscano, William; Segreto, Sabrina; Achenbach, Stephan; Hausleiter, Joerg; Schoepf, U. Joseph; Pugliese, Francesca (Journal of Cardiovascular Computed Tomography, 2017)
BACKGROUND: Coronary artery disease (CAD) and aortic stenosis share pathophysiological mechanisms and risk factors. We evaluated the clinical utility of coronary computed tomography angiography (CTA) to identify CAD and revascularization requirement in patients with severe aortic stenosis considered for transcatheter aortic valve replacement (TAVR). METHODS: Consecutive patients without known CAD underwent calcium scoring, CTA and invasive coronary angiography (ICA). A second-generation dual-source CT scanner was used. ICA-quantitative coronary angiography (QCA) served as reference standard. CAD was reported using a lenient threshold of ≥50% and a stricter threshold of ≥70% diameter reduction. Findings of ≥70% diameter reduction and of high-risk CAD were used to predict revascularization. RESULTS: The study included 140 patients [68 males; 82.3 (7.7) years]. CAD defined by the 50% threshold on ICA was found in 58/140 (41%) patients. CAD by the 70% threshold was found in 23/140 (16%) patients. High-risk CAD was found in 16/140 (11%) patients. CTA and ICA had similar odd-ratios of 3.22 (1.26-8.23) and 4.62 (1.64-13.05), respectively, in predicting revascularization. Forty-two/140 (30%) patients had <400 Agatston calcium score, 98/140 (70%) patients had ≥400 calcium score. The diagnostic performance of CTA in the low calcium score group was better than the high calcium score group (AUC 0.81 vs. 0.63). CONCLUSION: CTA remained questionable to rule-out CAD as gatekeeper to ICA in TAVR candidates who had severe coronary calcifications. In patients with less severe coronary calcifications, accounting for 30% of participants in this study, CTA may play a clinical role.
EVALuna2:33618

CT Attenuation of Pericoronary Adipose Tissue in Normal Versus Atherosclerotic Coronary Segments as Defined by Intravascular Ultrasound - Hell, Michaela; Schuhbaeck, Annika; Gauss, Soeren; Bittner, Daniel; Pflederer, Tobias; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2017)
BACKGROUND: The factors influencing genesis of atherosclerosis at specific regions within the coronary arterial system are currently uncertain. Local mechanical factors such as shear stress as well as metabolic factors, including inflammatory mediators released from epicardial fat, have been proposed. We analyzed computed tomographic (CT) attenuation of pericoronary adipose tissue in normal versus atherosclerotic coronary segments as defined by intravascular ultrasound (IVUS). PATIENTS AND METHODS: We evaluated the data sets of 29 patients who were referred for invasive coronary angiography and in whom IVUS of 1 coronary vessel was performed for clinical reasons. Coronary CT angiography was performed within 24 hours from invasive coronary angiography. Computed tomographic angiography was performed using dual-source CT (Siemens Healthcare; Forchheim, Germany). A contrast-enhanced volume data set was acquired (120 kV, 400 mA/rot, collimation 2 × 64 × 0.6 mm, 60-80 mL intravenous contrast agent). Intravascular ultrasound was performed using a 40-MHz IVUS catheter (Atlantis; Boston Scientific Corporation, Natick, Mass) and motorized pullback at 0.5 mm/s. Sixty corresponding coronary artery segments within the coronary artery system were identified in both dual source computed tomography and IVUS using bifurcation points as fiducial markers. In dual source computed tomography data sets, 8 serial parallel cross sections (2-mm slice thickness) were rendered orthogonal to the center line of the coronary artery for each segment. For each cross section, pericoronary adipose tissue within a radius of 3 mm from the coronary artery and enclosed within the epicardium (excluding coronary veins and myocardium) was manually traced and mean CT attenuation values were obtained. Intravascular ultrasound was used to define coronary segments as follows: presence of predominantly fibrous atherosclerotic plaque (hyperechoic), presence of predominantly lipid-rich atherosclerotic plaque (hypoechoic), and absence of atherosclerotic plaque. RESULTS: In IVUS, 20 coronary segments with fibrous plaque, 20 segments with lipid-rich plaque, and 20 coronary segments without plaque were identified. The mean CT attenuation of pericoronary adipose tissue for segments with any coronary atherosclerotic plaque was -34 ± 14 Hounsfield units (HU), as compared with -56 ± 16 HU for segments without plaque (P = 0.005). The density of pericoronary fat in segments with fibrous versus lipid-rich plaque as defined by IVUS was not significantly different (-35 ± 19 HU vs -36 ± 16 HU, P = 0.8). CONCLUSIONS: Mean CT attenuation of pericoronary adipose tissue is significantly lower for normal versus atherosclerotic coronary segments. This supports a hypothesis of different types of pericoronary adipose tissue, the more metabolically active of which might exert local effects on the coronary vessels, thus contributing to atherogenesis.
EVALuna2:33619

CT-based analysis of pericoronary adipose tissue density: Relation to cardiovascular risk factors and epicardial adipose tissue volume - Hell, Michaela M.; Achenbach, Stephan; Schuhbaeck, Annika; Klinghammer, Lutz; May, Matthias; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
Pericoronary adipose tissue (PCAT) can promote atherosclerosis. Metabolically active and inactive PCAT may display different CT densities. However, CT density could be influenced by partial volume effects and image interpolation.To investigate whether PCAT density values in CT displays differences that are larger than those attributable to interpolation and partial volume effects, which would manifest themselves through the relationship between PCAT density and distance from the contrast-enhanced coronary lumen.PCAT density analysis was performed (417 non-atherosclerotic segments, 63 patients) using dual-source CT with a threshold-based measurement method. Changes in PCAT density values depending on distance from the contrast-enhanced coronary lumen and the influence of cardiovascular risk profile were analyzed.Mean PCAT density was -78.1 ± 5.6 HU. PCAT density decreased from proximal to distal segments in the LAD (-78.0 ± 7.3 vs. -82.4 ± 7.7 HU; p < 0.001). PCAT density was higher close to the lumen compared to more peripheral locations (-76.0 ± 6.7 vs. -78.5 ± 5.4 HU; p < 0.001). Decreasing PCAT density was significantly associated with higher epicardial adipose tissue (EAT) volume and body mass index. There was a trend of lower PCAT values with a family history of coronary artery disease.CT-measured attenuation of PCAT is influenced by EAT volume and body mass index. A decrease of PCAT attenuation with increasing distance from the vessel and from proximal to distal segments may suggest variations in CT density of PCAT due to partial volume effects and image interpolation rather than solely due to differences in tissue composition or metabolic activity.
EVALuna2:12033

CT-based total vessel plaque analyses improves prediction of hemodynamic significance lesions as assessed by fractional flow reserve in patients with stable angina pectoris - Ovrehus, Kristian A.; Gaur, Sara; Leipsic, Jonathon; Jensen, Jesper M.; Dey, Damini; Botker, Hans E.; Ahmadi, Amir; Achenbach, Stephan; Ko, Brian; Norgaard, Bjarne L. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Coronary stenosis and plaque evaluation by coronary computed tomography angiography (CTA) may contribute to identify hemodynamically relevant lesions. We evaluated the most stenotic lesion including plaques proximal to it versus a total vessel analyses combined with stenosis for ischemia. METHODS: Patients scheduled for clinically indicated invasive coronary angiography (ICA) for suspected coronary artery disease underwent coronary CTA and ICA including fractional flow reserve (FFR) as part of the NXT trial (clinicaltrials.govNCT01757678). Stenoses were visually graded ≤50%, 51-70%, and >70% on coronary CTA. Semi-automated plaque analyses were performed using a proximal to the FFR pressure sensor location (including the most severe lesion to the coronary ostium) versus a total vessel (vessel diameter ≥2 mm) approach. Coronary stenosis and plaque parameters were evaluated for discrimination of ischemia by logistic regressions and combined models analyzed using receiver operating characteristics (ROC) with invasive FFR≤ 0.80 as reference standard. RESULTS: In 254 patients, mean (±SD) age 64 (±10) years, 64% male, a coronary CTA stenosis >50% was present in 239 (49%) vessels. Invasive FFR was ≤0.80 in 100 (21%) vessels. Coronary stenosis severity and low-density non-calcified plaque (LD-NCP) volume were independent predictors of ischemia in the "proximal" and "total-vessel" analyses. Stenosis severity + total vessel LD-NCP assessment performed better than stenosis severity + proximal LD-NCP evaluation (Area under curve [AUC] (95%CI): 0.83 (0.78-0.87) vs 0.81 (0.76-0.86), p-value = 0.009), whereas stenosis severity + proximal LD-NCP performed better than stenosis alone (AUC (95%CI): 0.81 (0.76-0.86) vs 0.78 (0.73-0.83), p-value = 0.019). CONCLUSION: Adding total vessel high-risk plaque volume to stenosis severity improves discrimination of ischemia in coronary CTA performed in patients with stable angina pectoris.
EVALuna2:35980

CT-derived left ventricular global strain: a head-to-head comparison with speckle tracking echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Mansour, H.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (International Journal of Cardiovascular Imaging, 2019)
We assessed CT-derived left ventricular strain in a cohort of patients referred for transcatheter aortic valve implantation (TAVI) and validated it against 2 dimensional speckle tracking echocardiography as the gold standard. 65 consecutive patients with symptomatic aortic valve stenosis referred for CT imaging prior to TAVI were included in this analysis. For all patients, retrospectively ECG-gated multi-phase functional CT data sets acquired with identical reconstruction parameters were available. All data sets were acquired using a third generation dual source system. In all patients, multiphase reconstructions in increments of 10% of the cardiac cycle were rendered (slice thickness 0.75, increment 0.5 mm, medium smooth reconstruction kernel) and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). Additional functional reconstructions for dynamic assessment and quantification of strain were processed. Multiplanar reconstructions (MPR) of the left ventricle similar to standard echocardiographic 4, 2 and apical 3 chamber views were rendered in CT. Similar to echocardiographic longitudinal strain, the perimeter of the left ventricle was manually traced within the myocardium and peak maximal shortening as a parameter representing longitudinal strain was calculated for each view and averaged to obtain a marker for global longitudinal strain (CT perimeter-derived strain). Furthermore, for quantification of 3-dimensional strain, endocardial and epicardial borders of myocardium were marked in six short axis views and peak maximum 3- dimensional strain of the myocardium was calculated in standard six basal, six mid and four apical segments. 3-dimensional strain values of the 16 standard segments as well as perimeter-derived strain values in the three standard windows were averaged to obtain global strain. Echocardiography was performed in all patients before CT data acquisition. Digital loops were acquired from three apical views (four-, two-, and three chamber views). For assessment of 2 dimensional global longitudinal strain (GLS), recordings were processed with acoustic-tracking software allowing offline semiautomated speckle-based strain analyses. The mean age of all 65 patients was 81 ± 5 years. The mean echocardiographic ejection fraction and mean echocardiographic GLS were 50 ± 12% and −13.6 ± 4.5%, respectively. The mean CT-derived peak 3-dimensional global strain and mean peak strain derived by perimeter was 43.2 ± 13.5% and −11.2 ± 3.5%, respectively. Both CTderived global 3D-strain and perimeter derived strain showed a significant correlation to GLS derived by echocardiography (r = −0.8, p < 0.0001 for 3D strain and r = 0.71, p < 0.0001 for perimeter-derived strain). Bland-Altman analysis showed a systematic underestimation (i. e. worse strain values) of CT perimeter-derived strain compared to GLS by echocardiography (mean difference −2.4% with 95% limits of agreement between 4% to −9%). ROC Curve analysis assuming a normal GLS when less than −18% showed that a CT-derived peak 3-dimensional global strain cut-off-value of 45% has a sensitivity of 91% and a specificity of 60% for detecting normal left ventricular strain (AUC 0.81, p = 0.001). For CT perimeter-derived strain, a cut-off value of −12%—assuming a normal echocardiographic GLS when less than −18%—achieved a sensitivity of 82% and a specificity of 61% (AUC of 0.82, p = 0.001) for detecting abnormal left ventricular strain. Using dedicated software, assessment of CT-derived left ventricular strain is feasible and comparable to strain derived by echocardiographic 2 dimensional speckle tracking.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Cardiac CT angiography; Echocardiography; Left ventricular global strain; Speckle tracking

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve implantation: a head-to-head comparison with echocardiography - Ammon, Fabian; Bittner, D.; Hell, M.; Schuhbaeck, A.; Röther, Jens; Feyrer, R.; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

CT-derived left ventricular global strain in aortic stenosis patients referred for transcatheter aortic valve replacement: a comparative study pre and post intervention - Bittner, D.; Hell, M.; Gitsioudis, Gitsios; Röther, Jens; Schuhbaeck, A.; Feyrer, R.; Arnold, M.; Achenbach, Stephan; Marwan, Mohamed (2017)
EVALuna2:36027

CT-derived left ventricular global strain in aortic valve stenosis patients: A comparative analysis pre and post transcatheter aortic valve implantation - Ammon, Fabian; Bittner, D.; Röther, Jens; Mekkhala, N.; Hell, M.; Schuhbaeck, A.; Gitsioudis, Gitsios; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: We assessed the potential of CT strain to detect changes in myocardial function in patients referred for TAVI pre and post intervention. PATIENTS AND METHODS: 25 consecutive patients with symptomatic aortic valve stenosis in whom TAVI had been performed were included in this analysis. Functional CT data sets acquired before and 3 to 6 months after TAVI were available. Multiphase reconstructions in increments of 10% of the cardiac cycle were rendered and transferred to a dedicated workstation (Ziostation2, Ziosoft Inc., Tokyo, Japan). For quantification of left ventricular strain, multiplanar reconstructions of the left ventricle in standard 4 chamber, 2 chamber as well as apical 3 chamber views were rendered. The perimeter of the left ventricle was traced dynamically through the cardiac cycle. Peak strain was calculated for each patient pre and post intervention. Furthermore, for quantification of 3-dimensional maximum principal strain, 2 volumetric regions of interests (VOI) were placed per each basal, mid and apical segment of the previously mentioned MPRs and peak maximal principal strain was calculated. Maximum principal strain as well as perimeter-derived longitudinal strain values in the three standard windows were averaged to obtain global strain. RESULTS: 25 patients were included in this analysis (mean age 78 ± 9 years, 13 males). Peak global maximum principal strain was significantly higher at follow-up compared to baseline (0.46 ± 0.19 vs. 0.59 ± 0.18, respectively, p = 0.001). Similarly global longitudinal strain derived by perimeter was significantly lower - implying better contraction - compared to baseline (-8.6% ± 2.8% vs. -9.8% ± 2.6%, respectively, p = 0.006). CONCLUSION: Using dedicated software, assessment of CT derived left ventricular strain is feasible. In patients treated with transcatheter aortic valve replacement, CT-derived parameters of global myocardial strain improve onshort-term follow-up.
EVALuna2:35994

CT-FFR in predicting future cardiovascular events - Smolka, S.; Fava, A.; Moshage, Maximilian; Marwan, Mohamed; Desai, M. Y.; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

CT predictors of post-procedural aortic regurgitation in patients referred for transcatheter aortic valve implantation: An analysis of 105 patients - Marwan, Mohamed; Achenbach, Stephan; Ensminger, Stefan M.; Pflederer, Tobias; Ropers, Dieter; Ludwig, Josef; Weyand, Michael; Daniel, Werner; Arnold, Martin (International Journal of Cardiovascular Imaging, 2013)
Cardiac computed tomography (CT) allows accurate and detailed analysis of the anatomy of the aortic root and valve, including quantification of calcium. We evaluated the correlation between different CT parameters and the degree of post-procedural aortic regurgitation (AR) after transcatheter aortic valve implantation (TAVI) using the balloon-expandable Edwards Sapien prosthesis. Preintervention contrast-enhanced dual source CT data sets of 105 consecutive patients (48 males, mean age 81 ± 6 years, mean logEuroSCORE 34 ± 13 %) with symptomatic severe aortic valve stenosis referred for TAVI using the Edwards Sapien prosthesis (Edwards lifesciences, Inc., CA, USA) were analysed. The degrees of aortic valve commissural calcification and annular calcification were visually assessed on a scale from 0 to 3. Furthermore, the degree of aortic valve calcification as quantified by the Agatston score, aortic annulus eccentricity, aortic diameter at the level of the sinus of valsalva and at the sinotubular junction were assessed. Early post-procedural AR was assessed using aortography. Significant AR was defined as angiographic AR of at least moderate degree (AR ≥ 2). Visual assessment of the degree of aortic annular calcification as well as the Agatston score of aortic valve calcium correlated weakly, yet significantly with the degree of post-procedural AR (r = 0.31 and 0.24, p = 0.001 and 0.013, respectively). Compared to patients with AR<2, patients with AR ≥ 2 showed more severe calcification of the aortic annulus (mean visual scores 1.9 ± 0.6 vs. 1.5 ± 0.6, p = 0.003) as well as higher aortic valve Agatston scores (1,517 ± 861 vs. 1,062 ± 688, p = 0.005). Visual score for commissural calcification did not differ significantly between both groups (mean scores 2.4 ± 0.5 vs. 2.5 ± 0.5, respectively, p = 0.117). No significant correlation was observed between the degree of AR and commissural calcification, aortic annulus eccentricity index or aortic diameters. The extent of aortic valve annular calcification, but not of commissural calcification, predicts significant post-procedural AR in patients referred for TAVI using the balloon-expandable Edwards Sapiens prosthesis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: AR; CT; TAVI

CT support of cardiac structural interventions - Hell, Michaela M.; Achenbach, Stephan (British Journal of Radiology, 2019)
Due to its high temporal and isotropic spatial resolution, CT has become firmly established for pre-procedural imaging in the context of structural heart disease interventions. CT allows to very exactly measure dimensions of the target structure, CT can provide information regarding the access route and, as a very valuable addition, volumetric CT data sets can be used to identify fluoroscopic projection angulations to optimally visualize the target structure and place devices. This review provides an overview of current methods and applications of pre-interventional CT to support adult cardiac interventions including transcatheter aortic valve implantation, percutaneous mitral valve intervention, left atrial appendage occlusion and paravalvular leak closure.
CRIS-Team WoS Importer:2019-06-07

Current but not past smoking increases the risk of cardiac events: insights from coronary computed tomographic angiography - Nakanishi, Rine; Berman, Daniel S.; Budoff, Matthew J.; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor Y.; Chinnaiyan, Kavitha; et al. (European Heart Journal, 2015)
We evaluated coronary artery disease (CAD) extent, severity, and major adverse cardiac events (MACEs) in never, past, and current smokers undergoing coronary CT angiography (CCTA).We evaluated 9456 patients (57.1 ± 12.3 years, 55.5% male) without known CAD (1588 current smokers; 2183 past smokers who quit >=3 months before CCTA; and 5685 never smokers). By risk-adjusted Cox proportional-hazards models, we related smoking status to MACE (all-cause death or non-fatal myocardial infarction). We further performed 1:1:1 propensity matching for 1000 in each group evaluate event risk among individuals with similar age, gender, CAD risk factors, and symptom presentation. During a mean follow-up of 2.8 ± 1.9 years, 297 MACE occurred. Compared with never smokers, current and past smokers had greater atherosclerotic burden including extent of plaque defined as segments with any plaque (2.1 ± 2.8 vs. 2.6 ± 3.2 vs. 3.1 ± 3.3, P < 0.0001) and prevalence of obstructive CAD [1-vessel disease (VD): 10.6% vs. 14.9% vs. 15.2%, P < 0.001; 2-VD: 4.4% vs. 6.1% vs. 6.2%, P = 0.001; 3-VD: 3.1% vs. 5.2% vs. 4.3%, P < 0.001]. Compared with never smokers, current smokers experienced higher MACE risk [hazard ratio (HR) 1.9, 95% confidence interval (CI) 1.4-2.6, P < 0.001], while past smokers did not (HR 1.2, 95% CI 0.8-1.6, P = 0.35). Among matched individuals, current smokers had higher MACE risk (HR 2.6, 95% CI 1.6-4.2, P < 0.001), while past smokers did not (HR 1.3, 95% CI 0.7-2.4, P = 0.39). Similar findings were observed for risk of all-cause death.Among patients without known CAD undergoing CCTA, current and past smokers had increased burden of atherosclerosis compared with never smokers; however, risk of MACE was heightened only in current smokers.
EVALuna2:12063

Current status of cardiac CT for the detection of myocardial ischemia - Schuhbaeck, A.; Marwan, Mohamed; Cury, R. C.; Achenbach, Stephan (Herz, 2013)
Stress and rest myocardial perfusion imaging using computed tomography (CT) can be accurately and safely performed. CT angiography allows for the anatomic visualization of coronary lesions and the components of atherosclerotic plaque, whereas according to currently available data, CT perfusion imaging improves the diagnostic accuracy for detecting ischemic lesions. However, the radiation exposure and contrast load that are involved cannot be neglected. Owing to the limited number of trials that have been published so far, and the fact that they used a wide variety of image acquisition and stress protocols, a standard acquisition protocol for CT perfusion imaging still needs to be found and evaluated in larger multicenter trials. Therefore, CT perfusion imaging, as opposed to other modalities such as magnetic resonance perfusion, SPECT, or positron emission tomography, cannot yet be regarded as clinical routine, but may be considered in patients with contraindications for other imaging modalities. © 2013 Urban & Vogel.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac computed tomography; Myocardial ischemia; Myocardial perfusion imaging; Pharmacologic stress; Significant coronary stenoses

Current trends in patients with chronic total occlusions undergoing coronary CT angiography - Opolski, Maksymilian P.; Hartaigh, Briain O.; Berman, Daniel S.; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Hadamitzky, Martin; et al. (Heart, 2015)
Data describing the prevalence, characteristics and management of coronary chronic total occlusions (CTOs) in patients undergoing coronary CT angiography (CCTA) have not been reported. The purpose of this study was to determine the prevalence, characteristics and treatment strategies of CTO identified by CCTA.We identified 23 745 patients who underwent CCTA for suspected coronary artery disease (CAD) from the prospective international CCTA registry. Baseline clinical data were collected, and allocation to early coronary revascularisation performed within 90 days of CCTA was determined. Multivariable hierarchical mixed-effects logistic regression reporting OR with 95% CI was performed.The prevalence of CTO was 1.4% (342/23 745) in all patients and 6.2% in patients with obstructive CAD (>=50% stenosis). The presence of CTO was independently associated with male sex (OR 3.12, 95% CI 2.39 to 4.08, p<0.001), smoking (OR 2.02, 95% CI 1.55 to 2.64, p<0.001), diabetes (OR 1.60, 95% CI 1.22 to 2.11, p=0.001), typical angina (OR 1.51, 95% CI 1.12 to 2.06, p=0.008), hypertension (OR 1.47, 95% CI 1.14 to 1.88, p=0.003), family history of CAD (OR 1.30, 95% CI 1.01 to 1.67, p=0.04) and age (OR 1.06, 95% CI 1.05 to 1.07, p<0.001). Most patients with CTO (61%) were treated medically, while 39% underwent coronary revascularisation. In patients with severe CAD (>=70% stenosis), CTO independently predicted revascularisation by coronary artery bypass grafting (OR 3.41, 95% CI 2.06 to 5.66, p<0.001), but not by percutaneous coronary intervention (p=0.83).CTOs are not uncommon in a contemporary CCTA population, and are associated with age, gender, angina status and CAD risk factors. Most individuals with CTO undergoing CCTA are managed medically with higher rates of surgical revascularisation in patients with versus without CTO.ClinicalTrials.gov identifier NCT01443637.
EVALuna2:12082

CV imaging: What was new in 2012? - Achenbach, Stephan; Friedrich, Matthias G.; Nagel, Eike; Kramer, Christopher M.; Kaufmann, Philip A.; Farkhooy, Amir; Dilsizian, Vasken; Flachskampf, Frank A. (Journal of the American College of Cardiology : Cardiovascular imaging, 2013)
Echocardiography, single-photon emission computed tomography (SPECT), positron emission tomography (PET), cardiac magnetic resonance, and cardiac computed tomography can be used for anatomic and functional imaging of the heart. All 4 methods are subject to continuous improvement. Echocardiography benefits from the more widespread availability of 3-dimensional imaging, strain and strain rate analysis, and contrast applications. SPECT imaging continues to provide very valuable prognostic data, and PET imaging, on the one hand, permits quantification of coronary flow reserve, a strong prognostic predictor, and, on the other hand, can be used for molecular imaging, allowing the analysis of extremely small-scale functional alterations in the heart. Magnetic resonance is gaining increasing importance as a stress test, mainly through perfusion imaging, and continues to provide very valuable prognostic information based on late gadolinium enhancement. Magnetic resonance coronary angiography does not substantially contribute to clinical cardiology at this point in time. Computed tomography imaging of the heart mainly concentrates on the imaging of coronary artery lumen and plaque and has made substantial progress regarding outcome data. In this review, the current status of the 5 imaging techniques is illustrated by reviewing pertinent publications of the year 2012.
CRIS-Team Scopus Importer:2023-03-08
Keywords: cardiac computed tomography; cardiac magnetic resonance; contrast; coronary angiography; echocardiography; late gadolinium enhancement; PET; SPECT; strain; strain rate

Data Structure, Management and Transmission. In: TEMOS - Telemedical Emergency Management on Board the International Space Station. Interdisciplinary Study between Johannes Gutenberg-University Mainz, University Erlangen, International Space University Strasbourg and Russian Society of Telemedicine; 50 WB 0148 DLR Final report (163p).p42-67. - Klinghammer, Lutz; Stolyar, Valery; Atkov, Oleg Jurewitsch; Maurer, J; Schäfer, Michael; Khan, Martin; Helou, L; Vollmer, J; Graf, J; Comtesse, R; Mann, Wolf (2004)
Keywords: Telemedicine; Expert Systems; ISS; Space Medicine; Cardiology

Declining radiation dose of coronary computed tomography angiography: German cardiac CT registry experience 2009-2014 - Schmermund, Axel; Hausleiter, Joerg; Barth, Sebastian; Bruder, Oliver; Kerber, Sebastian; Korosoglou, Grigorius; Leber, Alexander; Moshage, Werner; Schroeder, Stephen; Schneider, Steffen; Senges, Jochen; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2017)
BACKGROUND: Coronary computed tomography angiography (CTA) is increasingly used as a test to rule out coronary artery disease (CAD) in patients with a low to intermediate pre-test probability of the disease. We used the database of the German CT registry, collected between 2009 and 2014 in a broad patient population, to analyze contemporary radiation dose associated with coronary CTA in clinical practice. PATIENTS AND METHODS: The prospective observational registry included a total of 7061 patients ≥18 years, referred to 12 participating centers for a clinically indicated cardiac CT examination. All centers were cardiology units well experienced in CTA and used multi-slice CT scanners with at least 64 rows. Coronary CTA was performed in a subset of 5001 patients, 59.6 ± 11.8 years, body mass index (BMI) 26.9 ± 4.5 kg/m2, 38% females. Three time periods with approximately equal numbers of patients were created (01/09-03/10, 04/10-03/11, 04/11-07/14). The dose-length product of all examinations and derived effective dose in mSv (conversion factor k = 0.014) as well as the influence of patient characteristics on dose were compared for the three time periods. RESULTS: BMI and proportion of female patients remained stable over time, and mean heart rate decreased from 60.3 ± 9.0 to 58.5 ± 9.3 bpm from the first to the last time period (p < 0.001). Overall, the mean effective dose of coronary CTA was 3.6 mSv (Q1 1.8 mSv, Q3 7.4 mSv). Within the three time periods, it declined from 5.6 (2.7, 8.6) mSv during the first to 4.8 (2.1, 8.2) mSv during the second and 2.5 (1.3, 4.6) mSv during the last time period (p < 0.001). Paralleling the decline in radiation dose over time, the proportion of prospectively ECG-triggered examinations increased (68, 79, 83%; p < 0.001), and the proportion of examinations with retrospective gating and no tube current modulation decreased (5.3, 4.0, 1.6%; p < 0.001). Tube current (mAs) and voltage (kV) both decreased over time. In multivariable analysis, besides earlier time period, further independent predictors of an increased radiation dose were older age, higher heart rate, and higher BMI as well as the technical factors higher mAs, higher kV, and retrospective gating. At three sites, CT scanners with improved technology were installed during the last time period. CONCLUSIONS: In current clinical practice among German cardiology units with specific expertise in cross-sectional cardiovascular imaging, overall radiation dose of coronary CTA was comparably low. Over time, a decline in radiation dose was demonstrated, probably due to a combination of improvements in data acquisition protocols and patient preparation as well as installation of new CT scanners with advanced technology.
EVALuna2:33607

Decreased numbers of regulatory T cells are associated with human atherosclerotic lesion vulnerability and inversely correlate with infiltrated mature dendritic cells - Dietel, Barbara; Cicha, Iwona; Voskens, Caroline; Verhoeven, Eric; Achenbach, Stephan; Garlichs, Christoph (Atherosclerosis, 2013)
Purpose: Mature dendritic cells (DCs) play a crucial role in the inflammatory process within atherosclerotic lesions by stimulation of effector T cells, which can contribute to plaque instability. Interactions between DCs and regulatory T cells (Treg), which regulate immune response by attenuating acute inflammation, are postulated to be involved in the pathogenesis of autoimmune diseases. We investigated a possible correlation between infiltrated DCs and Treg in human atherosclerotic plaques. Methods: Cross-sections of 40 human carotid endarterectomy specimens were classified into groups of stable and vulnerable plaques using Trichrome staining. Immunohistochemical staining of plaques was used to detect infiltrated total (S100) and mature DCs (fascin, DC-LAMP, CD83), Treg (CD3, Foxp3), and to analyze the inflammatory state of the plaques (CD3, COX-2, CD68). In addition, RNA was isolated from plaque specimens and quantitative real-time PCR was performed to analyze transcription rates of DC markers (CD11c, CD209, HLA-DR), maturation markers (CD80, CD83, CD86), Treg-associated genes (CTLA-4, Foxp3) and of pro- and anti-inflammatory cytokines (TGFβ-family, IL-10, IFN-γ, IL-17α, IL-6). Migration assays and adhesion experiments were performed, to investigate the effects of Treg on mature DCs invitro. Results: As compared with stable plaques, vulnerable lesions were characterized by increased numbers of COX-2-expressing cells and T lymphocytes, indicating an enhanced inflammatory process. In vulnerable plaques, numbers of total and mature DCs were significantly higher in the inflammatory plaque shoulder, whereas the numbers of Treg were decreased compared to stable plaques. This inverse correlation and the association of the observed infiltration rates with plaque stability, were confirmed by PCR analyses, showing increased transcription levels of DC-specific markers, decreased mRNA expression of Treg-associated genes and decreased anti-inflammatory cytokines in vulnerable atherosclerotic plaques. In vitro, pre-incubation of mature DCs with Treg resulted in decreased DC migration and inhibited the adhesion of DCs to endothelial cells under non-uniform shear stress. Conclusions: The results of our study provide novel insights in the direct interaction of mature DCs and Treg in plaque inflammation and stability. © 2013 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atherosclerosis; Carotid plaques; Dendritic cells; Immunologic tolerance; Regulatory T cells

DECREASING GPLD 1-LEVELS IN PATIENTS AFTER ST-ELEVATED MYOCARDIAL INFARCTION - Kruse, A.; Bischof, Erik; Raaz-Schrauder, D.; Achenbach, Susanne; Dietel, B.; Tauchi, Miyuki; Urschel, K. (ATHEROSCLEROSIS, 2022)
CRIS-Team WoS Importer:2022-10-14

Deep Learning-Based Quantification of Epicardial Adipose Tissue Volume and Attenuation Predicts Major Adverse Cardiovascular Events in Asymptomatic Subjects - Eisenberg, Evann; McElhinney, Priscilla A.; Commandeur, Frederic; Chen, Xi; Cadet, Sebastien; Goeller, Markus; Razipour, Aryabod; Gransar, Heidi; Cantu, Stephanie; Miller, Robert J.H.; Slomka, Piotr J.; Wong, Nathan D.; et al. (Circulation: Cardiovascular Imaging, 2020)
BACKGROUND: Epicardial adipose tissue (EAT) volume (cm3) and attenuation (Hounsfield units) may predict major adverse cardiovascular events (MACE). We aimed to evaluate the prognostic value of fully automated deep learning-based EAT volume and attenuation measurements quantified from noncontrast cardiac computed tomography. METHODS: Our study included 2068 asymptomatic subjects (56±9 years, 59% male) from the EISNER trial (Early Identification of Subclinical Atherosclerosis by Noninvasive Imaging Research) with long-term follow-up after coronary artery calcium measurement. EAT volume and mean attenuation were quantified using automated deep learning software from noncontrast cardiac computed tomography. MACE was defined as myocardial infarction, late (>180 days) revascularization, and cardiac death. EAT measures were compared to coronary artery calcium score and atherosclerotic cardiovascular disease risk score for MACE prediction. RESULTS: At 14±3 years, 223 subjects suffered MACE. Increased EAT volume and decreased EAT attenuation were both independently associated with MACE. Atherosclerotic cardiovascular disease risk score, coronary artery calcium, and EAT volume were associated with increased risk of MACE (hazard ratio [95%CI]: 1.03 [1.01-1.04]; 1.25 [1.19-1.30]; and 1.35 [1.07-1.68], P<0.01 for all) and EAT attenuation was inversely associated with MACE (hazard ratio, 0.83 [95% CI, 0.72-0.96]; P=0.01), with corresponding Harrell C statistic of 0.76. MACE risk progressively increased with EAT volume ≥113 cm3 and coronary artery calcium ≥100 AU and was highest in subjects with both (P<0.02 for all). In 1317 subjects, EAT volume was correlated with inflammatory biomarkers C-reactive protein, myeloperoxidase, and adiponectin reduction; EAT attenuation was inversely related to these biomarkers. CONCLUSIONS: Fully automated EAT volume and attenuation quantification by deep learning from noncontrast cardiac computed tomography can provide prognostic value for the asymptomatic patient, without additional imaging or physician interaction.
CRIS-Team Scopus Importer:2020-02-28
Keywords: adipose tissue; calcium; deep learning; prognosis; tomography

Deep learning-based stenosis quantification from coronary CT angiography - Hong, Youngtaek; Commandeur, Frederic; Cadet, Sebastien; Göller, Markus; Doris, Mhairi K.; Chen, Xi; Kwiecinski, Jacek; Berman, Daniel S.; Slomka, Piotr J.; Chang, Hyuk Jae; Dey, Damini (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2019)
Coronary computed tomography angiography (CTA) allows quantification of stenosis. However, such quantitative analysis is not part of clinical routine. We evaluated the feasibility of utilizing deep learning for quantifying coronary artery disease from CTA. Methods: A total of 716 diseased segments in 156 patients (66 ± 10 years) who underwent CTA were analyzed. Minimal luminal area (MLA), percent diameter stenosis (DS), and percent contrast density difference (CDD) were measured using semi-automated software (Autoplaque) by an expert reader. Using the expert annotations, deep learning was performed with convolutional neural networks using 10-fold cross-validation to segment CTA lumen and calcified plaque. MLA, DS and CDD computed using deep-learning-based approach was compared to expert reader measurements. Results: There was excellent correlation between the expert reader and deep learning for all quantitative measures (r=0.984 for MLA; r=0.957 for DS; and r=0.975 for CDD, p<0.001 for all). The expert reader and deep learning method was not significantly different for MLA (median 4.3 mm2 for both, p=0.68) and CDD (11.6 vs 11.1%, p=0.30), and was significantly different for DS (26.0 vs 26.6%, p<0.05); however, the ranges of all the quantitative measures were within inter-observer variability between 2 expert readers. Conclusions: Our deep learning-based method allows quantitative measurement of coronary artery disease segments accurately from CTA and may enhance clinical reporting.
CRIS-Team Scopus Importer:2019-07-12
Keywords: contrast density difference; coronary CT Angiography; deep learning; minimum luminal area; quantitative CT.; stenosis

Deep learning-enabled coronary CT angiography for plaque and stenosis quantification and cardiac risk prediction: an international multicentre study - Lin, Andrew; Manral, Nipun; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Park, Caroline; Otaki, Yuka; Doris, Mhairi; et al. (The Lancet Digital Health, 2022)
BACKGROUND: Atherosclerotic plaque quantification from coronary CT angiography (CCTA) enables accurate assessment of coronary artery disease burden and prognosis. We sought to develop and validate a deep learning system for CCTA-derived measures of plaque volume and stenosis severity. METHODS: This international, multicentre study included nine cohorts of patients undergoing CCTA at 11 sites, who were assigned into training and test sets. Data were retrospectively collected on patients with a wide range of clinical presentations of coronary artery disease who underwent CCTA between Nov 18, 2010, and Jan 25, 2019. A novel deep learning convolutional neural network was trained to segment coronary plaque in 921 patients (5045 lesions). The deep learning network was then applied to an independent test set, which included an external validation cohort of 175 patients (1081 lesions) and 50 patients (84 lesions) assessed by intravascular ultrasound within 1 month of CCTA. We evaluated the prognostic value of deep learning-based plaque measurements for fatal or non-fatal myocardial infarction (our primary outcome) in 1611 patients from the prospective SCOT-HEART trial, assessed as dichotomous variables using multivariable Cox regression analysis, with adjustment for the ASSIGN clinical risk score. FINDINGS: In the overall test set, there was excellent or good agreement, respectively, between deep learning and expert reader measurements of total plaque volume (intraclass correlation coefficient [ICC] 0·964) and percent diameter stenosis (ICC 0·879; both p<0·0001). When compared with intravascular ultrasound, there was excellent agreement for deep learning total plaque volume (ICC 0·949) and minimal luminal area (ICC 0·904). The mean per-patient deep learning plaque analysis time was 5·65 s (SD 1·87) versus 25·66 min (6·79) taken by experts. Over a median follow-up of 4·7 years (IQR 4·0-5·7), myocardial infarction occurred in 41 (2·5%) of 1611 patients from the SCOT-HEART trial. A deep learning-based total plaque volume of 238·5 mm3 or higher was associated with an increased risk of myocardial infarction (hazard ratio [HR] 5·36, 95% CI 1·70-16·86; p=0·0042) after adjustment for the presence of deep learning-based obstructive stenosis (HR 2·49, 1·07-5·50; p=0·0089) and the ASSIGN clinical risk score (HR 1·01, 0·99-1·04; p=0·35). INTERPRETATION: Our novel, externally validated deep learning system provides rapid measurements of plaque volume and stenosis severity from CCTA that agree closely with expert readers and intravascular ultrasound, and could have prognostic value for future myocardial infarction. FUNDING: National Heart, Lung, and Blood Institute and the Miriam & Sheldon G Adelson Medical Research Foundation.
CRIS-Team Scopus Importer:2022-04-08

Deep Learning zur Erkennung der radiographischen Sakroiliitis - Knitza, Johannes (Zeitschrift für Rheumatologie, 2021)
CRIS-Team Scopus Importer:2021-07-09

Dependency of flow-mediated vasodilatation from basal nitric oxide activity - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Jung, Susanne; Striepe, Kristina; Ott, Christian; Delles, Christian; Schmieder, Roland (Clinical Physiology and Functional Imaging, 2021)
Background: Flow-mediated vasodilatation (FMD) has become one of the most widely assessed parameters to analyse endothelial and vascular function in cardiovascular medicine. The degree of contribution of nitric oxide (NO) to FMD is inconclusive and varies widely depending on the device used. In this study, we used a semi-automatic ultrasound device to analyse to what extent basal NO activity contributes to FMD of the brachial artery. Methods: FMD was assessed with the UNEX EF device in a cross-over single blinded randomized study at baseline and then during infusion of either a NO-synthase-inhibitor (NG-monomethyl-L-arginine (L-NMMA)) or saline. The analysis was repeated after 1 week with the alternative infusion of L-NMMA or saline. All measurements were analysed both automatically and by a technician manually. Results: In total, 25 healthy men subjects completed the study. Diastolic blood pressure and heart rate significantly changed during infusion of L-NMMA. Infusion of L-NMMA reduced FMD significantly (−37%, p = 0.002). Saline solution had no effect on FMD (+14%, p = 0.392). Change in FMD was significantly different between the groups (ΔFMDL-NMMA vs. ΔFMDsaline, p = 0.032). There was a statistically significant correlation between automatically analysed results and those obtained by an experienced technician (FMDsaline: r = 0.822, p < 0.001; FMDL-NMMA: r = 0.645, p = 0.007). Conclusion: The influence of NO on FMD is approximately 40% if assessed using the UNEX EF. Prior to use FMD as a marker of endothelial dysfunction, we should explore different methods including various duration of forearm ischaemia to increase NO dependency of FMD.
CRIS-Team Scopus Importer:2021-04-02
Keywords: basal nitric oxide activity; flow-mediated vasodilatation; UNEX EF

Der alte ACS-Patient: Konservative oder interventionelle Therapie? - Gaede, Luise; Möllmann, Helge (Klinikarzt, 2019)
CRIS-Team Scopus Importer:2019-05-21

Der alte Patient mit akutem Koronarsyndrom – Konservative oder interventionelle Therapie? - Gaede, Luise; Möllmann, Helge (Deutsche Medizinische Wochenschrift, 2021)
CRIS-Team Scopus Importer:2021-01-15
Keywords: acute coronary syndrome; conservative therapy; interventional therapy

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

DETAILED ANALYSIS OF VASCULAR STIFFNESS IN PATIENTS WITH CHRONIC HEART FAILURE - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Kannenkeril, Dennis; Ott, Christan; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Risk factors for chronic heart failure (CHF) lead as well to vascular stiffness of the large arteries, increasing thereby the afterload imposed on the left ventricle and deteriorating the clinical condition of CHF. The aim of this project was twofold: to compare vascular stiffness of patients with CHF (CHF+) to those without CHF (CHF-) and to analyse whether vascular stiffness is related to the severity of CHF. DESIGN AND METHOD: In this cross-sectional project a total of 223 patients were included (CHF+: n = 105, CHF-: n = 118). Patients in an euvolaemic state with a reduced left ventricular ejection fraction (LVEF) were included in the CHF+ group. The measurement of the pulse wave velocity (PWV), the most accepted vascular stiffness parameter, and the recording of the arterial pulse wave were performed using the SphygmoCor TM XCEL System under resting conditions. Under ambulatory conditions, blood pressure (BP) and vascular stiffness parameters were assessed by a validated device (Mobil-O-Graph, I.E.M.) over 24 hours. Additionally, blood and spot urine samples were used to measure laboratory markers, in particular NT-pro-BNP. RESULTS: Vascular stiffness parameters between the CHF+ and the CHF- group differed for resting central SBP (CHF+: 116.66 ± 15.18 mmHg, CHF-: 122.83 ± 15.87 mmHg, p = 0.004) and central augmentation index (CHF+: 21.24 ± 11.76 %, CHF-: 13.69 ± 11.49 %, p = <0.001) as well as for ambulatory central SBP (CHF+: 114.46 ± 15.35 mmHg, CHF-: 120.69 ± 13.97 mmHg, p = 0.007) and PWV (CHF+: 9.39 ± 1.56 m/s, CHF-: 8.19 ± 1.65 m/s, p = <0.001). In patients with CHF, greater levels of NT-pro-BNP were related to a higher central SBP (r = 0.292, p = 0.005), higher PWV (r = 0.340, p = <0.001) and a trend to higher central PP (r = 0.198, p = 0.058), after full adjustment for CHF risk factors and gender. In accordance, higher levels of NT-pro-BNP were related to a higher ambulatory peripheral PP (r = 0.322, p = 0.002) and total peripheral resistance (r = 0.227, p = 0.041). CONCLUSIONS: In patients with stable CHF we observed a worse vascular stiffness and function, compared to patients with no CHF. The extent of vascular stiffness and dysfunction was related to the severity of CHF.
CRIS-Team Scopus Importer:2022-09-09

Detecting human coronary inflammation by imaging perivascular fat - Antonopoulos, Alexios S.; Sanna, Fabio; Sabharwal, Nikant; Thomas, Sheena; Oikonomou, Evangelos K.; Herdman, Laura; Margaritis, Marios; Shirodaria, Cheerag; Kampoli, Anna-Maria; Akoumianakis, Ioannis; Petrou, Mario; Sayeed, Rana; et al. (Science Translational Medicine, 2017)
Early detection of vascular inflammation would allow deployment of targeted strategies for the prevention or treatment of multiple disease states. Because vascular inflammation is not detectable with commonly used imaging modalities, we hypothesized that phenotypic changes in perivascular adipose tissue (PVAT) induced by vascular inflammation could be quantified using a new computerized tomography (CT) angiography methodology. We show that inflamed human vessels release cytokines that prevent lipid accumulation in PVAT-derived preadipocytes in vitro, ex vivo, and in vivo. We developed a three-dimensional PVAT analysis method and studied CT images of human adipose tissue explants from 453 patients undergoing cardiac surgery, relating the ex vivo images with in vivo CT scan information on the biology of the explants. We developed an imaging metric, the CT fat attenuation index (FAI), that describes adipocyte lipid content and size. The FAI has excellent sensitivity and specificity for detecting tissue inflammation as assessed by tissue uptake of 18F-fluorodeoxyglucose in positron emission tomography. In a validation cohort of 273 subjects, the FAI gradient around human coronary arteries identified early subclinical coronary artery disease in vivo, as well as detected dynamic changes of PVAT in response to variations of vascular inflammation, and inflamed, vulnerable atherosclerotic plaques during acute coronary syndromes. Our study revealed that human vessels exert paracrine effects on the surrounding PVAT, affecting local intracellular lipid accumulation in preadipocytes, which can be monitored using a CT imaging approach. This methodology can be implemented in clinical practice to noninvasively detect plaque instability in the human coronary vasculature.
EVALuna2:33631

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Determination of optimal fluoroscopic angulations for aorto-coronary ostial interventions from coronary computed tomography angiography - Hell, Michaela; Schlundt, Christian; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2020)
Background: An optimal aorto-coronary angiographic projection, characterized by an orthogonal visualization of the proximal coronary artery, is crucial for interventional success. We determined the distribution of optimal C-arm positions and assessed their feasibility by invasive coronary angiography. Methods: Orthogonal aorto-coronary ostial angulations were determined in 310 CT data sets. In 100 patients undergoing subsequent invasive angiography, we assessed if the CT-predicted angulations were achievable by the C-arm system. If the predicted projection was not achievable due to mechanical constraints of the C-arm system, the most close, achievable angulation was determined. Patient characteristics were analyzed regarding the distribution of optimal angulations and its feasibility by the C-arm system. Results: For the left ostium, CT revealed a mean angulation of LAO 23 ​± ​21°/cranial 25 ​± ​23° (90% of patients with a LAO/cranial angulation, 3% LAO/caudal, 4% RAO/cranial, 3% RAO/caudal) and were achievable by the C-arm system in 87% of patients. For the right ostium, the mean CT-predicted orthogonal angulation was LAO 36 ​± ​37°/cranial 36 ​± ​51° (84% LAO/cranial, 2% LAO/caudal, 14% RAO/caudal) and achievable by the C-arm system in 45% of patients. For the left ostium, a higher body weight was associated with a steeper LAO/cranial angulation being less feasible by the C-arm system due to mechanical constraints. Conclusions: Orthogonal aorto-left coronary angulations show a relative narrow distribution predominately in LAO/cranial position whereas a wider range of angulations was found for the right coronary ostium. The feasibility of CT-predicted angulations by the C-arm system is more restricted for the right than the left coronary ostium.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Angulation; Computed tomography angiography; Coronary intervention; Ostial lesion

Determination of stenotic mitral valve area: New, old, and gold standards - Flachskampf, Frank A.; Klinghammer, Lutz (European Journal of Echocardiography, 2008)

Determination of the aortic annulus plane in CT imaging - A step-by-step approach - Achenbach, Stephan; Schuhbaeck, Annika; Min, James K.; Leipsic, Jonathon (Journal of the American College of Cardiology : Cardiovascular imaging, 2013)
CRIS-Team Scopus Importer:2023-03-08

Determining microvascular obstruction and infarct size with steady-state free precession imaging cardiac MRI - Wüst, Wolfgang; Lell, Michael; May, Matthias; Scharf, Michael; Schlundt, Christian; Achenbach, Stephan; Uder, Michael; Schmid, Andrea (PLoS ONE, 2015)
In cardiac MRI (cMRI) injection of contrast medium may be performed prior to the acquisition of cine steady-state free precession (SSFP) imaging to speed up the protocol and avoid delay before late Gadolinium enhancement (LGE) imaging. Aim of this study was to evaluate whether a condensed clinical protocol with contrast cine SSFP imaging is able to detect early microvascular obstruction (MO) and determine the infarct size compared to the findings of LGE inversion recovery sequences.The study complies with the Declaration of Helsinki and was performed following approval by the ethic committee of the University of Erlangen-Nuremberg. Written informed consent was obtained from every patient. 68 consecutive patients (14 females/54 males) with acute ST-elevation myocardial infarction (STEMI) treated by percutaneous coronary revascularization were included in this study. CMRI was performed 6.6±2 days after symptom onset and MO and infarct size in early contrast SSFP cine imaging were compared to LGE imaging.MO was detected in 47/68 (69%) patients on cine SSFP and in 41/68 (60%) patients on LGE imaging. In 6 patients MO was found on cine SSFP imaging but was not detectable on LGE imaging. Infarct size on cine SSFP showed a strong agreement to LGE imaging (intraclass correlation coefficient [ICC] of 0.96 for enddiastolic, p<0.001 and 0.96 for endsystolic, p<0.001 respectively). Significant interobserver agreement was found measuring enddiastolic and endsystolic infarct size on cine SSFP imaging (p<0.01).In patients after STEMI infarct size and presence of MO can be detected with contrast cine SSFP imaging. This could be an option in patients who are limited in their ability to comply with the demands of a cMRI protocol.
EVALuna2:12029

Development of a biofabrication process for the manufacture of vessel like structures - Ruther, Florian; Singh, Raminder; Zehnder, Tobias; Cicha, Iwona; Boccaccini, Aldo R.; Detsch, Rainer (Band 17, 2016)

Device innovation in cardiovascular medicine: a report from the European Society of Cardiology Cardiovascular Round Table - Windecker, Stephan; Gilard, Martine; Achenbach, Stephan; Cribier, Alain; Delgado, Victoria; Deych, Nataliya; Drossart, Inga; Eltchaninoff, Hélène; Fraser, Alan G.; Goncalves, Alexandra; Hindricks, Gerhard; Holborow, Richard; et al. (European Heart Journal, 2024)
Research performed in Europe has driven cardiovascular device innovation. This includes, but is not limited to, percutaneous coronary intervention, cardiac imaging, transcatheter heart valve implantation, and device therapy of cardiac arrhythmias and heart failure. An important part of future medical progress involves the evolution of medical technology and the ongoing development of artificial intelligence and machine learning. There is a need to foster an environment conducive to medical technology development and validation so that Europe can continue to play a major role in device innovation while providing high standards of safety. This paper summarizes viewpoints on the topic of device innovation in cardiovascular medicine at the European Society of Cardiology Cardiovascular Round Table, a strategic forum for high-level dialogue to discuss issues related to the future of cardiovascular health in Europe. Devices are developed and improved through an iterative process throughout their lifecycle. Early feasibility studies demonstrate proof of concept and help to optimize the design of a device. If successful, this should ideally be followed by randomized clinical trials comparing novel devices vs. accepted standards of care when available and the collection of post-market real-world evidence through registries. Unfortunately, standardized procedures for feasibility studies across various device categories have not yet been implemented in Europe. Cardiovascular imaging can be used to diagnose and characterize patients for interventions to improve procedural results and to monitor devices long term after implantation. Randomized clinical trials often use cardiac imaging-based inclusion criteria, while less frequently trials randomize patients to compare the diagnostic or prognostic value of different modalities. Applications using machine learning are increasingly important, but specific regulatory standards and pathways remain in development in both Europe and the USA. Standards are also needed for smart devices and digital technologies that support device-driven biomonitoring. Changes in device regulation introduced by the European Union aim to improve clinical evidence, transparency, and safety, but they may impact the speed of innovation, access, and availability. Device development programmes including dialogue on unmet needs and advice on study designs must be driven by a community of physicians, trialists, patients, regulators, payers, and industry to ensure that patients have access to innovative care.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Artificial intelligence; Cardiac surgery; Fusion imaging; Invasive cardiology; Medical Device Regulation; Transcatheter aortic valve implantation

Dextran-coated superparamagnetic iron oxide nanoparticles for magnetic resonance imaging: Evaluation of size-dependent imaging properties, storage stability and safety - Unterweger, Harald; Dezsi, Laszlo; Matuszak, Jasmin; Janko, Christina; Poettler, Marina; Jordan, Jutta; Bäuerle, Tobias; Szebeni, Janos; Fey, Tobias; Boccaccini, Aldo R.; Alexiou, Christoph; Cicha, Iwona (International Journal of Nanomedicine, 2018)
Keywords: Irritation potential; Cross-linking; CARPA; Storage stability; SPION; MRI

Diabetes and dementia - Bahrmann, A.; Bahrmann, P.; Kubiak, Thomas; Kopf, D.; Oster, P.; Sieber, Cornel; Daniel, Werner (Zeitschrift für Gerontologie und Geriatrie, 2012)
Diabetes mellitus is a known risk factor for cognitive dysfunction and dementia. Chronic hyperglycemia, genetic predisposition, arterial hypertension, hyperlipoproteinemia, micro- and macrovascular diseases, and depression play a major role in the development of cognitive dysfunction. Both pathophysiology of diabetes and dementia and the specifics of diabetes therapy in patients with dementia are presented in this review.
Keywords: Diabetes mellitus; type 2; Dementia; Cognition disorders; Hyperglycemia; Cytokines

Diabetes care and incidence of severe hypoglycemia in nursing home facilities and nursing services: The Heidelberg Diabetes Study - Bahrmann, A.; Woerz, E.; Specht-Leible, N.; Oster, P.; Bahrmann, P. (Zeitschrift für Gerontologie und Geriatrie, 2015)
The goal of this study was to perform a structured analysis of the treatment quality and acute complications of geriatric patients with diabetes mellitus (DM) cared for by nursing services and nursing home facilities. Secondly, structural problems and potentials for improvement in the care of multimorbid older people with DM treated by nursing homes and nursing services were analysed from the viewpoint of geriatric nurses, managers of nursing homes and general practitioners.In all, 77 older persons with DM from 13 nursing homes and 3 nursing services were included in the analysis (76.6% female, HbA1c 6.9 ± 1.4%, age 81.6 ± 9.9 years). Structural problems and potentials for improvement were collected from 95 geriatric nurses, 9 managers of nursing homes and 6 general practitioners using semistandardized questionnaires.Metabolic control was too strict in care-dependent older people with DM (mean HbA1c value: 6.9 ± 1.4 %; recommended by guidelines: 7-8%). The measurement of HbA1c was performed in 16 of 77 people (20.8%) within the last year despite a high visitation frequency of the general practitioners (12.7 ± 7.7 within the last 6 months). The incidence of severe hypoglycemia was 7.8%/patient/year. Regarding the management in case of diabetes-related acute complications 33 geriatric nurses (34.7%) stated not having any written standard (nursing home 39%, geriatric services 16.7%).Complex insulin therapies are still used in older people with DM with the consequence of a high incidence of severe hypoglycemia. Concrete management standards in the case of diabetes-related acute complications for geriatric nurses are lacking for more than one third of the nursing services.
EVALuna2:10566

Diagnosis of obstructive coronary artery disease using computed tomography angiography in patients with stable chest pain depending on clinical probability and in clinically important subgroups: Meta-analysis of individual patient data - Haase, Robert; Schlattmann, Peter; Gueret, Pascal; Andreini, Daniele; Pontone, Gianluca; Alkadhi, Hatem; Hausleiter, Jörg; Garcia, Mario J.; Leschka, Sebastian; Meijboom, Willem B.; Zimmermann, Elke; Gerber, Bernhard; et al. (British Medical Journal, 2019)
Objective To determine whether coronary computed tomography angiography (CTA) should be performed in patients with any clinical probability of coronary artery disease (CAD), and whether the diagnostic performance differs between subgroups of patients. Design Prospectively designed meta-analysis of individual patient data from prospective diagnostic accuracy studies. Data sources Medline, Embase, and Web of Science for published studies. Unpublished studies were identified via direct contact with participating investigators. Eligibility criteria for selecting studies Prospective diagnostic accuracy studies that compared coronary CTA with coronary angiography as the reference standard, using at least a 50% diameter reduction as a cutoff value for obstructive CAD. All patients needed to have a clinical indication for coronary angiography due to suspected CAD, and both tests had to be performed in all patients. Results had to be provided using 2×2 or 3×2 cross tabulations for the comparison of CTA with coronary angiography. Primary outcomes were the positive and negative predictive values of CTA as a function of clinical pretest probability of obstructive CAD, analysed by a generalised linear mixed model; calculations were performed including and excluding non-diagnostic CTA results. The no-treat/treat threshold model was used to determine the range of appropriate pretest probabilities for CTA. The threshold model was based on obtained post-test probabilities of less than 15% in case of negative CTA and above 50% in case of positive CTA. Sex, angina pectoris type, age, and number of computed tomography detector rows were used as clinical variables to analyse the diagnostic performance in relevant subgroups. Results Individual patient data from 5332 patients from 65 prospective diagnostic accuracy studies were retrieved. For a pretest probability range of 7-67%, the treat threshold of more than 50% and the no-treat threshold of less than 15% post-test probability were obtained using CTA. At a pretest probability of 7%, the positive predictive value of CTA was 50.9% (95% confidence interval 43.3% to 57.7%) and the negative predictive value of CTA was 97.8% (96.4% to 98.7%); corresponding values at a pretest probability of 67% were 82.7% (78.3% to 86.2%) and 85.0% (80.2% to 88.9%), respectively. The overall sensitivity of CTA was 95.2% (92.6% to 96.9%) and the specificity was 79.2% (74.9% to 82.9%). CTA using more than 64 detector rows was associated with a higher empirical sensitivity than CTA using up to 64 rows (93.4% v 86.5%, P=0.002) and specificity (84.4% v 72.6%, P<0.001). The area under the receiver-operating-characteristic curve for CTA was 0.897 (0.889 to 0.906), and the diagnostic performance of CTA was slightly lower in women than in with men (area under the curve 0.874 (0.858 to 0.890) v 0.907 (0.897 to 0.916), P<0.001). The diagnostic performance of CTA was slightly lower in patients older than 75 (0.864 (0.834 to 0.894), P=0.018 v all other age groups) and was not significantly influenced by angina pectoris type (typical angina 0.895 (0.873 to 0.917), atypical angina 0.898 (0.884 to 0.913), non-anginal chest pain 0.884 (0.870 to 0.899), other chest discomfort 0.915 (0.897 to 0.934)). Conclusions In a no-treat/treat threshold model, the diagnosis of obstructive CAD using coronary CTA in patients with stable chest pain was most accurate when the clinical pretest probability was between 7% and 67%. Performance of CTA was not influenced by the angina pectoris type and was slightly higher in men and lower in older patients. Systematic review registration PROSPERO CRD42012002780.
CRIS-Team Scopus Importer:2019-06-25

Diagnostic accuracy of low and high tube voltage coronary CT angiography using an X-ray tube potential-tailored contrast medium injection protocol - Albrecht, Moritz H.; Nance, John W.; Schoepf, U. Joseph; Jacobs, Brian E.; Bayer, Richard R.; Litwin, Sheldon E.; Reynolds, Michael A.; Otani, Katharina; Mangold, Stefanie; Varga-Szemes, Akos; De Santis, Domenico; Eid, Marwen; et al. (European Radiology, 2018)
OBJECTIVES: To compare the diagnostic accuracy between low-kilovolt peak (kVp) (≤ 100) and high-kVp (> 100) third-generation dual-source coronary CT angiography (CCTA) using a kVp-tailored contrast media injection protocol. METHODS: One hundred twenty patients (mean age = 62.6 years, BMI = 29.0 kg/m2) who underwent catheter angiography and CCTA with automated kVp selection were separated into two cohorts (each n = 60, mean kVp = 84 and 117). Contrast media dose was tailored to the kVp level: 70 = 40 ml, 80 = 50 ml, 90 = 60 ml, 100 = 70 ml, 110 = 80 ml, and 120 = 90 ml. Contrast-to-noise ratio (CNR) was measured. Two observers evaluated image quality and the presence of significant coronary stenosis (> 50% luminal narrowing). RESULTS: Diagnostic accuracy (sensitivity/specificity) with ≤ 100 vs. > 100 kVp CCTA was comparable: per patient = 93.9/92.6% vs. 90.9/92.6%, per vessel = 91.5/97.8% vs. 94.0/96.8%, and per segment = 90.0/96.7% vs. 90.7/95.2% (all P > 0.64). CNR was similar (P > 0.18) in the low-kVp vs. high-kVp group (12.0 vs. 11.1), as ws subjective image quality (P = 0.38). Contrast media requirements were reduced by 38.1% in the low- vs. high-kVp cohort (53.6 vs. 86.6 ml, P < 0.001) and radiation dose by 59.6% (4.3 vs. 10.6 mSv, P < 0.001). CONCLUSIONS: Automated tube voltage selection with a tailored contrast media injection protocol allows CCTA to be performed at ≤ 100 kVp with substantial dose reductions and equivalent diagnostic accuracy for coronary stenosis detection compared to acquisitions at > 100 kVp. KEY POINTS: • Low-kVp coronary CT angiography (CCTA) enables reduced contrast and radiation dose. • Diagnostic accuracy is comparable between ≤ 100 and > 100 kVp CCTA. • Image quality is similar for low- and high-kVp CCTA. • Low-kVp image acquisition is facilitated by automated tube voltage selection. • Tailoring contrast injection protocols to the automatically selected kVp-level is feasible.
EVALuna2:35999

Diagnostic and prognostic performance of multiple biomarkers for acute heart failure in older patients presenting to the emergency department - Bahrmann, A.; Hofner, Benjamin; Bertsch, T.; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, Philipp (European Heart Journal, 2014)

Diagnostic Performance of Angiogram-Derived Fractional Flow Reserve: A Pooled Analysis of 5 Prospective Cohort Studies - Witberg, Guy; De Bruyne, Bernard; Fearon, William F.; Achenbach, Stephan; Engstrom, Thomas; Matsuo, Hitoshi; Kornowski, Ran (Jacc-Cardiovascular Interventions, 2020)
Objectives: This study sought to assess the diagnostic performance of FFRangio (CathWorks, Kfar Saba, Israel), an angiogram-derived fractional flow reserve (FFR) technology. Background: Despite practice guidelines recommendations, the use of coronary physiologic assessment in daily practice remains low for patients undergoing coronary angiography. Angiogram-derived FFR technologies have the potential to promote the integration of physiologic assessment in daily practice. Methods: The study performed an analysis of pooled patient- and lesion-level data from 5 prospective cohort studies that examined the diagnostic performance of FFRangio compared with the reference standard wire-based FFR. Results: A total of 700 lesions from 588 patients were analyzed. Mean age was 65 years, 71% were men, and 40% presented with acute coronary syndromes. Mean FFR and FFRangio were 0.81 ± 0.12 and 0.81 ± 0.11, with 31.6% and 31.4% of lesions were in the 0.75 to 0.85 range, respectively. When using a binary cutoff FFR value of 0.80, FFRangio showed a sensitivity of 91%, a specificity of 94%, and a diagnostic accuracy of 93%. The mean difference between FFR and FFRangio was 0.00 ± 0.12. The correlation coefficient between FFR and FFRangio was 0.83 (p < 0.001). The C-statistic for FFRangio was 0.95 (p < 0.001). The accuracy of FFRangio was consistent across all subgroups examined. Conclusions: In the largest reported cohort examining the performance of angiogram-derived FFR technology, FFRangio showed excellent diagnostic performance, which was robust and consistent across all patient and lesion subgroups. Additional studies are needed allow FFRangio and fulfill its potential expand the implementation of functional assessment of coronary lesions in routine clinical practice.
CRIS-Team Scopus Importer:2020-02-18
Keywords: coronary heart disease; coronary physiology; fractional flow reserve

Diagnostic Performance of Angiogram-Derived Fractional Flow Reserve: A Pooled Analysis of 5 Prospective Cohort Studies - Witberg, Guy; Fearon, William; Achenbach, Stephan; Engstroem, Thomas; Matsuo, Hitoshi; Kornowski, Ran; Achenbach, Stephan (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Diagnostic performance of angiography-based fractional flow reserve by patient and lesion characteristics - Kobayashi, Yuhei; Collet, Carlos; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard A.; Fournier, Stephane; Kirtane, Ajay J.; Ali, Ziad A.; Kornowski, Ran; Leon, Martin B.; De Bruyne, Bernard; et al. (EuroIntervention, 2021)
Background: A large, prospective, multicentre trial recently showed that fractional flow reserve (FFR) derived from coronary angiography (FFRangio) has an accuracy of 92% compared with conventional guide-wire-based FFR (FFRwire); however, little is known about whether specific patient/lesion characteristics affect the diagnostic performance.
CRIS-Team WoS Importer:2021-08-06

DIAGNOSTIC PERFORMANCE OF ANGIOGRAPHY-BASED FRACTIONAL FLOW RESERVE IN SUBGROUPS: REPORT FROM THE FAST-FFR STUDY - Kobayashi, Yuhei; Collet, Carlos; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard; Jeremias, Allen; Fournier, Stephane; Kirtane, Ajay; Kornowski, Ran; Greenberg, Gabriel; Jubeh, Rami; et al. (2019)
EVALuna2:213016

Diagnostic performance of noninvasive fractional flow reserve derived from coronary computed tomography angiography in suspected coronary artery disease: the NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps) - Norgaard, Bjarne L.; Leipsic, Jonathon; Gaur, Sara; Seneviratne, Sujith; Ko, Brian S.; Ito, Hiroshi; Jensen, Jesper M.; Mauri, Laura; De Bruyne, Bernard; Bezerra, Hiram; Osawa, Kazuhiro; Naber, Christoph; et al. (Journal of the American College of Cardiology, 2014)
The goal of this study was to determine the diagnostic performance of noninvasive fractional flow reserve (FFR) derived from standard acquired coronary computed tomography angiography (CTA) datasets (FFR(CT)) for the diagnosis of myocardial ischemia in patients with suspected stable coronary artery disease (CAD).FFR measured during invasive coronary angiography (ICA) is the gold standard for lesion-specific coronary revascularization decisions in patients with stable CAD. The potential for FFR(CT) to noninvasively identify ischemia in patients with suspected CAD has not been sufficiently investigated.This prospective multicenter trial included 254 patients scheduled to undergo clinically indicated ICA for suspected CAD. Coronary CTA was performed before ICA. Evaluation of stenosis (>50% lumen reduction) in coronary CTA was performed by local investigators and in ICA by an independent core laboratory. FFR(CT) was calculated and interpreted in a blinded fashion by an independent core laboratory. Results were compared with invasively measured FFR, with ischemia defined as FFR(CT) or FFR <=0.80.The area under the receiver-operating characteristic curve for FFR(CT) was 0.90 (95% confidence interval [CI]: 0.87 to 0.94) versus 0.81 (95% CI: 0.76 to 0.87) for coronary CTA (p = 0.0008). Per-patient sensitivity and specificity (95% CI) to identify myocardial ischemia were 86% (95% CI: 77% to 92%) and 79% (95% CI: 72% to 84%) for FFR(CT) versus 94% (86 to 97) and 34% (95% CI: 27% to 41%) for coronary CTA, and 64% (95% CI: 53% to 74%) and 83% (95% CI: 77% to 88%) for ICA, respectively. In patients (n = 235) with intermediate stenosis (95% CI: 30% to 70%), the diagnostic accuracy of FFR(CT) remained high.FFR(CT) provides high diagnostic accuracy and discrimination for the diagnosis of hemodynamically significant CAD with invasive FFR as the reference standard. When compared with anatomic testing by using coronary CTA, FFR(CT) led to a marked increase in specificity. (HeartFlowNXT-HeartFlow Analysis of Coronary Blood Flow Using Coronary CT Angiography [HFNXT]; NCT01757678).
EVALuna2:11982

Diagnostic Performance of Transluminal Attenuation Gradient and Noninvasive Fractional Flow Reserve Derived from 320-Detector Row CT Angiography to Diagnose Hemodynamically Significant Coronary Stenosis: An NXT Substudy - Ko, Brian S.; Wong, Dennis T. L.; Norgaard, Bjarne L.; Leong, Darryl P.; Cameron, James D.; Gaur, Sara; Achenbach, Stephan; Kuribayashi, Sachio; Kimura, Takeshi; Meredith, Ian T.; Seneviratne, Sujith K.; Marwan, Mohamed (Radiology, 2016)
PURPOSE: To compare the diagnostic performance of 320-detector row computed tomography (CT) coronary angiography-derived computed fractional flow reserve (FFR; FFRCT), transluminal attenuation gradient (TAG; TAG320), and CT coronary angiography alone to diagnose hemodynamically significant stenosis as determined by invasive FFR. MATERIALS AND METHODS: This substudy of the prospective NXT study (no. NCT01757678) was approved by each participating institution's review board, and informed consent was obtained from all participants. Fifty-one consecutive patients who underwent 320-detector row CT coronary angiographic examination and invasive coronary angiography with FFR measurement were included. Independent core laboratories determined coronary artery disease severity by using CT coronary angiography, TAG320, FFRCT, and FFR. TAG320 is defined as the linear regression coefficient between luminal attenuation and axial distance from the coronary ostium. FFRCT was computed from CT coronary angiography data by using computational fluid dynamics technology. Diagnostic performance was evaluated and compared on a per-vessel basis by the area under the receiver operating characteristic (ROC) curve (AUC). RESULTS: Among 82 vessels, 24 lesions (29%) had ischemia by FFR (FFR ≤ 0.80). FFRCT exhibited a stronger correlation with invasive FFR compared with TAG320 (Spearman ρ, 0.78 vs 0.47, respectively). Overall per-vessel accuracy, sensitivity, specificity, and positive and negative predictive values for TAG320 (<15.37) were 78%, 58%, 86%, 64%, and 83%, respectively; and those of FFRCT were 83%, 92%, 79%, 65%, and 96%, respectively. ROC curve analysis showed a significantly larger AUC for FFRCT (0.93) compared with that for TAG320 (0.72; P = .003) and CT coronary angiography alone (0.68; P = .008). CONCLUSION: FFRCT computed from 320-detector row CT coronary angiography provides better diagnostic performance for the diagnosis of hemodynamically significant coronary stenoses compared with CT coronary angiography and TAG320.
EVALuna2:12105

Diagnostic value of prehospital ECG in acute stroke patients - Bobinger, Tobias; Kallmnzer, Bernd; Kopp, Markus; Kurka, Natalia; Heider, Stefan; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Neurology, 2017)
To investigate the diagnostic yield of prehospital ECG monitoring provided by emergency medical services in the case of suspected stroke.Consecutive patients with acute stroke admitted to our tertiary stroke center via emergency medical services and with available prehospital ECG were prospectively included during a 12-month study period. We assessed prehospital ECG recordings and compared the results to regular 12-lead ECG on admission and after continuous ECG monitoring at the stroke unit.Overall, 259 patients with prehospital ECG recording were included in the study (90.3% ischemic stroke, 9.7% intracerebral hemorrhage). Atrial fibrillation (AF) was detected in 25.1% of patients, second-degree or greater atrioventricular block in 5.4%, significant ST-segment elevation in 5.0%, and ventricular ectopy in 9.7%. In 18 patients, a diagnosis of new-onset AF with direct clinical consequences for the evaluation and secondary prevention of stroke was established by the prehospital recordings. In 2 patients, the AF episodes were limited to the prehospital period and were not detected by ECG on admission or during subsequent monitoring at the stroke unit. Of 126 patients (48.6%) with relevant abnormalities in the prehospital ECG, 16.7% received medical antiarrhythmic therapy during transport to the hospital, and 6.4% were transferred to a cardiology unit within the first 24 hours in the hospital.In a selected cohort of patients with stroke, the in-field recordings of the ECG detected a relevant rate of cardiac arrhythmia. The results can add to the in-hospital evaluation and should be considered in prehospital care of acute stroke.
EVALuna2:22506

Diamond-Forrester and cardiac CT : Is there a need to redefine the pretest probability of coronary artery disease? - Schuhbaeck, A.; Kolwelter, Julie; Achenbach, Stephan (Herz, 2016)
Apart from the Diamond-Forrester classification, which is widely used particularly in the USA for the pretest probability of coronary artery disease, other scores also exist, such as an updated version of the classification table by Genders et al., the Morise score and the Duke clinical risk score. These scores estimate the probability of coronary artery disease, defined as the presence of at least one high-grade stenosis, based on symptom characteristics, age, gender and other parameters. All of the scores were derived from patient cohorts in which invasive coronary angiography had been performed for clinical reasons. It has subsequently been shown that these scores, especially those developed several decades ago, substantially overestimate the pretest probability of coronary artery disease. When these risk scores are applied to patients for whom a non-invasive work-up of suspected coronary artery disease is planned, for example by coronary computed tomography (CT) angiography, the expected prevalence of significant coronary stenosis will be overestimated. This, in turn, influences the test characteristics and the significance of the non-invasive examination (positive and negative predictive values) and needs to be taken into account when interpreting test results.
EVALuna2:33691

Differences of inflammatory cytokine profile in patients with vulnerable plaque: A coronary CTA study - Roesner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, Damini; Kilian, Tobias; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (Atherosclerosis, 2022)
Background and aims: Various pro-and anti-inflammatory biomarkers are involved in the process of atherosclerosis. We analyzed the association of different biomarkers with coronary plaque volume and vulnerable plaque subcomponents. Methods: In 301 patients undergoing coronary CT angiography (CTA), total coronary plaque volume (TPV) and subcomponents including non-calcified plaque volume (NCPV) and vulnerable plaque burden were quantified using semi-automated software. Serum was analyzed for various cytokines. Results: Out of 301 patients, 207 (69%) were male. The mean age was 59 +/- 10 years. Patients were divided using the median of TPV, NCPV and vulnerable plaque burden. In univariable analysis, patients with high TPV, high NCPV and high vulnerable plaque burden showed significant higher serum levels for IFN?, IL-1a,-2,-4,-10 and-17 and significant lower levels for IL-8 and MCP-1 (all p < 0.05). Multivariable analysis showed positive associations between high vulnerable plaque burden, IL-1a (OR 2.60, p = 0.001) and Eotaxin (OR 1.89, p = 0.020), and inverse association to MCP-1 (OR 0.33, p < 0.001), independent of age, gender and CVRF. In exploratory subanalyses, patients with presence of atherosclerosis (n = 247; 82%) showed significantly higher levels of IL-17 in all subgroups with high vulnerable plaque burden, irrespective of overall plaque volume (all p < 0.001). Conclusions: The cytokine profile significantly differs between patients with high and low coronary plaque volume. IL-1a and IL-17 seem to play a major proatherogenic role in vulnerable plaque formation, whereas MCP-1 paradoxically portends protective effects. Longitudinal studies with serial cytokine testing are needed to identify potential targets for therapeutic interventions.
CRIS-Team WoS Importer:2022-06-24
Keywords: Inflammatory biomarkers; Interleukin; Atherosclerosis; Coronary CT-angiography; Plaque volume; Vulnerable plaque

Different treatment settings of Granulocyte-Colony Stimulating Factor and their impact on T cell-specific immune response in experimental stroke - Dietel, Barbara; Cicha, Iwona; Achenbach, Stephan; Kollmar, Rainer; Garlichs, Christoph; Tauchi, Miyuki (Immunology Letters, 2014)
Cerebral ischemia is associated with infectious complications due to immunosuppression and decreased T lymphocyte activity. G-CSF, which has neuroprotective properties, is known to modulate inflammatory processes after induced stroke. The aim of our study was to investigate the impact of G-CSF in experimental stroke and to compare two different modes of treatment, focusing on circulating T lymphocytes.Cerebral ischemia was induced in Wistar rats by occlusion of the middle cerebral artery, followed by reperfusion after 1h. G-CSF was applied either as a single dose 30 min after occlusion, or daily for seven days. Silver staining was used to determine infarct size. T lymphocytes in the peripheral blood were measured before and 7 days after induced cerebral ischemia by flow cytometry. In addition, migration of CD3-expressing T lymphocytes into the brain was investigated by immunohistochemistry.Both single dose and daily treatment with G-CSF significantly reduced infarct size. A significant improvement of neurological outcome was only observed after single application of G-CSF. While a decrease in peripheral T lymphocytes was detected seven days after induced stroke, no reduction was observed in the G-CSF-treated groups. Apart from that, G-CSF significantly reduced the number of brain migrated T lymphocytes in both treatment settings as compared to vehicle.A single dose of G-CSF exerted neuroprotective effects in ischemic stroke, which were less pronounced after daily G-CSF application. Both treatment strategies inhibited stroke-induced reduction of T lymphocytes in peripheral blood, which may have contributed to the reduction of infarct size.
EVALuna2:12004

Direct coronary stenting versus predilatation followed by stent placement - Klinghammer, Lutz; et al. (American Journal of Cardiology, 2002)

Direct head-to-head comparison of convolutional long short-term memory and transformer networks for artificial Intelligence-based quantification of atherosclerotic plaque and stenosis from coronary CT angiography - Manral, Nipun; Lin, Andrew; Park, Caroline; McElhinney, Priscilla; Killekar, Aditya; Matsumoto, Hidenari; Kwiecinski, Jacek; Pieszko, Konrad; Razipour, Aryabod; Grodecki, Kajetan; Doris, Mhairi; Kwan, Alan C.; et al. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2023)
Background: Coronary computed tomography angiography (CCTA) enables non-invasive assessment of luminal stenosis and coronary atherosclerotic plaque. We aimed to directly compare the performance of 2 novel deep learning networks—convolutional long short-term memory and transformer network—for artificial intelligence-based quantification of plaque volume and stenosis severity from CCTA. Methods: This was an international multicenter study of patients undergoing CCTA at 11 sites. The deep learning (DL) convolutional neural networks were trained to segment coronary plaque in 921 patients (5,045 lesions). The training dataset was further split temporally into training (80%) and internal validation (20%) datasets. The primary DL architecture was a hierarchical convolutional long short- term memory (ConvLSTM) network. This was compared against a TransUNet network, which combines the abilities of Vision Transformer with U-Net, enabling the capture of in-depth localization information while modeling long-range dependencies. Following training and internal validation, the both DL networks were applied to an external validation cohort of 162 patients (1,468 lesions) from the SCOT-HEART trial. Results: In the external validation cohort, agreement between DL and expert reader measurements was stronger when using the ConvLSTM network than with TransUNet, for both per-lesion total plaque volume (ICC 0·953 vs 0.830) and percent diameter stenosis (ICC 0·882 vs 0.735; both p<0.001). The ConvLSTM network showed higher per-cross-section overlap with expert reader segmentations (as measured by the Dice coefficient) compared to TransUnet, for vessel wall (0.947 vs 0.946), lumen (0.93 vs 0.92), and calcified plaque (0.87 vs 0.86; p<0.0001 for all), with similar execution times. Conclusions: In a direct comparison with external validation, the ConvLSTM network yielded higher agreement with expert readers for quantification of total plaque volume and stenosis severity compared to TransUnet, with faster execution times.
CRIS-Team Scopus Importer:2023-06-02
Keywords: artificial intelligence; atherosclerosis; convolutional long short-term memory network; coronary computed tomography angiography; deep learning; transformers

Discontinuation versus continuation of renin-angiotensin-system inhibitors in COVID-19 (ACEI-COVID): a prospective, parallel group, randomised, controlled, open-label trial - Bauer, Axel; Schreinlechner, Michael; Sappler, Nikolay; Dolejsi, Theresa; Tilg, Herbert; Aulinger, Benedikt A.; Weiss, Günter; Bellmann-Weiler, Rosa; Adolf, Christian; Wolf, Dominik; Pirklbauer, Markus; Graziadei, Ivo; et al. (The Lancet Respiratory Medicine, 2021)
Background: SARS-CoV-2 entry in human cells depends on angiotensin-converting enzyme 2, which can be upregulated by inhibitors of the renin–angiotensin system (RAS). We aimed to test our hypothesis that discontinuation of chronic treatment with ACE-inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) mitigates the course orecent-onset COVID-19. Methods: ACEI-COVID was a parallel group, randomised, controlled, open-label trial done at 35 centres in Austria and Germany. Patients aged 18 years and older were enrolled if they presented with recent symptomatic SARS-CoV-2 infection and were chronically treated with ACEIs or ARBs. Patients were randomly assigned 1:1 to discontinuation or continuation of RAS inhibition for 30 days. Primary outcome was the maximum sequential organ failure assessment (SOFA) score within 30 days, where death was scored with the maximum achievable SOFA score. Secondary endpoints were area under the death-adjusted SOFA score (AUCSOFA), mean SOFA score, admission to the intensive care unit, mechanical ventilation, and death. Analyses were done on a modified intention-to-treat basis. This trial is registered with ClinicalTrials.gov, NCT04353596. Findings: Between April 20, 2020, and Jan 20, 2021, 204 patients (median age 75 years [IQR 66–80], 37% females) were randomly assigned to discontinue (n=104) or continue (n=100) RAS inhibition. Within 30 days, eight (8%) of 104 died in the discontinuation group and 12 (12%) of 100 patients died in the continuation group (p=0·42). There was no significant difference in the primary endpoint between the discontinuation and continuation group (median [IQR] maximum SOFA score 0·00 (0·00–2·00) vs 1·00 (0·00–3·00); p=0·12). Discontinuation was associated with a significantly lower AUCSOFA (0·00 [0·00–9·25] vs 3·50 [0·00–23·50]; p=0·040), mean SOFA score (0·00 [0·00–0·31] vs 0·12 [0·00–0·78]; p=0·040), and 30-day SOFA score (0·00 [10–90th percentile, 0·00–1·20] vs 0·00 [0·00–24·00]; p=0·023). At 30 days, 11 (11%) in the discontinuation group and 23 (23%) in the continuation group had signs of organ dysfunction (SOFA score ≥1) or were dead (p=0·017). There were no significant differences for mechanical ventilation (10 (10%) vs 8 (8%), p=0·87) and admission to intensive care unit (20 [19%] vs 18 [18%], p=0·96) between the discontinuation and continuation group. Interpretation: Discontinuation of RAS-inhibition in COVID-19 had no significant effect on the maximum severity of COVID-19 but may lead to a faster and better recovery. The decision to continue or discontinue should be made on an individual basis, considering the risk profile, the indication for RAS inhibition, and the availability of alternative therapies and outpatient monitoring options. Funding: Austrian Science Fund and German Center for Cardiovascular Research.
CRIS-Team Scopus Importer:2021-08-13

Does coronary CT angiography improve risk stratification over coronary calcium scoring in symptomatic patients with suspected coronary artery disease? Results from the prospective multicenter international CONFIRM registry - Al-Mallah, Mouaz H.; Qureshi, Waqas; Lin, Fay Y.; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracy Q.; Chang, Hyuk-Jae; Cademartiri, Filippo; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Cheng, Victor Y.; et al. (European Heart Journal - Cardiovascular Imaging, 2014)
The prognostic value of coronary artery calcium (CAC) scoring is well established and has been suggested for use to exclude significant coronary artery disease (CAD) for symptomatic individuals with CAD. Contrast-enhanced coronary computed tomographic angiography (CCTA) is an alternative modality that enables direct visualization of coronary stenosis severity, extent, and distribution. Whether CCTA findings of CAD add an incremental prognostic value over CAC in symptomatic individuals has not been extensively studied.We prospectively identified symptomatic patients with suspected but without known CAD who underwent both CAC and CCTA. Symptoms were defined by the presence of chest pain or dyspnoea, and pre-test likelihood of obstructive CAD was assessed by the method of Diamond and Forrester (D-F). CAC was measured by the method of Agatston. CCTAs were graded for obstructive CAD (>70% stenosis); and CAD plaque burden, distribution, and location. Plaque burden was determined by a segment stenosis score (SSS), which reflects the number of coronary segments with plaque, weighted for stenosis severity. Plaque distribution was established by a segment-involvement score (SIS), which reflects the number of segments with plaque irrespective of stenosis severity. Finally, a modified Duke prognostic index-accounting for stenosis severity, plaque distribution, and plaque location-was calculated. Nested Cox proportional hazard models for a composite endpoint of all-cause mortality and non-fatal myocardial infarction (D/MI) were employed to assess the incremental prognostic value of CCTA over CAC. A total of 8627 symptomatic patients (50% men, age 56 ± 12 years) followed for 25 months (interquartile range 17-40 months) comprised the study cohort. By CAC, 4860 (56%) and 713 (8.3%) patients had no evident calcium or a score of >400, respectively. By CCTA, 4294 (49.8%) and 749 (8.7%) had normal coronary arteries or obstructive CAD, respectively. At follow-up, 150 patients experienced D/MI. CAC improved discrimination beyond D-F and clinical variables (area under the receiver-operator characteristic curve 0.781 vs. 0.788, P = 0.004). When added sequentially to D-F, clinical variables, and CAC, all CCTA measures of CAD improved discrimination of patients at risk for D/MI: obstructive CAD (0.82, P < 0.001), SSS (0.81, P < 0.001), SIS (0.81, P = 0.003), and Duke CAD prognostic index (0.82, P < 0.0001).In symptomatic patients with suspected CAD, CCTA adds incremental discriminatory power over CAC for discrimination of individuals at risk of death or MI.
EVALuna2:11993

DONOR SPECIFIC ANTI-HLA IGA ANTIBODIES AND GRAFT SURVIVAL AFTER KIDNEY TRANSPLANTATION - Bach, Christian; Heinemann, Falko M.; Dick, Andrea; Spriewald, Bernd M.; Arnold, Martin (2018)
EVALuna2:34162

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Drug-coated balloons in the treatment of small vessel disease - Rittger, Harald; Scheller, Bruno (Heart, 2014)
EVALuna2:12012

Dual-axis rotational coronary angiography versus conventional coronary angiography: a randomized comparison - Hell, Michaela; Gilg, Melanie; Röther, Jens; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian (Clinical Research in Cardiology, 2020)
Background: Dual-axis of rotational coronary angiography (RA), with one single cine acquisition during continuous C-arm motion along a pre-described path, is an alternative to conventional coronary angiography (CA). We assessed the performance of RA versus CA in a modern, experienced cath lab setting. Methods: Sixty-seven patients with suspected coronary artery disease undergoing invasive coronary angiography were randomized to CA (n = 35) or dual-axis RA (n = 32). CA was performed with four left and two right coronary artery acquisitions with manual contrast medium injection. In RA, one cine acquisition each was performed for the left (5 projections) and right coronary artery (3 projections) with a fixed amount of contrast medium applied by a power injector. In both groups, single cine acquisitions in additional angulations were performed to fully interpret the coronary system, if necessary. Procedural parameters and outcome were compared. Results: Mean age was 63 ± 12 years (64% males). Six additional projections were required in the RA group compared to 13 in the CA group (p = 0.173). Fluoroscopy duration (CA: 3 ± 3 min, RA: 3 ± 2 min, p = 0.748) and dose area product (CA: 1291 ± 761 µGym2, RA: 1476 ± 679 µGym2, p = 0.235) did not differ significantly between both groups. For CA, the amount of contrast medium (42 ± 13 vs. 46 ± 8 ml, p = 0.022) and procedure time (8 ± 5 vs. 11 ± 3 min, p < 0.001) were significantly lower. No major adverse event occurred during hospital stay. Conclusions: Dual-axis RA represents a feasible and safe alternative method to CA for obtaining coronary angiograms. However, no superiority was observed when performed by an experienced interventionalist with a modern system.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Coronary angiography; Coronary artery disease; Dual-axis rotational coronary angiography

Dual inhibition of Src family kinases and Aurora kinases by SU6656 modulates CTGF (connective tissue growth factor) expression in an ERK-dependent manner - Cicha, Iwona; Zitzmann, Rita; Goppelt-Strübe, Margarete (International Journal of Biochemistry & Cell Biology, 2014)
Src kinases are regulators of the expression of connective tissue growth factor (CTGF/CCN2), which plays a role in fibrotic injuries. The aim of the present study was to evaluate the potential of SU6656, a dual inhibitor of Src family and Aurora kinases, to interfere with the synthesis of this pro-fibrotic factor. SU6656 impaired TGF-?-mediated upregulation of CTGF mRNA and protein in proximal epithelial HKC-8 cells, and also reduced CTGF expression in cells exposed to autocrine growth factors. In association with the inhibition of Src family kinases and diminished focal adhesion kinase activity, adherence of the cells was reduced. Furthermore, SU6656 interfered with Aurora kinase activity resulting in inhibition of cell division and formation multilobular nuclei after 24h. Comparable alterations were observed in primary tubular cells. When cell division was inhibited by SU6656 or ZM447439, a specific inhibitor of Aurora kinases, CTGF levels were back to control or even increased after 48h. The activity of RhoA-Rho kinase and ERK signaling was analyzed to delineate the signaling pathways responsible for the biphasic regulation of CTGF. While Rho kinase was not significantly altered by SU6656, ERK activity was inhibited in the early phase and increased after 24-48h. ERK activity correlated with secreted CTGF. As ZM447439 increased ERK activity only after 48h, cellular reorganization is likely responsible for triggering the ERK-dependent upregulation of CTGF. Taken together, in non-transformed epithelial cells, SU6656 modulates the expression of the pro-fibrotic factor CTGF in a time-dependent manner by inhibition of Src kinases and Aurora kinases.
EVALuna2:3674

Dual source computed tomography based analysis of stent performance, its association with valvular calcification and residual aortic regurgitation after implantation of a balloon-expandable transcatheter heart valve - Gerstmeyer, Julius; Kuetting, Maximilian; Fujita, Buntaro; Schuhbaeck, Annika; Boergermann, Jochen; Achenbach, Stephan; Steinseifer, Ulrich; Gummert, Jan; Ensminger, Stephan; Arnold, Martin (Interactive Cardiovascular and Thoracic Surgery, 2017)
Objectives: The aim of this study was to investigate the mutual influence of valvular calcifications and transcatheter aortic valve stent geometry during and after implantation of a balloon-expandable SAPIEN ® /SAPIEN XT ® prostheses. Aortic valve calcification has been linked with adverse complications after transcatheter aortic valve implantation (TAVI). However, little is known about the fate of the calcifications after TAVI as well as its influence on transcatheter heart valve geometry. Methods: Thirty one patients underwent cardiac dual source computed tomography (DSCT) before and after a TAVI with the Edwards SAPIEN/SAPIEN XT ® prostheses. Detailed DSCT image analysis was performed with Mimics ® and 3Matic ® (both Materialise, Leuven, Belgium). Results: Implanted stents reached an average degree of expansion of 84% and achieved good circularity despite the presence of fairly oval native annuli and a heterogeneous degree of valvular calcification. Both, the degree of stent expansion and the degree of stent eccentricity were inversely related to the degree of oversizing, but independent of the degree of valvular calcification and native annular ovality. Visualization of the position of calcific debris before and after TAVI showed that calcifications were shifted upwards and outwards as a consequence of the implantation procedure. The degree of stent eccentricity was related to residual aortic regurgitation grade ≥2. Conclusions: The SAPIEN ® /SAPIEN XT ® prostheses achieved good degrees of stent expansion and circularity regardless of the morphology of the landing zone. Increased stent ovality was associated with an elevated risk for aortic regurgitation. The total calcification volume, degree of annular ovality and stent expansion were not associated with residual AR.
EVALuna2:33643

Dynamic Myocardial Perfusion CT for the Detection of Hemodynamically Significant Coronary Artery Disease - Nous, Fay M. A.; Geisler, Tobias; Kruk, Mariusz B. P.; Alkadhi, Hatem; Kitagawa, Kakuya; Vliegenthart, Rozemarijn; Hell, Michaela; Hausleiter, Jorg; Nguyen, Patricia K.; Budde, Ricardo P. J.; Nikolaou, Konstantin; Kepka, Cezary; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
OBJECTIVES In this international, multicenter study, using third-generation dual-source computed tomography (CT), we investigated the diagnostic performance of dynamic stress CT myocardial perfusion imaging (CT-MPI) in addition to cor-onary CT angiography (CTA) compared to invasive coronary angiography (ICA) and invasive fractional flow reserve (FFR). BACKGROUND CT-MPI combined with coronary CTA integrates coronary artery anatomy with inducible myocardial ischemia, showing promising results for the diagnosis of hemodynamically significant coronary artery disease in single-center studies. METHODS At 9 centers in Europe, Japan, and the United States, 132 patients scheduled for ICA were enrolled; 114 patients successfully completed coronary CTA, adenosine-stress dynamic CT-MPI, and ICA. Invasive FFR was performed in vessels with 25% to 90% stenosis. Data were analyzed by independent core laboratories. For the primary analysis, for each coronary artery the presence of hemodynamically significant obstruction was interpreted by coronary CTA with CT-MPI compared to coronary CTA alone, using an FFR of #0.80 and angiographic severity as reference. Territorial absolute myocardial blood flow (MBF) and relative MBF were compared using C-statistics. RESULTS ICA and FFR identified hemodynamically significant stenoses in 74 of 289 coronary vessels (26%). Coronary CTA with 50% stenosis demonstrated a per-vessel sensitivity, specificity, and accuracy for the detection of hemody-namically significant stenosis of 96% (95% CI: 91%-100%), 72% (95% CI: 66%-78%), and 78% (95% CI: 73%-83%), respectively. Coronary CTA with CT-MPI showed a lower sensitivity (84%; 95% CI: 75%-92%) but higher specificity (89%; 95% CI: 85%-93%) and accuracy (88%; 95% CI: 84%-92%). The areas under the receiver-operating characteristic curve of absolute MBF and relative MBF were 0.79 (95% CI: 0.71-0.86) and 0.82 (95% CI: 0.74-0.88), respectively. The median dose-length product of CT-MPI and coronary CTA were 313 mGy center dot cm and 138 mGy center dot cm, respectively. CONCLUSIONS Dynamic CT-MPI offers incremental diagnostic value over coronary CTA alone for the identification of hemodynamically significant coronary artery disease. Generalized results from this multicenter study encourage broader consideration of dynamic CT-MPI in clinical practice. (Dynamic Stress Perfusion CT for Detection of Inducible Myocardial Ischemia [SPECIFIC]; NCT02810795) (J Am Coll Cardiol Img 2022;15:75-87) (c) 2022 The Authors. Published by Elsevier on behalf of the American College of Cardiology Foundation. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2022-01-21

Early diagnosis of acute coronary syndrome - Katus, Hugo; Ziegler, Andre; Ekinci, Okan; Giannitsis, Evangelos; Stough, Wendy Gattis; Achenbach, Stephan; Blankenberg, Stefan; Brueckmann, Martina; Collinson, Paul; Comaniciu, Dorin; Crea, Filippo; Dinh, Wilfried; et al. (European Heart Journal, 2017)
The diagnostic evaluation of acute chest pain has been augmented in recent years by advances in the sensitivity and precision of cardiac troponin assays, new biomarkers, improvements in imaging modalities, and release of new clinical decision algorithms. This progress has enabled physicians to diagnose or rule-out acute myocardial infarction earlier after the initial patient presentation, usually in emergency department settings, which may facilitate prompt initiation of evidence-based treatments, investigation of alternative diagnoses for chest pain, or discharge, and permit better utilization of healthcare resources. A non-trivial proportion of patients fall in an indeterminate category according to rule-out algorithms, and minimal evidence-based guidance exists for the optimal evaluation, monitoring, and treatment of these patients. The Cardiovascular Round Table of the ESC proposes approaches for the optimal application of early strategies in clinical practice to improve patient care following the review of recent advances in the early diagnosis of acute coronary syndrome. The following specific 'indeterminate' patient categories were considered: (i) patients with symptoms and high-sensitivity cardiac troponin <99th percentile; (ii) patients with symptoms and high-sensitivity troponin <99th percentile but above the limit of detection; (iii) patients with symptoms and high-sensitivity troponin >99th percentile but without dynamic change; and (iv) patients with symptoms and high-sensitivity troponin >99th percentile and dynamic change but without coronary plaque rupture/erosion/dissection. Definitive evidence is currently lacking to manage these patients whose early diagnosis is 'indeterminate' and these areas of uncertainty should be assigned a high priority for research.
EVALuna2:33609

Early-onset coronary atherosclerosis in patients with low levels of omega-3 fatty acids - Bittner, D. O.; Göller, Markus; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (European Journal of Clinical Nutrition, 2020)
Objectives: Coronary artery calcification (CAC) can reliably predict cardiovascular events. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are thought to inhibit vascular calcification on a cellular level and in animal models, however, the correlation in humans is controversial. Methods: In symptomatic patients, CAC was quantified according to Agatstons’ method using non-contrast coronary CT. We assessed the association of EPA and DHA with early-onset coronary atherosclerosis, defined as presence of CAC above the 75th Agatston-Score (AS) percentile in sex adjusted age categories. Erythrocyte fatty acid composition was analyzed with a standardized methodology. The percentage of EPA and DHA in relation to all fatty acids present in the erythrocyte membrane is regarded the Omega-3 Index®. Results: Among 71 patients, 51 were below and 20 were above the 75th AS-percentile. No differences were seen in age, gender, cardiovascular risk factors, and relevant medication. In univariable analysis, significantly lower values for EPA (0.77%[0.63; 0.97] vs. 0.93%[0.72; 1.21]; p = 0.045), DHA (4.90%[4.12; 5.57] vs. 5.50%[4.58; 6.52]; p = 0.038) and the Omega-3 Index (5.73%[4.75; 6.35] vs. 6.22%[5.46; 7.71]; p = 0.034) were seen in patients above the 75th AS-percentile. All other fatty acids showed no significant differences. In multivariable analysis, the Omega-3 Index showed a significant inverse association with early onset of CAC (OR: 0.533 (95%CI: 0.303–0.938; p = 0.029)), independent of age, gender, statin use, and creatinine level (all p > 0.05). Conclusions: Low levels of EPA and DHA (Omega-3 Index) are associated with early-onset coronary atherosclerosis. This finding needs to be validated in larger cohorts and might help understand the beneficial cardiovascular effects of omega-3 fatty acids.
CRIS-Team Scopus Importer:2020-01-21

Early repolarization, left ventricular diastolic function, and left atrial size in professional soccer players - Wilhelm, Matthias; Brem, Matthias; Rost, Christian; Klinghammer, Lutz; Hennig, Friedrich; Daniel, Werner; Flachskampf, Frank (American Journal of Cardiology, 2010)
Recent data have suggested a relation among long-term endurance sport practice, left atrial remodeling, and atrial fibrillation. We investigated the influence of an increased vagal tone, represented by the early repolarization (ER) pattern, on diastolic function and left atrial size in professional soccer players. Fifty-four consecutive athletes underwent electrocardiography, echocardiography, and exercise testing as part of their preparticipation screening. Athletes were divided into 2 groups according to presence or absence of an ER pattern, defined as a ST-segment elevation at the J-point (STE) <0.1 mm in 2 leads. For linear comparisons average STE was calculated. Mean age was 24 ± 4 years. Twenty-five athletes (46%) showed an ER pattern. Athletes with an ER pattern had a significant lower heart rate (54 ± 9 vs 62 ± 11 beats/min, p = 0.024), an increased E/e′ ratio (6.1 ± 1.2 vs 5.1 ± 1.0, p = 0.002), and larger volumes of the left atrium (25.6 ± 7.3 vs 21.8 ± 5.0 ml/m2, p = 0.031) compared to athletes without an ER pattern. There were no significant differences concerning maximum workload, left ventricular dimensions, and systolic function. Univariate regression analysis revealed significant correlations among age, STE, and left atrial volume. In a stepwise multivariate regression analysis age, STE and e′ contributed independently to left atrial size (r = 0.659, p <0.001). In conclusion, athletes with an ER pattern had an increased E/e′ ratio, reflecting a higher left atrial filling pressure, contributing to left atrial remodeling over time. © 2010 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10

Early single center experience with a novel transcatheter anuloplasty system for the treatment of functional tricuspid regurgitation - Landendinger, M.; Smolka, S.; Tröbs, Monique; Anneken, Lars; Gaede, L.; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Easy-to-Prepare Coating of Standard Cell Culture Dishes for Cell-Sheet Engineering Using Aqueous Solutions of Poly(2-n-propyl-oxazoline) - Ryma, Matthias; Bloehbaum, Julia; Singh, Raminder; Sancho, Ana; Matuszak, Jasmin; Cicha, Iwona; Groll, Juergen (ACS Biomaterials Science and Engineering, 2019)
Cell-sheet technology is a well-known method by which cells are grown on thermoswitchable substrates that become nonadhesive upon cooling, such that a complete layer of adherent cells, along with the produced extracellular matrix, detaches as a sheet. Polymers that exhibit a lower critical solution temperature (LCST) below physiological temperature in water, commonly poly(N-isopropylacrylamide) (PNIPAM), are covalently grafted or, for block copolymers, physisorbed onto substrates in a monomolecular thin film to achieve this. Consequently, such substrates, and the polymers required for film formation, can only be prepared in a chemical lab with profound macromolecular expertise. In this study, we present an easy and robust method to coat standard cell culture dishes with aqueous solutions of commercially available poly(-n-propy1-2-oxazoline) (PnPrOx), a polymer that exhibits LCST behavior. Different standard cell culture dishes were repeatedly coated with 0.1 wt % aqueous solutions of PnPrOx and dried in an oven to create a fully covered and thermoresponsive surface. Using this PnPrOx surface a variety of cell types including endothelial cells, mesenchymal stem cells, and fibroblasts, were seeded and cultured until confluency. By decreasing the temperature to 16 degrees C, viable cell sheets were detached within cell-type dependent time frames and could be harvested for biological analysis. We show that the cytoskeleton rearranges, leading to a more contracted morphology of the cells in the detached cell sheet. The cellular junctions between single cells within the sheet could be detected using immunostainings, indicating that strong and intact intracellular contacts are preserved in the harvested sheets.
CRIS-Team WoS Importer:2019-03-29

Effect of Arteriovenous Anastomosis on Blood Pressure Reduction in Patients With Isolated Systolic Hypertension Compared With Combined Hypertension - Ott, Christian; Lobo, Melvin D.; Sobotka, Paul A.; Mahfoud, Felix; Stanton, Alice; Cockcroft, John; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al. (Journal of the American Heart Association, 2016)
Options for interventional therapy to lower blood pressure (BP) in patients with treatment-resistant hypertension include renal denervation and the creation of an arteriovenous anastomosis using the ROX coupler. It has been shown that BP response after renal denervation is greater in patients with combined hypertension (CH) than in patients with isolated systolic hypertension (ISH). We analyzed the effect of ROX coupler implantation in patients with CH as compared with ISH.The randomized, controlled, prospective ROX Control Hypertension Study included patients with true treatment-resistant hypertension (office systolic BP >=140 mm Hg, average daytime ambulatory BP >=135/85 mm Hg, and treatment with >=3 antihypertensive drugs including a diuretic). In a post hoc analysis, we stratified patients with CH (n=31) and ISH (n=11). Baseline office systolic BP (177±18 mm Hg versus 169±17 mm Hg, P=0.163) and 24-hour ambulatory systolic BP (159±16 mm Hg versus 154±11 mm Hg, P=0.463) did not differ between patients with CH and those with ISH. ROX coupler implementation resulted in a significant reduction in office systolic BP (CH: -29±21 mm Hg versus ISH: -22±31 mm Hg, P=0.445) and 24-hour ambulatory systolic BP (CH: -14±20 mm Hg versus ISH: -13±15 mm Hg, P=0.672), without significant differences between the two groups. The responder rate (office systolic BP reduction >=10 mm Hg) after 6 months was not different (CH: 81% versus ISH: 82%, P=0.932).Our data suggest that creation of an arteriovenous anastomosis using the ROX coupler system leads to a similar reduction of office and 24-hour ambulatory systolic BP in patients with combined and isolated systolic hypertension.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01642498.
EVALuna2:3926

Effect of empagliflozin on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Striepe, Kristina; Jung, Susan; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Recent studies indicated that sodium glucose cotransporter (SGLT)2 inhibition increases levels of ketone bodies in the blood in patients with type 1 and 2 diabetes. Other studies suggested that in patients with chronic heart failure (CHF), increased myocardial oxygen demand can be provided by ketone bodies as a fuel substrate. Experimental studies reported that ketone bodies, specifically beta-hydroxybutyrate (β-OHB) may increase blood pressure (BP) by impairing endothelium-dependant relaxation, thereby leading to increased vascular stiffness. In our study we assessed whether the SGLT 2 inhibition with empagliflozin increases ketone bodies in patients with stable CHF and whether such an increase impairs BP and vascular function. Methods: In a prospective, double blind, placebo controlled, parallel-group single centre study 75 patients with CHF (left ventricular ejection fraction 39.0 ± 8.2%) were randomised (2:1) to the SGLT-2 inhibitor empagliflozin 10 mg orally once daily or to placebo, 72 patients completed the study. After a run-in phase we evaluated at baseline BP by 24 h ambulatory blood pressure (ABP) monitoring, vascular stiffness parameters by the SphygmoCor system (AtCor Medical, Sydney, NSW, Australia) and fasting metabolic parameters, including β-OHB by an enzymatic assay (Beckman Coulter DxC 700 AU). The same measurements were repeated 12 weeks after treatment. In 19 of the 72 patients serum levels of β-OHB were beneath the lower border of our assay (< 0.05 mmol/l) therefore being excluded from the subsequent analysis. Results: In patients with stable CHF, treatment with empagliflozin (n = 36) was followed by an increase of β-OHB by 33.39% (p = 0.017), reduction in 24 h systolic (p = 0.038) and diastolic (p = 0.085) ABP, weight loss (p = 0.003) and decrease of central systolic BP (p = 0.008) and central pulse pressure (p = 0.008). The increase in β-OHB was related to an attenuated decrease of empagliflozin-induced 24 h systolic (r = 0.321, p = 0.069) and diastolic (r = 0.516, p = 0.002) ABP and less reduction of central systolic BP (r = 0.470, p = 0.009) and central pulse pressure (r = 0.391, p = 0.033). No significant changes were seen in any of these parameters after 12 weeks of treatment in the placebo group (n = 17). Conclusion: In patients with stable CHF ketone bodies as assessed by β-OHB increased after treatment with empagliflozin. This increase led to an attenuation of the beneficial effects of empagliflozin on BP and vascular parameters. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT03128528).
CRIS-Team Scopus Importer:2021-11-19

Effect of non-compliant balloon postdilatation on magnesium-based bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Weissner, Melissa; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: Optimal implantation results of bioresorbable scaffolds (BRS) are typically assumed to require postdilatation with non-compliant (NC) balloons to achieve full scaffold apposition and minimize event rates. We systematically evaluated the mechanical effect of NC balloon postdilatation on magnesium-based BRS (Magmaris (R), Biotronik AG, Bulach, Switzerland) in vivo.
CRIS-Team WoS Importer:2019-03-08

Effect of Plaque Composition, Morphology, and Burden on DESolve Novolimus-Eluting Bioresorbable Vascular Scaffold Expansion and Eccentricity - An Optical Coherence Tomography Analysis - Boeder, Niklas F.; Doerr, Oliver; Bauer, Timm; Elsaesser, Albrecht; Moellmann, Helge; Achenbach, Stephan; Hamm, Christian W.; Nef, Holger M. (Cardiovascular Revascularization Medicine, 2019)
Objective: This study of patients treated with novolimus-eluting bioresorbable scaffold (BRS) investigated the impact of plaque burden on the acute mechanical performance of the BRS and the short-term outcome.
CRIS-Team WoS Importer:2019-06-18

Effect of SGLT2 inhibition on ketone bodies in patients with stable chronic heart failure - Pietschner, Robert; Kolwelter, Julie; Bosch, Agnes; Kannenkeril, Dennis; Ott, C.; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

Effect of the ratio of coronary arterial lumen volume to left ventricle myocardial mass derived from coronary CT angiography on fractional flow reserve - Taylor, Charles A.; Gaur, Sara; Leipsic, Jonathon; Achenbach, Stephan; Berman, Daniel S.; Jensen, Jesper M.; Dey, Damini; Botker, Hans Erik; Kim, Hyun Jin; Khem, Sophie; Wilk, Alan; Zarins, Christopher K.; et al. (Journal of Cardiovascular Computed Tomography, 2017)
BACKGROUND: We hypothesize that in patients with suspected coronary artery disease (CAD), lower values of the ratio of total epicardial coronary arterial lumen volume to left ventricular myocardial mass (V/M) result in lower fractional flow reserve (FFR). METHODS: V/M was computed in 238 patients from the NXT trial who underwent coronary computed tomography angiography (CTA), quantitative coronary angiography (QCA) and FFR measurement in 438 vessels. Nitroglycerin was administered prior to CT, QCA and FFR acquisition. The V/M ratio was quantified on a patient-level from CT image data by segmenting the epicardial coronary arterial lumen volume (V) and the left ventricular myocardial mass (M). Calcified and noncalcified plaque volumes were quantified using semi-automated software. RESULTS: The median value of V/M (18.57 mm3/g) was used to define equal groups of low and high V/M patients. Patients with low V/M had greater diameter stenosis by QCA, more plaque and lower FFR (0.80 ± 0.12 vs. 0.87 ± 0.08; P < 0.0001) than those with high V/M. A total of 365 vessels in 202 patients had QCA stenosis ≤50% and measured FFR. In these patients, those with low V/M had higher percent diameter stenosis by QCA, greater total plaque volume and lower FFR (0.81 ± 0.12 vs. 0.88 ± 0.07; P < 0.0001) than those with high V/M. In multivariate logistic regression analysis, V/M was an independent predictor of FFR ≤0.80 (all p-values < 0.001). CONCLUSIONS: Patients with a low V/M ratio have lower FFR overall and in non-obstructive CAD, independent of plaque measures.
EVALuna2:33603

Effects of a diuretic regimen on body weight and echocardiographic parameters of the tricuspid valve in patients scheduled for transcatheter tricuspid annuloplasty - Landendinger, M.; Haug, J.; Achenbach, Stephan; Arnold, Martin (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Effects of cardiac medications for patients with obstructive coronary artery disease by coronary computed tomographic angiography: results from the multicenter CONFIRM registry - Schulman-Marcus, Joshua; Hartaigh, Briain O.; Giambrone, Ashley E.; Gransar, Heidi; Valenti, Valentina; Berman, Daniel S.; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Callister, Tracy Q.; et al. (Atherosclerosis, 2015)
This study sought to determine the correlation between baseline cardiac medications and cardiovascular outcomes in patients with obstructive coronary artery disease (CAD) diagnosed by coronary computed tomographic angiography (CCTA).1637 patients (mean age 64.8 ± 10.2 years, 69.6% male) with obstructive CAD from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry were followed over the course of three years. Obstructive CAD was defined as a >=50% stenosis in an epicardial vessel. Medications analyzed included statins, aspirin, beta-blockers, angiotensin converting enzyme (ACE) inhibitors, and angiotensin receptor blockers (ARBs). Using Cox proportional-hazards models, we calculated the hazard ratio (HR) with 95% confidence intervals (95% CIs) for incident major adverse cardiovascular events (MACE), defined as death, acute coronary syndrome, or myocardial infarction.At the time of CCTA, 59%, 54%, 40%, and 46% of patients were using statins, aspirin, beta-blockers, and ACE inhibitors or ARBs, respectively. Statins were associated with a 43% (95% CI = 0.38-0.87, p = 0.008) lower adjusted risk of MACE. Following adjustment, aspirin, beta-blockers, ACE inhibitors and ARBs did not attenuate the risk of MACE. When restricted to patients with multivessel obstructive CAD, only statins were associated with lower risk of MACE.In patients with obstructive CAD by CCTA, the baseline use of statins was associated with improved clinical outcomes. Other cardiac medications-including aspirin, beta-blockers, ACE inhibitors, and ARBs-were not associated with reduced risk of MACE.
EVALuna2:11988

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Effects of the sodium-glucose cotransporter 2 inhibitor empagliflozin on vascular function in patients with chronic heart failure - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Stabel, Lena; Kannenkeril, Dennis; Ott, Christian; Bramlage, Peter; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims Impairment of vascular function contributes to the progression of chronic heart failure (HF) by increasing the afterload. Treatment with selective sodium-glucose cotransporter 2 (SGLT2) inhibitors improves the prognosis of HF, but the precise mechanisms remain unclear. The aim of this study was to analyse the effect of empagliflozin on vascular function in patients with HF.
CRIS-Team WoS Importer:2021-10-01

Effects of weak/non-complement-binding HLA antibodies on C1q-binding - Hönger, G.; Amico, P.; Spriewald, B. M.; Schaub, S.; Arnold, Martin (HLA, 2017)
It is unknown under what conditions and to what extent weak/non-complement (C)-binding IgG subclasses (IgG2/IgG4) can block C1q-binding triggered by C-binding IgG subclasses (IgG1/IgG3). Therefore, we investigated in vitro C1q-binding induced by IgG subclass mixtures targeting the same HLA epitope. Various mixtures of HLA class II specific monoclonal antibodies of different IgG subclasses but identical V-region were incubated with HLA DRB1*07:01 beads and monitored for C1q-binding. The lowest concentration to achieve maximum C1q-binding was measured for IgG3, followed by IgG1, while IgG2 and IgG4 did not show appreciable C1q-binding. C1q-binding occurred only after a critical amount of IgG1/3 has bound and sharply increased thereafter. When both, C-binding and weak/non-C-binding IgG subclasses were mixed, C1q-binding was diminished proportionally to the fraction of IgG2/4. A 2- to 4-fold excess of IgG2/4 inhibited C1q-binding by 50%. Very high levels (10-fold excess) almost completely abrogated C1q-binding even in the presence of significant IgG1/3 levels that would usually lead to strong C1q-binding. In sensitized renal allograft recipients, IgG subclass constellations with >= 2-fold excess of IgG2/4 over IgG1/3 were present in 23/66 patients (34.8%) and overall revealed slightly decreased C1q signals. However, spiking of patient sera with IgG2 targeting a different epitope than the patient's IgG1/3 synergistically increased C1q-binding. In conclusion, if targeting the same epitope, an excess of IgG2/4 is repressing the extent of IgG1/3 triggered C1q-binding in vitro. Such IgG subclass constellations are present in about a third of sensitized patients and their net effect on C1q-binding is slightly inhibitory.
EVALuna2:13437

Efficacy of a Psychological Single-Session Intervention in Non-Cardiac Chest Pain: Are Chest Pain Perceptions Relevant? - Schroeder, Stefanie; Achenbach, Stephan; Martin, Alexandra (Journal of Psychology / Zeitschrift für Psychologie, 2020)
Despite medical reassurance, non-cardiac chest pain (NCCP) frequently persists. Psychological interventions seem promising, but single-session interventions (SSI) are under-studied. To analyze the efficacy of a SSI focusing on chest pain perceptions in a randomized controlled trial (RCT), and to identify predictors of pain persistence. Individuals presenting with NCCP to a cardiology unit were randomly assigned to SSI (N = 54) or treatment as usual (N = 59). Follow-up assessments were 1 month (FU1) and 6 months (FU2) later. Primary outcome measures were chest pain (German Pain Questionnaire) and chest pain perceptions (IPQ-B, Reassurance Scale). Two by Three ANOVAs revealed significant improvements over time, but against expectation no significant interaction with group. Health concern and cardiac attribution following cardiac testing predicted FU2 chest pain (p's ≤ .018). These predictors could serve as markers to identify individuals with a risk for persisting complaints, a group that may benefit from interventions addressing dysfunctional illness perceptions.
CRIS-Team Scopus Importer:2020-06-05
Keywords: brief psychological intervention; illness representations; non-cardiac chest pain; reassurance

Empfehlungen zur prähospitalen Behandlung des akuten Koronarsyndroms bei Patienten unter Dauertherapie mit neuen oralen Antikoagulanzien (NOAKs) - Hamm, Christian W.; Schneck, Emmanuel; Buerke, Michael; Darius, Harald; Gaede, Luise; Bergmann, Martin; Hoffmeister, Martin; Schneck, Franziska; Gräsner, Jan Thorsten; Dirkmann, Daniel; Sander, Michael (Der Kardiologe, 2021)
The anticoagulation strategy in patients suffering from an acute coronary syndrome prior to hospital admission plays a pivotal role in the treatment. Patients treated with non-vitamin K antagonist oral anticoagulants (NOACs) are at a higher risk for bleeding complications but currently no specific recommendations for the prehospital anticoagulation management of these patients exists. This joint consensus paper summarizes the current knowledge and makes recommendations for the treatment of this particular patient group. In summary, patients suffering from an acute coronary syndrome with ST-elevation should receive acetylsalicylic acid and heparin independently of the last intake of non-vitamin K antagonist oral anticoagulants. Furthermore, acetylsalicylic acid is indicated in patients presenting with angina pectoris and lack of ST-elevation while heparin should only be administered after careful individual consideration of the risks and benefits.
CRIS-Team Scopus Importer:2021-02-05
Keywords: ACS; Anticoagulation; Bleeding; NSTEMI; STEMI

Enzymatic lipid oxidation by eosinophils propagates coagulation, hemostasis, and thrombotic disease. - Uderhardt, Stefan; Ackermann, Jochen A.; Fillep, Tobias; Hammond, Victoria J.; Willeit, Johann; Santer, Peter; Mayr, Manuel; Biburger, Markus; Miller, Meike; Zellner, Katie R.; Stark, Konstantin; Zarbock, Alexander; et al. (Journal of Experimental Medicine, 2017)
Blood coagulation is essential for physiological hemostasis but simultaneously contributes to thrombotic disease. However, molecular and cellular events controlling initiation and propagation of coagulation are still incompletely understood. In this study, we demonstrate an unexpected role of eosinophils during plasmatic coagulation, hemostasis, and thrombosis. Using a large-scale epidemiological approach, we identified eosinophil cationic protein as an independent and predictive risk factor for thrombotic events in humans. Concurrent experiments showed that eosinophils contributed to intravascular thrombosis by exhibiting a strong endogenous thrombin-generation capacity that relied on the enzymatic generation and active provision of a procoagulant phospholipid surface enriched in 12/15-lipoxygenase-derived hydroxyeicosatetraenoic acid-phosphatidylethanolamines. Our findings reveal a previously unrecognized role of eosinophils and enzymatic lipid oxidation as regulatory elements that facilitate both hemostasis and thrombosis in response to vascular injury, thus identifying promising new targets for the treatment of thrombotic disease.

Epicardial adipose tissue density and volume are related to subclinical atherosclerosis, inflammation and major adverse cardiac events in asymptomatic subjects - Goeller, Markus; Achenbach, Stephan; Doris, Mhairi K.; Cadet, Sebastien; Commandeur, Frederic; Chen, Xi; Slomka, Piotr J.; Gransar, Heidi; Cao, J. Jane; Wong, Nathan D.; Albrecht, Moritz H.; Rozanski, Alan; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We investigated whether epicardial adipose tissue (EAT) volume and density are related to early atherosclerosis, plaque inflammation and major adverse cardiac events (MACE, cardiac death and myocardial infarction) in asymptomatic subjects. METHODS: EAT volume and density were quantified from non-contrast cardiac CT in 456 asymptomatic individuals (age 60.3 ± 8.3; 68% with CCS>0) from the prospective EISNER trial. EAT volume and density were examined in relation to coronary calcium score (CCS), inflammatory biomarkers and MACE. RESULTS: EAT volume was higher and EAT density lower in subjects with coronary calcium compared to subjects without [89 vs 74 cm3, p < 0.001] [-76.9 vs -75.7 HU,p = 0.024]. EAT volume was lowest in individuals with no coronary calcium and was significant higher in subjects with early atherosclerosis (CCS 1-99) [74 vs 87 cm3,p = 0.016] and in subjects with more advanced atherosclerosis (CCS≥100) [89 cm3,p = 0.002]). EAT volume was independently related to serum levels of PAI-1, and MCP-1 and inversely related to adiponectin and HDL-cholesterol (p < 0.05). EAT density was inversely related to PAI-1 and LDL-cholesterol and positively associated to adiponectin, sICAM-1 and HDL-cholesterol (p < 0.05). EAT density was more significantly associated with MACE [(HR 0.8, 95%CI:0.7-0.98), p = 0.029] than EAT volume or CCS. CONCLUSION: EAT volume was higher and density lower in subjects with coronary calcium compared to subjects with CCS = 0, with similar EAT volume in CCS<100 and CCS≥100. Lower EAT density and increased EAT volume were associated with coronary calcification, serum levels of plaque inflammatory markers and MACE, suggesting that dysfunctional EAT may be linked to early plaque formation and inflammation.
EVALuna2:33591

Epicardial adipose tissue volume but not density is an independent predictor for myocardial ischemia - Hell, Michaela M.; Ding, Xiaowei; Rubeaux, Mathieu; Slomka, Piotr; Gransar, Heidi; Terzopoulos, Demetri; Hayes, Sean; Achenbach, Stephan; Berman, Daniel S.; Dey, Damini; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
BACKGROUND: Epicardial adipose tissue (EAT) volume is associated with plaque formation and cardiovascular event risk, its density may reflect tissue composition and metabolic activity. OBJECTIVES: Global and regional associations between EAT volume and density, ischemia and coronary calcium were investigated using a novel automatic quantitative measurement software. METHODS: 71 patients with an intermediate pre-test probability for coronary artery disease and inducible ischemia by SPECT were matched to two same-gender controls (total of 213 patients, 90% male, age 60 ± 10 years). Non-contrast CT for assessment of EAT volume, density (in Hounsfield Unit [HU]) and coronary calcium score (CCS) was performed. RESULTS: Global EAT volume was significantly increased in ischemic patients compared to controls (96 ± 49 vs. 82 ± 36 cm(3), p = 0.04), density showed no significant difference (-75.6 ± 4.3 vs. -75.1 ± 4.1HU, p = 0.63). EAT volume and density differed significantly between coronary territories (LAD: 37 ± 18 cm(3), -77.8 ± 4.5HU; LCx: 16 ± 9 cm(3), -73.9 ± 4.1HU; RCA: 36 ± 17 cm(3), -71.7 ± 4.8HU, p < 0.001). For regional ischemia, only LCx territory showed a significantly higher EAT volume (18 ± 8 vs. 16 ± 9 cm(3), p = 0.048). Multivariable logistic regression revealed a significant association with ischemia for EAT volume (OR 2.09 (1.0; 4.3), p = 0.049) and CCS (OR 1.43 (1.1; 1.9), p = 0.006). EAT volume significantly improved discrimination of ischemia over CCS (Integrated Discrimination Improvement: 3.5%, 95%CI: 1.1-6.1%, p = 0.004). Hypertension was the only risk factor significantly influencing EAT volume and density (98 ± 48 vs. 78 ± 31 cm(3), p = 0.002, -76.0 ± 4.1 vs. -74.5 ± 4.1 HU, p = 0.01). CONCLUSIONS: EAT volume is associated with myocardial ischemia and improves the discriminative power for independent ischemia prediction over CCS. In hypertensive patients, EAT is characterized by lower density and higher volumes.
EVALuna2:12102

Epicardial fat and coronary artery calcification in patients on long-term hemodialysis - Gauss, Soeren; Klinghammer, Lutz; Jahn, Daniela; Schuhbaeck, Annika; Achenbach, Stephan; Marwan, Mohamed (Journal of Computer Assisted Tomography, 2014)
Introduction: Recent studies have shown a significant correlation between increased epicardial fat volume (EFV) andmortality, coronary artery disease events, andmeasures of coronary atherosclerotic burden, for example, coronary calcium. Patients with chronic kidney disease on hemodialysis have an increased prevalence of coronary atherosclerosis and coronary calcium. The mechanisms underlying both may differ from patients with normal kidney function. Only limited data are available on the relationship between epicardial fat and coronary calcium in these patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary artery calcification; Dialysis; Epicardial fat

Epicardial fat, cardiovascular risk factors and calcifications in patients with chronic kidney disease - Saritas, Turgay; Reinartz, Sebastian Daniel; Nadal, Jennifer; Schmoee, Jonas; Schmid, Matthias; Achenbach, Stephan; Stoerk, Stefan; Wanner, Christoph; Floege, Jurgen; Schneider, Markus; Schlieper, Georg; Marwan, Mohamed; et al. (Clinical Kidney Journal, 2020)
Background. Epicardial adipose tissue (EAT) exerts cardiopathogenic effects, but the independent association between EAT and cardiovascular (CV) calcification in patients with chronic kidney disease (CKD) remains controversial. We therefore assessed the association between EAT, CV risk factors and CV calcifications.
CRIS-Team WoS Importer:2020-10-30

Erratum to: Comparative assessment of image quality for coronary CT angiography with iobitridol and two contrast agents with higher iodine concentrations: iopromide and iomeprol. A multicentre randomized double-blind trial - Achenbach, Stephan; Paul, Jean-Francois; Laurent, Francois; Becker, Hans-Christoph; Rengo, Marco; Caudron, Jerome; Leschka, Sebastian; Vignaux, Olivier; Knobloch, Gesine; Benea, Giorgio; Schlosser, Thomas; Andreu, Jordi; et al. (European Radiology, 2017)
EVALuna2:33653

ESC Congress 2017 in Barcelona: Where the World of Cardiology Came Together - Bax, Jeroen J.; Achenbach, Stephan (Circulation, 2017)
EVALuna2:33611

ESC Congress Munich 2018 - Achenbach, Stephan (European Heart Journal, 2018)
EVALuna2:35964

Ethnic differences in coronary anatomy, left ventricular mass and CT-derived fractional flow reserve - Ihdayhid, Abdul Rahman; Thakur, Udit; Yap, Grace; Göller, Markus; Nerlekar, Nitesh; Adams, Daniel; Isa, Mourushi; Joshi, Mitwa; Cameron, James; Seneviratne, Sujith; Dey, Damini; Achenbach, Stephan; et al. (Journal of Cardiovascular Computed Tomography, 2020)
Background: Studies have observed higher incidence of cardiovascular mortality in South Asians (SA), and lower prevalence in East Asians (EA), compared with Caucasians. These observations are not entirely explained by ethnic differences in cardiovascular risk factors and mechanistic factors such as variations in cardiac anatomy and physiology may play a role. This study compared ethnic differences in CT-assessed left ventricular (LV) mass, coronary anatomy and non-invasive fractional flow reserve (FFRCT). Methods: Three-hundred symptomatic patients (age 59 ± 7.9, male 51%) underwent clinically-mandated CT-coronary-angiography (CTA) were matched for age, gender, BMI and diabetes (100 each ethnicity). Assessment of coronary stenosis, luminal dimensions and vessel dominance was performed by independent observers. LV mass, coronary luminal volume and FFRCT were quantified by blinded core-laboratory. A sub-analysis was performed on patients (n = 187) with normal/minimal disease (0–25% stenosis). Results: Stenosis severity was comparable across ethnic groups. EA demonstrated less left-dominant circulation (2%) compared with SA (8.2%) and Caucasians (10.1%). SA compared with EA and Caucasians demonstrated smallest indexed LV mass, coronary luminal volumes and dimensions. EA compared with Caucasians had comparable indexed LV mass, coronary luminal dimensions and highest luminal volumes. The latter was driven by higher prevalence of right-dominance including larger and longer right posterior left ventricular artery. FFRCT in the left anterior descending artery (LAD) was lowest in SA (0.87) compared with EA (0.89; P = 0.009) and Caucasians (0.89; P < 0.001), with no difference in other vessels. All observed differences were consistent in patients with minimal disease. Conclusion: This single-centre study identified significant ethnic differences in CT-assessed LV mass, coronary anatomy and LAD FFRCT. These hypotheses generating results may provide a mechanistic explanation for ethnic differences in cardiovascular outcomes and require validation in larger cohorts.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Computerized tomography (CT); Coronary artery dominance; Fractional flow reserve; Left ventricular mass; Race and ethnicity

Ethnic differences in coronary luminal volume, left ventricular mass and CT-derived fractional flow reserve - Ihdayhid, Abdul Rahman; Adams, Daniel; Göller, Markus; Dey, Damini; Thakur, Udit; Yap, Grace; Lim, Ren Yik; Isa, Mourushi; Michail, Michael; Cameron, James; Seneviratne, Sujith; Ko, Brian (2018)
EVALuna2:35967

European Association of Cardiovascular Imaging (EACVI) position paper: Multimodality imaging in pericardial disease - Cosyns, Bernard; Plein, Sven; Nihoyanopoulos, Petros; Smiseth, Otto; Achenbach, Stephan; Andrade, Maria Joao; Pepi, Mauro; Ristic, Arsen; Imazio, Massimo; Paelinck, Bernard; Lancellotti, Patrizio (European Heart Journal - Cardiovascular Imaging, 2015)
Although pericardial diseases are common in the daily clinical practice and can result in a significant morbidity and mortality, imaging of patients with suspected or known pericardial disorders remain challenging. Multimodality imaging is part of the management of pericardial diseases. Echocardiography, cardiac computed tomography, and cardiovascular magnetic resonance are often used as complementary imaging modalities. The choice of one or multiple imaging modalities is driven by the clinical context or conditions of the patient. The scope of the present document is to highlight the respective role of each technique according to the clinical context in the diagnosis and management of pericardial diseases.
EVALuna2:12075

European Association of Echocardiography recommendations for assessment of valvular regurgitation: A correction - Flachskampf, Frank A.; Klinghammer, Lutz (European Journal of Echocardiography, 2010)
CRIS-Team Scopus Importer:2023-07-10

European experience with a first totally leadless cardiac resynchronization therapy pacemaker system - Carabelli, Adrien; Jabeur, Mariem; Jacon, Peggy; Rinaldi, Christopher Aldo; Leclercq, Christophe; Rovaris, Giovanni; Venier, Sandrine; Neuzil, Petr; Defaye, Pascal; Arnold, Martin (Europace, 2021)
AIMS: Totally leadless cardiac resynchronization therapy (CRT) can be delivered with a combination of Micra and WiSE-CRT systems. We describe the technical feasibility and first insights into the safety and efficacy of this combination in European experience. METHODS AND RESULTS: Patients enrolled had indication for both Micra and WiSE-CRT systems because of heart failure related to high burden of pacing by a Micra necessitating system upgrade or inability to implant a conventional CRT system because of infectious or anatomical conditions. The endpoints of the study were technical success of WiSE-CRT implantation with right ventricle-synchonized CRT delivery, acute QRS duration reduction, and freedom from procedure-related major adverse events. All eight WiSE-CRT devices were able to detect the Micra pacing output and to be trained to deliver synchronous LV endocardial pacing. Acute QRS reduction following WiSE-CRT implantation was observed in all eight patients (mean QRS 204.38 ± 30.26 vs. 137.5 ± 24.75 mS, P = 0.012). Seven patients reached 6 months of follow-up. At 6 months after WiSE-CRT implantation, there was a significant increase in LV ejection fraction (28.43 ± 8.01% vs. 39.71 ± 11.89%; P = 0.018) but no evidence of LV reverse remodelling or improvement in New York Heart Association class. CONCLUSION: The Micra and the WiSE-CRT systems can successfully operate together to deliver total leadless CRT to a patient. Moreover, the WiSE-CRT system provides the only means to upgrade the large population of Micra patients to CRT capability without replacing the Micra. The range of application of this combination could broaden in the future with the upcoming developments of leadless cardiac pacing.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Cardiac pacing; Cardiac resynchronization therapy; Endocardial left ventricular pacing; Leadless; WiSE-CRT

European Society of Cardiology: Cardiovascular Disease Statistics 2019 - Timmis, Adam; Townsend, Nick; Gale, Chris P.; Torbica, Aleksandra; Lettino, Maddalena; Petersen, Steffen E.; Mossialos, Elias A.; Maggioni, Aldo P.; Kazakiewicz, Dzianis; May, Heidi T.; De Smedt, Delphine; Flather, Marcus; et al. (European Heart Journal, 2020)
AIMS: The 2019 report from the European Society of Cardiology (ESC) Atlas provides a contemporary analysis of cardiovascular disease (CVD) statistics across 56 member countries, with particular emphasis on international inequalities in disease burden and healthcare delivery together with estimates of progress towards meeting 2025 World Health Organization (WHO) non-communicable disease targets. METHODS AND RESULTS: In this report, contemporary CVD statistics are presented for member countries of the ESC. The statistics are drawn from the ESC Atlas which is a repository of CVD data from a variety of sources including the WHO, the Institute for Health Metrics and Evaluation, and the World Bank. The Atlas also includes novel ESC sponsored data on human and capital infrastructure and cardiovascular healthcare delivery obtained by annual survey of the national societies of ESC member countries. Across ESC member countries, the prevalence of obesity (body mass index ≥30 kg/m2) and diabetes has increased two- to three-fold during the last 30 years making the WHO 2025 target to halt rises in these risk factors unlikely to be achieved. More encouraging have been variable declines in hypertension, smoking, and alcohol consumption but on current trends only the reduction in smoking from 28% to 21% during the last 20 years appears sufficient for the WHO target to be achieved. The median age-standardized prevalence of major risk factors was higher in middle-income compared with high-income ESC member countries for hypertension 23.8% [interquartile range (IQR) 22.5-23.1%] vs. 15.7% (IQR 14.5-21.1%), diabetes [7.7% (IQR 7.1-10.1%) vs. 5.6% (IQR 4.8-7.0%)], and among males smoking [43.8% (IQR 37.4-48.0%) vs. 26.0% (IQR 20.9-31.7%)] although among females smoking was less common in middle-income countries [8.7% (IQR 3.0-10.8) vs. 16.7% (IQR 13.9-19.7%)]. There were associated inequalities in disease burden with disability-adjusted life years per 100 000 people due to CVD over three times as high in middle-income [7160 (IQR 5655-8115)] compared with high-income [2235 (IQR 1896-3602)] countries. Cardiovascular disease mortality was also higher in middle-income countries where it accounted for a greater proportion of potential years of life lost compared with high-income countries in both females (43% vs. 28%) and males (39% vs. 28%). Despite the inequalities in disease burden across ESC member countries, survey data from the National Cardiac Societies of the ESC showed that middle-income member countries remain severely under-resourced compared with high-income countries in terms of cardiological person-power and technological infrastructure. Under-resourcing in middle-income countries is associated with a severe procedural deficit compared with high-income countries in terms of coronary intervention, device implantation and cardiac surgical procedures. CONCLUSION: A seemingly inexorable rise in the prevalence of obesity and diabetes currently provides the greatest challenge to achieving further reductions in CVD burden across ESC member countries. Additional challenges are provided by inequalities in disease burden that now require intensification of policy initiatives in order to reduce population risk and prioritize cardiovascular healthcare delivery, particularly in the middle-income countries of the ESC where need is greatest.
CRIS-Team Scopus Importer:2020-01-14
Keywords: Cardiovascular disease; European Society of Cardiology; Health infrastructure; Morbidity; Mortality; Risk factors; Service provision; Statistics

European Society of Cardiology: Cardiovascular Disease Statistics 2019 (Executive Summary) - Timmis, Adam; Townsend, N.; Gale, C. P.; Torbica, A.; Lettino, M.; Petersen, S. E.; Mossialos, E. A.; Maggioni, A. P.; Kazakiewicz, D.; May, H. T.; De Smedt, D.; Flather, M.; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2020)
CRIS-Team Scopus Importer:2020-01-31
Keywords: Cardiovascular disease; European Society of Cardiology; Health infrastructure; Morbidity; Mortality; Risk factors; Service provision; Statistics

European Society of Cardiology: cardiovascular disease statistics 2021 - Timmis Chair Writing Group, Adam; Vardas, Panos; Townsend, Nick; Torbica, Aleksandra; Katus, Hugo; De Smedt, Delphine; Gale, Chris P.; Maggioni, Aldo P.; Petersen, Steffen E.; Huculeci, Radu; Kazakiewicz, Dzianis; de Benito Rubio, Victor; et al. (European Heart Journal, 2022)
AIMS: This report from the European Society of Cardiology (ESC) Atlas Project updates and expands upon the widely cited 2019 report in presenting cardiovascular disease (CVD) statistics for the 57 ESC member countries. METHODS AND RESULTS: Statistics pertaining to 2019, or the latest available year, are presented. Data sources include the World Health Organization, the Institute for Health Metrics and Evaluation, the World Bank, and novel ESC sponsored data on human and capital infrastructure and cardiovascular healthcare delivery. New material in this report includes sociodemographic and environmental determinants of CVD, rheumatic heart disease, out-of-hospital cardiac arrest, left-sided valvular heart disease, the advocacy potential of these CVD statistics, and progress towards World Health Organization (WHO) 2025 targets for non-communicable diseases. Salient observations in this report: (i) Females born in ESC member countries in 2018 are expected to live 80.8 years and males 74.8 years. Life expectancy is longer in high income (81.6 years) compared with middle-income (74.2 years) countries. (ii) In 2018, high-income countries spent, on average, four times more on healthcare than middle-income countries. (iii) The median PM2.5 concentrations in 2019 were over twice as high in middle-income ESC member countries compared with high-income countries and exceeded the EU air quality standard in 14 countries, all middle-income. (iv) In 2016, more than one in five adults across the ESC member countries were obese with similar prevalence in high and low-income countries. The prevalence of obesity has more than doubled over the past 35 years. (v) The burden of CVD falls hardest on middle-income ESC member countries where estimated incidence rates are ∼30% higher compared with high-income countries. This is reflected in disability-adjusted life years due to CVD which are nearly four times as high in middle-income compared with high-income countries. (vi) The incidence of calcific aortic valve disease has increased seven-fold during the last 30 years, with age-standardized rates four times as high in high-income compared with middle-income countries. (vii) Although the total number of CVD deaths across all countries far exceeds the number of cancer deaths for both sexes, there are 15 ESC member countries in which cancer accounts for more deaths than CVD in males and five-member countries in which cancer accounts for more deaths than CVD in females. (viii) The under-resourced status of middle-income countries is associated with a severe procedural deficit compared with high-income countries in terms of coronary intervention, ablation procedures, device implantation, and cardiac surgical procedures. CONCLUSION: Risk factors and unhealthy behaviours are potentially reversible, and this provides a huge opportunity to address the health inequalities across ESC member countries that are highlighted in this report. It seems clear, however, that efforts to seize this opportunity are falling short and present evidence suggests that most of the WHO NCD targets for 2025 are unlikely to be met across ESC member countries.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Cardiovascular disease; European Society of Cardiology; Health infrastructure; Morbidity; Mortality; Risk factors; Service provision; Statistics

European Society of Cardiology: cardiovascular disease statistics 2021: Executive Summary - Timmis, Adam; Vardas, Panos; Townsend, Nick; Torbica, Aleksandra; Katus, Hugo; De Smedt, Delphine; Gale, Chris P.; Maggioni, Aldo P.; Petersen, Steffen E.; Huculeci, Radu; Kazakiewicz, Dzianis; Rubio, Victor De Benito; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2022)
AIMS: This report from the European Society of Cardiology (ESC) Atlas Project updates and expands upon the widely cited 2019 report in presenting cardiovascular disease (CVD) statistics for the 57 ESC member countries. METHODS AND RESULTS: Statistics pertaining to 2019, or the latest available year, are presented. Data sources include the World Health Organization, the Institute for Health Metrics and Evaluation, the World Bank, and novel ESC sponsored data on human and capital infrastructure and cardiovascular healthcare delivery. New material in this report includes sociodemographic and environmental determinants of CVD, rheumatic heart disease, out-of-hospital cardiac arrest, leftsided valvular heart disease, the advocacy potential of these CVD statistics, and progress towards World Health Organization (WHO) 2025 targets for non-communicable diseases. Salient observations in this report: (i) Females born in ESC member countries in 2018 are expected to live 80.8 years and males 74.8 years. Life expectancy is longer in high income (81.6 years) compared with middle-income (74.2 years) countries. (ii) In 2018, high-income countries spent, on average, four times more on healthcare than middle-income countries. (iii) The median PM2.5 concentrations in 2019 were over twice as high in middle-income ESC member countries compared with high-income countries and exceeded the EU air quality standard in 14 countries, all middle-income. (iv) In 2016, more than one in five adults across the ESC member countries were obese with similar prevalence in high and low-income countries. The prevalence of obesity has more than doubled over the past 35 years. (v) The burden of CVD falls hardest on middle-income ESC member countries where estimated incidence rates are ∼30% higher compared with high-income countries. This is reflected in disability-adjusted life years due to CVD which are nearly four times as high in middle-income compared with high-income countries. (vi) The incidence of calcific aortic valve disease has increased seven-fold during the last 30 years, with age-standardized rates four times as high in high-income compared with middle-income countries. (vii) Although the total number of CVD deaths across all countries far exceeds the number of cancer deaths for both sexes, there are 15 ESC member countries in which cancer accounts for more deaths than CVD in males and five-member countries in which cancer accounts for more deaths than CVD in females. (viii) The under-resourced status of middle-income countries is associated with a severe procedural deficit compared with high-income countries in terms of coronary intervention, ablation procedures, device implantation, and cardiac surgical procedures. CONCLUSION: Risk factors and unhealthy behaviours are potentially reversible, and this provides a huge opportunity to address the health inequalities across ESC member countries that are highlighted in this report. It seems clear, however, that efforts to seize this opportunity are falling short and present evidence suggests that most of the WHO NCD targets for 2025 are unlikely to be met across ESC member countries.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Cardiovascular disease; European Society of Cardiology; Health infrastructure; Morbidity; Mortality; Risk factors; Service provision; Statistics

European Society of Cardiology Congress 2018: Munich Revisited and More Global Than Ever! - Bax, Jeroen J.; Achenbach, Stephan (Circulation, 2019)
CRIS-Team WoS Importer:2019-03-06

Evaluation of fibroblasts adhesion and proliferation on alginate-gelatin crosslinked hydrogel - Sarker, Bapi; Singh, Raminder; Silva, Raquel; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Schubert, Dirk W.; Cicha, Iwona; Boccaccini, Aldo R. (PLoS ONE, 2014)
Due to the relatively poor cell-material interaction of alginate hydrogel, alginate-gelatin crosslinked (ADA-GEL) hydrogel was synthesized through covalent crosslinking of alginate di-aldehyde (ADA) with gelatin that supported cell attachment, spreading and proliferation. This study highlights the evaluation of the physico-chemical properties of synthesized ADA-GEL hydrogels of different compositions compared to alginate in the form of films. Moreover, in vitro cell-material interaction on ADA-GEL hydrogels of different compositions compared to alginate was investigated by using normal human dermal fibroblasts. Viability, attachment, spreading and proliferation of fibroblasts were significantly increased on ADA-GEL hydrogels compared to alginate. Moreover, in vitro cytocompatibility of ADA-GEL hydrogels was found to be increased with increasing gelatin content. These findings indicate that ADA-GEL hydrogel is a promising material for the biomedical applications in tissue-engineering and regeneration. Copyright:

Evaluation of hydrogel matrices for vessel bioplotting: Vascular cell growth and viability - Singh, Raminder; Sarker, Bapi; Silva, Raquel; Detsch, Rainer; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Cicha, Iwona (Journal of Biomedical Materials Research Part A, 2015)
Developing matrices biocompatible with vascular cells is one of the most challenging tasks in tissue engineering. Here, we compared the growth of vascular cells on different hydrogels as potential materials for bioplotting of vascular tissue. Formulations containing alginate solution (Alg, 2%, w/v) blended with protein solutions (silk fibroin, gelatin, keratin, or elastin) at 1% w/v were prepared. Human umbilical vein endothelial cells (ECs), smooth muscle cells (SMCs), and fibroblasts were cultivated on hydrogels for 7 days. Cell number and morphology was visualised using fluorescent staining at day 3 and 7. Cell metabolic activity was analysed using WST assay. Compared to pure Alg, Alg/keratin, Alg/gelatin and Alg/silk fibroin provided superb surfaces for ECs, supporting their attachment, growth, spreading and metabolic activity. SMCs showed best colonization and growth on Alg/silk fibroin and Alg/keratin hydrogels, whereas on elastin-containing hydrogels, cell clustering was observed. Fibroblasts growth was enhanced on Alg/elastin, and strongly improved on silk fibroin- and keratin-containing hydrogels. In contrast to the previous studies with alginate dialdehyde-gelatin crosslinked gels, Alg/gelatin blend hydrogels provided a less favourable scaffold for fibroblasts. Taken together, the most promising results were obtained with silk fibroin- and keratin-containing hydrogels, which supported the growth of all types of vascular cells.
Keywords: alginate-protein hydrogels; biocompatibility; fibroblasts; scaffold endothelialisation; smooth muscle cells

Evaluation of novice reader diagnostic performance in coronary CT angiography using an advanced cardiac software package - Dankerl, Peter; Hammon, Matthias; Tsymbal, Alexey; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2014)
The purpose of this research was to evaluate whether a commercially available advanced cardiac software package for coronary CT angiography (CTA) interpretation may reliably assist inexperienced readers to screen for significant coronary artery stenoses.Coronary CTA data sets of 61 consecutive patients with suspected coronary artery disease were evaluated by three novice readers with no experience in cardiac CT interpretation. In the first 15 patients, the novice readers were trained to use the advanced cardiac software package (includes automatic detection of coronary vessels, curved MPR and VRT reconstructions and a measurement too) knowing the results of an expert read. In the next 46 patients, the novice readers had to state whether there is a significant coronary artery stenosis ([Formula: see text]50 %) and if they are confident with their diagnosis. The results of the novice readers were compared to the expert read.The 46 coronary CTA data sets contained 184 vessels with 15 stenoses in 9 patients. On a per-vessel analysis, novice reader 1/2/3 demonstrated 60 %/100 %/ 93% sensitivity, and 98 %/90 %/86 % specificity. Per patient, the readers diagnosed 36/28/29 cases correctly as free of stenoses, 6/9/8 correctly as having at least one stenosis, missed 3/0/1 cases with a stenosis and overdiagnosed 1/9/8 patients. Cohen's kappa values for the three readers versus the expert were 0.60, 0.61 and 0.54. The three novice readers felt confident in the diagnosis of 36/33/30 patients. In these patients, they missed one significant stenosis, showed a sensitivity of 100 %/100 %/75 % and a specificity of 100 %/92 %/88 %.The evaluated advanced cardiac software package successfully assists novice readers in interpreting coronary CTA data sets especially in ruling out significant coronary artery stenosis.
EVALuna2:11866

Everolimus-eluting bioresorbable scaffolds in patients with coronary artery disease: results from the German-Austrian ABSORB RegIstRy (GABI-R) - Nef, Holger M.; Wiebe, Jens; Kastner, Johannes; Mehilli, Julinda; Muenzel, Thomas; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Riemer, Thomas; et al. (EuroIntervention, 2017)
Aims: The aim of this study was to analyse the procedural results and midterm safety of everolimus-eluting bioresorbable vascular scaffolds (BVS) used for percutaneous coronary intervention in a large all-comers cohort from the German-Austrian ABSORB RegIstRy (GABI-R). Methods and results: A total of 3,231 patients were included in this prospective, observational, multicentre study (ClinicalTrials.gov NCT02066623) of consecutive patients undergoing BVS implantation between November 2013 and January 2016. Endpoints were major adverse cardiac events (MACE; a composite endpoint of death, target vessel revascularisation, and myocardial infarction), and target lesion failure (TLF; a composite endpoint of cardiac death, target vessel myocardial infarction, and target lesion revascularisation). Scaffold thrombosis was a further endpoint. Of all patients, 51.5% presented with acute coronary syndrome. Predilatation and post-dilatation were performed in 91.5% and 71.9% of patients, respectively. Procedural success was 98.9%. After six months, the incidence of MACE was 4.1% and of TLF 2.4%. The rate of target vessel MI was 1.5%, and target lesion revascularisation was performed in 1.8%. Definite/probable scaffold thrombosis was documented in 1.4% of patients. Conclusions: GABI-R, the largest registry to provide data regarding safety after BVS implantation in a real-world setting, reveals high procedural success and low six-month event rates.
EVALuna2:36015

Everolimus eluting bioresorbable vascular scaffolds in patients with acute coronary syndromes: Two-year results from the German-Austrian ABSORB registry - Tröbs, Monique; Achenbach, Stephan; Nef, Holger M.; Gori, Tomasso; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Hamm, Christian W. (Catheterization and Cardiovascular Interventions, 2021)
Objectives To identify potential differences in 2-year outcome between patients who underwent coronary revascularization using bioresorbable vascular scafffolds (BVS) in stable coronary artery disease (CAD) and acute coronary syndromes (ACS).
CRIS-Team WoS Importer:2021-07-02

Everolimus- vs. novolimus-eluting bioresorbable scaffolds in patients with acute coronary syndrome - Nef, H. M.; Wiebe, J.; Schmidt, G.; Möllmann, H.; Boeder, N. F.; Dörr, O.; Bauer, T.; Blachutzik, F.; Liebetrau, C.; Elsässer, A.; Foin, N.; Hamm, C. W. (Herz, 2020)
Background: Limited data exist on bioresorbable scaffolds (BRS) in patients with acute coronary syndrome (ACS). The aim of the present study was to evaluate novolimus-eluting BRS (DESolve) as interventional treatment for patients with ACS, and to compare its 12-month outcomes with the everolimus-eluting bioresorbable scaffolds (Absorb). Methods: In this retrospective study, patients with ACS (including unstable angina pectoris, ST-segment elevation myocardial infarction, or non-ST-segment elevation myocardial infarction) treated with either the Absorb or the DESolve BRS were evaluated in a 1:1 matched-pair analysis. Major adverse cardiac events (MACE), including death, myocardial infarction, and target lesion revascularization, were evaluated as a major endpoint. The occurrence of scaffold thrombosis was also assessed. Results: A total of 102 patients were eligible for this analysis. The rate of MACE at 12 months was comparable between the Absorb and the DESolve group (8.3% vs. 6.8%, p = 0.738). The occurrence of target lesion revascularization (6.2% vs. 4.7%; p = 0.700) and scaffold thrombosis (4.1% vs. 2.1%; p = 0.580) was comparable as well. All instances of scaffold thrombosis occurred within 30 days of the index procedure. Conclusion: In this study, similar 12-month event rates were observed for both BRS types after implantation for the treatment of ACS.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Absorbable implants; Coronary artery disease; Major adverse cardiac events; Myocardial ischemia; Thrombosis

Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883

Exercise Field Testing in Children: A New Approach for Age-Appropriate Evaluation of Cardiopulmonary Function - Schöffl, Isabelle; Ehrlich, Benedikt; Stanger, Simon; Rottermann, Kathrin; Dittrich, Sven; Schöffl, Volker (Pediatric Cardiology, 2020)
Based on the wide range of problems to effectively perform cardiopulmonary testing in young children, this study strives to develop a new cardiopulmonary exercise test for children using a mobile testing device worn in a backpack in order to test children during their natural movement habits, namely, running outdoors. A standard cardiopulmonary exercise ramp test on a cycle ergometer was performed by a group of twenty 7–10-year-old children. The results were compared with a self-paced incremental running test performed using a mobile cardiopulmonary exercise measuring device in an outdoor park. The children were able to reach significantly higher values for most of the cardiopulmonary exercise variables during the outdoor test and higher. Whereas a plateau in V ˙ O 2 was reached by 25% of the children during the outdoor test, only 75% were able to reach a reasonable VT2, let alone V ˙ O 2peak, during the bicycle test. The heart rate at VT1, the O2-pulse, and the OUES were comparable between both tests. OUES was also positively correlated with V ˙ O 2peak in both tests. Testing children outdoors using a mobile cardiopulmonary exercise unit represents an alternative to standard exercise testing, but without the added problems of exercise equipment like treadmills or bicycles. It allows for individualized exercise testing with the aim of standardized testing durations instead of standardized testing protocols. The running speeds determined during the outdoor tests may then be used to develop age-adapted testing protocols for treadmill testing.
CRIS-Team Scopus Importer:2020-05-19
Keywords: Cardiopulmonary function in children; Mobile spiroergometry; Outdoor testing; Pediatric cardiology; VO

Exhaustive Graph Cut-based Vasculature Reconstruction - Unberath, Mathias; Achenbach, Stephan; Fahrig, Rebecca; Maier, Andreas (Proceedings of the ISBI, 2016)
We propose an exhaustive extension to graph cut-based coronary artery reconstruction from multiple views of a rotational angiography sequence. The reconstruction is formulated as an energy minimization problem that is solved using the a-expansion algorithm. We enforce reprojection-based data consistency and completeness conditions on the reconstructed centerline. The proposed strategy omits the need for selection and manual refinement of a reference view. A phantom study is used to assess the performance in 2D and 3D. The average reprojection error decreased from 1.32 ± 0.99mm to 0.54 ± 0.02 mm. Moreover, an increase in Dice score from 0.50 ± 0.04 mm to 0.59 ± 0.00 mm was observed, indicating superior volumetric reconstruction quality. The results suggest that the proposed extension removes the susceptibility to reference frame selection and manual interaction, while increasing reconstruction quality.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.exhaus_2
Keywords: C-arm CT; Cardiac Dynamics; Cardiac Imaging; Epipolar Geometry; Graph Cut; Symmetrization

Extent of subclinical atherosclerosis on coronary computed tomography and impact of statins in patients with diabetes without known coronary artery disease: Results from CONFIRM registry - Shaikh, Kashif; Ahmed, Arslan; Gransar, Heidi; Lee, Ju Hwan; Leipsic, Jonathon; Nakanishi, Rine; Alla, Venkata; Bax, Jeroen J.; Chow, Benjamin J.W.; Berman, Daniel S.; Maffei, Erica; Lin, Fay Y.; et al. (Journal of Diabetes and Its Complications, 2022)
Background: Absence of subclinical atherosclerosis is considered safe to defer statin therapy in general population. However, impact of statins on atherosclerotic cardiovascular disease in patients with diabetes stratified by coronary artery calcium (CAC) scores and extent of non-obstructive CAD on coronary computed tomography angiography (CCTA) has not been evaluated. Methods: CONFIRM (Coronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multi-center Registry) study enrolled consecutive adults 18 years of age between 2005 and 2009 who underwent 364-detector row CCTA for suspected CAD. The long-term registry includes data on 12,086 subjects who underwent CCTA at 17 centers in 9 countries. In this sub-study of CONFIRM registry, patients with diabetes mellitus (DM) and without diabetes mellitus with normal CCTA or non-obstructive plaque (<50 % diameter stenosis) for whom data on baseline statin use was available were included. CAC score was calculated using Agatston score. The magnitude of non-obstructive coronary artery disease on CCTA was quantified using segment involvement score (SIS). Primary outcome was major cardiovascular events (MACE) which included all-cause mortality, myocardial infarction, and target vessel re-vascularization. Results: A total of 7247 patients (Mean age 56.8 years) with a median follow up of 5 years were included. For DM patients, baseline statin therapy significantly reduced MACE for patients with CAC ≥100 (HR: 0.24; 95 % CI 0.07–0.87; p = 0.03) and SIS≥3 (HR: 0.23; 95 % CI 0.06–0.83; p = 0.024) compared to those not on statin therapy. Among Diabetics with lower CAC (<100) and SIS (≤3) scores, MACE was similar in statin and non-statin groups. In contrast, among non-DM patients, MACE was similar in statin and no statin groups irrespective of baseline CAC (1–99 or ≥100) and SIS. Conclusion: In this large multicenter cohort of patients, the presence and extent of subclinical atherosclerosis as assessed by CAC and SIS identified patients most likely to derive benefit from statin therapy.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Atherosclerosis; Cardiac CT; Diabetes; Prevention; Statin

Facilitated Data Relay and Effects on Treatment of Severe Aortic Stenosis in Europe - Steeds, Richard P.; Lutz, Matthias; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Rudolph, Tanja K.; Lloyd, Guy; Santo Bortone, Alessandro; Hauptmann, Karl Eugen; Clerici, Alberto; et al. (Journal of the American Heart Association, 2019)
Background-Many patients with severe aortic stenosis are referred late with advanced symptoms or inappropriately denied intervention. The objective was to investigate whether a structured communication to referring physicians (facilitated data relay) might improve the rate and timeliness of intervention.
CRIS-Team WoS Importer:2019-11-15

Facts about the General Medical Care of Adults with Congenital Heart Defects: Experience of a Tertiary Care Center - Seidel, Lavinia; Nebel, Kathrin; Achenbach, Stephan; Bauer, Ulrike; Ewert, Peter; Freilinger, Sebastian; Gundlach, Ulrike; Kaemmerer, Harald; Nagdyman, Nicole; Oberhoffer, Renate; Pieper, Lars; Reinhard, Wibke; et al. (Journal of Clinical Medicine, 2020)
Background: Due to the increase in survival rates for congenital heart disease (CHD) in the last decades, over 90% of patients today reach adulthood. Currently, there are more than 300,000 adults with CHD (ACHD) living in Germany. They have an increased need for specialized medical care, since almost all ACHD have chronic heart disease and suffer from specific chronic symptoms, risks, and sequelae. Primary care physicians (PCPs) play a crucial role in referring patients to ACHD specialists or specialized institutions. This cross-sectional study is intended to clarify the real-world care of ACHD from the PCP's perspective.Methods:This analysis, initiated by the German Heart Centre Munich, was based on a 27-item questionnaire on actual ACHD health care practice in Germany from the PCP's perspective.Results: In total, 767 questionnaires were considered valid for inclusion. The majority of the PCPs were general practitioners (95.9%), and 84.1% had cared for ACHD during the past year. A majority (69.2%) of the PCPs had cared for patients with simple CHD, while 50.6% and 33.4% had cared for patients with moderate and severe CHD, respectively, in all age groups. PCPs treated almost all typical residual symptoms and sequelae, and advised patients regarding difficult questions, including exercise capacity, pregnancy, genetics, and insurance matters. However, 33.8% of the PCPs did not even know about the existence of certified ACHD specialists or centers. Only 23.9% involved an ACHD-specialized physician in their treatment. In cases of severe cardiac issues, 70.8% of the PCPs referred patients to ACHD-certified centers. Although 52.5% of the PCPs were not sufficiently informed about existing structures, 64.2% rated the current care situation as either "very good" or "good". Only 26.3% (n= 190) of the responding physicians were aware of patient organizations for ACHD.Conclusions: The present study showed that the majority of PCPs are not informed about the ACHD care structures available in Germany. The need for specialized ACHD follow-up care is largely underestimated, with an urgent need for optimization to reduce morbidity and mortality. For the future, solutions must be developed to integrate PCPs more intensively into the ACHD care network.
CRIS-Team WoS Importer:2020-07-31

Fast-track high-sensitive cardiac troponin T algorithm for diagnosis of non-ST-elevation myocardial infarction in older patients at the emergency department - Bahrmann, Philipp; Christ, M.; Bahrmann, A.; Rittger, Harald; Achenbach, Stephan; Bertsch, T.; Sieber, Cornel; Heppner, Hans Jürgen (European Heart Journal, 2013)

FcγRIIa genotype is associated with acute coronary syndromes as first manifestation of coronary artery disease - Raaz, Dorette; Herrmann, Martin; Ekici, Arif Bülent; Klinghammer, Lutz; Lausen, Berthold; Voll, Reinhard E.; Leusen, Jeanette H.W.; van de Winkel, Jan G.J.; Daniel, Werner; Reis, André; Garlichs, Christoph (Atherosclerosis, 2009)
Objective: Identification of clinically relevant determinants for acute coronary syndromes (ACS) promises reduction of ACS-associated mortality. C-reactive protein (CRP) has proved to be useful identifying people at risk for cardiovascular events. However, it is unknown whether genetic variants at Fcγ receptor IIa (FcγRIIa), the main receptor for CRP, are involved in CRP-related cardiovascular risk. We evaluated the potential impact of FcγRIIa through a genetic association study in patients with ACS. Methods and results: We conducted a genetic association study among 701 consecutive patients with first event of ACS compared to 467 patients with stable angina pectoris. All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa, where the arginine (R) allele results in an increased signal transduction upon CRP binding. In our study, the R/R131 genotype was significantly associated with ACS as the first manifestation of coronary artery disease (P = 1.2 × 10-9, odds ratio 2.86, 95% CI: 2.06-3.99) compared to the non-R/R131 genotype. Conclusions: Our data show a genetic association of the FcγRIIa R/R131 genotype with a more frequent occurrence of ACS as the first manifestation of coronary artery disease, probably mediated via its interaction with CRP. Genotyping of this FcγRIIa variant could help to improve risk stratification in the course of coronary disease in the future. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute coronary syndrome; Fcγ receptor IIa; Gene polymorphism; Inflammation

Feasibility of Respiratory-gated High-pitch Spiral CT:: Free-breathing Inspiratory Image Quality - Lell, Michael; Scharf, Michael; Eller, Achim; Wüst, Wolfgang; Allmendinger, Thomas; Fuchs, Florian; Achenbach, Stephan; Uder, Michael; May, Matthias (Academic Radiology, 2016)
This study aimed to develop and implement a respiratory-gated setup for dual-source computed tomography (CT) at high pitch to examine patients in a reproducible inspiratory phase.Twenty-one patients underwent free-breathing respiratory-gated chest CT using a high-pitch scan mode no more than 6 months after inspiratory breath-held nongated CT, which serves as reference. Scan parameters were as follows: pitch = 3.4, 128 × 0.6 mm collimation, 0.28 s gantry rotation time, and 150 ref.mAs per tube at 120 kV. The examinations were triggered using the tidal wave provided by a respiratory-gating system as input signal. Image quality was assessed focusing on artifacts and delineation of the anatomical and pathological structures. Lung volumes were measured on both free-breathing and reference examinations.All examinations were performed without complications. Image quality was high with both protocols. Significantly less motion artifacts were recorded with the high-pitch mode compared to the reference (P = 0.02). Most of the artifacts were located in the peripheral parts of the lower lobes for the study group and in the central part of the left lower lobe for the reference. Average total lung volume was 4.5 ± 1.5 L in respiratory-gated examinations and 5.8 ± 0.9 L in examinations with breath-hold in inspiration.High-pitch chest CT scanning during free breathing minimizes motion artifacts, improving image quality in patients with limited breath-holding abilities. To assure scanning in an inspiratory phase, data acquisition should be triggered with a respiratory-gating system.
EVALuna2:12027

FFR Derived From Coronary CT Angiography in Nonculprit Lesions of Patients With Recent STEMI - Gaur, Sara; Taylor, Charles A.; Jensen, Jesper M.; Botker, Hans Erik; Christiansen, Evald H.; Kaltoft, Anne K.; Holm, Niels R.; Leipsic, Jonathon; Zarins, Christopher K.; Achenbach, Stephan; Khem, Sophie; Wilk, Alan; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2017)
OBJECTIVES: This study sought to determine the diagnostic performance of noninvasive fractional flow reserve (FFR) derived from coronary computed tomography angiography (CTA) (FFRCT) for the diagnosis of lesion-specific ischemia in nonculprit vessels of patients with recent in ST-segment elevation myocardial infarction (STEMI). BACKGROUND: In patients with stable angina, FFRCThas high diagnostic performance in identification of ischemia-causing lesions. The potential value of FFRCTfor assessment of multivessel disease in patients with recent STEMI has not been evaluated. METHODS: Coronary CTA with calculation of FFRCTand invasive coronary angiography with FFR were performed 1 month after STEMI in patients with multivessel disease. Coronary CTA and invasive coronary angiography stenosis >50% were considered obstructive. Lesion-specific ischemia was assumed if FFRCTwas ≤0.80. FFR ≤0.80 was the reference standard. To evaluate the influence of vessel size, the total coronary vessel lumen volume relative to left ventricular mass (volume-to-mass ratio) was calculated and compared with that of patients with stable angina. RESULTS: The study evaluated 124 nonculprit vessels from 60 patients. Accuracy, sensitivity, and specificity of FFRCTwere 72%, 83%, and 66% versus 64% (p = 0.033), 93% (p = 0.15), and 49% (p < 0.001) for CTA and 72% (p = 1.00), 76% (p = 0.46), and 70% (p = 0.54) for invasive coronary angiography. Following STEMI, median volume-to-mass ratio was lower than in patients with stable angina, 53 versus 65 mm3/g (p = 0.009). In patients with volume-to-mass ratio ≥65 mm3/g (upper tertile) accuracy, sensitivity, and specificity of FFRCTwere all 83% versus 56% (p = 0.009), 75% (p = 0.61), and 44% (p = 0.003) in patients with <49 mm3/g (lower tertile). CONCLUSIONS: The diagnostic performance of FFRCTfor staged detection of ischemia in STEMI patients with multivessel disease is moderate. STEMI patients have a smaller vessel volume than do patients with stable angina. The diagnostic performance of FFRCTis influenced by the volume-to-mass ratio. This study does not support routine use of FFRCTin the post-STEMI setting. (Assessment of Coronary Stenoses Using Coronary CT-Angiography and Noninvasive Fractional Flow Reserve; NCT01739075).
EVALuna2:33644

Filarial extract of Litomosoides sigmodontis induces a type 2 immune response and attenuates plaque development in hyperlipidemic ApoE-knockout mice - Kühn, Constanze; Tauchi, Miyuki; Furtmair, Roman; Urschel, Katharina; Raaz-Schrauder, Dorette; Neumann, Anna Lena; Frohberger, Stefan J.; Hoerauf, Achim; Regus, Susanne; Lang, Werner; Sagban, Tolga Atilla; Stumpfe, Florian Matthias; et al. (The FASEB Journal, 2019)
A type 1 immune response is involved in atherosclerosis progression, whereas the role of a type 2 polarization, especially with regard to an enhanced T helper (Th)2 cell differentiation, is still unclear. Helminths trigger type 2 immune responses, protecting the host from inflammatory disorders. We investigated whether an increased type 2 polarization by administration of Litomosoides sigmodontis adult worm extract (LsAg) affects atherosclerosis in apolipoprotein E-deficient (ApoE-/-) mice. Injections of 50 µg LsAg, i.p. into ApoE-/- mice induced a type 2 immune response shown by increased frequencies of peritoneal eosinophils and alternatively activated macrophages. To analyze the effect of LsAg on atherosclerosis initiation, ApoE-/- mice received a high-fat diet for 12 wk and weekly injections of 50 µg LsAg from wk 5 to 12. Therapeutic effects on advanced atherosclerosis were analyzed in mice that were fed a high-fat diet for 12 wk followed by 12 wk of normal chow and weekly LsAg injections. Both preventive and therapeutic LsAg application significantly decreased plaque size. Therapeutic treatment even caused regression of plaque size and macrophage density in the aortic root and reduced Th1-specific gene expression and intraplaque inflammation. In addition, plaque size after therapeutic treatment was inversely correlated with plaque-infiltrated alternatively activated macrophages. In vitro, LsAg treatment of HUVECs reduced intracellular levels of phosphorylated NF-κB-p65, IκB-α, and JNK1/2. In bifurcation flow-through slides, THP-1 cell adhesion to a HUVEC monolayer was decreased by LsAg in regions of nonuniform shear stress. Applying inhibitors of the respective kinases suggests JNK1/2 inhibition is involved in the suppressed cell adhesion. A switch to an enhanced type 2 immune response by LsAg exerts antiatherogenic effects on murine plaque development, indicating a protective role of a hampered type 1 polarization. In vitro, LsAg affects endothelial signaling pathways, among which JNK1/2 inhibition seems to be involved in the suppression of monocytic cell adhesion under proatherogenic shear stress.-Constanze, K., Tauchi, M., Furtmair, R., Urschel, K., Raaz-Schrauder, D., Neumann, A.-L., Frohberger, S. J., Hoerauf, A., Regus, S., Lang, W., Sagban, T. A., Stumpfe, F. M., Achenbach, S., Hübner, M. P., Dietel, B. Filarial extract of Litomosoides sigmodontis induces a type 2 immune response and attenuates plaque development in hyperlipidemic ApoE-knockout mice.
CRIS-Team Scopus Importer:2019-05-21
Keywords: atherosclerosis; endothelial activation; helminth; inflammation; JNK

Final results of a self-apposing paclitaxel-eluting stent fOr the PErcutaNeous treatment of de novo lesions in native bifurcated coronary arteries study - Naber, Christoph K.; Pyxaras, Stylianos A.; Nef, Holger; Ijsselmuiden, Alexander J.; Briguori, Carlo; Schlundt, Christian; Wykrzykowska, Joanna; Eberli, Franz R.; Moellmann, Helge; Galatius, Soren; Rieber, Johannes; Commeau, Philippe; et al. (EuroIntervention, 2016)
AIMS: We aimed to evaluate the long-term safety and efficacy of the STENTYS self-apposing paclitaxeleluting stent (STENTYS-PES) in bifurcation lesions in routine clinical practice. METHODS AND RESULTS: The primary endpoint of the study was the composite major adverse cardiac events (MACE: cardiac death, myocardial infarction, clinically driven target lesion revascularisation, or emergent bypass surgery) assessed at six months after enrolment. This was reported in 21 patients (10.1%), mainly due to clinically driven target lesion revascularisation (TLR). At 12 months, 27 patients experienced MACE (13.0%). CONCLUSIONS: The long-term results of OPEN II show that the STENTYS-PES is safe and effective in the treatment of all-comers with coronary bifurcation lesions.
EVALuna2:12099

Five-year follow-up of patients who underwent everolimus-eluting bioresorbable scaffold implantation - Wiebe, Jens; Hofmann, Felix J.; Doerr, Oliver; Bauer, Timm; Boeder, Niklas; Liebetrau, Christoph; Blachutzik, Florian; Moellmann, Helge; Elsaesser, Albrecht; Achenbach, Stephan; Hamm, Christian W.; Nef, Holger M. (Catheterization and Cardiovascular Interventions, 2020)
Objectives The aim of this study was to evaluate very long-term results after unrestricted everolimus-eluting bioresorbable scaffolds (BRS) implantation.
CRIS-Team WoS Importer:2020-03-31

Flow cytometry for intracellular SPION quantification: specificity and sensitivity in comparison with spectroscopic methods - Friedrich, Ralf P.; Janko, Christina; Poettler, Marina; Tripal, Philipp; Zaloga, Jan; Cicha, Iwona; Dürr, Stephan; Nowak, Johannes; Odenbach, Stefan; Slabu, Ioana; Liebl, Maik; Trahms, Lutz; et al. (International Journal of Nanomedicine, 2015)
Due to their special physicochemical properties, iron nanoparticles offer new promising possibilities for biomedical applications. For bench to bedside translation of super-paramagnetic iron oxide nanoparticles (SPIONs), safety issues have to be comprehensively clarified. To understand concentration-dependent nanoparticle-mediated toxicity, the exact quantification of intracellular SPIONs by reliable methods is of great importance. In the present study, we compared three different SPION quantification methods (ultraviolet spectrophotometry, magnetic particle spectroscopy, atomic adsorption spectroscopy) and discussed the shortcomings and advantages of each method. Moreover, we used those results to evaluate the possibility to use flow cytometric technique to determine the cellular SPION content. For this purpose, we correlated the side scatter data received from flow cytometry with the actual cellular SPION amount. We showed that flow cytometry provides a rapid and reliable method to assess the cellular SPION content. Our data also demonstrate that internalization of iron oxide nanoparticles in human umbilical vein endothelial cells is strongly dependent to the SPION type and results in a dose-dependent increase of toxicity. Thus, treatment with lauric acid-coated SPIONs (SEON(LA)) resulted in a significant increase in the intensity of side scatter and toxicity, whereas SEON(LA) with an additional protein corona formed by bovine serum albumin (SEON(LA-BSA)) and commercially available Rienso(®) particles showed only a minimal increase in both side scatter intensity and cellular toxicity. The increase in side scatter was in accordance with the measurements for SPION content by the atomic adsorption spectroscopy reference method. In summary, our data show that flow cytometry analysis can be used for estimation of uptake of SPIONs by mammalian cells and provides a fast tool for scientists to evaluate the safety of nanoparticle products.
EVALuna2:19955

Formation of atherosclerotic lesions is independent of eosinophils in male mice - Hofheinz, Katharina; Seibert, Fabian; Ackermann, Jochen; Dietel, Barbara; Tauchi, Miyuki; Oszvar-Kozma, Maria; Kühn, Hartmut; Schett, Georg; Binder, Christoph J.; Krönke, Gerhard (Atherosclerosis, 2020)
Background and aims: Oxidation of low-density lipoprotein (LDL) and oxidized LDL-mediated activation of the innate immune system have been recognized as early key events during the pathogenesis of atherosclerosis. Recent evidence identified eosinophils as a major source of enzymatic lipid oxidation and suggested a potential role of type 2 immunity in atherogenesis. However, the involvement of individual type 2 immune cell subsets involved in this process has been incompletely defined. We therefore sought to determine the role of eosinophils during LDL oxidation and the pathogenesis of this disease. Methods: Using eosinophil-deficient dblGATA1 mice, we studied the role of eosinophils in two established mouse models of atherosclerosis. Results: These experiments revealed that the presence of eosinophils did neither affect biomarkers of LDL oxidation nor atherosclerotic lesion development. Conclusions: The obtained results show that LDL oxidation and development of atherosclerosis are largely independent of eosinophils or eosinophil-mediated LDL oxidation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Atherosclerosis; Eosinophils; Lipid oxidation

Fractional flow reserve derived from coronary computed tomography angiography: diagnostic performance in hypertensive and diabetic patients - Eftekhari, Ashkan; Min, James; Achenbach, Stephan; Budoff, Matthew; Leipsic, Jonathon; Gaur, Sara; Jensen, Jesper Moller; Ko, Brian S.; Christiansen, Evald Hoj; Kaltoft, Anne; Botker, Hans Erik; Jensen, Jens Flensted; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: Fractional flow reserve (FFR) derived from coronary computed tomography (FFRCT) has high diagnostic performance in stable coronary artery disease (CAD). The diagnostic performance of FFRCT in patients with hypertension (HTN) and diabetes (DM), who are at risk of microvascular impairment, is not known. Methods and results: We analysed the diagnostic performance of FFRCT, in patients (vessels) with DM (n = 16), HTN (n = 186), DM + HTN (n = 58) vs. controls (n = 107) with or with suspected CAD. Patients (vessels) were further divided according to left ventricular mass index (LVMI) tertiles. Reference standard was invasively measured FFR ≤0.80. Per-patient diagnostic accuracy (95% CI) in control patients was 71.7% (61.6-81.8) vs. 79.3 (74.0-85.0) (P = 0.12), 75.0% (47.6-92.7) (P = 0.52), and 75.9% (62.8-86.1) (P = 0.39) in patients with HTN, DM, and HTM + DM, respectively. There was no difference in discrimination of ischaemia by FFRCT between groups. On a per-vessel level, there was no significant difference in diagnostic performance or discrimination of ischaemia by FFRCT between groups. There was a decline in both per-patient and -vessel diagnostic specificity of FFRCT in the upper LVMI tertile when compared with lower tertiles; however, discrimination of ischaemia by FFRCT was unaltered across LVMI tertiles. Conclusion: The diagnostic performance of FFRCT is independent of the presence of HTN and DM. FFRCT is a robust method in a broad stable CAD population, including patients at high risk for microvascular disease.
EVALuna2:33598

Fractional flow reserve derived from coronary CT angiography: variation of repeated analyses - Gaur, Sara; Bezerra, Hiram G.; Lassen, Jens F.; Christiansen, Evald H.; Tanaka, Kentaro; Jensen, Jesper M.; Oldroyd, Keith G.; Leipsic, Jonathon; Achenbach, Stephan; Kaltoft, Anne K.; Botker, Hans Erik; Norgaard, Bjarne L. (Journal of Cardiovascular Computed Tomography, 2014)
Fractional flow reserve (FFR) is the standard of reference for assessing the hemodynamic significance of coronary stenoses in patients with stable coronary artery disease. Noninvasive FFR derived from coronary CT angiography (FFRCT) is a promising new noninvasive method for assessing the physiologic significance of epicardial stenoses. The reproducibility of FFRCT has not yet been established.The aim of this study was to evaluate the variation of repeated analyses of FFRCT per se and in the context of the reproducibility of repeated FFR measurements.Coronary CT angiography and invasive coronary angiography with repeated FFR measurements were performed in 28 patients (58 vessels) with suspected stable coronary artery disease. Based on the coronary CT angiography data set, FFRCT analyses were performed twice by 2 independent blinded analysts.In 12 of 58 (21%) vessels FFR was <= 0.80. The standard deviation for the difference between first and second FFRCT analyses was 0.034 vs 0.033 for FFR repeated measurements (P = .722). Limits of agreement were -0.06 to 0.08 for FFRCT and -0.07 to 0.06 for FFR. The coefficient of variation of FFRCT (CVFFRct) was 3.4% (95% confidence interval [CI], 1.4%-4.6%) vs 2.7% (95% CI, 1.8%-3.3%) for FFR. In vessels with mean FFR ranging between 0.70 and 0.90 (n = 25), the difference between the first and second FFRCT analyses was 0.035 and FFR repeated measurements was 0.043 (P = .357), whereas CVFFRct was 3.3% (95% CI, 1.5%-4.3%) and coefficient of variation for FFR was 3.6% (95% CI, 2.3%-4.6%).The reproducibility of both repeated FFRCT analyses and repeated FFR measurements is high.
EVALuna2:12007

Frailty and in-hospital outcomes in percutaneous coronary interventions - Kwok, C. S.; Achenbach, Stephan; Curzen, N.; Fischman, D. L.; Savage, M.; Bagur, R.; Kontopantelis, E.; Martin, G.; Steg, P. G.; Mamas, M. A. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Fully automated CT quantification of Epicardial adipose tissue by deep learning: A multicenter study - Commandeur, Frederic; Göller, Markus; Razipour, Aryabod; Cadet, Sebastien; Hell, Michaela; Kwiecinski, Jacek; Chen, Xi; Chang, Hyuk-Jae; Marwan, Mohamed; Achenbach, Stephan; Berman, Daniel S.; Slomka, Piotr J.; et al. (Radiology: Artificial Intelligence, 2019)
Purpose: To evaluate the performance of deep learning for robust and fully automated quantification of epicardial adipose tissue (EAT) from multicenter cardiac CT data. Materials and Methods: In this multicenter study, a convolutional neural network approach was trained to quantify EAT on non-contrast material-enhanced calcium-scoring CT scans from multiple cohorts, scanners, and protocols (n = 850). Deep learning performance was compared with the performance of three expert readers and with interobserver variability in a subset of 141 scans. The deep learning algorithm was incorporated into research software. Automated EAT progression was compared with expert measurements for 70 patients with baseline and follow-up scans. Results: Automated quantification was performed in a mean (6 standard deviation) time of 1.57 seconds 6 0.49, compared with 15 minutes for experts. Deep learning provided high agreement with expert manual quantification for all scans (R = 0.974; P, 001), with no significant bias (0.53 cm3; P =. 13). Manual EAT volumes measured by two experienced readers were highly correlated (R = 0.984; P, 001) but with a bias of 4.35 cm3 (P, 001). Deep learning quantifications were highly correlated with the measurements of both experts (R = 0.973 and R = 0.979; P, 001), with significant bias for reader 1 (5.11 cm3; P, 001) but not for reader 2 (0.88 cm3; P =. 26). EAT progression by deep learning correlated strongly with manual EAT progression (R = 0.905; P, 001) in 70 patients, with no significant bias (0.64 cm3; P =. 43), and was related to an increased noncalcified plaque burden quantified from coronary CT angiography (5.7% vs 1.8%; P =. 026). Conclusion: Deep learning allows rapid, robust, and fully automated quantification of EAT from calcium scoring CT. It performs as well as an expert reader and can be implemented for routine cardiovascular risk assessment.
CRIS-Team Scopus Importer:2023-03-08

Fully automated epicardial adipose tissue volume and density measured from non-contrast CT predict major adverse cardiovascular events in asymptomatic subjects - Mcelhinney, P.; Eisenberg, E.; Commandeur, F.; Chen, X.; Cadet, S.; Göller, Markus; Cantu, S.; Miller, R.; Slomka, P.; Wong, N.; Rozanski, A.; Achenbach, Stephan; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Functional Diagnostics for the Detection of Myocardial Ischemia - Gaede, Luise; Boenner, Florian (Aktuelle Kardiologie, 2020)
In the current guidelines on chronic coronary syndrome (CCS), functional diagnostics for the detection and quantification of myocardial ischemia play a central role: In contrast to purely anatomical methods, they can not only diagnose coronary heart disease, but also stratify the patient risk at the same time. Functional diagnostic procedures should initially be used non-invasively, but in any case - especially in case of absent or inconclusive non-invasive detection - with pressure wire measurements in the cath-lab. Non-invasive tests quantify the size of the ischemic area and determine whether revascularization is of prognostic benefit for the patient and thus decide on further interventional therapy. The hemodynamic significance of a coronary stenosis is determined by invasive quantification. The functional diagnostics also allow a statement about the function of the microcirculation. Diseases of the microcirculation are of comparable prognostic importance to diseases of the macrocirculation, but require less interventional than pharmacological treatment. Current technical developments of all modalities expand the diagnostic accuracy and the field of application of the individual methods at different speeds. The same diagnosis should therefore not always be initiated for all patients. The correct selection of the non-invasive test should be made depending on the patient, taking into account comorbidities, symptoms and pretest probability as well as local expertise. Older patients in particular, who often present with atypical symptoms and have higher complication rates with invasive procedures, benefit particularly from a well-considered diagnostic strategy.
CRIS-Team WoS Importer:2020-07-17

Functional Fc gamma receptor gene polymorphisms and donor-specific antibody-triggered microcirculation inflammation - Kainz, A.; Hidalgo, L. G.; Eskandary, F.; Kozakowski, N.; Wahrmann, Markus; Haslacher, H.; Oberbauer, R.; Heilos, A.; Spriewald, B. M.; Halloran, P. F.; Boehmig, G. A.; Arnold, Martin (American Journal of Transplantation, 2018)
Fc-dependent effector mechanisms may contribute to antibody-mediated rejection (ABMR), and distinct gene polymorphisms modifying the function of Fc gamma receptors (FcγRs) may influence the capability of donor-specific antibodies (DSAs) to trigger inflammation. To evaluate the relevance of functional FcγR variants in late ABMR, 85 DSA-positive kidney allograft recipients, who were recruited upon antibody screening of 741 prevalent patients, were genotyped for polymorphisms in FcγRIIA (FCGR2A-H/R131 ; rs1801274), FcγRIIIA (FCGR3A-V/F158 ; rs396991), and FcγRIIIB (FCGR3B-neutrophil antigen 1 ([NA1]/NA2; rs35139848). Individuals with high-affinity FCGR3A-V158 alleles (V/V158 or V/F158 ) showed a higher rate (and extent) of peritubular capillaritis (ptc) in protocol biopsies than homozygous carriers of the lower-affinity allele (ptc score ≥1: 53.6% vs 25.9%; P = .018). Associations were independent of C1q-binding to DSA or capillary C4d. In parallel, there was a trend toward increased macrophage- and injury-repair response-associated transcript subsets. Kidney function over 24 months, however, was not different. In support of a functional role of FcγRIIIA polymorphism, NK92 cells expressing FCGR3A-V158 produced >2 times as much interferon gamma upon incubation with HLA antibody-coated cells as those expressing FCGR3A-F158 . FcγRIIA and FcγRIIIB polymorphisms were not associated with allograft morphology. Our data suggest that the presence of high-affinity FcγRIIIA variants may favor DSA-triggered microcirculation inflammation.
EVALuna2:34170

Functional Fc Gamma Receptor Gene Polymorphisms and Long-Term Kidney Allograft Survival - Wahrmann, Markus; Döhler, Bernd; Scherer, Sabine; Mayer, Katharina A.; Haindl, Susanne; Haslacher, Helmuth; Böhmig, Georg A.; Süsal, Caner; Arnold, Martin (Frontiers in Immunology, 2021)
The functional Fc gamma receptor (FcγR) IIIA polymorphism FCGR3A-V/F158 was earlier suggested to determine the potential of donor-specific HLA antibodies to trigger microcirculation inflammation, a key lesion of antibody-mediated renal allograft rejection. Associations with long-term transplant outcomes, however, have not been evaluated to date. To clarify the impact of FCGR3A-V/F158 polymorphism on kidney transplant survival, we genotyped a cohort of 1,940 recipient/donor pairs. Analyzing 10-year death-censored allograft survival, we found no significant differences in relation to FCGR3A-V/F158. There was also no independent survival effect in a multivariable Cox model. Similarly, functional polymorphisms in two other activating FcγR, FCGR2A-H/R131 (FcγRIIA) and FCGR3B-NA1/NA2 (FcγRIIIB), were not associated with outcome. There were also no significant survival differences among patient subgroups at increased risk of rejection-related injury, such as pre-sensitized recipients (> 0% panel reactivity; n = 438) or recipients treated for rejection within the first year after transplantation (n = 229). Our study results suggest that the earlier shown association of FcγR polymorphism with microcirculation inflammation may not be strong enough to exert a meaningful effect on graft survival.
CRIS-Team Scopus Importer:2021-09-17
Keywords: allograft survival; anti-HLA antibodies; antibody-mediated rejection; Fc gamma receptor; kidney transplantation

Gender differences in the prevalence, severity, and composition of coronary artery disease in the young: a study of 1635 individuals undergoing coronary CT angiography from the prospective, multinational confirm registry - Otaki, Yuka; Gransar, Heidi; Cheng, Victor Y.; Dey, Damini; Labounty, Troy; Lin, Fay Y.; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (European Heart Journal - Cardiovascular Imaging, 2015)
Prior studies examining coronary atherosclerosis in the young have been limited by retrospective analyses in small cohorts. We examined the relationship between cardiovascular risk factors (RFs) and prevalence and severity of coronary atherosclerosis in a large, prospective, multinational registry of consecutive young individuals undergoing coronary computerized tomographic angiography (CCTA).Of 27 125 patients undergoing CCTA, 1635 young (<45 years) individuals without known coronary artery disease (CAD) or coronary anomalies were identified. Coronary plaque was assessed for any CAD, obstructive CAD (>=50% stenosis), and presence of calcified plaque (CP) and non-calcified plaque (NCP). Among 1635 subjects (70% men, age 38 ± 6 years), any CAD, obstructive CAD, CP, and NCP were observed in 19, 4, 5, and 8%, respectively. Compared with women, men demonstrated higher rates of any CAD (21 vs. 12%, P < 0.001), CP (6 vs. 3%, P = 0.01), and NCP (9 vs. 5%, P = 0.008), although no difference was observed for rates of obstructive CAD (5 vs. 4%, P = 0.46). Any CAD, obstructive CAD, and NCP were higher for young individuals with diabetes, hypertension, dyslipidaemia, current smoking, or family history of CAD; while only diabetes and dyslipidaemia were associated with CP. Increasing cardiovascular RFs was associated with a greater prevalence and extent and severity of CAD, with individuals with 0, 1, 2, >=3 RFs manifesting a dose-response increase in any CAD (P < 0.001, for trend), obstructive CAD (P < 0.001, for trend), NCP (P < 0.001, for trend), and CP (P < 0.001, for trend). In multivariable analysis adjusting for sex and cardiovascular RFs, male sex was the strongest predictor for any CAD (odds ratio [OR] = 1.95, 95% confidence interval [CI] = 1.43-2.66, P < 0.001), CP (OR = 1.46, 95% CI = 1.08-1.98, P = 0.01), and NCP (OR = 1.33, 95% CI = 1.06-1.67, P = 0.01); family history of CAD was the strongest predictor for obstructive CAD (OR = 2.71, 95% CI = 1.65-4.45, P < 0.001).Any and obstructive CAD is present in 1 in 5 and 1 in 20 young individuals, respectively, with family history associated with the greatest risk of obstructive CAD.
EVALuna2:12065

German cardiac CT registry: indications, procedural data and clinical consequences in 7061 patients undergoing cardiac computed tomography - Achenbach, Stephan; Korosoglou, Grigorios; Schmermund, Axel; Schneider, Steffen; Bruder, Oliver; Hausleiter, Joerg; Schroeder, Stephen; Barth, Sebastian; Kerber, Sebastian; Leber, Alexander; Moshage, Werner; Senges, Jochen; et al. (International Journal of Cardiovascular Imaging, 2018)
Cardiac computed tomography permits quantification of coronary calcification as well as detection of coronary artery stenoses after contrast enhancement. Moreover, cardiac CT offers high-resolution morphologic and functional imaging of cardiac structures which is valuable for various structural heart disease interventions and electrophysiology procedures. So far, only limited data exist regarding the spectrum of indications, image acquisition parameters as well as results and clinical consequences of cardiac CT examinations using state-of-the-art CT systems in experienced centers. Twelve cardiology centers with profound expertise in cardiovascular imaging participated in the German Cardiac CT Registry. Criteria for participation included adequate experience in cardiac CT as well of the availability of a 64-slice or newer CT system. Between 2009 and 2014, 7061 patients were prospectively enrolled. For all cardiac CT examinations, patient parameters, procedural data, indication and clinical consequences of the examination were documented. Mean patient age was 61 ± 12 years, 63% were males. The majority (63%) of all cardiac CT examinations were performed in an outpatient setting, 37% were performed during an inpatient stay. 91% were elective and 9% were scheduled in an acute setting. In most examinations (48%), reporting was performed by cardiologists, in 4% by radiologists and in 47% of the cases as a consensus reading. Cardiac CT was limited to native acquisitions for assessment of coronary artery calcification in 9% of patients, only contrast-enhanced coronary CT angiography was performed in 16.6% and combined native and contrast-enhanced coronary CT angiography was performed in 57.7% of patients. Non-coronary cardiac CT examinations constituted 16.6% of all cases. Coronary artery calcification assessment was performed using prospectively ECG-triggered acquisition in 76.9% of all cases. The median dose length product (DLP) was 42 mGy cm (estimated effective radiation dose of 0.6 mSv). Coronary CT angiography was performed using prospectively ECG-triggered acquisition in 77.3% of all cases. Tube voltage was 120 kV in 67.8% of patients and 100 kV in 30.7% of patients, with a resultant median DLP of 256 mGy cm (estimated effective dose of 3.6 mSv). Clinical consequences of cardiac CT were as follows: in 46.8% of the cases, invasive coronary angiography could be avoided; ischemia testing was recommended in 4.7% of the cases, invasive coronary angiography was recommended in 16.4% of the cases and change in medication in 21.6% of the examinations. Cardiac CT is performed in the majority of patients for non-invasive evaluation of the coronary arteries. CT frequently resulted in medication change, and otherwise planned downstream testing including invasive angiography could be avoided in a high percentage of patients. Radiation exposure in experienced centers is relatively low.
EVALuna2:35998

Ghidul societăţii Europene de cardiologie pentru cardiostimulare şi terapie de resincronizare cardiacă (2013) - Brignole, Michele; Auricchio, Angelo; Baron-Esquivias, Gonzalo; Bordachar, Pierre; Boriani, Giuseppe; Breithardt, Ole A.; Cleland, John; Deharo, Jean Claude; Delgado, Victoria; Elliott, Perry M.; Gorenek, Bulent; Israel, Carsten W.; et al. (Romanian Journal of Cardiology, 2014)
CRIS-Team Scopus Importer:2023-03-08

Glossary of process times and key indicators in the cardiac catheterization laboratory: CCL glossary Glossar zu Prozesszeiten und Kennzahlen im Herzkatheterlabor: HKL-Glossar - Dörr, Oliver; Schuster, Martin; Gaede, Luise; Ghanem, Alexander; Schmitz, Thomas; Hamm, Christian (Die Kardiologie, 2023)
The demographic change and innovative advances in interventional cardiology lead to changes in the quality of the medical care for patients with cardiovascular diseases. A successful management of cardiac catheterization laboratories can result in an efficiency-oriented organization of medical service processes as well as a robust reporting system, whereby healthcare and economic goals do not have to be in conflict. By establishing and standardizing process steps, process indicators can be derived to help improve the quality of care for patients with cardiovascular diseases.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Health economy; Hospital management; Process steps; Quality of care; Service processes

Growth of hypoplastic mitral valves in hypoplastic left heart complex and similar constellations after anatomical left superior vena cava correction - Cesnjevar, Robert; Harig, Frank; Dietz, Moritz; Alkassar, Muhannad; Waellisch, Wolfgang; Rueffer, André; Dittrich, Sven; Purbojo, Ariawan (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Left superior vena cava (LSVC)-related obstruction of mitral inflow is a rare finding in patients with complex cardiac anomalies like hypoplastic left heart complex. We report our experience by establishing a left superior to right superior caval vein continuity (innominate vein creation by direct LSVC-right superior vena cava end-to-side-anastomosis), and coronary sinus unroofing if indicated for LSVC-related mitral inflow obstruction. METHODS: Nineteen patients (median age: 1.0 ± 0.3 years; range: 7 days-4.8 years) underwent anatomical correction of LSVC without the use of foreign material in conjunction with repair or palliation of congenital anomalies in a single centre between April 2015 and November 2019. Indications for the procedure were LSVC-related obstruction of left ventricular inflow due to a dilated coronary sinus. Additional procedures included mitral (n = 7) or atrioventricular (n = 3) valve surgery, right ventricular to pulmonary artery conduit (n = 3), first stage palliation (n = 3) or biventricular repair (n = 5) of hypoplastic left heart complex. Three patients needed secondary mitral valve replacement (n = 3). RESULTS: All LSVC or coronary sinus-related obstructions were effectively relieved. No patient died early, 2 patients died late after the procedure. One patient needed stenting of the superior vena cava below the unobstructed cephalad vein anastomosis at the former right superior vena cava-cannulation-site. Follow-up was complete and demonstrated an 89.5% survival after 2.5 ± 0.4 years. Innominate vein patency was 100% documented by echocardiography (n = 19), cardiac catheterization (n = 6) or both. Mean mitral valve z-scores before the operation were -1.7 ± 0.2 (range -3.8 to 0.3) and increased to 0.7 ± 0.2 (range -0.7 to 1.9) after LSVC repair. CONCLUSIONS: Anatomical correction by surgical creation of an innominate vein is an effective method to relieve LSVC-related obstructions and promotes mitral valvar growth. Mitral ring sizes were at least normalized after surgery at the time of discharge. Further prospective follow-up studies to evaluate the growth potential of left-sided heart structures by reporting cardiac z-scores are needed to evaluate the true impact of coronary sinus unroofing.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Congenital heart disease; Hypoplastic left heart complex; Left superior vena cava; Mitral valve growth; Mitral valve z-score

Heart Failure in Ischemic Stroke: Relevance for Acute Care and Outcome - Siedler, Gabriela; Sommer, Kim; Macha, Kosmas; Marsch, Armin; Breuer, Lorenz; Stoll, Svenja; Engelhorn, Tobias; Dörfler, Arnd; Schwab, Stefan; Kallmünzer, Bernd; Arnold, Martin (Stroke, 2019)
Background and Purpose- Heart failure (HF) in patients with acute ischemic stroke constitutes the source of various detrimental pathophysiologic mechanisms including prothrombotic and proinflammatory states, worsening of cerebral tissue oxygenation, and hemodynamic impairment. In addition, HF might affect the safety and efficacy of the acute recanalization stroke therapies. Methods- Patients treated with intravenous recombinant tissue-type plasminogen activator or mechanical recanalization at a universitary stroke center were included into a prospective registry. Patients received cardiological evaluation, including echocardiography, during acute care. Functional outcome was assessed after 90 days by structured telephone interviews. Safety and efficacy of intravenous thrombolysis and mechanical thrombectomy were investigated among patients with HF and compared with patients with normal cardiac function after propensity score matching. Results- One thousand two hundred nine patients were included. HF was present in 378 patients (31%) and an independent predictor of unfavorable functional outcome. Recanalization rates were equal among patients with HF after intravenous thrombolysis and after mechanical recanalization or combined treatment. The rate of secondary intracranial hemorrhage was not different (7% versus 8%; P=0.909 after thrombolysis and 15% versus 20%, P=0.364 after mechanical recanalization or combined therapy). Early mortality within 48 hours after admission was equal (<1.5% in both groups). Conclusions- In this real-world cohort of patients with stroke, HF was an independent predictor of unfavorable functional long-term outcome, while the safety and efficacy of intravenous thrombolysis and mechanical recanalization appeared unaffected.
EVALuna2:204477

Heart failure monitoring with implantable defibrillators - Kirchner, Jens; Beckendorf, Claudia; Paule, Stefan; Czygan, Gerald; Arnold, Martin (Biomedizinische Technik. Biomedical engineering, 2012)
Heart failure is one of the most frequent diseases and a leading cause for hospital admission and death in Germany and other industrialized countries. Two types of impedance sensors are presented that promise to allow improved disease monitoring and hence better therapy adaptation in heart failure patients with an implanted defibrillator: thoracic impedance to estimate the lung fluid status of the patient, and intracardiac impedance for assessment of cardiac hemodynamics.<br

Hereditary transthyretin-related amyloidosis is frequent in polyneuropathy and cardiomyopathy of no obvious aetiology - Skrahina, Volha; Grittner, Ulrike; Beetz, Christian; Skripuletz, Thomas; Juenemann, Martin; Kraemer, Heidrun H.; Hahn, Katrin; Rieth, Andreas; Schaechinger, Volker; Patten, Monica; Tanislav, Christian; Achenbach, Stephan; et al. (Annals of Medicine, 2021)
Background Hereditary Transthyretin-Related Amyloidosis, a clinically heterogeneous autosomal dominant disease caused by pathogenic variants in the TTR gene, is characterized by the deposition of insoluble misfolded protein fibrils. The diagnosis, especially in non-endemic areas, is typically delayed by 4-5 years; a misdiagnosis due to clinical heterogeneity is common. The study objective was to define the prevalence of Hereditary Transthyretin-Related Amyloidosis in patients with polyneuropathy and/or cardiomyopathy of no obvious aetiology. Method A multicenter observational "Epidemiological analysis for the hereditary Transthyretin-Related AMyloidosis"-TRAM study was performed in Germany, Austria, and Switzerland. Results A total of 5141 participants were recruited by 50 neurologic and 27 cardiologic specialized centres. Genetic analysis demonstrated a 1.1% Hereditary Transthyretin-Related Amyloidosis positivity rate among patients with polyneuropathy and/or cardiomyopathy of not obvious aetiology. Twenty-one various TTR variants (TTR-positive) were identified. Body Mass Index was lower in the TTR-positive patients as an indicator for the involvement of the autonomic nervous system; the age of onset of clinical manifestations was higher in TTR-positive patients. There were no other genotype-phenotype correlations or the prevalence of specific clinical manifestations in TTR-positive patients. Conclusions Our data support the fact that Hereditary Transthyretin-Related Amyloidosis is underdiagnosed in polyneuropathy and cardiomyopathy patients. Routine implementation of genetic testing is recommended in patients with unexplained polyneuropathy and/or cardiomyopathy to accelerate the earlier diagnosis and the time-sensitive treatment initiation. KEY MESSAGES More than 5.000 participants with CM and/or PNP of no obvious aetiology were recruited in the observational "Epidemiological analysis for the hereditary Transthyretin-Related AMyloidosis" TRAM study and screened for pathogenic TTR variants. The study demonstrated >1% of patients with CM and/or PNP of unclear aetiology are positive for a pathogenic TTR variant. Routine genetic testing is recommended in patients with unexplained CM and/or PNP to accelerate the initial diagnosis and timely treatment initiation.
CRIS-Team WoS Importer:2021-10-29

High-degree atrioventricular block after valve-in-valve transcatheter aortic valve implantation: incidence and predictors - Jung, Susanne; Marwan, Mohamed; Kondruweit, Markus; Achenbach, Stephan; Arnold, Martin (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

High level of EPA is associated with lower perivascular coronary attenuation as measured by coronary CTA - Bittner, D. O.; Göller, Markus; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

High levels of eicosapentaenoic acid are associated with lower pericoronary adipose tissue attenuation as measured by coronary CTA - Bittner, Daniel O.; Göller, Markus; Dey, Damini; Zopf, Yurdagül; Achenbach, Stephan; Marwan, Mohamed (Atherosclerosis, 2020)
Background and aims: Higher pericoronary adipose tissue (PCAT) attenuation, a novel marker of inflammation in coronary CT angiography (CTA), has been shown to indicate increased cardiac mortality. Supplementation of eicosapentaenoic acid (EPA) has been shown to decrease cardiovascular death. Whether blood levels of n-3 fatty acids are associated with differences in PCAT attenuation is unknown. Methods: This is a cross-sectional analysis including 64 symptomatic patients who underwent coronary CTA. PCAT attenuation was measured in Hounsfield Units (HU) around the proximal 40 mm of the right coronary artery using semi-automated software. Erythrocyte membrane fatty acid composition was analyzed using gas chromatography. Individual fatty acids were expressed as a percentage of total identified fatty acids. Results: The patient cohort was divided into two groups using the median PCAT attenuation of −78.1 HU (each n = 32). No differences were seen in age, sex, BMI or traditional cardiovascular risk factors (CVRF) between groups (all p > 0.05). In univariable analysis, significantly higher values of EPA (1.00% [0.78; 1.26] vs. 0.78% [0.63; 0.99]; p = 0.02) were seen in patients with lower PCAT attenuation. All other fatty acids showed no differences (all p > 0.05). Moreover, a significant negative correlation was seen between PCAT attenuation and EPA (CC: 0.38; p = 0.002). In multivariable analysis, an inverse association of EPA with PCAT attenuation existed (ß = −0.31, p = 0.017), independent of age, gender, BMI and number of CVRF (all p > 0.1). Conclusions: High levels of EPA are associated with lower PCAT attenuation on coronary CTA. This may indicate a different composition of pericoronary adipose tissue, potentially caused by a lower degree of coronary inflammation.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Coronary CT-Angiography; Eicosapentaenoic acid; Omega-3 fatty acids; Perivascular coronary inflammation

Highlights from the latest articles in nanoparticles, nanomaterials and nanotoxicity testing - Lyer, Stefan; Cicha, Iwona; Friedrich, Ralf; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19966

Highlights of the Twelfth Annual Scientific Meeting of the Society of Cardiovascular Computed Tomography - Weir-Mccall, Jonathan R.; Villines, Todd C.; Shaw, Leslee J.; Abbara, Suhny; Ferencik, Maros; Nieman, Koen; Achenbach, Stephan; Nicol, Edward (Journal of Cardiovascular Computed Tomography, 2018)
The 12th Annual Scientific Meeting of the SCCT, held from July 6 to July 9 in Washington, DC, was one of the largest to date with 724 attendants from 34 countries, 130 invited talks, 4 "Read with the Experts" sessions, 42 oral abstracts presented, 20 rapid fire posters and 164 poster presentations with the abstracts of all of these published in the JCCT. This article summarises the many themes and topics of presentation and discussion in this meeting, and the many technical advances that are likely to impact future clinical practice and feature in future meetings.
EVALuna2:33588

Highly accelerated, Dixon-based non-contrast MR angiography versus high-pitch CT angiography - Zeilinger, Martin; Giese, Daniel; Schmidt, Michaela; May, Matthias; Janka, Rolf Matthias; Heiß, Rafael; Ammon, Fabian; Achenbach, Stephan; Uder, Michael; Treutlein, Christoph (Radiologia Medica, 2023)
Objectives: To compare a novel, non-contrast, flow-independent, 3D isotropic magnetic resonance angiography (MRA) sequence that combines respiration compensation, electrocardiogram (ECG)-triggering, undersampling, and Dixon water-fat separation with an ECG-triggered aortic high-pitch computed tomography angiography (CTA) of the aorta. Materials and methods: Twenty-five patients with recent CTA were scheduled for non-contrast MRA on a 3 T MRI. Aortic diameters and cross-sectional areas were measured on MRA and CTA using semiautomatic measurement tools at 11 aortic levels. Image quality was assessed independently by two radiologists on predefined aortic levels, including myocardium, proximal aortic branches, pulmonary veins and arteries, and the inferior (IVC) and superior vena cava (SVC). Image quality was assessed on a 5-point Likert scale. Results: All datasets showed diagnostic image quality. Visual grading was similar for MRA and CTA regarding overall image quality (0.71), systemic arterial image quality (p = 0.07–0.91) and pulmonary artery image quality (p = 0.05). Both readers favored MRA for SVC and IVC, while CTA was preferred for pulmonary veins (all p < 0.05). No significant difference was observed in aortic diameters or cross-sectional areas between native MRA and contrast-enhanced CTA (p = 0.08–0.94). Conclusion: The proposed non-contrast MRA enables robust imaging of the aorta, its proximal branches and the pulmonary arteries and great veins with image quality and aortic diameters and cross-sectional areas comparable to that of CTA. Moreover, this technique represents a suitable free-breathing alternative, without the use of contrast agents or ionizing radiation. Therefore, it is especially suitable for patients requiring repetitive imaging.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Angiography; Computed tomography; Follow-up studies; Magnetic resonance imaging

High-Risk Plaque Features on Coronary CT Angiography - Hecht, Harvey S.; Achenbach, Stephan; Kondo, Takeshi; Narula, Jagat (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
EVALuna2:12069

Histamine in atrial fibrillation (AF)–is there any connection? Results from an unselected population - Layritz, C. M.; Hagel, Alexander; Graf, V.; Reiser, C.; Klinghammer, Lutz; Ropers, Dieter; Achenbach, Susanne; Raithel, M. (International Journal of Cardiology, 2014)
EVALuna2:1903

How much evidence is in a case report? A road trip of scientific evidence, including skeptics, Ockham's razor, Hume's Fork, and Karl R. Popper - Achenbach, Stephan; Einstein, Andrew J.; Ferencik, Maros (Journal of Cardiovascular Computed Tomography, 2015)
EVALuna2:12071

Hybrid Coronary Percutaneous Treatment with Metallic Stents and Everolimus-Eluting Bioresorbable Vascular Scaffolds: 2-Years Results from the GABI-R Registry - Gori, Tommaso; Achenbach, Stephan; Riemer, Thomas; Mehilli, Julinda; Nef, Holger M.; Naber, Christoph; Richardt, Gert; Woehrle, Jochen; Zahn, Ralf; Neumann, Till; Kastner, Johannes; Schmermund, Axel; et al. (Journal of Clinical Medicine, 2019)
The limitations of the first-generation everolimus-eluting coronary bioresorbable vascular scaffolds (BVS) have been demonstrated in several randomized controlled trials. Little data are available regarding the outcomes of patients receiving hybrid stenting with both BVS and drug-eluting stents (DES). Of 3144 patients prospectively enrolled in the GABI-Registry, 435 (age 62 +/- 10, 19% females, 970 lesions) received at least one BVS and one metal stent (hybrid group). These patients were compared with the remaining 2709 (3308 lesions) who received BVS-only. Patients who had received hybrid stenting had more frequently a history of cardiovascular disease and revascularization (p < 0.05), had less frequently single-vessel disease (p < 0.0001), and the lesions treated in these patients were longer (p < 0.0001) and more frequently complex. Accordingly, the incidence of periprocedural myocardial infarction (p < 0.05) and that of cardiovascular death, target vessel and lesion failure and any PCI at 24 months was lower in the BVS-only group (all p < 0.05). The 24-months rate of definite and probable scaffold thrombosis was 2.7% in the hybrid group and 2.8% in the BVS-only group, that of stent thrombosis in the hybrid group was 1.86%. In multivariable analysis, only implantation in bifurcation lesions emerged as a predictor of device thrombosis, while the device type was not associated with this outcome (p = 0.21). The higher incidence of events in patients receiving hybrid stenting reflects the higher complexity of the lesions in these patients; in patients treated with a hybrid strategy, the type of device implanted did not influence patients ' outcomes.
CRIS-Team WoS Importer:2019-07-30

Hybrid hydrogels based on keratin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2014)
Novel hybrid hydrogels based on alginate and keratin were successfully produced for the first time. The self-assembly properties of keratin, and its ability to mimic the extracellular matrix were combined with the excellent chemical and mechanical stability and biocompatibility of alginate to produce 2D and 3D hybrid hydrogels. These hybrid hydrogels were prepared using two different approaches: sonication, to obtain 2D hydrogels, and a pressure-driven extrusion technique to produce 3D hydrogels. All results indicated that the composition of the hydrogels had a significant effect on their physical properties, and that they can easily be tuned to obtain materials suitable for biological applications. The cell-material interaction was assessed through the use of human umbilical vein endothelial cells, and the results demonstrated that the alginate/keratin hybrid biomaterials supported cell attachment, spreading and proliferation. The results proved that such novel hybrid hydrogels might find applications as scaffolds for soft tissue regeneration. © 2014 the Partner Organisations.

Hydrogel matrices based on elastin and alginate for tissue engineering applications - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz-Bortuzzo, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2018)
Hydrogels from natural polymers are widely used in tissue engineering due to their unique properties, especially when regarding the cell environment and their morphological similarity to the extracellular matrix (ECM) of native tissues. In this study, we describe the production and characterization of novel hybrid hydrogels composed of alginate blended with elastin from bovine neck ligament. The properties of elastin as a component of the native ECM were combined with the excellent chemical and mechanical stability as well as biocompatibility of alginate to produce two hybrid hydrogels geometries, namely 2D films obtained using sonication treatment and 3D microcapsules produced by pressure-driven extrusion. The resulting blend hydrogels were submitted to an extensive physico-chemical characterization. Furthermore, the biological compatibility of these materials was assessed using normal human dermal fibroblasts, indicating the suitability of this blend for soft tissue engineering. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Alginate; Elastin; Hybrid hydrogels; Soft matrices; Tissue engineering

Hypercalcemia mimicking myocardial infarction - Schmidt-Lauber, Christian; Anneken, Lars; Schödel, Johannes (Kidney International, 2019)
CRIS-Team Scopus Importer:2019-11-19

Hypertrophic remodelling of retinal arterioles in patients with congestive heart failure - Jung, Susanne; Kolwelter, Julie; Bosch, Agnes; Cífková, Renata; Harazny, Joanna M.; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Analysis of microvascular parameters in the retinal circulation—known to reflect those in the systemic circulation—allows us to differentiate between eutrophic and hypertrophic remodelling of small arteries. This study aimed to examine microvascular changes in patients with congestive heart failure (CHF) and reduced as well as mid-range ejection fraction. Methods and results: Forty subjects with CHF underwent measurement of retinal capillary flow (RCF), wall-to-lumen ratio (WLR), vessel and lumen diameter, wall thickness, and wall cross-sectional area (WCSA) of retinal arterioles of the right eye by scanning laser Doppler flowmetry (SLDF). Applying a matched pair approach, we compared this group with reference values of age-matched controls from a random sample in the population of Pilsen, Czech Republic. There was no significant difference in RCF and WLR between the groups (RCF: P = 0.513; WLR: P = 0.106). In contrast, wall thickness and WCSA, indicators of hypertrophic remodelling, were higher in CHF subjects (WT: 15.0 ± 4.2 vs. 12.7 ± 4.2 μm, P = 0.021; WCSA: 4437.6 ± 1314.5 vs. 3615.9 ± 1567.8 μm2, P = 0.014). Similarly, vessel (109.4 ± 11.1 vs. 100.5 ± 14.4 μm, P = 0.002) and lumen diameter (79.0 ± 7.9 vs. 75.2 ± 8.5 μm, P = 0.009) were increased in CHF. Conclusions: In CHF subjects, we observed hypertrophic remodelling of retinal arterioles indicative of similar changes of small resistance arteries in the systemic circulation. Microvascular structure and function assessed by SLDF may thereby represent a useful, non-invasive method for monitoring of microvascular damage in patients with CHF and may offer innovative treatment targets for new CHF therapies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Heart failure; Hypertrophic remodelling; Microvasculature; Retina

Iatrogenitate Adverse events associated with medical procedures - Bahrmann, Philipp; Haack, A.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2011)
Keywords: iatrogenesis; drug safety; falls in the elderly; perioperative complications; comorbidities; psychotropic drugs; prevention

Identification and characterization of the specific murine NK cell subset supporting graft-versus-leukemia- and reducing graft-versus-host-effects - Meinhardt, Kathrin; Kroeger, Irena; Bauer, Ruth; Ganss, Franziska; Ovsiy, Ilja; Rothamer, Johanna; Büttner, Maike; Atreya, Imke; Waldner, Maximilian; Bittrich, Max; Lehmann, Christian; Rieger, Michael A.; et al. (OncoImmunology, 2015)
Clinical studies investigating the impact of natural killer (NK) cells in allogeneic hematopoietic stem cell transplantation settings have yielded promising results. However, NK cells are a functionally and phenotypically heterogeneous population. Therefore, we addressed the functional relevance of specific NK cell subsets distinguished by expression of CD117, CD27 and CD11b surface markers in graft-versus-leukemia (GVL)-reaction and graft-versus-host-disease (GVHD). Our results clearly demonstrate that the subset of c-Kit(-)CD27(-)CD11b(+) NK cells expressed multiple cytotoxic pathway genes and provided optimal graft-versus-leukemia-effects, while significantly reducing T cell proliferation induced by allogeneic dendritic cells. Furthermore, these NK cells migrated to inflamed intestinal tissues where graft-versus-host-colitis was efficiently mitigated. For the first time, we identified the c-Kit(-)CD27(-)CD11b(+) NK cell population as the specific effector NK cell subset capable of significantly diminishing GVHD in fully mismatched bone marrow transplantation settings. In conclusion, the subset of c-Kit(-)CD27(-)CD11b(+) NK cells not only supports GVL, but also plays a unique role in the protection against GVHD by migrating to the peripheral GVHD target organs where they exert efficient immunoregulatory activities. These new insights demonstrate the importance of selecting the optimal NK cell subset for cellular immunotherapy following allogeneic hematopoietic stem cell transplantation.
EVALuna2:1965

IGA ISOTYPE ANTI-HLA ANTIBODIES AND ORGAN GRAFT SURVIVAL IN KIDNEY TRANSPLANTATION - Bach, Christian; Spriewald, B. M.; Arnold, Martin (2018)
EVALuna2:35091

Image quality of ultra-low radiation exposure coronary CT angiography with an effective dose <0.1 mSv using high-pitch spiral acquisition and raw data-based iterative reconstruction - Schuhbaeck, Annika; Achenbach, Stephan; Layritz, Christian; Eisentopf, Jasmin; Hecker, Franziska; Pflederer, Tobias; Gauss, Soeren; Rixe, Johannes; Kalender, Willi Alfred; Daniel, Werner; Lell, Michael; Ropers, Dieter (European Radiology, 2013)
Objectives: We evaluated the potential of prospectively ECG-triggered high-pitch spiral acquisition with low tube voltage and current in combination with iterative reconstruction to achieve coronary CT angiography with sufficient image quality at an effective dose below 0.1 mSv. Methods: Contrast-enhanced coronary dual source CT angiography (2 × 128 × 0.6 mm, 80 kV, 50 mAs) in prospectively ECG-triggered high-pitch spiral acquisition mode was performed in 21 consecutive individuals (body weight <100 kg, heart rate ≤60/min). Images were reconstructed with raw data-based filtered back projection (FBP) and iterative reconstruction (IR). Image quality was assessed on a 4-point scale (1 = no artefacts, 4 = unevaluable). Results: Mean effective dose was 0.06 ± 0.01 mSv. Image noise was significantly reduced in IR (128.9 ± 46.6 vs. 158.2 ± 44.7 HU). The mean image quality score was lower for IR (1.9 ± 1.1 vs. 2.2 ± 1.0, P < 0.0001). Of 292 coronary segments, 55 in FBP and 40 in IR (P = 0.12) were graded "unevaluable". In patients with a body weight ≤75 kg, both in FBP and in IR, the rates of fully evaluable segments were significantly higher in comparison to patients >75 kg. Conclusions: Coronary CT angiography with an estimated effective dose <0.1 mSv may provide sufficient image quality in selected patients through the combination of high-pitch spiral acquisition and raw data-based iterative reconstruction. Key Points: • Coronary CT angiography with an estimated effective dose <0.1 mSv is possible. • Combination of high-pitch spiral acquisition with iterative reconstruction achieves sufficient image quality. • Diagnostic accuracy remains to be assessed in future trials. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Dual source CT; High-pitch spiral acquisition; Image quality; Iterative reconstruction; Ultra low-dose coronary CT angiography

Imaging in ESC clinical guidelines: chronic coronary syndromes - Saraste, Antti; Barbato, Emanuele; Capodanno, Davide; Edvardsen, Thor; Prescott, Eva; Achenbach, Stephan; Bax, Jeroen J.; Wijns, William; Knuuti, Juhani (European Heart Journal - Cardiovascular Imaging, 2019)
The European Society of Cardiology (ESC) has recently published new guidelines on the diagnosis and management of chronic coronary syndromes (CCS). The 2019 guideline identified six common clinical scenarios of CCS defined by the different evolutionary phases of coronary artery disease (CAD), excluding the situations in which an acute coronary event, often with coronary thrombus formation, dominates the clinical presentation. This review aims at providing a summary of novel or revised concepts in the guidelines together with the recent data underlying the major changes on the use of cardiac imaging in patients with suspected or known CCS. Based on data from contemporary cohorts of patients referred for diagnostic testing, the pre-test probabilities of CAD based on age, sex and symptoms have been adjusted substantially downward as compared with 2013 ESC guidelines. Further, the impact of various risk factors and modifiers on the pre-test probability was highlighted and a new concept of 'Clinical likelihood of CAD' was introduced. Recommendations regarding diagnostic tests to establish or rule-out obstructive CAD have been updated with recent data on their diagnostic performance in different patient groups and impact on patient outcome. As the initial strategy to diagnose CAD in symptomatic patients, non-invasive functional imaging for myocardial ischaemia, coronary computed tomography angiography or invasive coronary angiography combined with functional evaluation may be used, unless obstructive CAD can be excluded by clinical assessment alone. When available, imaging tests instead of the exercise electrocardiogram are recommended when following the non-invasive diagnostic strategy.
CRIS-Team Scopus Importer:2019-10-29
Keywords: cardiac magnetic resonance; coronary artery disease; coronary computed tomography angiography; echocardiography; positron emission computed tomography; single-photon emission computed tomography

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Imaging of the Pericoronary Adipose Tissue (PCAT) Using Cardiac Computed Tomography: Modern Clinical Implications - Göller, Markus; Achenbach, Stephan; Duncker, Hendrik; Dey, Damini; Marwan, Mohamed (Journal of Thoracic Imaging, 2021)
Modern coronary computed tomography angiography (CTA) is the gold standard to visualize the epicardial adipose tissue (EAT) and pericoronary adipose tissue (PCAT). The EAT is a metabolic active fat depot enclosed by the visceral pericardium and surrounds the coronary arteries. In disease states with increased EAT volume and dysfunctional adipocytes, EAT secretes an increased amount of adipocytokines and the resulting imbalance of proinflammatory and anti-inflammatory mediators potentially causes atherogenic effects on the coronary vessel wall in a paracrine way ("outside-to-inside" signaling). These EAT-induced atherogenic effects are reported to increase the risk for the development of coronary artery disease, myocardial ischemia, high-risk plaque features, and future major adverse cardiac events. Coronary inflammation plays a key role in the development and progression of coronary artery disease; however, its noninvasive detection remains challenging. In future, this clinical dilemma might be changed by the CTA-derived analysis of the PCAT. On the basis of the concept of an "inside-to-outside" signaling between the inflamed coronary vessel wall and the surrounding PCAT recent evidence demonstrates that PCAT computed tomography attenuation especially around the right coronary artery derived from routine CTA is a promising imaging biomarker and "sensor" to noninvasively detect coronary inflammation. This review summarizes the biological and technical principles of CTA-derived PCAT analysis and highlights its clinical implications to improve modern cardiovascular prevention strategies.
CRIS-Team Scopus Importer:2021-05-21
Keywords: atherosclerosis; computed tomography attenuation; computed tomography imaging; inflammation; pericoronary adipose tissue

Imaging the Vulnerable Plaque on Coronary CTA - Achenbach, Stephan (Journal of the American College of Cardiology : Cardiovascular imaging, 2020)
CRIS-Team Scopus Importer:2020-04-07
Keywords: atherosclerosis; computed tomography; plaque

Impact of age and sex on left ventricular function determined by coronary computed tomographic angiography: results from the prospective multicentre CONFIRM study - Gebhard, Catherine; Buechel, Ronny R.; Stahli, Barbara E.; Gransar, Heidi; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Canister, Tracy Q.; Chow, Benjamin; Dunning, Allison; Al-Mallah, Mouaz H.; Cademartiri, Filippo; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Background: Left ventricular (LV) volumetric and functional parameters measured with cardiac computed tomography (cardiac CT) augment risk prediction and discrimination for future mortality. Gender- and age-specific standard values for LV dimensions and systolic function obtained by 64-slice cardiac CT are lacking. Methods and results: 1155 patients from the Coronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry (54.5% males, mean age 53.1 ± 12.4 years, range: 18-92 years) without known coronary artery disease (CAD), structural heart disease, diabetes, or hypertension who underwent cardiac CT for various indications were categorized according to age and sex. A cardiac CT data acquisition protocol was used that allowed volumetric measuring of LV function. Image interpretation was performed at each site. Patients with significant CAD (>50% stenosis) on cardiac CT were excluded from the analysis. Overall, mean left ventricular ejection fraction (LVEF) was higher in women when compared with men (66.6 ± 7.7% vs. 64.6 ± 8.1%, P < 0.001). This gender-difference in overall LVEF was caused by a significantly higher LVEF in women ≥70 years when compared with men ≥70 years (69.95 ± 8.89% vs. 65.50 ± 9.42%, P = 0.004). Accordingly, a significant increase in LVEF was observed with age (P = 0.005 for males and P < 0.001 for females), which was more pronounced in females (5.21%) than in males (2.6%). LV end-diastolic volume decreased in females from 122.48 ± 27.87 (<40 years) to 95.56 ± 23.17 (>70 years; P < 0.001) and in males from 155.22 ± 35.07 (<40 years) to 130.26 ± 27.18 (>70 years; P < 0.001). Conclusion: Our findings indicate that the LV undergoes a lifelong remodelling and highlight the need for age and gender adjusted reference values.
EVALuna2:33622

Impact of chronic kidney disease on efficacy and safety of interventional left atrial appendage closure - results from the prospective multicenter LAARGE registry - Fastner, C.; Brachmann, J.; Lewalter, T.; Zeymer, U.; Sievert, H.; Nienaber, C. A.; Weiss, C.; Ince, H.; Maier, J.; Achenbach, Stephan; Sigusch, H. H.; Hochadel, M.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Impact of conscious sedation and general anesthesia on periprocedural outcomes in Watchman left atrial appendage closure - Kleinecke, Caroline; Allakkis, Wasim; Buffle, Eric; Liu, Xiao-Xia; Mohrez, Yamen; Gloekler, Steffen; Brachmann, Johannes; Schnupp, Steffen; Achenbach, Stephan; Yu, Jiangtao (Cardiology Journal, 2021)
Background: Transcatheter left atrial appendage closure (LAAC) is performed either in conscious sedation (CS) or general anesthesia (GA), and limited data exist regarding clinical outcomes for the two approaches. The aim of the study was to analyze the effect of CS versus GA on acute outcomes in a large patient cohort undergoing LAAC with a Watchman occluder.
CRIS-Team WoS Importer:2021-07-30

Impact of coronary calcification on outcomes after ABSORB scaffold implantation: Insights from the GABI-R registry - Hemetsberger, Rayyan; Abdelghani, Mohammad; Mankerious, Nader; Allali, Abdelhakim; Toelg, Ralph; Gori, Tommaso; Achenbach, Stephan; Riemer, Thomas; Mehilli, Julinda; Nef, Holger M.; Naber, Christoph; Woehrle, Jochen; et al. (Coronary Artery Disease, 2020)
Objective To investigate the outcomes after bioresorbable scaffold (BRS) implantation in calcified coronary lesions. In calcified coronary lesions, durable metallic drug-eluting stent (DES) implantation is associated with worse clinical outcomes compared to noncalcified lesions. Although not recommended, BRSs were frequently implanted in calcified lesions in clinical practice. Their outcome is not well investigated. Methods Between November 2013 and January 2016, 3326 patients were enrolled in the German-Austrian ABSORB ReglstRy (GABI-R). Lesion calcification severity was classified into no (n=1144), mild (n=1306), and moderate-to-severe (n=690) calcification. Results Patients with calcification were older (none: 59.1±11.2 vs. mild: 61.6±10.9 vs. moderate to severe: 62.4±10.5years, P<0.001), had more diabetes (19.1 vs. 20.8 vs. 23.9%, P=0.015), and more often had previous myocardial infarction (MI) (19.3 vs. 23.1 vs. 25.4%, P=0.002). Despite a higher rate of postdilatations (P<0.001), lesions with calcification had more residual stenosis (2.05±9.36% vs. 3.11±9.36% vs. 3.89±9.39%, P<0.001). Consequently, procedural success was achieved in 97.7 vs. 96.2 vs. 93.6% of cases in none, mild, and moderate-to-severe calcification (P<0.001). At 24months, cardiac death (0.3 vs. 0.7 vs. 1.6%, P=0.009) was higher with increasing calcification. However, no significant between-group difference was observed in the incidence of target vessel MI, target vessel revascularization, or target lesion failure. The rate of probable scaffold thrombosis was significantly higher with increasing calcification. Conclusion In GABI-R, ABSORB scaffolds in calcified lesions required more postdilation, led to more residual stenosis, but did not portend increased target lesion revascularization over 2years. Nevertheless, coronary calcification severity emerged as a cardiovascular risk marker and was predictive of cardiovascular mortality. Clinicaltrial.gov NCT02066623.
CRIS-Team Scopus Importer:2020-10-23
Keywords: ABSORB; Bioresorbable vascular scaffold; Coronary calcification; GABI-R

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Impact of family history of coronary artery disease in young individuals (from the CONFIRM registry) - Otaki, Yuka; Gransar, Heidi; Berman, Daniel S.; Cheng, Victor Y.; Dey, Damini; Lin, Fay Y.; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (American Journal of Cardiology, 2013)
Although family history (FH) of coronary artery disease (CAD) is considered a risk factor for future cardiovascular events, the prevalence, extent, severity, and prognosis of young patients with FH of CAD have been inadequately studied. From 27,125 consecutive patients who underwent coronary computed tomographic angiography, 6,308 young patients (men aged <55 years and women aged <65 years) without known CAD were identified. Obstructive CAD was defined as >50% stenosis in a coronary artery >2 mm diameter. Risk-adjusted logistic regression, Kaplan-Meier, and Cox proportional-hazards models were used to compare patients with and without FH of CAD. Compared with subjects without FH of CAD, those with FH of CAD (FH+) had higher prevalences of any CAD (40% vs 30%, p <0.001) and obstructive CAD (11% vs 7%, p <0.001), with multivariate odds of FH+ increasing the likelihood of obstructive CAD by 71% (p <0.001). After a mean follow-up period of 2 ± 1 years (42 myocardial infarctions and 39 all-cause deaths), FH+ patients experienced higher annual rates of myocardial infarction (0.5% vs 0.2%, log-rank p = 0.001), with a positive FH the strongest predictor of myocardial infarction (hazard ratio 2.6, 95% confidence interval 1.4 to 4.8, p = 0.002). In conclusion, young FH+ patients have higher presence, extent, and severity of CAD, which are associated with increased risk for myocardial infarction. Compared with other clinical CAD risk factors, positive FH in young patients is the strongest clinical predictor of future unheralded myocardial infarction. © 2013 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Impact of Ivabradine on Inflammatory Markers in Chronic Heart Failure - Rohm, Ilonka; Kretzschmar, Daniel; Pistulli, Rudin; Franz, Marcus; Schulze, P. Christian; Stumpf, Christian; Yilmaz, Atilla (Journal of Immunology Research, 2016)
Background. Inflammation plays a crucial role in the progression of chronic heart failure (CHF). Ivabradine is known to reduce the morbidity and mortality of patients with CHF under certain conditions. Beyond the reduction of heart rate, only limited knowledge exists about potential anti-inflammatory effects of ivabradine that might contribute to its benefit in CHF. Thus, the present study aimed to investigate the effect of ivabradine on systemic inflammation. Methods. In the present study, 33 patients with CHF due to dilated, ischemic, and hypertensive cardiomyopathy were treated with ivabradine according to the guidelines of the European Society of Cardiology (ESC). A number of circulating dendritic cells as well as inflammatory mediators were investigated using FACS analysis and ELISA, respectively, before and during ivabradine therapy. Results. Treatment with ivabradine resulted in a significant improvement of CHF symptoms as well as an increase in left ventricular ejection fraction. Moreover, ivabradine treatment led to a significant reduction of TNF-alpha (TNF-alpha) serum levels and a reconstitution of circulating dendritic cells which are known to be reduced in patients with CHF. Conclusion. We show that treatment with ivabradine in patients with CHF resulted in an improvement of HF symptoms and ejection fraction as well as a normalization of inflammatory mediators.
EVALuna2:33707

IMPACT OF LITOMOSOIDES SIGMODONTIS ANTIGEN ON T CELL DIFFERENTIATION AND ON THE DEVELOPMENT OF INITIAL ATHEROSCLEROTIC LESIONS IN APOE-KNOCKOUT MICE - Kühn, Charlotte; Tauchi-Brueck, M.; Ajendra, J.; Hoerauf, A.; Stumpf, Christian; Achenbach, Stephan; Huebner, M.; Dietel, B. (2016)
EVALuna2:33680

Impact of single nucleotide polymorphisms in the VEGFR2 gene on endothelial cell activation under non‑uniform shear stress - Schacher, Nora; Raaz-Schrauder, Dorette; Pasutto, Francesca; Stumpfe, Florian M.; Tauchi, Miyuki; Dietel, Barbara; Achenbach, Stephan; Urschel, Katharina (International Journal of Molecular Medicine, 2019)
Single nucleotide polymorphisms (SNPs) in vascular endothelial growth factor receptor 2 (VEGFR2) are associated with coronary artery disease, hypertension and myocardial infarction. However, their association with atherosclerosis remains to be fully elucidated. The purpose of the present study was to determine whether SNPs are involved in atherogenesis, by analyzing their impact on human umbilical vein endothelial cells (HUVECs) under laminar and non-uniform shear stress in a well-established in vitro model that simulates shear stress-induced proatherogenic processes at vessel bifurcations. All experiments were performed using freshly isolated HUVECs. Three SNPs in the VEGFR2 gene (rs1870377 T>A, rs2071559 A>G and rs2305948 C>T) were genotyped and the expression levels of VEGFR2 were semi-quantitatively determined using western blotting. Subsequently, the HUVECs were seeded in bifurcating flow‑through cell culture slides and flow (9.6 ml/min) was applied for 19 h, including tumor necrosis factor-α stimulation during the final 2 h of flow. The protein expression levels of VCAM-1, E-selectin and VEGFR2 and the adhesion of THP-1 cells were analyzed in laminar and non-uniform shear stress regions. Data were analyzed for associations with the respective SNPs. The total expression of VEGFR2 was significantly lower under non‑uniform shear stress than under laminar shear stress conditions, independent of the genotype. The expression of VEGFR2 between the different shear stress patterns was not significantly altered by the different SNPs. The expression levels of VCAM-1 and E-selectin were lower in the A/A genotype compared with those in other genotypes in rs1870377 T>A and rs2071559 A>G. In conclusion, the results suggested that SNPs within the VEGFR2 gene have a significant impact on shear stress‑related endothelial activation.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Adhesion molecules; Atherosclerosis; Endothelial dysfunction; Shear stress; Single nucleotide polymorphism; Vascular endothelial growth factor receptor 2

IMPACT OF SINGLE NUCLEOTIDE POLYMORPHISMS RS1870377 A > T AND RS2305948 C > T ON ENDOTHELIAL CELL ACTIVATION UNDER NON-UNIFORM SHEAR STRESS - Urschel, Katharina; Schacher, Nora; Pasutto, Francesca; Achenbach, Stephan; Raaz-Schrauder, Dorette; Schrauder, Michael G.; Stumpfe, Florian; Dietel, Barbara (2017)
EVALuna2:9363

Impact of strut thickness on acute mechanical performance: A comparison study using optical coherence tomography between DESolve 150 and DESolve 100 - Boeder, Niklas F.; Doerr, Oliver; Bauer, Timm; Mattesini, Alessio; Elsaesser, Albrecht; Liebetrau, Christoph; Achenbach, Stephan; Hamm, Christian W.; Nef, Holger M. (International Journal of Cardiology, 2017)
OBJECTIVE: To evaluate the acute performance of a novolimus-eluting bioresorbable scaffold (BRS) with different strut thickness (DESolve system 150 and 100) using optical coherence tomography (OCT) in terms of appropriate scaffold deployment. BACKGROUND: Outcome after BRS implantation seen in registries and meta-analyses continue to show a higher rate of scaffold thrombosis than those reported with DES. Thus, second scaffold generations with lower strut thickness might have potential advantages in terms of flow disturbance. However, whether mechanical properties are comparable has to be evaluated. METHODS AND RESULTS: Fifty-seven patients undergoing OCT-guided scaffold implantation were enrolled consecutively in this retrospective study. The final pullback after DESolve 150 (n=42) and DESolve 100 (n=15) were compared. The following indices were calculated: mean and minimum area, residual area stenosis, incomplete strut apposition, tissue prolapse, eccentricity and symmetry indexes, strut fracture, and edge dissection. Most patients suffered a multi vessel disease. Maximum pre-dilatation balloon inflation pressure was 13.5±3.2 vs 14.5±2.5atm. OCT analysis showed a minimal lumen area of 6.1±1.9 vs 5.2±1.6mm2, p=0.06. Mean residual area stenosis was 15.3% vs 21.3, p=0.22. Mean eccentricity index did not differ significantly (0.8±0.1 vs 0.6±0.1, p=0.61). Prolapse area was 4.5±8.8 vs 5.6±9.8mm2. CONCLUSION: OCT showed similar post-procedural scaffold geometry and outcome indicating that both BRS may be implanted with good acute performance. However, the trend towards a smaller MLA and a higher percentage of RAS suggest a decreased radial strength for the 100μm BRS. The attempt to reduce strut thickness should not result in loss of radial strength. CONDENSED ABSTRACT: Rates of scaffold thrombosis after bioresorbable scaffold (BRS) implantation are reported to be higher than after metallic stent (DES) implantation. Thus, second scaffold generations with lower strut thickness might have potential advantages in terms of flow disturbance. We aimed to evaluate the acute performance of a novolimus-eluting BRS with different strut thickness (DESolve system 150 and 100) using optical coherence tomography (OCT) in terms of appropriate scaffold deployment. OCT showed similar post-procedural scaffold geometry and outcome indicating that both BRS may be implanted with good acute performance. However, the data suggest a decreased radial strength for the 100μm BRS.
EVALuna2:33610

Impact of telmisartan on the inflammatory state in patients with coronary atherosclerosis - Influence on IP-10, TNF-α and MCP-1 - Klinghammer, Lutz; Urschel, Katharina; Cicha, Iwona; Lewczuk, Piotr; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph (Cytokine, 2013)
Background: Hypertension is one of the most prominent risk factors for coronary artery disease (CAD). Treatment of hypertension is therefore important for reducing cardiovascular events and the progression of atherosclerosis. Several treatment strategies are common in clinical practice for example the use of ACE-blockers or angiotensin receptor II blockers (ARBs), so called sartans. Telmisartan, belonging to the class of ARBs, was shown to exert anti-inflammatory effects besides the blood pressure lowering. Methods: In this work, two separate substudy groups of hypertensives were compared. 16 patients with arterial hypertension have been treated with telmisartan (initial 40. mg Kinzalmono®) for 7.3±4.4 months. The telmisartan group was compared to a matched control group including 31 hypertensive patients without telmisartan treatment with a follow up period of 1.9±0.5 years. Serum samples from the beginning and the end of follow up were analyzed with Luminex® technology for 26 cytokines and chemokines. The baseline scores of coronary artery calcification (CAC) were gathered by multislice detector computer tomography. Results: After 7. months of telmisartan treatment and 2. years in control patients most of the measured analytes did not change significantly. MCP-1 (P=0.001; P<0.001) was increased significantly in both telmisartan and control group. The relative decrease in IP-10 and TNF-α levels was observed in telmisartan group, as opposed to the increase in control (telmisartan vs. control P=0.048; P=0.01). No linear rank-correlation between measured analytes and the initial CAC was found. Conclusion: Telmisartan reduced blood pressure in patients with atherosclerosis and arterial hypertension within a short time period, whereas the inflammatory status of these patients remained largely unchanged. An involvement of telmisartan in the regulation of inflammatory and anti-inflammatory mediators in the context of CAD and CAC is possible, but cannot clearly be assumed based on the present findings. © 2013.
CRIS-Team Scopus Importer:2023-03-08
Keywords: %Δa; Δ; Δa; Atherosclerosis; CAC; Chemokines; Cytokines; Risk factors; Telmisartan

Impact of the learning curve on procedural results and acute outcome after percutaneous coronary interventions with everolimus-eluting bioresorbable scaffolds in an all-comers population - Wiebe, Jens; Liebetrau, Christoph; Dörr, Oliver; Wilkens, Eva; Bauer, Timm; Elsässer, Albrecht; Achenbach, Stephan; Möllmann, Helge; Hamm, Christian W.; Nef, Holger M. (Cardiovascular Revascularization Medicine, 2015)
The implantation of bioresorbable scaffolds (BVSs) is an emerging technique in the treatment of coronary lesions and implantation of BVSs is different than that of metallic drug-eluting stents, however, due to different mechanical properties. This investigation focused on procedural and mid-term results and was designed to evaluate whether there is evidence of a learning curve with BVSs and how it might influence the clinical outcome.In an all-comers registry, the first 100 consecutive patients were compared with the second 100 patients. Target parameters were major adverse cardiac events (MACEs), including cardiac death, any myocardial infarction, and percutaneous or surgical target lesion revascularization (TLR). Target vessel failure (TVF) comprised cardiac death, target vessel myocardial infarction, and percutaneous or surgical target vessel revascularization (TVR).Baseline characteristics were not significantly different. Post-dilatation was used significantly more often in the second group (23.8% vs. 50.5%, p<0.05) as was intravascular imaging (9% vs. 19%, p<0.05). In-hospital MACEs (2.0% for both groups) and median duration of hospital stay (4 (2-6)days) did not differ significantly. During a follow-up of 210 (155-369) or 200 (176-286)days (p=n.s.) for the first and second groups, respectively, MACE (11.2% vs. 1.1%, p<0.01), TVF (10.1% vs. 1.1%, p<0.01), and TVR (9.9% vs. 1.1%, p<0.05) rates were significantly lower in the second group.There is evidence of a learning curve. Post-dilatation is most probably associated with an improved clinical result and intravascular imaging might be useful for further improvement.
EVALuna2:12121

Improved 5-year prediction of all-cause mortality by coronary CT angiography applying the CONFIRM score - Deseive, Simon; Shaw, Leslee J.; Min, James K.; Achenbach, Stephan; Andreini, Daniele; Al-Mallah, Mouaz H.; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracy Q.; Cademartiri, Filippo; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: To investigate the long-term performance of the CONFIRM score for prediction of all-cause mortality in a large patient cohort undergoing coronary computed tomography angiography (CCTA). Methods and results: Patients with a 5-year follow-up from the international multicentre CONFIRM registry were included. The primary endpoint was all-cause mortality. The predictive value of the CONFIRM score over clinical risk scores (Morise, Framingham, and NCEP ATP III score) was studied in the entire patient population as well as in subgroups. Improvement in risk prediction and patient reclassification were assessed using categorical net reclassification index (NRI) and integrated discrimination improvement (IDI). During a median follow-up period of 5.3 years, 982 (6.5%) of 15 219 patients died. The CONFIRM score outperformed the prognostic value of the studied three clinical risk scores (c-indices: CONFIRM score 0.696, NCEP ATP III score 0.675, Framingham score 0.610, Morise score 0.606; c-index for improvement CONFIRM score vs. NCEP ATP III score 0.650, P < 0.0001). Application of the CONFIRM score allowed reclassification of 34% of patients when compared with the NCEP ATP III score, which was the best clinical risk score. Reclassification was significant as revealed by categorical NRI (0.06 with 95% CI 0.02 and 0.10, P = 0.005) and IDI (0.013 with 95% CI 0.01 and 0.015, P < 0.001). Subgroup analysis revealed a comparable performance in a variety of patient subgroups. Conclusions: The CONFIRM score permits a significantly improved prediction of mortality over clinical risk scores for >5 years after CCTA. These findings are consistent in a large variety of patient subgroups.
EVALuna2:33648

IMPROVED CARDIAC RISK STRATIFICATION IN INDIVIDUALS WITH HIGH RISK PLAQUE FEATURES USING THE PERIVASCULAR FAT ATTENUATION INDEX ON CCTA - Kotanidis, Christos P.; Oikonomou, Evangelos K.; Kluener, Laura; Thomas, Katharine E.; Alashi, Alaa; Antonopoulos, Alexios S.; Shirodaria, Cheerag; Neubauer, Stefan; Channon, Keith M.; Achenbach, Stephan; Desai, Milind Y.; Antoniades, Charalambos; et al. (HEART, 2020)
CRIS-Team WoS Importer:2021-01-29

Improving Deep Learning-based Cardiac Abnormality Detection in 12-Lead ECG with Data Augmentation - Qiu, Jingna; Oppelt, Maximilian; Nissen, Michael; Anneken, Lars; Breininger, Katharina; Eskofier, Björn (: 2022 44th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2022)
Automated Electrocardiogram (ECG) classification using deep neural networks requires large datasets annotated by medical professionals, which is time-consuming and expensive. This work examines ECG augmentation as a method for enriching existing datasets at low cost. First, we introduce three novel augmentations: Limb Electrode Move and Chest Electrode Move both simulate a minor electrode mislocation during signal measurement, and Heart Vector Transform generates an ECG by modeling a rotated main heart axis. These techniques are then combined with nine time series signal augmentations from literature. Evaluation was performed on ICBEB, PTB-XL Diagnostic, PTB-XL Rhythm, and PTB-XL Form datasets. Compared to models trained without data augmentation, area under the receiver operating characteristic curve (AUC) was increased by 3.5%, 1.7%, 1.4% and 3.5%, respectively. Our experiments demonstrated that data augmentation can improve deep learning performance in ECG classification. Analyses of the individual augmenion effects established the efficacy of the three proposed augmentations.<br

Improving medical care and prevention in adults with congenital heart disease-reflections on a global problem-part I: development of congenital cardiology, epidemiology, clinical aspects, heart failure, cardiac arrhythmia - Neidenbach, Rhoia; Niwa, Koichiro; Oto, Oeztekin; Oechslin, Erwin; Aboulhosn, Jamil; Celermajer, David; Schelling, Joerg; Pieper, Lars; Sanftenberg, Linda; Oberhoffer, Renate; De Haan, Fokko; Weyand, Michael; et al. (Cardiovascular Diagnosis and Therapy, 2018)
Today most patients with congenital heart defects (CHD) survive into adulthood. Unfortunately, despite relevant residua and sequels, follow-up care of adults with congenital heart disease (ACHD) is not performed in specialized and/or certified physicians or centres. Major problems in the long-term course encompass heart failure, cardiac arrhythmias, heart valve disorders, pulmonary vascular disease, infective endocarditis, aortopathy and non-cardiac comorbidities. Many of them manifest themselves differently from acquired heart disease and therapy regimens from general cardiology cannot be transferred directly to CHD. It should be noted that even simple, postoperative heart defects that were until recently considered to be harmless can lead to problems with age, a fact that had not been expected so far. The treatment of ACHD has many special features and requires special expertise. Thereby, it is important that treatment regimens from acquired heart disease are not necessarily transmitted to CHD. While primary care physicians have the important and responsible task to set the course for adequate diagnosis and treatment early and to refer patients to appropriate care in specialized ACHD-facilities, they should actively encourage ACHD to pursue follow-up care in specialized facilities who can provide responsible and advanced advice. This medical update emphasizes the current data on epidemiology, heart failure and cardiac arrhythmia in ACHD.
EVALuna2:35958

Improving medical care and prevention in adults with congenital heart disease-reflections on a global problem-part II: infective endocarditis, pulmonary hypertension, pulmonary arterial hypertension and aortopathy - Neidenbach, Rhoia; Niwa, Koichiro; Oto, Oeztekin; Oechslin, Erwin; Aboulhosn, Jamil; Celermajer, David; Schelling, Joerg; Pieper, Lars; Sanftenberg, Linda; Oberhoffer, Renate; De Haan, Fokko; Weyand, Michael; et al. (Cardiovascular Diagnosis and Therapy, 2018)
Despite relevant residua and sequels, follow-up care of adults with congenital heart disease (ACHD) is too often not performed by/in specialized and/or certified physicians or centers although major problems in the long-term course may develop. The most relevant encompass heart failure, cardiac arrhythmias, heart valve disorders, pulmonary vascular disease, infective endocarditis (IE), aortopathy and non-cardiac comorbidities. The present publication emphasizes current data on IE, pulmonary and pulmonary arterial hypertension and aortopathy in ACHD and underlines the deep need of an experienced follow-up care by specialized and/or certified physicians or centers, as treatment regimens from acquired heart disease can not be necessarily transmitted to CHD. Moreover, the need of primary and secondary medical prevention becomes increasingly important in order to reduce the burden of disease as well as the socioeconomic burden and costs in this particular patient group.
EVALuna2:35959

Improving Segmentation Quality in Rotational Angiography Using Epipolar Consistency - Unberath, Mathias; Aichert, André; Achenbach, Stephan; Maier, Andreas (Proceedings of MICCAI CVII-STENT, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.improv_1

IMPULSE: The impact of gender on the presentation and management of aortic stenosis across Europe - Steeds, Richard Paul; Messika-Zeitoun, David; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Rudolph, Tanja K.; Lloyd, Guy; Bortone, Alessandro Santo; Clerici, Alberto; Delle-Karth, Georg; et al. (Open Heart, 2021)
Aims There is an increasing awareness of gender-related differences in patients with severe aortic stenosis and their outcomes after surgical aortic valve replacement (SAVR) and transcatheter aortic valve implantation (TAVI). Methods Data from the IMPULSE registry were analysed. Patients with severe aortic stenosis (AS) were enrolled between March 2015 and April 2017 and stratified by gender. A subgroup analysis was performed to assess the impact of age. Results Overall, 2171 patients were enrolled, and 48.0% were female. Women were characterised by a higher rate of renal impairment (31.7 vs 23.3%; p<0.001), were at higher surgical risk (EuroSCORE II: 4.5 vs 3.6%; p=0.001) and more often in a critical preoperative state (7.0vs 4.2%; p=0.003). Men had an increased rate of previous cardiac surgery (9.4 vs 4.7%; p<0.001) and a reduced left ventricular ejection fraction (4.9 vs 1.3%; p<0.001). Concomitant mitral and tricuspid valve disease was substantially more common among women. Symptoms were highly prevalent in both women and men (83.6 vs 77.3%; p<0.001). AVR was planned in 1379 cases. Women were more frequently scheduled to undergo TAVI (49.3 vs 41.0%; p<0.001) and less frequently for SAVR (20.3 vs 27.5%; p<0.001). Conclusions The present data show that female patients with severe AS have a distinct patient profile and are managed in a different way to males. Gender-based differences in the management of patients with severe AS need to be taken into account more systematically to improve outcomes, especially for women.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aortic valve stenosis; endovascular procedures; transcatheter aortic valve replacement

Incidence and outcome of peri-procedural transcatheter heart valve embolization and migration: the TRAVEL registry (TranscatheteR HeArt Valve EmboLization and Migration) - Kim, Won Keun; Schäfer, Ulrich; Tchetche, Didier; Nef, Holger; Avanzas, Pablo; Rudolph, Tanja; Scholtz, Smita; Barbanti, Marco; Kempfert, Jörg; Mangieri, Antonio; Lauten, Alexander; Frerker, Christian; et al. (European Heart Journal, 2019)
AIMS: Peri-procedural transcatheter valve embolization and migration (TVEM) is a rare but potentially devastating complication of transcatheter aortic valve implantation (TAVI). We sought to assess the incidence, causes, and outcome of TVEM in a large multicentre cohort. METHODS AND RESULTS: We recorded cases of peri-procedural TVEM in patients undergoing TAVI between January 2010 and December 2017 from 26 international sites. Peri-procedural TVEM occurred in 273/29 636 (0.92%) TAVI cases (age 80.8 ± 7.3 years; 53.8% female), of which 217 were to the ascending aorta and 56 to the left ventricle. The use of self-expanding or first-generation prostheses and presence of a bicuspid aortic valve were independent predictors of TVEM. Bail-out measures included repositioning attempts using snares or miscellaneous tools (41.0%), multiple valve implantations (83.2%), and conversion to surgery (19.0%). Using 1:4-propensity matching, we identified a cohort of 235 patients with TVEM (TVEMPS) and 932 patients without TVEM (non-TVEMPS). In the matched cohort, all-cause mortality was higher in TVEMPS than in non-TVEMPS at 30 days (18.6% vs. 4.9%; P < 0.001) and after 1 year (30.5% vs. 16.6%; P < 0.001). Major stroke was more frequent in TVEMPS at 30 days (10.6% vs. 2.8%; P < 0.001), but not at 1 year (4.6% vs. 1.9%; P = 0.17). The need for emergent cardiopulmonary support, major stroke at 30 days, and acute kidney injury Stages 2 and 3 increased the risk of 1-year mortality, whereas a better renal function at baseline was protective. CONCLUSION: Transcatheter valve embolization and migration occurred in approximately 1% and was associated with increased morbidity and mortality.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Aortic stenosis; Conversion; Embolization; Migration; Prosthesis; TAVR; Valve-in-valve

Incidental finding of a giant asymptomatic right atrial tumor - Strecker, Thomas; Agaimy, Abbas; Zelzer, Peter; Weyand, Michael; Wachter, David Lukas (International Journal of Clinical and Experimental Pathology, 2014)
Primary cardiac tumors are very rare, atrial myxoma being the most common benign tumor of the heart. They may present with a great variety of incidental asymptomatic masses to severe life-threatening cardiovascular complications necessitating emergency surgery. Here we report the diagnostic evaluation and successful surgical resection of such a giant cardiac tumor which was found on a routine medical check-up in a 62-year-old patient. Histology confirmed diagnosis of unusually huge myxoma. This article demonstrates it's necessary to include cardiac tumors in the differential diagnosis of subtle and non-specific cardiothoracic symptoms.
EVALuna2:6611

Incidental Finding of Strut Malapposition Is a Predictor of Late and Very Late Thrombosis in Coronary Bioresorbable Scaffolds - Boeder, Niklas F.; Weissner, Melissa; Blachutzik, Florian; Ullrich, Helen; Anadol, Remzi; Tröbs, Monique; Muenzel, Thomas; Hamm, Christian W.; Dijkstra, Jouke; Achenbach, Stephan; Nef, Holger M.; Gori, Tommaso (Journal of Clinical Medicine, 2019)
Malapposition is a common finding in stent and scaffold thrombosis (ScT). Evidence from studies with prospective follow-up, however, is scarce. We hypothesized that incidental observations of strut malapposition might be predictive of late ScT during subsequent follow-up. One hundred ninety-seven patients were enrolled in a multicentre registry with prospective follow-up. Optical coherence tomography (OCT), performed in an elective setting, was available in all at 353 (0-376) days after bioresorbable scaffold (BRS) implantation. Forty-four patients showed evidence of malapposition that was deemed not worthy of intervention. Malapposition was not associated with any clinical or procedural parameter except for a higher implantation pressure (p = 0.0008). OCT revealed that malapposition was associated with larger vessel size, less eccentricity (all p < 0.01), and a tendency for more uncovered struts (p = 0.06). Late or very late ScT was recorded in seven of these patients 293 (38-579) days after OCT. OCT-diagnosed malapposition was a predictor of late and very late scaffold thrombosis (p < 0.001) that was independent of the timing of diagnosis. We provide evidence that an incidental finding of malappositionregardless of the timing of diagnosis of the malappositionduring an elective exam is a predictor of late and very late ScT. Our data provide a rationale to consider prolonged dual antiplatelet therapy if strut malapposition is observed.
CRIS-Team WoS Importer:2019-06-25

Incidental papillary fibroelastoma of the tricuspid valve - Strecker, Thomas; Scheuermann, Sabine; Nooh, Ehab; Weyand, Michael; Agaimy, Abbas (Journal of Cardiothoracic Surgery, 2014)
Primary cardiac tumors are very rare, papillary fibroelastoma (PFE) being the second most common benign tumor of the heart in previous series. However, as a consequence of increased imaging examinations, incidental PFE may represent the most common cardiac tumor. Their clinical presentation varies from incidental asymptomatic masses to severe life-threatening cardiovascular complications necessitating emergency surgery. Here we report the diagnostic evaluation and successful surgical resection of such a cardiac tumor in a 67-year-old woman. Histology confirmed diagnosis of a papillary fibroelastoma. This report demonstrates it's necessary to include cardiac tumors in the differential diagnosis of subtle and non-specific cardiothoracic symptoms.
EVALuna2:6684

Increased long-term mortality in women with high left ventricular ejection fraction: data from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) long-term registry - Gebhard, Catherine; Maredziak, Monika; Messerli, Michael; Buechel, Ronny R.; Lin, Fay; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Bax, Jeroen J.; Berman, Daniel S.; Budoff, Matthew J.; et al. (European Heart Journal - Cardiovascular Imaging, 2020)
AIMS: There are significant sex-specific differences in left ventricular ejection fraction (LVEF), with a higher LVEF being observed in women. We sought to assess the clinical relevance of an increased LVEF in women and men. METHODS AND RESULTS: A total of 4632 patients from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry (44.8% women; mean age 58.7 ± 13.2 years in men and 59.5 ± 13.3 years in women, P = 0.05), in whom LVEF was measured by cardiac computed tomography, were categorized according to LVEF (low <55%, normal 55-65%, and high >65%). The prevalence of high LVEF was similar in both sexes (33.5% in women and 32.5% in men, P = 0.46). After 6 years of follow-up, no difference in mortality was observed in patients with high LVEF in the overall cohort (P = 0.41). When data were stratified by sex, women with high LVEF died more often from any cause as compared to women with normal LVEF (8.6% vs. 7.1%, log rank P = 0.032), while an opposite trend was observed in men (5.8% vs. 6.8% in normal LVEF, log rank P = 0.89). Accordingly, a first order interaction term of male sex and high LVEF was significant (hazard ratios 0.63, 95% confidence intervals 0.41-0.98, P = 0.043) in a Cox regression model of all-cause mortality adjusted for age, cardiovascular risk factors, and severity of coronary artery disease (CAD). CONCLUSION: Increased LVEF is highly prevalent in patients referred for evaluation of CAD and is associated with an increased risk of death in women, but not in men. Differentiating between normal and hyperdynamic left ventricles might improve risk stratification in women with CAD. CLINICAL TRIAL REGISTRATION: https://clinicaltrials.gov/ct2/show/NCT01443637.
CRIS-Team Scopus Importer:2020-03-31
Keywords: cardiovascular; coronary computed tomography angiography; gender; left ventricular ejection fraction; women

Increased prolactin in acute coronary syndromes as putative co-activator of ADP-stimulated P-selectin expression - Klinghammer, Lutz; et al. (Hormone and Metabolic Research, 2006)
Keywords: Angina pectoris; Coronary artery disease; Acute myocardial infarction; Platelets; Hormones; Leptin

Increased risk for vascular complications due to GP IIb/IIIa-antagonists in patients with cardiogenic shock supported by intraaortic balloon pump (IABP) - Röther, Jens; Tröbs, Monique; Schuhbäck, Annika; Ludwig, Josef; Achenbach, Stephan; Schlundt, Christian (Clinical Trials and Regulatory Science in Cardiology, 2015)
Background IABP is routinely used to support coronary blood flow and systemic circulation in patients with cardiogenic shock. Our aim was to explore the incidence of vascular complications associated with the use of IABP in this scenario and their influence on mortality. Methods Therefor we analysed 204 consecutive patients between 2002 and 2013 treated with IAPB in cardiogenic shock for vascular complications and mortality within 30 days after implantation of IAPB. Primary endpoints were severe bleeding (TIMI-definition: intracranial bleeding, loss of haemoglobin (Hb) > 5 g/dl or haematocrit (PCV) > 15%), vascular complications with therapeutic consequence (venous thrombosis, arterial embolism) and stroke. Results 80 (39%) patients died within 30 days after implantation of IABP. In 42 (21%) patients, vascular complications occurred: severe bleeding was present in 26 patients (62% of all complications), 13 (31%) patients suffered from venous thrombosis or arterial embolism and 3 (7%) patients from stroke. 25% of the patients who died had a vascular complication. The rate in patients who overcame cardiogenic shock was 17.7% (p = 0.22). Multivariate analyses showed treatment with Glycoprotein (GP) IIb/IIIa- inhibitors to be an independent risk factor for the occurrence of vascular complications (p = 0.04). Conclusion Vascular events with the use of IABP are common but in our study, not significantly associated with a higher mortality. Treatment with GP IIb/IIIa-antagonists is associated with a higher risk of vascular events.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiogenic shock; GP IIb/IIIa-antagonists; IABP; Vascular complications

Incremental prognostic utility of coronary CT angiography for asymptomatic patients based upon extent and severity of coronary artery calcium: results from the COronary CT Angiography EvaluatioN For Clinical Outcomes InteRnational Multicenter (CONFIRM) st - Cho, Iksung; Chang, Hyuk-Jae; Hartaigh, Briaino O.; Shin, Sanghoon; Sung, Ji Min; Lin, Fay Y.; Achenbach, Stephan; Heo, Ran; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracyq.; Al-Mallah, Mouaz H.; et al. (European Heart Journal, 2015)
Prior evidence observed no predictive utility of coronary CT angiography (CCTA) over the coronary artery calcium score (CACS) and the Framingham risk score (FRS), among asymptomatic individuals. Whether the prognostic value of CCTA differs for asymptomatic patients, when stratified by CACS severity, remains unknown.From a 12-centre, 6-country observational registry, 3217 asymptomatic individuals without known coronary artery disease (CAD) underwent CACS and CCTA. Individuals were categorized by CACS as: 0-10, 11-100, 101-400, 401-1000, >1000. For CCTA analysis, the number of obstructive vessels-as defined by the per-patient presence of a >=50% luminal stenosis-was used to grade the extent and severity of CAD. The incremental prognostic value of CCTA over and above FRS was measured by the likelihood ratio (LR) ?(2), C-statistic, and continuous net reclassification improvement (NRI) for prediction, discrimination, and reclassification of all-cause mortality and non-fatal myocardial infarction. During a median follow-up of 24 months (25th-75th percentile, 17-30 months), there were 58 composite end-points. The incremental value of CCTA over FRS was demonstrated in individuals with CACS >100 (LR?(2), 25.34; increment in C-statistic, 0.24; NRI, 0.62, all P < 0.001), but not among those with CACS <=100 (all P > 0.05). For subgroups with CACS >100, the utility of CCTA for predicting the study end-point was evident among individuals whose CACS ranged from 101 to 400; the observed predictive benefit attenuated with increasing CACS.Coronary CT angiography provides incremental prognostic utility for prediction of mortality and non-fatal myocardial infarction for asymptomatic individuals with moderately high CACS, but not for lower or higher CACS.
EVALuna2:12056

Incremental prognostic value of coronary computed tomographic angiography over coronary artery calcium score for risk prediction of major adverse cardiac events in asymptomatic diabetic individuals - Min, James K.; Labounty, Troy M.; Gomez, Millie J.; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor; Chinnaiyan, Kavitha M.; Chowk, Benjamin; et al. (Atherosclerosis, 2014)
Coronary artery disease (CAD) diagnosis by coronary computed tomographic angiography (CCTA) is useful for identification of symptomatic diabetic individuals at heightened risk for death. Whether CCTA-detected CAD enables improved risk assessment of asymptomatic diabetic individuals beyond clinical risk factors and coronary artery calcium scoring (CACS) remains unexplored.From a prospective 12-center international registry of 27,125 individuals undergoing CCTA, we identified 400 asymptomatic diabetic individuals without known CAD. Coronary stenosis by CCTA was graded as 0%, 1-49%, 50-69%, and >=70%. CAD was judged on a per-patient, per-vessel and per-segment basis as maximal stenosis severity, number of vessels with >=50% stenosis, and coronary segments weighted for stenosis severity (segment stenosis score), respectively. We assessed major adverse cardiovascular events (MACE) - inclusive of mortality, nonfatal myocardial infarction (MI), and late target vessel revascularization >=90 days (REV) - and evaluated the incremental utility of CCTA for risk prediction, discrimination and reclassification.Mean age was 60.4 ± 9.9 years; 65.0% were male. At a mean follow-up 2.4 ± 1.1 years, 33 MACE occurred (13 deaths, 8 MI, 12 REV) [8.25%; annualized rate 3.4%]. By univariate analysis, per-patient maximal stenosis [hazards ratio (HR) 2.24 per stenosis grade, 95% confidence interval (CI) 1.61-3.10, p < 0.001], increasing numbers of obstructive vessels (HR 2.30 per vessel, 95% CI 1.75-3.03, p < 0.001) and segment stenosis score (HR 1.14 per segment, 95% CI 1.09-1.19, p < 0.001) were associated with increased MACE. After adjustment for CAD risk factors and CACS, maximal stenosis (HR 1.80 per grade, 95% CI 1.18-2.75, p = 0.006), number of obstructive vessels (HR 1.85 per vessel, 95% CI 1.29-2.65, p < 0.001) and segment stenosis score (HR 1.11 per segment, 95% CI 1.05-1.18, p < 0.001) were associated with increased risk of MACE. Beyond age, gender and CACS (C-index 0.64), CCTA improved discrimination by maximal stenosis, number of obstructive vessels and segment stenosis score (C-index 0.77, 0.77 and 0.78, respectively). Similarly, CCTA findings improved risk reclassification by per-patient maximal stenosis [integrated discrimination improvement (IDI) index 0.03, p = 0.03] and number of obstructive vessels (IDI index 0.06, p = 0.002), and by trend for segment stenosis score (IDI 0.03, p = 0.06).For asymptomatic diabetic individuals, CCTA measures of CAD severity confer incremental risk prediction, discrimination and reclassification on a per-patient, per-vessel and per-segment basis.
EVALuna2:11987

Incremental prognostic value of coronary computed tomography angiography over coronary calcium scoring for major adverse cardiac events in elderly asymptomatic individuals - Han, Donghee; Hartaigh, Briain O.; Gransar, Heidi; Lee, Ji Hyun; Rizvi, Asim; Baskaran, Lohendran; Schulman-Marcus, Joshua; Dunning, Allison; Achenbach, Stephan; Al-Mallah, Mouaz H.; Berman, Daniel S.; Budoff, Matthew J.; et al. (European Heart Journal - Cardiovascular Imaging, 2018)
Aims: Coronary computed tomography angiography (CCTA) and coronary artery calcium score (CACS) have prognostic value for coronary artery disease (CAD) events beyond traditional risk assessment. Age is a risk factor with very high weight and little is known regarding the incremental value of CCTA over CAC for predicting cardiac events in older adults. Methods and results: Of 27 125 individuals undergoing CCTA, a total of 3145 asymptomatic adults were identified. This study sample was categorized according to tertiles of age (cut-off points: 52 and 62 years). CAD severity was classified as 0, 1-49, and ≥50% maximal stenosis in CCTA, and further categorized according to number of vessels ≥50% stenosis. The Framingham 10-year risk score (FRS) and CACS were employed as major covariates. Major adverse cardiovascular events (MACE) were defined as a composite of all-cause death or non-fatal MI. During a median follow-up of 26 months (interquartile range: 18-41 months), 59 (1.9%) MACE occurred. For patients in the top age tertile, CCTA improved discrimination beyond a model included FRS and CACS (C-statistic: 0.75 vs. 0.70, P-value = 0.015). Likewise, the addition of CCTA improved category-free net reclassification (cNRI) of MACE in patients within the highest age tertile (e.g. cNRI = 0.75; proportion of events/non-events reclassified were 50 and 25%, respectively; P-value <0.05, all). CCTA displayed no incremental benefit beyond FRS and CACS for prediction of MACE in the lower age tertiles. Conclusion: CCTA provides added prognostic value beyond cardiac risk factors and CACS for the prediction of MACE in asymptomatic older adults.
EVALuna2:35990

Independent predictors of major cardiovascular events as quantitatively assessed by coronary CT-angiography: a long-term follow-up analysis - Bittner, Daniel O.; Roesner, C.; Kilian, Tobias; Göller, Markus; Dey, D.; Raaz-Schrauder, Dorette; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Indications, procedural parameters, complications and consequences of fractional flow reserve measurements in a multicenter cohort - Tröbs, Monique; Gaede, L.; Feyrer, J.; Nazli, B.; Moellmann, H.; Giesler, T.; Rittger, H.; Pauschinger, M.; Rudolph, T.; Moshage, W.; Brueck, M.; Achenbach, Stephan; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Individual Lesion-Level Meta-Analysis Comparing Various Doses of Intracoronary Bolus Injection of Adenosine With Intravenous Administration of Adenosine for Fractional Flow Reserve Assessment - Wijntjens, Gilbert W.M.; van Uffelen, Ellen L.; Echavarría-Pinto, Mauro; Casadonte, Lorena; Stegehuis, Valérie E.; Murai, Tadashi; Marques, Koen M.J.; Yoon, Myeong Ho; Tahk, Seung Jea; Casella, Gianni; Leone, Antonio M.; López Palop, Ramón; et al. (Circulation: Cardiovascular Interventions, 2020)
BACKGROUND: Intravenous infusion of adenosine is considered standard practice for fractional flow reserve (FFR) assessment but is associated with adverse side-effects and is time-consuming. Intracoronary bolus injection of adenosine is better tolerated by patients, cheaper, and less time-consuming. However, current literature remains fragmented and modestly sized regarding the equivalence of intracoronary versus intravenous adenosine. We aim to investigate the relationship between intracoronary adenosine and intravenous adenosine to determine FFR. METHODS: We performed a lesion-level meta-analysis to compare intracoronary adenosine with intravenous adenosine (140 µg/kg per minute) for FFR assessment. The search was conducted in accordance to the Preferred Reporting for Systematic Reviews and Meta-Analysis statement. Lesion-level data were obtained by contacting the respective authors or by digitization of scatterplots using custom-made software. Intracoronary adenosine dose was defined as; low: <40 µg, intermediate: 40 to 99 µg, and high: ≥100 µg. RESULTS: We collected 1972 FFR measurements (1413 lesions) comparing intracoronary with intravenous adenosine from 16 studies. There was a strong correlation (correlation coefficient =0.915; P<0.001) between intracoronary-FFR and intravenous-FFR. Mean FFR was 0.81±0.11 for intracoronary adenosine and 0.81±0.11 for intravenous adenosine (P<0.001). We documented a nonclinically relevant mean difference of 0.006 (limits of agreement: -0.066 to 0.078) between the methods. When stratified by the intracoronary adenosine dose, mean differences between intracoronary and intravenous-FFR amounted to 0.004, 0.011, or 0.000 FFR units for low-dose, intermediate-dose, and high-dose intracoronary adenosine, respectively. CONCLUSIONS: The present study documents clinically irrelevant differences in FFR values obtained with intracoronary versus intravenous adenosine. Intracoronary adenosine hence confers a practical and patient-friendly alternative for intravenous adenosine for FFR assessment.
CRIS-Team Scopus Importer:2020-01-07
Keywords: adenosine; hyperemia; meta-analysis; software; vasodilatation

Influence of Cardiac MR Imaging on DNA Double-Strand Breaks in Human Blood Lymphocytes - Brand, Michael; Ellmann, Stephan; Sommer, Matthias; May, Matthias; Eller, Achim; Wüst, Wolfgang; Engert, Christina; Achenbach, Stephan; Kuefner, Michael A.; Bäuerle, Tobias; Lell, Michael; Uder, Michael (Radiology, 2015)
To evaluate the ability of magnetic resonance (MR) imaging to induce deoxyribonucleic acid (DNA) damage in patients who underwent cardiac MR imaging in daily routine by using ?-H2AX immunofluorescence microscopy.This study complies with the Declaration of Helsinki and was performed according to local ethics committee approval. Informed patient consent was obtained. Blood samples from 45 patients (13 women, 32 men; mean age, 50.3 years [age range, 20-89 years]) were obtained before and after contrast agent-enhanced cardiac MR imaging. MR imaging-induced double-strand breaks (DSBs) were quantified in isolated blood lymphocytes by using immunofluorescence microscopy after staining the phosphorylated histone variant ?-H2AX. Twenty-nine patients were examined with a myocarditis protocol (group A), 10 patients with a stress-testing protocol (group B), and six patients with flow measurements and angiography (group C). Paired t test was performed to compare excess foci before and after MR imaging.The mean baseline DSB level before MR imaging and 5 minutes after MR imaging was, respectively, 0.116 DSB per cell ± 0.019 (standard deviation) and 0.117 DSB per cell ± 0.019 (P = .71). There was also no significant difference in DSBs in these subgroups (group A: DSB per cell before and after MR imaging, respectively, 0.114 and 0.114, P = .91; group B: DSB per cell before and after MR imaging, respectively, 0.123 and 0.124, P = .78; group C: DSB per cell before and after MR imaging, respectively, 0.114 and 0.115, P = .36).By using ?-H2AX immunofluorescence microscopy, no DNA DSBs were detected after cardiac MR imaging.
EVALuna2:12028

Influence of Cardiovascular Risk Factors on the Prevalence of Coronary Atherosclerosis in Patients with Angiographically Normal Coronary Arteries - Bittner, Daniel O.; Klinghammer, Lutz; Schmid, Jasmin; Layritz, Christian; Hoffmann, Udo; Achenbach, Stephan; Pflederer, Tobias; Marwan, Mohamed (Academic Radiology, 2017)
RATIONALE AND OBJECTIVES: Cardiovascular (CV) disease is predominately influenced by CV risk factors and coronary computed tomography angiography (CTA) is capable of detecting early-stage coronary artery disease. We sought to determine the influence of CV risk factors on the prevalence of nonobstructive atherosclerosis in patients with normal-appearing coronary arteries in invasive coronary angiography (ICA). MATERIALS AND METHODS: In this retrospective analysis, we included 60 consecutive symptomatic patients, having undergone ICA and coronary CTA. Coronary dual source CTA was performed using electrocardiogram-triggered retrospective gated image acquisition at 40%-70% of RR interval (tube voltage 100-120 kV, tube current time product 320-440 mAs, 60 mL contrast, and flow rate 6 mL/s). RESULTS: Out of 60 patients (32 men, mean age 61 ± 11 years) with a normal coronary artery appearance in ICA, 45 (75%) patients showed atherosclerotic plaque in CTA. Plaque was present in 14 of 60 (23%) left main, 41 of 60 (68%) left anterior descending, 21 of 60 (35%) circumflex coronary arteries, and 24 of 60 (40%) right coronary arteries. More than 15% of all coronary artery segments showed detectable plaques. Interobserver agreement ranged from good to very good on a per-patient, per-vessel, and per-segment level. Patients with presence of plaque were significantly older (P = 0.005) and showed higher incidence of arterial hypertension (P = 0.019) as compared to individuals without coronary plaque in dual source computed tomography. CONCLUSIONS: The prevalence of coronary atherosclerosis by CTA is substantial in symptomatic patients with normal invasive coronary angiogram. Hypertension and older age significantly influence the prevalence of atherosclerotic plaque and highlight the importance of risk-modifying therapy.
EVALuna:33640

Influence of Coronary Calcification on the Diagnostic Performance of CT Angiography Derived FFR in Coronary Artery Disease: A Substudy of the NXT Trial - Norgaard, Bjarne L.; Gaur, Sara; Leipsic, Jonathon; Ito, Hiroshi; Miyoshi, Toni; Park, Seung-Jung; Zvaigzne, Ligita; Tzemos, Nikolaos; Jensen, Jesper M.; Hansson, Nicolaj; Ko, Brian; Bezerra, Hiram; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
The goal of this study was to examine the diagnostic performance of noninvasive fractional flow reserve (FFR) derived from coronary computed tomography angiography (CTA) (FFRCT) in relation to coronary calcification severity.FFRCT has shown promising results in identifying lesion-specific ischemia. The extent to which the severity of coronary calcification affects the diagnostic performance of FFRCT is not known.Coronary calcification was assessed by using the Agatston score (AS) in 214 patients suspected of having coronary artery disease who underwent coronary CTA, FFRCT, and FFR (FFR examination was performed in 333 vessels). The diagnostic performance of FFRCT (<=0.80) in identifying vessel-specific ischemia (FFR <=0.80) was investigated across AS quartiles (Q1 to Q4) and for discrimination of ischemia in patients and vessels with a low-mid AS (Q1 to Q3) versus a high AS (Q4). Coronary CTA stenosis was defined as lumen reduction >50%.Mean ± SD per-patient and per-vessel AS were 302 ± 468 (range 0 to 3,599) and 95 ± 172 (range 0 to 1,703), respectively. There was no statistical difference in diagnostic accuracy, sensitivity, or specificity of FFRCT across AS quartiles. Discrimination of ischemia by FFRCT was high in patients with a high AS (416 to 3,599) and a low-mid AS (0 to 415), with no difference in area under the receiver-operating characteristic curve (AUC) (0.86 [95% confidence interval (CI): 0.76 to 0.96] vs. 0.92 [95% CI: 0.88 to 0.96]) (p = 0.45). Similarly, discrimination of ischemia by FFRCT was high in vessels with a high AS (121 to 1,703) and a low-mid AS (0 to 120) (AUC: 0.91 [95% CI: 0.85 to 0.97] vs. 0.95 [95% CI: 0.91 to 0.98]; p = 0.65). Diagnostic accuracy and specificity of FFRCT were significantly higher than for stenosis assessment in each AS quartile at the per-patient (p < 0.001) and per-vessel (p < 0.05) level with similar sensitivity. In vessels with a high AS, FFRCT exhibited improved discrimination of ischemia compared with coronary CTA alone (AUC: 0.91 vs. 0.71; p = 0.004), whereas on a per-patient level, the difference did not reach statistical significance (AUC: 0.86 vs. 0.72; p = 0.09).FFRCT provided high and superior diagnostic performance compared with coronary CTA interpretation alone in patients and vessels with a high AS.
EVALuna2:12067

Influence of gender on coronary atherosclerosis and inflammatory biomarker profile: a CT angiographic study - Bittner, Daniel O.; Rösner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, D.; Kilian, Tobias; Achenbach, Susanne; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Influence of Heart Rate on Image Quality and Radiation Dose Exposure in Coronary CT Angiography - Stocker, Thomas J.; Leipsic, Jonathon; Chen, Marcus Y.; Achenbach, Stephan; Knuuti, Juhani; Newby, David; Hausleiter, Joerg (Radiology, 2021)
CRIS-Team WoS Importer:2021-09-03

Influence of image reconstruction parameters on diagnostic performance of on-site CT-derived FFR: Comparison with invasively measured FFR - Ammon, Fabian; Röther, Jens; Hell, M.; Schuhbaeck, A.; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Influence of irregular heart rhythm on radiation exposure, image quality and diagnostic impact of cardiac computed tomography angiography in 4,339 patients. Data from the German Cardiac Computed Tomography Registry - Korosoglou, Grigorios; Giusca, Sorin; Schmermund, Axel; Schneider, Steffen; Bruder, Oliver; Hausleiter, Joerg; Schroeder, Stephen; Leber, Alexander; Limbourg, Tobias; Gitsioudis, Gitsios; Rixe, Johannes; Zahn, Ralf; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Coronary computed tomography angiography (coronary CTA) provides non-invasive evaluation of the coronary arteries with high precision for the detection of significant coronary artery disease (CAD). AIM: To investigate whether irregular heart rhythm including atrial fibrillation and premature beats during data acquisition influences (i) radiation and contrast media exposure, (ii) number of non-evaluable coronary segments and (iii) diagnostic impact of coronary CTA. METHODS: Twelve tertiary care centers with ≥64 slice CT scanners and ≥5 years of experience with cardiovascular imaging participated in this registry. Between 2009 and 2014, 4339 examinations were analysed in patients who underwent clinically indicated coronary CTA for suspected CAD. Clinical and epidemiologic data were gathered from all patients. In addition, clinical presentation, heart rate and rhythm during the scan, Agatston score, radiation and contrast media exposure and the diagnostic impact of coronary CTA were systematically analysed. RESULTS: Of 4339 patients in total, 260 (6.0%) had irregular heart rhythm, whereas the remaining 4079 (94.0%) had stable sinus rhythm. Patients with irregular heart rhythm were older (63.2 ± 12.5yrs versus 58.6 ± 11.4yrs. p < 0.001), exhibited a higher rate of pathologic stress tests before CTA (37.1% versus 26.1%, p < 0.01) and higher heart rates during CTA compared to those with sinus rhythm (62.5 ± 11.6bpm versus 58.9 ± 8.5bpm, p < 0.001). Both contrast media exposure and radiation exposure were significantly higher in patients with irregular heart rhythm (90 mL (95%CI = 80-110 mL) versus 80 mL (95%CI = 70-90 mL) and 6.2 mSv (95%CI = 2.5-11.7) versus 3.3 mSv (95%CI = 1.7-6.9), p < 0.001 for both). Coronary CTA excluded significant CAD less frequently in patients with irregular heart rhythm (32.9% versus 44.8%, p < 0.001). This was attributed to the higher rate of examinations with at least one non-diagnostic coronary segment in patients with irregular heart rhythm (10.8% versus 4.6%, p < 0.001). Subsequent invasive angiography could be avoided in 47.2% of patients with irregular heart rhythm compared to 52.9% of patients with sinus rhythm (p = NS), whereas downstream stress testing was recommended in 3.2% of patients with irregular heart rhythm versus 4.0% of patients with sinus rhythm (p = NS). CONCLUSION: A significant number of patients scheduled for coronary CTA have irregular heart rhythm in a real-world clinical setting. In such patients, heart rate during coronary CTA is higher, possibly resulting in (i) higher radiation and contrast agent exposure and (ii) more frequent coronary CTA examinations with at least one non-diagnostic coronary artery segment. However, this does not seem to lead to increased downstream stress testing or subsequent invasive procedures.
EVALuna2:33590

Influence of irregular heart rhythm on radiation exposure, image quality and diagnostic impact of cardiac computed tomography angiography in 4,767 patients - Korosoglou, G.; Schmermund, A.; Schneider, S.; Giusca, S.; Gitsioudis, Gitsios; Bruders, O.; Hausleiter, J.; Schroeder, S.; Leber, A.; Rixe, J.; Katus, H. A.; Achenbach, Stephan; et al. (2017)
EVALuna2:36026

Influence of lesion location on the accuracy of CT derived FFR: head-to-head comparison with invasive FFR - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan; Ammon, Fabian; Ferstl, Paul; Göller, Markus; Bittner, Daniel O.; Uehlein, Sabrina; Bal, Zeynep; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Influence of reconstruction kernels on the accuracy of CT-derived fractional flow reserve - Ammon, Fabian; Moshage, Maximilian; Smolka, Silvia; Göller, Markus; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (European Radiology, 2021)
Objectives: We evaluated the influence of image reconstruction kernels on the diagnostic accuracy of CT-derived fractional flow reserve (FFRCT) compared to invasive FFR in patients with coronary artery disease. Methods: Sixty-nine patients, in whom coronary CT angiography was performed and who were further referred for invasive coronary angiography with FFR measurement via pressure wire, were retrospectively included. CT data sets were acquired using a third-generation dual-source CT system and rendered with medium smooth (Bv40) and sharp (Bv49) reconstruction kernels. FFRCT was calculated on-site using prototype software. Coronary stenoses with invasive FFR ≤ 0.80 were classified as significant. Agreement between FFRCT and invasive FFR was determined for both reconstruction kernels. Results: One hundred analyzed vessels in 69 patients were included. Twenty-five vessels were significantly stenosed according to invasive FFR. Using a sharp reconstruction kernel for FFRCT resulted in a significantly higher correlation with invasive FFR (r = 0.74, p < 0.01 vs. r = 0.58, p < 0.01; p = 0.04) and a higher AUC in ROC curve analysis to correctly identify/exclude significant stenosis (AUC = 0.92 vs. AUC = 0.82 for sharp vs. medium smooth kernel, respectively, p = 0.02). A FFRCT value of ≤ 0.8 using a sharp reconstruction kernel showed a sensitivity of 88% and a specificity of 92% for detecting ischemia-causing lesions, resulting in a diagnostic accuracy of 91%. The medium smooth reconstruction kernel performed worse (sensitivity 60%, specificity 89%, accuracy 82%). Conclusion: Compared to invasively measured FFR, FFRCT using a sharp image reconstruction kernel shows higher diagnostic accuracy for detecting lesions causing ischemia, potentially altering decision-making in a clinical setting. Key Points: • Image reconstruction parameters influence the diagnostic accuracy of simulated fractional flow reserve derived from coronary computed tomography angiography. • Using a sharp kernel image reconstruction algorithm delivers higher diagnostic accuracy compared to medium smooth kernel image reconstruction (gold standard invasive fractional flow reserve).
CRIS-Team Scopus Importer:2021-11-12
Keywords: Computed tomography angiography; Coronary artery disease; Fractional flow reserve; myocardial; Image processing; computer-assisted

Influence of sex on results and consequences of coronary fractional flow reserve in clinical practice: results of a prospective large-scale multicenter registry - Tröbs, Monique; Marwan, Mohamed; Gaede, Luise; Moellmann, H.; Giesler, T.; Rittger, H.; Rudolph, T.; Pauschinger, M.; Moshage, W.; Brueck, M.; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Influence of symptom typicality for predicting MACE in patients without obstructive coronary artery disease: From the CONFIRM Registry (Coronary Computed Tomography Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry) - Lee, Ji Hyun; Han, Donghee; Hartaigh, Briain O.; Gransar, Heidi; Lu, Yao; Rizvi, Asim; Park, Mahn Won; Roudsari, Hadi Mirhedayati; Stuijfzand, Wijnand J.; Berman, Daniel S.; Callister, Tracy Q.; Delago, Augustin; et al. (Clinical Cardiology, 2018)
Our objective was to assess the prognostic value of symptom typicality in patients without obstructive coronary artery disease (CAD), determined by coronary computed tomographic angiography (CCTA). We identified 4215 patients without prior history of CAD and without obstructive CAD (<50% CCTA stenosis). CAD severity was categorized as nonobstructive (1%-49%) and none (0%). Based upon the Diamond-Forrester criteria for angina pectoris, symptom typicality was classified as asymptomatic, nonanginal, atypical, and typical. Multivariable Cox proportional hazards models were used to assess the risk of major adverse cardiac events (MACE), comprising all-cause mortality, myocardial infarction, unstable angina, and late revascularization, according to symptom typicality. Mean patient age was 57.0 ±12.0 years (54.9% male). During a median follow-up of 5.3 years (interquartile range, 4.6-5.9 years), MACE were reported in 312 (7.4%) patients. Among patients with nonobstructive CAD, there was an association between symptom typicality and MACE (P for interaction = 0.05), driven by increased risk of MACE among those with typical angina and nonobstructive CAD (hazard ratio: 1.62, 95% confidence interval: 1.06-2.48, P = 0.03). No consistent relationship was found between symptom typicality and MACE among patients without any CAD (hazard ratio: 0.73, 95% confidence interval: 0.34-1.57, P = 0.08). In the CONFIRM registry, patients who presented with concomitant typical angina and nonobstructive CAD had a higher rate of MACE than did asymptomatic patients with nonobstructive CAD. However, the presence of typical angina did not appear to portend worse prognosis in patients with no CAD.
EVALuna2:35996

Influence of the coronary calcium score on the ability to rule out coronary artery stenoses by coronary CT angiography in patients with suspected coronary artery disease - Schuhbaeck, Annika; Schmid, Jasmin; Zimmer, Thomas; Muschiol, Gerd; Hell, Michaela M.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
BACKGROUND: Recent guidelines for the workup of patients with chest pain and suspected coronary artery disease include coronary computed tomography angiography (CTA). However, its diagnostic value may be limited in patients with severe coronary calcification. OBJECTIVE: We investigated the relationship between the extent of coronary calcium and the ability of coronary CTA to rule out significant stenoses in a series of consecutive patients with suspected coronary artery disease. METHODS: 2614 consecutive patients with suspected coronary artery disease in whom coronary calcium scoring and coronary CTA had been performed by Dual Source CT were analyzed. The ability of coronary CTA to rule out coronary artery stenoses (fully evaluable coronary arteries and absence of any luminal stenosis >75%) was analyzed relative to the coronary calcium score. RESULTS: The median coronary calcium score was 12, with calcium present in 60.5% of all patients. Coronary CTA ruled out stenoses in 82% of patients, while in 18% of patients at least one stenosis was found or could not be excluded. The threshold above which coronary CTA permitted to rule out stenoses in less than 50% of patients was an "Agatston Score" of 287. This threshold was significantly lower for male patients (213 vs. 330), for patients with a heart rate >65 beats/min (157 vs. 317) and for patients with a body mass index ≥25 kg/m(2) (208 vs. 392). The evaluability of coronary arteries decreased with increasing amounts of calcium and differed significantly between heart rates ≤65 beats/min and >65 beats/min (p < 0.0001). CONCLUSION: In the largest patient series evaluated so far, we identified an "Agatston Score" of 287 to represent a threshold above which coronary CTA permits to rule out coronary artery stenoses in less than 50% of cases.
EVALuna2:33681

Influence of ultrasound operating parameters on ultrasound-induced thrombolysis in vitro - Klinghammer, Lutz; et al. (Ultrasound in Medicine and Biology, 2005)
Keywords: Cavitation; Operating parameters; Ultrasound thrombolysis

Initial experience with cinematic rendering for the visualization of extracardiac anatomy in complex congenital heart defects - Röschl, Florian; Purbojo, Ariawan; Rüffer, André; Cesnjevar, Robert; Dittrich, Sven; Glöckler, Martin (Interactive Cardiovascular and Thoracic Surgery, 2019)
OBJECTIVES: Detailed anatomical information is essential for planning of surgical therapy in patients with congenital heart disease. We wanted to determine whether cinematic rendering, the novel 3-dimensional visualization technique, could help paediatric cardiac surgeons achieve better preoperative visualization of the extracardiac anatomy in patients with complex congenital heart defects. Therefore, cinematic rendering was compared to the traditional volume rendering technique by means of a questionnaire with predefined criteria. METHODS: Picture sets from 20 infant patients (mean age = 17 days) were generated from computed tomography data with both the cinematic rendering and the volume rendering techniques. These were presented side by side in a digital high-resolution portfolio without labelling them. Three experienced paediatric cardiac surgeons were provided with these portfolios and a questionnaire. They were asked to evaluate the images individually in predefined categories on a 4-point Likert scale from 1 = 'fully acceptable' to 4 = 'unacceptable'. RESULTS: Cinematic rendering scored significantly better values on the Likert scale in 7 of 9 categories, namely 'spatial impression in general', 'depth perception', 'delineation of the atrial appendages/pulmonary veins/peripheral pulmonary arteries', 'assessability of the anterior interventricular sulcus' and 'assessability of the aortic arch branches'. CONCLUSIONS: Cinematic rendering is a valuable software tool, and our data suggest that it provides significantly better visualization than volume rendering. The surgeons appraised improved depth perception and delineation of structures adjacent to the heart as the most significant advantages.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cinematic rendering; Computed tomography; Congenital heart disease; Three-dimensional

Initial German experience with transapical implantation of a second-generation transcatheter heart valve for the treatment of aortic regurgitation - Seiffert, Moritz; Bader, Ralf; Kappert, Utz; Rastan, Ardawan; Krapf, Stephan; Bleiziffer, Sabine; Hofmann, Steffen; Kallenbach, Klaus; Conradi, Lenard; Schlingloff, Friederike; Wilbring, Manuel; Schafer, Ulrich; et al. (Jacc-Cardiovascular Interventions, 2014)
This analysis reports on the initial German multicenter experience with the JenaValve (JenaValve Technology GmbH, Munich, Germany) transcatheter heart valve for the treatment of pure aortic regurgitation.Experience with transcatheter aortic valve implantation (TAVI) for severe aortic regurgitation is limited due to the risk of insufficient anchoring of the valve stent within the noncalcified aortic annulus.Transapical TAVI with a JenaValve for the treatment of severe aortic regurgitation was performed in 31 patients (age 73.8 ± 9.1 years) in 9 German centers. All patients were considered high risk for surgery (logistic EuroSCORE [European System for Cardiac Operative Risk Evaluation] 23.6 ± 14.5%) according to a local heart team consensus. Procedural results and clinical outcomes up to 6 months were analyzed.Implantation was successful in 30 of 31 cases (aortic annulus diameter 24.7 ± 1.5 mm); transcatheter heart valve dislodgement necessitated valve-in-valve implantation in 1 patient. Post-procedural aortic regurgitation was none/trace in 28 of 31 and mild in 3 of 31 patients. During follow-up, 2 patients underwent valvular reinterventions (surgical aortic valve replacement for endocarditis, valve-in-valve implantation for increasing paravalvular regurgitation). All-cause mortality was 12.9% and 19.3% at 30 days and 6 months, respectively. In the remaining patients, a significant improvement in New York Heart Association class was observed and persisted up to 6 months after TAVI.Aortic regurgitation remains a challenging pathology for TAVI. After initial demonstration of feasibility, this multicenter study revealed the JenaValve transcatheter heart valve as a reasonable option in this subset of patients. However, a significant early noncardiac mortality related to the high-risk population emphasizes the need for careful patient selection.
EVALuna2:12061

Instantaneous P-and T-wave detection: Assessment of three ECG fiducial points detection algorithms - Leutheuser, Heike; Gradl, Stefan; Anneken, Lars; Lang, Nadine; Achenbach, Stephan; Eskofier, Björn; Arnold, Martin (13th International Conference on Wearable and Implantable Body Sensor Networks (BSN), 2016)

Integrated prediction of lesion-specific ischaemia from quantitative coronary CT angiography using machine learning: a multicentre study - Dey, Damini; Gaur, Sara; Ovrehus, Kristian A.; Slomka, Piotr J.; Betancur, Julian; Goeller, Markus; Hell, Michaela M.; Gransar, Heidi; Berman, Daniel S.; Achenbach, Stephan; Botker, Hans Erik; Jensen, Jesper Moller; et al. (European Radiology, 2018)
OBJECTIVES: We aimed to investigate if lesion-specific ischaemia by invasive fractional flow reserve (FFR) can be predicted by an integrated machine learning (ML) ischaemia risk score from quantitative plaque measures from coronary computed tomography angiography (CTA). METHODS: In a multicentre trial of 254 patients, CTA and invasive coronary angiography were performed, with FFR in 484 vessels. CTA data sets were analysed by semi-automated software to quantify stenosis and non-calcified (NCP), low-density NCP (LD-NCP, < 30 HU), calcified and total plaque volumes, contrast density difference (CDD, maximum difference in luminal attenuation per unit area) and plaque length. ML integration included automated feature selection and model building from quantitative CTA with a boosted ensemble algorithm, and tenfold stratified cross-validation. RESULTS: Eighty patients had ischaemia by FFR (FFR ≤ 0.80) in 100 vessels. Information gain for predicting ischaemia was highest for CDD (0.172), followed by LD-NCP (0.125), NCP (0.097), and total plaque volumes (0.092). ML exhibited higher area-under-the-curve (0.84) than individual CTA measures, including stenosis (0.76), LD-NCP volume (0.77), total plaque volume (0.74) and pre-test likelihood of coronary artery disease (CAD) (0.63); p < 0.006. CONCLUSIONS: Integrated ML ischaemia risk score improved the prediction of lesion-specific ischaemia by invasive FFR, over stenosis, plaque measures and pre-test likelihood of CAD. KEY POINTS: • Integrated ischaemia risk score improved prediction of ischaemia over quantitative plaque measures • Integrated ischaemia risk score showed higher prediction of ischaemia than standard approach • Contrast density difference had the highest information gain to identify lesion-specific ischaemia.
EVALuna2:35992

Interobserver variability of CT angiography for evaluation of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) - Schmidkonz, Christian; Marwan, M.; Klinghammer, Lutz; Mitschke, M.; Schuhbaeck, A.; Lell, Michael; Achenbach, Susanne; Pflederer, T.; Arnold, Martin (European Journal of Radiology, 2014)
Assessment of aortic annulus dimensions prior to transcatheter aortic valve implantation (TAVI) is crucial for accurate prosthesis sizing in order to avoid prosthesis-annulus-mismatch possibly resulting in complications like valve dislodgement, paravalvular regurgitation or annulus rupture. Contrast-enhanced multidetector computed tomography allows 3-dimensional assessment of aortic annulus dimensions. Only limited data exist about its interobserver variability.In 100 consecutive patients with symptomatic severe aortic stenosis (51 male, BMI 27±5kg/m(2), age 81±7 years, heart rate 72±15bpm, Logistic Euroscore 31±14%, STS-Score 7±4%), pre-interventional aortic annulus assessment was performed by dual source computed tomography (collimation 2×128×0.6mm, high pitch spiral data acquisition mode, 40-60ml contrast agents, radiation dose 3.5±0.9mSv). The following aortic annulus characteristics were determined by three independent observers: aortic annulus maximum, minimum and mean diameters (Dmax, Dmin, Dmean), eccentricity index (EI), effective aortic annulus diameter according to its circumference (Dcirc), effective aortic annulus diameter according to its area (Darea), distance from the aortic annulus plane to the left (LCA) and right coronary artery (RCA) ostia, maximum (DmaxAR) and minimum aortic root diameter (DminAR), maximum (DmaxSTJ) and minimum diameter of the sinotubular junction (DminSTJ). Subsequently, interobserver variabilities were assessed.Correlation between the three observers showed moderate to close agreement (between r=0.67 and r=0.97, all p<0.001). Mean differences (SE) between the three observers ranged from 0.07 (0.06)mm to 0.24 (0.07)mm for assessing the mean AA diameter (Dmean), from 0.28 (0.04)mm to 0.60 (0.06)mm for determining the effective AA diameter derived from the annulus area (Darea) and from 0.03 (0.07)mm to 0.07 (0.11)mm derived from the AA perimeter (Dcirc). For measurements of LCA and RCA distances to the AA level, mean interobserver differences (SE) ranged from 0.36 (0.07)mm to 0.76 (0.09)mm and from 0.15 (0.06)mm to 0.45 (0.11)mm.Computed tomography provides reproducible measurements of the aortic annulus and root geometry in patients scheduled for TAVI. The perimeter-derived aortic annulus diameter shows the lowest interobserver differences. Interobserver variabilities in prosthesis size recommendation were further reduced, if all three sizing methods were considered and stated as a "consensus result".
EVALuna2:11956

Interpretation of 'incidental' cardiovascular findings in standard chest CTs impact of evolving scanner technology on educational requirements - Schoenhagen, Paul; Ghoshhajra, Brian; Achenbach, Stephan; Abbara, Suhny (Journal of Cardiovascular Computed Tomography, 2016)
EVALuna2:33694

Interscan reproducibility of quantitative coronary plaque volume and composition from CT coronary angiography using an automated method - Schuhbaeck, Annika; Dey, Damini; Otaki, Yuka; Slomka, Piotr; Kral, Brian G.; Achenbach, Stephan; Berman, Daniel S.; Fishman, Elliott K.; Lai, Shenghan; Lai, Hong (European Radiology, 2014)
Quantitative measurements of coronary plaque volume may play a role in serial studies to determine disease progression or regression. Our aim was to evaluate the interscan reproducibility of quantitative measurements of coronary plaque volumes using a standardized automated method.Coronary dual source computed tomography angiography (CTA) was performed twice in 20 consecutive patients with known coronary artery disease within a maximum time difference of 100 days. The total plaque volume (TP), the volume of non-calcified plaque (NCP) and calcified plaque (CP) as well as the maximal remodelling index (RI) were determined using automated software.Mean TP volume was 382.3 ± 236.9 mm(3) for the first and 399.0 ± 247.3 mm(3) for the second examination (p = 0.47). There were also no significant differences for NCP volumes, CP volumes or RI. Interscan correlation of the plaque volumes was very good (Pearson's correlation coefficients: r = 0.92, r = 0.90 and r = 0.96 for TP, NCP and CP volumes, respectively).Automated software is a time-saving method that allows accurate assessment of coronary atherosclerotic plaque volumes in coronary CTA with high reproducibility. With this approach, serial studies appear to be possible.Reproducibility of coronary atherosclerotic plaque volume in coronary CTA is high. Using automated software facilitates quantitative measurements. Serial studies to determine progression or regression of coronary plaque are possible.
EVALuna2:11992

Interventional treatment and outcome in elderly patients with stable coronary artery disease. Results from the German ALKK registry - Rittger, Harald; Hochadel, M.; Behrens, S.; Hauptmann, K. E.; Zahn, R.; Mudra, H.; Brachmann, J.; Zeymer, U. (Herz, 2014)
The number of elderly and very elderly patients undergoing percutaneous coronary interventions (PCI) is increasing. We therefore analyzed data from the German ALKK registry (Arbeitsgemeinschaft Leitende Krankenhausärzte; Working Group of Hospital Cardiologists) to determine differences in procedural features, antithrombotic treatment, and in-hospital outcome in patients with coronary artery disease (CAD) according to age in a large series of patients.The present analysis was based on the data of 35,534 consecutive patients undergoing elective PCI who were enrolled in the ALKK registry. Of these 27,145 (76.4 %) were younger than 75 years, 7,645 (21.5 %) were aged between 75 and 84 years, and 744 (2.1 %) patients were older than 85 years. Mean age was 68.5 years (60.9-74.5 years), and 25,784 patients (72.6 %) were male. Overall intraprocedural events were very low (1.1 %) and there was no significant difference between the three age groups [< 75 years (1.1 %); 75-< 85 years (1.2 %); >= 85 years (0.5 %) (p = not significant)]. Rates of in-hospital death, stroke and transient ischemic attack (TIA), as well as the combined endpoint in-hospital major adverse cardiac and cerebrovascular events (MACCE) were also very low (0.6 % vs. 0.9 % vs. 0.9 %; p < 0.001) but significantly higher in elderly patients with no further increase in the very elderly patient group.We found no differences in this registry in intraprocedural complications during elective PCI between younger and elderly patients. Although in-hospital MACCE were somewhat higher in the elderly, the overall event rate was low and thus elderly patients should not be deprived from this therapy because of age alone.
EVALuna2:12017

Intranasal delivery of nanoparticles - Friedrich, Ralf P.; Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2022)
CRIS-Team WoS Importer:2022-01-14

Invasive hemodynamic characteristics of low gradient severe aortic stenosis despite preserved ejection fraction - Lauten, Juliane; Rost, Christian; Breithardt, Ole A.; Seligmann, Christian; Klinghammer, Lutz; Daniel, Werner; Flachskampf, Frank A. (Journal of the American College of Cardiology, 2013)
Objectives: The study sought to compare echocardiographic with invasive hemodynamic data in patients with "paradoxic" aortic stenosis and in patients with conventionally defined severe aortic stenosis. Background: Controversy exists whether low gradient severe aortic stenosis despite preserved ejection fraction ("paradoxic" aortic stenosis; aortic valve area <1 cm2, mean gradient <40 mm Hg, ejection fraction >50%), which has been mainly diagnosed by echocardiography (echo), may be largely due to mistakes in echocardiographic measurements. Methods: We compared echocardiographic and invasive hemodynamic data from 58 patients (43% male, mean age 77 ± 5 years) with "paradoxic" aortic stenosis. Data of 22 patients (45% male, mean age 73 ± 7 years) with conventionally defined severe aortic stenosis area (aortic valve area ≤1 cm2, mean gradient >40 mm Hg, ejection fraction ≥50%) were also analyzed. Results: In patients with "paradoxic" aortic stenosis, orifice area by echo (0.80 ± 0.15 cm2) and catheterization showed modest agreement, whether stroke volume was measured by oxymetry (0.69 ± 0.16 cm 2, bias 0.14 ± 0.17 cm2), or by thermodilution (0.85 ± 0.19 cm2, bias -0.03 ± 0.19 cm2). Mean systolic gradients were very similar (32 ± 7 mm Hg vs. 31 ± 6 mm Hg; bias -0.08 ± 7.8 mm Hg). In comparison, in patients with conventionally defined severe aortic stenosis, orifice area by echo was 0.72 ± 0.17 cm2 and by catheterization 0.51 ± 0.15 cm 2 (oxymetry) and 0.68 ± 0.21 cm2 (thermodilution), respectively, and mean systolic gradient 51 ± 10 mm Hg and 55 ± 8 mm Hg, respectively. Ejection fractions did not differ significantly in both groups. Ascending aortic diameter was significantly smaller in the "paradoxic" aortic stenosis group than in patients with conventionally defined severe aortic stenosis (28 ± 5 mm vs. 31 ± 5 mm), and energy loss index was significantly larger (0.51 ± 0.12 cm 2/m2 vs. 0.42 ± 0.09 cm2/m2, respectively). Heart rate and mean blood pressure during echo and catheterization were not significantly different. Conclusions: Occurrence of low gradient severe aortic stenosis despite preserved ejection fraction was confirmed by invasive hemodynamics and was not the result of a systematic bias in the echo calculation of aortic orifice area. © 2013 American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-07-10
Keywords: aortic stenosis; cardiac catherization; echocardiography

Investigation of wall shear stress in cardiovascular research and in clinical practice—from bench to bedside - Urschel, Katharina; Tauchi, Miyuki; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2021)
In the 1900s, researchers established animal models experimentally to induce atherosclerosis by feeding them with a cholesterol-rich diet. It is now accepted that high circulating cholesterol is one of the main causes of atherosclerosis; however, plaque localization cannot be explained solely by hyperlipidemia. A tremendous amount of studies has demonstrated that hemodynamic forces modify endothelial athero-susceptibility phenotypes. Endothelial cells possess mechanosensors on the apical surface to detect a blood stream-induced force on the vessel wall, known as “wall shear stress (WSS)”, and induce cellular and molecular responses. Investigations to elucidate the mechanisms of this process are on-going: on the one hand, hemodynamics in complex vessel systems have been described in detail, owing to the recent progress in imaging and computational techniques. On the other hand, investigations using unique in vitro chamber systems with various flow applications have enhanced the understanding of WSS-induced changes in endothelial cell function and the involvement of the glycocalyx, the apical surface layer of endothelial cells, in this process. In the clinical setting, attempts have been made to measure WSS and/or glycocalyx degradation non-invasively, for the purpose of their diagnostic utilization. An increasing body of evidence shows that WSS, as well as serum glycocalyx components, can serve as a predicting factor for atherosclerosis development and, most importantly, for the rupture of plaques in patients with high risk of coronary heart disease.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Atherosclerosis; Endothelial activation; Glycocalyx; Mechanotrans-duction; Plaque; Rupture; Wall shear stress

ISCHEMIA trial: Is coronary CT angiography the new gatekeeper? ISCHEMIA-Studie: Stellt die koronare CT-Angiographie künftig die Weichen? - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan (Radiologe, 2020)
Background: The ISCHEMIA trial systematically compared two major principles in the therapy of coronary artery disease (CAD): medical therapy versus revascularization in patients with a positive noninvasive test for myocardial ischemia. Specifically, it was designed to answer the question whether in patients with demonstrated ischemia, after ruling out left main stenosis by coronary computed tomography angiography (CTA), a routine interventional strategy in addition to optimal medical therapy would improve clinical outcome over an initial strategy of medical therapy alone. Conclusion: Overall, this hypothesis could not be confirmed. In several ways, the trial yields interesting information in the field of cardiac imaging. First, a positive stress test result was not associated with a prognostic benefit of revascularization. Second, even though the evaluation of coronary CTA was not part of the protocol, the good outcome achieved by using coronary CTA as a “gatekeeper” during randomization supports the potential of coronary CTA as a diagnostic tool—both first- and second-line—when CAD is suspected. However, the trial also raises new questions in the field of cardiac imaging which will need to be addressed in future studies.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Acute coronary syndromes; Coronary heart disease; Diagnostic imaging; Revascularisation; Stable coronary artery disease

Is metabolic syndrome predictive of prevalence, extent, and risk of coronary artery disease beyond its components? Results from the multinational coronary CT angiography evaluation for clinical outcome: an international multicenter registry (CONFIRM) - Ahmadi, Amir; Leipsic, Jonathon; Feuchtner, Gudrun; Gransar, Heidi; Kalra, Dan; Heo, Ran; Achenbach, Stephan; Andreini, Daniele; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew; Cademartiri, Filippo; et al. (PLoS ONE, 2015)
Although metabolic syndrome is associated with increased risk of cardiovascular disease and events, its added prognostic value beyond its components remains unknown. This study compared the prevalence, severity of coronary artery disease (CAD), and prognosis of patients with metabolic syndrome to those with individual metabolic syndrome components. The study cohort consisted of 27125 consecutive individuals who underwent >= 64-detector row coronary CT angiography (CCTA) at 12 centers from 2003 to 2009. Metabolic syndrome was defined as per NCEP/ATP III criteria. Metabolic syndrome patients (n = 690) were matched 1:1:1 to those with 1 component (n = 690) and 2 components (n = 690) of metabolic syndrome for age, sex, smoking status, and family history of premature CAD using propensity scoring. Major adverse cardiac events (MACE) were defined by a composite of myocardial infarction (MI), acute coronary syndrome, mortality and late target vessel revascularization. Patients with 1 component of metabolic syndrome manifested lower rates of obstructive 1-, 2-, and 3-vessel/left main disease compared to metabolic syndrome patients (9.4% vs 13.8%, 2.6% vs 4.5%, and 1.0% vs 2.3%, respectively; p < 0.05), while those with 2 components did not (10.5% vs 13.8%, 2.8% vs 4.5% and 1.3% vs 2.3%, respectively; p > 0.05). At 2.5 years, metabolic syndrome patients experienced a higher rate of MACE compared to patients with 1 component (4.4% vs 1.6%; p = 0.002), while no difference observed compared to individuals with 2 components (4.4% vs 3.2% p = 0.25) of metabolic syndrome. In conclusion, Metabolic syndrome patients have significantly greater prevalence, severity, and prognosis of CAD compared to patients with 1 but not 2 components of metabolic syndrome.
EVALuna2:12077

Is PCAT CT Attenuation the ‘Game Changer’ in the Prediction of Death and Myocardial Infarction? - Göller, Markus; Marwan, Mohamed (Journal of the American College of Cardiology : Cardiovascular imaging, 2021)
CRIS-Team Scopus Importer:2021-07-30
Keywords: coronary CT angiography; CT attenuation; myocardial infarction; pericoronary adipose tissue

Is vascular remodelling in patients with chronic heart failure exaggerated? - Pietschner, Robert; Bosch, Agnes; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland; Kolwelter, Julie (ESC Heart Failure, 2022)
Background Vascular remodelling of large arteries increases afterload of the left ventricle. The aim of this study was to analyse whether vascular remodelling and function under laboratory and 24-hour ambulatory conditions is impaired in patients with chronic heart failure (CHF) independently of cardiovascular risk factors.
CRIS-Team WoS Importer:2022-10-21

Journal introduction - Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2014)
CRIS-Team Scopus Importer:2023-03-08

Journal watch: diagnostic nanoparticles - Poettler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33204

Jugular venous congestion in acute pulmonary embolism - Schlundt, Christian; Bietau, Christian; Achenbach, Susanne (Herz, 2014)
EVALuna2:11994

Kardiale Bildgebung – mehr als reine Diagnostik - Achenbach, Stephan (Herz, 2023)
CRIS-Team Scopus Importer:2023-10-20

Kardiológia v roku 2017 zobrazovacie metodiky - Delgado, Victoria; Knuuti, Juhani; Plein, Sven; Achenbach, Stephan; Bax, Jeroen J. (Cardiology Letters, 2018)
CRIS-Team Scopus Importer:2023-03-08

Koronare CT-Angiografie - Erstuntersuchung für alle Patienten mit Brustschmerz? - Achenbach, Stephan (Klinikarzt, 2018)
CRIS-Team Scopus Importer:2023-03-08

Koronare CT-Angiographie und koronare Atherosklerose: Wo stehen wir heute? - Achenbach, Stephan (Herz, 2023)
Cardiac computed tomography (CT) has made substantial progress in recent years. The main field of application is CT coronary angiography for visualization of the coronary arteries and for the detection and exclusion of coronary artery stenosis. This has been included in international guidelines for the management of stable coronary artery disease or chronic coronary syndrome as well as for the diagnostic work-up of patients with acute chest pain; however, it must be taken into account that the diagnostic validity is only sufficiently high when the image quality is good and therefore alternative diagnostic procedures should be included in patients where an unrestricted good image quality is not to be expected. The fact that CT angiography enables the detection not only of coronary stenosis but also of nonobstructive atherosclerotic plaque is interesting for the estimation of the risk of atherosclerotic events. It is practically certain that in the absence of detectable atherosclerotic plaque in CT angiography, statin treatment does not lower the risk of atherosclerotic events. To what extent CT is suitable to provide indications for statin treatment and the threshold for which the presence of nonobstructive plaque should prompt initiation of statin treatment are currently the subject of intensive research.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Acute coronary syndrome; Angiography; Atherosclerosis; Computed tomography; Coronary disease

Late Enhancement in the sense of an unrecognized Heart Attack - Achenbach, Stephan (Der Kardiologe, 2019)
CRIS-Team WoS Importer:2019-03-08

Leaders in Cardiovascular Research: Stephan Achenbach - Guzik, Tomasz J.; Achenbach, Stephan (Cardiovascular Research, 2020)
CRIS-Team Scopus Importer:2020-09-11

Leadless left ventricular endocardial pacing for CRT upgrades in previously failed and high-risk patients in comparison with coronary sinus CRT upgrades - Sidhu, Baldeep Singh; Sieniewicz, Benjamin; Gould, Justin; Elliott, Mark K.; Mehta, Vishal S.; Betts, Timothy R.; James, Simon; Turley, Andrew J.; Butter, Christian; Seifert, Martin; Boersma, Lucas V. A.; Riahi, Sam; et al. (Europace, 2021)
Aims: Cardiac resynchronization therapy (CRT) upgrades may be less likely to improve following intervention. Leadless left ventricular (LV) endocardial pacing has been used for patients with previously failed CRT or high-risk upgrades. We compared procedural and long-term outcomes in patients undergoing coronary sinus (CS) CRT upgrades with high-risk and previously failed CRT upgrades undergoing LV endocardial upgrades. Method and results: Prospective consecutive CS upgrades between 2015 and 2019 were compared with those undergoing WiSE-CRT implantation. Cardiac resynchronization therapy response at 6 months was defined as improvement in clinical composite score (CCS) and a reduction in LV end-systolic volume (LVESV) ≥15%. A total of 225 patients were analysed; 121 CS and 104 endocardial upgrades. Patients receiving WiSE-CRT tended to have more comorbidities and were more likely to have previous cardiac surgery (30.9% vs. 16.5%; P = 0.012), hypertension (59.2% vs. 34.7%; P < 0.001), chronic obstructive airways disease (19.4% vs. 9.9%; P = 0.046), and chronic kidney disease (46.4% vs. 21.5%; P < 0.01) but similar LV ejection fraction (30.0 ± 8.3% vs. 29.5 ± 8.6%; P = 0.678). WiSE-CRT upgrades were successful in 97.1% with procedure-related mortality in 1.9%. Coronary sinus upgrades were successful in 97.5% of cases with a 2.5% rate of CS dissection and 5.6% lead malfunction/displacement. At 6 months, 91 WiSE-CRT upgrades and 107 CS upgrades had similar improvements in CCS (76.3% vs. 68.5%; P = 0.210) and reduction in LVESV ≥15% (54.2% vs. 56.3%; P = 0.835). Conclusion: Despite prior failed upgrades and high-risk patients with more comorbidities, WiSE-CRT upgrades had high rates of procedural success and similar improvements in CCS and LV remodelling with CS upgrades.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cardiac resynchronization therapy; Endocardial pacing; Epicardial pacing; WiSE-CRT system

Leaflet thrombosis following transcatheter aortic valve implantation - Mekkhala, N.; Göller, Markus; Röther, Jens; Bittner, D.; Schuhbaeck, A.; Hell, M.; Muschiol, G.; Kolwelter, Julie; Feyrer, R.; Schlundt, Christian; Achenbach, Stephan; Arnold, M.; et al. (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: Transcatheter aortic valve implantation (TAVI) is increasingly being offered to high-risk patients with symptomatic aortic valve stenosis. Recent reports have suggested a high incidence of subclinical leaflet thrombosis following bioprosthestic aortic valve replacement. We report the frequency and clinical presentation of leaflet thrombosis identified by cardiac CT in patients referred for follow-up contrast enhanced CT angiography following TAVI. METHODS: 91 consecutive patients referred for follow-up contrast-enhanced CT angiography following TAVI were screened for inclusion in this analysis. Out of these, 13 patients were excluded. All CT examinations were performed using a 2nd or a 3rd generation dual-source system (Somatom Definition Flash/Force, Forchheim, Germany). In all patients, retrospectively ECG-gated spiral acquisition with tube modulation was performed to allow for assessment of leaflet motion. All prostheses were analyzed for presence of leaflet thrombosis defined as hypo-attenuated leaflet thickening with or without leaflet restriction. Post-procedural antithrombotic regimen as well as symptom status was documented in all patients. RESULTS: 78 consecutive patients (35 males, 81 ± 4 years) were analyzed. TAVI had been performed in all patients (76 transfemoral access, 2 transapical access) with either balloon-expandable prostheses (4 Sapien XT, 64 Sapien 3) or self-expandable prostheses (5 SJM Portico, 5 Symetis Acurate). Follow-up CT angiography was performed at a median of 4 months following index procedure (Interquartile range 1 month). Leaflet thrombosis was detected in 18 patients (23%, 14 Sapien 3, 1 Sapien XT, 2 SJM Portico, 1 Symetis Acurate). In patients with leaflet thickening on CT, only 11% were on either oral anticoagulation or new oral anticoagulants versus 50% for patients with no leaflet thickening (p 0.002). In patients with leaflet thrombosis, 3 leaflets were affected in 5 patients, 2 leaflets in 5 patients and in 8 patient only 1 leaflet was affected. Clinical symptoms (angina, dyspnea or both) were reported in 2/18 patients with leaflet thrombosis (11%) and in both patients a significant increase of the mean echocardiographic gradient over the prosthesis was documented. The peak and mean echocardiographic gradients obtained at the day of CT examination was significantly higher in symptomatic patients versus asymptomatic patients (peak 46 ± 7 vs. 23 ± 11 mmHg, mean 29 ± 7 vs. 12 ± 6 mmHg, p = 0.01 and 0.002, respectively). Follow-up CT was available for 4 patients with complete resolution of the hypo-attenuated leaflet thickening following treatment. CONCLUSION: Leaflet thrombosis following TAVI is a relatively frequent finding in patients referred for contrast enhanced CT angiography following TAVI. In the majority of patients it follows a subclinical course and is substantially more frequent in individuals who are not on oral anticoagulation. However, in patients with relevant increase in prosthetic gradients, symptomatic presentations are possible.
EVALuna2:33589

Leaflet thrombosis following transcatheter aortic valve implantation: insights from a single center experience - Achenbach, Stephan; Göller, Markus; Loders, Sabrina; Schuhbaeck, A.; Hell, M.; Marwan, Mohamed; Arnold, Martin (2016)
EVALuna2:33690

Left atrial appendage closure in patients with chronic kidney disease: results from the German multicentre LAARGE registry - Fastner, Christian; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Borggrefe, Martin; Nienaber, Christoph A.; Weiß, Christian; Pleger, Sven T.; Ince, Hüseyin; Maier, Jens; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2020)
Objectives: Chronic kidney disease (CKD) is associated with an increased complication rate after cardiac interventions. Although CKD has a high prevalence among atrial fibrillation patients, the impact of CKD on periprocedural complications and the outcome after an interventional left atrial appendage closure (LAAC) is unclear. The present study, therefore, aimed to investigate whether CKD influences the procedure’s effectiveness and safety. Methods: LAARGE is a prospective, non-randomised registry. LAAC was conducted with different standard commercial devices, and the follow-up period was one year. CKD was defined by an eGFR < 60 mL/min/1.73 m2, and subgroups were further analysed (i.e. eGFR < 15, 15–29, and 30–59 mL/min/1.73 m2, respectively). Results: Two hundred ninety-nine of 623 patients (48.0%) revealed a CKD. The prevalence of cardiovascular comorbidity, CHA2DS2-VASc score (4.9 vs. 4.2), and HAS-BLED score (4.3 vs. 3.5) was significantly higher in CKD patients (each p < 0.001). Implantation success was similarly high across all GFR groups (97.9%). Periprocedural MACCE (0.7 vs. 0.3%), and other major complications (4.7 vs. 3.7%) were comparably infrequent. Survival free of stroke was significantly lower among CKD patients within 1 year (82.0 vs. 93.0%; p < 0.001; consistent after adjustment for confounding factors), without significant accentuation in advanced CKD (i.e. eGFR < 30 mL/min/1.73 m2; p > 0.05 vs. eGFR 30–59 mL/min/1.73 m2). Non-fatal strokes were absolutely infrequent during follow-up (0 vs. 1.1%). Severe non-fatal bleedings were observed only among CKD patients (1.4 vs. 0%; p = 0.021). Conclusions: Despite an increased cardiovascular risk profile of CKD patients, device implantation was safe, and LAAC was associated with effective stroke prevention across all CKD stages.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Atrial fibrillation; Chronic kidney disease; LAARGE; Left atrial appendage; Left atrial appendage closure

Left atrial remodeling, early repolarization pattern, and inflammatory cytokines in professional soccer players - Stumpf, Christian; Simon, Michael; Wilhelm, Martin; Zimmermann, Stefan; Rost, Christian; Achenbach, Stephan; Brem, Matthias H. (Journal of Cardiology, 2016)
OBJECTIVES: Although regular physical exercise clearly reduces cardiovascular morbidity risk, long-term endurance sports practice has been recognized as a risk factor for atrial fibrillation (AF). However, the mechanisms how endurance sports can lead to AF are not yet clear. The aim of our present study was to investigate the influence of long-term endurance training on vagal tone, atrial size, and inflammatory profile in professional elite soccer players. METHODS: A total of 25 professional major league soccer players (mean age 24±4 years) and 20 sedentary controls (mean age 26±3 years) were included in the study and consecutively examined. All subjects underwent a sports cardiology check-up with physical examination, electrocardiography, echocardiography, exercise testing on a bicycle ergometer, and laboratory analysis [standard laboratory and cytokine profile: interleukin (IL)-6, tumor necrosis factor (TNF)-α, IL-8, IL-10]. RESULTS: Athletes were divided into two groups according to presence or absence of an early repolarization (ER) pattern, defined as a ST-segment elevation at the J-point (STE) ≥0.1mm in 2 leads. Athletes with an ER pattern showed significantly lower heart rate and an increased E/e' ratio compared to athletes without an ER pattern. STE significantly correlated with E/e' ratio as well as with left atrial (LA) volume. The pro-inflammatory cytokines IL-6, IL-8, TNF-α as well as the anti-inflammatory cytokine IL-10 were significantly elevated in all soccer players. However, athletes with an ER pattern had significantly higher IL-6 plasma levels than athletes without ER pattern. Furthermore, athletes with "high" level IL-6 had significantly larger LA volumes than players with "low" level IL-6. CONCLUSIONS: Athletes with an ER pattern had significantly higher E/e' ratios, reflecting higher atrial filling pressures, higher LA volume, and higher IL-6 plasma levels. All these factors may contribute to atrial remodeling over time and thus increase the risk of AF in long-term endurance sports.
EVALuna2:33695

Left ventricular contraction patterns in Takotsubo Syndrome and their correlation with long-term clinical outcome - Gaede, Luise; Herchenbach, Amanda; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (IJC Heart & Vasculature, 2021)
Background: Takotsubo Syndrome (TTS) is diagnosed in 1–2% of all patients presenting with acute coronary syndrome. Next to the typical apical manifestation, other locations of left ventricular contraction abnormality are possible, but their relationship to patient characteristics, clinical correlates as well as long-term outcome are poorly understood. Methods & results: We retrospectively analyzed 126 patients presenting TTS. Cases were categorized according to left ventricular contraction abnormality patterns: typical apical pattern (71%, n = 89) vs. atypical patterns (29%, n = 37). Cases with typical TTS showed significantly higher levels of troponin I (3.12 ng/ml vs. 1.32 ng/ml, p = 0.013) and creatin kinase (CK) on admission (461 (±1207)U/l vs. 173 (±177) U/l, p = 0.03) as well as peak CK (973 (±2860)U/l vs. 301 (±328) U/l, p = 0.03) and more often ischemia related ECG changes (p = 0.02). Follow-up data was available for 85% of the patients. Median FU time was 4.4 years (IQR 1.4–7.7 years). All-cause mortality during follow-up was 39%, with no significant difference between patients with typical or atypical TTS (43% vs. 29%, p = 0.17). In multivariate logistic regression analysis, only anemia was predictive for long-term mortality (OR 3.93, 95%CI 1.02–2.08, p = 0.015). The majority of surviving patients (69%) reported good quality of life, even though only 56% reported being symptom-free. Conclusion: Patients with TTS have poor long-term prognosis with an overall mortality of 39.1% within 4 years and nearly half of all patients report persisting symptoms. Even though the apical contraction pattern is associated with higher elevation of serum markers for myocardial damage, it was not associated with higher long-term mortality.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Broken heart syndrome; Contraction pattern; Stress cardiomyopathy; Takotsubo cardiomyopathy; Takotsubo Syndrome

Left ventricular function and volume with coronary CT angiography improves risk stratification and identification of patients at risk for incident mortality: results from 7758 patients in the prospective multinational CONFIRM observational cohort study - Arsanjani, Reza; Berman, Daniel S.; Gransar, Heidi; Cheng, Victor Y.; Dunning, Allison; Lin, Fay Y.; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Callister, Tracy Q.; Chang, Hyuk-Jae; Cademartiri, Filippo; et al. (Radiology, 2014)
To assess whether gradations of left ventricular (LV) ejection fraction (LVEF) and volumes measured with coronary computed tomography (CT) would augment risk stratification and discrimination for incident mortality.This study was approved by the institutional review board, and informed consent was obtained when required. Subjects without known coronary artery disease (CAD) who underwent cardiac CT angiography with quantitative LV measurements were categorized according to LVEF (>= 55%, 45%-54.9%, 35%-44.9%, or <35%). LV end-systolic volume (LVESV) and LV end-diastolic volume (LVEDV) were classified as normal (>= 90 mL) or abnormal (>= 200 mL). CAD extent and severity was categorized as none, nonobstructive, obstructive (>= 50%), one-vessel, two-vessel, and three-vessel or left main disease. LVEF and volumes were assessed for risk prediction and discrimination of future mortality by using Cox hazards model and receiver operating characteristic curve analysis, respectively.During a follow-up of 2.0 years ± 0.9, 7758 patients (mean age, 58.5 years ± 13.0; 4220 male patients [54.4%]) were studied. At multivariable analysis, worsening LVEF was independently associated with mortality for moderately (hazard ratio = 3.14, P < .001) and severely (hazard ratio = 5.19, P < .001) abnormal ejection fraction. LVEF demonstrated improved discrimination for mortality (Az = 0.816) when compared with CAD risk factors alone (Az = 0.781) or CAD risk factors plus extent and severity. At multivariable analysis of a subgroup of 3706 individuals, abnormal LVEDV (hazard ratio = 4.02) and LVESV (hazard ratio = 6.46) helped predict mortality (P < .001). Similarly, LVESV and LVEDV demonstrated improved discrimination when compared with CAD risk factors or CAD extent and severity (P < .05).LV dysfunction and volumes measured with cardiac CT angiography augment risk prediction and discrimination for future mortality.
EVALuna2:11990

Leitlinie zum Einrichten und Betreiben von Herzkatheterlaboren und Hybridoperationssälen/Hybridlaboren: 3. Auflage 2015 - Schächinger, V.; Nef, H.; Achenbach, Susanne; Butter, C.; Deisenhofer, I.; Eckardt, L.; Eggebrecht, H.; Kuon, E.; Levenson, B.; Linke, A.; Madlener, K.; Mudra, H.; et al. (Der Kardiologe, 2015)
Besides diagnostic heart catheterization and coronary interventions, numerous additional procedures are now performed in catheterization laboratories with special requirements for equipment and sequence of operations. The current third edition of the guidelines to establish and operate catheterization laboratories, hybrid operating rooms (OR) and hybrid laboratories gives recommendations with respect to these procedures, including invasive electrophysiology, implantation of rhythm devices and also with respect to catheter-based valve therapy, especially transcather aortic valve implantation (TAVI). Special aspects of hygiene and structural conditions, which are required for hybrid ORs and hybrid laboratories, are discussed. The guidelines provide recommendations for planning a catheterization laboratory and hybrid OR as well as for operational aspects, which include legal regulations, hygiene requirements, structural architectural aspects and radiation safety. Furthermore, aspects of technical equipment, integration of modern three-dimensional imaging modalities, data management and workforce, including cardiac analgesia, are provided.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac catheterization; Coronary intervention; Electrophysiology; Hybrid operating room; Transcatheter aortic valve implantation

Lesion-Specific and Vessel-Related Determinants of Fractional Flow Reserve Beyond Coronary Artery Stenosis - Ahmadi, Amir; Leipsic, Jonathon; Ovrehus, Kristian A.; Gaur, Sara; Bagiella, Emilia; Ko, Brian; Dey, Damini; Larocca, Gina; Jensen, Jesper M.; Botker, Hans Erik; Achenbach, Stephan; De Bruyne, Bernard; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2018)
OBJECTIVES: The aims of the present study were: 1) to investigate the contribution of the extent of luminal stenosis and other lesion composition-related factors in predicting invasive fractional flow reserve (FFR); and 2) to explore the distribution of various combinations of morphological characteristics and the severity of stenosis among lesions demonstrating normal and abnormal FFR. BACKGROUND: In patients with stable ischemic heart disease, FFR-guided revascularization, as compared with medical therapy alone, is reported to improve outcomes. Because morphological characteristics are the basis of plaque rupture and acute coronary events, a relationship between FFR and lesion characteristics may exist. METHODS: This is a subanalysis of NXT (HeartFlowNXT: HeartFlow Analysis of Coronary Blood Flow Using Coronary CT Angiography), a prospective, multicenter study of 254 patients (age 64 ± 10 years, 64% male) with suspected stable ischemic heart disease; coronary computed tomography angiography including plaque morphology assessment, invasive angiography, and FFR were obtained for 383 lesions. Ischemia was defined by invasive FFR ≤0.80. Computed tomography angiography-defined morphological characteristics of plaques and their vascular location were used in univariate and multivariate analyses to examine their predictive value for invasive FFR. The distribution of various combinations of plaque morphological characteristics and the severity of stenosis among lesions demonstrating normal and abnormal FFR were examined. RESULTS: The percentage of luminal stenosis, low-attenuation plaque (LAP) or necrotic core volume, left anterior descending coronary artery territory, and the presence of multiple lesions per vessel were the predictors of FFR. When grouped on the basis of degree of luminal stenosis, FFR-negative lesions had consistently smaller LAP volumes compared with FFR-positive lesions. The distribution of plaque characteristics in lesions with normal and abnormal FFR demonstrated that whereas FFR-negative lesions excluded likelihood of stenotic plaques with moderate to high LAP volumes, only one-third of FFR-positive lesions demonstrated obstructive plaques with moderate to high LAP volumes. CONCLUSIONS: In addition to the severity of luminal stenosis, necrotic core volume is an independent predictor of FFR. The distribution of plaque characteristics among lesions with varying luminal stenosis and normal and abnormal FFR may explain the outcomes associated with FFR-guided therapy.
EVALuna2:36000

Life-threatening Autoimmune Cardiomyopathy Reproducibly Induced in a Patient by Checkpoint Inhibitor Therapy - Tajmir-Riahi, Azadeh; Bergmann, Tanja; Schmid, Michael; Agaimy, Abbas; Schuler, Gerold; Heinzerling, Lucie (Journal of Immunotherapy, 2018)
Checkpoint inhibitors induce a plethora of immune-related adverse events (irAEs) including autoimmune colitis, hepatitis, endocrinopathies, and rarer side effects like neuritis. Here, a case of autoimmune cardiomyopathy (grade 3 CTCAE) and myocarditis under combination therapy with nivolumab plus ipilimumab in a 72-year-old melanoma patient is reported. Treatment induced a partial response for 14 months. However, after 10 infusions the patient developed dyspnea, edema of the legs, ascites and a weight gain of 10 kg because of a decompensated heart insufficiency with a reduced ejection fraction from formerly 48%-50% to 15%. Ischemia and viral infections were ruled out. Histopathology showed hypertrophic myocarditis with interstitial lymphocytes. Prednisolone improved the patient's condition within 3 days, leading to a 25% and 30% ejection fraction after 2 and 8 weeks, respectively, and clinical symptoms subsided completely. Importantly, reinduction of anti-PD1 therapy resulted in a flare of myocarditis. Awareness for potentially life-threatening irAE of checkpoint inhibitors like autoimmune cardiomyopathy and myocarditis is crucial to rapidly initiate adequate treatment.
EVALuna2:34413

Localization of the femoral artery bifurcation: hips don't lie - in at least 97% of cases - Uehlein, Sabrina; Smolka, S.; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Long-term clinical outcome after implantation of the self-expandable STENTYS stent in a large, multicenter cohort - Gaede, Luise; Liebetrau, Christoph; Doerr, Oliver; Blumenstein, Johannes; Elsaesser, Albrecht; Hamm, Christian W.; Moellmann, Helge; Schlundt, Christian; Nef, Holger M.; Achenbach, Stephan (Coronary Artery Disease, 2017)
OBJECTIVE: The objective of the study was to retrospectively evaluate the long-term clinical outcome after implantation of the self-expandable (SE) STENTYS stent in a large multicenter cohort. BACKGROUND: Incomplete stent apposition is known to cause higher rates of myocardial infarction (MI) and stent thrombosis. Because of its self-expanding features, the SE STENTYS stent adapts to the vessel wall and is therefore expected to minimize malapposition and therefore the rates of MI and stent thrombosis. PATIENTS AND METHODS: Treatment with a total of 351 SE coronary stents was attempted in 314 patients of a cohort from three German institutions between 2011 and 2015. Technical success was achieved with 331/351 (94%) stents. Patients treated successfully with SE stents (n=298) were followed up using the primary outcome measure of target lesion failure (TLF), a combined endpoint of cardiac mortality, recurrent target vessel MI, acute stent thrombosis, and clinically driven target lesion revascularization. Follow-up was complete in 268/298 (90%) patients with a median follow-up period of 2.5 (interquartile range: 1.4-3.3) years. RESULTS: TLF occurred in 54/298 (18%) patients. Event rates were 7.5% for cardiac mortality, 11.6% for target vessel MI, and 5.2% for clinically driven target lesion revascularization. Acute stent thrombosis occurred in 2/298 (0.7%). Overall, stent thrombosis had an incidence of 2.6% within the follow-up period. ST-elevation MI at baseline (P=0.02) and a dual antiplatelet therapy with clopidogrel for only 6 months (P=0.04) were the only clinical factors linked to the absence of TLF. CONCLUSION: Technical success of SE coronary stent implantation in an all-comer cohort of patients was high, although the rate of TLF and stent thrombosis during long-term follow-up was also relatively high.
EVALuna2:33608

Long-Term Outcomes After Treatment With a Paclitaxel-Coated Balloon Versus Balloon Angioplasty: Insights From the PEPCAD-DES Study (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel-Coated Percutaneous Transluminal C - Rittger, Harald; Waliszewski, Matthias; Brachmann, Johannes; Hohenforst-Schmidt, Wolfgang; Ohlow, Marc; Brugger, Andreas; Thiele, Holger; Birkemeyer, Ralf; Kurowski, Volkhard; Schlundt, Christian; Zimmermann, Stefan; Lonke, Sandra; et al. (Jacc-Cardiovascular Interventions, 2015)
The intention this PEPCAD-DES (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter) study update was to demonstrate the safety and efficacy of paclitaxel-coated balloon (PCB) angioplasty in patients with DES-ISR at 3 years.In the PEPCAD-DES trial late lumen loss and the need for repeat target lesion revascularization (TLR) was significantly reduced with PCB angioplasty compared with plain old balloon angioplasty (POBA) in patients with drug-eluting stent in-stent restenosis (DES-ISR) at 6 months. We evaluated whether the clinical benefit of reduced TLR and major adverse cardiac events (MACE) was maintained up to 3 years.A total of 110 patients with DES-ISR in native coronary arteries with reference diameters ranging from 2.5 mm to 3.5 mm and lesion lengths <=22 mm were randomized to treatment with either PCB or POBA in a multicenter, randomized, single-blind clinical study. With a 2:1 randomization, 72 patients were randomized to the PCB group and 38 patients to the POBA group. At baseline, there were lesions with at least 2 stent layers in PCB (52.8%, 38 of 72) and POBA (55.3%, 21 of 38) patients.At 36 months, the TLR rates were significantly lower in the PCB group compared with the POBA control group (19.4% vs. 36.8%; p = 0.046). Multiple TLRs in individual patients were more frequent in the POBA group compared with the PCB group (more than 1 TLR: POBA, 13.2%; PCB, 1.4%; p = 0.021). The 36-month MACE rate was significantly reduced in the PCB group compared with the POBA group (20.8% vs. 52.6%, log-rank p = 0.001).PCB angioplasty was superior to POBA for the treatment of DES-ISR patients in terms of MACE and TLR for up to 36 months. There was no late catch-up phenomenon. (Treatment of Drug-eluting Stent [DES] In-Stent Restenosis With SeQuent® Please Paclitaxel Eluting Percutaneous Transluminal Coronary Angioplasty [PTCA] Catheter [PEPCAD-DES]; NCT00998439).
EVALuna2:12089

Long-term prognostic impact of CT-Leaman score in patients with non-obstructive CAD: Results from the COronary CT Angiography EvaluatioN For Clinical Outcomes InteRnational Multicenter (CONFIRM) study - Andreini, Daniele; Pontone, Gianluca; Mushtaq, Saima; Gransar, Heidi; Conte, Edoardo; Bartorelli, Antonio L.; Pepi, Mauro; Opolski, Maksymilian P.; Hartaigh, Briain O.; Berman, Daniel S.; Budoff, Matthew J.; Achenbach, Stephan; et al. (International Journal of Cardiology, 2017)
BACKGROUND: Non-obstructive coronary artery disease (CAD) identified by coronary computed tomography angiography (CCTA) demonstrated prognostic value. CT-adapted Leaman score (CT-LeSc) showed to improve the prognostic stratification. Aim of the study was to evaluate the capability of CT-LeSc to assess long-term prognosis of patients with non-obstructive (CAD). METHODS: From 17 centers, we enrolled 2402 patients without prior CAD history who underwent CCTA that showed non-obstructive CAD and provided complete information on plaque composition. Patients were divided into a group without CAD and a group with non-obstructive CAD (<50% stenosis). Segment-involvement score (SIS) and CT-LeSc were calculated. Outcomes were non-fatal myocardial infarction (MI) and the combined end-point of MI and all-cause mortality. RESULTS: Patient mean age was 56±12years. At follow-up (mean 59.8±13.9months), 183 events occurred (53 MI, 99 all-cause deaths and 31 late revascularizations). CT-LeSc was the only multivariate predictor of MI (HRs 2.84 and 2.98 in two models with Framingham and risk factors, respectively) and of MI plus all-cause mortality (HR 2.48 and 1.94 in two models with Framingham and risk factors, respectively). This was confirmed by a net reclassification analysis confirming that the CT-LeSc was able to correctly reclassify a significant proportion of patients (cNRI 0.28 and 0.23 for MI and MI plus all-cause mortality, respectively) vs. baseline model, whereas SIS did not. CONCLUSION: CT-LeSc is an independent predictor of major acute cardiac events, improving prognostic stratification of patients with non-obstructive CAD.
EVALuna2:33647

Long-term prognostic utility of computed tomography coronary angiography in older populations - Gnanenthiran, Sonali R.; Naoum, Christopher; Leipsic, Jonathon A.; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Bax, Jeroen J.; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk Jae; et al. (European Heart Journal - Cardiovascular Imaging, 2019)
AIMS: The long-term prognostic value of coronary computed tomography angiography (CCTA)-identified coronary artery disease (CAD) has not been evaluated in elderly patients (≥70 years). We compared the ability of coronary CCTA to predict 5-year mortality in older vs. younger populations. METHODS AND RESULTS: From the prospective CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry, we analysed CCTA results according to age <70 years (n = 7198) vs. ≥70 years (n = 1786). The severity of CAD was classified according to: (i) maximal stenosis degree per vessel: none, non-obstructive (1-49%), or obstructive (>50%); (ii) segment involvement score (SIS): number of segments with plaque. Cox-proportional hazard models assessed the relationship between CCTA findings and time to mortality. At a mean 5.6 ± 1.1 year follow-up, CCTA-identified CAD predicted increased mortality compared with patients with a normal CCTA in both <70 years [non-obstructive hazard ratio (HR) confidence interval (CI): 1.70 (1.19-2.41); one-vessel: 1.65 (1.03-2.67); two-vessel: 2.24 (1.21-4.15); three-vessel/left main: 4.12 (2.27-7.46), P < 0.001] and ≥70 years [non-obstructive: 1.84 (1.15-2.95); one-vessel: HR (CI): 2.28 (1.37-3.81); two-vessel: 2.36 (1.33-4.19); three-vessel/left main: 2.41 (1.33-4.36), P = 0.014]. Similarly, SIS was predictive of mortality in both <70 years [SIS 1-3: 1.57 (1.10-2.24); SIS ≥4: 2.42 (1.65-3.57), P < 0.001] and ≥70 years [SIS 1-3: 1.73 (1.07-2.79); SIS ≥4: 2.45 (1.52-3.93), P < 0.001]. CCTA findings similarly predicted long-term major adverse cardiovascular outcomes (MACE) (all-cause mortality, myocardial infarction, and late revascularization) in both groups compared with patients with no CAD. CONCLUSION: The presence and extent of CAD is a meaningful stratifier of long-term mortality and MACE in patients aged <70 years and ≥70 years old. The presence of obstructive and non-obstructive disease and the burden of atherosclerosis determined by SIS remain important predictors of prognosis in older populations.
CRIS-Team Scopus Importer:2019-11-01
Keywords: age; coronary computed tomography angiography; major adverse cardiovascular events; mortality; older populations

Long term prognostic utility of coronary CT angiography in patients with no modifiable coronary artery disease risk factors: Results from the 5 year follow-up of the CONFIRM International Multicenter Registry - Cheruvu, Chaitu; Precious, Bruce; Naoum, Christopher; Blanke, Philipp; Ahmadi, Amir; Soon, Jeanette; Arepalli, Chesnaldey; Gransar, Heidi; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracy Q.; et al. (Journal of Cardiovascular Computed Tomography, 2016)
Coronary computed tomography angiography (coronary CTA) can prognosticate outcomes in patients without modifiable risk factors over medium term follow-up. This ability was driven by major adverse cardiovascular events (MACE).Determine if coronary CTA could discriminate risk of mortality with longer term follow-up. In addition we sought to determine the long-term relationship to MACE.From 12 centers, 1884 patients undergoing coronary CTA without prior coronary artery disease (CAD) or any modifiable CAD risk factors were identified. The presence of CAD was classified as none (0% stenosis), mild (1% to 49% stenosis) and obstructive (>=50% stenosis severity). The primary endpoint was all-cause mortality and the secondary endpoint was MACE. MACE was defined as the combination of death, nonfatal myocardial infarction, unstable angina, and late target vessel revascularization (>90 days).Mean age was 55.6 ± 14.5 years. At mean 5.6 ± 1.3 years follow-up, 145(7.7%) deaths occurred. All-cause mortality demonstrated a dose-response relationship to the severity and number of coronary vessels exhibiting CAD. Increased mortality was observed for >1 segment non-obstructive CAD (hazard ratio [HR]:1.73; 95% confidence interval [CI]: 1.07-2.79; p = 0.025), obstructive 1&2 vessel CAD (HR: 1.70; 95% CI: 1.08-2.71; p = 0.023) and 3-vessel or left main CAD (HR: 2.87; 95% CI: 1.57-5.23; p = 0.001). Both obstructive CAD (HR: 6.63; 95% CI: 3.91-11.26; p < 0.001) and non-obstructive CAD (HR: 2.20; 95% CI: 1.31-3.67; p = 0.003) predicted MACE with increased hazard associated with increasing CAD severity; 5.60% in no CAD, 13.24% in non-obstructive and 36.28% in obstructive CAD, p < 0.001 for trend.In individuals being assessed for CAD with no modifiable risk factors, all-cause mortality in the long term (>5 years) was predicted by the presence of more than 1 segment of non-obstructive plaque, obstructive 1- or 2-vessel CAD and 3 vessel/left main CAD. Any CAD, whether non-obstructive or obstructive, predicted MACE over the same time period.
EVALuna2:12053

Long-Term Prognostic Utility of Coronary CT Angiography in Stable Patients With Diabetes Mellitus - Blanke, Philipp; Naoum, Christopher; Ahmadi, Amir; Cheruvu, Chaitu; Soon, Jeanette; Arepalli, Chesnal; Gransar, Heidi; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracy Q.; Al-Mallah, Mouaz H.; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2016)
OBJECTIVES: The goal of this study was to determine the long-term prognostic value of coronary computed tomography angiography (CTA) among patients with diabetes mellitus (DM) compared with nondiabetic subjects. BACKGROUND: The long-term prognostic value of coronary CTA in patients with DM is not well established. METHODS: Patients enrolled in the CONFIRM (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter) registry with 5-year follow-up data were identified. The extent and severity of coronary artery disease (CAD) were analyzed at baseline coronary CTA and in relation to outcomes between diabetic and nondiabetic patients. CAD according to coronary CTA was defined as none (0% stenosis), nonobstructive (1% to 49% stenosis), or obstructive (≥50% stenosis). Time to death (and in a subgroup, time to major adverse cardiovascular event) was estimated by using multivariable Cox proportional hazards models. RESULTS: A total of 1,823 patients were identified as having DM with 5-year clinical follow-up and were propensity-matched to 1,823 patients without DM (mean age 61.8 ± 10.9 years; 54.4% male). Patients with DM did not exhibit a heightened risk of death compared with the propensity-matched nondiabetic subjects in the absence of CAD on coronary CTA (risk-adjusted hazard ratio [HR] of DM: 1.32; 95% confidence interval [CI]: 0.78 to 2.24; p = 0.296). Patients with DM were at increased risk of dying compared with nondiabetic subjects in the setting of nonobstructive CAD (in the propensity-matched cohort: HR, 2.10; 95% CI: 1.43 to 3.09; p < 0.001) with a mortality risk greater than nondiabetic subjects with obstructive disease (p < 0.001). In a risk-adjusted hazard analysis among patients with DM, both per-patient obstructive CAD and nonobstructive CAD conferred an increase in all-cause mortality risk compared with patients without atherosclerosis on coronary CTA (nonobstructive disease-HR: 2.07; 95% CI: 1.33 to 3.24; p = 0.001; obstructive disease-HR: 2.22; 95% CI: 1.47 to 3.36; p < 0.001). CONCLUSIONS: Among patients with DM, nonobstructive and obstructive CAD according to coronary CTA were associated with higher rates of all-cause mortality and major adverse cardiovascular events at 5 years, and this risk was significantly higher than in nondiabetic subjects. Importantly, patients with DM without CAD according to coronary CTA were at a risk comparable to that of nondiabetic subjects.
EVALuna2:33670

Long-term prognostic value of non-invasive fractional flow reserve derived from coronary CT angiography (FFRct) - Ihdayhid, A. R.; Norgaard, B. L.; Gaur, S.; Leipsic, J.; Osawa, K.; Miyoshi, T.; Jensen, J.; Kimura, T.; Shiomi, H.; Erglis, A.; Jegere, S.; Oldroyd, K. G.; et al. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Low-dose dual-source CT angiography with iterative reconstruction for coronary artery stent evaluation - Eisentopf, Jasmin; Achenbach, Stephan; Ulzheimer, Stefan; Layritz, Christian; Wüst, Wolfgang; May, Matthias; Lell, Michael; Ropers, Dieter; Klinghammer, Lutz; Daniel, Werner; Pflederer, Tobias (Journal of the American College of Cardiology : Cardiovascular imaging, 2013)
Objectives: The purpose of this study was to evaluate the image quality and diagnostic accuracy of very low-dose, dual-source computed tomography (DSCT) angiography for the evaluation of coronary stents. Background: Iterative reconstruction (IR) leads to substantial reduction of image noise and hence permits the use of very low-dose data acquisition protocols in coronary computed tomography angiography. Methods: Fifty symptomatic patients with 87 coronary stents (diameter 3.0 ± 0.4 mm) underwent coronary DSCT angiography (heart rate, 60 ± 6 beats/min; prospectively electrocardiography-triggered axial acquisition; 80 kV, 165 mA, 2 × 128 × 0.6-mm collimation; 60 ml of contrast at 6 ml/s) before invasive coronary angiography. DSCT images were reconstructed using both standard filtered back projection and a raw data-based IR algorithm (SAFIRE, Siemens Healthcare, Forchheim, Germany). Subjective image quality (4-point scale from 0 [nondiagnostic] to 3 [excellent image quality]), image noise, contrast-to-noise ratio as well as the presence of in-stent stenosis >50% were independently determined by 2 observers. Results: The median dose-length product was 23.0 (22.0; 23.0) mGy · cm (median estimated effective dose of 0.32 [0.31; 0.32] mSv). IR led to significantly improved image quality compared with filtered back projection (image quality score, 1.8 ± 0.6 vs. 1.5 ± 0.5, p < 0.05; image noise, 70 Hounsfield units [62; 80 Hounsfield units] vs. 96 Hounsfield units [82; 113 Hounsfield units], p < 0.001; contrast-to-noise ratio, 11.0 [9.6; 12.4] vs. 8.0 [6.2; 9.3], p < 0.001). To detect significant coronary stenosis in filtered back projection reconstructions, the sensitivity, specificity, positive predictive value, and negative predictive value were 97% (32 of 33), 53% (9 of 17), 80% (32 of 40), and 90% (9 of 10) per patient, respectively; 89% (43 of 48), 79% (120 of 152), 57% (42 of 74), and 96% (121 of 126) per vessel, respectively; and 85% (12 of 14), 69% (51 of 73), 32% (11 of 34), and 96% (51 of 53) per stent, respectively. In reconstructions obtained by IR, the corresponding values were 100% (33 of 33), 65% (11 of 17), 85% (33 of 39), and 100% (11 of 11) per patient, respectively; 96% (46 of 48), 84% (129 of 152), 66% (47 of 71), and 98% (127 of 129) per vessel, respectively; and 100% (14 of 14), 75% (55 of 73), 44% (14 of 32), and 100% (55 of 55) per stent, respectively. These differences were not significant. Conclusions: In selected patients, prospectively electrocardiography-triggered image acquisition with 80-kV tube voltage and low current in combination with IR permits the evaluation of patients with implanted coronary artery stents with reasonable diagnostic accuracy at very low radiation exposure. © 2013 American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: coronary CT angiography; iterative reconstruction; low dose; stent

LOW DOSE-EPLERENONE TREATMENT DECREASES AORTIC STIFFNESS IN PATIENTS WITH METABOLIC SYNDROME - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Lower mortality in an all-comers aortic stenosis population treated with TAVI in comparison to SAVR - Möllmann, Helge; Husser, Oliver; Blumenstein, Johannes; Liebetrau, Christoph; Dörr, Oliver; Kim, Won Keun; Nef, Holger; Tesche, Christian; Hamm, Christian W.; Elsässer, Albrecht; Achenbach, Stephan; Gaede, Luise (Clinical Research in Cardiology, 2019)
Background: Within the last years TAVI—especially transfemoral/transvascular TAVI—has proven to be a valuable therapeutic option for most patients suffering from AS. Here, we present the outcome of a complete dataset of all patients undergoing aortic valve replacement in Germany in 2018. Methods: The data of all aortic valve procedures performed in Germany in 2018 derive from the mandatory nationwide quality control program. Patients were stratified with a new version of the German Aortic valve score (AKL Score) divided in different risk stratification depending on the treatment with either a catheter based (TV-TAVI) or surgical (iSAVR) approach. In-hospital outcomes have been compared between the two approaches. Results: 19,317 transvascular (TV)–TAVI procedures were carried out. In contrast to this steady growth, the number of iSAVR andtransapical (TA) -TAVI procedures declined. In-hospital mortality after TV-TAVI (2.5%) was lower when compared to iSAVR (3.1%) as well as TA-TAVI (5.7%) in-hospital mortality after TV-TAVI was significantly lowest (Fig. 2) with an in-hospital mortality rate of 2.5%. TV-TAVI was the only approach with an observed vs. expected mortality ratio < 1 according to the used risk prediction model. Conclusion: TV-TAVI is more often performed and shows lower in-hospital mortality than iSAVR. TV-TAVI has replaced iSAVR as the gold-standard concerning in-hospital outcome in aortic stenosis management.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Mortality; Real-world; Registry; SAVR; TAVI; TAVR

Machine learning for prediction of all-cause mortality in patients with suspected coronary artery disease: a 5-year multicentre prospective registry analysis - Motwani, Manish; Dey, Damini; Berman, Daniel S.; Germano, Guido; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; et al. (European Heart Journal, 2017)
Aims: Traditional prognostic risk assessment in patients undergoing non-invasive imaging is based upon a limited selection of clinical and imaging findings. Machine learning (ML) can consider a greater number and complexity of variables. Therefore, we investigated the feasibility and accuracy of ML to predict 5-year all-cause mortality (ACM) in patients undergoing coronary computed tomographic angiography (CCTA), and compared the performance to existing clinical or CCTA metrics. Methods and results: The analysis included 10 030 patients with suspected coronary artery disease and 5-year follow-up from the COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry. All patients underwent CCTA as their standard of care. Twenty-five clinical and 44 CCTA parameters were evaluated, including segment stenosis score (SSS), segment involvement score (SIS), modified Duke index (DI), number of segments with non-calcified, mixed or calcified plaques, age, sex, gender, standard cardiovascular risk factors, and Framingham risk score (FRS). Machine learning involved automated feature selection by information gain ranking, model building with a boosted ensemble algorithm, and 10-fold stratified cross-validation. Seven hundred and forty-five patients died during 5-year follow-up. Machine learning exhibited a higher area-under-curve compared with the FRS or CCTA severity scores alone (SSS, SIS, DI) for predicting all-cause mortality (ML: 0.79 vs. FRS: 0.61, SSS: 0.64, SIS: 0.64, DI: 0.62; P< 0.001). Conclusions: Machine learning combining clinical and CCTA data was found to predict 5-year ACM significantly better than existing clinical or CCTA metrics alone.
EVALuna2:33650

Machine learning integration of circulating and imaging biomarkers for explainable patient-specific prediction of cardiac events: A prospective study - Tamarappoo, Balaji K.; Lin, Andrew; Commandeur, Frederic; McElhinney, Priscilla A.; Cadet, Sebastien; Goeller, Markus; Razipour, Aryabod; Chen, Xi; Gransar, Heidi; Cantu, Stephanie; Miller, Robert JH; Achenbach, Stephan; et al. (Atherosclerosis, 2020)
Background and aims: We sought to assess the performance of a comprehensive machine learning (ML) risk score integrating circulating biomarkers and computed tomography (CT) measures for the long-term prediction of hard cardiac events in asymptomatic subjects. Methods: We studied 1069 subjects (age 58.2 ± 8.2 years, 54.0% males) from the prospective EISNER trial who underwent coronary artery calcium (CAC) scoring CT, serum biomarker assessment, and long-term follow-up. Epicardial adipose tissue (EAT) was quantified from CT using fully automated deep learning software. Forty-eight serum biomarkers, both established and novel, were assayed. An ML algorithm (XGBoost) was trained using clinical risk factors, CT measures (CAC score, number of coronary lesions, aortic valve calcium score, EAT volume and attenuation), and circulating biomarkers, and validated using repeated 10-fold cross validation. Results: At 14.5 ± 2.0 years, there were 50 hard cardiac events (myocardial infarction or cardiac death). The ML risk score (area under the receiver operator characteristic curve [AUC] 0.81) outperformed the CAC score (0.75) and ASCVD risk score (0.74; both p = 0.02) for the prediction of hard cardiac events. Serum biomarkers provided incremental prognostic value beyond clinical data and CT measures in the ML model (net reclassification index 0.53 [95% CI: 0.23–0.81], p < 0.0001). Among novel biomarkers, MMP-9, pentraxin 3, PIGR, and GDF-15 had highest variable importance for ML and reflect the pathways of inflammation, extracellular matrix remodeling, and fibrosis. Conclusions: In this prospective study, ML integration of novel circulating biomarkers and noninvasive imaging measures provided superior long-term risk prediction for cardiac events compared to current risk assessment tools.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Artificial intelligence; Cardiac computed tomography; Cardiovascular risk stratification; Machine learning; Serum biomarkers

Machine learning of clinical variables and coronary artery calcium scoring for the prediction of obstructive coronary artery disease on coronary computed tomography angiography: analysis from the CONFIRM registry - Al'Aref, Subhi J.; Maliakal, Gabriel; Singh, Gurpreet; van Rosendael, Alexander R.; Ma, Xiaoyue; Xu, Zhuoran; Alawamlh, Omar Al Hussein; Lee, Benjamin; Pandey, Mohit; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; et al. (European Heart Journal, 2020)
AIMS: Symptom-based pretest probability scores that estimate the likelihood of obstructive coronary artery disease (CAD) in stable chest pain have moderate accuracy. We sought to develop a machine learning (ML) model, utilizing clinical factors and the coronary artery calcium score (CACS), to predict the presence of obstructive CAD on coronary computed tomography angiography (CCTA). METHODS AND RESULTS: The study screened 35 281 participants enrolled in the CONFIRM registry, who underwent ≥64 detector row CCTA evaluation because of either suspected or previously established CAD. A boosted ensemble algorithm (XGBoost) was used, with data split into a training set (80%) on which 10-fold cross-validation was done and a test set (20%). Performance was assessed of the (1) ML model (using 25 clinical and demographic features), (2) ML + CACS, (3) CAD consortium clinical score, (4) CAD consortium clinical score + CACS, and (5) updated Diamond-Forrester (UDF) score. The study population comprised of 13 054 patients, of whom 2380 (18.2%) had obstructive CAD (≥50% stenosis). Machine learning with CACS produced the best performance [area under the curve (AUC) of 0.881] compared with ML alone (AUC of 0.773), CAD consortium clinical score (AUC of 0.734), and with CACS (AUC of 0.866) and UDF (AUC of 0.682), P < 0.05 for all comparisons. CACS, age, and gender were the highest ranking features. CONCLUSION: A ML model incorporating clinical features in addition to CACS can accurately estimate the pretest likelihood of obstructive CAD on CCTA. In clinical practice, the utilization of such an approach could improve risk stratification and help guide downstream management.
CRIS-Team Scopus Importer:2020-01-28
Keywords: Coronary artery calcium score; Coronary artery disease; Coronary computed tomography angiography; Machine learning

Machine learning to predict the long-term risk of myocardial infarction and cardiac death based on clinical risk, coronary calcium and epicardial adipose tissue: a prospective study - Commandeur, F. C.; Slomka, P. J.; Göller, Markus; Chen, X.; Cadet, S.; Razipour, A.; Gransar, H.; Cantu, S.; Miller, R.; Rozanski, A.; Achenbach, Stephan; Tamarappoo, B.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Machine learning to predict the long-term risk of myocardial infarction and cardiac death based on clinical risk, coronary calcium, and epicardial adipose tissue: a prospective study - Commandeur, Frederic; Slomka, Piotr J.; Göller, Markus; Chen, Xi; Cadet, Sebastien; Razipour, Aryabod; McElhinney, Priscilla; Gransar, Heidi; Cantu, Stephanie; Miller, Robert J.H.; Rozanski, Alan; Achenbach, Stephan; et al. (Cardiovascular Research, 2020)
AIMS: Our aim was to evaluate the performance of machine learning (ML), integrating clinical parameters with coronary artery calcium (CAC), and automated epicardial adipose tissue (EAT) quantification, for the prediction of long-term risk of myocardial infarction (MI) and cardiac death in asymptomatic subjects. METHODS AND RESULTS: Our study included 1912 asymptomatic subjects [1117 (58.4%) male, age: 55.8 ± 9.1 years] from the prospective EISNER trial with long-term follow-up after CAC scoring. EAT volume and density were quantified using a fully automated deep learning method. ML extreme gradient boosting was trained using clinical co-variates, plasma lipid panel measurements, risk factors, CAC, aortic calcium, and automated EAT measures, and validated using repeated 10-fold cross validation. During mean follow-up of 14.5 ± 2 years, 76 events of MI and/or cardiac death occurred. ML obtained a significantly higher AUC than atherosclerotic cardiovascular disease (ASCVD) risk and CAC score for predicting events (ML: 0.82; ASCVD: 0.77; CAC: 0.77, P < 0.05 for all). Subjects with a higher ML score (by Youden's index) had high hazard of suffering events (HR: 10.38, P < 0.001); the relationships persisted in multivariable analysis including ASCVD-risk and CAC measures (HR: 2.94, P = 0.005). Age, ASCVD-risk, and CAC were prognostically important for both genders. Systolic blood pressure was more important than cholesterol in women, and the opposite in men. CONCLUSIONS: In this prospective study, machine learning used to integrate clinical and quantitative imaging-based variables significantly improves prediction of MI and cardiac death compared with standard clinical risk assessment. Following further validation, such a personalized paradigm could potentially be used to improve cardiovascular risk assessment.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Coronary calcium scoring; Epicardial adipose tissue; Machine learning; Myocardial infarction and cardiac death

Macromolecular interactions in alginate-gelatin hydrogels regulate the behavior of human fibroblasts - Sarker, Bapi; Singh, Raminder; Zehnder, Tobias; Forgber, Tim; Alexiou, Christoph; Cicha, Iwona; Detsch, Rainer; Boccaccini, Aldo R. (Journal of Bioactive and Compatible Polymers, 2017)
Keywords: alginate; fibroblast; gelatin; Hydrogels; tissue engineering

Magmaris vs. DESolve: a comparison study of acute mechanical performance using optical coherence tomography - Boeder, N. F.; Doerr, O.; Gaderer, R.; Bauer, T.; Elsaesser, A.; Achenbach, Stephan; Moellmann, H.; Hamm, C.; Nef, H. M. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Magnetic nanoparticles for magnetic drug targeting - Lyer, Stefan; Singh, Raminder; Tietze, Rainer; Alexiou, Christoph (Biomedizinische Technik, 2015)
Nanomedicine and superparamagnetic iron oxide nanoparticles (SPIONs) are thought to have an important impact on medicine in the future. Especially in cancer therapy, SPIONs offer the opportunity of improving the effectivity of the treatment and reduce side effects by magnetic accumulation of SPION-bound chemotherapeutics in the tumor area. Although still some challenges have to be overcome, before the new treatment concept of magnetic drug targeting will reach the patients, substantial progress has been made, and promising results were shown in the last years.
EVALuna2:20014

Magnetic nanoparticles for medical applications - Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33163

Magnetic resonance phase contrast velocity mapping for flow quantification in irregular heart rhythms using radial k-space ultrashort echo time imaging - Hell, Michaela; Francis, Jane M.; d'Arcy, Joanna; Robson, Matthew D.; Neubauer, Stefan; Achenbach, Stephan; Myerson, Saul G. (International Journal of Cardiology, 2020)
Background: Phase contrast velocity mapping sequences utilising ultrashort echo time (UTE) radial k-space sequences have been used to reduce intravoxel dephasing at high velocities. We evaluated the accuracy of the UTE flow sequence for mitral regurgitation (MR) quantification, including patients with atrial fibrillation. Methods: Forty patients underwent cardiac MRI for indirect MR quantification by assessment of aortic flow using a UTE phase contrast sequence (TE 0.65 ms) combined with left ventricular stroke volume. Retrospective ECG-gating was used in sinus rhythm (30 patients), prospective ECG-triggering in atrial fibrillation (10). MR was also quantified by a standard phase contrast sequence (TE 2.85 ms, standard flow method) and by comparing stroke volumes (volumetric method). Results: UTE flow-derived MR measurement showed modest agreement in sinus rhythm (95% limits of agreement: ±38.2 ml; ±29.8%) and atrial fibrillation (±33.7 ml; ±30.3%) compared to standard flow assessment. There was little systematic bias in sinus rhythm (mean offset −4.4 ml /−3.5% compared to standard flow assessment), but a slight bias towards greater regurgitation in atrial fibrillation (+15.2 ml /+14.0%). There were wider limits of agreement between the UTE flow method and volumetric method than between the regular flow method and the volumetric method in sinus rhythm (±48.4 ml; ±36.4%; mean offset: −12.2 ml /−9.0%) and similar limits of agreement in atrial fibrillation (±29.6 ml; 25.8%; +12.0 ml /+10.3%). Conclusions: UTE flow imaging is inferior to conventional flow techniques for MR assessment in patients with sinus rhythm as well as atrial fibrillation. However, the number of atrial fibrillation patients in this initial study is small.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Atrial fibrillation; ultrashort echo time imaging; Cardiac magnetic resonance; Flow imaging; Mitral regurgitation

Major coronary evaginations following implantation of bioresorbable vascular scaffolds: clinical and OCT characteristics - Blachutzik, F.; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, R.; Weissner, M.; Schlundt, Christian; Marwan, Mohamed (2017)
EVALuna2:36025

Major coronary evaginations following implantation of bioresorbable vascular scaffolds - Clinical and OCT characteristics - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Nef, Holger; Weissner, Melissa; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2019)
Background: Coronary evaginations can occur after implantation of bioresorbable vascular scaffolds (BRS) and may be associated with scaffold thrombosis. Aim of this study was to clarify the clinical manifestation, extent and time course of coronary artery remodeling in vessel segments that develop angiographically detectable evaginations following BRS implantation through optical coherence tomography (OCT) analysis.
CRIS-Team WoS Importer:2019-06-18

Management of patients with severe aortic stenosis in the TAVI-era: How recent recommendations are translated into clinical practice - Lauten, Alexander; Rudolph, Tanja K.; Messika-Zeitoun, David; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Frey, Norbert; Maly, Jiri; Aiello, Marco; Lloyd, Guy; Bortone, Alessandro Santo; Clerici, Alberto; et al. (Open Heart, 2021)
Objective Approximately 3.4% of adults aged >75 years suffer from aortic stenosis (AS). Guideline indications for aortic valve replacement (AVR) distinguish between patients with symptomatic and asymptomatic severe AS. The present analysis aims to assess contemporary practice in the treatment of severe AS across Europe and identify characteristics associated with treatment decisions, namely denial of AVR in symptomatic patients and assignment of asymptomatic patients to AVR. Methods Participants of the prospective, multinational IMPULSE database of patients with severe AS were grouped according to AS symptoms, and stratified into subgroups based on assignment to/denial of AVR. Results Of 1608 symptomatic patients, 23.8% did not undergo AVR and underwent medical treatment. Denial was independently associated with multiple factors, including severe frailty (p=0.024); mitral (p=0.002) or tricuspid (p=0.004) regurgitation grade III/IV, and the presence of renal impairment (p=0.017). Of 392 asymptomatic patients, 86.5% had no prespecified indication for AVR. Regardless, 36.3% were assigned to valve replacement. Those with an indexed aortic valve area (AVA; p=0.045) or left ventricular ejection fraction (LVEF; p<0.001) below the study median; or with a left ventricular end systolic diameter above the study median (p=0.007) were more likely to be assigned to AVR. Conclusions There may be considerable discrepancies between guideline-based recommendations and clinical practice decision-making in the treatment of AS. It appears that guidelines may not fully capture the complete clinical spectrum of patients with AS. Thus, there is a need to find ways to increase their acceptance and the rate of adoption.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aortic valve stenosis; cardiac surgical procedures; transcatheter aortic valve replacement

Management of stable chronic coronary artery disease - Achenbach, Stephan (Herz, 2015)
Stable coronary artery disease is one of the most frequent conditions encountered in cardiology. The diagnostic algorithm encompasses several steps, the first of which is a clinical assessment with an electrocardiogram (ECG) and echocardiography to determine the probability of disease. No further work-up is recommended if the probability of coronary artery disease remains below 15 %. For patients with an intermediate probability between 15 % and 85 %, noninvasive diagnostic testing for ischemia and coronary computed tomography (CT) angiography are recommended. In the case of a positive result, medicinal therapy should be started in order to lower the event risk and alleviate symptoms. Patients with large areas of inducible ischemia and patients who remain symptomatic in spite of medicinal therapy should undergo invasive angiography. Revascularization options include bypass surgery and, more liberally than previously, percutaneous coronary intervention with stent placement and must be decided on the basis of patient characteristics. Consultation in the form of a "heart team" is recommended. After revascularization, medicinal therapy must be continued on a lifelong basis. The widely practiced routine of annual ischemia testing in patients with known coronary artery disease is not enforced by current guidelines.
EVALuna2:12084

Management of therapeutic anticoagulation in patients with intracerebral haemorrhage and mechanical heart valves - Kuramatsu, Joji; Sembill, Jochen; Gerner, Stefan; Sprügel, Maximilian; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (European Heart Journal, 2018)
Aims Evidence is lacking regarding acute anticoagulation management in patients after intracerebral haemorrhage (ICH) with implanted mechanical heart valves (MHVs). Our objective was to investigate anticoagulation reversal and resumption strategies by evaluating incidences of haemorrhagic and thromboembolic complications, thereby defining an optimal time-window when to restart therapeutic anticoagulation (TA) in patients with MHV and ICH. Methods and results We pooled individual patient- data (n = 2504) from a nationwide multicentre cohort-study (RETRACE, conducted at 22 German centres) and eventually identified MHV-patients (n = 137) with anticoagulation-associated ICH for outcome analyses. The primary outcome consisted of major haemorrhagic complications analysed during hospital stay according to treatment exposure (restarted TA vs. no-TA). Secondary outcomes comprised thromboembolic complications, the composite outcome (haemorrhagic and thromboembolic complications), timing of TA, and mortality. Adjusted analyses involved propensity-score matching and multivariable cox-regressions to identify optimal timing of TA. In 66/137 (48%) of patients TA was restarted, being associated with increased haemorrhagic (TA = 17/66 (26%) vs. no-TA = 4/71 (6%); P < 0.01) and a trend to decreased thromboembolic complications (TA = 1/66 (2%) vs. no-TA = 7/71 (10%); P = 0.06). Controlling treatment crossovers provided an incidence rate-ratio [hazard ratio (HR) 10.31, 95% confidence interval (CI) 3.67-35.70; P < 0.01] in disadvantage of TA for haemorrhagic complications. Analyses of TA-timing displayed significant harm until Day 13 after ICH (HR 7.06, 95% CI 2.33-21.37; P < 0.01). The hazard for the composite-balancing both complications, was increased for restarted TA until Day 6 (HR 2.51, 95% CI 1.10-5.70; P = 0.03). Conclusion Restarting TA within less than 2 weeks after ICH in patients with MHV was associated with increased haemorrhagic complications. Optimal weighing-between least risks for thromboembolic and haemorrhagic complications-provided an earliest starting point of TA at Day 6, reserved only for patients at high thromboembolic risk.
EVALuna2:34917

Manual der Arbeitsgruppe Interventionelle Kardiologie (AGIK) der Deutschen Gesellschaft für Kardiologie – Herz- und Kreislaufforschung e. V. (DGK), Teil 1: „Durchführung der diagnostischen Herzkatheteruntersuchung“ - Nef, Holger M.; Achenbach, Stephan; Birkemeyer, Ralf; Bufe, Alexander; Doerr, Oliver; Elsaesser, Albrecht; Gaede, Luise; Gori, Tommaso; Hoffmeister, Hans M.; Hofmann, Felix J.; Katus, Hugo A.; Liebetrau, Christoph; et al. (Der Kardiologe, 2021)
This manual on diagnostic cardiac catheterization (part 1) is a recommendation for application by interventional cardiologists, which reflects the latest evidence in interventional cardiology. Each chapter was designed to focus on the everyday practicability and to provide decision support in the daily clinical routine of the catheter laboratory. Despite the practical advice by many experts, this manual cannot replace the medical evaluation of each individual patient and thus an adaptation of the diagnostics or treatment is necessary.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Acute coronary syndrome; Cardiovascular disease; Catheter laboratory; Coronary angiography; PCI

Manual der Arbeitsgruppe Interventionelle Kardiologie (AGIK) der Deutschen Gesellschaft für Kardiologie – Herz- und Kreislaufforschung e.V. (DGK) - Teil 2: „Durchführung der perkutanen Koronarintervention“ - Nef, Holger M.; Achenbach, Stephan; Birkemeyer, Ralf; Bufe, Alexander; Doerr, Oliver; Elsaesser, Albrecht; Gaede, Luise; Gori, Tommaso; Hoffmeister, Hans M.; Hofmann, Felix J.; Katus, Hugo A.; Liebetrau, Christoph; et al. (Der Kardiologe, 2021)
This manual addressing the interventional treatment (part 2) is a recommendation for interventional cardiologists. It displays the latest evidence in interventional cardiology. Each chapter was designed to focus on the everyday practicability and to provide decision support for cardiologists in the daily clinical routine of a catheter laboratory. Despite the practical advice by many experts, this manual cannot replace the medical evaluation of each individual patient and thus an adaptation of the diagnostics or treatment is necessary.
CRIS-Team WoS Importer:2021-10-08

Maximization of the usage of coronary CTA derived plaque information using a machine learning based algorithm to improve risk stratification; insights from the CONFIRM registry - Van Rosendael, Alexander R.; Maliakal, Gabriel; Kolli, Kranthi K.; Beecy, Ashley; Al'Aref, Subhi J.; Dwivedi, Aeshita; Singh, Gurpreet; Panday, Mohit; Kumar, Amit; Ma, Xiaoyue; Achenbach, Stephan; Al-Mallah, Mouaz H.; et al. (Journal of Cardiovascular Computed Tomography, 2018)
INTRODUCTION: Machine learning (ML) is a field in computer science that demonstrated to effectively integrate clinical and imaging data for the creation of prognostic scores. The current study investigated whether a ML score, incorporating only the 16 segment coronary tree information derived from coronary computed tomography angiography (CCTA), provides enhanced risk stratification compared with current CCTA based risk scores. METHODS: From the multi-center CONFIRM registry, patients were included with complete CCTA risk score information and ≥3 year follow-up for myocardial infarction and death (primary endpoint). Patients with prior coronary artery disease were excluded. Conventional CCTA risk scores (conventional CCTA approach, segment involvement score, duke prognostic index, segment stenosis score, and the Leaman risk score) and a score created using ML were compared for the area under the receiver operating characteristic curve (AUC). Only 16 segment based coronary stenosis (0%, 1-24%, 25-49%, 50-69%, 70-99% and 100%) and composition (calcified, mixed and non-calcified plaque) were provided to the ML model. A boosted ensemble algorithm (extreme gradient boosting; XGBoost) was used and the entire data was randomly split into a training set (80%) and testing set (20%). First, tuned hyperparameters were used to generate a trained model from the training data set (80% of data). Second, the performance of this trained model was independently tested on the unseen test set (20% of data). RESULTS: In total, 8844 patients (mean age 58.0 ± 11.5 years, 57.7% male) were included. During a mean follow-up time of 4.6 ± 1.5 years, 609 events occurred (6.9%). No CAD was observed in 48.7% (3.5% event), non-obstructive CAD in 31.8% (6.8% event), and obstructive CAD in 19.5% (15.6% event). Discrimination of events as expressed by AUC was significantly better for the ML based approach (0.771) vs the other scores (ranging from 0.685 to 0.701), P < 0.001. Net reclassification improvement analysis showed that the improved risk stratification was the result of down-classification of risk among patients that did not experience events (non-events). CONCLUSION: A risk score created by a ML based algorithm, that utilizes standard 16 coronary segment stenosis and composition information derived from detailed CCTA reading, has greater prognostic accuracy than current CCTA integrated risk scores. These findings indicate that a ML based algorithm can improve the integration of CCTA derived plaque information to improve risk stratification.
EVALuna2:35993

MCS-18, a natural product isolated from Helleborus purpurascens, inhibits maturation of dendritic cells in ApoE-deficient mice and prevents early atherosclerosis progression - Dietel, Barbara; Muench, Rabea; Kühn, Constanze; Kerek, Franz; Steinkasserer, Alexander; Achenbach, Stephan; Garlichs, Christoph; Zinser, Elisabeth (Atherosclerosis, 2014)
Inflammation accelerates both plaque progression and instability in the pathogenesis of atherosclerosis. The inhibition of dendritic cell (DC) maturation is a promising approach to suppress excessive inflammatory immune responses and has been shown to be protective in several autoimmune models. The aim of this study was to investigate the immune modulatory effects of the natural substance MCS-18, an inhibitor of DC maturation, regarding the progression of atherosclerosis in ApoE-deficient mice.ApoE-deficient mice were fed for twelve weeks with a Western-type diet (n = 32) or normal chow (control group; n = 16). Animals receiving high-fat diet were treated with MCS-18 (500 ?g/kg body weight, n = 16) or saline (n = 16) twice a week. After 12 weeks, animals were transcardially perfused and sacrificed. The percentage of mature DCs (CD3(-)/CD19(-)/CD14(-)/NK1.1(-)/CD11c(+)/MHCII(+)/CD83(+)/CD86(+)) and T cell subpopulations (CD4(+)/CD25(+)/Foxp3(+), CD3/CD4/CD8) was analyzed in peripheral blood and in the spleen using flow cytometry. Plaque size was determined in the aortic root and the thoracoabdominal aorta using en-face staining. Immunohistochemical stainings served to detect inflammatory cells in the aortic root. Several cytokines and chemokines were determined in serum using multiplex assays.In splenic cells derived from saline-treated atherosclerotic mice an increased DC maturation, reflected by the upregulation of CD83 and CD86 expression, was observed. The enhanced expression of both maturation markers was absent in MCS-18 treated atherosclerotic mice. While the percentage of splenic Foxp3 expressing Treg was increased in animals receiving MCS-18 compared to saline-treated atherosclerotic mice, cytotoxic T cells were reduced in the spleen and in atherosclerotic lesions of the aortic root. Furthermore, proatherogenic cytokines (e.g. IL-6 and IFN-?) and chemokines (e.g. MIP-1?) were decreased in serum of MCS-18-treated animals when compared to saline-treated atherosclerotic mice. Also plaque size in the aortic root and the thoracoabdominal aorta was significantly lower following administration of MCS-18.This study provides for the first time evidence that MCS-18 is able to prevent the onset of atherosclerosis in ApoE-deficient mice. The observed anti-atherogenic effect is associated with the suppression of DC maturation and an inhibited migration and proliferation of cytotoxic T cells.
EVALuna2:11981

Medical care of adults with congenital heart diseases : Present and future - Neidenbach, R.; Achenbach, Stephan; Andonian, C.; Beckmann, J.; Biber, S.; Dittrich, Sven; Ewert, P.; Freilinger, S.; Huntgeburth, M.; Nagdyman, N.; Oberhoffer, R.; Pieper, L.; et al. (Herz, 2019)
Congenital heart diseases (CHD) are the most common types of congenital organ defects. Thanks to medical progress in congenital cardiology and heart surgery, most children with CHD reach adulthood. Despite primarily successful treatment residual and subsequent conditions as well as (non)cardiac comorbidities can influence the chronic course of the disease and lead to a higher morbidity and mortality. Adults with congenital heart disease (ACHD) in Germany are not tied to the healthcare structure despite the great need for aftercare. According to the results of the medical care of ACHD (MC-ACHD) study, ACHD centers and specialists in Germany are insufficiently perceived despite increased complication rates and the great need for specialist guidance. General practitioners and patients are not adequately informed about existing ACHD facilities. A better awareness of the ACHD problem should be created at the level of primary medical supply in order to optimize care and to reduce morbidity and mortality. Improved future-oriented patient care includes lifelong regular follow-up and the possibility of interdisciplinary, integrated medical care of CHD.
EVALuna2:212989

Medical emergencies on board commercial passenger flights: what you need to know : An ESC TV Today interview with Lufthansa Physician Dr Thomas Schmitt - Achenbach, Stephan; Price, Susanna; Schmitt, Thomas (European Heart Journal, 2023)
CRIS-Team Scopus Importer:2023-09-08

Medical history for prognostic risk assessment and diagnosis of stable patients with suspected coronary artery disease - Min, James K.; Dunning, Allison; Gransar, Heidi; Achenbach, Stephan; Lin, Fay Y.; Al-Mallah, Mouaz; Budoff, Matthew J.; Callister, Tracy Q.; Chang, Hyuk-Jae; Cademartiri, Filippo; Maffei, Erica; Chinnaiyan, Kavitha; et al. (American Journal of Medicine, 2015)
To develop a clinical cardiac risk algorithm for stable patients with suspected coronary artery disease based upon angina typicality and coronary artery disease risk factors.Between 2004 and 2011, 14,004 adults with suspected coronary artery disease referred for cardiac imaging were followed: 1) 9093 patients for coronary computed tomography angiography (CCTA) followed for 2.0 years (CCTA-1); 2) 2132 patients for CCTA followed for 1.6 years (CCTA-2); and 3) 2779 patients for exercise myocardial perfusion scintigraphy (MPS) followed for 5.0 years. A best-fit model from CCTA-1 for prediction of death or myocardial infarction was developed, with integer values proportional to regression coefficients. Discrimination was assessed using C-statistic. The validated model was tested for estimation of the likelihood of obstructive coronary artery disease, defined as >=50% stenosis, as compared with the method of Diamond and Forrester. Primary outcomes included all-cause mortality and nonfatal myocardial infarction. Secondary outcomes included prevalent angiographically obstructive coronary artery disease.In CCTA-1, best-fit model discriminated individuals at risk of death or myocardial infarction (C-statistic 0.76). The integer model ranged from 3 to 13, corresponding to 3-year death risk or myocardial infarction of 0.25% to 53.8%. When applied to CCTA-2 and MPS cohorts, the model demonstrated C-statistics of 0.71 and 0.77, respectively. Both best-fit (C = 0.76; 95% confidence interval [CI], 0.746-0.771) and integer models (C = 0.71; 95% CI, 0.693-0.719) performed better than Diamond and Forrester (C = 0.64; 95% CI, 0.628-0.659) for estimating obstructive coronary artery disease.For stable symptomatic patients with suspected coronary artery disease, we developed a history-based method for prediction of death and obstructive coronary artery disease.
EVALuna2:12073

Medizinische Versorgung von Erwachsenen mit angeborenen Herzfehlern: Gegenwart und Zukunft - Neidenbach, R.; Achenbach, Stephan; Andonian, C.; Beckmann, J.; Biber, S.; Dittrich, Sven; Ewert, P.; Freilinger, S.; Huntgeburth, M.; Nagdyman, N.; Oberhoffer, R.; Pieper, L.; et al. (Herz, 2019)
Congenital heart diseases (CHD) are the most common types of congenital organ defects. Thanks to medical progress in congenital cardiology and heart surgery, most children with CHD reach adulthood. Despite primarily successful treatment residual and subsequent conditions as well as (non)cardiac comorbidities can influence the chronic course of the disease and lead to a higher morbidity and mortality. Adults with congenital heart disease (ACHD) in Germany are not tied to the healthcare structure despite the great need for aftercare. According to the results of the medical care of ACHD (MC-ACHD) study, ACHD centers and specialists in Germany are insufficiently perceived despite increased complication rates and the great need for specialist guidance. General practitioners and patients are not adequately informed about existing ACHD facilities. A better awareness of the ACHD problem should be created at the level of primary medical supply in order to optimize care and to reduce morbidity and mortality. Improved future-oriented patient care includes lifelong regular follow-up and the possibility of interdisciplinary, integrated medical care of CHD.
CRIS-Team Scopus Importer:2019-08-06
Keywords: ACHD; Cardiology; Comorbidities; Congenital heart defects; Prevention

Membranous septum length as predictor for permanent pacemaker implantation after TAVI - Jung, Susan; Ammon, Fabian; Smolka, Silvia; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Meta-Analysis of Bioprosthetic Valve Thrombosis After Transcatheter Aortic Valve Implantation - Rheude, Tobias; Pellegrini, Costanza; Stortecky, Stefan; Xhepa, Erion; Ammon, Fabian; Pilgrim, Thomas; Mayr, N. Patrick; Husser, Oliver; Achenbach, Stephan; Windecker, Stephan; Cassese, Salvatore; Joner, Michael; et al. (American Journal of Cardiology, 2020)
Bioprosthetic valve thrombosis may complicate transcatheter aortic valve implantation (TAVI). This meta-analysis sought to evaluate the prevalence and clinical impact of subclinical leaflet thrombosis (SLT) and clinical valve thrombosis (CVT) after TAVI. We summarized diagnostic strategies, prevalence of SLT and/or CVT and estimated their impact on the risk of all-cause death and stroke. Twenty studies with 12,128 patients were included. The prevalence of SLT and CVT was 15.1% and 1.2%, respectively. The risk of all-cause death was not significantly different between patients with SLT (relative risk [RR] 0.77; p = 0.22) and CVT (RR 1.29; p = 0.68) compared with patients without. The risk of stroke was higher in patients with CVT (RR 7.51; p <0.001) as compared with patients without, while patients with SLT showed no significant increase in the risk of stroke (RR 1.81; p = 0.17). Reduced left ventricular function was associated with increased prevalence, while oral anticoagulation was associated with reduced prevalence of bioprosthetic valve thrombosis. Bioprosthetic valve thrombosis is frequent after TAVI, but does not increase the risk of death. Clinical valve thrombosis is associated with a significantly increased risk of stroke. Future studies should focus on prevention and treatment of bioprosthetic valve thrombosis.
CRIS-Team Scopus Importer:2020-11-06

Meta-analysis of effect of single versus dual antiplatelet therapy on early patency of bypass conduits after coronary artery bypass grafting - Nocerino, Angelica G.; Achenbach, Stephan; Taylor, Allen J. (American Journal of Cardiology, 2013)
Aspirin monotherapy represents a standard therapy for preserving patency after coronary artery bypass grafting. Randomized trials addressing whether dual antiplatelet therapy is superior to single antiplatelet therapy to achieve graft patency early after coronary surgery have shown inconsistent results. We performed a meta-analysis of randomized controlled trials comparing single versus dual antiplatelet therapy after coronary artery bypass grafting. In a systematic published works search, 5 randomized controlled trials meeting inclusion criteria were identified. Pooled efficacy and safety data were abstracted and analyzed using a fixed-effects model. The 5 trials included 958 patients and a total of 2,919 grafts with treatment up to 1 year after coronary bypass surgery. Early occlusion was identified in 165 (6.5%) of 2,526 bypass grafts. Early occlusion occurred in a greater proportion of grafts among patients treated with single therapy (105 of 1,369; 7.7%) compared with dual antiplatelet therapy (69 of 1,386; 5.0%; p = 0.005). The odds ratio for graft occlusion with single versus dual therapy was 1.59 (95% confidence interval 1.16 to 2.17). For vein grafts, single antiplatelet therapy was associated with a significantly increased graft loss rate (91 of 846; 10.8%) versus dual antiplatelet therapy (57 of 860; 6.6%; odds ratio 1.70 [1.20 to 2.40]; p = 0.003). There was no effect on arterial graft patency. Bleeding was noted in 3.3% and 4.9% of single and dual therapy treated patients, respectively, with only 3 trials reporting bleeding outcomes. In conclusion, among 958 patients randomly assigned to either single or dual antiplatelet therapy for up to 1 year after coronary bypass surgery, single antiplatelet therapy significantly increased the risk for graft occlusion, an effect isolated to vein grafts, not arterial grafts. © 2013 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08

Mid-regional atrial natriuretic peptide and C-terminal pro-endothelin-1 for early diagnosis of acute heart failure in unselected older patients presenting to the emergency department - Bahrmann, Philipp; Bertsch, T.; Bahrmann, A.; Christ, M.; Achenbach, Stephan; Sieber, Cornel (European Heart Journal, 2013)

Mild therapeutic hypothermia after out-of-hospital cardiac arrest complicating ST-elevation myocardial infarction: Long-term results in clinical practice - Zimmermann, Stefan; Flachskampf, Frank A.; Schneider, Reinhard; Dechant, Katharina; Alff, Anna; Klinghammer, Lutz; Rittger, Harald; Achenbach, Stephan (Clinical Cardiology, 2013)
Background Recently, mild therapeutic hypothermia (MTH) has been integrated into the European resuscitation guidelines to improve outcomes after out-of-hospital cardiac arrest (OHCA). Data on long-term results are limited, especially in patients with acute ST-elevation myocardial infarction (STEMI). Hypothesis Invasive MTH influences long-term prognosis after OHCA due to STEMI. Methods We analyzed 48 patients who underwent emergency coronary angiography for STEMI after witnessed OHCA. In 24 consecutive patients, MTH was performed via intravascular cooling (CoolGard System, 34°C maintained for 24 hours) after initialization by rapid infusion of cold saline. Clinical, procedural, and mortality data were compared to 24 historical controls. Neurological recovery was assessed using the Cerebral Performance Category score (CPC) at 30-day and 1-year follow-up. Results Median time delay until arrival of emergency medical service was 6 minutes (MTH group) vs 6.5 minutes (controls) (P = 0.16). Initial rhythm was ventricular fibrillation in 75% vs 66.7% (P = 0.75). There were no differences regarding baseline characteristics, angiographic findings, and success of cardiac catheterization procedures. MTH was not associated with a higher frequency of bleeding complications or of pneumonia. Thirty-day mortality was 33.3% in both groups. One-year mortality was 37.5% (MTH group) vs 50% (controls) (P = 0.56). At 1 year, favorable neurological outcome (CPC ≤2) was significantly more frequent in the MTH group (58.3% vs 20.8%, P = 0.017). Multivariate analysis identified MTH as independent predictor of favorable neurological outcome (P < 0.02, odds ratio: 12.73). Conclusions MTH via intravascular cooling improves neurological long-term prognosis after OHCA due to STEMI and is safe in clinical practice. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08

Mitoxantrone-loaded superparamagnetic iron oxide nanoparticles as drug carriers for cancer therapy: Uptake and toxicity in primary human tubular epithelial cells - Cicha, Iwona; Scheffler, Laura; Ebenau, Astrid; Lyer, Stefan; Alexiou, Christoph; Goppelt-Strübe, Margarete (Nanotoxicology, 2016)
Superparamagnetic iron oxide nanoparticles (SPIONs) are in use for many clinical diagnostic and experimental therapeutic applications, for example, for targeted drug delivery. To analyze the cellular responses to mitoxantrone-carrying SPIONs (SPION-MTO), and to the drug released from SPIONs, we used an in vitro system that allows comparison of primary human cells with different endocytotic capacities, namely, epithelial cells from proximal and distal parts of the nephron. SPIONs were selectively and rapidly internalized by proximal tubular cells with high endocytotic potential, but not by distal tubular cells. Uptake did not affect cell viability or morphology. In both cell types, free MTO (10-100 nM) induced double-strand DNA breaks and senescence, cell hypertrophy and reduced cell proliferation. However, cadherin-mediated cell-cell adhesion, cytoskeletal structures or polarity of the cells were not affected. Interestingly, a comparable response was also observed upon treatment with SPION-MTO and was independent of uptake of the particles. The effect of SPION-MTO on cells which did not internalize particles was primarily related to the release of MTO from drug-coated particles upon incubation in serum-containing cell growth medium. In conclusion, we show that whereas the uptake of SPIONs does not affect cellular functions or viability, the toxicity of drug-loaded SPIONs depends essentially on the type of drug bound to nanoparticles. Due to the relatively low systemic toxicity of MTO, the effects of MTO-SPIONs on human tubular cells were moderate, but they may become clinically relevant when more nephrotoxic drugs are bound to SPIONs.
EVALuna2:3835

Mitral valve leaflet repair with the new PASCAL system: early real-world data from a German multicentre experience - Kriechbaum, Steffen D.; Boeder, Niklas F.; Gaede, Luise; Vigelius-Rauch, Ursula; Roth, Peter; Sander, Michael; Böning, Andreas; Bayer, Matthias; Elsässer, Albrecht; Möllmann, Helge; Hamm, Christian W.; Nef, Holger M.; et al. (Clinical Research in Cardiology, 2019)
Aims: To examine the clinical experience and practical use of the PASCAL transcatheter valve repair system (Edwards Lifesciences, Irvine, CA, USA) and to report some of the first clinical results. Methods and results: A total of 18 consecutive patients with severe, symptomatic mitral regurgitation (MR) were included in this German multicentre registry. All patients underwent clinical, echocardiographic, and laboratory assessment prior to the PASCAL procedure and before hospital discharge. MR was classified as functional in 6 patients, degenerative in 2, and combined in 10. All except one received a single PASCAL implant. The preprocedural severe MR present in all patients was reduced: grade 0 in 4 (22.2%), grade I in 11 (61.1%), grade II in 3 (16.7%). The v-wave was significantly reduced from 31.7 ± 9.5 to 18 ± 7.7 mmHg (p < 0.001). Independent leaflet capture, performed in 4 (22.2%) of the patients, wide clasps, and the 10-mm central spacer are features of the PASCAL device to optimize mitral leaflet repair. There were no periprocedural complications. Conclusion: PASCAL is a safe and effective mitral valve repair device for the treatment of severe MR. Device-specific features allow valve repair tailored to the individual anatomy of the underlying mitral pathology in each patient. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2019-10-22
Keywords: Leaflet repair; Mitral regurgitation; Mitral valve disease; Mitral valve repair

Multi-Center Comparison of Two Self-Expanding Transcatheter Heart Valves: A Propensity Matched Analysis - Blumenstein, Johannes; Eckel, Clemens; Husser, Oliver; Kim, Won-Keun; Renker, Matthias; Choi, Yeong-Hoon; Hamm, Christian W.; Al-Terki, Hani; Soetemann, Dagmar; Koerbi, Leon; Tiyerili, Vedat; Grothusen, Christina; et al. (Journal of Clinical Medicine, 2022)
Background: During the last years, several transcatheter aortic heart valves entered the clinical market and are commercially available. The prostheses differ regarding several technical and functional aspects. However, little is known regarding head-to-head comparative data of the ACURATE neo and the PORTICO valve prostheses. Objectives: The aim of this study was to compare two self-expanding transcatheter aortic heart valves (THV), the ACURATE neo and the PORTICO, with regard to in-hospital and 30-day outcomes, as well as early device failures. Methods: A total of 1591 consecutive patients with severe native aortic valve stenosis from two centers were included in the analyses and matched by 1:1 nearest neighbor matching to identify one patient treated with PORTICO (n = 344) for each patient treated with ACURATE neo (n = 344). Results: In-hospital complications were comparable between both valves, including any kind of stroke (ACURATE neo = 3.5% vs. PORTICO = 3.8%; p = 1.0), major vascular complications (ACURATE neo = 4.5% vs. PORTICO = 5.4%; p = 0.99) or life-threatening bleeding (ACURATE neo = 1% vs. PORTICO = 2%; p = 0.68). The rate of device failure defined by the VARC-2 criteria were comparable, including elevated gradients and moderate-to-severe paravalvular leakage (ACURATE neo = 7.3% vs. PORTICO = 7.6%; p = 1.0). However, the need for permanent pacemaker implantation (PPI) was significantly more frequent after the use of PORTICO THV (9.5% vs. 18.7%; p = 0.002). Conclusions: In this two-center case-matched comparison, short-term clinical and hemodynamic outcomes showed comparable results between PORTICO and ACURATE neo prostheses. However, PORTICO was associated with a significant higher incidence of PPI.
CRIS-Team WoS Importer:2022-08-12

Multicenter Evaluation Of Coronary Dual-Source CT angiography in patients with intermediate Risk of Coronary Artery Stenoses (MEDIC): study design and rationale - Hausleiter, Jörg; Abbara, Suhny; Hoffmann, Udo; Becker, Christoph; Ovrehus, Kristian; Ropers, Dieter; Bathina, Ravi; Berman, Dan; Anders, Katharina; Uder, Michael; Meave, Aloha; Alexánderson, Erick; et al. (Journal of Cardiovascular Computed Tomography, 2014)
The diagnostic performance of multidetector row CT to detect coronary artery stenosis has been evaluated in numerous single-center studies, with only limited data from large cohorts with low-to-intermediate likelihood of coronary disease and in multicenter trials. The Multicenter Evaluation of Coronary Dual-Source CT Angiography in Patients with Intermediate Risk of Coronary Artery Stenoses (MEDIC) trial determines the accuracy of dual-source CT (DSCT) to identify persons with at least 1 coronary artery stenosis among patients with low-to-intermediate pretest likelihood of disease.The MEDIC trial was designed as a prospective, multicenter, international trial to evaluate the diagnostic performance of DSCT for the detection of coronary artery stenosis compared with invasive coronary angiography. The study includes 8 sites in Germany, India, Mexico, the United States, and Denmark. The study population comprises patients referred for a diagnostic coronary angiogram because of suspected coronary artery disease with an intermediate pretest likelihood as determined by sex, age, and symptoms. All evaluations are performed by blinded core laboratory readers.The primary outcome of the MEDIC trial is the accuracy of DSCT to identify the presence of coronary artery stenoses with a luminal diameter narrowing of 50% or more on a per-vessel basis. Secondary outcome parameters include per-patient and per-segment diagnostic accuracy for 50% stenoses and accuracy to identify stenoses of 70% or more. Furthermore, secondary outcome parameters include the influence of heart rate, Agatston score, body weight, body mass index, image quality, and diagnostic confidence on the accuracy to detect coronary artery stenoses >50% on a per-vessel basis.The results of the MEDIC trial will assess the clinical utility of coronary CT angiography in the evaluation of patients with intermediate pretest likelihood of coronary artery disease.
EVALuna2:14371

Multicenter International Society for Immunotherapy of Cancer Study of the Consensus Immunoscore for the Prediction of Survival and Response to Chemotherapy in Stage III Colon Cancer - Mlecnik, Bernhard; Bifulco, Carlo; Bindea, Gabriela; Marliot, Florence; Lugli, Alessandro; Lee, J. Jack; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Borger, Elisa; Hartmann, Arndt; et al. (Journal of Clinical Oncology, 2020)
PURPOSEThe purpose of this study was to evaluate the prognostic value of Immunoscore in patients with stage III colon cancer (CC) and to analyze its association with the effect of chemotherapy on time to recurrence (TTR).METHODSAn international study led by the Society for Immunotherapy of Cancer evaluated the predefined consensus Immunoscore in 763 patients with American Joint Committee on Cancer/Union for International Cancer Control TNM stage III CC from cohort 1 (Canada/United States) and cohort 2 (Europe/Asia). CD3+ and cytotoxic CD8+ T lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The primary end point was TTR. Secondary end points were overall survival (OS), disease-free survival (DFS), prognosis in microsatellite stable (MSS) status, and predictive value of efficacy of chemotherapy.RESULTSPatients with a high Immunoscore presented with the lowest risk of recurrence, in both cohorts. Recurrence-free rates at 3 years were 56.9% (95% CI, 50.3% to 64.4%), 65.9% (95% CI, 60.8% to 71.4%), and 76.4% (95% CI, 69.3% to 84.3%) in patients with low, intermediate, and high immunoscores, respectively (hazard ratio [HR; high v low], 0.48; 95% CI, 0.32 to 0.71; P = .0003). Patients with high Immunoscore showed significant association with prolonged TTR, OS, and DFS (all P < .001). In Cox multivariable analysis stratified by participating center, Immunoscore association with TTR was independent (HR [high v low], 0.41; 95% CI, 0.25 to 0.67; P = .0003) of patient's sex, T stage, N stage, sidedness, and microsatellite instability status. Significant association of a high Immunoscore with prolonged TTR was also found among MSS patients (HR [high v low], 0.36; 95% CI, 0.21 to 0.62; P = .0003). Immunoscore had the strongest contribution 2 proportion for influencing survival (TTR and OS). Chemotherapy was significantly associated with survival in the high-Immunoscore group for both low-risk (HR [chemotherapy v no chemotherapy], 0.42; 95% CI, 0.25 to 0.71; P = .0011) and high-risk (HR [chemotherapy v no chemotherapy], 0.5; 95% CI, 0.33 to 0.77; P = .0015) patients, in contrast to the low-Immunoscore group (P > .12).CONCLUSIONThis study shows that a high Immunoscore significantly associated with prolonged survival in stage III CC. Our findings suggest that patients with a high Immunoscore will benefit the most from chemotherapy in terms of recurrence risk.
CRIS-Team WoS Importer:2020-11-27

Multicenter International Study of the Consensus Immunoscore for the Prediction of Relapse and Survival in Early-Stage Colon Cancer - Mlecnik, Bernhard; Lugli, Alessandro; Bindea, Gabriela; Marliot, Florence; Bifulco, Carlo; Lee, Jiun Kae Jack; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Börger, Elisa; Hartmann, Arndt; et al. (Cancers, 2023)
Background: The prognostic value of Immunoscore was evaluated in Stage II/III colon cancer (CC) patients, but it remains unclear in Stage I/II, and in early-stage subgroups at risk. An international Society for Immunotherapy of Cancer (SITC) study evaluated the pre-defined consensus Immunoscore in tumors from 1885 AJCC/UICC-TNM Stage I/II CC patients from Canada/USA (Cohort 1) and Europe/Asia (Cohort 2). METHODS: Digital-pathology is used to quantify the densities of CD3+ and CD8+ T-lymphocyte in the center of tumor (CT) and the invasive margin (IM). The time to recurrence (TTR) was the primary endpoint. Secondary endpoints were disease-free survival (DFS), overall survival (OS), prognosis in Stage I, Stage II, Stage II-high-risk, and microsatellite-stable (MSS) patients. RESULTS: High-Immunoscore presented with the lowest risk of recurrence in both cohorts. In Stage I/II, recurrence-free rates at 5 years were 78.4% (95%-CI, 74.4–82.6), 88.1% (95%-CI, 85.7–90.4), 93.4% (95%-CI, 91.1–95.8) in low, intermediate and high Immunoscore, respectively (HR (Hi vs. Lo) = 0.27 (95%-CI, 0.18–0.41); p < 0.0001). In Cox multivariable analysis, the association of Immunoscore to outcome was independent (TTR: HR (Hi vs. Lo) = 0.29, (95%-CI, 0.17–0.50); p < 0.0001) of the patient’s gender, T-stage, sidedness, and microsatellite instability-status (MSI). A significant association of Immunoscore with survival was found for Stage II, high-risk Stage II, T4N0 and MSS patients. The Immunoscore also showed significant association with TTR in Stage-I (HR (Hi vs. Lo) = 0.07 (95%-CI, 0.01–0.61); P = 0.016). The Immunoscore had the strongest (69.5%) contribution χ2 for influencing survival. Patients with a high Immunoscore had prolonged TTR in T4N0 tumors even for patients not receiving chemotherapy, and the Immunoscore remained the only significant parameter in multivariable analysis. CONCLUSION: In early CC, low Immunoscore reliably identifies patients at risk of relapse for whom a more intensive surveillance program or adjuvant treatment should be considered.
CRIS-Team Scopus Importer:2023-02-03
Keywords: colon cancer; early-stage; Immunoscore; predictive biomarkers; prognosis; tumor microenvironment

Multimodality imaging: bird's eye view from The European Society of Cardiology Congress 2014 Barcelona, August 30-September 3, 2014 - Bax, Jeroen J.; Delgado, Victoria; Achenbach, Stephan; Sechtem, Udo; Knuuti, Juhani (Journal of Nuclear Cardiology, 2014)
EVALuna2:11998

Multimodality imaging: Bird's eye view from The European Society of Cardiology Congress 2015 London, August 29-September 2, 2015 - Bax, Jeroen J.; Delgado, Victoria; Achenbach, Stephan; Sechtem, Udo; Knuuti, Juhani (Journal of Nuclear Cardiology, 2015)
EVALuna2:12092

Multimodality imaging: Bird's eye view from The European Society of Cardiology Congress 2016 : Rome, August 27-31, 2016 - Bax, Jeroen J.; Delgado, Victoria; Achenbach, Stephan; Plein, Sven; Kaufmann, Philipp A. (Journal of Nuclear Cardiology, 2017)
EVALuna2:33651

Multimodality imaging: Bird's eye view from The European Society of Cardiology Congress 2017, Barcelona, August 26-30, 2017 - Bax, Jeroen J.; Delgado, Victoria; Plein, Sven; Knuuti, Juhani; Achenbach, Stephan (Journal of Nuclear Cardiology, 2018)
EVALuna2:33584

Multimodality imaging in cardiology: a statement on behalf of the Task Force on Multimodality Imaging of the European Association of Cardiovascular Imaging - Fox, Kevin; Achenbach, Stephan; Bax, Jeroen; Cosyns, Bernard; Delgado, Victoria; Dweck, Marc R.; Edvardsen, Thor; Flachskampf, Frank; Habib, Gilbert; Lancellotti, Patrizio; Muraru, Denisa; Neglia, Danilo; et al. (European Heart Journal, 2019)
CRIS-Team WoS Importer:2019-03-06

Multiple biomarkers for risk stratification of unselected older patients in the emergency department - Bahrmann, Philipp; Bahrmann, A.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bertsch, T. (European Heart Journal, 2015)

Multiple biomarker strategy for improved diagnosis of acute heart failure in older patients presenting to the emergency department - Bahrmann, Philipp; Bahrmann, Anke; Hofner, Benjamin; Christ, Michael; Achenbach, Stephan; Sieber, Cornel; Bertsch, Thomas (European Heart Journal: Acute Cardiovascular Care, 2015)
Biomarkers can help to identity acute heart failure (AHF) as the cause of symptoms in patients presenting to the emergency department (ED). Older patients may prove a diagnostic challenge due to co-morbidities. Therefore we prospectively investigated the diagnostic performance of N-terminal pro-B-type natriuretic peptide (NT-proBNP) alone or in combination with other biomarkers for AHF upon admission at the ED.302 non-surgical patients aged >= 70 years were consecutively enrolled upon admission to the ED. In addition to NT-proBNP, mid-regional pro-adrenomedullin (MR-proADM), mid-regional pro-atrial natriuretic peptide (MR-proANP), C-terminal pro-endothelin-1 (CT-proET-1) and ultra-sensitive C-terminal pro-vasopressin (Copeptin-us) were measured at admission. Two cardiologists independently adjudicated the final diagnosis of AHF after reviewing all available baseline data excluding the biomarkers. We assessed changes in C-index, integrated discrimination improvement (IDI), and net reclassification improvement (NRI) for the multimarker approach.AHF was diagnosed in 120 (40%) patients (age 81±6 years, 64 men, 56 women). Adding MR-ADM to NT-proBNP levels improved C-index (0.84 versus 0.81; p=0.045), and yielded IDI (3.3%; p=0.002), NRI (17%, p<0.001) and continuous NRI (33.3%; p=0.002). Adding CT-proET-1 to NT-proBNP levels improved C index (0.86 versus 0.81, p=0.031), and yielded robust IDI (12.4%; p<0.001), NRI (31.3%, p<0.001) and continuous NRI (69.9%; p<0.001). No other dual or triple biomarker combination showed a significant improvement of both C-index and IDI.In older patients presenting to the ED, the addition of CT-proET-1 or MR-proADM to NT-proBNP improves diagnostic accuracy of AHF. Both dual biomarker approaches offer significant risk reclassification improvement over NT-proBNP.
EVALuna2:5476

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Myocardial adaptation to high-intensity (interval) training in previously untrained men with a longitudinal cardiovascular magnetic resonance imaging study (Running Study and Heart Trial) - Scharf, Michael; Schmid, Axel; Kemmler, Wolfgang; von Stengel, Simon; May, Matthias; Wüst, Wolfgang; Achenbach, Stephan; Uder, Michael; Lell, Michael (Circulation: Cardiovascular Imaging, 2015)
To prospectively evaluate whether short-term high-intensity (interval) training (HI(I)T) induces detectable morphological cardiac changes in previously untrained men in cardiovascular magnetic resonance imaging.Eighty-four untrained volunteers were randomly assigned to a HI(I)T group (n=42; 44.1±4.7 years) or an inactive control group (n=42; 42.3±5.6 years). HI(I)T focused on interval runs (intensity: 95%-105% of individually calculated heart rate at the anaerobic threshold). Before and after 16 weeks, all subjects underwent physiological examination, stepwise treadmill test with blood lactate analysis, and contrast-enhanced cardiovascular magnetic resonance imaging (cine, tagging, and delayed enhancement). Indexed left ventricular (LV) and right ventricular (RV) volume (LV, 77.1±8.5-83.9±8.6; RV, 80.5±8.5-86.6±8.1) and mass (LV, 58.2±6.4-63.4±8.1; RV, 14.8±1.7-16.1±2.1) significantly increased with HI(I)T. Changes in LV and RV morphological parameters with HI(I)T were highly correlated with an increase in maximal aerobic capacity (VO2max) and a decrease in blood lactate concentration at the anaerobic threshold. Mean LV and RV remodeling index of HI(I)T group did not alter with training (0.76 ±0.09 and 0.24±0.10 g/mL, respectively [P=0.97 and P=0.72]), indicating balanced cardiac adaptation. Myocardial circumferential strain decreased after HI(I)T within all 6 basal segments (anteroseptal, P=0.01 and anterolateral, P<0.001). There was no late gadolinium enhancement in any of the participants before or post HI(I)T.Sixteen weeks of HI(I)T lead to measurable changes in cardiac atrial and ventricular morphology and function in previously untrained men. This correlates with improvements in parameters of endurance capacity.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01406730.
EVALuna2:10107

Myocardial revascularization Controversy over noninvasive and invasive detection of ischemia - Gaede, Luise; Blumenstein, Johannes; Moellmann, Helge (Herz, 2022)
With some exceptions, myocardial revascularization in patients with chronic coronary syndrome (CCS) is generally decided on the basis of the extent of myocardial ischemia. Current data indicate that a patient will benefit from revascularization if ischemia is present in more than 10% of the myocardium. Accordingly, all patients presenting with CCS should undergo a noninvasive ischemia test that can answer this question before diagnostic coronary angiography. In order to be able to make a recommendation for revascularization based on scientific data even in those patients who previously had no clear evidence of ischemia, e.g., because of discrepant findings, measurement of the hemodynamic significance of coronary stenoses with a lumen diameter reduction >= 50% should be performed during coronary angiography. A decision to revascularize based on hemodynamic significance was shown to be beneficial to patients in several studies.
CRIS-Team WoS Importer:2022-05-13

Myocardial Twist from X-ray Angiography - Geimer, Tobias; Unberath, Mathias; Höhn, Johannes; Achenbach, Stephan; Maier, Andreas (Bildverarbeitung für die Medizin 2018 - Algorithmen - Systeme - Anwendungen, 2018)
We present preliminary evidence that left ventricular twist can be observed and thus estimated from rotational coronary angiography. Our method is based on an ellipsoidal parametric model initially developed for functional analysis of cardiac tagged MRI. First, we fit the model to 3D coronary artery centerlines reconstructed from rotational angiography and then use 3D/2D registration to optimize for the functional parameters driving the model. On two clinical acquisitions, we show that our method is able to recover cardiac motion indicated by an average reduction in reprojection error of 28.1±3.0 %. Analysis of the functional progression of the functional parameters over time reveals radial and longitudinal contraction, and left ventricular twist. We believe that these results are exciting and encourage improvement of the proposed method in future work.<br
UnivIS-Import:2018-09-06:Pub.2018.tech.IMMD.IMMD5.myocar

Myokines and Resistance Training: A Narrative Review - Zunner, Beate E.M.; Wachsmuth, Nadine B.; Eckstein, Max L.; Scherl, Lukas; Schierbauer, Janis R.; Haupt, Sandra; Stumpf, Christian; Reusch, Laura; Moser, Othmar (International Journal of Molecular Sciences, 2022)
In the last few years, the muscular system has gained attention due to the discovery of the muscle-secretome and its high potency for retaining or regaining health. These cytokines, described as myokines, released by the working muscle, are involved in anti-inflammatory, metabolic and immunological processes. These are able to influence human health in a positive way and are a target of research in metabolic diseases, cancer, neurological diseases, and other non-communicable diseases. Therefore, different types of exercise training were investigated in the last few years to find associations between exercise, myokines and their effects on human health. Particularly, resistance training turned out to be a powerful stimulus to enhance myokine release. As there are different types of resistance training, different myokines are stimulated, depending on the mode of training. This narrative review gives an overview about resistance training and how it can be utilized to stimulate myokine production in order to gain a certain health effect. Finally, the question of why resistance training is an important key regulator in human health will be discussed.
CRIS-Team Scopus Importer:2022-04-01
Keywords: BDNF; IL-6; Irisin; Myokine; Myostatin; PGC-1 alpha; Resistance training

Nano-biomaterials for cardiovascular applications: Clinical perspective - Cicha, Iwona; Singh, Raminder; Garlichs, Christoph D.; Alexiou, Christoph (Journal of Controlled Release, 2016)
Cardiovascular diseases, including ischemic heart disease and stroke, are responsible for nearly 25% of all deaths worldwide. Globally, their prevalence continues to increase, in spite of enormous progress in cardiovascular diagnostics and therapy. For therapeutic and regenerative purposes, biomaterials promise solutions with multiple advantages over synthetic materials. Furthermore, their easy availability as nanoformulations recommends their application as drug carriers or protective nanoshells improving the biocompatibility of imaging agents. In this work, we review the most promising and clinically meaningful scientific reports with regard to (nano)biomaterials with particular focus on potential improvements of existing, and development of novel constructs for cardiovascular applications.
EVALuna2:20019

Nanomedical innovation: the SEON-concept for an improved cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Unterweger, Harald; Zaloga, Jan; Singh, Raminder; Matuszak, Jasmin; Poettler, Marina; Friedrich, Ralf P.; Dürr, Stephan; Cicha, Iwona; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
Nanomedicine offers tremendous opportunities for the development of novel therapeutic and diagnostic tools. During the last decades, extensive knowledge was gained about stabilizing and the coating of nanoparticles, their functionalization for drug binding and drug release and possible strategies for therapies and diagnostics of different diseases. Most recently, more and more emphasis has been placed on nanotoxicology and nanosafety aspects. The section of experimental oncology and nanomedicine developed a concept for translating this knowledge into clinical application of magnetic drug targeting for the treatment of cancer and other diseases using superparamagnetic iron oxide nanoparticles. This approach includes reproducible synthesis, detailed characterization, nanotoxicological testing, evaluation in ex vivo models, preclinical animal studies and production of superparamagnetic iron oxide nanoparticles according to good manufacturing practice regulations.
EVALuna2:19990

Nanoparticles for intravascular applications: physicochemical characterization and cytotoxicity testing - Matuszak, Jasmin; Baumgartner, Jens; Zaloga, Jan; Juenet, Maya; Da Silva, Acarilia Eduardo; Franke, Danielle; Almer, Gunter; Texier, Isabelle; Faivre, Damien; Metselaar, Josbert M.; Navarro, Fabrice P.; Chauvierre, Cedric; et al. (Nanomedicine, 2016)
We report the physicochemical analysis of nanosystems intended for cardiovascular applications and their toxicological characterization in static and dynamic cell culture conditions.Size, polydispersity and ?-potential were determined in 10 nanoparticle systems including liposomes, lipid nanoparticles, polymeric and iron oxide nanoparticles. Nanoparticle effects on primary human endothelial cell viability were monitored using real-time cell analysis and live-cell microscopy in static conditions, and in a flow model of arterial bifurcations.The majority of tested nanosystems were well tolerated by endothelial cells up to the concentration of 100 ?g/ml in static, and up to 400 ?g/ml in dynamic conditions. Pilot experiments in a pig model showed that intravenous administration of liposomal nanoparticles did not evoke the hypersensitivity reaction. These findings are of importance for future clinical use of nanosystems intended for intravascular applications.
EVALuna2:20021

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

New ESC heart failure guideline - significance for general practitioners. - Tröbs, Monique; Achenbach, Stephan (MMW Fortschritte der Medizin, 2017)
EVALuna2:36043

No Difference in 30-Day Outcome and Quality of Life in Transradial Versus Transfemoral Access - Results From the German Austrian ABSORB Registry (GABI-R). - Wein, Bastian; Zaczkiewicz, Myron; Graf, Matthias; Zimmermann, Oliver; Gori, Tommaso; Nef, Holger M.; Kastner, Johannes; Mehilli, Julinda; Richardt, Gert; Wöhrle, Jochen; Achenbach, Stephan; Riemer, Thomas; et al. (Cardiovascular Revascularization Medicine, 2022)
BACKGROUND: Radial (RA) instead of femoral access (FA) for coronary interventions has become a European Society of Cardiology Class-IA guideline recommendation. But when the decision on the access site is left to the discretion of the operator, differences in adverse event rates mitigate. METHODS: We compared the 30-day outcome for RA and FA in all patients recruited for the observational German Austrian ABSORB Registry (GABI-R) in regard to all-cause mortality, stroke, myocardial infarction (MI), TIMI major bleedings (TMB) and quality of life (QoL). All patients were treated with a bioresorbable vascular scaffold. Access site was left to the discretion of the operator. RESULTS: In total, 3137 patients included by 92 centers received percutaneous coronary interventions (PCI) for acute MI in 51.5% and non-acute settings in 48.5%. RA was performed in 47.8% and had a higher median radiation exposure (3896 vs. 3082 cGycm2, p < 0.001). There was no difference in the amount of contrast used. There was also no difference in all-cause mortality (0.53% vs. 0.49%, p = 0.86), the combination of death, MI and stroke (1.87% vs. 1.83%, p = 0.94), but a trend towards more TMB (0.47% vs. 1.04%, p = 0.07) with FA. These outcomes were consistent across the subgroups of patients with ST-elevation MI, non-ST-elevation-ACS and stable coronary artery disease. Finally, QoL did not differ between RA and FA. CONCLUSIONS: In this contemporary GABI-R cohort, in which access site was left to the discretion of the operator, both access routes were safe and equal concerning QoL (ClinicalTrials.gov; NCT02066623).
EVALuna2:482646

Noncalcified Plaque in Cardiac CT: Quantification and Clinical Implications - Hell, Michaela; Achenbach, Stephan; Shah, Prediman K.; Berman, Daniel S.; Dey, Damini (Current Cardiovascular Imaging Reports, 2015)
Coronary computed tomography angiography (CTA) is being increasingly used for direct, noninvasive evaluation of the coronary arteries. Beyond stenosis, coronary CTA also permits assessment of atherosclerotic plaque (including total and noncalcified plaque burden) and coronary artery remodeling, previously only measurable through invasive techniques. It has been shown that coronary plaque volume for noncalcified and mixed plaques and the arterial remodeling index correlate closely with corresponding measures from invasive intravascular ultrasound. Several studies have also shown a strong relationship between adverse plaque features imaged by coronary CTA and acute coronary syndrome, major adverse cardiovascular events, and ischemia. The aim of this review is to summarize current methods for quantitative measurement of atherosclerotic plaque features from coronary CTA and to discuss the clinical implications of noncalcified plaque as detected by CTA and reported in the current literature.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary artery plaque; Coronary computed tomography angiography; Noncalcified plaque; Plaque characterization; Plaque quantification

Non-immunogenic dextran-coated superparamagnetic iron oxide nanoparticles: a biocompatible, size-tunable contrast agent for magnetic resonance imaging - Unterweger, Harald; Janko, Christina; Schwarz, Marc; Dezsi, Laszlo; Urbanics, Rudolf; Matuszak, Jasmin; Orfi, Erik; Fülöp, Tamás; Bäuerle, Tobias; Szebeni, Janos; Journe, Clement; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2017)

Non-invasive cardiac Imaging in the Diagnosis of CAD - Marwan, Mohamed (Deutsche Medizinische Wochenschrift, 2021)
CRIS-Team WoS Importer:2021-09-03

Non-invasive computed fractional flow reserve from computed tomography (CT) for diagnosing coronary artery disease - Japanese results from NXT trial (Analysis of Coronary Blood Flow Using CT Angiography: Next Steps) - Miyoshi, Toru; Osawa, Kazuhiro; Ito, Hiroshi; Kanazawa, Susumu; Kimura, Takeshi; Shiomi, Hiroki; Kuribayashi, Sachio; Jinzaki, Masahiro; Kawamura, Akio; Bezerra, Hiram; Achenbach, Stephan; Norgaard, Bjarne L. (Circulation Journal, 2015)
Recently, a non-invasive method using computational fluid dynamics to calculate vessel-specific fractional flow reserve (FFRCT) from routinely acquired coronary computed tomography angiography (CTA) was described. The Analysis of Coronary Blood Flow Using CT Angiography: Next Steps (NXT) trial, which was a prospective, multicenter trial including 254 patients with suspected coronary artery disease, noted high diagnostic performance of FFRCT compared with invasive FFR. The aim of this post-hoc analysis was to assess the diagnostic performance of non-invasive FFRCT vs. standard stenosis quantification on coronary CTA in the Japanese subset of the NXT trial.A total of 57 Japanese participants were included from Okayama University (n=36), Kyoto University (n=17), and Keio University (n=4) Hospitals. Per-patient diagnostic accuracy of FFRCT(74%; 95% confidence interval [CI]: 60-85%) was higher than for coronary CTA (47%; 95% CI: 34-61%, P<0.001) arising from improved specificity (63% vs. 27%, P<0.001). FFRCT correctly reclassified 53% of patients and 63% of vessels with coronary CTA false positives as true negatives. When patients with Agatston score >1,000 were excluded, per-patient accuracy of FFRCT was 83% with a high specificity of 76%, similar to the overall NXT trial findings.FFRCT has high diagnostic performance compared with invasive FFR in the Japanese subset of patients in the NXT trial.
EVALuna2:12059

Non-invasive detection of coronary inflammation using computed tomography and prediction of residual cardiovascular risk (the CRISP CT study): a post-hoc analysis of prospective outcome data - Oikonomou, Evangelos K.; Desai, Milind Y.; Mancio, Jennifer; Alashi, Alaa; Centeno, Erika Hutt; Thomas, Sheena; Herdman, Laura; Kotanidis, Christos P.; Thomas, Katharine E.; Griffin, Brian P.; Flamm, Scott D.; Antonopoulos, Alexios S.; et al. (Lancet, 2018)
BACKGROUND: Coronary artery inflammation inhibits adipogenesis in adjacent perivascular fat. A novel imaging biomarker-the perivascular fat attenuation index (FAI)-captures coronary inflammation by mapping spatial changes of perivascular fat attenuation on coronary computed tomography angiography (CTA). However, the ability of the perivascular FAI to predict clinical outcomes is unknown. METHODS: In the Cardiovascular RISk Prediction using Computed Tomography (CRISP-CT) study, we did a post-hoc analysis of outcome data gathered prospectively from two independent cohorts of consecutive patients undergoing coronary CTA in Erlangen, Germany (derivation cohort) and Cleveland, OH, USA (validation cohort). Perivascular fat attenuation mapping was done around the three major coronary arteries-the proximal right coronary artery, the left anterior descending artery, and the left circumflex artery. We assessed the prognostic value of perivascular fat attenuation mapping for all-cause and cardiac mortality in Cox regression models, adjusted for age, sex, cardiovascular risk factors, tube voltage, modified Duke coronary artery disease index, and number of coronary CTA-derived high-risk plaque features. FINDINGS: Between 2005 and 2009, 1872 participants in the derivation cohort underwent coronary CTA (median age 62 years [range 17-89]). Between 2008 and 2016, 2040 patients in the validation cohort had coronary CTA (median age 53 years [range 19-87]). Median follow-up was 72 months (range 51-109) in the derivation cohort and 54 months (range 4-105) in the validation cohort. In both cohorts, high perivascular FAI values around the proximal right coronary artery and left anterior descending artery (but not around the left circumflex artery) were predictive of all-cause and cardiac mortality and correlated strongly with each other. Therefore, the perivascular FAI measured around the right coronary artery was used as a representative biomarker of global coronary inflammation (for prediction of cardiac mortality, hazard ratio [HR] 2·15, 95% CI 1·33-3·48; p=0·0017 in the derivation cohort, and 2·06, 1·50-2·83; p<0·0001 in the validation cohort). The optimum cutoff for the perivascular FAI, above which there is a steep increase in cardiac mortality, was ascertained as -70·1 Hounsfield units (HU) or higher in the derivation cohort (HR 9·04, 95% CI 3·35-24·40; p<0·0001 for cardiac mortality; 2·55, 1·65-3·92; p<0·0001 for all-cause mortality). This cutoff was confirmed in the validation cohort (HR 5·62, 95% CI 2·90-10·88; p<0·0001 for cardiac mortality; 3·69, 2·26-6·02; p<0·0001 for all-cause mortality). Perivascular FAI improved risk discrimination in both cohorts, leading to significant reclassification for all-cause and cardiac mortality. INTERPRETATION: The perivascular FAI enhances cardiac risk prediction and restratification over and above current state-of-the-art assessment in coronary CTA by providing a quantitative measure of coronary inflammation. High perivascular FAI values (cutoff ≥-70·1 HU) are an indicator of increased cardiac mortality and, therefore, could guide early targeted primary prevention and intensive secondary prevention in patients. FUNDING: British Heart Foundation, and the National Institute of Health Research Oxford Biomedical Research Centre.
EVALuna2:35969

Noninvasive Fractional Flow Reserve Derived From Coronary CT Angiography: Clinical Data and Scientific Principles - Min, James K.; Taylor, Charles A.; Achenbach, Stephan; Koo, Bon Kwon; Leipsic, Jonathon; Norgaard, Bjarne L.; Pijls, Nico J.; De Bruyne, Bernard (Journal of the American College of Cardiology : Cardiovascular imaging, 2015)
Fractional flow reserve derived from coronary computed tomography angiography enables noninvasive assessment of the hemodynamic significance of coronary artery lesions and coupling of the anatomic severity of a coronary stenosis with its physiological effects. Since its initial demonstration of feasibility of use in humans in 2011, a significant body of clinical evidence has developed to evaluate the diagnostic performance of coronary computed tomography angiography-derived fractional flow reserve compared with an invasive fractional flow reserve reference standard. The purpose of this paper was to describe the scientific principles and to review the clinical data of this technology recently approved by the U.S. Food and Drug Administration.
EVALuna2:12070

Non-invasive imaging as the cornerstone of cardiovascular precision medicine - Achenbach, Stephan; Fuchs, Friedrich; Goncalves, Alexandra; Kaiser-Albers, Claudia; Ali, Ziad A.; Bengel, Frank M.; Dimmeler, Stefanie; Fayad, Zahi A.; Mebazaa, Alexandre; Meder, Benjamin; Narula, Jagat; Shah, Amil; et al. (European Heart Journal - Cardiovascular Imaging, 2022)
Aims To provide an overview of the role of cardiovascular (CV) imaging in facilitating and advancing the field of precision medicine in CV disease. Methods and results Non-invasive CV imaging is essential to accurately and efficiently phenotype patients with heart disease, including coronary artery disease (CAD) and heart failure (HF). Various modalities, such as echocardiography, nuclear cardiology, cardiac computed tomography (CT), cardiovascular magnetic resonance (CMR), and invasive coronary angiography, and in some cases a combination, can be required to provide sufficient information for diagnosis and management. Taking CAD as an example, imaging is essential for the detection and functional assessment of coronary stenoses, as well as for the quantification of cardiac function and ischaemic myocardial damage. Furthermore, imaging may detect and quantify coronary atherosclerosis, potentially identify plaques at increased risk of rupture, and guide coronary interventions. In patients with HF, imaging helps identify specific aetiologies, quantify damage, and assess its impact on cardiac function. Imaging plays a central role in individualizing diagnosis and management and to determine the optimal treatment for each patient to increase the likelihood of response and improve patient outcomes. Conclusions Advances in all imaging techniques continue to improve accuracy, sensitivity, and standardization of functional and prognostic assessments, and identify established and novel therapeutic targets. Combining imaging with artificial intelligence, machine learning and computer algorithms, as well as with genomic, transcriptomic, proteomic, and metabolomic approaches, will become state of the art in the future to understand pathologies of CAD and HF, and in the development of new, targeted therapies.
CRIS-Team WoS Importer:2022-04-08

Non-invasive measurement of coronary plaque from coronary CT angiography and its clinical implications - Dey, Damini; Schuhbaeck, Annika; Min, James K.; Berman, Daniel S.; Achenbach, Stephan (Expert Review of Cardiovascular Therapy, 2013)
Coronary CT angiography (CTA) is increasingly used worldwide for direct, non-invasive evaluation of the coronary arteries. Advances in computed tomography (CT) technology over the last decade have enabled such reliable imaging of the coronary arteries. Beyond arterial stenosis, coronary CTA also permits assessment of atherosclerotic plaque (including plaque burden) and coronary artery remodeling, previously only achievable through invasive means. It has been shown that coronary plaque volumes for non-calcified and mixed plaques and the arterial remodeling index, correlate closely with invasive intravascular ultrasound. Several studies have also shown a strong relationship of adverse plaque features imaged by coronary CTA with acute coronary syndrome, all-cause death, major adverse cardiovascular events and myocardial ischemia. The aim of this review is to summarize current methods for quantitative measurement of atherosclerotic plaque features from coronary CTA and to discuss their clinical implications. © 2013 Informa UK Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: acute coronary syndrome; coronary CT angiography; coronary plaque; lipid-lowering therapy; major adverse cardiovascular events; myocardial ischemia; prognosis

Non-invasive prediction of hemodynamically significant coronary artery stenoses by contrast density difference in coronary CT angiography - Hell, Michaela M.; Dey, Damini; Achenbach, Stephan; Schmid, Jasmin; Schuhbaeck, Annika; Marwan, Mohamed (European Journal of Radiology, 2015)
Coronary computed tomography angiography (CTA) allows the detection of obstructive coronary artery disease. However, its ability to predict the hemodynamic significance of stenoses is limited. We assessed differences in plaque characteristics and contrast density difference between hemodynamically significant and non-significant stenoses, as defined by invasive fractional flow reserve (FFR).Lesion characteristics of 59 consecutive patients (72 lesions) in whom invasive FFR was performed in at least one coronary artery with moderate to high-grade stenoses in coronary CTA were evaluated by two experienced readers. Coronary CTA data sets were acquired on a second-generation dual-source CT scanner using retrospectively ECG-gated spiral acquisition or prospectively ECG-triggered axial acquisition mode. Plaque volume and composition (non-calcified, calcified), remodeling index as well as contrast density difference (defined as the percentage decline in luminal CT attenuation/cross-sectional area over the lesion) were assessed using a semi-automatic software tool (Autoplaq). Additionally, the transluminal attenuation gradient (defined as the linear regression coefficient between intraluminal CT attenuation and length from the ostium) was determined. Differences in lesion characteristics between hemodynamically significant (invasively measured FFR <=0.80) and non-significant lesions (FFR >0.80) were determined.Mean patient age was 64±11 years with 44 males (75%). 21 out of 72 coronary artery lesions (29%) were hemodynamically significant according to invasive FFR. Mean invasive FFR was 0.66±0.12 vs. 0.91±0.05 for hemodynamically significant versus non-significant lesions. Hemodynamically significant lesions showed a significantly greater percentage of non-calcified plaque compared to non-hemodynamically relevant lesions (51.3±15.3% vs. 43.6±16.5%, p=0.021). Contrast density difference was significantly increased in hemodynamically relevant lesions (26.0±20.2% vs. 16.6±10.9% for non-significant lesions; p=0.013). At a threshold of >=24%, the contrast density difference predicted hemodynamically significant lesions with a specificity of 75%, sensitivity of 33%, PPV of 35% and NPV of 73%. The transluminal attenuation gradient showed no significant difference between hemodynamically significant and non-significant lesions (-1.4±1.4HU/mm vs. -1.1±1.3HU/mm, p=n.s.).Quantitative contrast density difference across coronary lesions in coronary CTA data sets may be applied as a non-invasive tool to identify hemodynamically significant stenoses.
EVALuna2:12090

Novel nanoparticulate drug delivery systems - Friedrich, Ralf P.; Pöttler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2016)
EVALuna2:33375

Novel nanosystems to combat atherosclerosis: Functional effects on human endothelial and monocytic cells - Cicha, Iwona; Matuszak, Jasmin; Juenet, M.; Chauvierre, Cedric; Texier, I.; Almer, G.; Prassl, R.; Metselaar, J.; Dezsi, L.; Urbanics, R.; Szebeni, J.; Alexiou, Christoph; et al. (2016)
EVALuna2:33162

Novel three-dimensional imaging approach for cryoballoon navigation and confirmation of pulmonary vein occlusion - Kowalewski, Christopher; Rodrigo, Miguel; Brodt, Chad; Haddad, Francois; Wang, Paul J.; Narayan, Sanjiv M. (Pace-Pacing and Clinical Electrophysiology, 2020)
Background Cryoballoon apposition is crucial for durable pulmonary vein isolation (PVI) in atrial fibrillation, yet the balloon is difficult to visualize by conventional mapping systems, and pulmonary venography may miss small or out-of-plane leaks. We report a novel imaging system that offers real-time 3D navigation of the cryoballoon within atrial anatomy that may circumvent these issues.
CRIS-Team WoS Importer:2020-03-03

OCT-assessment of scaffold resorption: Analysis of strut intensity by a new resorption index for poly-l-lactic acid bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Boeder, Niklas; Doerr, Oliver; Weissner, Melissa; Bauer, Timm; Nef, Holger; Hamm, Christian; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: The aim of this study was to analyze individual differences in resorption of bioresorbable vascular scaffolds (BRS) through optical coherence tomography (OCT) analysis and to identify factors potentially influencing the resorption process. Methods: Between April 2016 and July 2017 clinically driven invasive coronary angiography and OCT examinations were performed in 36 patients who had previously been treated with a total of 48 BRS (ABSORB BVS, Abbott Vascular, Santa Clara, CA). For each scaffold, a new BRS-RESORB-INDEX (BRI) was calculated. Results: The mean time interval since implantation was 789 ± 321 days. In OCT, BRS struts remained detectable in all 48 BRS. Normalized light intensity as a marker for the resorption of BRS struts increased with time in a linear fashion (Spearman Rho: p <.001, correlation coefficient =.90; R 2 [linear] =.91). Multivariable analysis identified diabetes (BRI of patients with diabetes vs. patients without diabetes: 0.34 ± 0.13 vs. 0.58 ± 0.22; p =.002) and presence of Peri-strut low intensity areas (PSLIA, BRI of 10 patients with PSLIA vs. 26 patients without PSLIA: 0.44 ± 0.21 vs. 0.61 ± 18; p =.027) as independent predictors for a prolonged BRS resorption, whereas the resorption rate in ACS patients (STEMI, NSTEMI, and unstable angina; n = 13) was significantly higher as compared to patients without ACS (0.62 ± 0.17 vs. 0.43 ± 0.24; p =.012). Conclusion: In humans, BRS resorption rate is significantly influenced by numerous factors. Our data suggest that diabetes and PSLIA are associated with a prolonged resorption process, whereas in ACS patients, BRS resorption appears to be significantly faster.
CRIS-Team Scopus Importer:2019-12-13
Keywords: bioresorbable vascular scaffolds; optical coherence tomography; percutaneous coronary intervention

OCT-assessment of scaffold resorption: analysis of strut intensity via the brs-resorb-index for poly-L-lactic acid bioresorbable vascular scaffolds - Blachutzik, F.; Achenbach, Stephan; Tröbs, Monique; Weissner, M.; Nef, H.; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Optical coherence tomography: influence of contrast concentration on image quality and diagnostic confidence - Blachutzik, Florian; Achenbach, Stephan; Nef, Holger; Hamm, Christian; Dorr, Oliver; Boeder, Niklas; Tröbs, Monique; Schneider, Reinhard; Röther, Jens; Schlundt, Christian; Marwan, Mohamed (Heart and Vessels, 2017)
OCT requires intracoronary injection of contrast agent to remove blood from the coronary lumen during data acquisition, which is a possible limitation of this method. Aim of this study was to analyze the influence of iodine concentration on image quality and diagnostic certainty of optical coherence tomography (OCT). OCT sequences acquired using contrast agent with a reduced concentration of 150 mg iodine/ml and a standard concentration of 350 mg iodine/ml were analyzed. Cross-sectional images with a spacing of 10 mm were evaluated regarding image quality and diagnostic confidence. A total of 67 OCT sequences acquired in 24 patients were analyzed. 31 sequences were acquired using contrast agent with a concentration of 150 mg iodine/ml and 36 sequences with a concentration of 350 mg iodine/ml. The percentage of remaining blood streaks in the cross sections was significantly lower for 350 mg iodine/ml compared to 150 mg iodine/ml (19 ± 21 vs. 34 ± 26%, p = 0.013). Contrast with 350 mg iodine/ml showed a significantly higher percentage of completely flushed pullback length as compared to 150 mg iodine/ml (78 ± 24 vs. 58 ± 27%, p = 0.004). Diagnostic certainty was significantly higher for 350 mg iodine/ml than for 150 mg iodine/ml (Likert scale average 1.4 ± 0.7 vs. 2.1 ± 1.2, p < 0.001; Likert scale: 1 = absolutely confident, 2 = confident with slight doubts, 3 = doubtful/not confident, 4 = non-diagnostic). Regarding image quality and diagnostic certainty, contrast agent with a concentration of 350 mg iodine/ml is superior to 150 mg iodine/ml.
EVALuna2:33638

Optimal Vessel Sizing for the Bioresorbable Scaffold Implantation and the Incidence of Scaffold Thrombosis: Insights From the COMPARE-ABSORB Trial - Chang, Chun-Chin; Onuma, Yoshinobu; Chevalier, Bernard; West, Nick; Gori, Tommaso; Barbato, Emanuele; Tarantini, Giuseppe; Kocka, Viktor; Achenbach, Stephan; Dudek, Dariusz; Escaned, Javier; Abdel-Wahab, Mohamed; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Optimization of cell seeding on electrospun PCL-silk fibroin scaffolds - Singh, Raminder; Eitler, David; Morelle, René; Friedrich, Ralf P.; Dietel, Barbara; Alexiou, Christoph; Boccaccini, Aldo R.; Liverani, Liliana; Cicha, Iwona (European Polymer Journal, 2020)
The availability of cell growth-supporting materials for regenerative medicine is limited. Here, we aimed to improve the attachment and growth of endothelial cells (HUVECs) and fibroblasts on electrospun poly(ε-caprolactone) (PCL) mats with different fiber diameters and on newly-established PCL and silk fibroin (PCL/SF) blended fibers obtained by using benign solvents (mixture of acetic acid and formic acid) for electrospinning. PCL mats were produced in two different average fiber diameters, namely micro and nano range. The electrospinning method was optimized to produce PCL/SF blended fibers. Morphology (F-actin), viability (calcein) and metabolic activity (WST-8 assay) of HUVECs and fibroblasts cultured in 2D on the mats of different fiber size and composition were compared. Subsequently, cylindrical PCL/SF scaffolds were produced and colonized with cells using 3D radial magnetic cell seeding. Both PCL and PCL/SF nanofibers provided better support for initial cell adhesion (day 1) compared with PCL microfibers. At day 7, the highest metabolic activity in HUVECs and fibroblasts was observed on PCL/SF mats. Microscopic studies confirmed that on day 7, the best support for cell growth was observed on PCL/SF. Tubular PCL/SF scaffolds were successfully colonized using magnetic nanoparticles and 3D radial magnetic cell seeding. Taken together, the fibers obtained by blending SF with PCL combine the mechanical benefits of PCL with improved biological functionality of SF. Electrospun PCL/SF nanofibers represent a promising material to produce both flat and 3D structures with potential for enhanced cell attachment and tissue regeneration.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Benign solvents; Electrospinning; Magnetic cell seeding; Nanofibers; Poly(ε-caprolactone); Silk fibroin

Optimized prognostic score for coronary computed tomographic angiography: Results from the CONFIRM registry (COronary CT angiography evaluation for clinical outcomes: An international multicenter registry) - Hadamitzky, Martin; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel; Budoff, Matthew; Cademartiri, Filippo; Callister, Tracy; Chang, Hyuk-Jae; Cheng, Victor; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Cury, Ricardo; et al. (Journal of the American College of Cardiology, 2013)
Objectives The aim of this study was to analyze the predictive value of coronary computed tomography angiography (CCTA) and to model and validate an optimized score for prognosis of 2-year survival on the basis of a patient population with suspected coronary artery disease (CAD). Background Coronary computed tomography angiography carries important prognostic information in addition to the detection of obstructive CAD. But it is still unclear how the results of CCTA should be interpreted in the context of clinical risk predictors. Methods The analysis is based on a test sample of 17,793 patients and a validation sample of 2,506 patients, all with suspected CAD, from the international CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry. On the basis of CCTA data and clinical risk scores, an optimized score was modeled. The endpoint was all-cause mortality. Results During a median follow-up of 2.3 years, 347 patients died. The best CCTA parameter for prediction of mortality was the number of proximal segments with mixed or calcified plaques (C-index 0.64, p < 0.0001) and the number of proximal segments with a stenosis >50% (C-index 0.56, p = 0.002). In an optimized score including both parameters, CCTA significantly improved overall risk prediction beyond National Cholesterol Education Program Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adult Treatment Panel III) score as best clinical score. According to this score, a proximal segment with either a mixed or calcified plaque or a stenosis >50% is equivalent to a 5-year increase in age or the risk of smoking. Conclusions In CCTA, both plaque burden and stenosis, particularly in proximal segments, carry incremental prognostic value. A prognostic score on the basis of this data can improve risk prediction beyond clinical risk scores.
CRIS-Team Scopus Importer:2023-03-08
Keywords: coronary artery disease; coronary CT angiography; prognosis

Outcome after new generation single-layer polytetrafluoroethylene-covered stent implantation for the treatment of coronary artery perforation - Kufner, Sebastian; Schacher, Nora; Ferenc, Miroslaw; Schlundt, Christian; Hoppmann, Petra; Abdel-Wahab, Mohamed; Mayer, Katharina; Fusaro, Massimiliano; Byrne, Robert A.; Kastrati, Adnan (Catheterization and Cardiovascular Interventions, 2019)
Aims: Coronary artery perforation (CAP) is a rare but severe complication during percutaneous coronary intervention (PCI). Implantation of covered stents (CS) represents a potentially life-saving treatment. Concerns exist regarding limited efficacy and high stent thrombosis (ST) rates related to early generation CS. The aim of this study was to evaluate angiographic and clinical outcomes of patients with CAP treated with a new generation single-layer polytetrafluoroethylene (PTFE)-CS. Methods: Between May 2013 and November 2017, we identified a total of 61 patients who underwent implantation of 71 single layer PTFE-CS after CAP. We analyzed angiographic results at follow up (including binary angiographic restenosis [BAR] and late-lumen-loss [LLL]) and clinical outcomes in hospital and at follow up, including target lesion revascularization (TLR), cardiovascular-, and all-cause mortality, myocardial infarction (MI) and stent thrombosis (ST). Results: Procedural success was achieved in all but two patients (96.7%). Procedure related MI, occurred in 19 cases (31.1%), in hospital death occurred in five cases (8.2%). At follow-up, TLR occurred in 11 cases (18.0%), two patients (3.3%) died from non-cardiovascular cause, there was no case of MI or ST. Conclusions: In this retrospective analysis, implantation of a new generation PTFE-CS, for the treatment of CAP showed high technical success rates. Although, periprocedural MI—and in-hospital-death rates remain not inconsiderable, new generation PTFE-CS showed favorable angiographic and clinical efficacy and high safety profile, especially with regard to thrombotic events.
CRIS-Team Scopus Importer:2019-05-02
Keywords: coronary artery perforation; covered stent

Outcome after single-layer polytetrafluoroethylene-covered stent implantation for the treatment of coronary artery perforation - Kufner, S.; Ferenc, M.; Schlundt, Christian; Hoppmann, P.; Abdel-Wahab, M.; Cassese, S.; Joner, M.; Xhepa, E.; Fusaro, M.; Schunkert, H.; Laugwitz, K-L.; Neumann, F. -J.; et al. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Outcome of percutaneous coronary intervention with everolimus-eluting bioresorbable vascular scaffolds in patients with STEMI as compared to stable CAD 2 year results from the German-Austrian ABSORB - Tröbs, Monique; Achenbach, Stephan; Nef, H.; Wiebe, J.; Kastner, J.; Mehili, J.; Muenzel, T.; Naber, C.; Neumann, T.; Richard, G.; Schmermundt, A.; Woehrle, J.; et al. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Outcomes of 10,312 patients treated with everolimus-eluting bioresorbable scaffolds during daily clinical practice – results from the European Absorb Consortium - Wiebe, Jens; Hofmann, Felix J.; West, Nick; Baumbach, Andreas; Carrie, Didier; Bermudez, Eduardo Pinar; Cayla, Guillaume; Hernandez, Felipe Hernandez; De La Torre Hernandez, Jose M.; Koning, Rene; Loi, Bruno; Moscarella, Elisabetta; et al. (Catheterization and Cardiovascular Interventions, 2021)
Objectives: To asses mid-term clinical outcomes of bioresorbable vascular scaffolds (BVS) for the treatment of coronary artery disease in a large-scale all-comers population. Background: Several clinical settings are underrepresented in randomized studies investigating BVS against drug-eluting stents. Whether their results can be translated into the heterogeny patient population seen during daily routine requires further investigation. Methods: The European ABSORB Consortium comprises the following European registries: GABI-R, ABSORB UK Registry, ABSORB France, BVS RAI Registry, and REPARA BVS Registry, which all prospectively collected patient-level data regarding outcomes following unrestricted BVS implantation. The primary endpoint of target lesion failure (TLF) includes cardiac death, target-vessel myocardial infarction (TVMI) and target-lesion revascularisation (TLR) at 12 months. The incidence of scaffold thrombosis (ST) according to ARC criteria was also assessed. Multivariable analysis was used to adjust for differences in patient and lesion characteristics. Results: A total of 10,312 patients (mean age 58.4 ± 11.4 y) underwent BVS implantation during routine practice. The 12-month follow-up was complete in 95.5% of patients. At 12 months, the primary endpoint of TLF occurred in 3.6%; its components cardiac death, TVMI and TLR were documented in 1.2%, 1.8%, and 2.6%, respectively. The definite/probable ST rate was 1.7%. Absence of predilatation, discontinuation of DAPT and scaffold diameter below 3 mm were independent predictors of ST. Conclusions: The EAC demonstrates reasonable real-world clinical outcome data after BVS implantation. However, the rate of scaffold thrombosis remains high.
CRIS-Team Scopus Importer:2021-09-10
Keywords: all-comers; bioresorbable scaffold; coronary artery disease; percutaneous coronary intervention; stent

Outcomes of contemporary interventional therapy of ST elevation infarction in patients older than 75 years - Zimmermann, Stefan; Ruthrof, Susanne; Nowak, Kathrin; Klinghammer, Lutz; Ludwig, Josef; Daniel, Werner; Flachskampf, Frank A. (Clinical Cardiology, 2009)
Background: Data on contemporary real-world outcomes of interventional revascularization in patients ≥75 y of age with ST elevation infarction (STEMI) are limited. Methods: We analyzed all 504 consecutive patients who underwent angiography for acute STEMI between 1999 and 2005 at our center, and followed them up over one year. Outcomes in patients ≥75 y of age were compared with younger patients. Results: Patients ≥75 y of age (n = 115) were majority females (55% versus 21%, p<0.001), more cases of diabetes (42% versus 27%, p = 0.004), hypertension (78% versus 65%, p = 0.03) and a history of coronary events (25% versus 15%, p = 0.002). Younger patients were more often smokers (63% versus 30%, p<0.001). After coronary angiography patients ≥75 y of age underwent less frequent intervention (PCI; 84% versus 93%, p = 0.01). However, if PCI was performed, technical success rates were similar to younger patients (84% versus 86%). The 30-d mortality was 13% versus 6.4% (p = 0.03), but after successful PCI, the 30-d mortality rate was not significantly higher in old patients (7.4% versus 3.9%, p = 0.23). Bleeding complications were very low in both age groups if the radial access route was chosen. Multivariate predictors of 30-d mortality were cardiogenic shock/survived cardiac arrest, ejection fraction < 30%, conservative treatment or unsuccessful PCI (OR 3.01), renal insufficiency, diabetes, and age. One-y mortality was higher in the elderly (24.3% versus 9.9%, p<0.001). Among 30-d-survivors, only multivessel disease and age were multivariate predictors of 1-ymortality. Conclusion: Patients ≥75 y of age benefit from PCI in STEMI, and failed or unattempted PCI worsens prognosis in the old as well as in younger patients. © 2009 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Acute cardiac care; Acute coronary syndrome; Percutaneous intervention

Outcomes of transcatheter mitral valve replacement for degenerated bioprostheses, failed annuloplasty rings, and mitral annular calcification - Yoon, Sung-Han; Whisenant, Brian K.; Bleiziffer, Sabine; Delgado, Victoria; Dhoble, Abhijeet; Schofer, Niklas; Eschenbach, Lena; Bansal, Eric; Murdoch, Dale J.; Ancona, Marco; Schmidt, Tobias; Yzeiraj, Ermela; et al. (European Heart Journal, 2019)
Aims We sought to evaluate the outcomes of transcatheter mitral valve replacement (TMVR) for patients with degenerated bioprostheses [valve-in-valve (ViV)], failed annuloplasty rings [valve-in-ring (ViR)], and severe mitral annular calcification [valve-in-mitral annular calcification (ViMAC)].
CRIS-Team WoS Importer:2019-03-06

Out of Focus: Increase of the Excess Longitudinal Range in Coronary Computed Tomographic Angiography - Stocker, Thomas J.; Heckner, Mathias; Leipsic, Jonathon; Hadamitzky, Martin; Deseive, Simon; Achenbach, Stephan; Chen, Marcus Y.; Rubinshtein, Ronen; Bax, Jeroen J.; Bittencourt, Marcio S.; Jadhav, Uday M.; Schlosser, Thomas; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2020)
EVALuna2:212139

Out-of-hospital cardiac arrest and percutaneous coronary intervention for ST-elevation myocardial infarction: Long-term survival and neurological outcome - Zimmermann, Stefan; Flachskampf, Frank A.; Alff, Anna; Schneider, Reinhard; Dechant, Katharina; Klinghammer, Lutz; Stumpf, Christian; Zopf, Yurdagül; Loehr, Thomas; Brand, Georg; Ludwig, Josef; Daniel, Werner; et al. (International Journal of Cardiology, 2013)
Background: Predictors of long-term outcome after ST-elevation myocardial infarction (STEMI) complicated by out-of-hospital cardiac arrest (OHCA) are incompletely understood, including the influence of successful coronary reperfusion. Methods: We analysed clinical and procedural data as well as 1-year outcome of 72 consecutive patients who underwent primary coronary intervention (PCI) after witnessed OHCA and STEMI and compared the results with 695 patients with STEMI and PCI, but without OHCA. Neurological recovery after OHCA was assessed using the Cerebral Performance Category (CPC) scale. Results: PCI was successful in 83.3% after OHCA vs. 84.3% in the non-OHCA group (p = 0.87). One-year mortality was 34.7% vs. 9.5% (p < 0.001). 58.3% of the OHCA-patients showed complete neurological recovery (CPC 1) or moderate neurological disability (CPC 2). Another 6.9% showed severe cerebral disability (CPC 3) or permanent vegetative status (CPC 4). Delay from collapse until start of Advanced Cardiopulmonary Life Support (ACLS) was shorter for survivors with CPC status ≤ 2 (median 1 min, range 0-11 min) compared to non-survivors or survivors with CPC status > 2 (median 8 min, range 0-13 min), p < 0.0001. Age-adjusted multivariate analysis identified 'unsuccessful PCI', 'vasopressors on admission' and 'start of ACLS after > 6 min' as independent predictors of negative long-term outcome (death or CPC > 2). Conclusions: Mortality is high in patients with STEMI complicated by OHCA - even though PCI was performed with the same success rate as in patients without OHCA. The majority of survivors had favourable neurological outcomes at 1 year, especially if advanced life support had been started within ≤ 6 min and PCI was successful. © 2011 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac arrest; Outcome; Primary coronary intervention; Prognosis; Resuscitation; ST-elevation myocardial infarction

Overlapping implantation of bioresorbable novolimus-eluting scaffolds: an observational optical coherence tomography study - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian; et al. (Heart and Vessels, 2017)
Overlapping implantation of bioresorbable vascular scaffolds is frequently necessary, but its influence on vessel and scaffold structure has not been thoroughly analyzed previously. The aim of this study was to analyze the acute effects of overlapping implantation on BRS as determined by optical coherence tomography (OCT). A total of 38 patients with de novo coronary artery stenoses who underwent OCT in the context of implantation of novolimus-eluting BRS (DESolve, Elixir Medical Corporation, Sunnyvale, California, USA) were investigated. In 15 patients, overlapping implantation of two BRS was performed, while 23 patients with implantation of one single BRS served as the control group. OCT data were retrospectively analyzed regarding acute scaffold implantation results. There were no significant differences between the overlap and control group in terms of residual in-scaffold area stenosis, scaffold area, mean or minimal lumen area, eccentricity index, incomplete scaffold apposition area or malapposition. While strut fracture was slightly more frequent in BRS with overlap its incidence was low overall. In patients with overlapping BRS, overlap segments did not display smaller lumen areas than segments without overlap (mean lumen area overlap: 8.16 ± 2.97 mm2vs. no overlap: 7.70 ± 2.55 mm2; p = 0.71; minimal lumen area overlap: 6.83 ± 2.71 mm2vs. no overlap: 6.17 ± 2.58 mm2; p = 0.37). Acute mechanical performance of novolimus-eluting BRS is not impaired by overlapping implantation. It can be assumed that vessel expansion compensates for the double scaffold layer in the overlap area resulting in a similar lumen area in overlap areas and in those with a single strut layer.
EVALuna2:33634

Oversizing in transcatheter aortic valve replacement, a commonly used term but a poorly understood one: dependency on definition and geometrical measurements - Blanke, Philipp; Willson, Alexander B.; Webb, John G.; Achenbach, Stephan; Piazza, Nicolo; Min, James K.; Pache, Gregor; Leipsic, Jonathon (Journal of Cardiovascular Computed Tomography, 2014)
In transcatheter aortic valve replacement, prosthesis oversizing is essential to prevent paravalvular regurgitation. However, the estimated extent of oversizing strongly depends on the measurement used for annular sizing.The aim was to investigate the influence of geometrical parameters for calculation of relative oversizing in transcatheter aortic valve replacement, reported as percentage in relation to the native annulus size, to standardize reporting.Electrocardiogram-gated cardiac dual-source CT data of 130 consecutive patients with severe aortic stenosis (mean age, 81 ± 8 years; 56 men; mean aortic valve area, 0.67 ± 0.18 cm2) were included. Aortic annulus dimensions were quantified by means of planimetry that yielded area and perimeter at the level of the basal attachment points of the aortic cusps during systole. Area- and perimeter-derived diameters were calculated as DA = 2 × ?(A/?) and DP = P/?. Hypothetical prosthesis sizing was based on DA (23-mm prosthesis for 19-22 mm; 26-mm prosthesis for 22-25 mm; 29-mm prosthesis for 25-28 mm). Relative oversizing for hypothetical prosthesis selection was calculated as percentage in relation to the native annulus size.Mean annulus area was 492.12 ± 94.9 mm2 and mean perimeter was 80.1 ± 7.6 mm. DP was significantly larger than DA (25.5 ± 2.4 mm vs 24.9 ± 2.4 mm; P < .001). Mean maximum diameter was 28.1 ± 3.0 mm and mean minimal diameter was 22.8 ± 2.4 mm. Calculated eccentricity index [EI = 1 - minimal diameter/maximum diameter)] was 0.19 ± 0.06. Difference between DP and DA correlated significantly with EI (r = 0.67; P < .001). Relative oversizing was 10.2% ± 3.8% and 21.6% ± 8.4% by DA and area, and 7.8% ± 3.9% by both DP and perimeter.For planimetric assessment of aortic annulus dimensions with CT, the percentage oversizing calculated strongly depends on the geometrical variable used for quantifying annular dimensions. Standardized nomenclature seems warranted for comparison of future studies.
EVALuna2:11999

Patient-specific predictors of image noise in coronary CT angiography - Schuhbaeck, Annika; Schäfer, Marcella; Marwan, Mohamed; Gauss, Soeren; Muschiol, Gerd; Lell, Michael; Pflederer, Tobias; Ropers, Dieter; Rixe, Johannes; Hamm, Christian; Daniel, Werner G.; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
Background: Coronary computed tomography (CT) angiography can be associated with high radiation exposure. Reduction of tube voltage from 120 kV to 100 kV can reduce the dose by up to 40%, but it also increases image noise. Objective: We aimed to find a patient-specific predictor of image noise to determine the use of reduced tube voltage. Methods: Contrast-enhanced coronary dual-source CT angiography data sets [prospectively electrocardiogram (ECG)-triggered axial and retrospectively ECG-gated spiral acquisition, rotation of 280 milliseconds, 2 × 128 × 0.6 mm collimation, 100 kV, 320 mAs] of 165 patients (age, 54 ± 13 years) for the detection of coronary artery stenoses were analyzed. Image noise was measured in the aortic root. Influence of body weight, height, body mass index, thoracic cross sectional area, as well as the area of the thoracic solid tissue were analyzed. Results: Mean image noise in the aorta was 35.1 ± 8.9 HU. Mean dose length product was 207 ± 184 cm · cGy with an average effective dose of 2.9 ± 2.6 mSv. The patient cohort was divided into tertiles according to image noise. Numerous parameters, including BMI and body weight, were significantly different between the highest and lowest tertiles. In multivariable regression analysis, the area of the thoracic solid tissue was the only independent predictor of image noise (P < 0.0001). Conclusions: The area of the thoracic solid tissue at the level of the aortic root predicts image noise and may hence be used for the decision to reduce tube voltage from 120 kV to 100 kV. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary CT angiography; Dual-source CT; Image noise; Tube voltage

Patients Undergoing High-Risk CRT Upgrades with a WiSE-CRT System Have at Trend towards Improved Left Ventricular Remodelling Compared with Epicardial CRT Upgrades - Sidhu, Baldeep S.; Gould, Justin; Porter, Bradley; Diemberger, Igor; Biffi, Mauro; Seifert, Martin; Butter, Christian; Boersma, Lucas V. A.; Riahi, Sam; Neuzil, Petr; Vergara, Pasquale; Defaye, Pascal; et al. (JOURNAL OF CARDIAC FAILURE, 2019)
CRIS-Team WoS Importer:2019-09-13

Patients with acute coronary syndromes express enhanced CD40 ligand/CD 154 on platelets - Klinghammer, Lutz; et al. (Heart, 2001)
UnivIS-Import:2015-03-09:Pub.2001.med.MKIPI.MKIPLA.patien
Keywords: Acute coronary syndromes; Platelets; Unstable angina; CD40L/CD 154

Patients with atypical chest pain show associations with pro-atherogenic cytokines and levels of sRANKL and OPG - Raaz-Schrauder, D.; Stumpf, Christian; Schrauder, Michael G.; Lewczuk, Piotr; Dietel, B.; Garlichs, Christoph; Achenbach, Stephan; Klinghammer, Lutz (2016)
EVALuna2:33388

Patients with unstable angina pectoris show an increased frequency of the Fc gamma RIIa R131 allele - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Munoz, Luis Enrique; Klinghammer, Lutz; Voll, Reinhard E.; Leusen, Jeanette H.W.; Van De Winkel, Jan G.J.; Reis, André; Schett, Georg; Garlichs, Christoph; Herrmann, Martin (Autoimmunity, 2012)
Patients with Systemic Lupus Erythematosus (SLE) carry an increased risk for the development of coronary artery disease (CAD). The R131 allele of the Fc gamma receptor IIa (FcγRIIa) is associated with SLE incidence and disease severity but also with CAD. Compared to stable angina pectoris (SAP) the unstable angina (UAP), as a manifestation of destabilizing CAD, is associated with increased risk of persistent instability, myocardial infarction, and death. Identification of clinically relevant determinants for unstable angina promises reduction of UAP-associated mortality in patients with SLE. We conducted a clinical study among 553 consecutive patients with stable angina pectoris (n 330) and unstable angina pectoris (n 223). All patients were genotyped for a frequent functional variant at position 131 of the mature FcγRIIa. UAP, but not SAP was significantly associated with the R/R131 genotype (P < 0.001). In troponin-negative patients with angina carrying the R/R131 genotype the odds ratio for suffering from UAP was 4.02 (95% confidence interval, 2.526.41) compared to those with non-R/R131 genotypes. In a multivariable analysis, the R/R131 genotype independently predicted the risk for development of UAP in a model adjusted for classical atherogenic risk factors. Our data imply that risk stratification of SLE- and other high risk patients with troponin-negative angina could be significantly improved by FcγRIIa genotyping. © Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Allele R131; Coronary disease; Fc gamma receptor IIa; SLE; Stable; Unstable angina pectoris

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Susanne; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Percutaneous coronary intervention of unprotected left main stenoses - Procedural data and outcome depending on SYNTAX I Score - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2018)
BACKGROUND: We hypothesized that SYNTAX I score is a predictor for procedure complexity in left main PCI. Procedure complexity, duration and contrast load may contribute to adverse outcome of complex left main percutaneous coronary intervention (PCI). METHODS: In 105 consecutive patients who underwent PCI of unprotected left main coronary artery stenoses between 2014 and 2016, clinical parameters as well as PCI characteristics and follow-up data were analyzed. RESULTS: The mean SYNTAX I score was 29 ± 12, with 66 patients having a SYNTAX I score ≤ 32 and 39 patients a SYNTAX I score > 32. In patients with high SYNTAX I score vs. low-to-intermediate SYNTAX I score, single stent techniques were performed significantly less frequently (18% vs. 68%; p < 0.001), while Crush (44% vs. 5%; p < 0.001) and Culotte techniques (20% vs. 5%; p = 0.003) were performed significantly more frequently. Procedural success was achieved in all 105 cases without periprocedural mortality. During follow up, repeat PCI was necessary significantly more frequently in patients with high compared to patients with low-to-intermediate SYNTAX I score (34% vs.13%; p = 0.003). Nevertheless, overall mortality did not differ between patients with high vs. low-to-intermediate SYNTAX I score (20% vs. 18%). CONCLUSIONS: PCI strategies for the treatment of left main coronary artery stenoses get significantly more complex with increasing SYNTAX I scores. While this translates into a significantly longer procedure duration and contrast load, short-term outcome seems not to be influenced by the SYNTAX I score.
EVALuna2:213082

Performance of high-sensitivity troponin T in the early diagnosis of non-ST-elevation myocardial infarction in elderly patients presenting to an emergency department - Bahrmann, Philipp; Bahrmann, A.; Christ, M.; Bertsch, T.; Sieber, Cornel (European Heart Journal, 2012)

Performing and Interpreting Fractional Flow Reserve Measurements in Clinical Practice: An Expert Consensus Document - Achenbach, Stephan; Rudolph, Tanja; Rieber, Johannes; Eggebrecht, Holger; Richardt, Gert; Schmitz, Thomas; Werner, Nikos; Boenner, Florian; Möllmann, Helge (Interventional Cardiology (London), 2017)
Fractional flow reserve (FFR) measurements can determine the haemodynamic relevance of coronary artery stenoses. Current guidelines recommend their use in lesions in the absence of non-invasive proof of ischaemia. The prognostic impact of FFR has been evaluated in randomised trials, and it has been shown that revascularisation can be safely deferred if FFR is >0.80, while revascularisation of stenoses with FFR values ≤0.80 results in significantly lower event rates compared to medical treatment. Left main stenoses, aorto-ostial lesions, as well as patients with left ventricular hypertrophy and severely-impaired ejection fraction, have been excluded from large, randomised trials. While FFR measurements are relatively straightforward to perform, uncertainty about procedural logistics, as well as data acquisition and interpretation in specific situations, could explain why they are not widely used in clinical practice. We summarise the clinical data in support of FFR measurements, and provide recommendations for performing and interpreting the procedure.
EVALuna2:36039

Pericardial constriction and pediatric cardiac CT - Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2014)
EVALuna2:12014

Pericoronary adipose tissue and quantitative global non-calcified plaque characteristics from CT angiography do not differ in matched South Asian, East Asian and European-origin Caucasian patients with stable chest pain - Göller, Markus; Rahman Ihdayhid, Abdul; Cadet, Sebastien; Lin, Andrew; Adams, Daniel; Thakur, Udit; Yap, Grace; Achenbach, Stephan; Dey, Damini; Ko, Brian; Marwan, Mohamed (European Journal of Radiology, 2020)
Purpose: South Asian (SA) have been observed to have higher cardiovascular mortality rates compared to East Asians (EA) and Caucasians. Pericoronary adipose tissue (PCAT) attenuation around the right coronary artery (RCA) from coronary CT angiography (CTA) has been associated with coronary inflammation and cardiac death. We aimed to investigate i) the relationship between plaque characteristics and PCAT attenuation and ii) to assess gender and ethnic differences in PCAT attenuation using a matched cohort of SA, EA and Caucasians. Method: Three-hundred symptomatic patients who underwent CTA were matched for age, gender, BMI and diabetes (100 in each ethnic group). Semi-automated software was used to quantify the total volumes and burden of non-calcified plaque (NCP), low-density non-calcified plaque (LD-NCP) and calcified plaque (CP) in blinded core-lab analysis. PCAT CT attenuation was measured around the RCA (10–50 mm from RCA ostium), the most standardized model for PCAT analysis. Results: The total volumes and burden of NCP, LD-NCP and CP were comparable in the ethnic groups (each p > 0.05). PCAT attenuation was higher in patients with coronary plaque. PCAT attenuation correlated with the total volumes and burden of NCP, LD-NCP and CP (r>0.17; p < 0.003). Within the RCA this correlation persisted only for NCP features (r>0.39;p < 0.001). Males showed higher PCAT attenuation (p < 0.001). PCAT attenuation was similar between Caucasian, EA and SA (p = 0.32). Conclusions: PCAT CT attenuation correlated most with its surrounded NCP features further highlighting its role as surrogate measure of coronary inflammation. As coronary plaque burden and RCA PCAT attenuation did not differ between ethnic groups, causes of increased cardiac mortality in South Asians needs further investigations.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Atherosclerosis; Computerized tomography (CT); Pericoronary adipose tissue; Race and ethnicity

Pericoronary Adipose Tissue Computed Tomography Attenuation and High-Risk Plaque Characteristics in Acute Coronary Syndrome Compared With Stable Coronary Artery Disease - Goeller, Markus; Achenbach, Stephan; Cadet, Sebastien; Kwan, Alan C.; Commandeur, Frederic; Slomka, Piotr J.; Gransar, Heidi; Albrecht, Moritz H.; Tamarappoo, Balaji K.; Berman, Daniel S.; Dey, Damini; Marwan, Mohamed (JAMA Cardiology, 2018)
Importance: Pericoronary adipose tissue (PCAT) computed tomography (CT) attenuation measured from coronary CT angiography (CTA) may be a promising metric in identifying high-risk plaques. Objective: To determine whether high-risk plaque characteristics from coronary CTA are associated with PCAT CT attenuation in patients with a first acute coronary syndrome (ACS) and matched controls with stable coronary artery disease (CAD). Design, Setting, and Participants: This retrospective, single-center case-control study (data were acquired at the University of Erlangen from 2009-2010) analyzed the CTA data sets of 19 patients who presented with ACS and 16 controls with stable CAD who were matched based on sex, age, and risk factors. Study observers were blinded to patients' clinical data. Semiautomated software was used to quantify and characterize plaques. The CT attenuation (Hounsfield unit [HU]) of PCAT was automatically measured around all lesions. Main Outcomes and Measures: To investigate the association between high-risk plaque characteristics from CTA and PCAT CT attenuation as a novel surrogate measure of coronary inflammation. Results: A total of 35 patients (mean [SD] age, 59.5 [11.3] years; 30 men [86%] and 5 women [14%]) were included in the analysis. Low- and intermediate-attenuation noncalcified plaque (NCP) burden were increased in culprit lesions (n = 19) compared with both nonculprit lesions (n = 55) in patients with ACS (12.6% vs 3.6%; P < .001; 38.4% vs 19.4%; P < .001) and the control group's highest-grade stenosis lesions (n = 16) (12.6% vs 5.6%; P = .002; 38.4% vs 22.1%; P < .001). Pericoronary adipose tissue attenuation was increased around culprit lesions (n = 19) compared with nonculprit lesions (n = 55) in patients with ACS (-69.1 HU vs -74.8 HU; P = .01) and highest-grade stenosis lesions in control patients (n = 16) (-69.1 HU vs -76.4 HU; P = .01). Pericoronary adipose tissue CT attenuation of all lesions in patients with ACS (n = 74) correlated more strongly with intermediate-attenuation (r = 0.393; P = .001) over low-attenuation (r = 0.221; P = .06) and high-attenuation NCP burden (r = -0.103; P = .38). In a multivariable analysis, low- and intermediate-attenuation NCP burden and PCAT CT attenuation were independently associated with the presence of culprit lesions (P < .05). Conclusions and Relevance: Pericoronary CT attenuation was increased around culprit lesions compared with nonculprit lesions of patients with ACS and the lesions of matched controls. Combined quantitative high-risk plaque features and PCAT CT attenuation may allow for a more reliable identification of vulnerable plaques.
EVALuna2:35975

Pericoronary adipose tissue CT attenuation and its association with serum levels of atherosclerosis-relevant inflammatory mediators, coronary calcification and major adverse cardiac events - Göller, Markus; Achenbach, Stephan; Herrmann, Nicolai; Bittner, Daniel O.; Kilian, Tobias; Dey, Damini; Raaz-Schrauder, Dorette; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2021)
Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) derived from coronary CTA might detect coronary inflammation. We investigated a potential association between RCA PCAT attenuation and serum levels of atherosclerosis-relevant cytokines and MACE (coronary revascularization, myocardial infarction and/or cardiac death). Methods: Blood samples of 293 clinically stable individuals (59.0 ​± ​9.8 years, 69% males) were analyzed for atherosclerosis-relevant cytokines including interleukin (IL)-2, IL- 4, IL-6, IL-7, IL-8, IL-10, IL-13, IL-15, IL-17, TNF-a, IP-10, CRP, MCP-1, MIP-1a, Eotaxin and GM-CSF. Subjects also underwent coronary calcium scoring (CCS) followed by CTA. PCAT CT attenuation was measured around the RCA using semi-automated software. Increased RCA PCAT attenuation was defined as PCAT attenuation above the 75th percentile (>−73.5 HU). To assess MACE, 232 individuals were followed for a mean duration of 9.6 ​± ​2.1 years. Results: In patients with increased RCA PCAT attenuation the serum levels of MCP-1 were increased (p ​< ​0.01), whereas levels of anti-inflammatory mediators IL-4 and -13 were significantly reduced (each p ​< ​0.05). Adipocytokine MCP-1 (r ​= ​0.23, p ​< ​0.01) and pro-inflammatory mediator IL-7 (r ​= ​0.12, p ​= ​0.04) showed a mild positive correlation with RCA PCAT attenuation, whereas anti-inflammatory mediators Il-4, -10 and -13 correlated inversely (each r < −0.12, each p ​< ​0.05). 40/232 patients experienced MACE during follow-up. In multivariable Cox regression analysis increased RCA PCAT attenuation was shown to be an independent predictor of MACE (HR 2.01, p ​= ​0.044). Conclusions: Increased RCA PCAT CT attenuation shows a weak association with serum levels of selected atherosclerosis-relevant inflammatory biomarkers. Increased RCA PCAT attenuation is an independent predictor of MACE and may potentially guide future prevention strategies in stable patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Atherosclerosis-relevant inflammatory biomarkers; Coronary calcium score; CT attenuation; Inflammation; MACE; Pericoronary adipose tissue

PERIVASCULAR FAT ATTENUATION INDEX MAPPING AROUND THE RIGHT AND LEFT CORONARY ARTERY INDEPENDENTLY PREDICT CARDIAC MORTALITY - Kotanidis, Christos P.; Oikonomou, Evangelos K.; Thomas, Katharine E.; Alashi, Alaa; Antonopoulos, Alexios S.; Shirodaria, Cheerag; Neubauer, Stefan; Channon, Keith M.; Achenbach, Stephan; Desai, Milind Y.; Antoniades, Charalambos; Marwan, Mohamed (HEART, 2020)
CRIS-Team WoS Importer:2021-01-29

Perivascular fat attenuation index stratifies the cardiac risk associated with high-risk plaque features on coronary computed tomography angiography - Oikonomou, E. K.; Mancio, J.; Kotanidis, C. K.; Thomas, K. E.; Alashi, A.; Centeno, E. Hutt; Antonopoulos, A. S.; Shirodaria, C.; Neubauer, S.; Channon, K. M.; Achenbach, Stephan; Desai, M. Y.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

PHENOTYPE OF VULNERABLE ATHEROSCLEROTIC PLAQUES SHOWS STRONG ASSOCIATION WITH SINGLE NUCLEOTIDE POLYMORPHISM ALLELES OF COMMON RISK VARIANTS FOR CORONARY ARTERY DISEASE - Furtmair, R.; Kühn, Charlotte; Koenig, C.; Ekici, Arif Bülent; Klinghammer, Lutz; Achenbach, Stephan; Reis, André; Tauchi, M.; Dietel, B. (2016)
EVALuna2:33679

Photoinducible penetration enhancement and drug release for cancer treatment - Cicha, Iwona; Lyer, Stefan; Dürr, Stephan; Schwarz, Marc; Tietze, Rainer; Tripal, Philipp; Alexiou, Christoph (Nanomedicine, 2014)
EVALuna2:19949

Plaque Rupture, Compared With Plaque Erosion, Is Associated With a Higher Level of Pancoronary Inflammation - Nakajima, Akihiro; Sugiyama, Tomoyo; Araki, Makoto; Seegers, Lena Marie; Dey, Damini; McNulty, Iris; Lee, Hang; Yonetsu, Taishi; Yasui, Yumi; Teng, Yun; Nagamine, Tatsuhiro; Nakamura, Sunao; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
Objectives: The aim of this study was to compare the level of coronary inflammation between plaque rupture and plaque erosion using pericoronary adipose tissue (PCAT) attenuation. Background: Vascular inflammation plays a key role in plaque rupture, while the role of inflammation in plaque erosion remains less well defined. PCAT attenuation determined using computed tomography has emerged as a marker specific for coronary artery inflammation. Methods: Patients with non–ST-segment elevation acute coronary syndromes who underwent preintervention coronary computed tomographic angiography and optical coherence tomographic culprit lesion imaging were enrolled. PCAT attenuation was measured around the culprit lesion and in the proximal 40 mm of all coronary arteries. Results: Among 198 patients, plaque rupture was the underlying mechanism in 107 (54.0%) and plaque erosion in 91 (46.0%). Plaque rupture had higher PCAT attenuation than plaque erosion both at the culprit plaque level (−65.8 ± 7.5 HU vs −69.5 ± 11.4 HU; P = 0.010) and at the culprit vessel level (−67.1 ± 7.1 HU vs −69.6 ± 8.2 HU; P = 0.024). The mean PCAT attenuation of all 3 coronary arteries was also significantly higher in patients with plaque rupture than in plaque erosion, indicating a higher level of inflammation (−67.9 ± 5.7 HU vs −69.9 ± 6.8 HU; P = 0.030). In multivariable analysis, plaque rupture was significantly associated with high PCAT attenuation. Conclusions: PCAT attenuation in culprit plaque, culprit vessel, and all 3 coronary arteries was higher in plaque rupture than in plaque erosion. The results suggest that pancoronary inflammation plays a more significant role in plaque rupture than in plaque erosion. (Massachusetts General Hospital and Tsuchiura Kyodo General Hospital Coronary Imaging Collaboration; NCT04523194)
CRIS-Team Scopus Importer:2022-05-06
Keywords: acute coronary syndrome; computed tomography angiography; optical coherence tomography; pericoronary adipose tissue attenuation; plaque erosion; plaque rupture

Plasma levels of sRANKL and OPG are associated with atherogenic cytokines in patients with intermediate cardiovascular risk - Raaz-Schrauder, Dorette; Schrauder, Michael G.; Stumpf, Christian; Lewczuk, Piotr; Kilian, Tobias; Dietel, Barbara; Garlichs, Christoph D.; Schlundt, Christian; Achenbach, Stephan; Klinghammer, Lutz (Heart and Vessels, 2017)
Osteoprotegerin (OPG) and receptor activator of nuclear factor-κB ligand (RANKL) are regulators of bone remodeling, but are also considered to play important roles in coronary artery disease (CAD). This study evaluated potential associations of soluble (s) RANKL and OPG with atherosclerosis-relevant cytokines. Blood was collected from 414 individuals who presented to our hospital with intermediate likelihood for CAD for further examination. Plasma concentrations of total sRANKL, OPG, and 20 cytokines were measured using sandwich-type enzyme-linked immunoassays (ELISAs; OPG and sRANKL) and Luminex laser-based fluorescence analysis and correlated with each other. The plasma levels of interferon-γ (IFN-γ) and the T-helper cell 2 cytokines interleukin-4 (IL-4) and IL-13 showed a positive correlation with sRANKL. The association with sRANKL levels was negative for IFN-γ-induced protein-10 (IP-10) and monocyte chemotactic protein-1 (MCP-1). The strongest independent association with sRANKL in multivariable analyses was found for IFN-γ (positive) and IP-10 (negative), while IL-13 showed a positive and independent association with OPG plasma levels. OPG and sRANKL plasma levels correlate strongly and independently with specific circulating atherosclerosis-related cytokines in patients with intermediate cardiovascular risk.
EVALuna2:33557

Platelet CD40 contributes to enhanced monocyte chemoattractant protein 1 levels in patients with resistant hypertension - Stumpf, Christian; Raaz, Dorette; Klinghammer, Lutz; Schneider, Markus; Schmieder, Roland; Garlichs, Christoph D.; Achenbach, Stephan (European Journal of Clinical Investigation, 2016)
Growing evidence shows that inflammation plays a pivotal role in the pathophysiology of essential hypertension (EH). Although it is acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages. However, recently, platelets were identified as inducing inflammation partly by releasing cytokines. The goal of our study was to evaluate the role of platelets as inflammatory cells in the pathogenesis of EH.Thirty-nine patients with EH and 30 healthy normotensive controls have been examined. Expression of platelet CD40 was measured by flow cytometry. Serum levels of monocyte chemoattractant protein 1 (MCP-1) and sCD40L were measured via a multiplexing assay. In in vitro experiments, activated platelets were cocultured with human umbilical vein endothelial cells (HUVEC) in the presence and absence of anti-CD154 antibodies. MCP-1 in the supernatants was measured by EIA.Essential hypertension patients showed significantly enhanced MCP-1 levels with highest levels in EH patients with microalbuminuria. EH patients showed increased expression of platelet CD40. In the cell coculture model, activated platelets were able to significantly induce MCP-1 release from HUVEC in a CD40L-dependent manner. EH patients showed elevated sCD40L levels with a positive correlation with MCP-1 levels.Platelets can contribute to enhanced MCP-1 levels in EH. MCP-1 is markedly elevated in serum of EH patients with highest levels in patients with microalbuminuria, one early sign of renal target organ damage. Further studies are required to test whether MCP-1 blocking or antiplatelet strategies may represent new therapeutic options in preventing hypertensive target organ damage.
EVALuna2:3852

Pneumatic external counterpulsation–a new technical perfusion principle Pneumatische externe Gegenpulsation–ein neues perfusionstechnisches Prinzip. - Klinghammer, Lutz; et al. (Biomedizinische Technik, 1998)

Point of Care Clinical Risk Score to Improve the Negative Diagnostic Utility of an Agatston Score of Zero: Averting the Need for Coronary Computed Tomography Angiography - Alshahrani, Ali M.; Mahmood, Hamza; Wells, George A.; Hossain, Alomgir; Rybicki, Frank J.; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Bax, Jeroen J.; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; et al. (Circulation: Cardiovascular Imaging, 2019)
BACKGROUND: Coronary artery calcification is a marker of underlying atherosclerotic vascular disease. The absence of coronary artery calcification is associated with a low prevalence of obstructive coronary artery disease (CAD), but it cannot be ruled out completely. We sought to develop a clinical tool that can be added to Agatston score of zero to rule out obstructive CAD with high accuracy. METHODS: We developed a clinical score retrospectively from a cohort of 4903 consecutive patients with an Agatston score of zero. Patients with prior diagnosis of CAD, coronary percutaneous coronary intervention, or surgical revascularization were excluded. Obstructive CAD was defined as any epicardial vessel diameter narrowing of ≥50%. The score was validated using an external cohort of 4290 patients with an Agatston score of zero from a multinational registry. RESULTS: The score consisted of 7 variables: age, sex, typical chest pain, dyslipidemia, hypertension, family history, and diabetes mellitus. The model was robust with an area under the curve of 0.70 (95% CI, 0.65-0.76) in the derivation cohort and 0.69 (95% CI, 0.65-0.72) in the validation cohort. Patients were divided into 3 risk groups based on the score: low (≤6), intermediate (7-13), and high (≥14). Patients who score ≤6 have a negative likelihood ratio of 0.42 for obstructive CAD, whereas those who score ≥14 have a positive likelihood ratio of >5.5 for obstructive CAD. The outcome was ruled out in >98% of patients with a score ≤6 in the validation cohort. CONCLUSIONS: We developed a score that may be used to identify the likelihood of obstructive CAD in patients with an Agatston score of zero, which may be used to direct the need for additional testing. However, the results of this retrospective analysis are hypothesis generating and before clinical implementation should be validated in a trial with a prospectively collected data.
CRIS-Team Scopus Importer:2019-09-27
Keywords: chest pain; coronary artery disease; diabetes mellitus; humans; registries

Polydopamine and gelatin coating for rapid endothelialization of vascular scaffolds - Kopeć, Kamil; Wojasiński, Michał; Eichler, Mathis; Genc, Hatice; Friedrich, Ralf P.; Stein, René; Singh, Raminder; Alexiou, Christoph; Hlawaty, Hanna; Ciach, Tomasz; Cicha, Iwona (Materials Science and Engineering C, 2021)
Rapid endothelialization helps overcome the limitations of small-diameter vascular grafts. To develop biomimetic non-thrombogenic coatings supporting endothelialization, medical-grade polyurethane (PU) nanofibrous mats and tubular scaffolds with a diameter below 6 mm prepared by solution blow spinning were coated with polydopamine (PDA), or PDA and gelatin (PDA/Gel). The scaffolds were characterized by scanning electron microscopy, porosity measurement, tensile testing, wettability, Fourier Transform Infrared spectroscopy, and termogravimetric analysis, followed by the measurement of coating stability on the tubular scaffolds. The effect of coating on scaffold endothelialization and hemocompatibility was evaluated using human umbilical vein endothelial cells (HUVECs) and human platelets, showing low numbers of adhering platelets and significantly higher numbers of HUVECs on PDA- and PDA/Gel-coated mats compared to control samples. Tubular PU scaffolds and commercial ePTFE prostheses coated with PDA or PDA/Gel were colonized with HUVECs using radial magnetic cell seeding. PDA/Gel-coated samples achieved full endothelial coverage within 1–3 days post-endothelialization. Altogether, PDA and PDA/Gel coating significantly enhance the endothelialization on the flat surfaces, tubular small-diameter scaffolds, and commercial vascular prostheses. The presented approach constitutes a fast and efficient method of improving scaffold colonization with endothelial cells, expected to work equally well upon implantation.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Human endothelial cell; Magnetic cell seeding; Polydopamine coating; Polyurethane scaffolds; Tubular grafts

Positionspapier der Kommission Digitale Rheumatologie der Deutschen Gesellschaft für Rheumatologie e. V.: Aufgaben, Ziele und Perspektiven für eine moderne Rheumatologie - Knitza, Johannes; Callhoff, J.; Chehab, G.; Hueber, Axel; Kiltz, U.; Kleyer, Arnd; Krusche, M.; Simon, David; Specker, C.; Schneider, M.; Voormann, A.; Welcker, M.; et al. (Zeitschrift für Rheumatologie, 2020)
Digitalization in the healthcare system is a great challenge for rheumatology as for other medical disciplines. The German Society for Rheumatology (DGRh) wants to actively participate in this process and benefit from it. By founding the commission on digital rheumatology, the DGRh has created a committee that deals with the associated tasks, advises the DGRh on questions and positions associated with digital health. For the DGRh, this affects the most diverse areas of digitalization in medicine and rheumatology. This position paper presents the topics and developments currently handled by the commission and the tasks identified.
CRIS-Team Scopus Importer:2020-07-24
Keywords: App; Digitalization; eHealth; Health services research; mHealth

Post-dilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study of acute mechanical effects - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Röther, Jens; Tröbs, Monique; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian W.; et al. (Clinical Research in Cardiology, 2017)
OBJECTIVES: The objective was to investigate the acute mechanical effects of post-dilatation on bioresorbable scaffolds (BRS) as determined by optical coherence tomography (OCT). BACKGROUND: Post-dilatation with high-pressure balloons is regarded as a key component of BRS implantation for treatment of coronary artery stenoses. However, the impact of post-dilatation on BRS in vivo has not been thoroughly investigated. METHODS: OCT was performed after the implantation procedure of 51 everolimus-eluting or novolimus-eluting polylactic acid-based BRS with (n = 27) or without non-compliant balloon post-dilatation (n = 24). The number of malapposed struts, strut fractures, edge dissections, residual in-scaffold area stenosis, and incomplete scaffold apposition area was analyzed over the complete length of each BRS with a spacing of 1 mm. RESULTS: OCT revealed a significantly lower incomplete scaffold apposition area if post-dilatation was performed (0.16 ± 0.49 mm2with post-dilatation vs. 2.65 ± 2.78 mm2without post-dilatation, p < 0.001), as well as a significantly lower absolute number of malapposed struts (1 ± 2 with post-dilatation vs. 13 ± 13 without post-dilatation, p < 0.001). No significant differences regarding residual in-scaffold area stenosis, strut fracture, edge dissection, symmetry index, or eccentricity index were observed in patients with vs. without post-dilatation. CONCLUSION: Post-dilatation of BRS with non-compliant balloons significantly reduces the number of malapposed struts and incomplete scaffold apposition area without inducing higher rates of edge dissection or strut fracture.
EVALuna2:33645

Postdilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study on acute mechanistic effects - Blachutzik, F.; Boeder, N.; Wiebe, J.; Mattesini, A.; Doerr, O.; Most, A.; Bauer, T.; Koepp, T.; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; et al. (2016)
EVALuna2:33685

Predictive Value of Age- and Sex-Specific Nomograms of Global Plaque Burden on Coronary Computed Tomography Angiography for Major Cardiac Events - Naoum, Christopher; Berman, Daniel S.; Ahmadi, Amir; Blanke, Philipp; Gransar, Heidi; Narula, Jagat; Shaw, Leslee J.; Kritharides, Leonard; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Budoff, Matthew J.; et al. (Circulation: Cardiovascular Imaging, 2017)
Background-Age-adjusted coronary artery disease (CAD) burden identified on coronary computed tomography angiography predicts major adverse cardiovascular event (MACE) risk; however, it seldom contributes to clinical decision making because of a lack of nomographic data. We aimed to develop clinically pragmatic age- and sex-specific nomograms of CAD burden using coronary computed tomography angiography and to validate their prognostic use. Methods and Results-Patients prospectively enrolled in phase I of the CONFIRM registry (Coronary CT Angiography Evaluation for Clinical Outcomes) were included (derivation cohort: n=21,132; 46% female) to develop CAD nomograms based on age-sex percentiles of segment involvement score (SIS) at each year of life (40-79 years). The relationship between SIS age-sex percentiles (SIS%) and MACE (all-cause death, myocardial infarction, unstable angina, and late revascularization) was tested in a nonoverlapping validation cohort (phase II, CONFIRM registry; n=3030, 44% female) by stratifying patients into 3 SIS% groups (<= 50th, 51-75th, and >75th) and comparing annualized MACE rates and time to MACE using multivariable Cox proportional hazards models adjusting for Framingham risk and chest pain typicality. Age-sex percentiles were well fitted to second-order polynomial curves (men: R-2=0.86 +/- 0.12; women: R-2=0.86 +/- 0.14). Using the nomograms, there were 1576, 965, and 489 patients, respectively, in the <= 50th, 51-75th, and >75th SIS% groups. Annualized event rates were higher among patients with greater CAD burden (2.1% [95% confidence interval: 1.7%-2.7%], 3.9% [95% confidence interval: 3.0%-5.1%], and 7.2% [95% confidence interval: 5.4%-9.6%] in 50th, 51-75th, and >75th SIS% groups, respectively; P<0.001). Adjusted MACE risk was significantly increased among patients in SIS% groups above the median compared with patients below the median (hazard ratio [95% confidence interval]: 1.9 [1.3-2.8] for 51-75th SIS% group and 3.4 [2.3-5.0] for >75th SIS% group; P<0.01 for both). Conclusions-We have developed clinically pragmatic age- and sex-specific nomograms of CAD prevalence using coronary computed tomography angiography findings. Global plaque burden measured using SIS% is predictive of cardiac events independent of traditional risk assessment.
EVALuna2:33649

Predictive Value of Biomarker for Diagnosis and Prognosis of Acute Heart Failure in Geriatric Patients in the Emergency Room - Bahrmann, Philipp; Bertsch, T.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, A. (Zeitschrift für Gerontologie und Geriatrie, 2016)

Predictive value of cardiac computed tomography and the impact of renal function on all cause mortality (from coronary computed tomography angiography evaluation for clinical outcomes) - Dwivedi, Girish; Cocker, Myra; Yam, Yeung; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Cheng, Victor; Chinnaiyan, Kavitha M.; et al. (American Journal of Cardiology, 2013)
Patients with chronic kidney disease have a worse cardiovascular prognosis than those without. The aim of this study was to determine the incremental prognostic value of coronary computed tomographic angiography in predicting mortality across the entire spectrum of renal function in patients with known or suspected coronary artery disease (CAD). A large international multicenter registry was queried, and patients with left ventricular ejection fraction (LVEF) and creatinine data were screened. National Cholesterol Education Program Adult Treatment Panel III risk was calculated. Coronary computed tomographic angiographic results were evaluated for CAD severity (normal, nonobstructive, or obstructive) and an LVEF <50%. Patients were followed for the end point of all-cause mortality. Among 5,655 patients meeting the study criteria, follow-up was available for 5,572 (98.9%; median follow-up duration 18.6 months). All-cause mortality (66 deaths) significantly increased with every 10-unit decrease in renal function (hazard ratio [HR] 1.23, 95% confidence interval [CI] 1.07 to 1.41). All-cause mortality occurred in 0.33% of patients without coronary atherosclerosis, 1.82% of patients with nonobstructive CAD, and 2.43% of patients with obstructive CAD. Multivariate Cox proportional-hazards models revealed that impaired renal function (HR 2.29, 95% CI 1.65 to 3.18), CAD severity (HR 1.81, 95% CI 1.31 to 2.51), and an abnormal LVEF (HR 4.16, 95% CI 2.45 to 7.08) were independent predictors of all-cause mortality. In conclusion, coronary computed tomographic angiographic measures of CAD severity and the LVEF provide effective risk stratification across a wide spectrum of renal function. Furthermore, renal dysfunction, CAD severity, and the LVEF have additive value for predicting all-cause death in patients with suspected obstructive CAD. © 2013 Published by Elsevier Inc. All rights.
CRIS-Team Scopus Importer:2023-03-08

Predictive value of the decrease in circulating dendritic cell precursors in stable coronary artery disease - Yilmaz, Atilla; Schaller, Tina; Cicha, Iwona; Altendorf, Regina; Stumpf, Christian; Klinghammer, Lutz; Ludwig, Josef; Daniel, Werner; Garlichs, Christoph (Clinical Science, 2009)
DCs (dendritic cells) are present in atherosclerotic lesions leading to vascular inflammation, and the number of vascular DCs increases during atherosclerosis. Previously, we have shown that the levels of circulating DCPs (DC precursors) are reduced in acute coronary syndromes through vascular recruitment. In the present study, we have investigated whether DCP levels are also reduced in stable CAD (coronary artery disease). The levels of circulating mDCPs (myeloid DCPs), pDCPs (plasmacytoid DCPs) and tDCP (total DCPs) were investigated using flow cytometry in 290 patients with suspected stable CAD. A coronary angiogram was used to evaluate a CAD score for each patient as follows: (i) CAD excluded (n = 57); (ii) early CAD (n = 63); (iii) moderate CAD (n = 85); and (iv) advanced CAD (n = 85). Compared with controls, patients with advanced stable CAD had lower HDL (high-density lipoprotein)-cholesterol (P = 0.03) and higher creatinine (P = 0.003). In advanced CAD, a significant decrease in circulating mDCPs, pDCPs and tDCPs was observed (each P < 0.001). A significant inverse correlation was observed between the CAD score and mDCPs, pDCPs or tDCPs (each P < 0.001). Patients who required percutaneous coronary intervention or coronary artery bypass grafting had less circulating mDCPs, pDCPs and tDCPs than controls (each P < 0.001). Multiple stepwise logistic regression analysis suggested mDCPs, pDCPs and tDCPs as independent predictors of CAD. In conclusion, we have shown that patients with stable CAD have significantly lower levels of circulating DCPs than healthy individuals. Their decrease appears to be an independent predictor of the presence of, and subsequent therapeutic procedure in, stable CAD. © The Authors Journal compilation © 2009 Biochemical Society.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Atherosclerosis; Coronary artery disease; Dendritic cell; Immune system; Inflammation

Predictors of CT-derived FFR in patients with suspected CAD beyond severity of coronary stenosis - Smolka, S.; Fava, A.; Moshage, Maximilian; Marwan, Mohamed; Achenbach, Stephan; Desai, M. Y. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Predictors of early scaffold thrombosis: results from the multicenter prospective German-Austrian ABSORB RegIstRy - Woehrle, Jochen; Nef, Holger M.; Naber, Christoph; Achenbach, Stephan; Riemer, Thomas; Mehilli, Julinda; Muenzel, Thomas; Schneider, Steffen; Markovic, Sinisa; Seeger, Julia; Rottbauer, Wolfgang; Pfannebecker, Thomas; et al. (Coronary Artery Disease, 2018)
BACKGROUND: In randomized clinical trials, the risk of thrombotic events with the absorb bioresorbable vascular scaffold (BVS) was significantly higher than with metallic drug-eluting stents. We evaluated predictors of scaffold thrombosis in the large-scale, multicenter German-Austrian ABSORB RegIstRy. METHODS AND RESULTS: 3178 patients with treatment of 4252 lesions using 5020 scaffolds were included. Follow-up rate at 6 months was 97.4%. Forty-five (1.42%) patients experienced definite/probable scaffold thrombosis during follow-up. Multiple regression analysis showed implantation of absorb BVS in bifurcation lesions [odds ratio (OR): 4.43; 95% confidence interval (CI): 1.69-11.59; P=0.0024] or treatment in the years 2013/2014 (OR: 1.88; 95% CI: 1.02-3.47; P=0.04) to be significant predictors of scaffold thrombosis. Excluding bifurcation lesions, the incidence of definite/probable scaffold thrombosis decreased from 1.8% (95% CI: 1.17-2.64%) in 2013/2014 to 0.89% (95% CI: 0.5-1.46%) in 2015/2016. In the latter period, absorb BVS were implanted more often in younger patients with less complex de novo lesions, and debulking devices and postdilatation were used more frequently. Between the two treatment periods, there was a significant reduction in myocardial infarction (2.73-1.24%, P<0.01; OR: 0.45; 95% CI: 0.26-0.77), definite/probable scaffold thrombosis (1.79-0.88%, P<0.05; OR: 0.49; 95% CI: 0.26-0.93), and target lesion failure and revascularization during follow-up. CONCLUSION: Improved procedural technique and more strict patient selection may explain a significant decrease in the absorb BVS thrombosis rates during the recruitment period of the large-scale German-Austrian ABSORB RegIstRy. In addition, treatment of bifurcation lesions was identified as an independent predictor of definite/probable scaffold thrombosis.
EVALuna2:35979

Predictors of Left Ventricular Outflow Tract Obstruction After Transcatheter Mitral Valve Replacement - Yoon, Sung-Han; Bleiziffer, Sabine; Latib, Azeem; Eschenbach, Lena; Ancona, Marco; Vincent, Flavien; Kim, Won-Keun; Unbehaum, Axel; Asarni, Masahiko; Dhoble, Abhijeet; Silaschi, Miriam; Frangieh, Antonio H.; et al. (Jacc-Cardiovascular Interventions, 2019)
Objectives: The aim of this study was to evaluate the predictors of left ventricular outflow tract (LVOT) obstruction after transcatheter mitral valve replacement (TMVR). Background: LVOT obstruction is a major concern with TMVR, but limited data exist regarding its predictors and impact on outcomes. Methods: Patients with pre-procedural multidetector row computed tomography (MDCT) undergoing TMVR for failed mitral bioprosthetic valves (valve-in-valve), annuloplasty rings (valve-in-ring), and mitral annular calcification (valve-in-MAC) were included in this study. Echocardiographic and procedural characteristics were recorded, and comprehensive assessment with MDCT was performed to identify the predictors of LVOT obstruction (defined as an increment of mean LVOT gradient ≥10 mm Hg from baseline). The new LVOT (neo-LVOT) area left after TMVR was estimated by embedding a virtual valve into the mitral annulus on MDCT, simulating the procedure. Results: Among 194 patients with pre-procedural MDCT undergoing TMVR (valve-in-valve, 107 patients; valve-in-ring, 50 patients; valve-in-MAC, 37 patients), LVOT obstruction was observed in 26 patients (13.4%), with a higher rate after valve-in-MAC than valve-in-ring and valve-in-valve (54.1% vs. 8.0% vs. 1.9%; p < 0.001). Patients with LVOT obstruction had significantly higher procedural mortality compared with those without LVOT obstruction (34.6% vs. 2.4%; p < 0.001). Receiver-operating characteristic curve analysis showed that an estimated neo-LVOT area ≤1.7 cm2 predicted LVOT obstruction with sensitivity of 96.2% and specificity of 92.3%. Conclusions: LVOT obstruction after TMVR was associated with higher procedural mortality. A small estimated neo-LVOT area was significantly associated with LVOT obstruction after TMVR and may help identify patients at high risk for LVOT obstruction.
CRIS-Team Scopus Importer:2019-07-09
Keywords: annuloplasty ring; degenerated bioprosthesis; left ventricular outflow tract obstruction; mitral annular calcification; mitral valve; transcatheter valve implantation

Predictors of scaffold failure and impact of optimized scaffold implantation technique on outcome: Results from the German-Austrian ABSORB RegIstRy - Boeder, Niklas F.; Kastner, Johannes; Mehilli, Julinda; Muenzel, Thomas; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Riemer, Thomas; Achenbach, Stephan; et al. (Catheterization and Cardiovascular Interventions, 2021)
Aims We aimed to investigate predictors of scaffold failure and the potential impact of an optimized scaffold implantation technique by means of a learning curve on long-term clinical outcome after bioresorbable scaffold (BRS) implantation and to evaluate predictors of scaffold failure.
CRIS-Team WoS Importer:2021-07-02

Predictors of Technical Failure in Transradial Coronary Angiography and Intervention - Tröbs, Monique; Achenbach, Stephan; Plank, Pia Maria; Röther, Jens; Klinghammer, Lutz; Blachutzik, Florian; Schlundt, Christian; Marwan, Mohamed (American Journal of Cardiology, 2017)
Transradial access for coronary angiography and intervention is preferred over the femoral approach but can be technically challenging. Identification of predictors of transradial access failure is important, especially in the context of acute coronary syndromes. We therefore retrospectively analyzed 13,095 consecutive patients (66 ± 12 years, 64% male) in whom transradial access was attempted for coronary angiography or intervention to identify predictors of transradial access failure. Angiograms and patient files were systematically reviewed to analyze patient characteristics associated with failure. Transradial access failure rate was 6.8% (909 of 13,095). Patients with transradial access failure were more frequently female (9.5% vs 5.5%; p <0.001), significantly older (68 ± 12 vs 66 ± 12 years, p <0.001), and had a smaller body surface area (1.89 ± 0.21 vs 1.94 ± 0.2 m2; p <0.001). Transradial failure was not significantly more frequent in ST-elevation myocardial infarction versus other patients (8.1% vs 6.9%, p = 0.195). After multivariable adjustment, only female sex (odds ratio [OR] 1.44, p <0.001), higher patient age (OR 1.01/year, p = 0.002), and lower height (OR 0.98/cm, p = 0.004) independently predicted transradial access failure. In conclusion, female sex, higher age, and smaller height independently predict transradial access failure in coronary angiography and intervention. Failure rate in ST-elevation myocardial infarction is not significantly increased.
EVALuna2:33605

Preoperative assessment of the aortic arch in children younger than 1 year with congenital heart disease: utility of low-dose high-pitch dual-source computed tomography. A single-centre, retrospective analysis of 62 cases - Glöckler, Martin; Halbfass, Julia; Koch, Andreas; Dittrich, Sven; Achenbach, Stephan; Rueffer, Andre; Ihlenburg, Katharina Susanne; Cesnjevar, Robert; May, Matthias; Uder, Michael; Rompel, Oliver (European Journal of Cardio-Thoracic Surgery, 2014)
To evaluate the feasibility, image quality and impact of 3D imaging in low-dose high-pitch dual-source computed tomography (DSCT) to assess arbitrary anatomical malformations of the aortic arch in children <1 year of age with congenital heart disease (CHD).Between January 2010 and May 2013, DSCT was performed to assess the aortic arch anatomy in a total of 62 consecutive patients with CHD (aged 0-348 days). DSCT was used whenever conventional echocardiography was not sufficient to display the complex anatomy entirely. Image data acquisition was realized within a single cardiac cycle using prospective ECG triggering. 3D reconstruction for surgical planning was performed. Image quality was assessed retrospectively, using a 4-point scale from '1 = no artefacts' to '4 = uninterpretable'. The accuracy and impact of the 3D reconstructions was compared with intraoperative findings using a 5-point scale (from '1 = essential' to '5 = misleading'). Administered radiation exposure was evaluated.Imaging was successful in all patients, image quality was rated 1.34 on the 4-point scale and the impact of the 3D reconstructions for surgical planning was 2.05 on the 5-point scale. Mean dose-length product was 6.8 ± 2.6 mGy cm, and the effective dose was 0.45 ± 0.13 mSv (0.21-0.74).DSCT is a fast and appropriate imaging modality in the preoperative assessment of the aortic arch for surgical planning in CHD.
EVALuna2:11864

Preprocedural coronary CT angiography significantly improves success rates of PCI for chronic total occlusion - Rolf, Andreas; Werner, Gerald S.; Schuhbaeck, Annika; Rixe, Johannes; Moellmann, Helge; Nef, Holger M.; Gundermann, Constantin; Liebetrau, Christoph; Krombach, Gabriele A.; Hamm, Christian W.; Achenbach, Stephan (International Journal of Cardiovascular Imaging, 2013)
Chronic total occlusions of coronary arteries occur in about 20 % of patients with suspected coronary artery disease and are more frequent with increasing age. The success rate of interventions is lower (55-80 %) compared to conventional lesions (>90 %). Coronary CT angiography (coronary CTA) provides information about the occluded segment, which cannot be obtained from invasive angiograms (XA). We therefore hypothesized that preprocedural coronary CTA may improve success rates of percutaneous coronary intervention (PCI) for coronary arteries (CTO). 30 patients with chronic total coronary artery occlusions (mean age 73 years, 26 men) and predicted high complexity were imaged by coronary CTA prior to PCI for CTO. CT data sets were acquired with a 64 detector row dual source scanner and retrograde ECG gating, 0.6 mm collimation and z-flying focal spot, yielding isovoxel spatial resolution of about 0.4 mm. Based on the CT data sets, established complexity criteria for CTO (Euro CTO club, Di Mario et al. in EuroIntervention 3(1):30-43, 2007) were evaluated and compared to invasive coronary angiography. Three-dimensional volume-rendered images of the occluded coronary artery were displayed in the catheterization lab during PCI to guide the advancement of the wire. PCI success, defined as the ability to advance the guide wire into the distal lumen with thrombolysis in myocardial infarction III flow was compared to 43 controls without coronary CTA using propensity score matching based on established criteria of procedural success. The course of the occluded segments was visualized by coronary CTA in all cases. Calcification, lesion length, stump morphology and presence of side branches were underestimated by invasive angiograms when compared to coronary CTA. PCI success rate in 30 patients who underwent pre-procedural CTA was significantly higher than in patients without prior coronary CTA [unmatched: CT 90 % (27/30) vs. no CT 63 % (27/43), p = 0.009; matched: CT 88 % (22/25) vs. no CT 64 % (16/25) p = 0.03]. Through information not readily seen on invasive coronary angiography, coronary CTA can significantly enhance success rates of PCI for CTO. © 2013 Springer Science+Business Media Dordrecht.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chronic total occlusion; Coronary computed tomography angiography; PCI

Prevalence and Clinical Impact of Bioprosthesis Thrombosis After Transcatheter Aortic Valve Implantation. A Collaborative Meta-Analysis - Rheude, Tobias; Pellegrini, Costanza; Stortecky, Stefan; Xhepa, Erion; Alvarez, Hector; Ammon, Fabian; Pilgrim, Thomas; Kastrati, Adnan; Cassese, Salvatore; Joner, Michael (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

PREVALENCE AND IMPACT OF PREFORMED ANTI-HLA ANTIBODIES OF THE IGA ISOTYPE IN KIDNEY TRANSPLANTATION - Preiss, A.; Bach, Christian; Spriewald, B.; Banas, B.; Zecher, D.; Arnold, Martin (2018)
EVALuna2:35090

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Prior-Free Respiratory Motion Estimation in Rotational Angiography - Unberath, Mathias; Taubmann, Oliver; Aichert, André; Achenbach, Stephan; Maier, Andreas (IEEE Transactions on Medical Imaging, 2018)
Rotational coronary angiography using C-arm angiography systems enables intra-procedural 3-D imaging that is considered beneficial for diagnostic assessment and interventional guidance. Despite previous efforts, rotational angiography was not yet successfully established in clinical practice for coronary artery procedures due to challenges associated with substantial intra-scan respiratory and cardiac motion. While gating handles cardiac motion during reconstruction, respiratory motion requires compensation. State-of-the-art algorithms rely on 3-D / 2-D registration that requires an uncompensated reconstruction of sufficient quality. To overcome this limitation, we investigate two prior-free respiratory motion estimation methods based on the optimization of: 1) epipolar consistency conditions (ECCs) and 2) a task-based auto-focus measure (AFM). The methods assess redundancies in projection images or impose favorable properties of 3-D space, respectively, and are used to estimate the respiratory motion of the coronary arteries within rotational angiograms. We evaluate our algorithms on the publicly available CAVAREV benchmark and on clinical data. We quantify reductions in error due to respiratory motion compensation using a dedicated reconstruction domain metric. Moreover, we study the improvements in image quality when using an analytic and a novel temporal total variation regularized algebraic reconstruction algorithm. We observed substantial improvement in all figures of merit compared with the uncompensated case. Improvements in image quality presented as a reduction of double edges, blurring, and noise. Benefits of the proposed corrections were notable even in cases suffering little corruption from respiratory motion, translating to an improvement in the vessel sharpness of (6.08 ± 4.46)% and (14.7 ± 8.80)% when the ECC-based and the AFM-based compensation were applied. On the CAVAREV data, our motion compensation approach exhibits an improvement of (27.6 ± 7.5)% and (97.0 ± 17.7)% when the ECC and AFM were used, respectively. At the time of writing, our method based on AFM is leading the CAVAREV scoreboard. Both motion estimation strategies are purely image-based and accurately estimate the displacements of the coronary arteries due to respiration. While current evidence suggests the superior performance of AFM, future work will further investigate the use of ECC in the context of angiography as they solely rely on geometric calibration and projection-domain images.
EVALuna2:35976

Procedural Outcomes of a Self-Expanding Transcatheter Heart Valve in Patients with Porcelain Aorta - Eckel, Clemens; Blumenstein, Johannes; Grothusen, Christina; Tiyerili, Vedat; Elsaesser, Albrecht; Dohmen, Guido; Zeckzer, Anna; Gaede, Luise; Choi, Yeong-Hoon; Charitos, Efstratios I.; Hamm, Christian W.; Kim, Won-Keun; et al. (Journal of Clinical Medicine, 2023)
Background: Severe calcification of the ascending aorta increases the peri-operative risk for neurological complications in patients with severe aortic stenosis. Transcatheter aortic valve implantation (TAVI) seems to be an optimal treatment option in these patients. However, the impact of the extent of aortic calcification on procedural and neurological outcomes during TAVI is unclear. Methods: Data from 3010 patients with severe native aortic valve stenosis treated with ACURATE neo/neo2 from May 2012 to July 2022 were evaluated and matched by 2-to-1 nearest-neighbor matching to identify one patient with porcelain aorta (PA) (n = 492) compared with two patients without PA (n = 984). PA was additionally subdivided into circumferential (classic PA) (n = 89; 3.0%) and non-circumferential (partial PA) (n = 403; 13.4%) calcification. We compared outcomes according to VARC-3 criteria among patients with and without PA and identified predictors for occurrence of stroke in the overall population. Results: Technical success (88.5% vs. 87.4%, p = 0.589) and device success at 30 days (82.3% vs. 81.5%, p = 0.755) after transcatheter ACURATE neo/neo2 implantation according to VARC-3 definition was high and did not differ between non-calcified aortas or PA. The rate of in-hospital complications according to VARC-3-definitions was low in both groups. Rates of all stroke (3.2% (n = 31) vs. 2.6% (n = 13), p = 0.705) or transitory ischemic attacks (1.1% vs. 1.2%, p =1.000) did not differ significantly. Thirty-day all-cause mortality did not differ (3.0% vs. 3.2%, RR 1.1; p = 0.775). Overall device migration/embolization (OR 5.0 [2.10; 11.87]), severe bleeding (OR 1.79 [1.11; 2.89]), and major structural cardiac complications (OR 3.37 [1.32; 8.57]) were identified as independent predictors for in-hospital stroke in a multivariate analysis after implantation of ACURATE neo/neo2. Conclusion: A porcelain aorta does not increase the risk of neurological complications after transfemoral ACURATE neo/neo2 implantation. Based on these findings, transfemoral ACURATE neo/neo2 implantation is safe in these particularly vulnerable patients.
CRIS-Team WoS Importer:2023-03-10

Procedural Safety and Device Performance of the Portico (TM) Valve from Experienced TAVI Centers: 30-Day Outcomes in the Multicenter CONFIDENCE Registry - Mollmann, Helge; Linke, Axel; Nombela-Franco, Luis; Sluka, Martin; Oteo Dominguez, Juan Francisco; Montorfano, Matteo; Kim, Won-Keun; Arnold, Martin; Vasa-Nicotera, Mariuca; Conradi, Lenard; Camuglia, Anthony; Bedogni, Francesco; et al. (Journal of Clinical Medicine, 2022)
A total of 1001 subjects (82.0 years, 62.5% female, 63.7% NYHA III/IV at baseline) with severe aortic stenosis at high surgical risk were enrolled in the prospective CONFIDENCE registry and treated with a Portico (TM) transcatheter heart valve (THV) using either a first-generation delivery system (DS) or the FlexNav (TM) DS. The objective of this registry is to characterize the procedural safety and device performance of the Portico (TM) THV at 30 days. The study collected 'standard-of-care' clinical and device performance data, with adverse events adjudicated by an independent clinical event committee according to the Valve Academic Research Consortium-2 criteria. The implantation of a single Portico (TM) THV was successful in 97.5% of subjects. The 30-day all-cause mortality, cardiovascular mortality, and disabling stroke rates were 2.6%, 2.1%, and 1.8%, respectively. A new pacemaker was implanted in 19.0% of subjects at 30 days. At 30 days, the effective orifice area and mean gradient values were 1.82 cm(2) and 7.1 mmHg, respectively. The 30-day rate of moderate paravalvular leak (PVL) was 2.1%, with no occurrence of severe PVL. The Portico (TM) THV demonstrated improved hemodynamic performance and low rates of safety events at 30 days in a large cohort of subjects implanted with the Portico (TM) THV with either the first-generation DS or FlexNav (TM) DS.
CRIS-Team WoS Importer:2022-09-09

Prognostic and therapeutic implications of statin and aspirin therapy in individuals with nonobstructive coronary artery disease: results from the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry) re - Chow, Benjamin J. W.; Small, Gary; Yam, Yeung; Chen, Li; Mcpherson, Ruth; Achenbach, Stephan; Al-Mallah, Mouaz; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (Arteriosclerosis, Thrombosis, and Vascular Biology, 2015)
We sought to examine the risk of mortality associated with nonobstructive coronary artery disease (CAD) and to determine the impact of baseline statin and aspirin use on mortality.Coronary computed tomographic angiography permits direct visualization of nonobstructive CAD. To date, the prognostic implications of nonobstructive CAD and the potential benefit of directing therapy based on nonobstructive CAD have not been carefully examined. A total of 27 125 consecutive patients who underwent computed tomographic angiography (12 enrolling centers and 6 countries) were prospectively entered into the COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter (CONFIRM) registry. Patients, without history of previous CAD or obstructive CAD, for whom baseline statin and aspirin use was available were analyzed. Each coronary segment was classified as normal or nonobstructive CAD (1%-49% stenosis). Patients were followed up for a median of 27.2 months for all-cause mortality. The study comprised 10 418 patients (5712 normal and 4706 with nonobstructive CAD). In multivariable analyses, patients with nonobstructive CAD had a 6% (95% confidence interval, 1%-12%) higher risk of mortality for each additional segment with nonobstructive plaque (P=0.021). Baseline statin use was associated with a reduced risk of mortality (hazard ratio, 0.44; 95% confidence interval, 0.28-0.68; P=0.0003), a benefit that was present for individuals with nonobstructive CAD (hazard ratio, 0.32; 95% confidence interval, 0.19-0.55; P<0.001) but not for those without plaque (hazard ratio, 0.66; 95% confidence interval, 0.30-1.43; P=0.287). When stratified by National Cholesterol Education Program/Adult Treatment Program III, no mortality benefit was observed in individuals without plaque. Aspirin use was not associated with mortality benefit, irrespective of the status of plaque.The presence and extent of nonobstructive CAD predicted mortality. Baseline statin therapy was associated with a significant reduction in mortality for individuals with nonobstructive CAD but not for individuals without CAD.URL: http://clinicaltrials.gov/. Unique identifier NCT01443637.
EVALuna2:12055

Prognostication of post-infarct chronic heart failure: Superiority of clinical assessment vs. cardiopulmonary and left ventricular function analysis - Nixdorff, Uwe; Drees, Michael; von Bardeleben, Stephan; Mohr-Kahaly, Susanne; Klinghammer, Lutz (International Journal of Cardiology, 2009)
Background: Prognostication of congestive heart failure post-myocardial infarction (MI) is important for decision making. We sought of a head-to-head comparison between the prognostic implication of clinical, cardiopulmonary, and left ventricular (LV) function assessment. Methods: Retrospectively, 100 consecutive post-MI patients (MI history 1418 ± 1668 days ago) were stratified by NYHA functional classification system, cardiopulmonary exercise testing (CPX) [oxygen consumption at maximal exercise (VO2max) and at the anaerobic threshold (VO2AT) resulting in the Weber classification], and LV function analysis by M-mode and two-dimensional echocardiography [LV end-diastolic and -systolic diameter index (LVDDI and LVSDI), shortening fraction (%D), and LV end-diastolic and -systolic volume index (EDVI and ESVI), LV ejection fraction (EF)]. Patients were controlled by phone call 1470 ± 607 days later. Results: There was only a modest correlation between NYHA and Weber classes (r = 0.402) and no correlation between VO2max and ESVI (r = 0.080) nor between NYHA and ESVI (r = 0.174). Several parameters (ESVI, LVDDI, LVSDI, %D) could discriminate NYHA classes to a higher significance (p = 0.05; 0.0008; 0.0002; 0.04) than the Weber classes (n.s.; p = 0.03; n.s.; n.s.). The following parameters could significantly differentiate quartiles in a log-rank analysis (Kaplan-Meier survival curves): NYHA classes (p = 0.0001), Weber classes (p = 0.069), EDVI (p = 0.004), ESVI (p = 0.0001), EF (p = 0.002), LVDDI (p = 0.002), LVSDI (p < 0.001) and %D (p < 0.001). Multivariate analysis isolated the following three parameters implying decreasing, independent prognostic information: NYHA classes (p = 0.001), ESVI (p = 0.003), and Weber classes (p = 0.040). Conclusions: In post-MI patients the thorough clinical assessment according the NYHA functional classification system implies higher prognostic information than more objective measures. This should be considered especially in primary care and should lessen the dependence on costly and expertise-dependent technical investigations. © 2007 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Cardiopulmonary exercise test; Congestive heart failure; Echocardiography; Myocardial infarction; NYHA; Prognosis

Prognostic implications of coronary artery calcium in the absence of coronary artery luminal narrowing - Cho, Iksung; Hartaigh, Briain O.; Gransar, Heidi; Gransar, Heidi; Valenti, Valentina; Lin, Fay Y.; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Callister, Tracy Q.; Al-Mallah, Mouaz H.; Cademartiri, Filippo; et al. (Atherosclerosis, 2017)
BACKGROUND AND AIMS: Coronary artery calcium (CAC) scoring is a predictor of future adverse clinical events, and a surrogate measure of overall coronary artery plaque burden. Coronary computed tomographic angiography (CCTA) is a contrast-enhanced method that allows for visualization of plaque as well as whether that plaque causes luminal narrowing. To date, the prognosis of individuals with CAC but without stenosis has not been reported. We explored the prevalence of CAC>0 and its prognostic utility for future mortality for patients without luminal narrowing by CCTA. METHODS: From 17 sites in 9 countries, we identified patients without known coronary artery disease, who underwent CAC scoring and CCTA, and were followed for >3 years. CCTA was graded for % stenosis according to a modified American Heart Association 16-segment model. We calculated hazard ratios (HR) with 95% confidence intervals (95% CI) for incident mortality and compared risk of death for patients as a function of presence or absence of CAC and presence or absence of luminal narrowing by CCTA. RESULTS: Among 6656 patients who underwent CCTA and CAC scoring, 399 patients (6.0%) had no coronary luminal narrowing but CAC>0. During a median follow-up of 5.1 years (IQR: 3.9-5.9 years), 456 deaths occurred. Compared to individuals without luminal narrowing or CAC, individuals without luminal narrowing but CAC>0 were older, more likely to be male and had higher rates of diabetes, hypertension, and dyslipidemia. Individuals without luminal narrowing but CAC experienced a 2-fold increased risk of mortality, with increasing risk of mortality with higher CAC score. Following adjustment, incident death persisted (HR, 1.8; 95% CI, 1.1-2.9, p = 0.02) among patients without luminal narrowing but with CAC>0 compared with patients whose CACS = 0. Individuals without luminal narrowing but CAC ≥100 had mortality risks similar to individuals with non-obstructive CAD (0 < stenosis<50%) by CCTA [HR 2.5 (95% CI 1.3-4.9) and 2.2 (95% CI 1.6-3.0), respectively]. CONCLUSIONS: Patients without luminal narrowing but with CAC experience greater risk of 5-year mortality. Patients with CAC score ≥100 and no coronary luminal narrowing experience death rates similar to those with non-obstructive CAD.
EVALuna2:33633

Prognostic significance of calcified plaque among symptomatic patients with nonobstructive coronary artery disease - Shah, Sana; Bellam, Naveen; Leipsic, Jonathon; Berman, Daniel S.; Quyyumi, Arshed; Hausleiter, Joerg; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Fillippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (Journal of Nuclear Cardiology, 2014)
Coronary artery calcium (CAC) is a well-established predictor of clinical outcomes for population screening. Limited evidence is available as to its predictive value in symptomatic patients without obstructive coronary artery disease (CAD). The aim of the current study was to assess the prognostic value of CAC scores among symptomatic patients with nonobstructive CAD.From the COronary Computed Tomographic Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter (CONFIRM) registry, 7,200 symptomatic patients with nonobstructive CAD (<50% coronary stenosis) on coronary-computed tomographic angiography were prospectively enrolled and followed for a median of 2.1 years. Patients were categorized as without (0% stenosis) or with (>0% but <50% coronary stenosis) a luminal stenosis. CAC scores were calculated using the Agatston method. Univariable and multivariable Cox proportional hazard models were employed to estimate all-cause mortality and/or myocardial infarction (MI). Four-year death and death or MI rates were 1.9% and 3.3%.Of the 4,380 patients with no luminal stenosis, 86% had CAC scores of <10 while those with a luminal stenosis had more prevalent and extensive CAC with 31.9% having a CAC score of >=100. Among patients with no luminal stenosis, CAC was not predictive of all-cause mortality (P = .44). However, among patients with a luminal stenosis, 4-year mortality rates ranged from 0.8% to 9.8% for CAC scores of 0 to >=400 (P < .0001). The mortality hazard was 6.0 (P = .004) and 13.3 (P < .0001) for patients with a CAC score of 100-399 and >=400. In patients with a luminal stenosis, CAC remained independently predictive in all-cause mortality (P < .0001) and death or MI (P < .0001) in multivariable models containing CAD risk factors and presenting symptoms.CAC allows for the identification of those at an increased hazard for death or MI in symptomatic patients with nonobstructive disease. From the CONFIRM registry, the extent of CAC was an independent estimator of long-term prognosis among symptomatic patients with luminal stenosis and may further define risk and guide preventive strategies in patients with nonobstructive CAD.
EVALuna2:12005

Prognostic Significance of Nonobstructive Left Main Coronary Artery Disease in Patients With and Without Diabetes: Long-Term Outcomes From the CONFIRM Registry - Lee, Juhwan; Shaikh, Kashif; Nakanishi, Rine; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Bax, Jeroen J.; Berman, Daniel S.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk Jae; et al. (Heart Lung and Circulation, 2022)
Background: Prognostic significance of non-obstructive left main (LM) disease was recently reported. However, the influence of diabetes mellitus (DM) on event rates in patients with and without non-obstructive LM disease is not well-known. Methods: We evaluated 27,252 patients undergoing coronary computed tomographic angiography from the COroNary CT Angiography Evaluation For Clinical Outcomes: An InteRnational Multicenter (CONFIRM) Registry. Cumulative long-term incidence of all-cause mortality (ACM) was assessed between DM and non-DM patients by normal or non-obstructive LM disease (1–49% stenosis). Results: The mean age of the study population was 57.6 ± 12.6 years. Of the 27,252 patients, 4,434 (16%) patients had DM. A total of 899 (3%) deaths occurred during the follow-up of 3.6±1.9. years. Compared to patients with normal LM, those with non-obstructive LM had more pronounced overall coronary atherosclerosis and more cardiovascular risk factors. After clinical risk factors, segment involvement score, and stenosis severity adjustment, compared to patients without DM and normal LM, patients with DM were associated with increased ACM regardless of normal (HR 1.48, 95% CI 1.22–1.78, p<0.001) or non-obstructive LM (HR 1.46, 95% CI 1.04–2.04, p=0.029), while nonobstructive LM disease was not associated with increased ACM in patients without DM (HR 0.85, 95% CI 0.67–1.07, p=0.165) and there was no significant interaction between DM and LM status (HR 1.03, 95% CI 0.69–1.54, p=0.879). Conclusion: From the CONFIRM registry, we demonstrated that DM was associated with increased ACM. However, the presence of non-obstructive LM was not an independent risk marker of ACM, and there was no significant interaction between DM and non-obstructive LM disease for ACM.
CRIS-Team Scopus Importer:2022-12-16
Keywords: All-cause mortality; Coronary computed tomographic angiography; Diabetes mellitus; Left main; Nonobstructive coronary artery disease

Prognostic Significance of Nonobstructive Left Main Coronary Artery Disease in Women Versus Men Long-Term Outcomes From the CONFIRM (Coronary CT Angiography Evaluation For Clinical Outcomes: An International Multicenter) Registry - Xie, Joe X.; Eshtehardi, Parham; Varghese, Tina; Goyal, Abhinav; Mehta, Puja K.; Kang, William; Leipsic, Jonathon; Hartaigh, Briain O.; Merz, C. Noel Bairey; Berman, Daniel S.; Gransar, Heidi; Budoff, Matthew J.; et al. (Circulation: Cardiovascular Imaging, 2017)
Background-Patients with obstructive (<= 50% stenosis) left main (LM) coronary artery disease (CAD) are at high risk for adverse events; prior studies have also documented worse outcomes among women than men with severe multivessel/LM CAD. However, the prognostic significance of nonobstructive (1%-49% stenosis) LM CAD, including sex-specific differences, has not been previously examined. Methods and Results-In the long-term CONFIRM (Coronary CT Angiography Evaluation For Clinical Outcomes: An International Multicenter) registry, patients underwent elective coronary computed tomographic angiography for suspected CAD and were followed for 5 years. After excluding those with obstructive LM CAD, 5166 patients were categorized as having normal LM or nonobstructive LM (18% of cohort). Cumulative 5-year incidence of death, myocardial infarction, or revascularization was higher among patients with nonobstructive LM than normal LM in both women and men: women (34.3% versus 15.4%; P<0.0001); men (24.6% versus 18.2%; P<0.0001). A significant interaction existed between sex and LM status for the composite outcome (P=0.001). In multivariable Cox regression, the presence of nonobstructive LM plaque increased the risk for the composite outcome in women (adjusted hazard ratio, 1.48; P=0.005) but not in men (adjusted hazard ratio, 0.98, P=0.806). In subgroup analysis, women with nonobstructive LM CAD had a nearly 80% higher risk for events than men with nonobstructive LM CAD (adjusted hazard ratio, 1.78; P=0.017); sex-specific interactions were not observed across other patterns (eg, location or extent) of nonobstructive plaque. Conclusion-Nonobstructive LM CAD was frequently detected on coronary computed tomographic angiography and strongly associated with adverse events among women. Recognizing the sex-specific prognostic significance of nonobstructive LM plaque may augment risk stratification efforts.
EVALuna2:33623

Prognostic significance of plaque location in non-obstructive coronary artery disease: from the CONFIRM registry - Han, Donghee; Chen, Billy; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Budoff, Matthew J.; Cademartiri, Filippo; Maffei, Erica; Callister, Tracy Q.; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Delago, Augustin; et al. (European Heart Journal - Cardiovascular Imaging, 2021)
Aim Obstructive coronary artery disease (CAD) in proximal coronary segments is associated with a poor prognosis. However, the relative importance of plaque location regarding the risk for major adverse cardiovascular events (MACE) in patients with non-obstructive CAD has not been well defined. Methods and results From the Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter (CONFIRM) registry, 4644 patients without obstructive CAD were included in this study. The degree of stenosis was classified as 0 (no) and 1-49% (non-obstructive). Proximal involvement was defined as any plaque present in the left main or the proximal segment of the left anterior descending artery, left circumflex artery, and right coronary artery. Extensive CAD was defined as segment involvement score of >4. During a median follow-up of 5.2 years (interquartile range 4.1-6.0), 340 (7.3%) MACE occurred. Within the non-obstructive CAD group (n = 2065), proximal involvement was observed in 1767 (85.6%) cases. When compared to non-obstructive CAD patients without proximal involvement, those with proximal involvement had an increased MACE risk (log-rank P = 0.033). Multivariate Cox analysis showed when compared to patients with no CAD, proximal non-obstructive CAD was associated with increased MACE risk [hazard ratio (HR) 1.90, 95% confidence interval (CI) 1.47-2.45, P < 0.001] after adjusting for extensive CAD and conventional cardiovascular risk factors; however, non-proximal non-obstructive CAD did not increase MACE risk (HR 1.26, 95% CI 0.79-2.01, P = 0.339). Conclusions Independent of plaque extent, proximal coronary involvement was associated with increased MACE risk in patients with non-obstructive CAD. The plaque location information by coronary computed tomography angiography may provide additional risk prediction over CAD extent in patients with non-obstructive CAD.
CRIS-Team WoS Importer:2022-05-13

Prognostic significance of subtle coronary calcification in patients with zero coronary artery calcium score: From the CONFIRM registry - Han, Donghee; Klein, Eyal; Friedman, John; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H.; Budoff, Matthew J.; Cademartiri, Filippo; Maffei, Erica; Callister, Tracy Q.; Chinnaiyan, Kavitha; Chow, Benjamin J.W.; et al. (Atherosclerosis, 2020)
Background and aims: The Agatston coronary artery calcium score (CACS) may fail to identify small or less dense coronary calcification that can be detected on coronary CT angiography (CCTA). We investigated the prevalence and prognostic importance of subtle calcified plaques on CCTA among individuals with CACS 0. Methods: From the prospective multicenter CONFIRM registry, we evaluated patients without known CAD who underwent CAC scan and CCTA. CACS was categorized as 0, 1–10, 11–100, 101–400, and >400. Patients with CACS 0 were stratified according to the visual presence of coronary plaques on CCTA. Plaque composition was categorized as non-calcified (NCP), mixed (MP) and calcified (CP). The primary outcome was a major adverse cardiac event (MACE) which was defined as death and myocardial infarction. Results: Of 4049 patients, 1741 (43%) had a CACS 0. NCP and plaques that contained calcium (MP or CP) were detected by CCTA in 110 patients (6% of CACS 0) and 64 patients (4% of CACS 0), respectively. During a 5.6 years median follow-up (IQR 5.1–6.2 years), 413 MACE events occurred (13%). Patients with CACS 0 and MP/CP detected by CCTA had similar MACE risk compared to patients with CACS 1–10 (p = 0.868). In patients with CACS 0, after adjustment for risk factors and symptom, MP/CP was associated with an increased MACE risk compared to those with entirely normal CCTA (HR 2.39, 95% CI [1.09–5.24], p = 0.030). Conclusions: A small but non-negligible proportion of patients with CACS 0 had identifiable coronary calcification, which was associated with increased MACE risk. Modifying CAC image acquisition and/or scoring methods could improve the detection of subtle coronary calcification.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Agatston score; Computed tomography; Coronary artery calcium; Coronary artery disease

Prognostic value and incremental benefit of ischaemic myocardial burden subtended by non-invasive CT-derived fractional flow reserve (FFRCT) significant stenoses - Ihdayhid, A. R.; Norgaard, B. L.; Khav, N.; Gaur, S.; Leipsic, J.; Nerlekar, N.; Osawa, K.; Miyoshi, T.; Jensen, J.; Kimura, T.; Shiomi, H.; Erglis, A.; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Prognostic Value and Risk Continuum of Noninvasive Fractional Flow Reserve Derived from Coronary CT Angiography - Ihdayhid, Addul Rahman; Norgaard, Bjarne L.; Gaur, Sara; Leipsic, Jonathan; Nerlekar, Nitesh; Osawa, Kazuhiro; Miyoshi, Toru; Jensen, Jeper M.; Kimura, Takeshi; Shiomi, Hiroki; Erglis, Andrejs; Jegere, Sande; et al. (Radiology, 2019)
Background: Coronary CT angiography with noninvasive fractional flow reserve (FFR) predicts lesion-specific ischemia when compared with invasive FFR. The longer term prognostic value of CT-derived FFR (FFRCT) is unknown.
CRIS-Team WoS Importer:2019-08-02

Prognostic value of age adjusted segment involvement score as measured by coronary computed tomography: a potential marker of vascular age - Ayoub, Chadi; Kritharides, Leonard; Yam, Yeung; Chen, Li; Hossain, Alomgir; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; et al. (Heart and Vessels, 2018)
Extent of coronary atherosclerotic disease (CAD) burden on coronary computed tomography angiography (CCTA) as measured by segment involvement score (SIS) has a prognostic value. We sought to investigate the incremental prognostic value of 'age adjusted SIS' (aSIS), which may be a marker of premature atherosclerosis and vascular age. Consecutive patients were prospectively enrolled into the CONFIRM (Coronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicentre) multinational observational study. Patients were followed for the outcome of all-cause death. aSIS was calculated on CCTA for each patient, and its incremental prognostic value was evaluated. A total of 22,211 patients [mean age 58.5 ± 12.7 years, 55.8% male) with a median follow-up of 27.3 months (IQR 17.8, 35.4)] were identified. After adjustment for clinical factors and presence of obstructive CAD, higher aSIS was associated with increased death on multivariable analysis, with hazard ratio (HR) 2.40 (1.83-3.16, p < 0.001), C-statistic 0.723 (0.700-0.756), net reclassification improvement (NRI) 0.36 (0.26-0.47, p < 0.001), and relative integrated discrimination improvement (IDI) 0.33 (p = 0.009). aSIS had HR 3.48 (2.33-5.18, p < 0.001) for mortality in those without obstructive CAD, compared to HR 1.79 (1.25-2.58, p = 0.02) in those with obstructive CAD. In conclusion, aSIS has an incremental prognostic value to traditional risk factors and obstructive CAD, and may enhance CCTA risk stratification.
EVALuna2:35963

Prognostic value of chronic total occlusions detected on coronary computed tomographic angiography - Opolski, Maksymilian P.; Gransar, Heidi; Lu, Yao; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Bax, Jeroen J.; Berman, Daniel S.; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; et al. (Heart, 2019)
Objective Data describing clinical relevance of chronic total occlusion (CTO) identified by coronary CT angiography (CCTA) have not been reported to date. We investigated the prognosis of CTO on CCTA. Methods We identified 22 828 patients without prior known coronary artery disease (CAD), who were followed for a median of 26 months. Based on CCTA, coronary lesions were graded as normal (no atherosclerosis), non-obstructive (1%-49%), moderate-to-severe (50%-99%) or totally occluded (100%). All-cause mortality, and major adverse cardiac events defined as mortality, non-fatal myocardial infarction and late coronary revascularisation (>= 90 days after CCTA) were assessed. Results The distribution of patients with normal coronaries, non-obstructive CAD, moderate-to-severe CAD and CTO was 10 034 (44%), 7965 (34.9%), 4598 (20.1%) and 231 (1%), respectively. The mortality rate per 1000 person-years of CTO patients was non-significantly different from patients with moderate-to-severe CAD (22.95; 95% CI 12.71 to 41.45 vs 14.46; 95% CI 12.34 to 16.94; p=0.163), and significantly higher than of those with normal coronaries and non-obstructive CAD (p<0.001 for both). Among 14 382 individuals with follow-up for the composite end point, patients with CTO had a higher rate of events than those with moderate-to-severe CAD (106.56; 95% CI 76.51 to 148.42 vs 65.45; 95% CI 58.01 to 73.84, p=0.009). This difference was primarily driven by an increase in late revascularisations in CTO patients (27 of 35 events). After multivariable adjustment, compared with individuals with normal coronaries, the presence of CTO conferred the highest risk for adverse cardiac events (14.54; 95% CI 9.11 to 23.20, p<0.001). Conclusions The detection of CTO on non-invasive CCTA is associated with increased rate of late revascularisation but similar 2-year mortality as compared with moderate-to-severe CA
CRIS-Team WoS Importer:2019-03-12

Prognostic Value of Coronary CTA in Stable Chest Pain: CAD-RADS, CAC, and Cardiovascular Events in PROMISE - Bittner, Daniel O.; Mayrhofer, Thomas; Budoff, Matt; Szilveszter, Balint; Foldyna, Borek; Hallett, Travis R.; Ivanov, Alexander; Janjua, Sumbal; Meyersohn, Nandini M.; Staziaki, Pedro V.; Achenbach, Stephan; Ferencik, Maros; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2020)
Objectives: The purpose of this study was to compare Coronary Artery Disease Reporting and Data System (CAD-RADS) to traditional stenosis categories and the coronary artery calcium score (CACS) for predicting cardiovascular events in patients with stable chest pain and suspected coronary artery disease (CAD). Background: The 2016 CAD-RADS has been established to standardize the reporting of CAD on coronary CT angiography (CTA). Methods: PROMISE (Prospective Multicenter Imaging Study for Evaluation of Chest Pain) trial participants’ CTAs were assessed by a central CT core laboratory for CACS, traditional stenosis-based categories, and modified CAD-RADS grade including high-risk coronary plaque (HRP) features. Traditional stenosis categories and CAD-RADS grade were compared for the prediction of the composite endpoint of death, myocardial infarction, or hospitalization for unstable angina over a median follow-up of 25 months. Incremental prognostic value over traditional risk factors and CACS was assessed. Results: In 3,840 eligible patients (mean age: 60.4 ± 8.2 years; 49% men), 3.0% (115) experienced events. CAD-RADS (concordance statistic [C-statistic] 0.747) had significantly higher discriminatory value than traditional stenosis-based assessments (C-statistic 0.698 to 0.717; all p for comparison ≤0.001). With no plaque (CAD-RADS 0) as the baseline, the hazard ratio (HR) for an event increased from 2.43 (95% confidence interval [CI]: 1.16 to 5.08) for CAD-RADS 1 to 21.84 (95% CI: 8.63 to 55.26) for CAD-RADS 4b and 5. In stepwise nested models, CAD-RADS added incremental prognostic value beyond ASCVD risk score and CACS (C-statistic 0.776 vs. 0.682; p < 0.001), and added incremental value persisted in all CACS strata. Conclusions: These data from a large representative contemporary cohort of patients undergoing coronary CTA for stable chest pain support the prognostic value of CAD-RADS as a standard reporting system for coronary CTA.
CRIS-Team Scopus Importer:2020-07-03
Keywords: CAD-RADS; coronary artery calcium; coronary artery disease; coronary CT angiography; coronary stenosis; high-risk plaque; prognosis

Prognostic value of coronary CT angiography beyond coronary artery calcium in stable chest pain: comparison between conventional stenosis severity and CAD-RADS stenosis categories in the PROMISE trial - Bittner, D.; Mayrhofer, T.; Budoff, M.; Szilveszter, B.; Hallett, T.; Ivanov, A.; Janjua, S.; Meyersohn, N.; Staziaki, P.; Achenbach, Stephan; Ferencik, M.; Douglas, P.; et al. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Programming and isolation of highly pure physiologically and pharmacologically functional sinus-nodal bodies from pluripotent stem cells - Jung, Julia Jeannine; Husse, Britta; Rimmbach, Christian; Krebs, Stefan; Stieber, Juliane; Steinhoff, Gustav; Dendorfer, Andreas; Franz, Wolfgang-Michael; David, Robert (Stem Cell Reports, 2014)
Therapeutic approaches for "sick sinus syndrome" rely on electrical pacemakers, which lack hormone responsiveness and bear hazards such as infection and battery failure. These issues may be overcome via "biological pacemakers" derived from pluripotent stem cells (PSCs). Here, we show that forward programming of PSCs with the nodal cell inducer TBX3 plus an additional Myh6-promoter-based antibiotic selection leads to cardiomyocyte aggregates consisting of >80% physiologically and pharmacologically functional pacemaker cells. These induced sinoatrial bodies (iSABs) exhibited highly increased beating rates (300-400 bpm), coming close to those found in mouse hearts, and were able to robustly pace myocardium ex vivo. Our study introduces iSABs as highly pure, functional nodal tissue that is derived from PSCs and may be important for future cell therapies and drug testing in vitro.
EVALuna2:8516

Prospectively ECG-triggered high-pitch coronary angiography with third-generation dual-source CT at 70 kVp tube voltage: Feasibility, image quality, radiation dose, and effect of iterative reconstruction - Hell, Michaela M.; Bittner, Daniel; Schuhbaeck, Annika; Muschiol, Gerd; Brand, Michael; Lell, Michael; Uder, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Low tube voltage reduces radiation exposure in coronary CT angiography (CTA). Using 70 kVp tube potential has so far not been possible because CT systems were unable to provide sufficiently high tube current with low voltage.We evaluated feasibility, image quality (IQ), and radiation dose of coronary CTA using a third-generation dual-source CT system capable of producing 450 mAs tube current at 70 kVp tube voltage.Coronary CTA was performed in 26 consecutive patients with suspected coronary artery disease, selected for body weight <100 kg and heart rate <60 beats/min. High-pitch spiral acquisition was used. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. IQ was assessed using a 4-point rating scale (1 = excellent, 4 = nondiagnostic) and objective parameters.Mean age was 62 ± 9 years (46% males; mean body mass index, 27.7 ± 3.8 kg/m(2); mean heart rate, 54 ± 5 beats/min). Mean dose-length product was 20.6 ± 1.9 mGy × cm; mean estimated effective radiation dose was 0.3 ± 0.03 mSv. Diagnostic IQ was found in 365 of 367 (FBP) and 366 of 367 (IR) segments (P nonsignificant). IQ was rated "excellent" in 53% (FBP) and 86% (IR) segments (P = .001) and "nondiagnostic" in 2 (FBP) and 1 segment (IR) (P nonsignificant). Mean IQ score was lesser in FBP vs IR (1.5 ± 0.4 vs 1.1 ± 0.2; P < .001). Image noise was lower in IR vs FBP (60 ± 10 HU vs 74 ± 8 HU; P < .001).In patients <100 kg and with a regular heart rate <60 beats/min, third-generation dual-source CT using high-pitch spiral acquisition and 70 kVp tube voltage is feasible and provides both robust IQ and very low radiation exposure.
EVALuna2:11954

Protecting the esophagus from thermal injury during radiofrequency ablation with an esophageal cooling device - Montoya, Marcela Mercado; Mickelsen, Steven; Clark, Brad; Hanks, Joseph; Sauter, Eric; Kulstad, Erik; Arnold, Martin (Journal of Atrial Fibrillation, 2019)
Purpose: We sought to quantify the capabilities of a commercially available cooling device to protect the esophagus from RF injury in an animal model and develop a mathematical model to describe the system and provide a framework from which to advance this technology. Methods: A series of ablations (10 W, duration 30-45 seconds) were performed directly on exposed swine esophagus. Control ablations were performed with static 37°C water, and treatment ablations were performed with water (range 5°C-37°C) circulating within the device. Mucosal lesions were evaluated visually and with target tissue histology. A mathematical model was then developed and compared against the experimental data. Results: All 23 ablations (100%) performed under control conditions produced visible external esophageal lesions; 12 of these (52%) were transmural. Under treatment conditions, only 5 of 23 ablations (22%) produced visible external lesions; none (0%) were transmural. Transmurality of lesions decreased as circulating water temperature decreased, with absolute reduction ranging from 5.1% with the use of 37°C water (p=0.7) to 44.5% with the use of 5°C water (p<0.001). Comparison to the mathematical model showed an R2 of 0.75, representing good agreement. Conclusions: Under worst-case conditions, with RF energy applied directly to the adventitial side of the esophagus, internal esophageal cooling with an esophageal cooling device provides significant protective effect from thermal injury. A mathematical model of the process provides a means to further investigate this approach to preventing esophageal injury during RF ablation and can serve to guide ongoing clinical investigations currently in progress.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Ablation; Atrial Fibrillation; Esophageal Cooling; Esophageal Protection; Finite Element Model; Mathematical Modeling; Pulmonary Vein Isolation; Radiofrequency Energy

Psychological insulin resistance in geriatric patients with diabetes mellitus - Bahrmann, Anke; Abel, Amelie; Zeyfang, Andrej; Petrak, Frank; Kubiak, Thomas; Hummel, Jana; Oster, Peter; Bahrmann, Philipp (Patient Education and Counseling, 2014)
To determine the extent to which geriatric patients with diabetes mellitus experience psychological insulin resistance (PIR).A total of 67 unselected geriatric patients with diabetes (mean age 82.8±6.7 years, diabetes duration 12.2 [0.04-47.2] years, 70.1% female) were recruited in a geriatric care center of a university hospital. A comprehensive geriatric assessment (CGA) was performed including WHO-5, Hospital Anxiety and Depression Scale (HADS), Mini Mental State Examination (MMSE) and Barthel-Index. We assessed PIR using the Barriers of Insulin Treatment Questionnaire (BIT) and the Insulin Treatment Appraisal Scale in a face-to-face interview.Insulin-naïve patients (INP) showed higher PIR scores than patients already on insulin therapy (BIT-sum score: 4.3±1.4 vs. 3.2±1.0; p<0.001). INP reported in the BIT increased fear of injection and self-testing (2.4±2.4 vs. 1.3±0.8; p=0.016), expect disadvantages from insulin treatment (2.7±1.6 vs. 1.9±1.4; p=0.04), and fear of stigmatization by insulin injection (5.2±2.3 vs. 3.6±2.6; p=0.008). Fear of hypoglycemia, however, did not differ significantly (6.3±2.8 vs. 5.1±3.1; p=0.11). Depression was not shown to be a barrier to insulin therapy.INP with diabetes have a significantly more negative attitude toward insulin therapy in comparison to patients already on insulin.Systematic assessment of barriers of insulin therapy, individualized diabetes treatment plans and information of patients may help to overcome such negative attitudes, leading to quicker initiation of therapy, improved adherence to treatment and a better quality of life.
EVALuna2:10540

Qualitätskriterien für die Erbringung kardialer CT-Leistungen: Positionspapier der Deutschen Gesellschaft für Kardiologie - Rolf, Andreas; Schmermund, Axel; Hell, Michaela M.; Schmitt, Ramona; Bernhardt, Peter; Kelle, Sebastian; Perings, Christian; Achenbach, Stephan; Thiele, Holger (Die Kardiologie, 2023)
Cardiac computed tomography (CT) has a high potential for optimization of patient care, especially in patients with chronic coronary syndrome and for planning catheter-assisted treatment of structural heart disease. A look at the United Kingdom (UK), where computed tomography angiography of the coronaries (CCTA) is now the standard and has become the primary diagnostic procedure, shows that the indications for invasive coronary diagnostics can be used with high patient safety and cost efficiency. To achieve this goal it is necessary to have clear quality criteria on the indications, performance, evaluation of the results and treatment recommendations. A cooperative heart team model with joint performance of services by radiologists and cardiologists is best suited to achieve these quality targets and to avoid a non-evidence-based expansion of services, which provokes additional workloads and therefore a significantly increased burden for the healthcare system.
CRIS-Team WoS Importer:2023-03-17

Quality of life in patients with Marfan syndrome: A cross-sectional study of 102 adult patients - Andonian, Caroline; Freilinger, Sebastian; Achenbach, Stephan; Ewert, Peter; Gundlach, Ulrike; Kaemmerer, Harald; Nagdyman, Nicole; Neidenbach, Rhoia Clara; Pieper, Lars; Schelling, Jörg; Weyand, Michael; Beckmann, Jürgen (Cardiovascular Diagnosis and Therapy, 2021)
Background: Marfan syndrome (MFS) is a genetically determined multiorgan disease that leads to severe physiological and psychological impairments in adult life. Little consensus exists regarding quality of life (QOL) in individuals with MFS. The present study sought to investigate QOL in a representative cohort of adults with MFS. Methods: Patient-reported outcome measures from a representative sample of 102 adults with MFS (39.3±13.1 years of age; 40.2% female) were retrospectively analyzed and compared with those from adults with different congenital heart defects (CHD), at the German Heart Center Munich. QOL was assessed using the updated five-level version of the EQ-5D. Results: Differences between both populations were analyzed. Subjects affected by MFS reported an overall reduced QOL. Compared to CHD patients, individuals with MFS scored significantly lower in the dimensions of pain/discomfort, anxiety/depression, mobility and usual activities (P<0.05). Conclusions: Patients with MFS are at high risk for impaired QOL, especially in mental and physical domains. Psychosocial consequences of MFS cost resources for both, patients and professionals. Current findings highlight the great importance of additional psychological support to cope with disease-related challenges. Increased attention should be directed towards enhancing their subjective wellbeing to potentially improve their QOL and long-term health outcomes.
CRIS-Team Scopus Importer:2021-05-14
Keywords: EQ-5D; Marfan syndrome (MFS); Prevention; Psychological situation; Quality of life

Quality of life of patients with coronary heart disease treated with the bioresorbable vascular scaffold (ABSORB (TM)): 2-year results from the GABI-R-registry - Pahmeier, Kathrin; Neusser, Silke; Hamm, Christian; Kastner, Johannes; Wohrle, Jochen; Zahn, Ralf; Achenbach, Stephan; Mehilli, Julinda; Gori, Tommaso; Naber, Christoph; Nef, Holger; Neumann, Till; et al. (Bmc Cardiovascular Disorders, 2022)
Background Numerous studies have reported clinical endpoints following coronary revascularization using bioresorbable vascular scaffolds (BVS), while information about the impact on health-related quality of life is sparse. In this analysis of the German-Austrian ABSORB RegIstRy, the 2 year results concerning quality of life development in a large cohort of patients treated with BVS were reported. Methods Data were collected at baseline as well as 30 days, 6 and 24 months after coronary revascularization using BVS. The EQ-5D score, EQ visual analogue scale (VAS) and Seattle Angina Questionnaire (SAQ) were determined for each time point. Patients were categorized according to the indication for coronary revascularization [acute coronary syndrome (ACS), stable angina pectoris (SAP), silent myocardial ischemia (SMI), or other]. Binary logistic regression analysis was performed to determine factors that predict above-average scores two years after implantation. Results Data from 1317 patients in 88 centres were included. Reasons for revascularization were: ACS (n = 643), SAP (n = 443), SMI (n = 52), and other (n = 179). Mean EQ-5D was significantly increased after six months, while a value comparable to baseline was found two years after implantation. EQ VAS and four of five dimensions of SAQ were significantly improved over baseline at all follow-up surveys. Particularly strong improvements were seen in SAQ scores angina frequency and quality of life. Binary regressions showed different statistically significant predictors in the respective models. Conclusions Following coronary revascularization with BVS strong decrease in self-reported angina frequency and increase of self-reported quality of life were observed with continuous improvements over two years of follow-up. Trial registration ClinicalTrials.gov Identifier: NCT02066623.
CRIS-Team WoS Importer:2022-09-02

Quantification of epicardial adipose tissue by cardiac CT: Influence of acquisition parameters and contrast enhancement - Koenig, Susanna; Schreiber, Kirsten; Ammon, Fabian; Göller, Markus; Bittner, Daniel; Achenbach, Stephan; Hell, Michaela; Marwan, Mohamed (European Journal of Radiology, 2019)
Purpose: While computed tomography (CT) is frequently used to quantify epicardial adipose tissue (EAT), the effect of different acquisition parameters on EAT volume has not been systematically reported. We assessed the influence of low-voltage acquisition and contrast enhancement on EAT quantification. Method: Two independent cohorts (100 and 127 patients) referred for routine coronary CT were included. One cohort received a low-voltage and a standard voltage non-contrast acquisition (120 and 100 kV), the other cohort underwent non-contrast and contrast-enhanced CT. EAT volume was quantified using a semi-automated analysis software. Whereas the lower EAT threshold was consistently set at -190 Hounsfield Units (HU), different upper thresholds for EAT were analyzed. Bland-Altman analysis was used to analyze the agreement of EAT volume between scans with different acquisition parameters. We referred to a non-enhanced 120 kV acquisition with an upper threshold of -30 HU. Results: Mean EAT volume was 159 ± 76 ml as measured in 120 kV non-contrast data sets with an upper threshold of -30 HU. For 100 kV data sets, an upper threshold of -40 HU showed the best correlation (r = 0.961, p < 0.05). Significant overestimation was found for upper thresholds of -20 and -30 HU and significant underestimation for -50 HU. In non-contrast vs. contrast-enhanced acquisitions, there was a significant underestimation of EAT volume for contrast-enhanced scans (mean difference 31 ml, 95% limits of agreement 27 to −89 ml). Conclusions: CT-based EAT volume quantification in low-voltage and contrast-enhanced images is feasible. However, adjustment of the upper threshold for detection of fat is mandatory.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Cardiac computed tomography; Contrast-enhanced imaging; Epicardial adipose tissue; Low-dose acquisition

Quantification of epicardial fat by computed tomography: Why, when and how? - Marwan, Mohamed; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
In the past decade, interest has grown in the relation between epicardial fat and cardiovascular disease. Several imaging modalities such as echocardiography, computed tomography, and magnetic resonance imaging can be used to quantify epicardial adipose tissue. Computed tomography provides high spatial resolution and true volume coverage of the heart; therefore, it constitutes an attractive approach to quantifying epicardial fat. An increasing body of evidence has been accumulated which shows a relation between epicardial fat volume and coronary atherosclerosis, cardiovascular outcomes, and even non-atherosclerotic heart disease such as atrial fibrillation. The association of increased epicardial fat volume with cardiac disease remains significant even after correction for weight, body mass index, and traditional cardiovascular risk factors. The mechanisms have not been reliably identified, but metabolic properties of epicardial fat may play a role. At the present time, epicardial fat quantification is not included in recommended algorithms for risk stratification. However, the available data are intriguing enough to warrant further research. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: CT; Epicardial fat

Quantification of plaque lipids in the aortic root of ApoE-deficient mice by 3D DIXON magnetic resonance imaging in an ex vivo model - Dietel, Barbara; Budinsky, Lubos; Kühn, Constanze; Uder, Michael; Achenbach, Stephan; Heß, Andreas (European Radiology, 2015)
To establish a dedicated protocol for the three-dimensional (3D) quantification of plaque lipids in apolipoprotein E-deficient (apoE(-/-)) mice using ex vivo MRI.ApoE(-/-) mice were fed a high-fat diet (n = 10) or normal food (n = 10) for 3 months. Subsequently, a 3D FLASH MRI sequence was used to view the anatomy of the aortic root in the isolated hearts, where a 3D double-echo two-excitation pulse sequence (DIXON sequence) was used to selectively image plaque lipids. The vessel wall, lumen and plaque lipid volumes were quantified by MRI and histology for correlation analysis.DIXON MRI allowed visualisation and accurate quantification of plaque lipids. When comparing the vessel wall, lumen and plaque lipid sizes in the aortic root, Bland-Altman and linear regression analysis revealed a close correlation between MRI results and the histological data both on a slice-by-slice basis and of the volumetric measurements (vessel wall: r (2) = 0.775, p < 0.001; vessel lumen: r (2) = 0.875; p = 0.002; plaque lipid: r (2) = 0.819, p = 0.003).The combination of 3D FLASH and DIXON-sequence MRI permits an accurate ex vivo assessment of the investigated plaque parameters in the aortic root of mice, particularly the lipid content.o Ex vivo MRI allows high resolution quantification of plaque parameters in mice o DIXON MRI enables visualisation of plaque lipids in the aortic root of mice o A close correlation between histology and MRI quantifies plaque parameters o Preservation of tissue integrity allows additional analysis to be performed o Short measurement time may permit the translation into in vivo measurements.
EVALuna2:11953

Quantitative global plaque characteristics from coronary computed tomography angiography for the prediction of future cardiac mortality during long-term follow-up - Hell, Michaela M.; Motwani, Manish; Otaki, Yuka; Cadet, Sebastien; Gransar, Heidi; Miranda-Peats, Romalisa; Valk, Jacob; Slomka, Piotr J.; Cheng, Victor Y.; Rozanski, Alan; Tamarappoo, Balaji K.; Hayes, Sean; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Aims: Adverse plaque characteristics determined by coronary computed tomography angiography (CTA) have been associated with future cardiac events. Our aim was to investigate whether quantitative global per-patient plaque characteristics from coronary CTA can predict subsequent cardiac death during long-term follow-up. Methods and results: Out of 2748 patients without prior history of coronary artery disease undergoing CTA with dual-source CT, 32 patients suffered cardiac death (mean follow-up of 5 ± 2 years). These patients were matched to 32 controls by age, gender, risk factors, and symptoms (total 64 patients, 59% male, age 69 ± 10 years). Coronary CTA data sets were analysed by semi-automated software to quantify plaque characteristics over the entire coronary tree, including total plaque volume, volumes of non-calcified plaque (NCP), low-density non-calcified plaque (LD-NCP, attenuation <30 Hounsfield units), calcified plaque (CP), and corresponding burden (plaque volume × 100%/vessel volume), as well as stenosis and contrast density difference (CDD, maximum percent difference in luminal attenuation/cross-sectional area compared to proximal cross-section). In patients who died from cardiac cause, NCP, LD-NCP, CP and total plaque volumes, quantitative stenosis, and CDD were significantly increased compared to controls (P < 0.025 for all). NCP > 146 mm³ [hazards ratio (HR) 2.24; 1.09-4.58; P = 0.027], LD-NCP > 10.6 mm³ (HR 2.26; 1.11-4.63; P = 0.025), total plaque volume > 179 mm³ (HR 2.30; 1.12-4.71; P = 0.022), and CDD > 35% in any vessel (HR 2.85;1.4-5.9; P = 0.005) were associated with increased risk of future cardiac death, when adjusted for segment involvement score. Conclusion: Among quantitative global plaque characteristics, total, non-calcified, and low-density plaque volumes as well as CDD predict cardiac death in long-term follow-up.
EVALuna2:33597

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Radiation exposure during transcatheter aortic valve implantation (TAVI): comparison of balloon-expandable versus self-expandable prostheses - Arnold, Martin; Nemec, S.; Kondruweit, Markus; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Radiomics-Based Precision Phenotyping Identifies Unstable Coronary Plaques From Computed Tomography Angiography - Lin, Andrew; Kolossváry, Márton; Cadet, Sebastien; McElhinney, Priscilla; Göller, Markus; Han, Donghee; Yuvaraj, Jeremy; Nerlekar, Nitesh; Slomka, Piotr J.; Marwan, Mohamed; Nicholls, Stephen J.; Achenbach, Stephan; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2022)
Objectives: The aim of this study was to precisely phenotype culprit and nonculprit lesions in myocardial infarction (MI) and lesions in stable coronary artery disease (CAD) using coronary computed tomography angiography (CTA)-based radiomic analysis. Background: It remains debated whether any single coronary atherosclerotic plaque within the vulnerable patient exhibits unique morphology conferring an increased risk of clinical events. Methods: A total of 60 patients with acute MI prospectively underwent coronary CTA before invasive angiography and were matched to 60 patients with stable CAD. For all coronary lesions, high-risk plaque (HRP) characteristics were qualitatively assessed, followed by semiautomated plaque quantification and extraction of 1,103 radiomic features. Machine learning models were built to examine the additive value of radiomic features for discriminating culprit lesions over and above HRP and plaque volumes. Results: Culprit lesions had higher mean volumes of noncalcified plaque (NCP) and low-density noncalcified plaque (LDNCP) compared with the highest-grade stenosis nonculprits and highest-grade stenosis stable CAD lesions (NCP: 138.1 mm3 vs 110.7 mm3 vs 102.7 mm3; LDNCP: 14.2 mm3 vs 9.8 mm3 vs 8.4 mm3; both Ptrend < 0.01). In multivariable linear regression adjusted for NCP and LDNCP volumes, 14.9% (164 of 1,103) of radiomic features were associated with culprits and 9.7% (107 of 1,103) were associated with the highest-grade stenosis nonculprits (critical P < 0.0007) when compared with highest-grade stenosis stable CAD lesions as reference. Hierarchical clustering of significant radiomic features identified 9 unique data clusters (latent phenotypes): 5 contained radiomic features specific to culprits, 1 contained features specific to highest-grade stenosis nonculprits, and 3 contained features associated with either lesion type. Radiomic features provided incremental value for discriminating culprit lesions when added to a machine learning model containing HRP and plaque volumes (area under the receiver-operating characteristic curve 0.86 vs 0.76; P = 0.004). Conclusions: Culprit lesions and highest-grade stenosis nonculprit lesions in MI have distinct radiomic signatures compared with lesions in stable CAD. Within the vulnerable patient may exist individual vulnerable plaques identifiable by coronary CTA-based precision phenotyping.
CRIS-Team Scopus Importer:2022-05-06
Keywords: coronary computed tomography angiography; coronary plaque; machine learning; myocardial infarction; radiomics

Randomized Clinical Trial Comparing a Rivaroxaban-Based Strategy With an Antiplatelet-Based Strategy for the Prevention of Subclinical Leaflet Thrombosis in Transcatheter Aortic Valves (GALILEO-4D) - De Backer, Ole; Dangas, George; Jilaihawi, Hasan; Leipsic, Jonathon; Terkelsen, Christian J.; Makkar, Raj; Kini, Annapoorna S.; Veien, Karsten T.; Abdel-Wahab, Mohamed; Kim, Won-Keun; Balan, Prakash; Van Mieghem, Nicolas; et al. (CIRCULATION, 2019)
CRIS-Team WoS Importer:2020-02-04

Randomized Comparison of Intracoronary Lithotripsy and Rotational Atherectomy for the Treatment of Severely Calcified Vessels-ROTA.shock Trial - Nef, Holger; Schlattner, Sophia; Weissner, Melissa; Gori, Tommaso; Ullrich, Helen; Gaede, Luise; Achenbach, Stephan; Moellmann, Helge; Blumenstein, Johannes; Aksoy, Adem; Nickenig, Georg; Weferling, Maren; et al. (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Randomized trial of acupuncture to lower blood pressure - Klinghammer, Lutz; et al. (Circulation, 2007)
Keywords: Hypertension; Life style; Risk factors

Rapidly growing cardiac myxoma diagnosed within 1 year after unremarkable prior cardiac imaging - Strecker, Thomas; Nooh, Ehab; Agaimy, Abbas; Marwan, Mohamed (Journal of Cardiac Surgery, 2019)
CRIS-Team Scopus Importer:2019-11-26
Keywords: cardiac surgery; cardiac tumors; computed tomography; echocardiography; myxoma; pathology

Rationale and design of the HeartFlowNXT (HeartFlow analysis of coronary blood flow using CT angiography: NeXt sTeps) study - Gaur, Sara; Achenbach, Stephan; Leipsic, Jonathon; Mauri, Laura; Bezerra, Hiram G.; Jensen, Jesper Moller; Botker, Hans Erik; Lassen, Jens Flensted; Norgaard, Bjarne Linde (Journal of Cardiovascular Computed Tomography, 2013)
Introduction: Coronary CT angiography (CTA) is an established noninvasive method for visualization of coronary artery disease. However, coronary CTA lacks physiological information; thus, it does not permit differentiation of ischemia-causing lesions. Recent advances in computational fluid dynamic techniques applied to standard coronary CTA images allow for computation of fractional flow reserve (FFR), a measure of lesion-specific ischemia. The diagnostic performance of computed FFR (FFRCT) compared with invasively measured FFR is not yet fully established. Methods/Design: HeartFlowNXT (HeartFlow analysis of coronary blood flow using coronary CT angiography: NeXt sTeps) is a prospective, international, multicenter study designed to evaluate the diagnostic performance of FFRCT for the detection and exclusion of flow-limiting obstructive coronary stenoses, as defined by invasively measured FFR as the reference standard. FFR values ≤0.80 will be considered to be ischemia causing. All subjects (N= 270; 10 investigative sites) will undergo coronary CTA (single- or dual-source CT scanners with a minimum of 64 slices) and invasive coronary angiography with FFR. Patients with insufficient quality of coronary CTA will be excluded. Blinded core laboratory interpretation will be performed for FFRCT, invasive coronary angiography, and FFR. Stenosis severity by coronary CTA will be evaluated by the investigative site in addition to a blinded core laboratory interpretation. The primary objective of the study is to determine the diagnostic performance of FFRCT compared with coronary CTA alone to noninvasively determine the presence of hemodynamically significant coronary lesions. The secondary end point comprises assessment of diagnostic accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of FFRCT. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computational fluid dynamics; Computed tomography; Coronary artery disease; Coronary CT angiography; Fractional flow reserve

Rationale and design of the MULTISTARS AMI Trial: A randomized comparison of immediate versus staged complete revascularization in patients with ST-segment elevation myocardial infarction and multivessel disease - Stähli, Barbara E.; Varbella, Ferdinando; Schwarz, Bettina; Nordbeck, Peter; Felix, Stephan B.; Lang, Irene M.; Toma, Aurel; Moccetti, Marco; Valina, Christian; Vercellino, Matteo; Rigopoulos, Angelos G.; Rohla, Miklos; et al. (American Heart Journal, 2020)
About half of patients with acute ST-segment elevation myocardial infarction (STEMI) present with multivessel coronary artery disease (MVD). Recent evidence supports complete revascularization in these patients. However, optimal timing of non-culprit lesion revascularization in STEMI patients is unknown because dedicated randomized trials on this topic are lacking. Study design: The MULTISTARS AMI trial is a prospective, international, multicenter, randomized, two-arm, open-label study planning to enroll at least 840 patients. It is designed to investigate whether immediate complete revascularization is non-inferior to staged (within 19-45 days) complete revascularization in patients in stable hemodynamic conditions presenting with STEMI and MVD and undergoing primary percutaneous coronary intervention (PCI). After successful primary PCI of the culprit artery, patients are randomized in a 1:1 ratio to immediate or staged complete revascularization. The primary endpoint is a composite of all-cause death, non-fatal myocardial infarction, ischemia-driven revascularization, hospitalization for heart failure, and stroke at 1 year. Conclusions: The MULTISTARS AMI trial tests the hypothesis that immediate complete revascularization is non-inferior to staged complete revascularization in stable patients with STEMI and MVD.
CRIS-Team Scopus Importer:2020-09-04

Real-time optical coherence tomography coregistration with angiography in patients underground percutaneous coronary intervention - Boeder, N. F.; Doerr, O.; Bauer, T.; Elsaesser, A.; Achenbach, Stephan; Modellmann, H.; Hamm, C.; Nef, H. M. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Real-world experience of leadless left ventricular endocardial cardiac resynchronization therapy: A multicenter international registry of the WiSE-CRT pacing system - Sieniewicz, Benjamin J.; Betts, Timothy R.; James, Simon; Turley, Andrew; Butter, Christian; Seifert, Martin; Boersma, Lucas V.A.; Riahi, Sam; Neuzil, Petr; Biffi, Mauro; Diemberger, Igor; Vergara, Pasquale; et al. (Heart Rhythm, 2020)
Background: Biventricular endocardial pacing (BiV ENDO) is a therapy for heart failure patients who cannot receive transvenous epicardial cardiac resynchronization therapy (CRT) or have not responded adequately to CRT. BiV ENDO CRT can be delivered by a new wireless LV ENDO pacing system (WiSE-CRT system; EBR Systems, Sunnyvale, CA), without the requirement for lifelong anticoagulation. Objective: The purpose of this study was to assess the safety and efficacy of the WiSE-CRT system during real-world clinical use in an international registry. Methods: Data were prospectively collected from 14 centers implanting the WiSE-CRT system as part of the WiCS-LV Post Market Surveillance Registry. (ClinicalTrials.gov Identifier: NCT02610673). Results: Ninety patients from 14 European centers underwent implantation with the WiSE-CRT system. Patients were predominantly male, age 68.2 ± 10.5 years, left ventricular ejection fraction 30.6% ± 8.9%, mean QRS duration 180.7 ± 27.0 ms, and 40% with ischemic etiology. Successful implantation and delivery of BiV ENDO pacing was achieved in 94.4% of patients. Acute (<24 hours), 1- to 30-day, and 1- to 6-month complications rates were 4.4%, 18.8%, and 6.7%, respectively. Five deaths (5.6%) occurred within 6 months (3 procedure related). Seventy percent of patients had improvement in heart failure symptoms. Conclusion: BiV ENDO pacing with the WiSE-CRT system seems to be technically feasible, with a high success rate. Three procedural deaths occurred during the study. Procedural complications mandate adequate operator training and implantation at centers with immediately available cardiothoracic and vascular surgical support.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Cardiac resynchronization therapy; Endocardial pacing; Heart failure; Leadless pacing; Nonresponder

Real World Experience of Leadless LV Endocardial CRT with the WiSE CRT Pacing System; An International Study - Sieniewicz, Benjamin J.; Betts, Timothy R.; James, Simon; Turley, Andrew J.; Butter, Christian; Seifert, Martin; Boersma, Lucas V. A.; Riahi, Sam; Neuzil, Petr; Biffi, Mauro; Diemberger, Igor; Keane, David T.; et al. (2018)
EVALuna2:213064

Recent nanomedicine articles of outstanding interest: nanoparticle functionalization for disease diagnostics and therapy - Janko, Christina; Pöttler, Marina; Friedrich, Ralf P.; Lyer, Stefan; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19956

Reconstruction of 3D-Movement of ICD Leads from Clinical-Routine X-Ray Movies - Kirchner, Jens; Fischer, Georg; Arnold, Martin (2017 IEEE International Symposium on Signal Processing and Information Technology (ISSPIT), 2017)
A technique is proposed to reconstruct the threedimensional movement of leads of implantable cardioverter defibrillators from X-ray movies obtained as part of clinical routine during implantation. The technique is applied to data from 16 patients. 12 of them provide results with a sufficient accuracy of less than 2.5 mm in terms of half of the minimum distance of the projection lines and when compared to the length of the shock coil as reference. From the reconstructed 3D data, the movement along and perpendicular to the lead axes as well as tilt are obtained. Such data will prove useful in research on material fatigue and cardiac sensors integrated into the lead
Keywords: cardiology; defibrillators; diagnostic radiography; image reconstruction; medical image processing; prosthetics; reconstructed 3D data; lead axes; implantable cardioverter defibrillators; three-dimensional movement; clinical-routine X-ray movies; ICD leads; 3D-movement; shock coil; projection lines; minimum distance; motion pictures; electric shock lead; heart; X-ray imaging; image reconstruction; signal processing; ICD; lead; cardiac movement; X-ray movie; 3D reconstruction; implantation

Recurrent shock and pulmonary edema due to acetazolamide medication after cataract surgery - Zimmermann, S.; Achenbach, Susanne; Wolf, M.; Janka, Rolf Matthias; Marwan, M.; Mahler, V. (Heart & Lung, 2014)
We report a patient with recurrent shock and transient non-cardiogenic pulmonary edema within a period of two months - every time occurring after cataract surgery and a single oral dose of standard post-operative medication with acetazolamide.Records of the intensive care unit, review of the literature.This case demonstrates a rare but severe side effect of acetazolamide. We also present a review of the literature to raise the awareness of health care providers for this special form of non-cardiogenic pulmonary edema.
EVALuna2:11868

Red blood cell omega-3 fatty acids and the risk of ventricular arrhythmias in patients with heart failure - Wilhelm, Matthias; Tobias, Rueth; Asskali, Fatima; Kraehner, Robert; Kuly, Simone; Klinghammer, Lutz; Böhles, Hans Josef; Daniel, Werner (American Heart Journal, 2008)

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

RELATION BETWEEN NOISE ANNOYANCE, STRESS HORMONES AND THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Rauh, Manfred; Ott, Christian; Striepe, Kristina; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Relation of frailty to outcomes in percutaneous coronary intervention - Kwok, Chun Shing; Achenbach, Stephan; Curzen, Nick; Fischman, David L.; Savage, Michael; Bagur, Rodrigo; Kontopantelis, Evangelos; Martin, Glen P.; Steg, P. Gabriel; Mamas, Mamas A. (Cardiovascular Revascularization Medicine, 2019)
There is growing awareness that frailty may be an important marker of adverse outcomes in PCI but there is no literature from national cohorts. This study examines a national cohort of patients who underwent percutaneous coronary intervention (PCI) regarding the prevalence of frailty, changes over time, and associated outcomes. The National Inpatients Sample was used to identify adults who underwent PCI procedures between 2004 and 2014. Frailty risk was measured using a validated Hospital Frailty Risk Score (HFRS) using the cutoffs <5, 5–15 and >15 for low, intermediate and high HFRS. From 7,306,007 admissions, a total of 94.58% of admissions were for patients who had a low HFRS(<5), 5.39% had an intermediate HFRS(5–15) and 0.03% had a high HFRS(>15). The prevalence of intermediate or high frailty risk patients has increased over time from 1.9% in 2004 to 11.7% in 2014. The incidence of in-hospital death increased from 1.0% with low HFRS to 13.9% with high HFRS. Mean length of stay also increased from 2.9 days to 17.1 days from low to high HFRS. High frailty risk was independently associated with an OR 9.91 95%CI 7.17–13.71 for in-hospital death, OR 4.99 95%CI 3.82–6.51 for bleeding and OR 3.96 95%CI 3.00–5.23 for vascular injury as compared to patients with low risk of HFRS. While rare in frequency overall, frailty is increasing in prevalence in recent years and intermediate and high HFRS associated with increased odds of mortality compared to low risk of frailty.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Complications; Frailty; Mortality; Percutaneous coronary intervention

Relation of functional echocardiographic parameters to infarct scar transmurality by magnetic resonance imaging - Rost, Christian; Rost, Marie-Charlotte; Breithardt, Ole A.; Schmid, Michael; Klinghammer, Lutz; Stumpf, Christian; Daniel, Werner; Flachskampf, Frank A. (Journal of the American Society of Echocardiography, 2014)
Identification of viable but dysfunctional myocardium after myocardial infarction is important for management, including the decision for revascularization. Assessment of infarct transmurality (TRM) by late contrast enhancement on magnetic resonance imaging (MRI) is frequently used for this task but has several limitations, particularly its availability. The goal of this study was to compare the value of several simple echocardiographic parameters measured at rest at the bedside for the identification of three degrees of infarct TRM, with contrast-enhanced MRI as the gold standard.In a prospective, single-center study, 41 patients (33 men; mean age, 62 ± 10 years; 32 with ST-segment elevation infarctions) underwent resting echocardiography and contrast-enhanced MRI <5 days after infarction. Wall motion score, preejection velocity by tissue Doppler, and longitudinal, circumferential, and radial peak systolic strain by speckle-tracking-based strain imaging were assessed, and the findings were compared with infarct TRM stratified by contrast-enhanced MRI (no scar, 0% TRM; nontransmural scar, 1%-50% TRM; and transmural scar, 51%-100% TRM).Four hundred segments showed no scar, 125 showed nontransmural scar, and 213 showed transmural scar on contrast-enhanced MRI. The sensitivity and specificity of visual wall motion scoring to detect any scar versus no scar were 71% and 81%, respectively, similar to values for circumferential strain (sensitivity and specificity both 81% with a cutoff of -14.5%). Longitudinal and radial strain performed less well, and the presence of preejection velocity performed distinctly worse (45% and 90%, respectively). The sensitivity and specificity for identifying nontransmural versus transmural infarction was better for circumferential strain (78% and 75%, respectively, with a cutoff of -10.5%) than for the other strain types, preejection velocity (52% and 67%, respectively), or visual wall motion scoring (50% and 81%, respectively, for a score > 2).Visual wall motion analysis alone is able to detect infarcted myocardium but cannot differentiate sufficiently between transmural and nontransmural infarction. This is best achieved at the bedside using speckle-tracking-based circumferential strain.
EVALuna2:11951

Relationship between changes in pericoronary adipose tissue attenuation and coronary plaque burden quantified from coronary computed tomography angiography - Goeller, Markus; Tamarappoo, Balaji K.; Kwan, Alan C.; Cadet, Sebastien; Commandeur, Frederic; Razipour, Aryabod; Slomka, Piotr J.; Gransar, Heidi; Chen, Xi; Otaki, Yuka; Friedman, John D.; Cao, J. Jane; et al. (European Heart Journal - Cardiovascular Imaging, 2019)
AIMS: Increased attenuation of pericoronary adipose tissue (PCAT) around the proximal right coronary artery (RCA) from coronary computed tomography angiography (CTA) has been shown to be associated with coronary inflammation and improved prediction of cardiac death over plaque features. Our aim was to investigate whether PCAT CT attenuation is related to progression of coronary plaque burden. METHODS AND RESULTS: We analysed CTA studies of 111 stable patients (age 59.2 ± 9.8 years, 77% male) who underwent sequential CTA (3.4 ± 1.6 years between scans) with identical acquisition protocols. Total plaque (TP), calcified plaque (CP), non-calcified plaque (NCP), and low-density non-calcified plaque (LD-NCP) volumes and corresponding burden (plaque volume × 100%/vessel volume) were quantified using semi-automated software. PCAT CT attenuation (HU) was measured around the proximal RCA, the most standardized method for PCAT analysis. Patients with an increase in NCP burden (n = 51) showed an increase in PCAT attenuation, whereas patients with a decrease in NCP burden (n = 60) showed a decrease 4.4 [95% confidence interval (CI) 2.6-6.2] vs. -2.78 (95% CI -4.6 to -1.0) HU, P < 0.0001. Changes in PCAT attenuation correlated with changes in the burden of NCP (r = 0.55, P < 0.001) and LD-NCP (r = 0.24, P = 0.01); but not CP burden (P = 0.3). Increased baseline PCAT attenuation ≥-75 HU was independently associated with increase in NCP (odds ratio 3.07, 95% CI 1.4-7.0; P < 0.008) and TP burden on follow-up CTA. CONCLUSION: PCAT attenuation measured from routine CTA is related to the progression of NCP and TP burden. This imaging biomarker may help to identify patients at increased risk of high-risk plaque progression and allow monitoring of beneficial changes from medical therapy.
CRIS-Team Scopus Importer:2019-07-09
Keywords: coronary CT angiography; coronary plaque progression; CT attenuation; inflammation; pericoronary adipose tissue

Relationship Between Quantitative Adverse Plaque Features From Coronary Computed Tomography Angiography and Downstream Impaired Myocardial Flow Reserve by 13N-Ammonia Positron Emission Tomography: A Pilot Study - Dey, Damini; Diaz Zamudio, Mariana; Schuhbaeck, Annika; Juarez Orozco, Luis Eduardo; Otaki, Yuka; Gransar, Heidi; Li, Debiao; Germano, Guido; Achenbach, Stephan; Berman, Daniel S.; Meave, Aloha; Alexanderson, Erick; et al. (Circulation: Cardiovascular Imaging, 2015)
We investigated the relationship of quantitative plaque features from coronary computed tomography (CT) angiography and coronary vascular dysfunction by impaired myocardial flow reserve (MFR) by (13)N-Ammonia positron emission tomography (PET).Fifty-one patients (32 men, 62.4±9.5 years) underwent combined rest-stress (13)N-ammonia PET and CT angiography scans by hybrid PET/CT. Regional MFR was measured from PET. From CT angiography, 153 arteries were evaluated by semiautomated software, computing arterial noncalcified plaque (NCP), low-density NCP (NCP<30 HU), calcified and total plaque volumes, and corresponding plaque burden (plaque volumex100%/vessel volume), stenosis, remodeling index, contrast density difference (maximum difference in luminal attenuation per unit area in the lesion), and plaque length. Quantitative stenosis, plaque burden, and myocardial mass were combined by boosted ensemble machine-learning algorithm into a composite risk score to predict impaired MFR (MFR<=2.0) by PET in each artery. Nineteen patients had impaired regional MFR in at least 1 territory (41/153 vessels). Patients with impaired regional MFR had higher arterial NCP (32.4% versus 17.2%), low-density NCP (7% versus 4%), and total plaque burden (37% versus 19.3%, P<0.02). In multivariable analysis with 10-fold cross-validation, NCP burden was the most significant predictor of impaired MFR (odds ratio, 1.35; P=0.021 for all). For prediction of impaired MFR with 10-fold cross-validation, receiver operating characteristics area under the curve for the composite score was 0.83 (95% confidence interval, 0.79-0.91) greater than for quantitative stenosis (0.66, 95% confidence interval, 0.57-0.76, P=0.005).Compared with stenosis, arterial NCP burden and a composite score combining quantitative stenosis and plaque burden from CT angiography significantly improves identification of downstream regional vascular dysfunction.
EVALuna2:12125

Relationship of epicardial fat volume from noncontrast CT with impaired myocardial flow reserve by positron emission tomography - Otaki, Yuka; Hell, Michaela; Slomka, Piotr J.; Schuhbaeck, Annika; Gransar, Heidi; Huber, Brandi; Nakazato, Ryo; Germano, Guido; Hayes, Sean W.; Thomson, Louise E. J.; Friedman, John D.; Achenbach, Stephan; et al. (Journal of Cardiovascular Computed Tomography, 2015)
Impaired myocardial flow reserve (MFR) is a marker of coronary vascular dysfunction with prognostic significance.We aimed to investigate the relationship between epicardial fat volume (EFV) measured from noncontrast CT and impaired MFR derived from rest-stress Rb-82 positron emission tomography (PET).We retrospectively studied 85 consecutive patients without known coronary artery disease who underwent rest-stress Rb-82 myocardial PET/CT and were subsequently referred for invasive coronary angiography. EFV was computed from noncontrast CT by validated software and indexed to body surface area (EFVi, cm3/m2). Global stress and rest MFR were automatically derived from PET. Patient age, sex, cardiovascular risk factors, coronary calcium score (CCS), and EFVi were combined by boosted ensemble machine learning algorithm into a novel composite risk score, using 10-fold cross-validation, to predict impaired global MFR (MFR <=2.0) by PET.Patients with impaired MFR (44 of 85; 52%) were older (71 vs. 65 years; P = .03) and had higher frequency of CCS (>=400; P = .02) with significantly higher EFVi (63.1 ± 20.4 vs. 51.3 ± 14.1 cm3/m2; P = .003). On multivariate logistic regression (with age, sex, number of risk factors, CCS, and EFVi), EFVi was the only independent predictor of impaired MFR (odds ratio, 7.39; P = .02). The machine learning composite risk score significantly improved risk reclassification of impaired MFR compared to CCS or EFVi alone (integrated discrimination improvement = 0.19; P = .007 and IDI = 0.22; P = .002, respectively).Increased EFVi and composite risk score combining EFVi and CCS significantly improve identification of impaired global MFR by PET.
EVALuna2:12079

Relationship of Hypertension to Coronary Atherosclerosis and Cardiac Events in Patients With Coronary Computed Tomographic Angiography - Nakanishi, Rine; Baskaran, Lohendran; Gransar, Heidi; Budoff, Matthew J.; Achenbach, Stephan; Al-Mallah, Mouaz; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; Chow, Benjamin J. W.; Delago, Augustin; et al. (Hypertension, 2017)
Hypertension is an atherosclerosis factor and is associated with cardiovascular risk. We investigated the relationship between hypertension and the presence, extent, and severity of coronary atherosclerosis in coronary computed tomographic angiography and cardiac events risk. Of 17 181 patients enrolled in the CONFIRM registry (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry) who underwent ≥64-detector row coronary computed tomographic angiography, we identified 14 803 patients without known coronary artery disease. Of these, 1434 hypertensive patients were matched to 1434 patients without hypertension. Major adverse cardiac events risk of hypertension and non-hypertensive patients was evaluated with Cox proportional hazards models. The prognostic associations between hypertension and no-hypertension with increasing degree of coronary stenosis severity (nonobstructive or obstructive ≥50%) and extent of coronary artery disease (segment involvement score of 1-5, >5) was also assessed. Hypertension patients less commonly had no coronary atherosclerosis and more commonly had nonobstructive and 1-, 2-, and 3-vessel disease than the no-hypertension group. During a mean follow-up of 5.2±1.2 years, 180 patients experienced cardiac events, with 104 (2.0%) occurring in the hypertension group and 76 (1.5%) occurring in the no-hypertension group (hazard ratios, 1.4; 95% confidence intervals, 1.0-1.9). Compared with no-hypertension patients without coronary atherosclerosis, hypertension patients with no coronary atherosclerosis and obstructive coronary disease tended to have higher risk of cardiac events. Similar trends were observed with respect to extent of coronary artery disease. Compared with no-hypertension patients, hypertensive patients have increased presence, extent, and severity of coronary atherosclerosis and tend to have an increase in major adverse cardiac events.
EVALuna2:33630

Relationship of low- and high-density lipoproteins to coronary artery plaque composition by CT angiography - Nakazato, Ryo; Gransar, Heidi; Berman, Daniel S.; Cheng, Victor Y.; Lin, Fay Y.; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; et al. (Journal of Cardiovascular Computed Tomography, 2013)
Background: The association between lipoprotein levels and coronary plaque composition is not well understood. Objective: The aim of this prospective international multicenter study of statin-naive individuals was to evaluate the association of low-density lipoprotein (LDL), high-density lipoprotein (HDL), and total cholesterol (TC) to coronary plaque composition by coronary computed tomographic angiography (CTA). Methods: We studied 4575 individuals without known coronary artery disease not taking statin medications who underwent coronary CTA. Comparisons were made between those with high versus low LDL, HDL, TC, and non-HDL. We assessed the relationship of lipoproteins and plaques of specific composition (noncalcified [NCP], partially calcified [PCP], or calcified [CP] plaque). Results: Mean age was 57 ± 11 years (55% men). In univariable analyses, high LDL, low HDL, high TC, and high non-HDL were each associated with increased prevalence of NCPs, PCPs, and CPs (P < 0.05 for all). In multivariable analyses, high non-HDL was associated with the presence of NCP (odds ratio, 1.47; 95% CI, 1.22-1.78: P < 0.001). In the further subanalysis, a weak relationship between the highest group of non HDL (≥190 mg/dL) and the presence of CP was also noted (odds ratio, 1.33; 95% CI, 1.01-1.76; P = 0.04). Further, high non-HDL was associated with increasing numbers of segments with NCP (β coefficient, 0.043; 95% CI, 0.021-0.065; P < 0.001) but not segments with PCP or CP. Conclusion: NCP presence and extent are associated with high non-HDL. These results suggest a relationship between lipid profile and plaque composition. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Coronary artery disease; Coronary CTA; Lipid profile; Plaque composition; Serum lipoproteins

Renal and intraglomerular haemodynamics in chronic heart failure with preserved and reduced ejection fraction - Jung, Susanne; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Schuster, Tizia; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Congestive heart failure (CHF) and impaired renal function are two often co-existing medical conditions and associated with adverse cardiovascular outcome. The aim of the current study was to assess renal and intraglomerular haemodynamics by constant infusion input clearance technique in subjects with CHF. Methods and results: The group of subjects with CHF consisted of 27 individuals with HFpEF and 27 individuals with HFrEF and were compared with 31 healthy controls. Subjects underwent renal clearance examination to measure glomerular filtration rate (GFR) and renal blood and plasma flow (RBF and RPF) and to calculate intraglomerular haemodynamics such as resistances of the afferent (RA) and efferent arterioles (RE) as well as intraglomerular pressure (Pglom). Measured GFR was lower in CHF subjects (68.1 ± 10.1 mL/min/1.73 m2) compared with controls (83.6 ± 13.4 mL/min/1.73 m2, Padj < 0.001) as was Pglom (Padj < 0.001). Total renal vascular resistance (RVR) was higher in CHF subjects (87.3 ± 20.1 vs. 73.8 ± 17.1 dyn × s/cm5, Padj < 0.001) mediated by an increased resistance at the afferent site (3201 ± 1084 vs. 2181 ± 796 dyn × s/cm5, Padj < 0.001). Comparing HFpEF and HFrEF subjects, RA was higher in HFrEF subjects. The severity of CHF assessed by NT-proBNP revealed an inverse association with renal perfusion (RPF r = −0.421, P = 0.002, RBF r = −0.414, P = 0.002) and a positive relation with RVR (r = 0.346, P = 0.012) at the post-glomerular site (RE: r = 0.318, P = 0.022). Conclusions: Renal function assessed by measured GFR is reduced and renal vascular resistance at the preglomerular, afferent site is increased in HFpEF and, to greater extent, in HFrEF. Our data indicate a close cardiorenal interaction in CHF.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cardiorenal interaction; Heart failure; Preserved ejection fraction; Reduced ejection fraction; Renal haemodynamics

Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine - Ott, Christian; Jung, Susanne; Korn, Manuel; Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods: Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric acid and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR). Intraglomerular hemodynamics were calculated according the Gomez´ model. Results: Treatment with E+L reduced GFR (p = 0.003), but RPF remained unchanged (p = 0.536). In contrast, M+I not only reduced GFR (p = 0.001), but also resulted in a significant reduction of RPF (p < 0.001). Renal vascular resistance (RVR) decreased with E+L treatment (p = 0.001) but increased with M+I treatment (p = 0.001). The changes in RPF and RVR were different between the two groups (both padjust < 0.001). Analysis of intraglomerular hemodynamics revealed that E+L did not change resistance of afferent arteriole (RA) (p = 0.116), but diminished resistance of efferent arterioles (RE) (p = 0.001). In M+I group RA was increased (p = 0.006) and RE remained unchanged (p = 0.538). The effects on RA (padjust < 0.05) and on RE (padjust < 0.05) differed between the groups. Conclusions: In patients with type 2 diabetes and preserved renal function treatment with M+I resulted in reduction of renal perfusion and increase in vascular resistance, in contrast to treatment with E+I that preserved renal perfusion and reduced vascular resistance. Moreover, different underlying effects on the resistance vessels have been estimated according to the Gomez model, with M+I increasing RA and E+L predominantly decreasing RE, which is in contrast to the proposed sodium-glucose cotransporter 2 inhibitor effects. Trial registration: The study was registered at www.clinicaltrials.gov (NCT02752113) on April 26, 2016
CRIS-Team Scopus Importer:2021-09-17
Keywords: Hemodynamics; Intraglomerular; Renal; Type 2 diabetes

Reply: Leaflet thrombosis following transcatheter aortic valve implantation - Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
EVALuna2:35995

Reproducibility of aortic annulus measurements by computed tomography - Schuhbaeck, Annika; Achenbach, Stephan; Pflederer, Tobias; Schmid, Julia; Nef, Holger; Rixe, Johannes; Hecker, Franziska; Schneider, Christian; Lell, Michael; Uder, Michael; Arnold, Martin; Marwan, Mohamed (European Radiology, 2014)
To evaluate a systematic approach for measurement of aortic annulus dimensions by cardiac computed tomography.CT data sets of 64 patients were evaluated. An oblique cross-section aligned with the aortic root was created by systematically identifying the caudal insertion points of the three aortic cusps and sequentially aligning them in a double oblique plane. Aortic annulus dimensions, distances of coronary ostia and a suitable fluoroscopic projection angle were independently determined by two observers.Interobserver intraclass correlation coefficients (ICC) for aortic annulus diameters were excellent (ICC 0.89-0.93). Agreement for prosthesis size selection was excellent (? = 0.86 for mean, ? = 0.84 for area-derived and ? = 0.91 for circumference-derived diameter). Mean distances of the left/right coronary ostium were 13.4 ± 2.4/14.4 ± 2.8 mm for observer 1 and 13.2 ± 2.7/13.5 ± 3.2 mm for observer 2 (p = 0.30 and p = 0.0001, respectively; ICC 0.76/0.77 for left/right coronary artery). A difference of less than 10° for fluoroscopic projection angle was achieved in 84.3% of patients.A systematic approach to generate a double oblique imaging plane exactly aligned with the aortic annulus demonstrates high interobserver and intraobserver agreements for derived measurements which are not influenced by aortic root calcification.o Systematic approach to generate a double oblique imaging plane for TAVI evaluation. o This method is straightforward and software independent. o An approach with high reproducibility, not influenced by aortic root calcification.
EVALuna2:11952

Reproducibility of semi-automatic coronary plaque quantification in coronary CT angiography with sub-mSv radiation dose - Ovrehus, Kristian Altern; Schuhbaeck, Annika; Achenbach, Stephan; Norgaard, Bjarne Linde; Botker, Hans Erik; Dey, Damini; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
INTRODUCTION: Coronary computed tomographic angiography (CTA) can characterize coronary atherosclerotic plaque components as calcified and non-calcified. Quantitative measurements of coronary plaque burden by coronary CTA may play a role in serial studies to determine disease progression or response to medical therapies. The reproducibility from repeated assessment of such quantitative measurements from low-radiation dose coronary CTA has not been previously assessed. PURPOSE: To evaluate the interscan, interobserver and intraobserver reproducibility for coronary plaque volume assessment using semi-automatic plaque analyses algorithm in low radiation dose coronary CTA. METHODS: In 50 consecutive patients undergoing two 128-slice dual source CT scans within 12 days with a mean radiation dose of 0.7 mSv per coronary CTA, the interscan, interobserver and intraobserver reproducibility of coronary plaque assessment using validated software (AutoPlaq) were evaluated. RESULTS: Interscan, interobserver and intraobserver agreement for non-calcified and calcified plaque volumes were excellent (Spearman rho 0.87-0.99). Interscan mean percentage difference in non-calcified and calcified plaque volumes were 0.1% (p = 0.8) and 1.9% (p = 0.19) with limits of agreement of ±11% and ±48.5%; per inter- and intraobserver mean percentage differences were 0.1% (p = 0.25) and 0.3% (p = 0.001), and 0.3% (p = 0.33) and 0.4% (p = 0.59) with limits of agreement of ±7% and ±32.9%, and ±6.6% and ±32.1%, respectively. CONCLUSION: A semi-automatic plaque assessment algorithm in repeated low radiation dose coronary CTA allows for high reproducibility of coronary plaque characterization and quantification measures.
EVALuna2:33994

Resolution of leaflet thrombosis under anticoagulant therapy in patients after transcatheter aortic valve implantation: influence of prosthesis type and size - Ferstl, Paul; Arnold, Martin; Göller, Markus; Ammon, Fabian; Smolka, S.; Moshage, Maximilian; Uehlein, Sabrina; Achenbach, Stephan; Bittner, Daniel O.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Respiratory Motion Compensation in Rotational Angiography: Graphical Model-Based Optimization of Auto-Focus Measures - Unberath, Mathias; Taubmann, Oliver; Bier, Bastian; Geimer, Tobias; Hell, Michaela; Achenbach, Stephan; Maier, Andreas (IEEE International Symposium on Biomedical Imaging, Proceedings of the, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.respir_2
Keywords: Angiography; Cardiac imaging; Cone-beam CT; Discrete optimization; Markov random fields

Response to letter regarding article, "Randomized trial of acupuncture to lower blood pressure" [2] - Flachskampf, Frank A.; Wortmann, Alois; Klinghammer, Lutz; Daniel, Werner; Gallasch, Joachim; Pflederer, Wolfgang; Gefeller, Olaf; Pfahlberg, Annette Bettina; Gan, Junxue; Mao, Juntong (Circulation, 2008)

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography - Jung, Susanne; Bosch, Agnes; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Scientific Reports, 2020)
Spectral-domain optical coherence tomography (SD-OCT) represents a reliable tool for retinal layer volume and thickness measurement. The aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (ESRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age- and gender-adjusted retinal layer volumes such as total retinal volume (p = 0.037), ganglion cell layer volume (GCL, p = 0.003), ganglion cell layer – inner plexiform layer volume (GCL-IPL, p = 0.005) and inner retinal layer volume (IRL, p = 0.042) of the right eye were lower in ESRD patients. Inner plexiform layer volume of both eyes (IPL, right eye: p = 0.017; left eye: 0.044) was reduced, as was RNFL thickness in the temporal superior sector (right eye: p = 0.016). A subgroup analysis excluding patients with diabetes revealed that GCL (p = 0.014) and GCL-IPL volume of the right eye (p = 0.024) and temporal superior sector of the RNFL scan (p = 0.021) in ESRD patients were still significantly thinner. We observed a decrease in several retinal layer volumes and temporal RNFL thickness indicative of retinal neurodegenerative processes in patients with ESRD.
CRIS-Team Scopus Importer:2020-04-03

Risk Assessment of Coronary Obstruction During Transcatheter Aortic Valve Replacement: Insights From Post-BASILICA Computed Tomography - Kitamura, Mitsunobu; Wilde, Johannes; Dumpies, Oliver; Richter, Ines; Obradovic, Danilo; Krieghoff, Christian; Gohmann, Robin F.; Majunke, Nicolas; Desch, Steffen; Gutberlet, Matthias; Borger, Michael; Marwan, Mohamed; et al. (Jacc-Cardiovascular Interventions, 2022)
Objectives: The aim of this study was to examine the predictive value of preprocedural computed tomography (CT)–based risk stratification of coronary obstruction during transcatheter aortic valve replacement (TAVR) on the basis of geometric measurements on postprocedural CT. Background: Proper patient selection for additional procedures to prevent coronary obstruction during TAVR has not been adequately evaluated. Methods: Pre- and postprocedural computed tomographic scans of 28 patients treated using bioprosthetic or native aortic scallop intentional laceration to prevent iatrogenic coronary artery obstruction (BASILICA) and TAVR were analyzed. Using the postprocedural computed tomographic images, threatened coronary obstruction (TCO) was defined as: 1) ostial obstruction (adherence of the transcatheter heart valve [THV] to the coronary ostium with leaflet extension above the ostium); and/or 2) sinus sequestration (THV adherence to the sinotubular junction [STJ] with leaflet extension above the STJ) and was substratified into complete and incomplete types. Results: A total of 51 leaflets were evaluated (88% surgical tissue valves) after excluding leaflets not visible on CT (n = 5). On postprocedural CT, complete TCO was observed in 25.4% (13 of 51 leaflets). On preprocedural CT, leaflets were at high risk for complete TCO (incidence 53%) if the virtual THV–to–coronary distance (VTC) was <3.0 mm, or if the virtual THV–to–STJ distance (VTSTJ) was <1.0 mm with STJ height − leaflet length <0 mm (leaflet-STJ mismatch). Leaflets were at low risk (incidence 0%) if the VTC was ≥3 mm and VTSTJ was ≥3.0 mm or STJ height − leaflet length was ≥+2.0 mm. Of 28 leaflets treated using BASILICA, complete TCO was seen in 35.7% (n = 10), due to sinus sequestration (100%) with coexisting ostial obstruction (30%). Actual coronary events occurred in 7.1% (n = 2) because of leaflet prolapse, corresponding to an absolute risk reduction by BASILICA of 29% (P = 0.021). Conclusions: Risk assessment of coronary obstruction after TAVR may improve with a multiparametric approach incorporating VTC, VTSTJ, and leaflet-STJ mismatch. BASILICA appeared to reduce actual coronary events even in leaflets with anticipated coronary obstruction.
CRIS-Team Scopus Importer:2022-03-11
Keywords: BASILICA; computed tomography; coronary obstruction; transcatheter aortic valve replacement

Risk factors for cardiovascular disease among individuals with hepatic steatosis - Karady, Julia; Ferencik, Maros; Mayrhofer, Thomas; Meyersohn, Nandini M.; Bittner, Daniel O.; Staziaki, Pedro; Szilveszter, Balint; Hallett, Travis R.; Lu, Michael T.; Puchner, Stefan B.; Simon, Tracey G.; Foldyna, Borek; et al. (Hepatology Communications, 2022)
Cardiovascular disease (CVD) is the leading cause of mortality in adults with hepatic steatosis (HS). However, risk factors for CVD in HS are unknown. We aimed to identify factors associated with coronary artery disease (CAD) and incident major adverse cardiovascular events (MACE) in individuals with HS. We performed a nested cohort study of adults with HS detected on coronary computed tomography in the PROspective Multicenter Imaging Study for Evaluation of chest pain (PROMISE) trial. Obstructive CAD was defined as ≥50% coronary stenosis. MACE included hospitalization for unstable angina, nonfatal myocardial infarction, or all-cause death. Multivariate modeling, adjusted for age, sex, atherosclerotic CVD (ASCVD) risk score and body mass index, identified factors associated with obstructive CAD. Cox regression, adjusted for ASCVD risk score, determined the predictors of MACE. A total of 959 of 3,756 (mean age 59.4 years, 55.0% men) had HS. Obstructive CAD was present in 15.2% (145 of 959). Male sex (adjusted odds ratio [aOR] = 1.83, 95% confidence interval [CI] 1.18–1.2.84; p = 0.007), ASCVD risk score (aOR = 1.05, 95% CI 1.03–1.07; p < 0.001), and n-terminal pro-b-type natriuretic peptide (NT-proBNP; aOR = 1.90, 95% CI 1.38–2.62; p < 0.001) were independently associated with obstructive CAD. In the 25-months median follow-up, MACE occurred in 4.4% (42 of 959). Sedentary lifestyle (adjusted hazard ratio [aHR] = 2.53, 95% CI 1.27–5.03; p = 0.008) and NT-proBNP (aOR = 1.50, 95% CI 1.01–2.25; p = 0.046) independently predicted MACE. Furthermore, the risk of MACE increased by 3% for every 1% increase in ASCVD risk score (aHR = 1.03, 95% CI 1.01–1.05; p = 0.02). Conclusion: In individuals with HS, male sex, NT-pro-BNP, and ASCVD risk score are associated with obstructive CAD. Furthermore, ASCVD, NT-proBNP, and sedentary lifestyle are independent predictors of MACE. These factors, with further validation, may help risk-stratify adults with HS for incident CAD and MACE.
CRIS-Team Scopus Importer:2022-11-04

Risk factors for chylothorax and persistent serous effusions after congenital heart surgery - Raatz, Anna; Schöber, Martin; Zant, Robert; Cesnjevar, Robert; Rüffer, André; Purbojo, Ariawan; Dittrich, Sven; Alkassar, Muhannad (European Journal of Cardio-Thoracic Surgery, 2019)
OBJECTIVES: This study evaluated the various risk factors for chylothorax and persistent serous effusions (>7 days) after congenital heart surgery and developed equations to calculate the probability of their occurrence. METHODS: We performed a retrospective review of different medical databases at the University Hospital of Erlangen between January 2014 and December 2016. Full model regression analysis was used to identify risk factors, and prediction algorithms were set up to calculate probabilities. Discriminative power of the models was checked with the help of C-statistics. RESULTS: Of 745 operations on 667 patients, 68 chylothoraxes (9.1%) and 125 persistent pleural effusions (16.8%) were diagnosed. Lowest temperature [P = 0.043; odds ratio (OR) 0.899], trisomy 21 (P = 0.001; OR 5.548), a higher vasoactive inotropic score on the day of surgery (P = 0.001; OR 1.070) and use of an assist device (P = 0.001; OR 5.779) were significantly associated with chylothorax. Risk factors for persistent serous effusions were a given or possible involvement of the aortic arch during the operation (P = 0.000; OR 3.982 and 2.905), univentricular hearts (P = 0.019; OR 2.644), a higher number of previous heart operations (P = 0.014; OR 1.436), a higher vasoactive inotropic score 72 h after surgery (P = 0.019; OR 1.091), a higher central venous pressure directly after surgery (P = 0.046; OR 1.076) and an aortic cross-clamp time >86 min (P = 0.023; OR 2.223), as well as use of an assist device (P = 0.002; OR 10.281). The prediction models for both types of effusions proved to have excellent discriminative power. CONCLUSIONS: Persistent serous effusion is associated with a higher vasoactive inotropic score 72 h after surgery, an aortic cross-clamp time >86 min and elevated central venous pressure directly after surgery, which, in combination, potentially indicate cardiac stress. The developed logistic algorithm helps to estimate future likelihood.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Cardiac insufficiency; Cardiac surgery; Chylothorax; Congenital heart disease; Persistent effusions; Risk factor

Risk Reclassification With Coronary Computed Tomography Angiography-Visualized Nonobstructive Coronary Artery Disease According to 2018 American College of Cardiology/American Heart Association Cholesterol Guidelines (from the Coronary Computed Tomography Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry [CONFIRM]) - Han, Donghee; Beecy, Ashley; Anchouche, Khalil; Gransar, Heidi; Dunham, Patricia C.; Lee, Ji Hyun; Achenbach, Stephan; Al-Mallah, Mouaz H.; Andreini, Daniele; Berman, Daniel S.; Bax, Jeroen J.; Budoff, Matthew J.; et al. (American Journal of Cardiology, 2019)
The 2018 American College of Cardiology (ACC)/American Heart Association (AHA) cholesterol management guideline recommends risk enhancers in the borderline-risk and statin recommended/intermediate-risk groups. We determined the risk reclassification by the presence and severity of coronary computed tomography angiography (CCTA)-visualized coronary artery disease (CAD) according to statin eligibility groups. Of 35,281 individuals who underwent CCTA, 1,303 asymptomatic patients (age 59, 65% male) were identified. Patients were categorized as low risk, borderline risk, statin recommended/intermediate risk or statin recommended/high risk according to the guideline. CCTA-visualized CAD was categorized as no CAD, nonobstructive, or obstructive. Major adverse cardiovascular events (MACE) were defined as a composite outcome of all-cause mortality, nonfatal myocardial infarction, and late coronary revascularization (>90 days). We tested a reclassification wherein no CAD reclassifies downward, and the presence of any CAD reclassifies upward. During a median follow-up of 2.9 years, 93 MACE events (7.1%) were observed. Among the borderline-risk and statin-recommended/intermediate-risk groups eligible for risk enhancers, the presence or absence of any CCTA-visualized CAD led to a net increase of 2.3% of cases and 22.4% of controls correctly classified (net reclassification index [NRI] 0.27, 95% CI 0.13 to 0.41, p = 0.0002). The NRI was not significant among low- or statin-recommended/high-risk patients (all p >0.05). The presence or absence of CCTA-visualized CAD, including both obstructive and nonobstructive CAD, significantly improves reclassification in patients eligible for risk enhancers in 2018 ACC/AHA guidelines. Patients in low- and high-risk groups derive no significant improvement in risk reclassification from CCTA.
CRIS-Team Scopus Importer:2019-10-01

Risks and benefits of cardiac imaging: an analysis of risks related to imaging for coronary artery disease - Knuuti, Juhani; Bengel, Frank; Bax, Jeroen J.; Kaufmann, Philipp A.; Le Guludec, Dominique; Filardi, Pasquale Perrone; Marcassa, Claudio; Marsan, Nina Ajmone; Achenbach, Stephan; Kitsiou, Anastasia; Flotats, Albert; Eeckhout, Eric; et al. (European Heart Journal, 2014)
EVALuna2:12003

Risk stratification by analysis of QT dispersion and late potentials in the electrocardiogram and biplanar magnetocardiogram in patients with coronary heart disease Risikostratifikation durch Analyse von QT-Dispersion und Spätpotentialen im Elektrokardiogramm und biplanen Magnetokardiogramm bei Patienten mit KHK. - Klinghammer, Lutz; et al. (Biomedizinische Technik, 1998)

Risk Stratification With the Use of Coronary Computed Tomographic Angiography in Patients With Nonobstructive Coronary Artery Disease - Taron, Jana; Foldyna, Borek; Mayrhofer, Thomas; Osborne, Michael T.; Meyersohn, Nandini; Bittner, Daniel O.; Puchner, Stefan B.; Emami, Hamed; Lu, Michael T.; Ferencik, Maros; Pagidipati, Neha J.; Douglas, Pamela S.; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2021)
Objectives: The purpose of this study was to develop a risk prediction model for patients with nonobstructive CAD. Background: Among stable chest pain patients, most cardiovascular (CV) events occur in those with nonobstructive coronary artery disease (CAD). Thus, developing tailored risk prediction approaches in this group of patients, including CV risk factors and CAD characteristics, is needed. Methods: In Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) computed tomographic angiography patients, a core laboratory assessed prevalence of CAD (nonobstructive 1% to 49% left main or 1% to 69% stenosis any coronary artery), degree of stenosis (minimal: 1% to 29%; mild: 30% to 49%; or moderate: 50% to 69%), high-risk plaque (HRP) features (positive remodeling, low-attenuation plaque, and napkin-ring sign), segment involvement score (SIS), and coronary artery calcium (CAC). The primary end point was an adjudicated composite of unstable angina pectoris, nonfatal myocardial infarction, and death. Cox regression analysis determined independent predictors in nonobstructive CAD. Results: Of 2,890 patients (age 61.7 years, 46% women) with any CAD, 90.4% (n = 2,614) had nonobstructive CAD (mean age 61.6 yrs, 46% women, atherosclerotic cardiovascular disease [ASCVD] risk 16.2%). Composite events were independently predicted by ASCVD risk (hazard ratio [HR]: 1.03; p = 0.001), degree of stenosis (30% to 69%; HR: 1.91; p = 0.011), and presence of ≥2 HRP features (HR: 2.40; p = 0.008). Addition of ≥2 HRP features to: 1) ASCVD and CAC; 2) ASCVD and SIS; or 3) ASCVD and degree of stenosis resulted in a statistically significant improvement in model fit (p = 0.0036; p = 0.0176; and p = 0.0318; respectively). Patients with ASCVD ≥7.5%, any HRP, and mild/moderate stenosis had significantly higher event rates than those who did not meet those criteria (3.0% vs. 6.2%; p = 0.007). Conclusions: Advanced coronary plaque features have incremental value over total plaque burden for the discrimination of clinical events in low-risk stable chest pain patients with nonobstructive CAD. This may be a first step to improve prevention in this cohort with the highest absolute risk for CV events.
CRIS-Team Scopus Importer:2021-05-14
Keywords: computed tomographic angiography; nonobstructive coronary artery disease; risk stratification

Role of Cardiac CT Before Transcatheter Aortic Valve Implantation (TAVI) - Achenbach, Stephan; Marwan, Mohamed (Current Cardiology Reports, 2016)
Catheter-based aortic valve implantation is increasingly being performed in high-risk patients with symptomatic aortic valve stenosis. For successful planning of the procedure, CT has been shown to provide crucial information concerning the aortic root as well as the peripheral access vessels. This article illustrates the increasing role of CT before transcatheter aortic valve implantation.
EVALuna2:12078

Role of CT Imaging for Coronary and Non-coronary Interventions - Marwan, Mohamed; Achenbach, Stephan (Current Cardiovascular Imaging Reports, 2017)
Purpose of Review: Pre-procedural imaging is essential for successful planning and performance of several cardiac interventions. Cardiac computed tomography (CT) is a non-invasive imaging modality capable of providing precise information required for different coronary and non-coronary interventions. The role of cardiac CT for the guidance of different cardiac interventions will be described in this review. Recent Findings: Contrast-enhanced computed tomography imaging is increasingly being used for guiding transcatheter cardiac interventions. Anatomical and functional information provided by CT helps in successful planning and performance of several cardiac interventions. Summary: Over the last decade, the continuous growth of interventional cardiology has been associated with widespread acknowledgment that CT is particularly useful for pre-interventional imaging with increasing implementation in clinical routine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Chronic total occlusion; Chronic total occlusions; Coronary interventions; Left atrial appendage; Structural heart disease; TAVI

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial

Rubbing salt into wounded endothelium: sodium potentiates proatherogenic effects of TNF-? under non-uniform shear stress - Wild, Johannes; Soehnlein, Oliver; Dietel, Barbara; Urschel, Katharina; Garlichs, Christoph; Cicha, Iwona (Thrombosis and Haemostasis, 2014)
Increased consumption of sodium is a risk factor for hypertension and cardiovascular diseases. In vivo studies indicated that high dietary sodium may have a direct negative influence on endothelium. We investigated the effects of high sodium on the endothelial activation during early steps of atherogenesis. Endothelial cells (HUVECs) grown in a model of arterial bifurcations were exposed to shear stress in the presence of normal or high (+ 30 mmol/l) sodium. Adherent THP-1 cells, and the adhesion molecule expression were quantified. Sodium channel blockers, pathways' inhibitors, and siRNA against tonicity-responsive enhancer binding protein (TonEBP) were used to identify the mechanisms of sodium effects on endothelium. ApoE-deficient mice on low-fat diet received water containing normal or high salt (8% w/v) for four weeks, and the influence of dietary salt on inflammatory cell adhesion in the common carotid artery and carotid bifurcation was measured by intravital microscopy. In vitro, high sodium dramatically increased the endothelial responsiveness to tumour necrosis factor-? under non-uniform shear stress. Sodium-induced increase in monocytic cell adhesion was mediated by reactive oxygen species and the endothelial nitric oxygen synthase, and was sensitive to the knockdown of TonEBP. The results were subsequently confirmed in the ApoE-deficient mice. As compared with normal-salt group, high-salt intake significantly enhanced the adhesion of circulating CD11b+ cells to carotid bifurcations, but not to the straight segment of common carotid artery. In conclusion, elevated sodium has a direct effect on endothelial activation under atherogenic shear stress in vitro and in vivo, and promotes the endothelial-leukocyte interactions even in the absence of increased lipid concentrations.
EVALuna2:12000

Safety and Performance of the Resorbable Magnesium Scaffold, Magmaris in a Real World Setting - First 400 Subjects at 12-month Follow-up of the BIOSOLVE-IV Registry - Lee, Michael; Wlodarczak, Adrian; Bennett, Johan; Torzewski, Jan; Haude, Michael; Vrolix, Mathias; Buck, Thomas; Aminian, Adel; Van Der Schaaf, Rene; Nuruddin, Amin Ariff; Wiemer, Marcus; Yan, Bryan; et al. (2018)
EVALuna2:35968

SCCT guidelines for the interpretation and reporting of coronary CT angiography: a report of the Society of Cardiovascular Computed Tomography Guidelines Committee - Leipsic, Jonathon; Abbara, Suhny; Achenbach, Stephan; Cury, Ricardo; Earls, James P.; Mancini, G. B. John; Nieman, Koen; Pontone, Gianluca; Raff, Gilbert L. (Journal of Cardiovascular Computed Tomography, 2014)
EVALuna2:12011

SCCT guidelines for the performance and acquisition of coronary computed tomographic angiography: A report of the society of Cardiovascular Computed Tomography Guidelines Committee: Endorsed by the North American Society for Cardiovascular Imaging (NASCI) - Abbara, Suhny; Blanke, Philipp; Maroules, Christopher D.; Cheezum, Michael; Choi, Andrew D.; Han, B. Kelly; Naoum, Chris; Norgaard, Bjarne L.; Rubinshtein, Ronen; Schoenhagen, Paul; Villines, Todd; Leipsic, Jonathon; et al. (Journal of Cardiovascular Computed Tomography, 2016)
In response to recent technological advancements in acquisition techniques as well as a growing body of evidence regarding the optimal performance of coronary computed tomography angiography (coronary CTA), the Society of Cardiovascular Computed Tomography Guidelines Committee has produced this update to its previously established 2009 "Guidelines for the Performance of Coronary CTA" (1). The purpose of this document is to provide standards meant to ensure reliable practice methods and quality outcomes based on the best available data in order to improve the diagnostic care of patients. Society of Cardiovascular Computed Tomography Guidelines for the Interpretation is published separately (2). The Society of Cardiovascular Computed Tomography Guidelines Committee ensures compliance with all existing standards for the declaration of conflict of interest by all authors and reviewers for the purpose ofclarity and transparency.
EVALuna2:33668

SCORE2 risk prediction algorithms: new models to estimate 10-year risk of cardiovascular disease in Europe - Hageman, Steven; Pennells, Lisa; Ojeda, Francisco; Kaptoge, Stephen; Kuulasmaa, Kari; De Vries, Tamar; Xu, Zhe; Kee, Frank; Chung, Ryan; Wood, Angela; Mcevoy, John William; Veronesi, Giovanni; et al. (European Heart Journal, 2021)
Aims The aim of this study was to develop, validate, and illustrate an updated prediction model (SCORE2) to estimate 10-year fatal and non-fatal cardiovascular disease (CVD) risk in individuals without previous CVD or diabetes aged 40-69 years in Europe.
CRIS-Team WoS Importer:2021-07-30

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

SEMI-AUTOMATIC MEASUREMENT OF INTIMA-MEDIA THICKNESS OF BRACHIAL ARTERY IN PATIENTS WITH CONGESTIVE HEART FAILURE - Kannenkeril, Dennis; Kolwelter, Julie; Pietschner, Robert; Striepe, Kristina; Bosch, Agnes; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Cardiovascular diseases are associated with an increase in intima-media thickness (IMT). However, the techniques used to measure IMT have limitations. A semi-automatic device called UNEX has been developed, which overcomes the limitation of classic systems (in particular the investigator-dependency of conventional, "hand-held'' measurements). The purpose of this study was to measure the intima-media thickness of the brachial artery (bIMT) with the UNEX device in patients with and without congestive heart failure. DESIGN AND METHOD: The UNEX device is comprised of a 7.5-MHz, H-shaped linear array transducer and a novel stereotactic probe-holding device (UNEX EF 18G; UNEX Co., Nagoya, Japan). Another advantage of this device is the continuous recording of B-mode images and A-mode waves of the brachial artery. Measurement of bIMT was automatically performed on A-mode images of the far wall of the brachial artery. The analysis system automatically detects the measurement point where an image was clearly obtained. The average of mean measurement values obtained from 10 cardiac cycles was defined as bIMT. In a first set of clinical studies, we measured bIMT in patients with reduced left ventricular ejection fraction (HFrEF) and in patients without heart failure. RESULTS: Patients with HFrEF (n = 85, ejection fraction: 38.3 ± 8.4 %, NT-pro-BNP: 713 ± 714.7 pg/ml) compared to patients without heart failure (n = 63) were older (66.4 ± 9.2 vs. 53.8 ± 12.6 years, p < 0.001), with more male subjects (67 vs. 40, p = 0.039). bIMT was higher in patients with HFrEF compared to the other group (0.295 ± 0.083 vs. 0.249 ± 0.083 mm, p < 0.001). After adjustment for age, gender and other cardiovascular risk factors, the result remained significant (p = 0.032). CONCLUSIONS: Our study demonstrate that IMT of large muscular arteries can be automatically (investigator independently) measured. Our data indicate an increased vascular remodeling in patients with HFrEF independent of other confounders.
CRIS-Team Scopus Importer:2022-09-16

Sequential changes in myocardial function after valve replacement for aortic stenosis by speckle tracking echocardiography - Rost, Christian; Korder, S.; Wasmeier, G.; Wu, M.; Klinghammer, Lutz; Flachskampf, F. A.; Daniel, Werner; Voigt, J. U. (European Journal of Echocardiography, 2010)
Aims Regional myocardial function may change differently in different pathology. Speckle tracking echocardiography (STE) was applied to evaluate longitudinal, radial, and circumferential function in patients with aortic stenosis (AS) before, within 1 week, and 6 months after aortic valve replacement (AVR). Methods and results In 40 consecutive patients with severe AS, we acquired apical four-, three-, and two-chamber views and standard short-axis view pre- and post-AVR and after 6 months. Longitudinal, radial, and circumferential (LS, RS, and CS) were calculated by commercial STE software. Further, we analysed diastolic myocardial function by measuring E/e′ ratio. With AVR, valve area increased and remained stable at 6 months follow-up. Left ventricular mass was unchanged 1 week after AVR (270 ± 58 g vs. 267 ± 58 g, n.s.) but decreased significantly during the next 6 months (219 ± 50 g, P < 0.05). Left ventricular ejection fraction remained unchanged. Strain values did not change significantly within 1 week after AVR but increased significantly after 6 months (LS by 16, RS by 21, and CS by 28 of baseline values). E/e′ ratio was highly augmented before AVR (26.1 ± 12.5) and decreased significantly 6 months after AVR (15.9 ± 5.9). Conclusion Myocardial function significantly recovers after replacing the stenosed aortic valve. However, there is a considerable difference between the response of longitudinal, radial, and circumferential function. Our data suggest that echocardiographic assessment of regional function is feasible and of potential clinical importance. © The Author 2010.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Aortic stenosis; Aortic valve replacement; Diastolic dysfunction; Echocardiography; Strain

SERIO - Side Effect Registry Immuno-Oncology Side Effect Registry for rare, severe and complex Side Effects of Immunotherapy - Kramer, Rafaela; Mentzer, D.; Erdmann, M.; Knauss, S.; Broeckelmann, P. J.; Hassel, J. C.; Ugurel, S.; Pavel, Marianne Ellen; Nickel, Franziska; Landendinger, M.; Fuchs, Friederike; Meidenbauer, Norbert; et al. (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

Serio - Side Effect Registry in Immuno-Oncology - Koutzamanidis, Rafaela; Mentzer, Dirk; Knauss, Samuel; Broeckelmann, Paul J.; Hassel, Jessica Cecile; Ugurel-Becker, Selma; Pavel, Marianne Ellen; Nickel, Florian; Landendinger, Melanie; Fuchs, Florian; Meidenbauer, Norbert; Jefremow, Andre; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

SERUM IL-6 CONCENTRATION CORRELATES WITH PLAQUE VULNERABILITY AND RUPTURE IN PATIENTS WITH SEVERE CAROTID STENOSIS - Dietel, B.; Urschel, K.; Tauchi, Miyuki; Achenbach, Susanne (ATHEROSCLEROSIS, 2022)
CRIS-Team WoS Importer:2022-10-14

Serum levels of the Th1 chemoattractant interferon-gamma-inducible protein (IP) 10 are elevated in patients with essential hypertension - Stumpf, Christian; Auer, Claudia; Yilmaz, Atilla; Lewczuk, Piotr; Klinghammer, Lutz; Schneider, Markus; Daniel, Werner; Schmieder, Roland; Garlichs, Christoph (Hypertension Research, 2011)
Growing evidence shows that inflammation has a pivotal role in the pathophysiology of essential hypertension (EH). Although it has been acknowledged that target organ damage involves an inflammatory response, most work has focused on the role of macrophages, but T lymphocytes have recently become the center of interest. The goal of our study was to evaluate the role of T-cell-specific cytokines in the pathogenesis of EH. The study examined 39 patients with EH (57.7±6.8 years, systolic blood pressure (SBP) 157.5±11.8 mm Hg, diastolic blood pressure 92.2±12.9 mm Hg, mean arterial pressure 113.9±12.6 mm Hg) and 30 healthy, normotensive controls (55.2±4.9 years). Blood was drawn from a peripheral vein, and serum levels of interferon-inducible protein (IP)-10 and interleukins (IL)-4,-7 and-13 were measured by a multiplexing assay. Hypertensive patients had significantly higher levels of IP-10, IL-4, IL-7 and IL-13 than control subjects. When the patients were classified into tertiles according to their serum IP-10 levels (T1: 41.2-9±4.1 pg ml-1; T2: 103.4-1±62.5 pg ml 1; T3: 171.7-443.5 pgml 1), the patients classified into the highest tertile also had the highest blood pressure. In a correlation analysis, plasma IP-10 concentration was significantly associated with SBP (r0.59, P<0.001). Furthermore, hypertensives with microalbuminuria, an early sign of hypertensive target organ damage, had the highest IP-10 levels. A stepwise multivariate regression analysis revealed IP-10 as the strongest independent predictor of SBP (P<0.01). In conclusion, our study provides new insights into the pathophysiological mechanisms in EH linking inflammation and IP-10. However, these preliminary results need to be confirmed in larger trials. © 2011 The Japanese Society of Hypertension All rights reserved.
CRIS-Team Scopus Importer:2023-07-10
Keywords: cytokines; inflammation; IP-10; microalbuminuria; T-cells

Sex and age-specific interactions of coronary atherosclerotic plaque onset and prognosis from coronary computed tomography - Van Rosendael, Sophie E.; Bax, A. Maxim; Lin, Fay Y.; Achenbach, Stephan; Andreini, Daniele; Budoff, Matthew J.; Cademartiri, Filippo; Callister, Tracy Q.; Chinnaiyan, Kavitha; Chow, Benjamin J.W.; Cury, Ricardo C.; DeLago, Augustin J.; et al. (European Heart Journal - Cardiovascular Imaging, 2023)
Aims: The totality of atherosclerotic plaque derived from coronary computed tomography angiography (CCTA) emerges as a comprehensive measure to assess the intensity of medical treatment that patients need. This study examines the differences in age onset and prognostic significance of atherosclerotic plaque burden between sexes. Methods and results: From a large multi-center CCTA registry the Leiden CCTA score was calculated in 24 950 individuals. A total of 11 678 women (58.5 ± 12.4 years) and 13 272 men (55.6 ± 12.5 years) were followed for 3.7 years for major adverse cardiovascular events (MACE) (death or myocardial infarction). The age where the median risk score was above zero was 12 years higher in women vs. men (64-68 years vs. 52-56 years, respectively, P < 0.001). The Leiden CCTA risk score was independently associated with MACE: score 6-20: HR 2.29 (1.69-3.10); score > 20: HR 6.71 (4.36-10.32) in women, and score 6-20: HR 1.64 (1.29-2.08); score > 20: HR 2.38 (1.73-3.29) in men. The risk was significantly higher for women within the highest score group (adjusted P-interaction = 0.003). In pre-menopausal women, the risk score was equally predictive and comparable with men. In post-menopausal women, the prognostic value was higher for women [score 6-20: HR 2.21 (1.57-3.11); score > 20: HR 6.11 (3.84-9.70) in women; score 6-20: HR 1.57 (1.19-2.09); score > 20: HR 2.25 (1.58-3.22) in men], with a significant interaction for the highest risk group (adjusted P-interaction = 0.004). Conclusion: Women developed coronary atherosclerosis approximately 12 years later than men. Post-menopausal women within the highest atherosclerotic burden group were at significantly higher risk for MACE than their male counterparts, which may have implications for the medical treatment intensity.
CRIS-Team Scopus Importer:2023-09-15
Keywords: coronary artery disease; coronary computed tomography angiography (CCTA); prognosis; sex differences

Sex-based prognostic implications of nonobstructive coronary artery disease: results from the international multicenter CONFIRM study - Leipsic, Jonathon; Taylor, Carolyn M.; Gransar, Heidi; Shaw, Leslee J.; Ahmadi, Amir; Thompson, Angus; Humphries, Karin; Berman, Daniel S.; Hausleiter, Joerg; Achenbach, Stephan; Al-Mallah, Mouaz; Budoff, Matthew J.; et al. (Radiology, 2014)
To determine the clinical outcomes of women and men with nonobstructive coronary artery disease ( CAD coronary artery disease ) with coronary computed tomographic (CT) angiography data in patients who were similar in terms of CAD coronary artery disease risk factors, angina typicality, and CAD coronary artery disease extent and distribution.Institutional review board approval was obtained for all participating sites, with either informed consent or waiver of informed consent. In a prospective international multicenter cohort study of 27 125 patients undergoing coronary CT angiography at 12 centers, 18 158 patients with no CAD coronary artery disease or nonobstructive (<50% stenosis) CAD coronary artery disease were examined. Men and women were propensity matched for age, CAD coronary artery disease risk factors, angina typicality, and CAD coronary artery disease extent and distribution, which resulted in a final cohort of 11 462 subjects. Nonobstructive CAD coronary artery disease presence and extent were related to incident major adverse cardiovascular events ( MACE major adverse cardiovascular events ), which were inclusive of death and myocardial infarction and were estimated by using multivariable Cox proportional hazards models.At a mean follow-up ± standard deviation of 2.3 years ± 1.1, MACE major adverse cardiovascular events occurred in 164 patients (0.6% annual event rate). After matching, women and men experienced identical annualized rates of myocardial infarction (0.2% vs 0.2%, P = .72), death (0.5% vs 0.5%, P = .98), and MACE major adverse cardiovascular events (0.6% vs 0.6%, P = .94). In multivariable analysis, nonobstructive CAD coronary artery disease was associated with similarly increased MACE major adverse cardiovascular events for both women (hazard ratio: 1.96 [95% confidence interval CI confidence interval : 1.17, 3.28], P = .01) and men (hazard ratio: 1.77 [95% CI confidence interval : 1.07, 2.93], P = .03).When matched for age, CAD coronary artery disease risk factors, angina typicality, and nonobstructive CAD coronary artery disease extent, women and men experience comparable rates of incident mortality and myocardial infarction.
EVALuna2:12015

Sex-Specific Associations Between Coronary Artery Plaque Extent and Risk of Major Adverse Cardiovascular Events: The CONFIRM Long-Term Registry - Schulman-Marcus, Joshua; Hartaigh, Briain O.; Gransar, Heidi; Lin, Fay; Valenti, Valentina; Cho, Iksung; Berman, Daniel; Callister, Tracy; Delago, Augustin; Hadamitzky, Martin; Hausleiter, Joerg; Al-Mallah, Mouaz; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2016)
OBJECTIVES: The purpose of this study was to examine sex-specific associations, if any, between per-vessel coronary artery disease (CAD) extent and the risk of major adverse cardiovascular events (MACE) over a 5-year study duration. BACKGROUND: The presence and extent of CAD diagnosed by coronary computed tomography angiography (CTA) is associated with increased short-term mortality and MACE. Nevertheless, some uncertainty remains regarding the influence of sex on these findings. METHODS: 5,632 patients (mean age 60.2 ± 11.8 years, 36.5% women) from the CONFIRM (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter) registry were followed for 5 years. Obstructive CAD was defined as ≥50% luminal stenosis in a coronary vessel. Using Cox proportional hazards models, we calculated the hazard ratio (HR) for incident MACE among women and men, defined as death or myocardial infarction. RESULTS: Obstructive CAD was more prevalent in men (42% vs. 26%; p < 0.001), whereas women were more likely to have normal coronary arteries (43% vs. 27%; p < 0.001). There were a total of 798 incident MACE events. After adjustment, there was a strong association between increased MACE risk and nonobstructive CAD (HR: 2.16 for women, 2.56 for men; p < 0.001 for both), obstructive 1-vessel CAD (HR: 3.69 and 2.66; p < 0.001), 2-vessel CAD (HR: 3.92 and 3.55; p < 0.001), and 3-vessel/left main CAD (HR: 5.94 and 4.44; p < 0.001). Further exploratory analyses of atherosclerotic burden did not identify sex-specific patterns predictive of MACE. CONCLUSIONS: In a large prospective coronary CTA cohort followed long-term, we did not observe an interaction of sex for the association between MACE risk and increased per-vessel extent of obstructive CAD. These findings highlight the persistent prognostic significance of anatomic CAD subsets as detected by coronary CTA for the risk of MACE in both women and men.
EVALuna2:12103

SHEAR STRESS-DEPENDENT EXPRESSION OF GLYPICAN-4 AND HEPARAN SULFATE IN DIFFERENT PRIMARY HUMAN ENDOTHELIAL CELLS - Hug, K.; Tauchi, M.; Raaz-Schrauder, Dorette; Stumpfe, F.; Achenbach, Stephan; Dietel-Schor, B.; Urschel, K. (ATHEROSCLEROSIS, 2019)
CRIS-Team WoS Importer:2019-09-10

Shear stress dependent expression of glypican-4 and heparan sulfate in human endothelial cells - Urschel, K.; Hug, K.; Raaz-Schrauder, Dorette; Stumpfe, F. M.; Tauchi, M.; Achenbach, Stephan; Dietel-Schor, B. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Shell matters: Magnetic targeting of SPIONs and in vitro effects on endothelial and monocytic cell function - Matuszak, Jasmin; Doerfler, Philipp; Zaloga, Jan; Unterweger, Harald; Lyer, Stefan; Dietel, Barbara; Alexiou, Christoph; Cicha, Iwona (Clinical Hemorheology and Microcirculation, 2015)
Superparamagnetic iron oxide nanoparticles (SPIONs) are versatile and easily functionalized agents with high potential for diagnostic and therapeutic intravascular applications. In this study, we analyzed the responses of endothelial (ECs) and monocytic cells to three different types of SPIONs, in order to assess the influence of physico-chemical properties on the biological reactions to SPIONs. The following formulations were used: (1) Lauric acid-coated and BSA-stabilized SPION-1,(2) Lauric acid/BSA-coated SPION-2 and (3) dextran-coated SPION-3. SPION-1 were strongly internalized by ECs and reduced their viability in static conditions. Additionally, they had a dose-dependent inhibitory effect on monocytic cell chemotaxis to MCP-1, but did not affect monocytic cell recruitment by ECs. SPION-2 uptake was less pronounced, both in ECs and monocytic cells, and these particles were better tolerated by the vascular cells. Not being internalized by endothelial or monocytic cells, SPION-3 did not induce relevant effects on cell viability, motility or endothelial-monocytic cell interactions.Taken together, localized accumulation of circulating SPION under physiologic-like flow conditions and their cellular uptake depends on the physicochemical characteristics. Our findings suggest that SPION-2 are suitable for magnetic targeting of atherosclerotic plaques. Due to their excellent biocompatibility and low internalization, SPION-3 may represent a suitable imaging agent for intravascular applications.
EVALuna2:12025

Short-term outcome of patients with ST-segment elevation myocardial infarction (STEMI) treated with an everolimus-eluting bioresorbable vascular scaffold - Wiebe, Jens; Moellmann, Helge; Most, Astrid; Doerr, Oliver; Weipert, Kay; Rixe, Johannes; Liebetrau, Christoph; Elsaesser, Albrecht; Achenbach, Stephan; Hamm, Christian; Nef, Holger (Clinical Research in Cardiology, 2014)
To evaluate safety and efficacy of the everolimus-eluting bioresorbable scaffold (BVS) in patients with ST-segment elevation myocardial infarction (STEMI).According to the current guidelines, drug-eluting stents are the treatment of choice in patients with STEMI. BVS represents a new technology capable to restore the native vessel vasomotion and potentially avoiding long-term limitations such as stent thrombosis.From October 2012 to May 2013, patients with evidence of STEMI eligible for BVS implantation were included in this study. Exclusion criteria were not defined.A total of 25 patients, respectively 31 lesions, were treated. Procedural success was achieved in 97 %. Two major adverse cardiac events occurred during hospitalization and follow-up: one patient with cardiogenic shock at the index procedure subsequently died. One patient suffered from instable angina with need for interventional revascularization of a previously untreated vessel. One target vessel failure as a consequence of an intra-procedural dissection was seen. However, no target lesion failure was noted. During 132.7 ± 68.7 days of follow-up none of the patients died.Our findings suggest that implantation of BVS in STEMI patients is feasible in this small cohort of highly selected patients. Further evaluation in randomized-controlled trials is needed.
EVALuna2:11876

Short-term prognosis of contemporary interventional therapy of ST-elevation myocardial infarction: Does gender matter? - Zimmermann, Stefan; Ruthrof, Susanne; Nowak, Kathrin; Alff, Anna; Klinghammer, Lutz; Schneider, Reinhard; Ludwig, Josef; Pfahlberg, Annette; Daniel, Werner; Flachskampf, Frank A. (Clinical Research in Cardiology, 2009)
Background: A higher mortality risk for women with acute ST-elevation myocardial infarction (STEMI) has been a common finding in the past, even after acute percutaneous coronary intervention (PCI). We set out to analyze whether there are gender differences in real-world contemporary treatment and outcomes of STEMI. Patients and methods: A retrospective analysis of all consecutive patients with STEMI and acute coronary angiography with the intention of performing a PCI at our center 6/1999-6/2006 was carried out (n = 566). Data were examined for gender-specific differences regarding patients' characteristics, referral patterns, timing of acute symptoms, angiographic findings, procedural details, and adverse events at 30 days after PCI. Results: Women (n = 161) were on average 8 years older than men (n = 405), had higher co-morbidity, were more often transported to the hospital by ambulance and presented less often to the emergency room on their own (4.2% vs. 12.6% in men, P = 0.02). The pre-hospital delay from symptom onset to admission was significantly longer for women (median 185 vs. 135 min, P < 0.02). There was no gender difference in time from admission to PCI (median 46 min vs. 48 min, P = 0.42). Both genders received PCI with similar frequency (88.8% vs. 92.4%, P = 0.19), with similar success rates (83.2% vs. 85.3%, P = 0.68). Thirty-day overall mortality for women was not significantly higher than for men (8.7% vs. 7.2%, P = 0.6). Re-infarction or stroke within 30 days were rare for both genders without gender-specific differences whereas bleeding necessitating blood replacement was significantly more frequent in women (16.8% vs. 5.9%, P < 0.001). In multivariate analysis, female gender was not independently associated with a higher risk of 30-day mortality (OR 0.964, P = 0.93). Conclusions: Women underwent PCI therapy for STEMI with the same frequency and the same angiographic success as men. Despite their more advanced age and the higher prevalence of co-morbidities, they did not have a significantly higher 30-day mortality rate than men. Female gender was not an independent risk factor of 30-day mortality. Longer pre-hospital delays before hospital admission in women indicate that awareness of risk from coronary artery disease should be further raised in women. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2023-07-10
Keywords: Gender differences; Outcomes; Primary coronary intervention; ST-elevation myocardial infarction

Side effects and major adverse cardiac events caused by fractional flow reserve measurement: a systematic review and meta-analysis of 12,215 patients - Altstidl, Johannes Michael; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Simultaneous hemodialysis during coronary angiography fails to prevent radiocontrast-induced nephropathy in chronic renal failure - Klinghammer, Lutz; et al. (Clinical Nephrology, 2003)
Keywords: Radiocontrast-induced nephropathy; Simultaneous hemodialysis; Chronic renal failure

Six-Year Prognostic Value of Microvascular Obstruction After Reperfused ST-Elevation Myocardial Infarction as Assessed by Contrast-Enhanced Cardiovascular Magnetic Resonance - Regenfus, Matthias; Schlundt, Christian; Kraehner, Robert; Schoenegger, Carolin; Adler, Werner; Ludwig, Josef; Daniel, Werner; Schmid, Michael (American Journal of Cardiology, 2015)
Although recent studies showed the prognostic value of cardiac magnetic resonance (CMR) parameters especially microvascular obstruction (MO) after reperfused ST-elevation myocardial infarction (STEMI), a study assessing their prognostic significance for long-term follow-up is missing so far. The objective of this study was to determine the prognostic impact of MO on long-term prognosis after reperfused first STEMI in a setting allocating CMR-assessed parameters to hard clinical events only. In 249 patients, CMR was performed after reperfused STEMI, and hereby, left ventricular ejection fraction (LVEF), infarct size (IS), and the amount of MO were quantified. Follow-up (median 6.0 years) was obtained regarding occurrence of major adverse cardiac events (MACE). MACE occurred more often in patients showing presence of MO (MO vs no MO: n = 61 [54%] vs n = 12 [9%], p <0.0001). By multivariate analysis, the extent of MO remained the strongest predictor (p <0.001) for occurrence of MACE and provided incremental prognostic value over clinical variables and LVEF (p = 0.028, c-index increase from 0.723 to 0.817). In conclusion, CMR-assessed MO proves predictive for assessment of 6-year prognosis in patients after reperfused first STEMI and provides incremental prognostic information over clinical variables and LVEF in a setting based on hard end points.
EVALuna2:5505

Small whole heart volume predicts cardiovascular events in patients with stable chest pain: insights from the PROMISE trial - Foldyna, Borek; Zeleznik, Roman; Eslami, Parastou; Mayrhofer, Thomas; Scholtz, Jan Erik; Ferencik, Maros; Bittner, Daniel O.; Meyersohn, Nandini M.; Puchner, Stefan B.; Emami, Hamed; Pellikka, Patricia A.; Aerts, Hugo J.W.L.; et al. (European Radiology, 2021)
Objectives: The size of the heart may predict major cardiovascular events (MACE) in patients with stable chest pain. We aimed to evaluate the prognostic value of 3D whole heart volume (WHV) derived from non-contrast cardiac computed tomography (CT). Methods: Among participants randomized to the CT arm of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE), we used deep learning to extract WHV, defined as the volume of the pericardial sac. We compared the WHV across categories of cardiovascular risk factors and coronary artery disease (CAD) characteristics and determined the association of WHV with MACE (all-cause death, myocardial infarction, unstable angina; median follow-up: 26 months). Results: In the 3798 included patients (60.5 ± 8.2 years; 51.5% women), the WHV was 351.9 ± 57.6 cm3/m2. We found smaller WHV in no- or non-obstructive CAD, women, people with diabetes, sedentary lifestyle, and metabolic syndrome. Larger WHV was found in obstructive CAD, men, and increased atherosclerosis cardiovascular disease (ASCVD) risk score (p < 0.05). In a time-to-event analysis, small WHV was associated with over 4.4-fold risk of MACE (HR (per one standard deviation) = 0.221; 95% CI: 0.068–0.721; p = 0.012) independent of ASCVD risk score and CT-derived CAD characteristics. In patients with non-obstructive CAD, but not in those with no- or obstructive CAD, WHV increased the discriminatory capacity of ASCVD and CT-derived CAD characteristics significantly. Conclusions: Small WHV may represent a novel imaging marker of MACE in stable chest pain. In particular, WHV may improve risk stratification in patients with non-obstructive CAD, a cohort with an unmet need for better risk stratification. Key Points: • Heart volume is easily assessable from non-contrast cardiac computed tomography. • Small heart volume may be an imaging marker of major adverse cardiac events independent and incremental to traditional cardiovascular risk factors and established CT measures of CAD. • Heart volume may improve cardiovascular risk stratification in patients with non-obstructive CAD.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cardiac volume; Coronary disease; Heart failure; Multidetector computed tomography

Soft–matrices based on Fibrous Proteins for Biofabrication - Silva Lourenco, Rauqel; Sarker, Bapi; Singh, Raminder; Cicha, Iwona; Roether, Judith; Kaschta, Joachim; Detsch, Rainer; Garlichs, Christoph; Schubert, Dirk W.; Boccaccini, Aldo R. (14th BIONANO-MATERIALS, 2013)

Soft-matrices based on silk fibroin and alginate for tissue engineering - Silva, Raquel; Singh, Raminder; Sarker, Bapi; Papageorgiou, Dimitrios G.; Juhasz, Judith A.; Roether, Judith; Cicha, Iwona; Kaschta, Joachim; Schubert, Dirk W.; Chrissafis, Konstantinos; Detsch, Rainer; Boccaccini, Aldo R. (International Journal of Biological Macromolecules, 2016)
Keywords: Alginate; Endothelial cells; Silk fibroin; Soft-matrix; Tissue engineering

Software-based automated CT analysis for planning TAVI-Procedures: Systematic validation against expert and novice human interpretation - Weber, J.; Göller, Markus; Smolka, S.; Bittner, D. O.; Gaede, L.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Software innovations in computed tomography for structural heart disease interventions - Hell, Michaela; Gaede, Luise; Achenbach, Stephan; Marwan, Mohamed (EuroIntervention, 2016)
Computed tomography (CT) provides high, isotropic spatial resolution and has become firmly established in pre-procedural imaging for structural heart disease interventions. It allows determination of the exact dimensions of the target structure, provides information regarding the access route and permits identification of fluoroscopic projection angles to provide optimal visualisation for device placement. Several software solutions are available and have been systematically evaluated in the context of transcatheter aortic valve implantation (TAVI). The use of software products to perform automated measurements can be useful, especially when the experience and expertise regarding evaluation of CT in the context of structural heart disease are limited. In scientific studies, software has been demonstrated to provide accurate support for annulus sizing and prosthesis selection, to aid in reliably identifying patients in whom a transfemoral access may be problematic, and to suggest suitable angulations for fluoroscopic imaging to achieve an orthogonal view onto the aortic valve during implantation.
EVALuna2:12098

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

Soy Protein-based composite hydrogels: Physico-chemical characterization and in vitro cytocompatibility - Tansaz, Samira; Singh, Raminder; Cicha, Iwona; Boccaccini, Aldo R. (Polymers, 2018)
Keywords: Tissue engineering; Bioactive glass nanoparticles; Composite hydrogels; Biocompatibility; Soy protein isolate; Human cells

Soy protein isolate/bioactive glass composite membranes: Processing and properties - Tansaz, Samira; Schulte, M.; Kneser, U.; Mohn, D.; Stark, W.; Roether, Judith; Cicha, Iwona; Boccaccini, Aldo R. (European Polymer Journal, 2018)
Keywords: Clotting assay; Cytocompatibility; Bioactive glass; Soy protein isolate; Wound dressing

Spatio-temporally Regularized 4-D Cardiovascular C-arm CT Reconstruction Using a Proximal Algorithm - Taubmann, Oliver; Unberath, Mathias; Lauritsch, Günter; Achenbach, Stephan; Maier, Andreas (Proceedings of the 2017 IEEE International Symposium on Biomedical Imaging, 2017)
Tomographic reconstruction of cardiovascular structures from rotational angiograms acquired with interventional C-arm devices is challenging due to cardiac motion. Gating strategies are widely used to reduce data inconsistency but come at the cost of angular undersampling. We employ a spatio-temporally regularized 4-D reconstruction model, which is solved using a proximal algorithm, to handle the substantial undersampling associated with a strict gating setup. In a numerical phantom study based on the CAVAREV framework, similarity to the ground truth is improved from 82.3% to 87.6%by this approach compared to a state-of-the-art motion compensation algorithm, whereas previous regularized methods evaluated on this phantom achieved results below 80%. We also show first image results for a clinical patient data set.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.spatio_6
Keywords: C-arm CT; Cardiovascular reconstruction; Spatio-temporal regularization; Total variation

Standardized measurement of coronary inflammation using cardiovascular computed tomography: integration in clinical care as a prognostic medical device - Oikonomou, Evangelos K.; Antonopoulos, Alexios S.; Schottlander, David; Marwan, Mohamed; Mathers, Chris; Tomlins, Pete; Siddique, Muhammad; Kluner, Laura; Shirodaria, Cheerag; Mavrogiannis, Michail C.; Thomas, Sheena; Fava, Agostina; et al. (Cardiovascular Research, 2021)
Aims Coronary computed tomography angiography (CCTA) is a first-line modality in the investigation of suspected coronary artery disease (CAD). Mapping of perivascular fat attenuation index (FAI) on routine CCTA enables the non-invasive detection of coronary artery inflammation by quantifying spatial changes in perivascular fat composition. We now report the performance of a new medical device, CaRi-Heart (R), which integrates standardized FAI mapping together with clinical risk factors and plaque metrics to provide individualized cardiovascular risk prediction.
CRIS-Team WoS Importer:2021-12-17

Standardized medical terminology for cardiac computed tomography 2023 update: An Expert Consensus Document of the Society of Cardiovascular Computed Tomography (SCCT), American Association of Physicists in Medicine (AAPM), American College of Radiology (ACR), North American Society for Cardiovascular Imaging (NASCI) and Radiological Society of North America (RSNA) with endorsement by the Asian Society of Cardiovascular Imaging (ASCI), the European Association of Cardiovascular Imaging (EACI), and the European Society of Cardiovascular Radiology (ESCR). - Koweek, Lynne; Achenbach, Stephan; Berman, Daniel S.; Carr, J. Jeffrey; Cury, Ricardo C.; Ghoshhajra, Brian; Litmanovich, Diana; McCollough, Cynthia H.; Taylor, Allen J.; Truong, Quynh A.; Wang, Jia; Weigold, W. Guy; et al. (Journal of Cardiovascular Computed Tomography, 2023)
Since the emergence of cardiac computed tomography (Cardiac CT) at the turn of the 21st century, there has been an exponential growth in research and clinical development of the technique, with contributions from investigators and clinicians from varied backgrounds: physics and engineering, informatics, cardiology, and radiology. However, terminology for the field is not unified. As a consequence, there are multiple abbreviations for some terms, multiple terms for some concepts, and some concepts that lack clear definitions and/or usage. In an effort to aid the work of all those who seek to contribute to the literature, clinical practice, and investigation of the field, the Society of Cardiovascular Computed Tomography updates a standard set of medical terms commonly used in clinical and research activities related to cardiac CT.
CRIS-Team Scopus Importer:2023-08-11

State-of-the-Art Review: Anatomical and Imaging Considerations During Transcatheter Tricuspid Valve Repair Using an Annuloplasty Approach - Wunderlich, Nina C.; Landendinger, Melanie; Achenbach, Stephan; Swaans, Martin J.; Siegel, Robert J.; Ho, Siew Yen; Arnold, Martin (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter techniques for the treatment of tricuspid regurgitation (TR) are being more frequently used and several new devices are in development. Since 90% of patients with TR have secondary TR, catheter based systems which reduce the dilated tricuspid annulus area are of particular interest. In order to perform an annuloplasty procedure effectively and safely, knowledge about the anatomy of the tricuspid valve apparatus and especially of the annulus in relation to the important neighboring structures such as the aortic root, the RCA, the electrical pathways and the CS is fundamental. In addition, comprehensive understanding of the device itself, the delivery system, its maneuverability and the individual procedural steps is required. Furthermore, the use of multi-modality imaging is important. For each step of the procedure the appropriate imaging modality as well as the optimal; imaging planes are crucial to provide the necessary information to best guide the individual procedural step.
CRIS-Team WoS Importer:2021-03-12

STEMI of the anterior wall associated with Sneddon's syndrome - Scheuermann, S.; Schlundt, Christian (Herz, 2014)
EVALuna2:12085

Stent deformation in bifurcation stenting with final kissing balloon inflation: in vivo demonstration with enhanced cine fluoroscopic imaging - Achenbach, Stephan; Schlundt, Christian (Jacc-Cardiovascular Interventions, 2014)
EVALuna2:12019

Stent evaluation in low-dose coronary CT angiography: Effect of different iterative reconstruction settings - Wüst, Wolfgang; May, Matthias; Scharf, Michael; Layritz, Christian; Eisentopf, Jasmin; Ropers, Dieter; Pflederer, Tobias; Uder, Michael; Achenbach, Stephan; Lell, Michael (Journal of Cardiovascular Computed Tomography, 2013)
Background: Different iterative reconstruction (IR) techniques compensate increased noise from lower tube current-time product settings, yet the differences between IR settings remain unclear. Objective: Aim of this study was to test whether different IR settings have a clinically relevant influence on image quality and on the diagnostic accuracy of low-dose CT angiography in patients with a stent. Methods: Forty-two patients with 73 coronary stents were prospectively enrolled. Data were acquired with dual-source CT, and images were reconstructed with standard filtered back projection (FBP) and raw data-based IR with different settings (I3, I4, I5). Quantitative parameters, including CT-attenuation, noise, signal-to-noise ratio, contrast-to-noise ratio, as well as the presence of in-stent stenosis > 50% were determined. All patients had invasive angiography as reference standard. Results: Mean effective dose was 0.32 ± 0.02 mSv. Image noise decreased significantly compared with FBP (I3= 29%; I4= 38% and I5= 45%), whereas signal-to-noise and contrast-to-noise ratios increased significantly (all IR settings P <.01). Subjective image quality was superior with all IR settings (P < .01). FBP sensitivity, specificity, positive predictive value, and negative predictive value were 83%, 71%, 36%, and 96% per stent compared with 100%, 76%, 44%, and 100%, respectively, in IR reconstructions independent of the IR setting applied. Conclusion: In low-dose coronary CT angiography, higher IR settings significantly improved subjective and objective image quality but had no effect on accuracy. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary stents; Iterative reconstruction; Low dose; SAFIRE

Strategies for radiation dose reduction in nuclear cardiology and cardiac computed tomography imaging: a report from the European Association of Cardiovascular Imaging (EACVI), the Cardiovascular Committee of European Association of Nuclear Medicine (EANM), and the European Society of Cardiovascular Radiology (ESCR) - Gimelli, Alessia; Achenbach, Stephan; Buechel, Ronny R.; Edvardsen, Thor; Francone, Marco; Gaemperli, Oliver; Hacker, Marcus; Hyafil, Fabien; Kaufmann, Philipp A.; Lancellotti, Patrizio; Nieman, Koen; Pontone, Gianluca; et al. (European Heart Journal, 2018)
EVALuna2:33587

Stratified prevention: opportunities and limitations. Report on the 1st interdisciplinary cardiovascular workshop in Augsburg - Kirchhof, Gregor; Lindner, Josef Franz; Achenbach, Stephan; Berger, Klaus; Blankenberg, Stefan; Fangerau, Heiner; Gimpel, Henner; Gassner, Ulrich M.; Kersten, Jens; Magnus, Dorothea; Rebscher, Herbert; Schunkert, Heribert; et al. (Clinical Research in Cardiology, 2018)
Sufficient exercise and sleep, a balanced diet, moderate alcohol consumption and a good approach to handle stress have been known as lifestyles that protect health and longevity since the Middle Age. This traditional prevention quintet, turned into a sextet by smoking cessation, has been the basis of the "preventive personality" that formed in the twentieth century. Recent analyses of big data sets including genomic and physiological measurements have unleashed novel opportunities to estimate individual health risks with unprecedented accuracy, allowing to target preventive interventions to persons at high risk and at the same time to spare those in whom preventive measures may not be needed or even be harmful. To fully grasp these opportunities for modern preventive medicine, the established healthy life styles require supplementation by stratified prevention. The opportunities of these developments for life and health contrast with justified concerns: A "surveillance society", able to predict individual behaviour based on big data, threatens individual freedom and jeopardises equality. Social insurance law and the new German Disease Prevention Act (Präventionsgesetz) rightly stress the need for research to underpin stratified prevention which is accessible to all, ethical, effective, and evidence based. An ethical and acceptable development of stratified prevention needs to start with autonomous individuals who control and understand all information pertaining to their health. This creates a mandate for lifelong health education, enabled in an individualised form by digital technology. Stratified prevention furthermore requires the evidence-based development of a new taxonomy of cardiovascular diseases that reflects disease mechanisms. Such interdisciplinary research needs broad support from society and a better use of biosamples and data sets within an updated research governance framework.
EVALuna2:36007

Successful cardiopulmonary resuscitation after cardiac arrest as a sepsis-like-syndrome - Bal, Zeynep; Klinghammer, Lutz; Achenbach, Stephan; Schneider, R. (2016)
EVALuna2:33687

Summary of the ESC position paper on cancer treatment and cardiovascular toxicity - Hoog, Jana; Achenbach, Stephan (Herz, 2016)
The numbers of survivors of cancer have increased as a consequence of advances in chemotherapy; however, the side effects of cancer treatment have become increasingly more important. The most frequent side effects include cardiovascular complications, which can lead to acute and delayed morbidity and mortality, often many years later. The discipline of cardio-oncology deals with the prevention, diagnostics and treatment of cardiovascular diseases caused by cancer therapy. The most important cardiovascular side effects of cytostatic therapy are heart failure due to myocardial dysfunction (cardiotoxicity), coronary artery disease, valvular disease and ventricular arrhythmia as a result of QT extension. In addition, arterial hypertension, thromboembolic events, pulmonary hypertension, vasculopathy and pericardial complications can also occur. Fundamentally, a strict limitation of risk factors is necessary to minimize the cardiovascular side effects of potentially cardiotoxic therapeutic procedures. Patients with impaired left ventricular function should be identified by echocardiographic examination prior to cardiotoxic chemotherapy. Treatment with beta blockers and angiotensin-converting enzyme (ACE) inhibitors can also be indicated in asymptomatic patients in order to minimize the effects of chemotherapy on myocardial dysfunction. Prophylactic administration of ACE inhibitors and beta blockers during anthracycline chemotherapy can be considered in patients free of cardiac disease.
EVALuna2:33660

Superior Risk Stratification With Coronary Computed Tomography Angiography Using a Comprehensive Atherosclerotic Risk Score - van Rosendael, Alexander R.; Shaw, Leslee J.; Xie, Joe X.; Dimitriu-Leen, Aukelien C.; Smit, Jeff M.; Scholte, Arthur J.; van Werkhoven, Jacob M.; Callister, Tracy Q.; DeLago, Augustin; Berman, Daniel S.; Hadamitzky, Martin; Hausleiter, Jeorg; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2019)
Objectives: This study was designed to assess the prognostic value of a new comprehensive coronary computed tomography angiography (CTA) score compared with the stenosis severity component of the Coronary Artery Disease-Reporting and Data System (CAD-RADS). Background: Current risk assessment with coronary CTA is mainly focused on maximal stenosis severity. Integration of plaque extent, location, and composition in a comprehensive model may improve risk stratification. Methods: A total of 2,134 patients with suspected but without known CAD were included. The predictive value of the comprehensive CTA score (ranging from 0 to 42 and divided into 3 groups: 0 to 5, 6 to 20, and >20) was compared with the CAD-RADS combined into 3 groups (0% to 30%, 30% to 70% and ≥70% stenosis). Its predictive performance was internally and externally validated (using the 5-year follow-up dataset of the CONFIRM [Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry], n = 1,971). Results: The mean age of patients was 55 ± 13 years, mean follow-up 3.6 ± 2.8 years, and 130 events (myocardial infarction or death) occurred. The new, comprehensive CTA score showed strong and independent predictive value using the Cox proportional hazard analysis. A model including clinical variables plus comprehensive CTA score showed better discrimination of events compared with a model consisting of clinical variables plus CAD-RADS (0.768 vs. 0.742, p = 0.001). Also, the comprehensive CTA score correctly reclassified a significant proportion of patients compared with the CAD-RADS (net reclassification improvement 12.4%, p < 0.001). Good predictive accuracy was reproduced in the external validation cohort. Conclusions: The new comprehensive CTA score provides better discrimination and reclassification of events compared with the CAD-RADS score based on stenosis severity only. The score retained similar prognostic accuracy when externally validated. Anatomic risk scores can be improved with the addition of extent, location, and compositional measures of atherosclerotic plaque. (Comprehensive CTA risk score calculator is available at: http://18.224.14.19/calcApp/)
CRIS-Team Scopus Importer:2019-10-01
Keywords: coronary computed tomography angiography; risk stratification; stable coronary artery disease

Suppression of proatherogenic leukocyte interactions by MCS-18 - Impact on advanced atherosclerosis in ApoE-deficient mice - Kühn, Constanze; Tauchi, Miyuki; Stumpf, Christian; Daniel, Christoph; Bäuerle, Tobias; Schwarz, Marc; Kerek, Franz; Steinkasserer, Alexander; Zinser, Elisabeth; Achenbach, Stephan; Dietel, Barbara (Atherosclerosis, 2016)
Atherosclerosis is associated with chronic inflammatory responses of the arterial blood vessels. The previously observed protective effect of the MCS-18 substance against the initiation of atherosclerosis in a murine model was explained by its pronounced anti-inflammatory activity. Here, we investigated its impact on murine plaque progression in advanced atherosclerosis and on proatherogenic processes.ApoE-deficient mice were fed a high-fat diet for 12 weeks to induce atherosclerosis, followed by normal chow and intraperitoneal injections of either MCS-18 (500 ?g, n = 10) or saline (n = 10) twice a week for another 12 weeks. Plaque size was reduced in MCS-18 treated mice compared to controls (p = 0.001), which was associated with a reduced size of the lipid core (p = 0.01). There was a decrease in apoptotic cells (p = 0.02), endothelial ICAM-1 expression (p < 0.001), and macrophage density (p = 0.01) in the MCS-18 group. In addition, human and murine dendritic cells (DCs) and human umbilical vein endothelial cells (HUVECs) were treated with MCS-18 (50-200 ?g/ml) to analyze cell migration and adhesion under flow conditions. MCS-18 reduced human (p = 0.01) and murine (p = 0.006) DC migration. Furthermore, adhesion of MCS-18-treated DCs to a HUVEC monolayer was decreased (p < 0.001). Compared to controls, CD209 (p < 0.001) and CCR7 (p = 0.003) expression was decreased in MCS-18-treated DCs, while in HUVECs lower levels of ICAM-1 (p < 0.001) and of phosphorylated NF-?B-p65 (p = 0.002) were observed. Blocking of ICAM-1 reduced DC adhesion (p < 0.001).MCS-18 exhibits interesting therapeutic effects when applied in advanced murine atherosclerosis. Its antiatherogenic impact might be associated with a suppressed adhesion to the endothelium due to down-regulation of endothelial ICAM-1 expression.
EVALuna2:12031

Symmetry, Outliers, and Geodesics in Coronary Artery Centerline Reconstruction from Rotational Angiography - Unberath, Mathias; Taubmann, Oliver; Hell, Michaela; Achenbach, Stephan; Maier, Andreas (Medical Physics, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.symmet
Keywords: angiography; cone-beam CT; postprocessing; spanning trees

Symptoms, disease severity and treatment of adults with a new diagnosis of severe aortic stenosis - Frey, Norbert; Steeds, Richard Paul; Rudolph, Tanja K.; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Lloyd, Guy; Bortone, Alessandro Santo; Hauptmann, Karl Eugen; Clerici, Alberto; et al. (Heart (British Cardiac Society), 2019)
OBJECTIVE: Contemporary data on patients with previously undiagnosed severe aortic stenosis (AS) are scarce. We aimed to address this gap by gathering data from consecutive patients diagnosed with severe AS on echocardiography. METHODS: This was a prospective, multicentre, multinational, registry in 23 tertiary care hospitals across 9 European countries. Patients with a diagnosis of severe AS were included using echocardiography (aortic valve area (AVA) <1 cm2, indexed AVA <0.6 cm2/m2, maximum jet-velocity (Vmax) >4 m/s and/or mean transvalvular gradient >40 mm Hg). RESULTS: The 2171 participants had a mean age of 77.9 years and 48.0% were female. The mean AVA was 0.73 cm2, Vmax4.3 m/s and mean gradient 47.1 mm Hg; 62.1% had left ventricular hypertrophy and 27.3% an ejection fraction (EF) <50%. 1743 patients (80.3%) were symptomatic (shortness-of-breath 91.0%; dizziness 30.2%, chest pain 28.9%). Patients had a EuroSCORE II of 4.0; 25.3% had a creatinine clearance <50 mL/min, and 3.2% had an EF <30%. Symptomatic patients were older and had more comorbidities than asymptomatic patients. Despite European Society of Cardiology 2017 valvular heart disease guideline class I recommendation, in only 76.2% a decision was made for an intervention (transcatheter 50.4%, surgical aortic valve replacement 25.8%). In asymptomatic patients, 57.7% with a class I/IIa indication were scheduled for a procedure, while 36.3% patients without an indication had their valve replaced. CONCLUSIONS: The majority of patients with severe AS presented at an advanced disease stage. Management of severe AS remained suboptimal in a significant proportion of contemporary patients with severe AS. TRIAL REGISTRATION NUMBER: NCT02241447;Results.
CRIS-Team Scopus Importer:2019-11-08
Keywords: aortic stenosis; surgical aortic valve replacement; symptoms; transcatheter aortic valve replacement

Synthesis and characterization of tissue plasminogen activator—functionalized superparamagnetic iron oxide nanoparticles for targeted fibrin clot dissolution - Heid, Susanne; Unterweger, Harald; Tietze, Rainer; Friedrich, Ralf P.; Weigel, Bianca; Cicha, Iwona; Eberbeck, Dietmar; Boccaccini, Aldo R.; Alexiou, Christoph; Lyer, Stefan (International Journal of Molecular Sciences, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) have attracted great attention in many biomedical fields and are used in preclinical/experimental drug delivery, hyperthermia and medical imaging. In this study, biocompatible magnetite drug carriers, stabilized by a dextran shell, were developed to carry tissue plasminogen activator (tPA) for targeted thrombolysis under an external magnetic field. Different concentrations of active tPA were immobilized on carboxylated nanoparticles through carbodiimide-mediated amide bond formation. Evidence for successful functionalization of SPIONs with carboxyl groups was shown by Fourier transform infrared spectroscopy. Surface properties after tPA immobilization were altered as demonstrated by dynamic light scattering and ζ potential measurements. The enzyme activity of SPION-bound tPA was determined by digestion of fibrin-containing agarose gels and corresponded to about 74% of free tPA activity. Particles were stored for three weeks before a slight decrease in activity was observed. tPA-loaded SPIONs were navigated into thrombus-mimicking gels by external magnets, proving effective drug targeting without losing the protein. Furthermore, all synthesized types of nanoparticles were well tolerated in cell culture experiments with human umbilical vein endothelial cells, indicating their potential utility for future therapeutic applications in thromboembolic diseases.
Keywords: Activated ester reaction; Drug targeting; Fibrinolysis; Protein binding; Superparamagnetic iron oxide nanoparticles; Tissue plasminogen activator

Systematic assessment of health care perception in adults with congenital heart disease in Germany - Neidenbach, Rhoia; Achenbach, Stephan; Andonian, Caroline; Bauer, Ulrike M.M.; Ewert, Peter; Freilinger, Sebastian; Gundlach, Ulrike; Kaemmerer, Ann Sophie; Nagdyman, Nicole; Nebel, Kathrin; Oberhoffer, Renate; Pieper, Lars; et al. (Cardiovascular Diagnosis and Therapy, 2021)
Background: The number of adults with congenital heart disease (ACHD) is steadily rising due to increased survival rate and improved medical resources. Accordingly, more than 330,000 ACHD are currently living in Germany. Almost all of them require lifelong specialized medical follow-up for their chronic heart disease, often accompanied by residua, sequelae, or comorbidities. Primary care physicians (PCPs) are a crucial factor in directing patients to ACHD specialists or specialized institutions, but despite all efforts, the number of ACHD under specialized care is low, the lost-to-follow-up rate is high, and the morbidity and mortality is substantial. The present cross-sectional study was designed to systematically characterize the health care of ACHD from a patient perspective, including (I) use of medical care by ACHD, (II) medical counselling needs, and (III) perceived satisfaction with health care. Methods: The German-wide analysis was based on a 25-item questionnaire designed to address different aspects of medical status and health issues of ACHD from their own perspective, performed between May of 2017 and July of 2020. Results: A total of 4,008 ACHD (52% female; mean age 41.9±17.2 years) completed the questionnaire. The majority of ACHD (3,524, 87.9%) reported, that they consulted their PCP for non-cardiac health problems, and 49.7% (n=1,991) consulted their PCP also for medical problems associated with the underlying CHD. Almost all ACHD reported a need for medical advice concerning exercise capacity and daily life activities, occupational skills, pregnancy, rehabilitation, genetic counselling, insurance, and retirement. A total of 1,840 (45.9%) patients were not aware of the existence of certified ACHD specialists or centers. Moreover, 2,552 (67.6%) of those surveyed were uninformed about patient organizations for ACHD. Conclusions: The present study demonstrates that ACHD are largely uninformed about the ACHD care structures available nationwide, although the patients have a great need for specialized follow-up, advice, and care.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Adults with congenital heart disease (ACHD); Congenital heart disease (CHD); General practitioners; Medical health supply; Primary care physicians (PCPs); Primary health care

Tako-Tsubo Cardiomyopathy: clinical correlations of typical and atypical left ventricular contraction patterns - Gaede, L.; Herchenbach, A.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Targeted Temperature Management: Peltier's Element-Based Focal Brain Cooling Protects Penumbra Neurons from Progressive Damage in Experimental Cerebral Ischemia - Tauchi, Miyuki; De Rink, Maria Mercedes Tejada; Fujioka, Hiroshi; Okayama, Satoko; Nakamura, Kei-Ichiro; Dietel, Barbara; Achenbach, Stephan; Kollmar, Rainer; Schwab, Stefan; Ushijima, Kazuo; Harada, Hideki (Therapeutic Hypothermia and Temperature Management, 2018)
Targeted temperature management (TTM), or therapeutic hypothermia, is one of the most potent neuroprotective approaches after ischemic and traumatic brain injuries. TTM has been applied clinically with various methods, but effective achievement and maintenance of the target temperature remain challenging. Furthermore, timing of cooling and target body and brain temperature to optimize effectiveness for neuroprotection and to minimize side effects are yet to be standardized. Focal brain cooling is a potential strategy to minimize adverse effects of systemic TTM. In this study, we report on a focal brain cooling device for animals and its effectiveness of focal cooling in several animal models of ischemic cerebral stroke. A focal brain cooling device was constructed using a Peltier's element, a thermoelectric heat pump. The device was validated for its cooling ability, and optimal settings to induce an effective intracranial temperature were determined using male Sprague-Dawley rats. Transient and permanent middle cerebral artery occlusions were experimentally induced, and focal brain cooling was applied using the device varying the timing and duration of cooling. The stroke-induced infarct and edema volumes were evaluated from Nissl-stained cryosections. The focal brain cooling device was able to decrease and subsequently maintained cerebral hypothermia in free-moving rats without altering the core temperature. The device with validated intracranial temperatures produced neuroprotective effects in the acute phase of ischemic neural death, reperfusion injury, progressing damage to the penumbra, and edema formation. In conclusion, our validated focal cooling device enabled rapid and accurate cerebral TTM in rats. Using this device, we were able to test the neuroprotective effect of focal TTM in several pathological stages of cerebral ischemia, which warrants further studies to develop clinically feasible TTM procedures for patients with cerebral stroke.
EVALuna2:36338

Temporal trends in transcatheter and surgical aortic valve replacement : An analysis of aortic valve replacements in Germany during 2012-2014 - Gaede, L.; Kim, W. -K.; Blumenstein, J.; Liebetrau, C.; Doerr, O.; Nef, H.; Hamm, Christian; Walther, T.; Achenbach, Stephan; Elsaesser, A.; Moellmann, H. (Herz, 2017)
This analysis of the data of the obligatory quality assurance programme AQUA shows the perioperative risk as well as the procedural outcome evaluated by the observed versus expected in-hospital mortality ratio (O/E ratio) of 62,872 patients undergoing isolated surgical (sAVR), transcatheter transvascular (TV-), or transapical (TA-) aortic valve replacement (TAVI) from 2012 to 2014 in Germany. The number of TAVI procedures increased from 9,352 in 2012 to 13,278 in 2014, whereas the number of sAVR remained constant (2012: 9,949; 2014: 9,953). Between 2012 and 2014, the number of TAVI implanted in patients with a logistic EuroScore I (logESI) of ≤10 % (2012: 21 %; 2014: 26 %) as well as with a logESI <20 % (2012: 57 %; 2014: 64 %) increased. In-hospital mortality in TAVI patients decreased from 5.2 % (TV: 5.0 %; TA: 7.4 %) in 2012 to 4.2 % (TV: 3.8 %; TA: 5.5 %) in 2014, whereas it was stable for sAVR patients (2012: 2.8 %; 2014: 2.6 %). The O/E ratio of TAVI patients decreased from 0.91 (TV: 0.79; TA: 1.2) to 0.73 (TV: 0.69; TA: 0.89), whereas this ratio remained constant for sAVR patients (2012: 0.92; 2014: 0.93). In summary, estimated surgical risk, in-hospital mortality, as well as the O/E ratio for patients undergoing TAVI declined constantly during the last 3 years.
EVALuna2:33642

Textile Integrated Wearable Technologies for Sports and Medical Applications - Leutheuser, Heike; Lang, Nadine; Gradl-Trautvetter, Stefan; Struck, Matthias; Tobola, Andreas; Hofmann, Christian; Anneken, Lars; Eskofier, Björn (Smart Textiles, 2017)

The association of pericoronary adipose tissue attenuation with major adverse cardiac events (MACE) and atherosclerosis-relevant inflammatory mediators - Göller, Markus; Achenbach, Stephan; Herrmann, N.; Bittner, Daniel O.; Ammon, Fabian; Kilian, Tobias; Smolka, S.; Uehlein, Sabrina; Moshage, Maximilian; Raaz-Schrauder, Dorette; Dey, D.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

The best way to assess oedema using T1, T2 mapping or three-dimensional T2-weighted fast-spin-echo triple inversion recovery sequences via cardiovascular MRI in outpatients with suspected myocarditis - Jeserich, M.; Kimmel, S.; Maisch, P.; von Rauffer, S.; Achenbach, Stephan (Clinical Radiology, 2020)
AIM: To evaluated T1-, T2 mapping, and a three-dimensional (3D) T2-weighted fast-spin-echo triple inversion recovery sequences (3D STIR) for diagnosing myocardial oedema in patients with suspected early myocarditis and at follow-up. MATERIALS AND METHODS: Sixteen patients with suspected myocarditis and 15 controls matched for gender and age were examined prospectively. To evaluate oedema, an electrocardiogram-triggered T1 and T2 mapping with a gradient spin echo technique and 3D STIR sequences were used to cover the entire left ventricle. The signal intensity ratio (heart muscle in relation to skeletal muscle) was calculated (3D STIR ratio). All patients underwent repeat examinations at follow-up. RESULTS: The mean 3D-STIR ratio was 2.14±0.45 at the patients' initial examination as compared to the control patients' 1.54±0.18 in (p=0.0001) and 1.75±0.16 in patients at follow-up (p=0.002 versus first visit). The 3D STIR ratio of the septum, anterior, lateral, and inferior wall also differed significantly between patients and controls. No significant difference was observed in T1 and T2 mapping between patients and controls at baseline and patients at follow-up. CONCLUSIONS: A significantly higher global signal intensity ratio with 3D-STIR was identified in patients with suspected myocarditis compared to controls, and a significant change during follow-up. No significant difference was detected in T1-, T2 mapping between patients and controls, or between the initial examination and follow-up of patients. The global 3D-STIR ratio may therefore be useful for the diagnosis of myocarditis and should be explored further.
CRIS-Team Scopus Importer:2020-03-10

The Coronary Artery Disease-Reporting and Data System (CAD-RADS): Prognostic and Clinical Implications Associated With Standardized Coronary Computed Tomography Angiography Reporting - Xie, Joe X.; Cury, Ricardo C.; Leipsic, Jonathon; Crim, Matthew T.; Berman, Daniel S.; Gransar, Heidi; Budoff, Matthew J.; Achenbach, Stephan; Hartaigh, Briain O.; Callister, Tracy Q.; Marques, Hugo; Rubinshtein, Ronen; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2018)
OBJECTIVES: This study sought to assess clinical outcomes associated with the novel Coronary Artery Disease-Reporting and Data System (CAD-RADS) scores used to standardize coronary computed tomography angiography (CTA) reporting and their potential utility in guiding post-coronary CTA care. BACKGROUND: Clinical decision support is a major focus of health care policies aimed at improving guideline-directed care. Recently, CAD-RADS was developed to standardize coronary CTA reporting and includes clinical recommendations to facilitate patient management after coronary CTA. METHODS: In the multinational CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) registry, 5,039 patients without known coronary artery disease (CAD) underwent coronary CTA and were stratified by CAD-RADS scores, which rank CAD stenosis severity as 0 (0%), 1 (1% to 24%), 2 (25% to 49%), 3 (50% to 69%), 4A (70% to 99% in 1 to 2 vessels), 4B (70% to 99% in 3 vessels or ≥50% left main), or 5 (100%). Kaplan-Meier and multivariable Cox models were used to estimate all-cause mortality or myocardial infarction (MI). Receiver-operating characteristic (ROC) curves were used to compare CAD-RADS to the Duke CAD Index and traditional CAD classification. Referrals to invasive coronary angiography (ICA) after coronary CTA were also assessed. RESULTS: Cumulative 5-year event-free survival ranged from 95.2% to 69.3% for CAD-RADS 0 to 5 (p < 0.0001). Higher scores were associated with elevations in event risk (hazard ratio: 2.46 to 6.09; p < 0.0001). The ROC curve for prediction of death or MI was 0.7052 for CAD-RADS, which was noninferior to the Duke Index (0.7073; p = 0.893) and traditional CAD classification (0.7095; p = 0.783). ICA rates were 13% for CAD-RADS 0 to 2, 66% for CAD-RADS 3, and 84% for CAD-RADS ≥4A. For CAD-RADS 3, 58% of all catheterizations occurred within the first 30 days of follow-up. In a patient subset with available medication data, 57% of CAD-RADS 3 patients who received 30-day ICA were either asymptomatic or not receiving antianginal therapy at baseline, whereas only 32% had angina and were receiving medical therapy. CONCLUSIONS: CAD-RADS effectively identified patients at risk for adverse events. Frequent ICA use was observed among patients without severe CAD, many of whom were asymptomatic or not taking antianginal drugs. Incorporating CAD-RADS into coronary CTA reports may provide a novel opportunity to promote evidence-based care post-coronary CTA.
EVALuna2:33592

The diagnostic accuracy and outcomes after coronary computed tomography angiography vs. conventional functional testing in patients with stable angina pectoris: a systematic review and meta-analysis - Nielsen, Lene H.; Ortner, Nino; Norgaard, Bjarne L.; Achenbach, Stephan; Leipsic, Jonathon; Abdulla, Jawdat (European Heart Journal - Cardiovascular Imaging, 2014)
To systematically review and perform a meta-analysis of the diagnostic accuracy and post-test outcomes of conventional exercise electrocardiography (XECG) and single-photon emission computed tomography (SPECT) compared with coronary computed tomography angiography (coronary CTA) in patients suspected of stable coronary artery disease (CAD).We systematically searched for studies published from January 2002 to February 2013 examining the diagnostic accuracy (defined as at least >=50% luminal obstruction on invasive coronary angiography) and outcomes of coronary CTA (>=16 slice) in comparison with XECG and SPECT. The search revealed 11 eligible studies (N = 1575) comparing the diagnostic accuracy and 7 studies (N = 216.603) the outcomes of coronary CTA vs. XECG or/and SPECT. The per-patient sensitivity [95% confidence interval (95% CI)] to identify significant CAD was 98% (93-99%) for coronary CTA vs. 67% (54-78%) (P < 0.001) for XECG and 99% (96-100%) vs. 73% (59-83%) (P = 0.001) for SPECT. The specificity (95% CI) of coronary CTA was 82% (63-93%) vs. 46% (30-64%) (P < 0.001) for XECG and 71% (60-80%) vs. 48% (31-64%) (P = 0.14) for SPECT. The odds ratio (OR) of downstream test utilization (DTU) for coronary CTA vs. XECG/SPECT was 1.38 (1.33-1.43, P < 0.001), for revascularization 2.63 (2.50-2.77, P < 0.001), for non-fatal myocardial infarction 0.53 (0.39-0.72, P < 0.001), and for all-cause mortality 1.01 (0.87-1.18, P = 0.87).The up-front diagnostic performance of coronary CTA is higher than of XECG and SPECT. When compared with XECG/SPECT testing, coronary CTA testing is associated with increased DTU and coronary revascularization.
EVALuna2:11985

The Effect of Antibacterial Particle Incorporation on the Mechanical Properties, Biodegradability, and Biocompatibility of PLA and PHBV Composites - Mazur, Karolina; Singh, Raminder; Friedrich, Ralf P.; Genc, Hatice; Unterweger, Harald; Sałasińska, Kamila; Bogucki, Rafał; Kuciel, Stanisław; Cicha, Iwona (Macromolecular Materials and Engineering, 2020)
The composites based on polylactide (PLA) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with the addition of antibacterial particles: silver (Ag) and copper oxide (CuO) are characterized. Basic mechanical properties and biodegradation processes, as well as biocompatibility of materials with human cells are determined. The addition of Ag or CuO to the polymers do not significantly affect their mechanical properties, flammability, or biodegradation rate. However, several differences between the base materials are observed. PLA-based composites have higher tensile and impact strength values, while PHBV-based ones have a higher modulus of elasticity, as well as better mechanical properties at elevated temperatures. Concerning biocompatibility, each of the tested materials support the growth of fibroblasts over time, although large differences are observed in the initial cell attachment. The analysis of hydrolytic degradation effects on the structure of materials shows that PHBV degrades much faster than PLA. The results of this study confirm the good potential of the investigated biodegradable polymer composites with antibacterial particles for future biomedical applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: biocompatibility; biocomposites; copper oxide particles; poly (3-hydroxybutyrate-co-3-hydroxyvalerate); polylactide; silver particles

The future of coronary computer tomography angiography - Achenbach, Stephan (European Heart Journal, 2016)
CRIS-Team Scopus Importer:2023-03-08

The impact of frailty on in-hospital outcomes among patients undergoing percutaneous coronary intervention in the United States - Kwok, Shing; Achenbach, Stephan; Curzen, Nick; Fischman, David; Savage, Michael; Bagur, Rodrigo; Kontopantelis, Evangelos; Martin, Glen; Steg, P. Gabriel; Mamas, Mamas (HEART, 2019)
CRIS-Team WoS Importer:2019-07-02

The Involvement of Cx43 in JNK1/2-Mediated Endothelial Mechanotransduction and Human Plaque Progression - Tauchi, Miyuki; Oshita, Kensuke; Urschel, Katharina; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balazs; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2023)
Atherosclerotic lesions preferentially develop at bifurcations, characterized by non-uniform shear stress (SS). The aim of this study was to investigate SS-induced endothelial activation, focusing on stress-regulated mitogen-activated protein kinases (MAPK) and downstream signaling, and its relation to gap junction proteins, Connexins (Cxs). Human umbilical vein endothelial cells were exposed to flow (“mechanical stimulation”) and stimulated with TNF-α (“inflammatory stimulation”). Phosphorylated levels of MAPKs (c-Jun N-terminal kinase (JNK1/2), extracellular signal-regulated kinase (ERK), and p38 kinase (p38K)) were quantified by flow cytometry, showing the activation of JNK1/2 and ERK. THP-1 cell adhesion under non-uniform SS was suppressed by the inhibition of JNK1/2, not of ERK. Immunofluorescence staining and quantitative real-time PCR demonstrated an induction of c-Jun and c-Fos and of Cx43 in endothelial cells by non-uniform SS, and the latter was abolished by JNK1/2 inhibition. Furthermore, plaque inflammation was analyzed in human carotid plaques (n = 40) using immunohistochemistry and quanti-gene RNA-assays, revealing elevated Cx43+ cell counts in vulnerable compared to stable plaques. Cx43+ cell burden in the plaque shoulder correlated with intraplaque neovascularization and lipid core size, while an inverse correlation was observed with fibrous cap thickness. Our results constitute the first report that JNK1/2 mediates Cx43 mechanoinduction in endothelial cells by atheroprone shear stress and that Cx43 is expressed in human carotid plaques. The correlation of Cx43+ cell counts with markers of plaque vulnerability implies its contribution to plaque progression.
CRIS-Team Scopus Importer:2023-02-03
Keywords: atherogenesis; endothelial dysfunction; gap junctions; MAPK; mechanotransduction; shear stress

The ischemia trial: Implication for cardiac imaging in 2020 and beyond - Leipsic, Jonathon A.; Achenbach, Stephan (Radiology: Cardiothoracic Imaging, 2020)
Establishing a diagnosis of coronary artery disease (CAD) is more difficult than it would seem. Diagnosis of CAD can be approached in two ways: Detection of ischemia (often with stress myocardial perfusion at SPECT, PET, and cardiac MRI) and visualization of the coronary artery anatomy to demonstrate stenosis (noninvasively with cardiac CT). In addition to providing further supportive evidence for the use of coronary CT angiography as the first-line test for the evaluation of CAD, the ISCHEMIA trial also resulted in some interesting findings with regard to imaging; these findings resulted in the open-ended question of “What does this mean for imagers?”.
CRIS-Team Scopus Importer:2023-03-08

The ISCHEMIA trial: Implications for non-invasive imaging - Rakisheva, Amina; Achenbach, Stephan; Marwan, Mohamed (Anatolian Journal of Cardiology, 2020)
Coronary artery disease (CAD) is highly prevalent and constitutes the single most common cause of death worldwide. However, the diagnosis of CAD remains challenging. There are two ways to approach the diagnosis of CAD, namely (1) by a functional non-invasive stress test to detect ischemia (stress echocardiography, stress cardiovascular magnetic resonance, single-photon emission computed tomography, positron emission tomography) or (2) by imaging for stenosis visualization (coronary computed tomography angiography or invasive coronary angiography). There are also two approaches for treatment: medical treatment and revascularization. The International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial investigated the outcome differences of patients who had moderate to severe ischemia on stress testing and who, after CT angiography, had ruled out left main stenosis and demonstrated at least 1 coronary artery stenosis exceeding 50%. The patients were randomized to an initially conservative treatment versus immediate revascularization. No difference in hard outcomes was found, but angina relief was more effective in the revascularization group. In this article, we explore the implications of the ISCHEMIA trial for non-invasive testing in suspected CAD.
CRIS-Team WoS Importer:2020-07-24

The Journal of Cardiovascular Computed Tomography: 2020 Year in review - Villines, Todd C.; Al'Aref, Subhi J.; Andreini, Daniele; Chen, Marcus Y.; Choi, Andrew D.; De Cecco, Carlo N.; Dey, Damini; Earls, James P.; Ferencik, Maros; Gransar, Heidi; Hecht, Harvey; Leipsic, Jonathon A.; et al. (Journal of Cardiovascular Computed Tomography, 2021)
The purpose of this review is to highlight the most impactful, educational, and frequently downloaded articles published in the Journal of Cardiovascular Computed Tomography (JCCT) for the year 2020. The JCCT reached new records in 2020 for the number of research submissions, published manuscripts, article downloads and social media impressions. The articles in this review were selected by the Editorial Board of the JCCT and are comprised predominately of original research publications in the following categories: Coronavirus disease 2019 (COVID-19), coronary artery disease, coronary physiology, structural heart disease, and technical advances. The Editorial Board would like to thank each of the authors, peer-reviewers and the readers of JCCT for making 2020 one of the most successful years in its history, despite the challenging circumstances of the global COVID-19 pandemic.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cardiac computed tomography; Cardiac CT; Coronary artery calcium; Coronary CT angiography; COVID-19; Journal of cardiovascular computed tomography; Structural heart disease

The journal of cardiovascular computed tomography: A year in review: 2022 - Pontone, Gianluca; Mushtaq, Saima; Al'Aref, Subhi J.; Andreini, Daniele; Baggiano, Andrea; Canan, Arzu; Cavalcante, Joao L.; Chelliah, Anjali; Chen, Marcus; Choi, Andrew; Damini, Dey; De Cecco, Carlo Nicola; et al. (Journal of Cardiovascular Computed Tomography, 2023)
This review aims to summarize key articles published in the Journal of Cardiovascular Computed Tomography (JCCT) in 2022, focusing on those that had the most scientific and educational impact. The JCCT continues to expand; the number of submissions, published manuscripts, cited articles, article downloads, social media presence, and impact factor continues to grow. The articles selected by the Editorial Board of the JCCT in this review highlight the role of cardiovascular computed tomography (CCT) to detect subclinical atherosclerosis, assess the functional relevance of stenoses, and plan invasive coronary and valve procedures. A section is dedicated to CCT in infants and other patients with congenital heart disease, in women, and to the importance of training in CT. In addition, we highlight key consensus documents and guidelines published in JCCT last year. The Journal values the tremendous work by authors, reviewers, and editors to accomplish these contributions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: CTA=coronary CT angiography; HRP=high risk plaques; TAVR=Transcatheter aortic valve replacement

The 'Magic of Cardiology' - Achenbach, Stephan (European Heart Journal, 2023)
CRIS-Team Scopus Importer:2023-03-24

The Munich-Transarterial Chemoembolisation Score Holds Superior Prognostic Capacities Compared to TACE-Tailored Modifications of 9 Established Staging Systems for Hepatocellular Carcinoma - Op Den Winkel, Mark; Nagel, Dorothea; Op Den Winkel, Philip; Paprottka, Philipp M.; Schmidt, Laura; Bourhis, Helene; Trojan, Joerg; Göller, Markus; Reiter, Florian P.; Stecher, Stephanie-Susanne; De Toni, Enrico N.; Gerbes, Alexander L.; et al. (Digestion, 2019)
Background/Aims: The recently proposed Munich-transarterial chemoembolisation-score (M-TACE) was tailored to suit hepatocellular Carcinoma (HCC) patients evaluated for TACE. M-TACE outperformed the established HCC-staging-systems and successfully passed external validation. Modifications of staging-systems through the rearrangement of stages or by adding prognostic factors are methods of improving prognostic power. M-TACEs performance compared to scores modified this way should be tested. Methods: Seven well-known HCC staging-systems (including Cancer of the Liver Italian Program-score [CLIP] and Barcelona Clinic liver cancer [BCLC]) and 2 TACE-specific scores (Selection for Transarterial Chemoembolisation Treatment [STATE] and Hepatoma Arterial embolisation Prognostic [HAP]) were rearranged in a cohort of 186 TACE-patients through score-point-analysis and subsequent linking of non-significant adjacent score-points. Additionally, a new score was constructed by combining the top established staging-system in TACE patients (CLIP-TACE) and the prognostic parameter with the highest hazard ratio for death in the TACE-cohort [C-reactive protein (CRP)]. Additionally, the TACE-tailored-scores were applied to an external TACE-cohort (n = 71). Results: Rearrangement resulted in optimal stratification and monotonicity. CLIP-TACE demonstrated the best prognostic capability of all rearranged scores (c-index 0.668, AIC 1294) and the addition of CRP yielded further prognostic improvement (c-index 0.680, AIC 1289). However, superiority over M-TACE could not be achieved by any of the new scores in the internal and external cohort. Conclusion: M-TACE outperforms TACE-tailored modifications of all relevant HCC-staging-systems. Prospective validation of M-TACE to promote its role as the preferred staging-system for TACE-patients is therefore justified.
CRIS-Team WoS Importer:2019-07-19

The Predictive Value of Coronary Artery Calcium Scoring for Major Adverse Cardiac Events According to Renal Function (from the Coronary Computed Tomography Angiography Evaluation for Clinical Outcomes: An International Multicenter [CONFIRM] Registry) - Lee, Ji Hyun; Rizvi, Asim; Hartaigh, Bríain; Han, Donghee; Park, Mahn Won; Roudsari, Hadi Mirhedayati; Stuijfzand, Wijnand J.; Gransar, Heidi; Lu, Yao; Callister, Tracy Q.; Berman, Daniel S.; DeLago, Augustin; et al. (American Journal of Cardiology, 2019)
The prognostic performance of coronary artery calcium score (CACS) for predicting adverse outcomes in patients with decreased renal function remains unclear. We aimed to examine whether CACS improves risk stratification by demonstrating incremental value beyond a traditional risk score according to renal function status. 9,563 individuals without known coronary artery disease were enrolled. Estimated glomerular filtration rate (eGFR, ml/min/1.73 m 2 ) was ascertained using the modified Modification of Diet in Renal Disease formula, and was categorized as: ≥90, 60 to 89, and <60. CACS was categorized as 0, 1 to 100, 101 to 400, and >400. Multivariable Cox regression was used to estimate hazard ratios (HR) with 95% confidence intervals (95% CI) for major adverse cardiac events (MACE), comprising all-cause mortality, myocardial infarction, and late revascularization (>90 days). Mean age was 55.8 ± 11.5 years (52.8% male). In total, 261 (2.7%) patients experienced MACE over a median follow-up of 24.5 months (interquartile range: 16.9 to 41.1). Incident MACE increased with higher CACS across each eGFR category, with the highest rate observed among patients with CACS >400 and eGFR <60 (95.1 per 1,000 person-years). A CACS >400 increased MACE risk with HR 4.46 (95% CI 1.68 to 11.85), 6.63 (95% CI 4.03 to 10.92), and 6.14 (95% CI 2.85 to 13.21) for eGFR ≥90, 60 to 89, and <60, respectively, as compared with CACS 0. Further, CACS improved discrimination and reclassification beyond Framingham 10-year risk score (FRS) (AUC: 0.70 vs 0.64; category free-NRI: 0.51, all p <0.001) for predicting MACE in patients with impaired renal function (eGFR < 90). In conclusion, CACS improved risk stratification and provided incremental value beyond FRS for predicting MACE, irrespective of eGFR status.
CRIS-Team Scopus Importer:2019-05-02

The proinflammatory effect of C-reactive protein on human endothelial cells depends on the Fc?RIIa genotype - Raaz-Schrauder, Dorette; Ekici, Arif Bülent; Klinghammer, Lutz; Stumpf, Christian; Achenbach, Stephan; Herrmann, Martin; Reis, André; Garlichs, Christoph (Thrombosis Research, 2014)
The stimulatory effects of CRP (C-reactive protein) on endothelial cells are mainly mediated via Fc?RIIa. This receptor exists in two different allotypes bearing either arginine (R131) or histidine (H131) at the extracellular amino acid position 131 of the mature protein, but only Fc?RIIa-R131 displays high avidity for CRP. This study investigated the role of the Fc?RIIa genotype in CRP-stimulated endothelial cells.We tested the effects of CRP on expression of the adhesion molecules ICAM-1, VCAM-1, and E-selectin, as well as the endothelial release of pro-inflammatory molecules as a function of the Fc?RIIa-genotype (Fc?RIIa-H/H131, Fc?RIIa-H/R131, Fc?RIIa-R/R131) in HUVEC (Human Umbilical Vein Endothelial Cells). HUVEC were grouped according to their Fc?RIIa status by genotyping with an allele specific nested-PCR. The expression of ICAM-1, VCAM-1, and E-selectin on HUVEC was detected by flow cytometry. The release of soluble markers (sCD40L, IL-6, IL-8, MCP-1, tPA, sP-selectin, and sVCAM-1) was measured using a multiplex assay for flow cytometry.CRP-stimulated expression of ICAM-1 and E-selectin was dependent on the specific Fc?RIIa-genotype, with most pronounced induction in HUVEC with the Fc?RIIa-R/R genotype, followed by H/R and H/H. In accordance with this finding, the supernatants of stimulated HUVEC with the R/R genotype showed significantly higher levels of tPA, MCP-1, and IL-6. Our data show that CRP stimulates the expression of adhesion molecules and the release of soluble markers by HUVEC as a function of the Fc?RIIa-genotype. These findings could be relevant in the context of risk stratification in patients with cardiovascular disease.
EVALuna2:9209

THERAPEUTIC IMPACT OF FILARIAL ANTIGEN OF LITOMOSOIDES SIGMODONTIS ON ADVANCED ATHEROSCLEROSIS IN APOE-KNOCKOUT MICE, BASED ON T CELL DIFFERENTIATION - Kühn, Constanze; Tauchi, Miyuki; Hoerauf, Achim; Stumpf, Christian; Achenbach, Stephan; Huebner, Marc; Dietel, Barbara (2017)
EVALuna2:33624

The ratio of coronary arterial lumen volume to left ventricle mass identifies patients with nonobstructive coronary artery disease having vessel-specific ischemia measured by fractional flow reserve - Taylor, C.; Gaur, S.; Khem, S.; Kim, H. J.; Wilk, A.; Zarins, C. K.; Achenbach, Stephan; Bezerra, H.; Nishino, S.; Jensen, J. M.; Leipsic, J.; Botker, H. E.; et al. (2016)
EVALuna2:33686

The relation of aortic dimensions and obesity in adults with Marfan or Loeys-Dietz syndrome - Suleiman, Mathieu; Freilinger, Sebastian; Meierhofer, Christian; May, Matthias; Bischoff, Gert; Ewert, Peter; Freiberger, Annika; Huntgeburth, Michael; Kaemmerer, Ann-Sophie; Marwan, Mohamed; Nagdyman, Nicole; Roth, Jan-Peter; et al. (Cardiovascular Diagnosis and Therapy, 2022)
Background: Aortic aneurysm and aortic dissection can have a major impact on the life expectancy of Marfan syndrome (MFS) or Loeys-Dietz syndrome (LDS) patients. Although obesity can influence the development of aortic complications, evidence on whether obesity influences the development of aortic aneurysm or dissection in MFS and LDS is limited. The aim of the present study was to elucidate the relationship between aortic size and body composition, assessed by modern bioelectrical impedance analysis (BIA) in MFS/LDS-patients.Methods: In this exploratory cross-sectional study in MFS or LDS patients, enrolled between June 2020 and May 2022, 34 patients received modern BIA and magnetic resonance imaging (MRI) (n=32) or computed tomography (CT) imaging (n=2) of the entire aorta. A P value of <0.05 was considered significant.Results: Fifty-one patients (66% female; mean age: 37.7 +/- 11.7; range, 17-68 years) with MFS or LDS were enrolled; 34 patients, 27 with MFS and 7 with LDS, underwent aortic MRI or CT scanning. The mean aortic length was 503.7 +/- 58.7 mm, and the mean thoracic aortic length and abdominal aortic length were 351.5 +/- 52.4 and 152.2 +/- 27.4 mm, respectively. The aortic bulb and the ascending aorta were measured only in the non-surgically repaired patients. Fifteen MFS (88.2%) and two LDS (40.0%) patients had an aortic aneurysm. In these, the aortic bulb tended to be larger in MFS than in LDS patients [42.6x41.9x41.2 vs. 37.8x37.4x36.8 mm; P=0.07 (-1.1; 9.1); P=0.07 (-1.2; 8.4); P=0.07 (-1.5; 7.9)]. BIA revealed mean body fat levels of 31.6%+/- 8.7% (range, 9.5-53.5%), indicating that 18 patients (52.9%) were obese. There was a significant correlation between body fat content and thoracic aortic length (R=-0.377; P=0.02), muscle mass and total aortic length (R=0.359; P=0.03), thoracic aortic length (R=0.399; P=0.02), extracellular mass (ECM), and total aortic length (R=0.354; P=0.04) , connective tissue and aortic diameters at the aortic arch (R=0.511; P=0.002), aortic isthmus (R=0.565; P<0.001), and abdominal aorta (R=0.486; P=0.004). Older age was correlated with wider aortic arch, isthmus, and abdominal aorta. Male patients had a longer aorta.Conclusions: While a slender habitus is commonly known for MFS and LDS patients, our data show that many MFS and LDS patients (especially female) do not fit this phenotypic characteristic and are obese, which is associated with a more severe aortic phenotype. This topic should be included in the clinical assessment of affected MFS and LDS patients, in addition to measurement of the aortic diameters. Physicians should systematically screen MFS and LDS patients for obesity, educate them about the potential risk of resulting aortic complications, and encourage them to adopt a healthy lifestyle, that includes (mild) exercise and a balanced diet.
CRIS-Team WoS Importer:2023-02-03
Keywords: Adults with connective tissue disease; Marfan syndrome (MFS); Loeys-Dietz syndrome (LDS); body composition; obesity

The relevance of accuracy of heartbeat perception in noncardiac and cardiac chest pain - Schroeder, Stefanie; Gerlach, Alexander L.; Achenbach, Stephan; Martin, Alexandra (International Journal of Behavioral Medicine, 2015)
The development and course of noncardiac chest pain are assumed to be influenced by interoceptive processes.It was investigated whether heartbeat perception was enhanced in patients suffering from noncardiac chest pain and to what degree it was associated with self-reported cognitive-perceptual features and chest pain characteristics.A total of 42 patients with noncardiac chest pain (NCCP), 35 patients with cardiac chest pain, and 52 healthy controls were recruited. Heartbeat perception was assessed using the Schandry task and a modified Brener-Kluvitse task. Self-report measures assessed anxiety sensitivity, somatosensory amplification, heart-focused anxiety, and chest pain characteristics.Heartbeat perception was not more accurate in patients with NCCP, compared to patients with cardiac chest pain and healthy controls. However, in patients with NCCP, the error score (Schandry task) was significantly associated with stronger chest pain impairment, and the response bias (Brener-Kluvitse task) was associated with lower chest pain intensity.Against assumptions of current etiological models, heartbeat perception was not enhanced in patients with NCCP. Chest pain characteristics and particularly their appraisal as threatening might be more relevant to NCCP than the perceptional accuracy of cardiac sensations and should be focused in psychological interventions. However, associations with chest pain impairment suggest cardiac interoception to influence the course of NCCP.
EVALuna2:12123

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

The Shear Stress–Regulated Expression of Glypican-4 in Endothelial Dysfunction In Vitro and Its Clinical Significance in Atherosclerosis - Urschel, Katharina; Hug, Karsten; Zuo, Hanxiao; Büttner, Michael; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balaz; Achenbach, Stephan; Yuan, Yan; Dietel-Schor, Barbara; Tauchi-Brück, Miyuki (International Journal of Molecular Sciences, 2023)
Retention of circulating lipoproteins by their interaction with extracellular matrix molecules has been suggested as an underlying mechanism for atherosclerosis. We investigated the role of glypican-4 (GPC4), a heparan sulfate (HS) proteoglycan, in the development of endothelial dysfunction and plaque progression; Expression of GPC4 and HS was investigated in human umbilical vein/artery endothelial cells (HUVECs/HUAECs) using flow cytometry, qPCR, and immunofluorescent staining. Leukocyte adhesion was determined in HUVECs in bifurcation chamber slides under dynamic flow. The association between the degree of inflammation and GPC4, HS, and syndecan-4 expressions was analyzed in human carotid plaques; GPC4 was expressed in HUVECs/HUAECs. In HUVECs, GPC4 protein expression was higher in laminar than in non-uniform shear stress regions after a 1-day or 10-day flow (p < 0.01 each). The HS expression was higher under laminar flow after a 1 day (p < 0.001). Monocytic THP-1 cell adhesion to HUVECs was facilitated by GPC4 knock-down (p < 0.001) without affecting adhesion molecule expression. GPC4 and HS expression was lower in more-inflamed than in less-inflamed plaque shoulders (p < 0.05, each), especially in vulnerable plaque sections; Reduced expression of GPC4 was associated with atherogenic conditions, suggesting the involvement of GPC4 in both early and advanced stages of atherosclerosis.
CRIS-Team Scopus Importer:2023-08-11
Keywords: atherosclerosis; endothelial dysfunction; glypican-4; heparan sulfate; plaque; sex differences; shear stress

The Tobacco Endgame-Eradicating a Worsening Epidemic: A Joint Opinion From the American Heart Association, World Heart Federation, American College of Cardiology, and the European Society of Cardiology. - Willett, Jeffrey; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena; Elkind, Mitchell S. V. (Circulation, 2021)
EVALuna2:482708

The Tobacco Endgame: Eradicating a Worsening Epidemic A Joint Opinion From the American Heart Association, World Heart Federation, American College of Cardiology, and the European Society of Cardiology - Willett, Jeffrey; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena; Elkind, Mitchell S.V. (Journal of the American College of Cardiology, 2021)
CRIS-Team Scopus Importer:2021-06-18

The tobacco endgame—eradicating a worsening epidemic - Willett, Jeffrey; Achenbach, Stephan; Pinto, Fausto J.; Poppas, Athena; Elkind, Mitchell S.V. (Global Heart, 2021)
CRIS-Team Scopus Importer:2021-06-25
Keywords: Cardiology; Tobacco

The Utility of the SYNTAX Score II and SYNTAX Score 2020 for Identifying Patients with Three-Vessel Disease Eligible for Percutaneous Coronary Intervention in the Multivessel TALENT Trial: A Prospective Pilot Experience - Ninomiya, Kai; Serruys, Patrick W.; Garg, Scot; Hara, Hironori; Masuda, Shinichiro; Kageyama, Shigetaka; Kotoku, Nozomi; Sevestre, Emelyne; Kumar, Abhishek; O'Kane, Peter; Zaman, Azfar; Farah, Bruno; et al. (Reviews in Cardiovascular Medicine, 2022)
Background: Personalized prognosis plays a vital role in deciding between percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in patients with three-vessel disease (3VD). The aim of this study is to compare the modality of revascularization chosen by the local heart team to that recommended by using individualized predictions of medium, and long-term all-cause mortality amongst patients with 3VD screened in the Multivessel TALENT trial. Methods: The SYNTAX score II (SS-II) and SS-2020 were evaluated in 200 consecutive patients by a core laboratory and compared to the decision of the "on site" heart team. Results: According to the SS-II, CABG was the recommended treatment in 51 patients (25.5%) however 34 (66.6%) of them received PCI. According to SS-2020 the predicted absolute risk differences (ARD) between PCI and CABG were significantly higher in patients receiving CABG compared to those treated by PCI for major adverse cardiovascular and cerebrovascular events, a composite of all-cause mortality, stroke or myocardial infarction at 5-years (8.8 +/- 4.6% vs 6.0 +/- 4.0%, p < 0.001) and all-cause mortality at 5- (5.2 +/- 3.5% vs 3.7 +/- 3.0%, p = 0.008) and 10-years (9.3 +/- 4.8% vs 6.2 +/- 4.2%, p < 0.001). Based on the novel threshold of equipoise (individual absolute risk differences [ARD]<4.5%), 133 patients were eligible for PCI however 23 of them underwent CABG; conversely, amongst the 67 patients where CABG was recommendation (individual ARD>4.5%), only 19 received it. Conclusions: Despite the robustness of the risk models proposed for screening, several deviations from the recommended mode of revascularization were observed by the core laboratory among the first 200 patients with 3VD screened in the Multivessel TALENT trial. Clinical Trial Registration: ClinicalTrials.gov reference: NCT04390672.
CRIS-Team WoS Importer:2022-06-03

The WISE-CRT System Leads to Left Ventricular Remodeling and Improved Symptoms in Patients Who are Non-Responders to Epicardial CRT - Sidhu, Baldeep S.; Gould, Justin; Porter, Badley; Turley, Andrew; Diemberger, Igor; Biffi, Mauro; Seifert, Martin; Butter, Christian; Boersma, Lucas V. A.; Riahi, Sam; Neuzil, Petr; Vergara, Pasquale; et al. (JOURNAL OF CARDIAC FAILURE, 2019)
CRIS-Team WoS Importer:2019-09-13

The WiSE-CRT System Results in Left Ventricular Remodelling and Improved Symptoms in Patients Undergoing CRT Upgrades - Sidhu, Baldeep S.; Gould, Justin; Porter, Bradley; Diemberger, Igor; Biffi, Mauro; Seifert, Martin; Butter, Christian; Boersman, Lucas V. A.; Riahi, Sam; Neuzi, Petr; Vergara, Pasquale; Defaye, Pascal; et al. (JOURNAL OF CARDIAC FAILURE, 2019)
CRIS-Team WoS Importer:2019-09-13

The year in cardiology 2017: imaging - Delgado, Victoria; Knuuti, Juhani; Plein, Sven; Achenbach, Stephan; Bax, Jeroen J. (European Heart Journal, 2018)
EVALuna2:33586

The Year in Cardiology 2018: imaging - Delgado, Victoria; Popescu, Bogdan A.; Plein, Sven; Achenbach, Stephan; Knuuti, Juhani; Bax, Jeroen J. (European Heart Journal, 2019)
EVALuna2:213024

Three-Dimensional Rotational Angiography during Catheterization of Congenital Heart Disease – A ten Years’ experience at a single center - Söder, Stephan; Wällisch, Wolfgang; Dittrich, Sven; Cesnjevar, Robert; Pfammatter, Jean Pierre; Glöckler, Martin (Scientific Reports, 2020)
This paper aims to assess the usability and advantages of three-dimensional rotational angiography (3DRA) in patients with congenital heart disease (CHD) and its application in the cath lab. Up to now, its use in CHD is not widespread or standardized. We analyzed all patients with CHD who underwent a 3DRA at our facility between January 2010 and May 2019. The 3DRAs were evaluated for radiation exposure, contrast dye consumption, diagnostic utility and image quality. We performed 872 3DRAs. 3DRA was used in 67.1% of the cases for interventional procedures and in 32.9% for diagnostic purposes. Two different acquisition programs were applied. The median dose-area product (DAP) for all 872 rotations was 54.1 µGym2 (21.7–147.5 µGym2) and 1.6 ml/kg (0.9–2.07 ml/kg) of contrast dye was used. Diagnostic utility of the generated 3D-model was rated superior to the native 3D angiography in 94% (819/872). 3DRA is an excellent and save diagnostic and interventional tool. However, 3DRA has not become a standard imaging procedure in pediatric cardiology up to now. Effort and advantage seems to be unbalanced, but new less invasive techniques may upgrade this method in future.
CRIS-Team Scopus Importer:2020-05-05

Timing of Complete Revascularization with Multivessel PCI for Myocardial Infarction. - Stähli, Barbara E.; Varbella, Ferdinando; Linke, Axel; Schwarz, Bettina; Felix, Stephan B.; Seiffert, Moritz; Kesterke, Rahel; Nordbeck, Peter; Witzenbichler, Bernhard; Lang, Irene M.; Kessler, Mirjam; Valina, Christian; et al. (New England Journal of Medicine, 2023)
Background In patients with ST-segment elevation myocardial infarction (STEMI) with multivessel coronary artery disease, the time at which complete revascularization of nonculprit lesions should be performed remains unknown. Methods We performed an international, open-label, randomized, noninferiority trial at 37 sites in Europe. Patients in a hemodynamically stable condition who had STEMI and multivessel coronary artery disease were randomly assigned to undergo immediate multivessel percutaneous coronary intervention (PCI; immediate group) or PCI of the culprit lesion followed by staged multivessel PCI of nonculprit lesions within 19 to 45 days after the index procedure (staged group). The primary end point was a composite of death from any cause, nonfatal myocardial infarction, stroke, unplanned ischemia-driven revascularization, or hospitalization for heart failure at 1 year after randomization. The percentages of patients with a primary or secondary end-point event are provided as Kaplan-Meier estimates at 6 months and at 1 year. Results We assigned 418 patients to undergo immediate multivessel PCI and 422 to undergo staged multivessel PCI. A primary end-point event occurred in 35 patients (8.5%) in the immediate group as compared with 68 patients (16.3%) in the staged group (risk ratio, 0.52; 95% confidence interval, 0.38 to 0.72; P<0.001 for noninferiority and P<0.001 for superiority). Nonfatal myocardial infarction and unplanned ischemia-driven revascularization occurred in 8 patients (2.0%) and 17 patients (4.1%), respectively, in the immediate group and in 22 patients (5.3%) and 39 patients (9.3%), respectively, in the staged group. The risk of death from any cause, the risk of stroke, and the risk of hospitalization for heart failure appeared to be similar in the two groups. A total of 104 patients in the immediate group and 145 patients in the staged group had a serious adverse event. Conclusions Among patients in hemodynamically stable condition with STEMI and multivessel coronary artery disease, immediate multivessel PCI was noninferior to staged multivessel PCI with respect to the risk of death from any cause, nonfatal myocardial infarction, stroke, unplanned ischemia-driven revascularization, or hospitalization for heart failure at 1 year. (Supported by Boston Scientific; MULTISTARS AMI ClinicalTrials.gov number, NCT03135275.)
CRIS-Team Scopus Importer:2023-12-08
Keywords: Cardiology; Cardiology General; Coronary Disease/Myocardial Infarction

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, D.; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in hypertension and related organ damage - Kolwelter, Julie; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2020)
Most textbooks state that sodium (Na) accumulation goes hand in hand with fluid retention to maintain the environmental isotonicity. In the last century, several studies found, however, that Na is stored in the extravascular space leading to an activation of the monocyte phagocytic system cells that work as a regulator of the interstitial electrolyte homeostasis. Na-23-MRI was developed to quantify noninvasively, accurately and reliably tissue Na content. In this review, we give an up-to-date overview of clinical studies utilizing this Na-23-MRI technique to elucidate the importance of tissue Na content in patients with cardiovascular risk factors leading to microvascular and macrovascular complications. Na storage leads ultimately to organ damage such as left ventricular hypertrophy or hypertrophic vascular remodeling of resistance vessels. Elevated Na content in muscle and skin has been detected in patients with treatment resistant hypertension, type 2 diabetes mellitus, acute and chronic heart failure, chronic kidney disease and end-stage renal failure. Pharmacological interventions have shown that a mobilization of extracellular accumulated Na is possible and may emerge as a new therapeutic approach in some diseases.
CRIS-Team WoS Importer:2021-01-01

Torsional Heart Motion in Cone-beam Computed Tomography Reconstruction - Unberath, Mathias; Mentl, Katrin; Taubmann, Oliver; Achenbach, Stephan; Fahrig, Rebecca; Hornegger, Joachim; Maier, Andreas (Proceedings of the Fully3D, 2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.IMMD.IMMD5.torsio_3

Towards a FHIR-Based Data Model for Coronary Angiography Observations - Holweg, Florian; Achenbach, Stephan; Deppenwiese, Noemi; Gaede, Luise; Prokosch, Hans-Ulrich (Healthcare of the Future 2022, 2022)
Coronary heart disease is among the most frequent causes of death globally. Thus, our research project aims to develop prognostic models, to predict the risk of spontaneous myocardial infarctions based on a combination of clinical parameters and image data sets (invasive coronary angiograms). To train such models we use data from more than 30,000 coronary angiograms acquired at the cardiology department of Erlangen University Hospital. To linking such proprietary data with additional clinical parameters and to harmonize it for future cross-hospital federated machine learning approaches we defined a mapping for coronary angiography based on the symptom/ clinical phenotype HL7® FHIR® module of the German medical informatics initiative. In this paper we describe the final design of the coronary angiography information model and our mapping approach to ICD-10 and SNOMED CT. From the database we use a subset of 15 required values patient characteristics to create the HL7® FHIR® resource.
CRIS-Team Scopus Importer:2022-05-27
Keywords: coronary angiography; data model; HL7 FHIR; SNOMED CT

Toxicity of Mitoxantrone-loaded Superparamagnetic Iron Oxide Nanoparticles in a HT-29 Tumour Spheroid Model - Hornung, Annkathrin; Poettler, Marina; Friedrich, Ralf P.; Weigel, Bianca; Dürr, Stephan; Zaloga, Jan; Cicha, Iwona; Alexiou, Christoph; Janko, Christina (Anticancer Research, 2016)
Cancer research is commonly carried out in two-dimensional (2D) cell cultures, which poorly reflect in vivo settings where the growing tumours are exposed to mechanical forces and biochemical gradients. In this study we established a HF-29 colon carcinoma tumor spheroid model to investigate the effect of free mitoxantrone (MTO) and its nanoparticle-bound form (SPION(MTO)) under 3D cell culture conditions.Tumour spheroids were generated by seeding HT-29 colon carcinoma cells on agarose-coated cell culture wells. Growth of the spheroids was monitored daily by transmission microscopy upon treatment with free MTO, SPION(MTO) or unloaded SPION.Unloaded SPION did not affect the spheroid size compared to untreated controls, while both free MTO and SPION(MTO) inhibited growth of the spheroids in a dose- and time-dependent manner. In comparison to free MTO, the effect of SPION(MTO) on spheroid growth was slightly delayed. Further analyses are necessary to investigate if MTO infiltrates spheroids in its nanoparticle-bound form or whether it is released from SPION before infiltration.
EVALuna2:20010

Transarterial chemoembolization for hepatocellular carcinoma: development and external validation of the Munich-TACE score - Op Den Winkel, Mark; Nagel, Dorothea; Op Den Winkel, Philip; Trojan, Joerg; Paprottka, Philipp M.; Steib, Christian J.; Schmidt, Laura; Göller, Markus; Stieber, Petra; Goehring, Peter; Herbst, Andreas; Rentsch, Markus; et al. (European Journal of Gastroenterology & Hepatology, 2018)
BACKGROUND: Allocation of patients with hepatocellular carcinoma (HCC) to the adequate therapy is determined by both tumor burden and liver function. The Barcelona Clinic Liver Cancer (BCLC) staging system and therapeutic algorithm recommends transarterial chemoembolization (TACE) based on the best evidence available to patients with intermediate-stage HCC (BCLC-B). However, many centers also treat subgroups of patients outside these recommendations and with more advanced disease by TACE. The purpose of this study was to identify prognostic factors in a TACE cohort, including BCLC-B patients, as well as patients treated outside of BCLC-B, to test the prognostic capabilities of published staging systems and to optimize prognostication for TACE patients. PATIENTS AND METHODS: A cohort of 186 first-line TACE patients was analyzed. Independent prognostic factors were identified and used to construct the Munich-TACE score (M-TACE). M-TACE was tested against established staging systems (including BCLC and two recently published TACE-specific scores) and a ranking using concordance index and Akaike Information Criterion was performed. Finally, an external validation in an independent TACE cohort (n=71) was conducted. RESULTS: Bilirubin, Quick/international normalized ratio, C-reactive protein, creatinine, α-feto protein, and tumor extension were identified as independent prognostic factors and used to construct M-TACE. M-TACE identifies three distinct subgroups (P<0.0001) with median survival times of 35.2, 16.9, and 8.6 months, respectively. Compared with established staging systems, M-TACE showed the best prognostic capabilities in both cohorts of patients (cohort 1: c-index, 0.71; Akaike Information Criterion: 1276; cohort 2: c-index, 0.754). CONCLUSION: We identified independent risk factors for patients treated with TACE. The newly constructed M-TACE score is superior to established staging systems and might prove helpful to identify patients who are most suitable for TACE.
EVALuna2:36012

Transcatheter Aortic Valve Replacement for Isolated Aortic Regurgitation Using a New Self-Expanding TAVR System - Adam, Matti; Tamm, Alexander; Wienemann, Hendrik; Unbehaun, Axel; Klein, Christoph; Arnold, Martin; Marwan, Mohamed; Theiss, Hans; Braun, Daniel; Bleiziffer, Sabine; Geyer, Martin; Goncharov, Arseniy; et al. (Jacc-Cardiovascular Interventions, 2023)
Background: Patients with severe aortic regurgitation (AR) are often not considered for surgery because of increased surgical risk. Because of unique anatomical characteristics among patients with AR, interventional treatment options are limited, and implantation results are inconsistent compared with those among patients with aortic stenosis. Objectives: The authors describe the initial commercial experience of the first Conformité Européenne–marked transfemoral transcatheter aortic valve replacement system (JenaValve Trilogy [JV]) for the treatment of patients with AR. Methods: This multicenter registry included 58 consecutive patients from 6 centers across Germany. Transcatheter aortic valve replacement was performed with the JV system for isolated severe and symptomatic AR. Patient characteristics, primary implantation outcomes, and valve performance up to 30 days were analyzed using Valve Academic Research Consortium 3 definitions. Results: The mean patient age was 76.5 ± 9 years, with a mean Society of Thoracic Surgeons score of 4.2% ± 4.3%. Device success was achieved in 98% of patients. The mean gradient was 4.3 ± 1.6 mm Hg, and no moderate or severe paravalvular regurgitation occurred. No conversion to open heart surgery or valve embolization was reported. There were no major vascular complications or bleeding events. The rate of new permanent pacemaker implantation was 19.6%. At 30 days, 92% of the patients were in NYHA functional class I or II, and the 30-day mortality rate was 1.7%. Conclusions: Treatment of patients with severe symptomatic AR using the transfemoral JV system is safe and effective. Given its favorable hemodynamic performance and low complication rates, this system may offer a new treatment option for patients with AR not suitable for surgery.
CRIS-Team Scopus Importer:2023-09-01
Keywords: aortic regurgitation; JenaValve; paravalvular regurgitation; TAVR

Transcatheter-based aortic valve replacement vs. isolated surgical aortic valve replacement in 2020 - Gaede, Luise; Blumenstein, Johannes; Eckel, Clemens; Grothusen, Christina; Tiyerili, Vedat; Soetemann, Dagmar; Nef, Holger; Elsaesser, Albrecht; Achenbach, Stephan; Moellmann, Helge (Clinical Research in Cardiology, 2022)
Background: Based on the results of several recent randomized trials, European and American guidelines on valvular heart disease management have substantially expanded the indications for transcatheter aortic valve implantation (TAVI). We present an all-comer data on peri-operative risk profile and in-hospital outcomes from Germany for patients treated by TAVI or isolated surgical aortic valve replacement (iSAVR) in 2020, providing an opportunity to compare study data with data from daily clinical practice. Methods: Data concerning all isolated aortic valve procedures performed in Germany in 2020 were retrieved from the mandatory nationwide quality control program. Expected mortality was calculated with the annually revised German Aortic valve score (AKL-score) based on the data of either catheter-based (AKL-CATH) or isolated surgical (AKL-CHIR) aortic valve replacement in Germany from the previous year (2019). Results: In 2020 21,903 TAVI procedures (20,810 transvascular (TV; vs. 2019: 22.973; − 9.4%), 1093 transapical (TA; vs. 2019: 1413; − 22.6%)) and 6144 (vs. 2019 7905; − 22.5%) iSAVR were performed in Germany. Patients who received TAVI showed a significantly higher perioperative risk profile than patients undergoing iSAVR based on older age and more severe co-morbidities. While in-hospital mortality after TAVI (2.3%) was numerically lower than in 2019 (2.5%), this difference was not significant (p = 0.11). In-hospital mortality after iSAVR was identical in 2020 and 2019 (2.8%) and thus higher than after TAVI (p = 0.003), resulting in an observed expected mortality ratio of 1.02 after TAVI and 1.05 after iSAVR. After exclusion of the emergency procedures, in-hospital mortality did not differ significantly between the groups (TAVI 2.2% vs. iSAVR 1.9%, p = 0.26). Conclusion: Total numbers of both iSAVR and TAVI in Germany were lower in 2020 than in 2019, most likely due to the COVID-19 pandemic. However, the relative number of patients treated by TAVI as compared to iSAVR continues to increase. Despite older age and more severe comorbidities compared to patients undergoing iSAVR the in-hospital mortality after TAVI continued to decrease in 2020 and remains significantly lower than after iSAVR. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-04-15
Keywords: Aortic valve replacement; Real world; Registry; TAVI; TAVR

Transcatheter closure of ruptured sinus of Valsalva aneurysm into the right ventricle with an Amplatzer Vascular Plug II - Rittger, Harald; Gundlach, Ulrike; Koch, Andreas (Catheterization and Cardiovascular Interventions, 2015)
We report a case of a 52-year-old female patient with perforated sinus of Valsalva (SVA) aneurysm presenting with severe left-to-right shunt from the aorta into the right ventricle.Aneuryms of the aortic sinus, better known as SVA are rare. Until interventional devices were introduced, the only treatment option for ruptured SVA aneurysms was surgery.The case was discussed in the heart team and decision was made to implant an Amplatzer Vascular Plug (AVP) II. Initially, closing attempts using AVP 16 mm and 14 mm devices were performed. Presumably as a consequence of inadequate sizing, the discs were not well formed in the connecting tunnel, leaving a severe rest shunt after both procedures. Finally, after implantation of a 12 mm AVP-device, only a minimal rest shunt remained detectable. Absence of aortic regurgitation was confirmed by transesophageal echocardiography, and the occluder was released. Mean pulmonary artery pressure immediately decreased from 39 to 15 mm Hg. Medication with aspirin (100 mg qid) and clopidogrel (75 mg qid) was initiated. Follow-up examinations at 4 weeks and 3 months confirmed the minimal rest shunt and a continuous decrease of systolic pulmonary artery pressure to 35 mm Hg, as assessed with transthoracal echocardiography.In conclusion, in cases of SVA rupture, closure with an AVP II represents an alternative to surgical treatment and other devices used for transcatheter treatment of SVA. © 2014 Wiley Periodicals, Inc.
EVALuna2:12010

Transcatheter Treatment of Secondary Tricuspid Regurgitation with Direct Annuloplasty: Results from a Multicenter Real-World Experience - Körber, Maria I.; Landendinger, Melanie; Gerçek, Muhammed; Beuthner, Bo E.; Friedrichs, Kai P.; Puls, Miriam; Baldus, Stephan; Rudolph, Volker; Jacobshagen, Claudius; Pfister, Roman; Arnold, Martin (Circulation: Cardiovascular Interventions, 2021)
Background: Treatment options for secondary tricuspid regurgitation (TR) remain limited. Early real-world data of a new percutaneous direct annuloplasty system for tricuspid repair were examined. Methods: The first 60 patients treated with the Cardioband tricuspid valve repair system at 4 centers were included in this retrospective study. The primary efficacy end point was technical success with reduction of TR ≥2 grades at discharge. Combined primary safety end point was major adverse events (death, myocardial infarction, cardiothoracic surgery, and stroke) at 30 days. Results: Median patient age was 76 years (73-82), median EuroScore II was 3.9% (2.2-8.1), heart failure with preserved ejection fraction was present in 78%, and 81.7% were in the New York Heart Association class III/IV. Massive or torrential TR was found in 51.7%, and severe TR in 48.3%. The primary efficacy end point was achieved in 45%, while 60.3% of patients had less-than-severe TR at discharge. Vena contracta was reduced by 47% from 12.9±4.8 to 7.0±3.4 mm (P<0.001). Overall, the majority of patients (81.7%) improved at least by 1 New York Heart Association class. At follow-up 81.3% of patients presented in the New York Heart Association class I or II. The primary safety end point occurred in 4 patients with 2 in-hospital deaths, both not device related. Right coronary artery complications (vessel perforation or stent implantation) occurred in 9 patients (15%). Procedural time decreased from 298 to 185 minutes (P<0.001) with efficacy remaining stable (P=0.817) when comparing procedure numbers 11 or more to the earliest 5 procedures per center. Conclusions: This first real-world experience suggests that transcatheter treatment of advanced secondary TR using direct annuloplasty is feasible and reasonably safe early in the learning curve, with significant symptomatic benefit. Further studies are warranted to provide data on long-term outcome and patient prognosis.
CRIS-Team Scopus Importer:2021-08-27
Keywords: follow-up studies; learning curve; mitral valve; prognosis; tricuspid valve insufficiency

Transesophageal demonstration of a coronary fistula with associated infective endocarditis Transosophageale darstellung einer koronarfistel bei gleichzeitiger endocarditis lenta - Klinghammer, Lutz; et al. (Z KARDIOL, 1999)
Keywords: Endocarditis; Coronary fistula; Transesophageal echocardiography

Transient acute right coronary artery deformation during transcatheter interventional tricuspid repair with the Cardioband tricuspid system - Gercek, Muhammed; Rudolph, Volker; Arnold, Martin; Beuthner, Bo Eric; Pfister, Roman; Landendinger, Melanie; Koerber, Maria Isabel; Friedrichs, Kai P.; Jacobshagen, Claudius (EuroIntervention, 2021)
Background: The Cardioband tricuspid valve reconstruction system is a size-adjustable tricuspid reconstruction device for interventional treatment of tricuspid regurgitation (TR). Contraction of the device after successful implantation can be associated with an acute deformation of the right coronary artery (RCA).
CRIS-Team WoS Importer:2021-06-04

Transradial approach for coronary angioplasty in the setting of acute myocardial infarction: A dual-center registry - Klinghammer, Lutz; et al. (Catheterization and Cardiovascular Interventions, 2002)
Keywords: Abciximab; Radial artery; Rescue angioplasty; Acute myocardial infarction; Primary angioplasty; Thrombolysis

Transtracheal single-point stent fixation in posttracheotomy tracheomalacia under cone-beam computer tomography guidance by transmural suturing with the Berci needle - a perspective on a new tool to avoid stent migration of Dumon stents - Hohenforst-Schmidt, Wolfgang; Linsmeier, Bernd; Zarogoulidis, Paul; Freitag, Lutz; Darwiche, Kaid; Browning, Robert; Turner, J. Francis; Huang, Haidong; Li, Qiang; Vogl, Thomas; Zarogoulidis, Konstantinos; Brachmann, Johannes; et al. (Therapeutics and Clinical Risk Management, 2015)
Tracheomalacia or tracheobronchomalacia (TM or TBM) is a common problem especially for elderly patients often unfit for surgical techniques. Several surgical or minimally invasive techniques have already been described. Stenting is one option but in general long-time stenting is accompanied by a high complication rate. Stent removal is more difficult in case of self-expandable nitinol stents or metallic stents in general in comparison to silicone stents. The main disadvantage of silicone stents in comparison to uncovered metallic stents is migration and plugging. We compared the operation time and in particular the duration of a sufficient Dumon stent fixation with different techniques in a patient with severe posttracheotomy TM and strongly reduced mobility of the vocal cords due to Parkinson's disease. The combined approach with simultaneous Dumon stenting and endoluminal transtracheal externalized suture under cone-beam computer tomography guidance with the Berci needle was by far the fastest approach compared to a (not performed) surgical intervention, or even purely endoluminal suturing through the rigid bronchoscope. The duration of the endoluminal transtracheal externalized suture was between 5 minutes and 9 minutes with the Berci needle; the pure endoluminal approach needed 51 minutes. The alternative of tracheobronchoplasty was refused by the patient. In general, 180 minutes for this surgical approach is calculated. The costs of the different approaches are supposed to vary widely due to the fact that in Germany 1 minute in an operation room costs on average approximately 50-60EUR inclusive of taxes. In our own hospital (tertiary level), it is nearly 30EUR per minute in an operation room for a surgical approach. Calculating an additional 15 minutes for patient preparation and transfer to wake-up room, therefore a total duration inside the investigation room of 30 minutes, the cost per flexible bronchoscopy is per minute on average less than 6EUR. Although the Dumon stenting requires a set-up with more expensive anesthesiology accompaniment, which takes longer than a flexible investigation estimated at 1 hour in an operation room, still without calculation of the costs of the materials and specialized staff that the surgical approach would consume at least 3,000EUR more than a minimally invasive approach performed with the Berci needle. This difference is due to the longer time of the surgical intervention which is calculated at approximately 180 minutes in comparison to the achieved non-surgical approach of 60 minutes in the operation suite.
EVALuna2:12091

Transvascular transcatheter aortic valve implantation in 2017 - Gaede, Luise; Blumenstein, Johannes; Liebetrau, Christoph; Dörr, Oliver; Kim, Won Keun; Nef, Holger; Husser, Oliver; Gülker, Jan; Elsässer, Albrecht; Hamm, Christian W.; Achenbach, Stephan; Möllmann, Helge (Clinical Research in Cardiology, 2019)
Background: Transcatheter aortic valve implantation (TAVI) is emerging as the standard of care for patients with severe aortic stenosis. Recent results have been favourable even for patients with low periprocedural risk. Methods: We analysed the number of procedures, complications, and in-hospital mortality rates of all patients undergoing isolated aortic valve replacement in 2017 in Germany, focussing especially on transvascular (TV) TAVI. Patients were stratified according the German Aortic Valve Score (AKL) into the risk classes low, intermediate, high and very high (≥ 10%). Results: A total of 17,956 TV-TAVI and 9011 isolated surgical aortic valve replacements (iSAVR) were performed in Germany in 2017. Although the total rate of intraprocedural complications after TV-TAVI was the same as in 2016 (both 7.4%), fewer patients experienced an arterial vascular complication in 2017 (2017: 6.0%; 2016: 7.1%; p < 0.001). Likewise, the rate of new pacemaker implantation decreased (2017: 9.6%; 2016:11.4%; p < 0.001). In-hospital mortality after TV-TAVI and iSAVR was equal (2.7%) in 2017, despite the much higher risk profile of TV-TAVI patients. Using the AKL score as reference, TV-TAVI showed a more favourable observed-to-expected mortality (O/E) ratio (0.89) than iSAVR (1.14)- even more pronounced in patients at low risk (0.81 vs. 1.14). Conclusions: The rates of major complications like bleeding and permanent pacemaker implantation after TV-TAVI keep declining. In 2017 patients undergoing TV-TAVI had a low in-hospital mortality rate with an O/E ratio < 1, indicating that the results were again better than those of all TAVI and SAVR of the previous year. Graphic abstract: Overall in-hospital mortality after transvascular TAVI and isolated aortic valve repair 2017 in Germany stratified to risk groups by the German Aortic Valve Score (German AV Score/AKL Score): low risk group (AKL 0– < 3%), intermediate risk group (AKL 3– < 6%), high risk group (AKL 6– < 10%) and very high risk group (AKL ≥ 10%)[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-09
Keywords: AKL score; Aortic valve replacement; Mortality; Outcome; Surgery; TAVI

Treatment and outcome of coronary artery perforations using a dual guiding catheter technique - Röther, Jens; Tröbs, Monique; Ludwig, Josef; Achenbach, Susanne; Schlundt, Christian (International Journal of Cardiology, 2015)
To evaluate the success rate and outcome of coronary artery perforation treatment using a dual guiding catheter technique.Coronary artery perforation is a rare but severe complication during percutaneous coronary intervention (PCI) with high mortality. The use of a second guiding catheter is a helpful technique to minimize hemorrhage through the perforation during interventional repair.We screened all patients between March 2004 and December 2014 who underwent PCI in our department for the occurrence of peri-interventional coronary perforation that was treated using a dual catheter technique. Patient and lesion characteristics as well as outcome were determined.We identified 8 patients who experienced coronary artery perforations (Ellis grade III) during coronary intervention and were treated using a dual guiding catheter approach. The procedure was technically successful (placement of covered stent and sealing of perforation) in 6 patients. Pericardiocentesis was required in 3 patients (38%). Total mortality was 12% (n=1). No coronary or peripheral vascular access complication occurred due to the use of a second guiding catheter.We suggest that the dual guiding catheter technique is a useful and alternative approach to treat severe Ellis grade III coronary artery perforations that occur in the context of percutaneous coronary interventions.
EVALuna2:12076

Treat or track: nanoagents in the service of health - Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33195

Tricuspid Annuloplasty: Transcatheter Approaches - Arnold, Martin; Haug, Julia; Landendinger, Melanie (Current Cardiology Reports, 2021)
Purpose of Review: New transcatheter techniques to perform tricuspid annuloplasty are evolving and are introduced into the clinical routine. Yet, clinical experience is limited. Recent Findings: Currently, 3 different techniques for tricuspid annuloplasty have been used in larger clinical cohorts. They can be divided into direct annuloplasty techniques and suture plication techniques. The largest clinical evidence is related to direct annuloplasty techniques. It has been shown that annular dimensions can be effectively reduced. This translates into an improvement of the degree of tricuspid regurgitation and improvement of clinical symptoms. Due to the newness of this type of therapy, long-term data is limited, but for one of the described techniques, published data show that the positive effects persist over a 2-year period. Summary: Transcatheter approaches are safe and are able to treat tricuspid regurgitation effectively. There are still differences in the efficacy of the different techniques. Clinical experience varies among the different approaches.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Interventional valve therapy; Transcatheter tricuspid annuloplasty; Tricuspid regurgitation; TTVR

Ultra-low dose comprehensive cardiac CT imaging in a patient with acute myocarditis - Tröbs, Monique; Brand, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
The ability of contrast-enhanced CT to detect "late enhancement" in a fashion similar to magnetic resonance imaging has been previously reported. We report a case of acute myocarditis with coronary CT angiography as well as "late enhancement" imaging with ultra-low effective radiation dose.
EVALuna2:11957

Unusual coarctation repair with double lumen distal arch - Hell, Michaela M.; Orchard, Elizabeth; Westaby, Stephen; Myerson, Saul G. (European Heart Journal, 2018)
EVALuna2:36003

Usefulness of baseline statin therapy in non-obstructive coronary artery disease by coronary computed tomographic angiography: From the CONFIRM (COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter) study - Cho, Yun-Kyeong; Nam, Chang-Wook; Koo, Bon-Kwon; Schulman-Marcus, Joshua; Hartaigh, Briain O.; Gransar, Heidi; Lu, Yao; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Bax, Jeroen J.; Budoff, Matthew J.; et al. (PLoS ONE, 2018)
BACKGROUND: The extent to which the presence and extent of subclinical atherosclerosis by coronary computed tomography angiography influences a potential mortality benefit of statin is unknown. We evaluated the relationship between statin therapy, mortality, and subclinical atherosclerosis. METHODS: In the CONFIRM study, patients with normal or non-obstructive plaque (<50% diameter stenosis) for whom data on baseline statin use was available were included. Coronary artery calcium (CAC) was quantified using the Agatston score. The extent of non-obstructive coronary atherosclerosis was quantified using the segment involvement score (SIS). 8,016 patients were followed for a median of 2.5 years with analysis of all-cause mortality and major adverse cardiac events (MACE) including all-cause mortality, myocardial infarction, unstable angina, target vessel revascularization, and coronary artery disease-related hospitalization. RESULTS: 1.2% of patients experienced all-cause mortality. Patients not on baseline statin therapy had a stepwise increased risk of all-cause mortality by CAC (relative to CAC = 0; CAC 1-99: hazard ratio [HR] 1.65, CAC 100-299: HR 2.19, and CAC≥300: HR 2.98) or SIS (relative to SIS = 0; SIS 1: HR 1.62, SIS 2-3: 2.48 and SIS≥4: 2.95). Conversely, in patients on baseline statin therapy, there was no significant increase in mortality risk with increasing CAC (p value for interaction = 0.049) or SIS (p value for interaction = 0.007). The incidence of MACE was 2.1%. Similar to the all-cause mortality, the risk of MACE was increased with CAC or SIS strata in patient not on baseline statin therapy. However, this relation was not observed in patient on baseline statin therapy. CONCLUSION: In individuals with non-obstructive coronary artery disease, increased risk of adverse events occurs with increasing CAC or SIS who are not on baseline statin therapy. Statin therapy is associated with a mitigation of risk of cardiac events in the presence of increasing atherosclerosis, with no particular threshold of disease burden.
EVALuna2:35957

Usefulness of magnetocardiography for the investigation of fetal arrhythmias - Klinghammer, Lutz; et al. (American Journal of Cardiology, 2001)

Valve Hemodynamics by Valve Size and 1-Year Survival Following Implantation of the Portico Valve in the Multicenter CONFIDENCE Registry - Möllmann, Helge; Linke, Axel; Nombela-Franco, Luis; Sluka, Martin; Francisco Oteo Dominguez, Juan; Montorfano, Matteo; Kim, Won Keun; Arnold, Martin; Vasa-Nicotera, Mariuca; Fichtlscherer, Stephan; Conradi, Lenard; Camuglia, Anthony; et al. (Structural Heart, 2023)
Background: The CONtrolled delivery For ImproveD outcomEs with cliNiCal Evidence registry was initiated to characterize the clinical safety and device performance from experienced transcatheter aortic valve implantation (TAVI) centers in Europe and Australia that use the Portico valve to treat patients with severe aortic stenosis. We herein report for the first time the valve performance at 30-day across all implanted valve sizes and the 1-year survival from this registry. Methods: This was a prospective, multicenter, single-arm observational clinical investigation of patients clinically indicated for implantation of a Portico valve in experienced TAVI centers. Patients were treated with a commercially available valve (size 23, 25, 27, or 29 mm) using either the first-generation delivery system (DS) (n = 501) or the second-generation (FlexNav) DS (n = 500). Adverse events were adjudicated by an independent clinical events committee according to Valve Academic Research Consortium-2 criteria. Echocardiographic outcomes were assessed at 30 days by an independent core laboratory, and a survival check was performed at 1 year. Results: We enrolled 1001 patients (82.0 years, 62.5% female, 63.7% New York Heart Association functional class III/IV at baseline) from 27 clinical sites in 8 countries across Europe and one site in Australia. Implantation of a single valve was successful in 97.5% of subjects. Valve hemodynamics at 30 days were substantially improved relative to baseline, with large aortic valve areas and low mean gradients across all implanted valve sizes (aortic valve areas were 1.7 ± 0.4, 1.7 ± 0.5, 1.8 ± 0.5, and 2.0 ± 0.5 cm2, and mean gradients were 7.0 ± 2.7, 7.5 ± 4.7, 7.3 ± 3.3, and 6.4 ± 3.3 mmHg for 23, 25, 27, and 29 mm valve sizes, respectively). Across all implanted valve sizes, most patients (77.1%) had no patient-prosthesis mismatch. Death from any cause within 1 year occurred in 13.7% of the patients in the first-generation DS group as compared with 11.0% in the second-generation DS group (p = 0.2). Conclusions: The Portico valve demonstrated excellent hemodynamic performance across all valve sizes in a large cohort of subjects implanted in experienced TAVI centers. One-year survival rates were favorable when using both the first-generation and second-generation (FlexNav) DSs in this high-risk cohort. ClinicalTrials.gov Identifier: NCT03752866.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Aortic stenosis; Self-expanding; TAVI; TAVR; Transcatheter aortic valve implantation; Transcatheter aortic valve replacement

Versorgung von Erwachsenen mit angeborenen Herzfehlern in Deutschland – tragende Rolle von Internisten und Hausärzten - Kaemmerer, Harald; Freilinger, Sebastian; Neidenbach, Rhoia; Achenbach, Stephan; Andonian, Caroline; Ewert, Peter; De Haan, Fokko; Nagdyman, Nicole; Schelling, Joerg; Hofbeck, Michael; Bauer, Ulrike; Huntgeburth, Michael; et al. (Internist, 2022)
Background: The number of adults with congenital heart disease (ACHD) is steadily increasing. The present cross-sectional study was conceived to investigate ACHD care from the perspective of patients and family practitioners (specialists for general medicine and internal medicine, general practitioners). Methods: Questionnaire-based cross-sectional study to analyze the real care situation of ACHD in Germany from the perspective of patients and primary care physicians (PCP). Results: The questionnaire was completed by 4493 ACHD (53.7% female; 41.3 ± 16.9 years) and 1055 PCP. The majority of ACHD (79.8%) visited their PCP for noncardiac health problems but also for cardiac problems. Almost all ACHD had substantial needs for medical consultation (performance, employment etc.). Of the patients 2014 (44.8%) did not know of any certified ACHD specialists or specialized centers and 2816 (62.7%) respondents were not aware of any ACHD patient organization. Of the PCPs 87.5% had cared for ACHD of all severities due to defect-typical residual and resulting symptoms. Many were not aware of any certified ACHD specialists. Only 28.5% consulted an ACHD specialist. Only 23.5% were aware of ACHD patient organizations. Conclusion: General practitioners are a mainstay of ACHD care in Germany. The present study shows that ACHD and their general practitioners are largely uninformed about the specialized care structures available nationwide, despite the high level of need for specialist care. In order to keep the morbidity and mortality of affected patients low, solutions must be elaborated in future to involve and integrate primary care physicians more intensively into the already existing dedicated ACHD care structures, in cooperation with specialized pediatric cardiologists, cardiologists and centers.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Cross-sectional study; Primary health care; Questionnaire; Real world data; Specialized care structures

Very low-dose coronary artery calcium scanning with high-pitch spiral acquisition mode: Comparison between 120-kV and 100-kV tube voltage protocols - Marwan, Mohamed; Mettin, Carina; Pflederer, Tobias; Seltmann, Martin; Schuhbaeck, Annika; Muschiol, Gerd; Ropers, Dieter; Daniel, Werner; Achenbach, Stephan (Journal of Cardiovascular Computed Tomography, 2013)
Background: Effective radiation dose from a single coronary artery calcification CT scan can range from 0.8 to 10.5 mSv, depending on the protocol. Reducing the effective radiation dose to reasonable levels without affecting diagnostic image quality can result in substantial dose reduction in CT. Objectives: We prospectively compared tube voltages of 120 and 100 kV in a low-dose CT acquisition protocol for measuring coronary artery calcified plaque with prospectively electrocardiogram (ECG)-triggered high-pitch spiral acquisition. Methods: In 150 consecutive patients, measurement of coronary artery calcified plaque was performed with prospectively ECG-triggered high-pitch spiral acquisition. Imaging was first done with tube voltage of 120 kV voltage and subsequently repeated with 100 kV and otherwise unchanged parameters. CT was performed with a dual-source CT system with 280 milliseconds of rotation time, 2 × 128 slices, pitch of 3.4, triggered at 60% of the R-R interval. Tube current for both protocols was set at 80 mAs. With the use of a medium sharp reconstruction kernel (Siemens B35f), cross-sectional images were reconstructed with 3.0-mm slice thickness and 1.5-mm increment. Agatston scores were determined per patient for both scan settings by 2 independent readers with the use of a standard threshold of 130 HU for calcium detection. In addition, the Agatston score was calculated with a previously proposed threshold of 147 HU for 100-kV acquisitions. Results: Mean image noise was 20 ± 5 and 27 ± 7 for 120 and 100 kV, respectively (P < 0.0001). Mean dose length product was 24 ± 6 cm · cGy for the 120-kV protocol and 14 ± 4 cm · cGy for the 100-kV protocol, corresponding to average estimated effective doses of 0.3 and 0.2 mSv (P < 0.0001). Five patients were excluded from the analysis. In the remaining 145 patients, using the standard tube voltage of 120 kV, any coronary calcium was detected in 76 identical patients by both observers. In 75 of these patients, calcium was also identified by both observers in 100-kV data sets, whereas 1 patient was scored negative by 1 reader and was assigned an Agatston score of 0.7 (threshold, 130 HU) and 0.2 (threshold, 147 HU) by the other. Interobserver disagreement for assigning a patient a zero Agatston score was the same for both scan settings (each 4 patients). The mean Agatston scores for 120-kV and 100-kV (threshold, 147 HU) scans were 105 ± 245 (range, 0-1865) and 116 ± 261 (range, 0-1917), respectively (P < 0.0001). Bland-Altman analysis indicated a systematic overestimation of the Agatston score with tube voltage of 100 kV and threshold of 147 HU (mean difference, 11; 95% limits of agreement, 62 to -40). Similar results were observed for coronary calcium volume scores. Conclusion: High-pitch spiral acquisition allows coronary calcium scoring with effective doses below 0.5 mSv. The use of 100-kV tube voltage further reduces effective radiation dose compared with the standard of 120 kV; however, it leads to significant overestimation of the Agatston score when the standard threshold of 130 HU is used. Adjusting the threshold to 147 HU leads to a better agreement compared with standard 120 kV protocols yet with a remaining systematic bias toward overestimation of the Agatston score. For high-pitch spiral acquisition mode, effective radiation dose reduction when using a 100-kV setting is minimal compared with the standard 120-kV setting and may be considered nonsignificant in a clinical setting. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Calcium score; CT; Low-dose protocols

Viewpoint Planning for Quantitative Coronary Angiography - Preuhs, Alexander; Berger, Martin; Bauer, Sebastian; Redel, Thomas; Unberath, Mathias; Achenbach, Stephan; Maier, Andreas (Computer Assisted Radiology and Surgery Proceedings of the 32nd International Congress and Exhibition, 2018)
Purpose: In coronary angiography, the condition of myocardial blood supply is assessed by analyzing 2-D X-ray projections of contrasted coronary arteries. This is done using a flexible C-arm system. Due to the X-ray immanent dimensionality reduction projecting the 3-D scene onto a 2-D image, the viewpoint is critical to guarantee an appropriate view onto the affected artery and, thus, enable reliable diagnosis. In this work, we introduce an algorithm computing optimal viewpoints for the assessment of coronary arteries without the need for 3-D models. Methods: We introduce the concept of optimal viewpoint planning solely based on a single angiographic X-ray image. The subsequent viewpoint is computed such that it is rotated precisely around a vessel, while minimizing foreshortening. Results: Our algorithm reduces foreshortening substantially compared to the input view and completely eliminates it for 90 ∘ rotations. Rotations around isocentered foreshortening-free vessels passing the isocenter are exact. The precision, however, decreases when the vessel is off-centered or foreshortened. We evaluate worst-case boundaries, providing insight in the maximal inaccuracies to be expected. This can be utilized to design viewpoints guaranteeing desired requirements, e.g., a true rotation around the vessel of at minimum 30 ∘. In addition, a phantom study is performed investigating the impact of input views to 3-D quantitative coronary angiography (QCA). Conclusion: We introduce an algorithm for optimal viewpoint planning from a single angiographic X-ray image. The quality of the second viewpoint—i.e., vessel foreshortening and true rotation around vessel—depends on the first viewpoint selected by the physician; however, our computed viewpoint is guaranteed to reduce the initial foreshortening. Our novel approach uses fluoroscopy images only and, thus, seamlessly integrates with the current clinical workflow for coronary assessment. In addition, it can be implemented in the QCA workflow without increasing user interaction, making vessel-shape reconstruction more stable by standardizing viewpoints.
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.viewpo_9
Keywords: Active vision; C-arm; Coronary angiography; Foreshortening; Interventional imaging; Patient-specific imaging; QCA

Viewpoint Planning for Quantitative Coronary Angiography (IJCARS) - Preuhs, Alexander; Berger, Martin; Bauer, Sebastian; Redel, Thomas; Unberath, Mathias; Achenbach, Stephan; Maier, Andreas (International Journal of Computer Assisted Radiology and Surgery, 2018)
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.viewpo_5
Keywords: coronary angiography; C-arm; interventional imaging; QCA; active vision; patient specific imaging; foreshortening

Virtual Single-frame Subtraction Imaging - Unberath, Mathias; Aichert, André; Achenbach, Stephan; Maier, Andreas (Proceedings of the 4th CT Meeting, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.virtua_8

'Well-being paradox' revisited: a cross-sectional study of quality of life in over 4000 adults with congenital heart disease - Andonian, Caroline Sophie; Freilinger, Sebastian; Achenbach, Stephan; Ewert, Peter; Gundlach, Ulrike; Hoerer, Jürgen; Kaemmerer, Harald; Pieper, Lars; Weyand, Michael; Neidenbach, Rhoia Clara; Beckmann, Jürgen (BMJ Open, 2021)
Objective The present cross-sectional study investigated quality of life (QOL) in a large cohort of German adults with congenital heart disease (ACHDs) in association with patient-related and clinical variables. Design Cross-sectional survey. Participants Between 2016 and 2019, a representative sample of 4014 adults with various forms of congenital heart defect (CHD) was retrospectively analysed. Inclusion criteria were confirmed diagnosis of CHD; participant aged 18 years and older; and necessary physical, cognitive and language capabilities to complete self-report questionnaires. Primary and secondary outcome measures QOL was assessed using the 5-level EQ-5D version (EQ-5D-5L). Sociodemographic and medical information was obtained by a self-devised questionnaire. Associations of QOL with patient-reported clinical and sociodemographic variables were quantified using multiple regression analysis and multiple ordinal logit models. Results Overall, ACHDs (41.8±17.2 years, 46.5% female) reported a good QOL comparable to German population norms. The most frequently reported complaints occurred in the dimensions pain/discomfort (mean: 16.3, SD: p<0.001) and anxiety/depression (mean: 14.3, p<0.001). QOL differed significantly within ACHD subgroups, with patients affected by pretricuspid shunt lesions indicating the most significant impairments (p<0.001). Older age, female sex, medication intake and the presence of comorbidities were associated with significant reductions in QOL (p<0.001). CHD severity was positively associated with QOL within the dimensions of self-care (OR 0.148, 95% CI 0.04 to 0.58) and mobility (OR 0.384, 95% CI 0.19 to 0.76). Conclusion Current findings temper widely held assumptions among clinicians and confirm that ACHDs experience a generally good QOL. However, specific subgroups may require additional support to cope with disease-related challenges. The negative correlation of QOL with age is especially alarming as the population of ACHDs is expected to grow older in the future. Trial registration number DRKS00017699; Results.
CRIS-Team Scopus Importer:2021-07-16
Keywords: adult cardiology; cardiac epidemiology; congenital heart disease; epidemiology; mental health; preventive medicine

What makes a plaque rupture? A simple answer seems too much to ask for - Achenbach, Stephan (EuroIntervention, 2023)
CRIS-Team Scopus Importer:2023-02-03

When Does a Calcium Score Equates to Secondary Prevention?: Insights From the Multinational CONFIRM Registry - Budoff, Matthew J.; Kinninger, April; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz; Bax, Jeroen J.; Berman, Daniel S.; Cademartiri, Filippo; Callister, Tracy Q.; Chang, Hyuk Jae; Chow, Benjamin J.W.; Cury, Ricardo C.; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Background: Elevated coronary artery calcium (CAC) scores in subjects without prior atherosclerotic cardiovascular disease (ASCVD) have been shown to be associated with increased cardiovascular risk. Objectives: The authors sought to determine at what level individuals with elevated CAC scores who have not had an ASCVD event should be treated as aggressively for cardiovascular risk factors as patients who have already survived an ASCVD event. Methods: The authors performed a cohort study comparing event rates of patients with established ASVCD to event rates in persons with no history of ASCVD and known calcium scores to ascertain at what level elevated CAC scores equate to risk associated with existing ASCVD. In the multinational CONFIRM (Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter) registry, the authors compared ASCVD event rates in persons without a history of myocardial infarction (MI) or revascularization (as categorized on CAC scores) to event rates in those with established ASCVD. They identified 4,511 individuals without known coronary artery disease (CAC) who were compared to 438 individuals with established ASCVD. CAC was categorized as 0, 1 to 100, 101 to 300, and >300. Cumulative major adverse cardiovascular events (MACE), MACE plus late revascularization, MI, and all-cause mortality incidence was assessed using the Kaplan-Meier method for persons with no ASCVD history by CAC level and persons with established ASCVD. Cox proportional hazards regression analysis was used to calculate HRs with 95% CIs, which were adjusted for traditional cardiovascular risk factors. Results: The mean age was 57.6 ± 12.4 years (56% male). In total, 442 of 4,949 (9%) patients experienced MACEs over a median follow-up of 4 years (IQR: 1.7-5.7 years). Incident MACEs increased with higher CAC scores, with the highest rates observed with CAC score >300 and in those with prior ASCVD. All-cause mortality, MACEs, MACE + late revascularization, and MI event rates were not statistically significantly different in those with CAC >300 compared with established ASCVD (all P > 0.05). Persons with a CAC score <300 had substantially lower event rates. Conclusions: Patients with CAC scores >300 are at an equivalent risk of MACE and its components as those treated for established ASCVD. This observation, that those with CAC >300 have event rates comparable to those with established ASCVD, supplies important background for further study related to secondary prevention treatment targets in subjects without prior ASCVD with elevated CAC. Understanding the CAC scores that are associated with ASCVD risk equivalent to stable secondary prevention populations may be important for guiding the intensity of preventive approaches more broadly.
CRIS-Team Scopus Importer:2023-08-11
Keywords: coronary artery disease; coronary calcium; coronary computed tomography angiography; prognosis

WHEN DOES A CALCIUM SCORE EQUATE TO SECONDARY PREVENTION: INSIGHTS FROM THE CONFIRM REGISTRY - Budoff, Matthew J.; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz; Bax, Jeroen J.; Berman, Daniel; Cademartiri, Filippo; Callister, Tracy; Chang, Hyuk-Jae; Chow, Benjamin; Cury, Ricardo; Feuchtner, Gudrun; et al. (2019)
EVALuna2:213021

White Matter Lesions, Carotid and Coronary Atherosclerosis in Late-Onset Depression and Healthy Controls - Devantier, Torben Albert; Norgaard, Bjarne Linde; Poulsen, Mikael Kjaer; Garde, Ellen; Ovrehus, Kristian Altern; Achenbach, Stephan; Dey, Damini; Sorensen, Leif Hougaard; Videbech, Poul; Marwan, Mohamed (Psychosomatics, 2016)
BACKGROUND: Cerebral white matter lesions (WMLs) are more common in individuals with late-onset or late-life depression. It has been proposed that carotid atherosclerosis may predispose to WMLs by inducing cerebral hypoperfusion. This hemodynamic effect of carotid atherosclerosis could be important for the formation of WMLs in depression. METHODS: The case-control study included 29 patients with late-onset major depressive disorder and 27 controls matched for sex, age, and tobacco use. WML volume, carotid intima-media thickness, and coronary plaque volume were assessed using magnetic resonance imaging, ultrasound scan, and coronary computed tomography (CT) angiography, respectively. RESULTS: The mean age for the total sample was 59.7 ± 4.7 years. There was no difference in carotid intima-media thickness between patients and controls (p = 0.164), whereas a higher WML volume in the patients was found (p = 0.051). In both patients and controls, WML volume was associated with carotid but not with coronary atherosclerosis. In adjusted multiple linear regression, a 0.1mm increase in averaged carotid intima-media thickness was associated with a 52% (95% CI: 8.4-112, p = 0.032) increase in WML volume. The association between carotid intima-media thickness and WML volume was, however, similar in patients and controls. CONCLUSIONS: In older persons aged between 50 and 70 years, WMLs do not seem to be a part of generalized atherosclerotic disease, but seem to be dependent on atherosclerosis in the carotid arteries. Carotid atherosclerosis, however, could not explain the higher WML load observed in the depressed patients, and thus, studies are needed to establish the mechanisms linking depression and WMLs.
EVALuna2:12104

Wireless LV endocardial stimulation for CRT: Acute and short term results after retrograde and transseptal implantation - Gruber, M.; Anneken, Lars; Feher, Marcel; Yovcheva, I.; Achenbach, Stephan; Arnold, Martin (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Age- and sex-based resource utilisation and costs in patients with acute chest pain undergoing cardiac CT angiography: pooled evidence from ROMICAT II and ACRIN-PA trials - Bamberg, Fabian; Mayrhofer, Thomas; Ferencik, Maros; Bittner, Daniel O.; Hallett, Travis R.; Janjua, Sumbal; Schlett, Christopher L.; Nagurney, John T.; Udelson, James E.; Truong, Quynh A.; Woodard, Pamela K.; Hollander, Judd E.; et al. (European Radiology, 2018)
OBJECTIVES: To determine resource utilisation according to age and gender-specific subgroups in two large randomized diagnostic trials. METHODS: We pooled patient-specific data from ACRIN-PA 4005 and ROMICAT II that enrolled subjects with acute chest pain at 14 US sites. Subjects were randomized between a standard work-up and a pathway utilizing cardiac computed tomography angiography (CCTA) and followed for the occurrence of acute coronary syndrome (ACS) and resource utilisation during index hospitalisation and 1-month follow-up. Study endpoints included diagnostic accuracy of CCTA for the detection of ACS as well as resource utilisation. RESULTS: Among 1240 patients who underwent CCTA, negative predictive value of CCTA to rule out ACS remained very high (≥99.4%). The proportion of patients undergoing additional diagnostic testing and cost increased with age for both sexes (p < 0.001), and was higher in men as compared to women older than 60 years (43.1% vs. 23.4% and 4559 ± 3382 vs. 3179 ± 2562, p < 0.01; respectively). Cost to rule out ACS was higher in men (p < 0.001) and significantly higher for patients older than 60 years (2860-5935 in men, p < 0.001). CONCLUSIONS: CCTA strategy in patients with acute chest pain results in varying resource utilisation according to age and gender-specific subgroups, mandating improved selection for advanced imaging. KEY POINTS: • In this analysis, CAD and ACS increased with age and male gender. • CCTA in patients with acute chest pain results in varying resource utilisation. • Significant increase of diagnostic testing and cost with age for both sexes. • Cost to rule out ACS is higher in men and patients >60 years. • Improved selection of subjects for cardiac CTA result in more resource-driven implementation.
EVALuna2:33585

Clinical implementation of an emergency department coronary computed tomographic angiography protocol for triage of patients with suspected acute coronary syndrome - Ghoshhajra, Brian B.; Takx, Richard A. P.; Staziaki, Pedro V.; Vadvala, Harshna; Kim, Phillip; Neilan, Tomas G.; Meyersohn, Nandini M.; Bittner, Daniel; Janjua, Sumbal A.; Mayrhofer, Thomas; Greenwald, Jeffrey L.; Truong, Quyhn A.; et al. (European Radiology, 2017)
OBJECTIVES: To evaluate the efficiency and safety of emergency department (ED) coronary computed tomography angiography (CTA) during a 3-year clinical experience. METHODS: Single-center registry of coronary CTA in consecutive ED patients with suspicion of acute coronary syndrome (ACS). The primary outcome was efficiency of coronary CTA defined as the length of hospitalization. Secondary endpoints of safety were defined as the rate of downstream testing, normalcy rates of invasive coronary angiography (ICA), absence of missed ACS, and major adverse cardiac events (MACE) during follow-up, and index radiation exposure. RESULTS: One thousand twenty two consecutive patients were referred for clinical coronary CTA with suspicion of ACS. Overall, median time to discharge home was 10.5 (5.7-24.1) hours. Patient disposition was 42.7 % direct discharge from the ED, 43.2 % discharge from emergency unit, and 14.1 % hospital admission. ACS rate during index hospitalization was 9.1 %. One hundred ninety two patients underwent additional diagnostic imaging and 77 underwent ICA. The positive predictive value of CTA compared to ICA was 78.9 % (95 %-CI 68.1-87.5 %). Median CT radiation exposure was 4.0 (2.5-5.8) mSv. No ACS was missed; MACE at follow-up after negative CTA was 0.2 %. CONCLUSIONS: Coronary CTA in an experienced tertiary care setting allows for efficient and safe management of patients with suspicion for ACS. KEY POINTS: • ED Coronary CTA using advanced systems is associated with low radiation exposure. • Negative coronary CTA is associated with low rates of MACE. • CTA in ED patients enables short median time to discharge home. • CTA strategy is characterized by few downstream tests including unnecessary ICA.
EVALuna2:33636

Coronary CT Angiography as a Diagnostic and Prognostic Tool: Perspective from a Multicenter Randomized Controlled Trial: PROMISE - Bittner, Daniel O.; Ferencik, Maros; Douglas, Pamela S.; Hoffmann, Udo (Current Cardiology Reports, 2016)
The PROMISE (Prospective multicenter imaging study for evaluation of chest pain) trial compared the effectiveness of coronary CT angiography and functional testing as initial diagnostic test for patients with suspicion for stable coronary artery disease (CAD). With 10,003 patients randomized at 193 sites, the PROMISE trial provides a snapshot of real-world care for this very common presentation. Over a median follow-up of 25 months, PROMISE did not find significant differences in major clinical events (composite endpoint 164 vs. 151, HR 1.04 (0.83-1.29); p = 0.75) between the two strategies. Other major findings were the large discrepancy between estimates of pre-test likelihood and observed prevalence for obstructive CAD (≥50 %) and the proportion of noninvasive tests positive for ischemia or obstructive CAD (53 vs. 11 %; respectively) and the better efficiency of coronary computed tomography angiography (CTA) to select patients for invasive coronary angiography (ICA) who had obstructive CAD (72 vs. 48 % for coronary CTA and functional testing, respectively). Radiation exposure was higher in the CT arm compared to all functional testing but lower than for nuclear perfusion stress testing. Improvement of patient selection for diagnostic testing and risk stratification will be keys to increase efficacy and efficiency of management of patients with suspicion for stable CAD.
EVALuna2:33701

Differences in the association of total versus local coronary artery calcium with acute coronary syndrome and culprit lesions in patients with acute chest pain: The coronary calcium paradox - Puchner, Stefan B.; Mayrhofer, Thomas; Park, Jakob; Lu, Michael T.; Liu, Ting; Maurovich-Horvat, Pal; Ghemigian, Khristine; Bittner, Daniel O.; Fleg, Jerome L.; Udelson, James E.; Truong, Quynh A.; Hoffmann, Udo; et al. (Atherosclerosis, 2018)
BACKGROUND AND AIMS: Total coronary artery calcium (CAC) burden is associated with an increased cardiovascular risk, while local CAC may represent stable plaques. We determined differences in relationship of total CAC with acute coronary syndrome (ACS) and local CAC with culprit lesions in patients with suspected ACS. METHODS: We performed computed tomography (CT) for CAC and CT angiography to assess the presence of significant stenosis and high-risk plaque (positive remodeling, low CT attenuation, napkin-ring sign, spotty calcium) in 37 patients with ACS and 223 controls. Total and segmental Agatston scores were measured. Culprit lesions were assessed in subjects with ACS. RESULTS: Patients (n = 260) with vs. without ACS had higher total CAC score (median 229, 25th-75th percentile 75-517 vs. 27, 25th-75th percentile 0-99, p<0.001), higher prevalence of significant stenosis (78% vs. 7%, p<0.001) and high-risk plaque (95% vs. 59%, p<0.001). In those with ACS, culprit (n = 41) vs. non-culprit (n = 200) lesions, had similar segmental CAC score (median 22, 25th-75th percentile 4-71 vs. 14, 25th-75th percentile 0-51; p=0.37), but higher prevalence of significant stenosis (81% vs. 11%, p<0.001) and high-risk plaque (76% vs. 51%, p=0.005). Significant stenosis (odds ratio 40.2, 95%CI 15.6-103.9, p<0.001) and high-risk plaque (odds ratio 3.4, 95%CI 1.3-9.1, p=0.02), but not segmental CAC score (odds ratio 1.0, 95%CI 1.0-1.0, p=0.47), were associated with culprit lesions of ACS. CONCLUSIONS: Total CAC burden was associated with ACS but segmental CAC was not associated with culprit lesions. Our findings suggest that total but not local CAC is a marker of ACS risk and support the hypothesis that extensive local CAC is a marker of plaque stability.
EVALuna2:213100

European heart health survey 2019 - Gaede, Luise; Sitges, Marta; Neil, Johnson; Selvi, Eleonara; Woan, William; Derks, Richard; Möllmann, Helge (Clinical Cardiology, 2020)
Background: Rising life expectancy in the western population is increasing the prevalence of heart valve diseases (HVD). Hypothesis: The level of awareness and initial screening for HVD should be sufficient. The potential impact of HVD on the daily activities of the elderly population in Europe might affect our society. Methods and Results: A survey was conducted, including a total of 12 832 people aged ≥ 60 years in 11 European countries. Of all the people surveyed, 5.6% could correctly describe aortic valve stenosis. Most participants (75.0%) claimed they regularly do activities like sports or social activities, 29.2% provide care for a family member, friend or acquaintance. The majority (69.2%) would be prevented from doing these activities by symptoms such as chest pain, fatigue or shortness of breath. Having chest pain (76.5%) and shortness of breath (57.8%) were reasons for most people to arrange an appointment with their GP, whereas only 26.2% would visit a GP for fatigue. 67.6% of respondents claimed to be checked with a stethoscope by their GP occasionally, never, or only when they ask. The preferred treatment option for HVD is a keyhole procedure (45.8%), whereas open heart surgery would only be preferred by 7.0%. Conclusion: Knowledge about HVD is still low. Neither appointments with a GP driven by symptoms nor regular use of a stethoscope are a reliable guarantee for early diagnosis. With the over 60s in Europe playing an active role in social life, awareness campaigns and regular heart health checks may guarantee early diagnosis and treatment of HVD.
CRIS-Team Scopus Importer:2020-11-06
Keywords: aortic stenosis; awareness; heart valve disease; knowledge; survey

Identification of coronary artery calcification can optimize risk stratification in patients with acute chest pain - Bittner, Daniel O.; Takx, Richard A. P.; Staziaki, Pedro V.; Janjua, Sumbal; Neilan, Tomas G.; Meyersohn, Nandini M.; Lu, Michael T.; Prabhakar, Anand M.; Nagurney, John T.; Hoffmann, Udo; Ghoshhajra, Brian B. (International Journal of Cardiology, 2017)
BACKGROUND: The number of patients presenting to the emergency department (ED) with suspected acute coronary syndrome (ACS) is substantial. We tested whether identification of coronary artery calcium (CAC) can improve the negative predictive value (NPV) of clinical risk assessment for ACS in patients with acute chest pain. METHODS AND RESULTS: We included 826 consecutive patients (mean age: 53±11years; 42% female) without known coronary artery disease (CAD) or initially elevated serum biomarkers, whom underwent non-contrast CT, to assess the CAC score, and CT angiography (CTA), to detect coronary stenosis. We analyzed the diagnostic performance of CAC and the Thrombolysis In Myocardial Infarction (TIMI) risk score for our primary outcomes (ACS and obstructive CAD). No CAC was found in 54% (n=444) of all patients, 63% (n=524) had a TIMI score of 0 and 40% (n=328) had both. The prevalence of obstructive CAD was 16% for ≥50% stenosis and 8.7% for ≥70% stenosis. The incidence of ACS was 7.9%, (MI=11, UAP=54). The NPV of CAC=0 was 99.5% for ACS. The NPV of a combination of TIMI score=0 and no CAC was 89% for any CAD (any plaque or stenosis) and 99.7% for ≥50% stenosis. A 100% NPV was found for ≥70% stenosis and ACS, correctly identifying 328 (40%) patients. CONCLUSIONS: The exclusion of CAC, in combination with clinical risk assessment, has high clinical value in patients with acute chest pain, as it identifies patients at low risk for ACS and obstructive CAD more accurately as compared to clinical risk assessment alone.
EVALuna2:33593

Impact of Coronary Calcification on Clinical Management in Patients With Acute Chest Pain - Bittner, Daniel O.; Mayrhofer, Thomas; Bamberg, Fabian; Hallett, Travis R.; Janjua, Sumbal; Addison, Daniel; Nagurney, John T.; Udelson, James E.; Lu, Michael T.; Truong, Quynh A.; Woodard, Pamela K.; Hollander, Judd E.; et al. (Circulation: Cardiovascular Imaging, 2017)
Background Coronary artery calcification (CAC) may impair diagnostic assessment of coronary computed tomography angiography (CTA). We determined whether CAC affects efficiency of coronary CTA in patients with suspected acute coronary syndrome (ACS). Methods and Results This is a pooled analysis of ACRIN-PA (American College of Radiology Imaging Network-Pennsylvania) 4005 and the ROMICAT-II trial (Rule Out Myocardial Infarction/Ischemia Using Computer Assisted Tomography) comparing an initial coronary CTA strategy to standard of care in acute chest pain patients. In the CTA arms, we investigated appropriateness of downstream testing, cost, and diagnostic yield to identify patients with obstructive coronary artery disease on subsequent invasive coronary angiography across CAC score strata (Agatston score: 0, >0-10, >10-100, >100-400, >400). Out of 1234 patients (mean age 518.8 years), 80 (6.5%) had obstructive coronary artery disease (70% stenosis) and 68 (5.5%) had ACS. Prevalence of obstructive coronary artery disease (1%-64%), ACS (1%-44%), downstream testing (4%-72%), and total (2337-8484 US) and diagnostic cost (2310-6678 US) increased across CAC strata (P<0.001). As the increase in testing and cost were lower than the increase of ACS rate in patients with CAC>400, cost to diagnose one ACS was lowest in this group (19 283 US versus 464 399 US) as compared with patients without CAC. The diagnostic yield of invasive coronary angiography was highest in patients with CAC>400 (87% versus 38%). Conclusions Downstream testing, total, and diagnostic cost increased with increasing CAC, but were found to be appropriate because obstructive coronary artery disease and ACS were more prevalent in patients with high CAC. In patients with acute chest pain undergoing coronary CTA, cost-efficient testing and excellent diagnostic yield can be achieved even with high CAC burden. Clinical Trial Registration URL: http://www.clinicaltrials.gov. Unique identifiers: NCT01084239 and NCT00933400.
EVALuna2:33641

Left main bifurcation lesions: Medina reclassification revisited—as easy as ABC - Ludwig, Josef; Mohamed, Mohamed; Mamas, Mamas A. (Catheterization and Cardiovascular Interventions, 2020)
CRIS-Team Scopus Importer:2020-07-17

Perivascular Epicardial Fat Stranding at Coronary CT Angiography: A Marker of Acute Plaque Rupture and Spontaneous Coronary Artery Dissection - Hedgire, Sandeep; Baliyan, Vinit; Zucker, Evan J.; Bittner, Daniel O.; Staziaki, Pedro V.; Takx, Richard A. P.; Scholtz, Jan-Erik; Meyersohn, Nandini; Hoffmann, Udo; Ghoshhajra, Brian (Radiology, 2018)
Purpose To evaluate the frequency and implications of perivascular fat stranding on coronary computed tomography (CT) angiograms obtained for suspected acute coronary syndrome (ACS). Materials and Methods This retrospective registry study was approved by the institutional review board. The authors reviewed the medical records and images of 1403 consecutive patients (796 men, 607 women; mean age, 52.8 years) who underwent coronary CT angiography at the emergency department from February 2012 to March 2016. Fat attenuation, length and number of circumferential quadrants of the affected segment, and attenuation values in the unaffected epicardial and subcutaneous fat were measured. "Cases" were defined as patients with perivascular fat stranding. Patients with significant stenosis but without fat stranding were considered control subjects. Baseline imaging characteristics, ACS frequency, and results of subsequent downstream testing were compared between cases and control subjects by using two-sample t, Mann-Whitney U, and Fisher tests. Results Perivascular fat stranding was seen in 11 subjects, nine with atherosclerotic lesions and two with spontaneous coronary artery dissections, with a mean fat stranding length of 19.2 mm and circumferential extent averaging 2.9 quadrants. The mean attenuation of perivascular fat stranding, normal epicardial fat, and normal subcutaneous fat was 17, -93.2, and -109.3 HU, respectively (P < .001). Significant differences (P < .05) between cases and control subjects included lower Agatston score, presence of wall motion abnormality, and initial elevation of serum troponin level. ACS frequency was 45.4% in cases and 3.8% in control subjects (P = .001). Conclusion Recognition of perivascular fat stranding may be a helpful additional predictor of culprit lesion and marker of risk for ACS in patients with significant stenosis or spontaneous coronary artery dissection. © RSNA, 2018 Online supplemental material is available for this article.
EVALuna2:213069

Pretest probability for patients with suspected obstructive coronary artery disease: re-evaluating Diamond-Forrester for the contemporary era and clinical implications: insights from the PROMISE trial - Foldyna, Borek; Udelson, James E.; Karády, Júlia; Banerji, Dahlia; Lu, Michael T.; Mayrhofer, Thomas; Bittner, Daniel O.; Meyersohn, Nandini M.; Emami, Hamed; Genders, Tessa S.S.; Fordyce, Christopher B.; Ferencik, Maros; et al. (European Heart Journal - Cardiovascular Imaging, 2019)
AIMS: To update pretest probabilities (PTP) for obstructive coronary artery disease (CAD ≥ 50%) across age, sex, and clinical symptom strata, using coronary computed tomography angiography (CTA) in a large contemporary population of patients with stable chest pain referred to non-invasive testing. METHODS AND RESULTS: We included patients enrolled in the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial and randomized to CTA. Exclusively level III-certified readers, blinded to demographic and clinical data, assessed the prevalence of CAD ≥ 50% in a central core lab. After comparing the recent European Society of Cardiology-Diamond and Forrester PTP (ESC-DF) with the actual observed prevalence of CAD ≥ 50%, we created a new PTP set by replacing the ESC-DF PTP with the observed prevalence of CAD ≥ 50% across strata of age, sex, and type of angina. In 4415 patients (48.3% men; 60.5 ± 8.2 years; 78% atypical angina; 11% typical angina; 11% non-anginal chest pain), the observed prevalence of CAD ≥ 50% was 13.9%, only one-third of the average ESC-DF PTP (40.6; P < 0.001 for difference). The PTP in the new set ranged 2-48% and were consistently lower than the ESC-DF PTP across all age, sex, and angina type categories. Initially, 4284/4415 (97%) patients were classified as intermediate-probability by the ESC-DF (PTP 15-85%); using the PROMISE-PTP, 50.2% of these patients were reclassified to the low PTP category (PTP < 15%). CONCLUSION: The ESC-DF PTP overestimate vastly the actual prevalence of CAD ≥ 50%. A new set of PTP, derived from results of non-invasive testing, may substantially reduce the need for non-invasive tests in stable chest pain.
CRIS-Team Scopus Importer:2019-07-16
Keywords: computed tomography angiography; coronary stenosis; Diamond and Forrester; obstructive coronary artery disease; stable chest pain

Prognostic Value of Coronary Artery Calcium in the PROMISE Study (Prospective Multicenter Imaging Study for Evaluation of Chest Pain) - Budoff, Matthew J.; Mayrhofer, Thomas; Ferencik, Maros; Bittner, Daniel; Lee, Kerry L.; Lu, Michael T.; Coles, Adrian; Jang, James; Krishnam, Mayil; Douglas, Pamela S.; Hoffmann, Udo (Circulation, 2017)
BACKGROUND: Coronary artery calcium (CAC) is an established predictor of future major adverse atherosclerotic cardiovascular events in asymptomatic individuals. However, limited data exist as to how CAC compares with functional testing (FT) in estimating prognosis in symptomatic patients. METHODS: In the PROMISE trial (Prospective Multicenter Imaging Study for Evaluation of Chest Pain), patients with stable chest pain (or dyspnea) and intermediate pretest probability for obstructive coronary artery disease were randomized to FT (exercise electrocardiography, nuclear stress, or stress echocardiography) or anatomic testing. We evaluated those who underwent CAC testing as part of the anatomic evaluation (n=4209) and compared that with results of FT (n=4602). We stratified CAC and FT results as normal or mildly, moderately, or severely abnormal (for CAC: 0, 1-99 Agatston score [AS], 100-400 AS, and >400 AS, respectively; for FT: normal, mild=late positive treadmill, moderate=early positive treadmill or single-vessel ischemia, and severe=large ischemic region abnormality). The primary end point was all-cause death, myocardial infarction, or unstable angina hospitalization over a median follow-up of 26.1 months. Cox regression models were used to calculate hazard ratios (HRs) and C statistics to determine predictive and discriminatory values. RESULTS: Overall, the distribution of normal or mildly, moderately, or severely abnormal test results was significantly different between FT and CAC (FT: normal, n=3588 [78.0%]; mild, n=432 [9.4%]; moderate, n=217 [4.7%]; severe, n=365 [7.9%]; CAC: normal, n=1457 [34.6%]; mild, n=1340 [31.8%]; moderate, n=772 [18.3%]; severe, n=640 [15.2%];P<0.0001). Moderate and severe abnormalities in both arms robustly predicted events (moderate: CAC: HR, 3.14; 95% confidence interval, 1.81-5.44; and FT: HR, 2.65; 95% confidence interval, 1.46-4.83; severe: CAC: HR, 3.56; 95% confidence interval, 1.99-6.36; and FT: HR, 3.88; 95% confidence interval, 2.58-5.85). In the CAC arm, the majority of events (n=112 of 133, 84%) occurred in patients with any positive CAC test (score >0), whereas fewer than half of events occurred in patients with mildly, moderately, or severely abnormal FT (n=57 of 132, 43%;P<0.001). In contrast, any abnormality on FT was significantly more specific for predicting events (78.6% for FT versus 35.2% for CAC;P<0.001). Overall discriminatory ability in predicting the primary end point of mortality, nonfatal myocardial infarction, and unstable angina hospitalization was similar and fair for both CAC and FT (C statistic, 0.67 versus 0.64). Coronary computed tomographic angiography provided significantly better prognostic information compared with FT and CAC testing (C index, 0.72). CONCLUSIONS: Among stable outpatients presenting with suspected coronary artery disease, most patients experiencing clinical events have measurable CAC at baseline, and fewer than half have any abnormalities on FT. However, an abnormal FT was more specific for cardiovascular events, leading to overall similarly modest discriminatory abilities of both tests. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01174550.
EVALuna2:33600

Reduced leaflet motion after transcatheter aortic-valve replacement - de Backer, Ole; Dangas, George D.; Jilaihawi, Hasan; Leipsic, Jonathon A.; Terkelsen, Christian J.; Makkar, Raj; Kini, Annapoorna S.; Veien, Karsten T.; Abdel-Wahab, Mohamed; Kim, Won Keun; Balan, Prakash; van Mieghem, Nicolas; et al. (New England Journal of Medicine, 2020)
BACKGROUND Subclinical leaflet thickening and reduced leaflet motion of bioprosthetic aortic valves have been documented by four-dimensional computed tomography (CT). Whether anticoagulation can reduce these phenomena after transcatheter aortic-valve replacement (TAVR) is not known. METHODS In a substudy of a large randomized trial, we randomly assigned patients who had undergone successful TAVR and who did not have an indication for long-term anticoagulation to a rivaroxaban-based antithrombotic strategy (rivaroxaban [10 mg] plus aspirin [75 to 100 mg] once daily) or an antiplatelet-based strategy (clopidogrel [75 mg] plus aspirin [75 to 100 mg] once daily). Patients underwent evaluation by four-dimensional CT at a mean (±SD) of 90±15 days after randomization. The primary end point was the percentage of patients with at least one prosthetic valve leaflet with grade 3 or higher motion reduction (i.e., involving >50% of the leaflet). Leaflet thickening was also assessed. RESULTS A total of 231 patients were enrolled. At least one prosthetic valve leaflet with grade 3 or higher motion reduction was found in 2 of 97 patients (2.1%) who had scans that could be evaluated in the rivaroxaban group, as compared with 11 of 101 (10.9%) in the antiplatelet group (difference, -8.8 percentage points; 95% confidence interval [CI], -16.5 to -1.9; P=0.01). Thickening of at least one leaflet was observed in 12 of 97 patients (12.4%) in the rivaroxaban group and in 33 of 102 (32.4%) in the antiplatelet group (difference, -20.0 percentage points; 95% CI, -30.9 to -8.5). In the main trial, the risk of death or thromboembolic events and the risk of life-threatening, disabling, or major bleeding were higher with rivaroxaban (hazard ratios of 1.35 and 1.50, respectively). CONCLUSIONS In a substudy of a trial involving patients without an indication for long-term anticoagulation who had undergone successful TAVR, a rivaroxaban-based antithrombotic strategy was more effective than an antiplatelet-based strategy in preventing subclinical leaflet-motion abnormalities. However, in the main trial, the rivaroxaban-based strategy was associated with a higher risk of death or thromboembolic complications and a higher risk of bleeding than the antiplatelet-based strategy.
CRIS-Team Scopus Importer:2020-01-24

Subclinical Burden of Coronary Artery Calcium in Patients With Coarctation of the Aorta - Krishnamurthy, Yamini; Schmidt, Ada C. Stefanescu; Bittner, Daniel O.; Scholtz, Jan-Erik; Bui, Amy; Reddy, Rajesh; Youniss, Mohamed A.; Donohoe, Kendall; Flannery, Laura D.; Fahed, Akl C.; Ghoshhajra, Brian B.; Yeh, Doreen Defaria; et al. (American Journal of Cardiology, 2019)
Coronary computed tomography (CT) angiography is often performed in adults with coarctation of the aorta (CoA) for anatomic assessment. As this population ages, assessment of atherosclerotic cardiovascular disease burden is important. Thus, quantitative and qualitative coronary artery calcium (CAC) scores were assessed for patients with CoA >= 16 years of age, who were seen at a referral center. CoA patients had either coronary CT angiography or chest CT with interpretable coronary information performed for clinical indications (follow-up, preoperative, or for symptoms) from 2004 to 2017. Qualitative CAC was determined based on low-dose CT and lung cancer screening protocols. Quantitative CAC scores were compared with an age- and gender-matched control cohort of patients chosen from an emergency department database of patients who received coronary CT angiography for chest pain evaluation. Atherosclerotic cardiovascular disease 10-year predicted risk scores were calculated for both cohorts. Out of 131 patients with CoA (mean age 46.1 +/- 15.3 years), 22 patients (17%) had multivessel atherosclerotic disease on qualitative assessment. In the subgroup of patients >= 40 years, those with CoA were more likely to have a quantitative CAC score >= 400 compared with those without CoA (14% vs 4%, p = 0.02). Median atherosclerotic cardiovascular disease risk score was 8% (interquartile range 2% to 12%) for CoA patients >= 40 years, and 5% (interquartile range 2% to 9%) for patient without CoA >= 40 years. In conclusion, we determined that CoA patients have subclinical atherosclerosis identifiable on CT in high rates when compared with patients without CoA. Atherosclerotic cardiovascular disease should be assessed in these patients for prevention and treatment. (C) 2018 Published by Elsevier Inc.
CRIS-Team WoS Importer:2019-05-21

Use of High-Risk Coronary Atherosclerotic Plaque Detection for Risk Stratification of Patients With Stable Chest Pain: A Secondary Analysis of the PROMISE Randomized Clinical Trial - Ferencik, Maros; Mayrhofer, Thomas; Bittner, Daniel O.; Emami, Hamed; Puchner, Stefan B.; Lu, Michael T.; Meyersohn, Nandini M.; Ivanov, Alexander V.; Adami, Elizabeth C.; Patel, Manesh R.; Mark, Daniel B.; Udelson, James E.; et al. (JAMA Cardiology, 2018)
Importance: Coronary computed tomographic angiography (coronary CTA) can characterize coronary artery disease, including high-risk plaque. A noninvasive method of identifying high-risk plaque before major adverse cardiovascular events (MACE) could provide practice-changing optimizations in coronary artery disease care. Objective: To determine whether high-risk plaque detected by coronary CTA was associated with incident MACE independently of significant stenosis (SS) and cardiovascular risk factors. Design, Setting, and Participants: This prespecified nested observational cohort study was part of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial. All stable, symptomatic outpatients in this trial who required noninvasive cardiovascular testing and received coronary CTA were included and followed up for a median of 25 months. Exposures: Core laboratory assessment of coronary CTA for SS and high-risk plaque (eg, positive remodeling, low computed tomographic attenuation, or napkin-ring sign). Main Outcomes and Measures: The primary end point was an adjudicated composite of MACE (defined as death, myocardial infarction, or unstable angina). Results: The study included 4415 patients, of whom 2296 (52%) were women, with a mean age of 60.5 years, a median atherosclerotic cardiovascular disease (ASCVD) risk score of 11, and a MACE rate of 3% (131 events). A total of 676 patients (15.3%) had high-risk plaques, and 276 (6.3%) had SS. The presence of high-risk plaque was associated with a higher MACE rate (6.4% vs 2.4%; hazard ratio, 2.73; 95% CI, 1.89-3.93). This association persisted after adjustment for ASCVD risk score and SS (adjusted hazard ratio [aHR], 1.72; 95% CI, 1.13-2.62). Adding high-risk plaque to the ASCVD risk score and SS assessment led to a significant continuous net reclassification improvement (0.34; 95% CI, 0.02-0.51). Presence of high-risk plaque increased MACE risk among patients with nonobstructive coronary artery disease relative to patients without high-risk plaque (aHR, 4.31 vs 2.64; 95% CI, 2.25-8.26 vs 1.49-4.69). There were no significant differences in MACE in patients with SS and high-risk plaque as opposed to those with SS but not high-risk plaque (aHR, 8.68 vs. 9.31; 95% CI, 4.25-17.73 vs 4.21-20.61). High-risk plaque was a stronger predictor of MACE in women (aHR, 2.41; 95% CI, 1.25-4.64) vs men (aHR, 1.40; 95% CI, 0.81-2.39) and younger patients (aHR, 2.33; 95% CI, 1.20-4.51) vs older ones (aHR, 1.36; 95% CI, 0.77-2.39). Conclusions and Relevance: High-risk plaque found by coronary CTA was associated with a future MACE in a large US population of outpatients with stable chest pain. High-risk plaque may be an additional risk stratification tool, especially in patients with nonobstructive coronary artery disease, younger patients, and women. The importance of findings is limited by low absolute MACE rates and low positive predictive value of high-risk plaque. Trial Registration: clinicaltrials.gov Indentifier: NCT01174550.
EVALuna2:213077